Application of Self-Organizing Maps to characterize subglacial bedrock properties based on gravity, magnetic and radar data – an example for the Wilkes and Aurora Subglacial Basin region, East Antarctica - Liebsch, Jonas; Ebbing, Jörg; Matsuoka, Kenichi (Solid Earth, 2025)
Publisher: Copernicus Publications
Keywords: Antarktis; geovitenskap; glasiologi; innlandsis; subglasial geologi

The OCEAN ICE mooring compilation: a standardised, pan-Antarctic database of ocean hydrography and current time series - Zhou, S.; Dutrieux, P.; Giulivi, C. F.; Jenkins, A.; Silvano, A.; Auckland, C.; Abrahamsen, E. P.; Meredith, M.; Vaňková, I.; Nicholls, K.; Davis, P. E. D.; Østerhus, S.; et al. (Earth Syst. Sci. Data, 2025)
Continuous moored time series of temperature, salinity, pressure and current speed and direction are of great importance for understanding the continental shelf and under-ice-shelf dynamics and thermodynamics that govern water mass transformations and ice melting in and around Antarctic marginal seas. In these regions, icebergs and sea ice make ship-based mooring deployment and recovery challenging. Nevertheless, over decades, expeditions around the fringe of Antarctica sporadically deployed and recovered hundreds of moored instruments, including those facilitated through ice shelves boreholes. These datasets tend to be archived in a wide range of data centres, with, to our knowledge, no clear format standardisation. As a result, systematic analysis of historical mooring time series in the marginal seas is often challenging. Here we present the first version of a standardised pan-Antarctic moored hydrography and current time series compilation, with broad international contributions from data centres, research institutes and individual data owners. The mooring records in this compilation span over five decades, from the 1970s to the 2020s, providing an opportunity for a systematic study of the pan-Antarctic water mass transport and shelf connectivity. As a demonstration of the utility of this compilation, we present spectral analysis of the compiled current velocity time series, which unsurprisingly shows the dominating presence of tidal variability within most records. This component of the variability is fitted using multi-linear regression to tidal frequencies, and the tidal fit is removed from the original time series to leave de-tided variability. Given the limited record durations to months to years, de-tided variability is dominated by synoptic (3–10 d period), intraseasonal (10–80 d) and seasonal (∼6 months–1 year) signals. The spatial distribution of the kinetic energy integrated within frequency bands is presented and discussed within respective regional contexts, and future avenues of research are proposed. This data compilation is assembled under the endorsement of Ocean-Cryosphere Exchanges in ANtarctica: Impacts on Climate and the Earth System (OCEAN ICE) project (https://ocean-ice.eu/, last access: 23 October 2025) funded by the European Commission and UK Research and Innovation. It is available and regularly updated in NetCDF format with the SEANOE database at https://doi.org/10.17882/99922 (Zhou et al., 2024a).
Publisher: Copernicus Publications
Keywords: Sørishavet; database; geofysikk; hydrografi; oseanografi

Time series of the summertime atmospheric water vapour isotopic composition at Concordia station, East Antarctica - Ollivier, I.; Lauwers, T.; Dutrievoz, N.; Agosta, C.; Casado, M.; Fourré, E.; Genthon, C.; Jossoud, O.; Prié, F.; Steen-Larsen, H. C.; Landais, A. (Earth Syst. Sci. Data, 2025)
Measurements of stable water isotopes in the atmospheric water vapour can be used to better understand the physical processes of the atmospheric water cycle. In polar regions, the atmospheric water vapour isotopic composition is a key parameter to understand the link between the precipitation and snow isotopic compositions and interpret isotope climate records from ice cores. In this study we present a novel 2.5-month accurate record of the atmospheric water vapour isotopic composition during the austral summer 2023–2024 (6 December 2023 to 14 February 2024) at Concordia Station (East Antarctica), from two laser spectrometers based on different measurement techniques, which are independently calibrated and both optimised to measure in low humidity environments. We show that both instruments accurately measure the summertime diurnal variability in the water vapour δ18O, δD, and d-excess, when the water vapour mixing ratio is consistently higher than 200 ppmv. We compare these measurements to outputs of the isotope-enabled atmospheric general circulation model LMDZ6-iso and show that the model exhibits biases in both the mean water vapour isotopic composition and the amplitude of the diurnal cycle, consistent with previous studies. Hence, this study provides a novel dataset of the atmospheric water vapour isotopic composition on the Antarctic Plateau, which can be used to evaluate isotope-enabled atmospheric general circulation models. The dataset is available on the public repository PANGAEA (https://doi.org/10.1594/PANGAEA.974597, Landais et al., 2024b).
Publisher: Copernicus Publications
Keywords: Antarktis; meteorologi

A potential new sea surface temperature proxy based on isomeric highly branched isoprenoid lipid biomarkers: EZ25 - Belt, Simon T.; Smik, Lukas; Husum, Katrine; Knies, Jochen (Organic Geochemistry, 2025)
Two tri-unsaturated and isomeric (E/Z) highly branched isoprenoid (HBI) diatom lipid biomarkers were quantified in 228 water column samples collected from the English Channel, West Svalbard (Arctic), the Scotia Sea (Southern Ocean) and East Antarctica. We found that the relative amounts of the two HBIs correlate well with water temperatures taken at the time of sampling. Based on these findings and some other HBI data reported previously, we suggest that the proportion of the HBI E-isomer (termed EZ25) may serve as a new proxy for palaeo sea surface temperatures, including in the polar regions. Next steps will involve determination of EZ25 in surface and downcore sediments to ascertain whether the temperature response described herein translates well to the geological record.
Article number: 105056
Keywords: Scotiahavet; Sørishavet; biogeokjemi; biomarkører; geologi; paleontologi; polarområdene

The Maud Belt (East Antarctica) as an accretionary orogen in Rodinia: Isotopic composition, evolution and spatial variation - Wang, Cheng-Cheng; Jacobs, Joachim; Marschall, Horst R.; Hemming, Sidney; Jacques, Guillaume; Läufer, Andreas (Gondwana Research, 2025)
The Maud Belt of East Antarctica represents a late Mesoproterozoic orogen along the periphery of the Proto-Kalahari Craton, and a better understanding of its orogenic nature helps to elucidate the configuration of Kalahari within the Rodinia supercontinent. In this study, we present original and compiled zircon U–Pb geochronological and Hf isotopic data spanning ca. 1180 to 950 Ma along with whole-rock Nd isotopes, covering a broad expanse of the Maud Belt and the adjacent Archean Grunehogna Craton, in an attempt to delineate the spatial and temporal patterns of isotopic compositions and evolution, and to better understand the orogenic architecture and style. Spatial isotopic variations are particularly evident in the western front of the orogen (western H.U. Sverdrupfjella) in contrast to other regions. The former exhibits a wide range of isotopic compositions, with the majority showing highly evolved signatures, indicating that the orogenic crust developed through the reworking of pre-existing Archean–Paleoproterozoic continental crust. In contrast, most other regions of the Maud Belt are characterized by relatively juvenile Hf and Nd isotopic compositions, which are interpreted to be derived from a mixture of juvenile magmas and Paleoproterozoic crust. The Hf isotopic evolution from 1180 Ma to 950 Ma indicates significantly less reworking of pre-existing continental crust compared to other contemporaneous Rodinia-forming orogens, including the Grenville Orogen itself, and emphasizes a predominant addition of juvenile material, implying a continuous subduction process. The isotopic investigation in this study, combined with the geological and paleomagnetic evidence, indicates that the Maud Belt most likely represents an exterior accretionary orogen along the eastern margin of the Proto-Kalahari Craton, rather than being part of the continental collision zones that led to Rodinia amalgamation.
Keywords: Dronning Maud Land; geokjemi; geokronologi; geologi; paleogeografi; paleomagnetisme

Dynamical reconstruction of Southern Ocean and Antarctic climate variability since 1700 - Dalaiden, Quentin; Goosse, Hugues; Holland, Paul R.; Barthelemy, Antoine (Scientific Data, 2025)
Understanding long-term climate variability in the high latitudes of the Southern Hemisphere is critical due to the key role of the Southern Ocean in the global climate system. However, sparse observations (in space and time) coupled with strong internal variability limit our ability to interpret the origin of recent changes, and their longer-term context. Here we present a dynamically consistent reconstruction of the Antarctic atmosphere and Southern Ocean from 1700 to 2023. We first use data assimilation (DA)-based Antarctic atmospheric reanalyses that combine instrumental observations (1958–2023) and paleoclimate proxies (1700–2000) with Earth System Models to reconstruct key surface climate fields. We then drive a global ocean–sea-ice model with this atmospheric reanalysis to simulate historical ocean conditions, including temperature, salinity, currents, and sea-ice-related variables at 1° resolution. This reconstruction provides the first long-term physically consistent dataset of Antarctic atmosphere–ocean variability, suitable for studying low-frequency climate variability, evaluating climate models, and potentially driving regional atmospheric and ocean models as well as ice sheet models.
Keywords: Sørishavet; global klimamodell; klimamodeller; paleoklimatologi

Dive wiggles as a proxy of prey consumption in krill-feeding penguins - Oosthuizen, W. Chris; Schoombie, Stefan; Chimienti, Marianna; Pistorius, Pierre A.; Lowther, Andrew D. (Journal of Experimental Marine Biology and Ecology, 2025)
The dive profiles of pursuit-diving marine predators are often used to infer foraging behaviour, including potential indicators of prey consumption. ‘Wiggles’ are undulations in dive profiles that relate to foraging activity in a variety of marine predators. In penguins, wiggles are sometimes used as a proxy for prey consumption (e.g., catch per unit effort, CPUE), but this relationship remains poorly validated and likely varies with diet. We deployed animal-borne video cameras and depth recorders on chinstrap penguins (Pygoscelis antarcticus; n = 37) and identified over 17,000 euphausiid prey captures - mainly Antarctic krill (Euphausia superba) - during dives deeper than 3 m (n = 2458 dives). Using the video-observed prey captures as a reference, we tested how well various wiggle metrics derived from 1 Hz depth data predicted krill consumption by the penguins. Wiggle metrics generally showed a positive but noisy and highly variable relationship with the number of krill captured per dive, with association strength varying among metrics. While it is tempting to infer detailed foraging behaviours from dive wiggles (including ‘bottom distance’ generated by the R package diveMove), our results show: (1) notable rates of foraging – non-foraging dive misclassification; (2) only moderate agreement between CPUE estimated from wiggle counts and video observations; and (3) imprecise predictive models of actual prey consumption. While wiggle analyses offer some insight into prey consumption of krill-feeding penguins, our results suggest that alternative methods (e.g., acceleration-based indices) are needed to obtain more robust quantitative estimates of prey consumption.
Keywords: Sør-Orknøyene; Sørishavet; biologging; marin biologi; marin økologi; pingviner; sjøfugler

Refining Zooplankton Diet Composition Studies Over Short and Long Time Scales by Combining 18S Metabarcoding With Fatty Acid Analyses - Pauli, Nora-Charlotte; Metfies, Katja; Neuhaus, Stefan; Graeve, Martin; Cleary, Alison C.; Iversen, Morten H.; Meyer, Bettina (Molecular Ecology Resources, 2025)
ABSTRACT Understanding diet composition is essential for unravelling trophic interactions in aquatic ecosystems. DNA metabarcoding, utilising various variable regions of the 18S rRNA gene, is increasingly employed to investigate zooplankton diet composition. However, accurate results depend on rapid inactivation of digestive enzymes and DNA nucleases through proper sample processing and preservation. In this study, we compare the prey communities of Antarctic krill retrieved from the 18S variable regions V4 and V7 and assess how different processing treatments affect the detected prey composition of both krill and salps. Our findings highlight the critical importance of prompt sample processing for species with highly efficient digestive enzymes, such as krill, to preserve rapidly digested prey, including gelatinous plankton. Comparative analyses of the V4 and V7 regions revealed significantly different prey communities within the same krill samples, indicating that these regions may not be suitable for direct comparisons within or across studies. To complement molecular approaches, we also analyse fatty acids (FA) as trophic markers which provide insights into dietary habits over both short and long time scales. By comparing FA signals from stomach and tissue samples of the same krill and salp individuals, we identified significant differences in trophic markers representing different plankton groups. These findings emphasise the necessity of separating digestive tract from tissue to distinguish between short- and long-term diet signals. Furthermore, integrating FA analysis with metabarcoding offers valuable insights into zooplankton digestion efficiency across taxonomic levels. This combined approach enhances our understanding of zooplankton feeding ecology and trophic interactions in marine ecosystems.
Publisher: John Wiley & Sons, Ltd Article Number: e70030
Keywords: Sørishavet; Weddellhavet; genetikk; krill; marin biologi; marine økosystemer; zooplankton

Controls of the global overturning circulation of the ocean - Roquet, Fabien; Bell, Michael J.; de Boer, Agatha M.; Ferreira, David; Jones, C. Spencer; LaCasce, Joseph H.; de Lavergne, Casimir; Marshall, David P.; Munday, David R.; Nycander, Jonas; Ödalen, Malin (npj Climate and Atmospheric Science, 2025)
The global overturning circulation (GOC) is the largest scale component of the ocean circulation, associated with a global redistribution of key tracers such as heat and carbon. The GOC generates decadal to millennial climate variability, and will determine much of the long-term response to anthropogenic climate perturbations. This review aims at providing an overview of the main controls of the GOC. By controls, we mean processes affecting the overturning structure and variability. We distinguish three main controls: mechanical mixing, convection, and wind pumping. Geography provides an additional control on geological timescales. An important emphasis of this review is to present how the different controls interact with each other to produce an overturning flow, making this review relevant to the study of past, present and future climates as well as to exoplanets’ oceans.
Article number: 304
Keywords: Sørishavet; geologi; klimaendringer; klimamodeller; oseanografi; paleogeografi; paleoklimatologi; paleoseanografi

Enhanced basal melting in winter and spring: seasonal ice–ocean interactions at the Ekström Ice Shelf, East Antarctica - Zeising, O.; Hattermann, T.; Kaleschke, L.; Berger, S.; Boebel, O.; Drews, R.; Ershadi, M. R.; Fromm, T.; Pattyn, F.; Steinhage, D.; Eisen, O. (The Cryosphere, 2025)
Publisher: Copernicus Publications

Basal Melt Rate Variability and Tidal Current Vertical Structure From Observations Beneath Ronne Ice Shelf, Antarctica - Anselin, J.; Nicholls, K. W.; Holland, P. R.; Taylor, J. R.; Østerhus, S.; Makinson, K. (Journal of Geophysical Research: Oceans, 2025)
This study examines the interplay between water column structure, tidal currents, and basal melting at a site beneath Ronne Ice Shelf, using a 3-year data set of oceanographic measurements, and a collocated year-long time series of radar-derived melt rate estimates. Currents at the site are characterized by mixed semidiurnal tides with strong spring-neap variability, superimposed on a nontidal flow. The product of current speed and thermal driving, both measured approximately 19 m from the ice base, explains 88% of the melt rate variability. Although current speed is the dominant driver of this variability, thermal driving also contributes non-negligibly on spring-neap and longer timescales. The semidiurnal tidal ellipses feature marked vertical variations, transitioning from nearly rectilinear in the mid-water column to more circular and clockwise (CW)-rotating near the ice. This depth-dependence of the semidiurnal tide is attributed to the differential influence of boundary friction on the CW and anticlockwise (ACW) rotary components near the critical latitude (where the tidal frequency equals the Coriolis frequency). A theoretical model, which assumes depth-independent eddy viscosity, successfully reproduces the observed 3-year mean vertical structure of the tidal ellipses. Considering the total tidal current rather than individual constituents, ice base friction damps both the time-mean flow speed and the tidal fluctuations, with attenuation varying over the spring-neap cycle, peaking during spring tides. The observed latitude- and time-dependent effects of ice base friction on the barotropic tide are not captured in parameterizations that estimate tide-induced friction velocity by scaling the time-averaged barotropic tidal speed with a constant drag coefficient.
Publisher: John Wiley & Sons, Ltd Article number: e2025JC022524
Keywords: Antarktis; Sørishavet; Weddellhavet; glasiologi; hydrografi; isshelf; oseanografi

Bout time for krill: contrasting Adélie penguin foraging behaviour during years of high and low krill availability - Riaz, Javed; Machado-Gaye, Ana Laura; Chimienti, Marianna; Kato, Akiko; Ropert-Coudert, Yan; Alegría, Nicolás; Barbosa, Andrés; Soutullo, Alvaro (Animal Behaviour, 2025)
Understanding how marine predators structure and adjust their foraging in response to prey field characteristics is a longstanding objective in marine ecology. This is particularly challenging in Southern Ocean ecosystems, where logistical and financial constraints hinder assessment of predator foraging and prey field information at relevant spatial and temporal scales. Here, we examine how Adélie penguins, Pygoscelis adeliae, a key Southern Ocean indicator species, perform and organize their foraging behaviour during two contrasting years of krill (Euphausia superba) abundance. Using multiyear krill acoustic data from King George Island in the West Antarctic Peninsula (WAP), we assess broad seasonal conditions in krill availability. We also analyse a suite of penguin biologging data (spatial location, dive and accelerometry-derived activities) during the same period to identify broad behavioural differences in their bout-diving activity, a classical measure of the temporal organization of foraging in diving predators. During years of high krill abundance and availability, penguins performed shorter dive bouts (consisting of shallower and shorter-duration dives), which were more concentrated in time and space. Despite these differences in bout structure, prey capture attempts occurred at the same rate within bouts. These findings challenge traditional interpretations assuming that increased bout durations (and related proxies of prey capture effort) signal increased krill patch abundance and profitability. Although additional data are required to understand the full scope of penguin bout diving and krill prey field associations, our work improves understanding of penguin behavioural variation and provides insights into how foraging behaviours could potentially be used to interpret krill availability at predator- and management-relevant scales.
Article number: 123260
Keywords: Sørishavet; ekkolodd; krill; marin biologi; marin økologi; marine økosystemer; matauk; pingviner; plankton

Abundance and Diversity of Aerobic Anoxygenic Phototrophic Bacteria in Polar Plant Microbiomes - Mäkinen, Emilia A.; Franz, Ole; Ihalainen, Janne A.; Helander, Marjo; Nissinen, Riitta; Mathew, Suni A.; Saloniemi, Irma; Saikkonen, Kari (Physiologia Plantarum, 2025)
ABSTRACT Here, we examined the occurrence of plant-associated aerobic anoxygenic phototrophic bacteria (AAPB) across polar regions. Recently found in polar soils and cold-climate plants, AAPBs are photoheterotrophs that rely on environmental organic carbon but capture solar energy via anoxygenic photosynthesis. We revealed the abundance of AAPBs by extracting bacteria from plant tissues and imaging the colonies with bacteriochlorophyll-based near-infrared fluorescence. The taxonomic distribution of AAPBs was determined via 16S rRNA gene analysis. From the northern hemisphere, we describe AAPBs from the leaf endo- and phyllospheres of numerous sub- and Arctic plant species in Northern Finland, Svalbard, and Greenland. In the southern hemisphere, we focused on AAPBs in the root and leaf endospheres and the phyllospheres of Deschampsia antarctica in Chilean Patagonia and maritime Antarctica. Additionally, we describe AAPB from the tissues of several other plant species in Patagonia. We found AAPBs commonly associated with the sampled plant species across both hemispheres. A diversity of Alphaproteobacteria was found to contain the AAP capability: at all sampling sites, Sphingomonas was the most abundant taxon (up to 60%), while Methylobacteria made up a notable proportion of sub-Arctic and sub-Antarctic AAPB samples (up to 32%). In contrast to previous studies describing Methylobacteria frequently in various plant communities, AAP-containing Methylobacteria were virtually absent from our high-latitude sites. With diverse AAPB taxa found ubiquitously across polar regions and plant tissues, our results call attention to the potential ecological interaction between AAPBs and their plant hosts.
Publisher: John Wiley & Sons, Ltd
Keywords: Antarktis; biodiversitet; biogeografi; biologi; mikroorganismer; polarområdene

The foraging distribution and habitat use of chick-rearing snow petrels from two colonies in Dronning Maud Land, Antarctica - Honan, Eleanor Maedhbh; Wakefield, Ewan D.; Phillips, Richard A.; Grecian, W. James; Prince, Stephanie; Robert, Henri; Descamps, Sébastien; Rix, Anna; Hoelzel, A. Rus; McClymont, Erin L. (Marine Biology, 2025)
The polar sea-ice zones are highly productive and seasonal habitats that support large populations of vertebrate predators. In the Antarctic, snow petrels (Pagodroma nivea) are regarded as highly ice-dependant, yet knowledge of their habitat use and foraging distribution during the breeding period comes largely from ship-based observations. Snow petrels show sexual size dimorphism, and previous studies have demonstrated a degree of sexual segregation in habitat use in East Antarctica during the incubation period. Here, we characterise the movements, behaviour and habitat use of foraging snow petrels using bird movement and remotely sensed environmental data. We tracked snow petrels from two colonies in Dronning Maud Land, East Antarctica during early chick rearing in January to February 2022, a period of unusually rapid sea-ice retreat in the region. During the chick-rearing period, mean foraging range was c. 395 km and did not differ between the sexes. However, we found some evidence of differing habitat use between the sexes: males foraged more in areas of higher sea-ice concentration and over the continental shelf, while females utilized deeper waters and lower sea-ice concentrations. Sexes also diverged in their behavioural responses to both sea ice and depths, with males more likely to switch to foraging in areas of higher sea-ice concentrations than females and females more likely to switch to foraging in deeper waters than males. Although both sexes were more likely to forage at higher sea-ice concentrations, they also used areas with little or no sea ice. This contrasts with previous studies and may have been due to the unusual paucity of sea-ice cover during our tracking period.
Keywords: Dronning Maud Land; klimaendringer; marin biologi; ornitologi; petreller; sjøfugler; zoologi

Robustness and Mechanisms of the Atmospheric Response Over the Southern Ocean to Idealized Freshwater Input Around Antarctica - Xu, Xiaoqi; Martin, Torge; Beadling, Rebecca L.; Liu, Jiping; Bischof, Sabine; Hattermann, Tore; Huo, Wenjuan; Li, Qian; Marshall, John C.; Muilwijk, Morven; Pauling, Andrew G.; Purich, Ariaan; et al. (Geophysical Research Letters, 2025)
Enhanced Antarctic ice sheet mass loss yields ocean surface freshening, cooling and sea ice expansion, which result in changes in the atmospheric conditions. Using the Southern Ocean Freshwater Input from Antarctica (SOFIA) multi-model ensemble, we study the atmospheric response to a 100-year idealized freshwater release of 0.1 Sv. All models simulate a surface-intensified tropospheric cooling and lower-stratospheric warming south of 35°S. Tropospheric cooling is attributed to sea ice expansion and the associated albedo enhancement in winter and a colder sea surface in summer. This cooling yields a downward displacement of the tropopause, reduced stratospheric water vapor content and ultimately warming around 200 hPa. An enhanced southward eddy heat flux explains warming at 10?100 hPa during austral winter. Despite a temporally (and spatially) uniform prescribed freshwater flux, a prominent sea ice seasonal cycle and atmosphere dynamics result in a distinct seasonal pattern in the occurrence and magnitude of the temperature responses.
Publisher: John Wiley & Sons, Ltd Article number: e2024GL113734
Keywords: Sørishavet; klimamodeller; klimatologi; oseanografi

Investigation on morphological and molecular fingerprints of penguin brain using label-free optical imaging and spectroscopic techniques - Bhatt, Sunil; Verma, Ashwani Kumar; Dastidar, Prabir G.; Kumar, Punit; Thapa, Pramila; Jacob, Tony George; Roy, Tara Sankar; Iyengar, Soumya; Kumaran, Senthil; Ahluwalia, Balpreet Singh; Mehta, Dalip Singh (Scientific Reports, 2025)
The morphology and molecular study of the penguin brain are crucial to define its survival in the extreme conditions of Antarctica. The present study focusses on extracting different optical parameters of the penguin brain using label-free optical imaging and spectroscopic techniques. In label-free optical imaging, we have used quantitative phase imaging, which provides morphological information about the neurons in brain tissue, giving the quantitative phase value of 5 to 20 radians corresponding to the 8 µm tissue section. In label-free spectroscopic techniques, we have used autofluorescence and Raman spectroscopy. Autofluorescence spectroscopy provides molecular information about nicotinamide dinucleotide, flavins, lipofuscins, and porphyrins in the brain’s spectral range of 420 nm to 700 nm. Raman spectroscopy provides multiple peaks associated with different molecules in the brain; among them, few signals are observed at approximately 1305 cm−1, 1448 cm−1, and 1661 cm−1, which correspond to vibrational modes indicative of vibrational features within lipids and protein structures, as well as the presence of amide groups within brain tissue constituents. All these techniques provide the microscopic and molecular fingerprint of the penguin brain, which can be useful for understanding penguin’s anatomical, physiological, and social behavior.
Keywords: Antarktis; anatomi; biofysikk; biologi; biomarkører; fysiologi; morfologi; nevrologi; pingviner

Impacts of the CICE sea ice model and ERA atmosphere on an Antarctic MetROMS ocean model, MetROMS-UHel-v1.0 - Äijälä, C.; Nie, Y.; Gutiérrez-Loza, L.; De Falco, C.; Lauvset, S. K.; Cheng, B.; Bailey, D. A.; Uotila, P. (Geoscientific Model Development, 2025)
In recent years, the Antarctic sea ice has experienced major changes, which are neither well understood nor adequately reproduced by Earth system models. To support model development with an aim to improve Antarctic sea ice and upper-ocean predictions, the impacts of updating the sea ice model and the atmospheric forcing are investigated. In the new MetROMS-UHel-v1.0 (henceforth MetROMS-UHel) ocean–sea ice model, the sea ice component has been updated from CICE5 to CICE6, and the forcing has been updated from ERA-Interim (ERAI) to ERA5 reanalyses. The two versions of MetROMS evaluated in this study use a version of the regional ROMS ocean model including ice shelf cavities. We find that the update of CICE (Community Ice CodE) and ERA reduced the negative bias of the sea ice area in summer. However, the sea ice volume decreases after the CICE update but increases when the atmospheric forcing is updated. As a net result after both updates, the modelled sea ice becomes thinner and more deformed, particularly near the coast. The ROMS ocean model usually yielded a deeper ocean mixed layer compared to observations. Using ERA5, the situation was slightly improved. The update from CICE5 to CICE6 resulted in a fresher coastal ocean due to a smaller salt flux from sea ice to the ocean. In the ice shelf cavities, the modelled melt rates are generally underestimated compared with observations, with the largest underestimation coming from the ice shelves in the too cold Amundsen and Bellingshausen seas as well as from the Australian sector in East Antarctica. These identified sea ice and oceanic changes vary seasonally and regionally. By determining sea ice and oceanic changes after the model and forcing updates and evaluating them against observations, this study informs modellers on improvements and aspects requiring attention with potential model adjustments.
Keywords: Amundsenhavet; Bellingshausenhavet; Sørishavet; havis; klimaendringer; klimamodeller; klimatologi; meteorologi; sjøis

Evidence of active subglacial lakes under a slowly moving coastal region of the Antarctic Ice Sheet - Arthur, Jennifer F.; Shackleton, Calvin; Moholdt, Geir; Matsuoka, Kenichi; van Oostveen, Jelte (The Cryosphere, 2025)
Active subglacial lakes beneath the Antarctic Ice Sheet provide insights into the dynamic subglacial environment, with implications for ice-sheet dynamics and mass balance. Most previously identified lakes have been found upstream (>100 km) of fast-flowing glaciers in West Antarctica, and none have been found in the coastal region of Dronning Maud Land (DML) in East Antarctica. The regional distribution and extent of lakes as well as their timescales and mechanisms of filling–draining activity remain poorly understood. We present local ice surface elevation changes in the coastal DML region that we interpret as unique evidence of seven active subglacial lakes located under slowly moving ice near the grounding line margin. Laser altimetry data from ICESat-2 and ICESat (Ice, Cloud, and Land Elevation Satellites) combined with multi-temporal Reference Digital Elevation Model of Antarctica (REMA) strips reveal that these lakes actively fill and drain over periods of several years. Stochastic analyses of subglacial water routing together with visible surface lineations on ice shelves indicate that these lakes discharge meltwater across the grounding line. Two lakes are within 15 km of the grounding line, while another three are within 54 km. Ice flows 17–172 m a−1 near these lakes, much slower than the mean ice flow speed near other active lakes within 100 km of the grounding line (303 m a−1). Our results improve knowledge of subglacial meltwater dynamics and evolution in this region of East Antarctica and provide new observational data to refine subglacial hydrological models.
Publisher: Copernicus Publications
Keywords: Dronning Maud Land; glasiologi; innlandsis; isstrøm; satellite altimetri; subglasial innsjø

The carbon footprint of Antarctic tourism: an update of carbon emissions based on satellite Automatic Identification System (AIS) data - Cajiao, Daniela; Tejedo, Pablo; Aase, Johnny; Benayas, Javier; Vereda, Marisol; Obermann, Anisja; Lamers, Machiel; Amelung, Bas (Journal of Sustainable Tourism, 2025)
Cruise and aircraft operations constitute the primary transportation modes for accessing Antarctica, and both are highly carbon-intensive. Since the first carbon calculations, the number of tourists has increased twentyfold; routes have expanded further south, involving different modalities, activities, and itineraries. This study presents an assessment and discussion of the carbon footprint of Antarctic tourism based on a comprehensive methodology for calculating emissions. We used satellite data to reconstruct vessel itineraries, gathered individual vessels’ engine specifications, and integrated multiple databases to improve accuracy. We analyzed emissions for four tourism modalities, also incorporating their corresponding aircraft emissions. We found that the Cruise-only modality has the lowest emissions, while the Seaborne Ross Sea & Continent modality has the highest emissions per capita. Despite introducing more efficient fuels and the near-total renovation of the Antarctic fleet, emissions have not decreased significantly. This may be attributed to extended journeys and a higher frequency of trips. The significant carbon footprint of Antarctic tourism poses a challenge in the context of the global climate crisis, influencing perceptions of the industry’s environmental image. We expect that this research will contribute to debates on how to manage growth and diversification of tourism if the aim is Antarctica’s conservation.
Publisher: Routledge
Keywords: Antarktis; bærekraft; cruiseturisme; karbonavtrykk; menneskelig påvirkning; turisme; utslipp

Can we really use design-free hydroacoustic data from fishing vessels for assessing abundance and distribution of marine species? A proof of concept analysis on Antarctic krill - Canseco, J.A.; Niklitschek, E.J.; Skaret, G. (Ecological Indicators, 2025)
Euphausia superba is a well-known Antarctic crustacean of great economic and ecological importance, whose management requires accurate and precise abundance and distribution estimates. Such estimates are difficult to achieve given the remoteness, extension, and large spatio-temporal variability of its geographic distribution. Acoustic data collected on board krill fishing vessels during normal fishing operation has a great potential to enhance such abundance and distribution estimates. In the present work we test the hypothesis that design-free hydroacoustic data collected during regular fishing operations can be used to produce abundance and distribution estimates with similar accuracy and precision than design-based scientific surveys. Thus, we produced and compared distribution and abundance estimates produced using either design-free hydroacoustic data collected during regular fishing operations or design-based data from scientific surveys conducted off the South Orkney Islands during summer 2017 and 2019. Following a Bayesian geostatistical approach that considered and fitted simultaneously the spatial and temporal correlation of the data, we tested different auto-correlation structures and selected the most informative models. The comparison included the means and coefficients of variation (CV) of the probability of presence (p), conditional density (d) and relative abundance index (RAI) estimates. In addition, we also simulated scenarios of parallel and orthogonal transects and obtained RAI estimates from each scenario to compare with design-based and design-free estimates for each year. In 2017, the mean RAI estimated using design-free data (94 421 m2; CV: 14 %) was ∼ 50 % higher than the one estimated with design-based data (60 232 m2; CV: 42 %), both within the fishing area. In 2019, the mean RAI estimated using design-free data (509 413 m2 CV: 6 %) was ∼ 5-fold higher than the one obtained using design-based data (113 654 m2; CV: 33 %) in the same area. Design-free RAI estimates were highly sensitive to extrapolating the inference area from fishing to the high-density sub-area. On the other hand, changing from an hourly-resolved spatio-temporal model to a purely spatial model resulted in neglectable changes. Despite observed differences in mean estimates, both methods identified similar areas of high presence and density of Antarctic krill north and north-west of the South Orkney Islands. The 2017 estimate from design-free data was probably affected by a larger dispersion of krill, and a less observed effective area during regular fishing operations. Our results show that despite using state-of-the-art methods for processing and analyzing design-free, acoustic data collected by the fishing fleet, it still yielded unreliable RAI estimates. The bias and uncertainty related to design-free data were reduced when parallel or orthogonal transects were applied although orthogonal transects yielded results with increased accuracy as they were only 21 % lower and 0.02 % higher than the true value in 2017 and 2019, respectively. Other possible approach to minimize bias would be integrating hydroacoustic information from multiple vessels.
Article number: 113284
Keywords: Sørishavet; geostatistikk; hydroakustikk; krill; marin biologi; oseanografi

Brief communication: Annual variability of the atmospheric circulation at large spatial scale reconstructed from a data assimilation framework cannot explain local East Antarctic ice rises' surface mass balance records - Cavitte, M. G. P.; Goosse, H.; Dalaiden, Q.; Ghilain, N. (The Cryosphere, 2025)
Ice cores are influenced by local processes that alter surface mass balance (SMB) records. To evaluate whether atmospheric circulation on large spatial scales explains the differing SMB trends at eight East Antarctic ice rises, we assimilated ice core SMB records within a high-resolution downscaled atmospheric model, while incorporating radar-derived SMB constraints to quantify local observation errors. The reconstruction captures the diverse variability from SMB records but may over-fit by introducing unrealistic wind spatial heterogeneity. While local errors are quantified, they might not cover all uncertainties. Moreover, small-scale wind circulation, unresolved in the reconstruction, could significantly affect local ice core SMB signals.
Publisher: Copernicus Publications
Keywords: Dronning Maud Land; iskjerner; klimamodeller; kryosfæren; meteorologi

Ephemerality and Performance: Sastrugi: Sounds of Antarctic Sea Ice - Chua, Sean Minhui Tashi; Chester, Diana (Leonardo, 2025)
This paper explores the research, making, and performance of Sastrugi: Sounds of Antarctic Sea Ice. Combining the techniques of sonification, field recording, and musique concrète, Sastrugi orchestrates multisensory world building where immersive soundscapes, data-driven violin composition, and expansive visuals narrate the poignant tale of vanishing sea ice in the Antarctic and Southern Ocean. In the face of a record-breaking year for Antarctic sea ice in 2023, this project emerged as a vital testament to the Earth’s changing climate and highlights the power of creative approaches for engaging audiences with science and vast amounts of data.
Keywords: Sørishavet; fotografi; havis; klimaendringer; kunst; musikk; sjøis

Editorial: Microplastics and nanoplastics in polar areas: Arctic, Antarctica, and the world’s glaciers - Corami, Fabiana; Iannilli, Valentina; Hallanger, Ingeborg G. (Frontiers in Marine Science, 2025)
Plastic particles are present in biotic and abiotic matrices; hence, plastic pollution is a global issue involving terrestrial and marine fauna and poses a threat to humans. Ocean circulation is a crucial vector of microplastics worldwide. Plastic pollution is among the significant threats to the ocean ecosystem. Studies and papers on plastic pollution in the oceans worldwide have been reported. However, the distribution, characterization, and abundance of micro- and nano plastics in the global ocean still need to be carefully investigated. Once plastics are present in the environment, they denature, degrade, and are more prone to fragmentation. It is well established that large plastic objects and macroplastics fragment into mesoplastics and large microplastics through photodegradation and weathering. Hence microplastics easily break up into fragments <100 µm (small microplastics, SMPs) or even into sub-micrometric particles, the nanoplastics. The small size of these SMPs and nanoplastics allows them to be ingested by different organisms according to their mouthparts’ size. Besides, this fragmentation will enable additives and plasticizers to be released into the environment, where they may pose a threat to biota throughout the trophic web in various ecosystems, e.g., from oceans and soils to glaciers. Micro- and nanoplastics (MNPs) can be transported over long distances, together with the other airborne particles. As a result of long-range transport and short-range transport, airborne MNPs can be carried from worldwide to mountain glaciers; from mid-latitudes, they can reach the very high and very low latitudes, i.e., the Arctic and Antarctica. Due to global climate change, warm ocean streams heavily affect the sea circulation in polar areas, carrying regulated and emerging pollutants, microplastics being among them. In this scenario, polar environments may be significantly enriched by MNPs carried by warmer ocean currents intruding into the polar oceans and those in atmospheric aerosol. MNPs may threaten the sea ice formation and enhance the melting of glaciers. The melting and disappearance of glaciers and the intrusion of warm currents into polar areas are also compounded by the thawing of permafrost, which can release pollutants, including MNPs. This Research Topic aims to study the interconnected pathways of MNPs that are paramount to understanding the global microplastic cycle and how climate change alters polar environments and the rest of the world. Furthermore, we aim to identify bioindicators in marine species, populations, and ecosystems, while acknowledging the interconnectedness of freshwater, terrestrial and atmospheric environments to the polar environment. Research on world glaciers will provide a comprehensive evaluation of the impacts of plastic pollution on the marine polar environment and biota, including impacts on humans.
Article Number: 1587557
Keywords: Antarktis; forurensning; isbreer; klimaendringer; mikroplast; miljøgifter; polarområdene; økologi; økosystemer

Observation-Based Estimate of Net Community Production in Antarctic Sea Ice - Dalman, Laura A.; Meiners, Klaus M.; Thomas, David N.; Deman, Florian; Bestley, Sophie; Moreau, Sébastien; Arrigo, Kevin R.; Campbell, Karley; Corkill, Matthew; Cozzi, Stefano; Delille, Bruno; Fransson, Agneta; et al. (Geophysical Research Letters, 2025)
Abstract Antarctic sea ice is one of the largest biomes on Earth providing a critical habitat for ice algae. Measurements of primary production in Antarctic sea ice remain scarce and an observation-based estimate of primary production has not been revisited in over 30 years. We fill this knowledge gap by presenting a newly compiled circumpolar data set of particulate and dissolved organic carbon from 362 ice cores, sampled between 1989 and 2019, to estimate sea-ice net community production using a carbon biomass accumulation approach. Our estimate of 26.8?32.9 Tg C yr?1 accounts for at least 15%?18% of the total primary production in the Antarctic sea-ice zone, less than a previous observation-based estimate (63?70 Tg C yr?1) and consistent with recent modeled estimates. The results underpin the ecological significance of sea-ice algae as an early season resource for pelagic food webs.
Publisher: John Wiley & Sons, Ltd
Keywords: Sørishavet; biogeokjemi; fotosyntese; havis alger; karbondioksid; karbonsyklus; oseanografi; primærproduksjon; sjøis

Antarctic Water Stable Isotopes in the Global Atmospheric Model LMDZ6: From Climatology to Boundary Layer Processes - Dutrievoz, Niels; Agosta, Cécile; Risi, Camille; Vignon, Étienne; Nguyen, Sébastien; Landais, Amaëlle; Fourré, Elise; Leroy-Dos Santos, Christophe; Casado, Mathieu; Masson-Delmotte, Valérie; Jouzel, Jean; Dubos, Thomas; et al. (Journal of Geophysical Research: Atmospheres, 2025)
Observations of water stable isotopes in Antarctic surface snow, precipitation and water vapor are key for improving our understanding of the atmospheric water cycle and past climate reconstructions from ice cores. In this study, we use isotopic observations in Antarctica to assess the skill of the isotope-enabled atmospheric general circulation model LMDZ6, nudged to ERA5 above the boundary layer (1980?2023 period). The model has no significant bias for time-mean temperature and snow accumulation over the ice sheet. Sensitivity test on parameterized supersaturation strength highlights its opposite effect on precipitation ${\delta }{18}$O and d-excess. Selecting an intermediate supersaturation strength resulted in a minimal bias for surface snow ${\delta }{18}$O across the continent, with a reduced but systematic positive bias in surface snow d-excess ( ${\sim} $5?). We then assessed seasonal and diurnal isotope variability with daily precipitation and continuous vapor isotopes at Dumont d?Urville (DDU, coastal station) and Concordia (inland station). On a seasonal scale, LMDZ6iso accurately reproduces the seasonal cycle of precipitation ${\delta }{18}$O and d-excess at both stations. Moving from statistical evaluation to physical analysis, we use the individual process contributions to boundary-layer water vapor isotopes to identify the main drivers controlling the clear-sky isotopic daily cycles. At Concordia, daily isotope variations are mainly driven by surface sublimation, whereas at DDU they are driven by surface sublimation and advection by the katabatic flow. Our results suggest that to further improve water isotopes in LMDZ6iso, fractionation during surface sublimation should be included and fractionation at condensation for low temperature should be better constrained.
Publisher: John Wiley & Sons, Ltd Article number: e2024JD042073
Keywords: Antarktis; global klimamodell; iskjerner; klimamodeller; klimatologi; meteorologi; paleoklimatologi; vannstabile isotoper

A new dynamic distribution model for Antarctic krill reveals interactions with their environment, predators, and the commercial fishery in the south Scotia Sea region - Freer, Jennifer J.; Warwick-Evans, Victoria; Skaret, Georg; Krafft, Bjørn A.; Fielding, Sophie; Trathan, Philip N. (Limnology and Oceanography, 2025)
The management strategy for the Antarctic krill (Euphausia superba) fishery is being revised. A key aim is to spatially and temporally allocate catches in a manner that minimizes impacts to both the krill stock and dependent predators. This process requires spatial information on the distribution and abundance of krill, yet gaps exist for an important fishing area surrounding the South Orkney Islands in the south Scotia Sea. To fill this need, we create a dynamic distribution model for krill in this region. We used data from a spatially and temporally consistent acoustic survey (2011-2020) and year-specific environmental covariates within a two-part hurdle model. The model successfully captured observed spatial and temporal patterns in krill density. The covariates found to be most important included distance from shelf break, distance from summer sea ice extent, and salinity. The northern and eastern shelf edges of the South Orkney Islands were areas of consistently high krill density and displayed strong spatial overlap between intense fishing activity and foraging chinstrap penguins. High mean krill density was also linked to oceanographic features located within the Weddell Sea. Our data suggest that years in which these features were closer to the South Orkney shelf were also years of positive Southern Annular Mode and higher observed krill densities. Our findings highlight existing fishery?predator?prey overlap in the region and support the hypothesis that Weddell Sea oceanography may play a role in transporting krill into this region. These results will feed into the next phase of krill fisheries management assessment.
Publisher: John Wiley & Sons, Ltd
Keywords: Scotiahavet; Sør-Orknøyene; Sørishavet; Weddellhavet; ekkolodd; fiskerier; krill; oseanografi; plankton

Inferring the seasonality of sea ice floes in the Weddell Sea using ICESat-2 - Gupta, M.; Regan, H.; Koo, Y.; Chua, S. M. T.; Li, X.; Heil, P. (The Cryosphere, 2025)
Over the last decade, the Southern Ocean has experienced episodes of severe sea ice area decline. Abrupt events of sea ice loss are challenging to predict, in part due to incomplete understanding of processes occurring at the scale of individual ice floes. Here, we use high-resolution altimetry (ICESat-2) to quantify the seasonal life cycle of floes in the perennial sea ice pack of the Weddell Sea. The evolution of the floe chord distribution (FCD) shows an increase in the proportion of smaller floes between November and February, which coincides with the asymmetric melt–freeze cycle of the pack. The freeboard ice thickness distribution (fITD) suggests mirrored seasonality between the western and southern sections of the Weddell Sea ice cover, with an increasing proportion of thicker floes between October and March in the south and the opposite in the west. Throughout the seasonal cycle, there is a positive correlation between the mean chord length of floes and their average freeboard thickness. Composited floe profiles reveal that smaller floes are more vertically round than larger floes and that the mean roundness of floes increases during the melt season. These results show that regional differences in ice concentration and type at larger scales occur in conjunction with different behaviors at the small scale. We therefore suggest that floe-derived metrics obtained from altimetry could provide useful diagnostics for floe-aware models and improve our understanding of sea ice processes across scales.
Publisher: Copernicus Publications
Keywords: Sørishavet; Weddellhavet; fjernmåling; havis; klimaendringer; klimamodeller; klimatologi; oseanografi; sjøis

Local Drivers of Antarctic Spring Sea Ice Retreat - Himmich, Kenza; Vancoppenolle, Martin; Stammerjohn, Sharon; Bocquet, Marion; Madec, Gurvan; Fleury, Sara (Geophysical Research Letters, 2025)
Antarctic sea ice has changed significantly over the past four decades; yet limited understanding of fundamental processes, including its seasonal cycle, hinders our ability to interpret these changes. Here, we examine the processes determining the moment when sea ice locally disappears each spring, defined as the retreat date, using satellite observations over 1994?2020. We find that climatological retreat date is driven by sea ice melt in most of the seasonal ice zone and strongly constrained by the seasonal maximum ice thickness. Ice removal due to drifting ice export predominantly drives retreat only in coastal polynyas. At interannual timescales, retreat date anomalies are also preconditioned by prior maximum ice thickness, which affects melt-driven spring ice loss through the ice-albedo feedback, though this effect appears limited to specific regions. Winds emerge as a primary driver of interannual variability in the retreat date, influencing both drift- and melt-related spring ice removal processes.
Publisher: John Wiley & Sons, Ltd Article number: e2025GL114764
Keywords: Sørishavet; havis; klimamodeller; klimatologi; oseanografi; sjøis

Using a multi-layer snow model for transient paleo-studies: surface mass balance evolution during the Last Interglacial - Hoang, Thi-Khanh-Dieu; Quiquet, Aurélien; Dumas, Christophe; Born, Andreas; Roche, Didier M. (Clim. Past, 2025)
During the Quaternary, ice sheets experienced several retreat–advance cycles, strongly influencing climate patterns. In order to properly simulate these phenomena, it is preferable to use physics-based models instead of parameterizations to estimate the surface mass balance (SMB), which strongly influences the evolution of the ice sheet. To further investigate the potential of these SMB models, this work evaluates the BErgen Snow SImulator (BESSI), a multi-layer snow model with high computational efficiency, as an alternative to providing the SMB for the Earth system model iLOVECLIM for multi-millennial simulations as in paleostudies. We compare the behaviors of BESSI and insolation temperature melt (ITM), an existing SMB scheme of iLOVECLIM during the Last Interglacial (LIG). Firstly, we validate the two SMB models using the regional climate model Mod- èle Atmosphérique Régional (MAR) as forcing and reference for the present-day climate over the Greenland and Antarctic ice sheets. The evolution of the SMB over the LIG (130–116 ka) is computed by forcing BESSI and ITM with transient climate forcing obtained from iLOVECLIM for both ice sheets. For present-day climate conditions, both BESSI and ITM exhibit good performance compared to MAR despite a much simpler model setup. While BESSI performs well for both Antarctica and Greenland for the same set of parame- ters, the ITM parameters need to be adapted specifically for each ice sheet. This suggests that the physics embedded in BESSI allows better capture of SMB changes across varying climate conditions, while ITM displays a much stronger sen- sitivity to its tunable parameters. The findings suggest that BESSI can provide more reliable SMB estimations for the iLOVECLIM framework to improve the model simulations of the ice sheet evolution and interactions with climate for multi-millennial simulations.
Publisher: Copernicus Publications
Keywords: Antarktis; innlandsis; klimamodeller; paleoklimatologi; polarområdene

Synoptic Drivers and Moisture Sources of Snowfall in Coastal Victoria Land, Antarctica - Hofsteenge, M. G.; Cullen, N. J.; Sodemann, H.; Katurji, M. (Journal of Geophysical Research: Atmospheres, 2025)
Snowfall is an important component of the mass balance of ice sheets and glaciers in Antarctica. In coastal Victoria Land (VL), changes to snowfall can impact ice masses, landscapes, and coastal ecosystems. Coastal VL is characterized by strong gradients in snowfall rates between the polar desert of the McMurdo Dry Valleys and the high accumulation in northern VL. Extreme precipitation events significantly contribute to total precipitation, with the largest contribution in the Terra Nova Bay area. We present a comprehensive analysis of snowfall dynamics in this region, using a Lagrangian moisture source diagnostic to study moisture sources and Self-Organizing Maps (SOM) to link these to different synoptic weather types. The moisture for snowfall in VL originates from the Southern Ocean, with more local sources in the Ross Sea embayment in summer when sea ice is reduced. We show a strong division in moisture sources between northern and southern VL, with the north receiving precipitation from moisture sources to the west and southern VL from the east. Precipitation in northern VL results from meridional transport of marine air from lower latitudes, while precipitation in southern VL is related to cyclonic disturbances in the Ross Sea that bring moisture from the east. Extreme precipitation in northern VL occurs during blocking highs that intensify meridional transport. Such intrusions of marine air, sometimes in the form of atmospheric rivers, do not impact the more isolated western Ross Ice Shelf and southern VL further in the Ross Sea embayment.
Publisher: John Wiley & Sons, Ltd Article number: e2024JD042021
Keywords: Rosshavet; Sørishavet; havis; klimatologi; meteorologi; nedbør; sjøis

Strong turbulent flow in the subauroral region in the Antarctic can deteriorate satellite-based navigation signals - Kotova, D. S.; Sinevich, A. A.; Chernyshov, A. A.; Chugunin, D. V.; Jin, Y.; Miloch, W. J. (Scientific Reports, 2025)
In the subauroral zone at the boundary of the auroral oval in the evening and night hours during geomagnetic disturbances, a narrow (about 1°–2°) and extended structure (several hours in longitude) is formed. It is known as a polarization jet (PJ) or the subauroral ion drift (SAID). The PJ/SAID is a fast westward ion drift and is one of the main signatures of a geomagnetic disturbance in the subauroral ionosphere at the altitudes of the F-layer, when the geomagnetic AE index reaches more than 500 nT. Plasma speed in the PJ/SAID can reach several kilometres per second, and the size of plasma irregularities inside it can reach scales from tens of meters to several hundred meters. Such high velocities and structured plasma can affect trans-ionospheric radio waves and lead to scintillations in the received signal. We show that at the moment of auroral activity intensification, an increase in the magnitude of phase scintillation index (σϕ) as well as loss of satellite signals lock were observed in the region of the PJ/SAID equatorward of the auroral oval over Dronning Maud Land (Queen Maud Land) in Antarctica. We find that fluctuations inside the PJ/SAID can lead to serious deterioration of radio communication or navigational services. We emphasize the importance of considering the geometry of the beam passing from the GNSS satellite to the receiver on the ground. We highlight the mutual contribution of the PJ/SAID and the diffuse aurora boundary, which are almost impossible to separate in practice. Our results demonstrate the importance of considering the subauroral zone, where very dynamic plasma formations can occur with a strong flow and various-scale irregularities inside that lead to serious interference in satellite communications.
Keywords: Dronning Maud Land; aurora; fysikk; geomagnetiske stormer; ionosfæren; magnetosfæren; romfysikk; sørlys

Assessing trawls size selectivity in Antarctic krill: The role of sex and maturity stages - Krag, Ludvig Ahm; Brčić, Jure; Herrmann, Bent; Nalon, Marco; Krafft, Bjørn Arne (Regional Studies in Marine Science, 2025)
Understanding the connection between maturity stages and morphology in relation to size selectivity in trawls is essential for assessing the impact of various fishing gear on the population structures of harvested species, their fishing mortality rates, and the efficiency of the gear used. The Antarctic krill (Euphausia superba) fishery is the largest in the Southern Ocean by volume, and there is increasing interest in expanding the industry. The krill fishery employs different trawl designs and is not currently subject to technical regulations specifying the types of fishing gear and mesh sizes that can legally be used. There is a need to establish a robust model predicting size selectivity that includes the morphological variation in the population of krill. Male and female Antarctic krill are described with 12 maturity stages, from juveniles to sexually mature adults, each with distinct morphological features. The current study established a morphological description of each individual krill maturity stage to identify and parameterize what determines size selectivity using the FISHSELECT framework. This framework is used to predict size selectivity for each of the different stages in various mesh sizes and openings relevant to the krill fishery, in both actual and virtual populations. The results can be used to assess size selectivity for specific fishing gears and population structures, facilitating more accurate understanding and modeling of the fishery’s impact on the demographic composition of the krill stock.
Article number: 104223
Keywords: Sørishavet; fiskerier; fiskeriforvaltning; krill; marine økosystemer; plankton; populasjonsbiologi

Basal Melting and Oceanic Observations Beneath Central Fimbulisen, East Antarctica - Lindbäck, Katrin; Darelius, Elin; Moholdt, Geir; Vaňková, Irena; Hattermann, Tore; Lauber, Julius; de Steur, Laura (Journal of Geophysical Research: Oceans, 2025)
Abstract Basal melting of ice shelves is fundamental to Antarctic ice sheet mass loss, yet direct observations remain sparse. We present the first year-round melt record (2017-2021) from a phase-sensitive radar on Fimbulisen, one of the fastest flowing ice shelves in Dronning Maud Land, East Antarctica. The observed long-term mean ablation rate at 350 m depth below the central ice shelf was 1.0 ± 0.5 m yr?1, marked by substantial sub-weekly variability ranging from 0.4 to 3.5 m yr?1. 36-h filtered basal melt rate fluctuations closely align with ocean velocity. On seasonal time scales, melt rates peak during austral spring to autumn (September-March), driven by both elevated ocean velocities and thermal driving near the base. The combined effect of thermal driving and current speed explains the majority of the melt rate variability (r = 0.84), highlighting the dominant role of shear-driven turbulence. This relationship enables parameterization of melt rates for the decade-long ocean record (2010?2021), although deviations appear under low and high forcing conditions. Both observed and parameterized melt rates show similar yearly mean magnitudes compared to satellite-derived melt rates but with a tenfold lower seasonal amplitude and a 3-month delay in seasonality. These detailed concurrent ice?ocean observations provide essential validation data for remote sensing and numerical models that aim to quantify and project ice-shelf response to a change in ocean forcing. In situ measurements and continued monitoring are crucial for accurately assessing and modeling future basal melt rates, and for understanding the complex dynamics driving ice-shelf stability and sea-level change.
Publisher: John Wiley & Sons, Ltd Article number: e2023JC020506
Keywords: Dronning Maud Land; fjernmåling; klimamodeller; oseanografi

Southern Ocean Carbon Export Revealed by Backscatter and Oxygen Measurements From BGC-Argo Floats - Liniger, Guillaume; Moreau, Sébastien; Lannuzel, Delphine; Carranza, Magdalena M.; Strutton, Peter G. (Global Biogeochemical Cycles, 2025)
The Southern Ocean (south of 30°S) contributes significantly to global ocean carbon uptake through the solubility, physical and biological pumps. Many studies have estimated carbon export to the deep ocean, but very few have attempted a basin-scale perspective, or accounted for the sea-ice zone (SIZ). In this study, we use an extensive array of BGC-Argo floats to improve previous estimates of carbon export across basins and frontal zones, specifically including the SIZ. Using a new method involving changes in particulate organic carbon and dissolved oxygen along the mesopelagic layer, we find that the total Southern Ocean carbon export from 2014 to 2022 is 2.69 ± 1.23 PgC y?1. The polar Antarctic zone contributes the most (41%) with 1.09 ± 0.46 PgC y?1. Conversely, the SIZ contributes the least (8%) with 0.21 ± 0.09 PgC y?1 and displays a strong shallow respiration in the upper 200 m. However, the SIZ contribution can increase up to 14% depending on the depth range investigated. We also consider vertical turbulent fluxes, which can be neglected at depth but are important near the surface. Our work provides a complementary approach to previous studies and is relevant for work that focuses on evaluating the biogeochemical impacts of changes in Antarctic sea-ice extent. Refining estimates of carbon export and understanding its drivers ultimately impacts our comprehension of climate variability at the global ocean scale.
Publisher: John Wiley & Sons, Ltd Article number: e2024GB008193
Keywords: Sørishavet; biogeokjemi; fotosyntese; fytoplankton; havis; karbon syklus; sjøis

Giant iceberg meltwater increases upper-ocean stratification and vertical mixing - Lucas, Natasha S.; Brearley, J. Alexander; Hendry, Katharine R.; Spira, Theo; Braakmann-Folgmann, Anne; Abrahamsen, E. Povl; Meredith, Michael P.; Tarling, Geraint A. (Nature Geoscience, 2025)
Ice-sheet mass loss is one of the clearest manifestations of climate change, with Antarctica discharging mass into the ocean via melting or through calving. The latter produces icebergs that can modify ocean water properties, often at great distances from source. This affects upper-ocean physics and primary productivity, with implications for atmospheric carbon drawdown. A detailed understanding of iceberg modification of ocean waters has hitherto been hindered by a lack of proximal measurements. Here unique measurements of a giant iceberg from an underwater glider enable quantification of meltwater effects on the physical and biological processes in the upper layers of the Southern Ocean, a region disproportionately important for global heat and carbon sequestration. Iceberg basal melting erodes seasonally produced winter water layer stratification, normally forming a strong potential energy barrier to vertical exchange of surface and deep waters, while freshwater run-off increases and shoals near-surface stratification. Nutrient-rich deeper waters, incorporating meltwater loaded with terrigenous material, are ventilated to below this stratification maxima, providing a potential mechanism for alleviating critical phytoplankton-limiting components. Regional historical hydrographic data demonstrate similar stratification changes during the passage of another large iceberg, suggesting that they may be an important pathway of aseasonal winter water modification.
Keywords: Sørishavet; Weddellhavet; biogeokjemi; glasiologi; global oppvarming; hydrografi; klimaendringer; klimatologi; oseanografi

Katabatic and foehn winds control the distribution of supraglacial lakes in Dronning Maud Land, Antarctica - Mahagaonkar, Anirudha; Moholdt, Geir; Glaude, Quentin; Schuler, Thomas V. (Earth and Planetary Science Letters, 2025)
Meltwater ponding along the margins of Antarctica poses a threat to ice shelf stability, increasing the risk of accelerated inland ice mass loss. Understanding the key drivers of supraglacial lake formation is therefore essential for assessing the vulnerability and future stability of Antarctic ice shelves. In this study, we combine high-resolution simulation from the regional climate model Modèle Atmosphérique Régional (MAR) with satellite-derived records of supraglacial lakes in coastal Dronning Maud Land to investigate the role of topographic downslope winds on spatial lake distribution. We find that persistent katabatic winds and episodic foehn winds are key controls on the observed regional patterns of lakes. Katabatic winds, most persistent in eastern Dronning Maud Land, exert a sustained impact near grounding zones through snow erosion, scouring and sublimation. Foehn winds predominantly affect ice shelves on the lee (western) side of large ice rises and promontories, causing considerable surface warming. While these downslope winds directly contribute to surface melt and ponding during summer, they also precondition the surface year-round through wind-driven warming and sublimation. Statistical analysis of downslope wind exposure further allows us to identify other Antarctic ice shelves that may become vulnerable to future ponding as firn retention capacity is diminished.
Article number: 119482
Keywords: Dronning Maud Land; glasiologi; isshelf; klimamodeller; klimatologi; kryosfæren; meteorologi; subglasial innsjø

Dispersal and habitat preference of juvenile emperor penguins—implications for conservation management - Makhado, Azwianewi Benedict; Crawford, Robert J. M.; Dyer, Bruce M.; Masotla, Makhudu; Lowther, Andrew (Royal Society Open Science, 2025)
Seabirds can disperse widely when searching for prey, particularly during nonbreeding periods. Conservation measures predominately focus on protecting breeding colonies, while spatial protection at sea is often based on knowledge of the distribution of breeding adults, despite accumulating evidence that marine habitats used by immature birds sometimes differ from those of adults. Juvenile emperor penguins from Atka Bay, west Dronning Maud Land, Antarctica, tracked immediately after fledging performed long migrations to the northern extents of the Convention for the Conservation of Antarctic Marine Living Resources subareas 48.4 and 48.6. Individuals did not remain long at their northern positions, before commencing a rapid southerly movement to within a few hundred km of the marginal ice zone (MIZ). The initial migratory movement was broadly synchronous across individuals. The southward movement and subsequent change to area-restricted searching were consistent with the MIZ representing a potentially important feeding habitat for juvenile emperor penguins. Spatio-temporal management mechanisms may be beneficial in reducing threats to these young penguins.
Publisher: Royal Society Article Number: 231800
Keywords: Dronning Maud Land; biologi; marine økosystemer; ornitologi; pingviner; sjøfugler; telemetri; økologi

Evaluating Cloud Properties at Scott Base: Comparing Ceilometer Observations With ERA5, JRA55, and MERRA2 Reanalyses Using an Instrument Simulator - McDonald, Adrian J.; Kuma, Peter; Panell, M.; Petterson, Orlon K. L.; Plank, Graeme E.; Rozliaiani, M. A. H.; Whitehead, Luke E. (Journal of Geophysical Research: Atmospheres, 2025)
This study compares CL51 ceilometer observations made at Scott Base, Antarctica, with statistics from the ERA5, JRA55, and MERRA2 reanalyses. To enhance the comparison we use a lidar instrument simulator to derive cloud statistics from the reanalyses which account for instrumental factors. The cloud occurrence in the three reanalyses is slightly overestimated above 3 km, but displays a larger underestimation below 3 km relative to observations. Unlike previous studies, we see no relationship between relative humidity and cloud occurrence biases, suggesting that the cloud biases do not result from the representation of moisture. We also show that the seasonal variation of cloud occurrence and cloud fraction, defined as the vertically integrated cloud occurrence, are small in both the observations and the reanalyses. We also examine the quality of the cloud representation for a set of weather states derived from ERA5 surface winds. The variability associated with grouping cloud occurrence based on weather state is much larger than the seasonal variation, highlighting weather state is a strong control of cloud occurrence. All the reanalyses continue to display underestimates below 3 km and overestimates above 3 km for each weather state. But the variability in ERA5 statistics matches the changes in the observations better than the other reanalyses. We also use a machine learning scheme to estimate the quantity of supercooled liquid water cloud from the ceilometer observations. Ceilometer low-level supercooled liquid water cloud occurrences are considerably larger than values derived from the reanalyses, further highlighting the poor representation of low-level clouds in the reanalyses.
Publisher: John Wiley & Sons, Ltd Article number: e2024JD041754
Keywords: Antarktis; dataanalyse; forskningsstasjoner; meteorologi

Global Marine Flyways Identified for Long-Distance Migrating Seabirds From Tracking Data - Morten, Joanne M.; Carneiro, Ana P. B.; Beal, Martin; Bonnet-Lebrun, Anne-Sophie; Dias, Maria P.; Rouyer, Marie-Morgane; Harrison, Autumn-Lynn; González-Solís, Jacob; Jones, Victoria R.; Garcia Alonso, Virginia A.; Antolos, Michelle; Arata, Javier A.; et al. (Global Ecology and Biogeography, 2025)
Aim To identify the broad-scale oceanic migration routes (?marine flyways?) used by multiple pelagic, long-distance migratory seabirds based on a global compilation of tracking data. Location Global. Time Period 1989?2023. Major Taxa Studied Seabirds (Families: Phaethontidae, Hydrobatidae, Diomedeidae, Procellariidae, Laridae and Stercorariidae). Methods We collated a comprehensive global tracking dataset that included the migratory routes of 48 pelagic and long-distance migrating seabird species across the Atlantic, Indian, Pacific and Southern Oceans. We grouped individuals that followed similar routes, independent of species or timings of migration, using a dynamic time warping clustering approach. We visualised the routes of each cluster using a line density analysis and used knowledge of seabird spatial ecology to combine the clusters to identify the broad-scale flyways followed by most pelagic migratory seabirds tracked to-date at an ocean-basin scale. Results Six marine flyways were identified across the world's oceans: the Atlantic Ocean Flyway, North Indian Ocean Flyway, East Indian Ocean Flyway, West Pacific Ocean Flyway, Pacific Ocean Flyway and Southern Ocean Flyway. Generally, the flyways were used bidirectionally, and individuals either followed sections of a flyway, a complete flyway, or their movements linked two or more flyways. Transhemispheric figure-of-eight routes in the Atlantic and Pacific oceans, and a circumnavigation flyway in the Southern Ocean correspond with major wind-driven ocean currents. Main Conclusions The marine flyways identified demonstrate that pelagic seabirds have similar and repeatable migration routes across ocean-basin scales. Our study highlights the need to account for connectivity in seabird conservation and provides a framework for international cooperation.
Publisher: John Wiley & Sons, Ltd Article number: e70004
Keywords: Sørishavet; biogeografi; biologging; sjøfugler; økologi

Multi-model assessment of the deglacial climatic evolution at high southern latitudes - Obase, T.; Menviel, L.; Abe-Ouchi, A.; Vadsaria, T.; Ivanovic, R.; Snoll, B.; Sherriff-Tadano, S.; Valdes, P. J.; Gregoire, L.; Kapsch, M.-L.; Mikolajewicz, U.; Bouttes, N.; et al. (Climate of the Past, 2025)
The Quaternary climate is characterized by glacial–interglacial cycles, with the most recent transition from the last glacial maximum to the present interglacial (the last deglaciation) occurring between ∼ 21 and 9 ka. While the deglacial warming at high southern latitudes is mostly in phase with atmospheric CO2 concentrations, some proxy records indicate that the onset of the warming occurred before the CO2 increase. In addition, high southern latitudes exhibit a cooling event in the middle of the deglaciation (15–13 ka) known as the “Antarctic Cold Reversal”. In this study, we analyse transient simulations of the last deglaciation performed with six different climate models as part of the 4th phase of the Paleoclimate Modelling Intercomparison Project (PMIP4) to understand the processes driving high-southern-latitude surface temperature changes. As the protocol of the last deglaciation sets the choice of freshwater forcing as flexible, the freshwater forcing is different in each model, thus complicating the multi-model comparison. While proxy records from West Antarctica and the Pacific sector of the Southern Ocean suggest the presence of an early warming before 18 ka, only half the models show a significant warming at this time (∼ 1 °C or ∼ 10 % of the total deglacial warming). All models simulate a major warming during Heinrich Stadial 1 (18–15 ka), concurrent with the CO2 increase and with a weakening of the Atlantic Meridional Overturning Circulation (AMOC) in some models. However, the simulated Heinrich Stadial 1 warming over Antarctica is smaller than the one suggested from ice core data. During the Antarctic Cold Reversal, simulations with an abrupt AMOC strengthening exhibit a high-southern-latitude cooling of 1 to 2 °C, in relative agreement with proxy records, while simulations with rapid North Atlantic meltwater input exhibit a warming. Using simple models to extract the relative AMOC contribution, we find that all climate models simulate a high-southern-latitude cooling in response to an AMOC increase with a response timescale of several hundred years, suggesting the choice of the North Atlantic meltwater forcing substantially affects high-southern-latitude temperature changes. Thus, further work needs to be carried out to reconcile the deglacial AMOC evolution with the Northern Hemisphere ice sheet disintegration and associated meltwater input. Finally, all simulations exhibit only minimal changes in Southern Hemisphere westerlies and Southern Ocean meridional circulation during the last deglaciation. Improved understanding of the processes impacting Southern Hemisphere atmospheric and oceanic circulation changes accounting for deglacial atmospheric CO2 increase is needed.
Keywords: Antarktis; Sørishavet; deglasiasjon; klimamodeller; paleoklimatologi

Surface processes and drivers of the snow water stable isotopic composition at Dome C, East Antarctica – a multi-dataset and modelling analysis - Ollivier, I.; Steen-Larsen, H. C.; Stenni, B.; Arnaud, L.; Casado, M.; Cauquoin, A.; Dreossi, G.; Genthon, C.; Minster, B.; Picard, G.; Werner, M.; Landais, A. (The Cryosphere, 2025)
Water stable isotope records in polar ice cores have been largely used to reconstruct past local temperatures and other climatic information such as evaporative source region conditions of the precipitation reaching the ice core sites. However, recent studies have identified post-depositional processes taking place at the ice sheet's surface, modifying the original precipitation signal and challenging the traditional interpretation of ice core isotopic records. In this study, we use a combination of existing and new datasets of precipitation, snow surface, and subsurface isotopic compositions (δ18O and deuterium excess (d-excess)); meteorological parameters; ERA5 reanalyses; outputs from the isotope-enabled climate model ECHAM6-wiso; and a simple modelling approach to investigate the transfer function of water stable isotopes from precipitation to the snow surface and subsurface at Dome C in East Antarctica. We first show that water vapour fluxes at the surface of the ice sheet result in a net annual sublimation of snow, from 3.1 to 3.7 mm w.e. yr−1 (water equivalent) between 2018 and 2020, corresponding to 12 % to 15 % of the annual surface mass balance. We find that the precipitation isotopic signal cannot fully explain the mean, nor the variability in the isotopic composition observed in the snow, from annual to intra-monthly timescales. We observe that the mean effect of post-depositional processes over the study period enriches the snow surface in δ18O by 3.0 ‰ to 3.3 ‰ and lowers the snow surface d-excess by 3.4 ‰ to 3.5 ‰ compared to the incoming precipitation isotopic signal. We also show that the mean isotopic composition of the snow subsurface is not statistically different from that of the snow surface, indicating the preservation of the mean isotopic composition of the snow surface in the top centimetres of the snowpack. This study confirms previous findings about the complex interpretation of the water stable isotopic signal in the snow and provides the first quantitative estimation of the impact of post-depositional processes on the snow isotopic composition at Dome C, a crucial step for the accurate interpretation of isotopic records from ice cores.
Keywords: Antarktis; fysisk geografi; geologi; klimamodeller; kryosfæren; paleoklimatologi

Dive wiggles as a proxy of prey consumption in krill-feeding penguins - Oosthuizen, W. Chris; Schoombie, Stefan; Chimienti, Marianna; Pistorius, Pierre A.; Lowther, Andrew D. (Journal of Experimental Marine Biology and Ecology, 2025)
The dive profiles of pursuit-diving marine predators are often used to infer foraging behaviour, including potential indicators of prey consumption. ‘Wiggles’ are undulations in dive profiles that relate to foraging activity in a variety of marine predators. In penguins, wiggles are sometimes used as a proxy for prey consumption (e.g., catch per unit effort, CPUE), but this relationship remains poorly validated and likely varies with diet. We deployed animal-borne video cameras and depth recorders on chinstrap penguins (Pygoscelis antarcticus; n = 37) and identified over 17,000 euphausiid prey captures - mainly Antarctic krill (Euphausia superba) - during dives deeper than 3 m (n = 2458 dives). Using the video-observed prey captures as a reference, we tested how well various wiggle metrics derived from 1 Hz depth data predicted krill consumption by the penguins. Wiggle metrics generally showed a positive but noisy and highly variable relationship with the number of krill captured per dive, with association strength varying among metrics. While it is tempting to infer detailed foraging behaviours from dive wiggles (including ‘bottom distance’ generated by the R package diveMove), our results show: (1) notable rates of foraging – non-foraging dive misclassification; (2) only moderate agreement between CPUE estimated from wiggle counts and video observations; and (3) imprecise predictive models of actual prey consumption. While wiggle analyses offer some insight into prey consumption of krill-feeding penguins, our results suggest that alternative methods (e.g., acceleration-based indices) are needed to obtain more robust quantitative estimates of prey consumption.
Article Number: 152115
Keywords: Sørishavet; biologging; marin biologi; pingviner; sjøfugler; økologi

Advances and shortfalls in knowledge of Antarctic terrestrial and freshwater biodiversity - Pertierra, L. R.; Convey, P.; Barbosa, A.; Biersma, E. M.; Cowan, D.; Diniz-Filho, J. A. F.; de los Ríos, A.; Escribano-Álvarez, P.; Fraser, C. I.; Fontaneto, D.; Greve, M.; Griffiths, H. J.; et al. (Science, 2025)
Antarctica harbors many distinctive features of life, yet much about the diversity and functioning of Antarctica?s life remains unknown. Evolutionary histories and functional ecology are well understood only for vertebrates, whereas research on invertebrates is largely limited to species descriptions and some studies on environmental tolerances. Knowledge on Antarctic vegetation cover showcases the challenges of characterizing population trends for most groups. Recent community-level microbial studies have provided insights into the functioning of life at its limits. Overall, biotic interactions remain largely unknown across all groups, restricted to basic information on trophic level placement. Insufficient knowledge of many groups limits the understanding of ecological processes on the continent. Remedies for the current situation rely on identifying the caveats of each ecological discipline and finding targeted solutions. Such precise delimitation of knowledge gaps will enable a more aware, representative, and strategic systematic conservation planning of Antarctica.
Publisher: American Association for the Advancement of Science
Keywords: Antarktis; biodiversitet; biogeografi; biologi; biomonitorering; mikroorganismer; økologi; økosystemer

Bedmap3 updated ice bed, surface and thickness gridded datasets for Antarctica - Pritchard, Hamish D.; Fretwell, Peter T.; Fremand, Alice C.; Bodart, Julien A.; Kirkham, James D.; Aitken, Alan; Bamber, Jonathan; Bell, Robin; Bianchi, Cesidio; Bingham, Robert G.; Blankenship, Donald D.; Casassa, Gino; et al. (Scientific Data, 2025)
We present Bedmap3, the latest suite of gridded products describing surface elevation, ice-thickness and the seafloor and subglacial bed elevation of the Antarctic south of 60 °S. Bedmap3 incorporates and adds to all post-1950s datasets previously used for Bedmap2, including 84 new aero-geophysical surveys by 15 data providers, an additional 52 million data points and 1.9 million line-kilometres of measurement. These efforts have filled notable gaps including in major mountain ranges and the deep interior of East Antarctica, along West Antarctic coastlines and on the Antarctic Peninsula. Our new Bedmap3/RINGS grounding line similarly consolidates multiple recent mappings into a single, spatially coherent feature. Combined with updated maps of surface topography, ice shelf thickness, rock outcrops and bathymetry, Bedmap3 reveals in much greater detail the subglacial landscape and distribution of Antarctica’s ice, providing new opportunities to interpret continental-scale landscape evolution and to model the past and future evolution of the Antarctic ice sheets.
Article Number: 414
Keywords: Antarktis; geofysikk; geomorfologi; glasiologi; hydrologi; oseanografi

Controls of the global overturning circulation of the ocean - Roquet, Fabien; Bell, Michael J.; de Boer, Agatha M.; Ferreira, David; Jones, C. Spencer; LaCasce, Joseph H.; de Lavergne, Casimir; Marshall, David P.; Munday, David R.; Nycander, Jonas; Ödalen, Malin (npj Climate and Atmospheric Science, 2025)
The global overturning circulation (GOC) is the largest scale component of the ocean circulation, associated with a global redistribution of key tracers such as heat and carbon. The GOC generates decadal to millennial climate variability, and will determine much of the long-term response to anthropogenic climate perturbations. This review aims at providing an overview of the main controls of the GOC. By controls, we mean processes affecting the overturning structure and variability. We distinguish three main controls: mechanical mixing, convection, and wind pumping. Geography provides an additional control on geological timescales. An important emphasis of this review is to present how the different controls interact with each other to produce an overturning flow, making this review relevant to the study of past, present and future climates as well as to exoplanets’ oceans.
Article Number: 304
Keywords: Sørishavet; global klimamodell; klimamodeller; klimatologi; meteorologi; oseanografi; paleoseanografi

Modeling Antarctic Sea Ice Variability Using a Brittle Rheology - Santana, Rafael; Boutin, Guillaume; Horvat, Christopher; Ólason, Einar; Williams, Timothy; Rampal, Pierre (Journal of Advances in Modeling Earth Systems, 2025)
Sea ice is a composite solid material that sustains large fracture features at scales from meters to kilometres. These fractures can play an important role in coupled atmosphere-ocean processes. To model these features, brittle sea ice physics, via the Brittle-Bingham-Maxwell (BBM) rheology, has been implemented in the Lagrangian neXt generation Sea Ice Model (neXtSIM). In Arctic-only simulations, the BBM rheology has shown a capacity to represent observationally consistent sea ice fracture patterns and breakup across a wide range of time and length scales. Still, it has not been tested whether this approach is suitable for the modeling of Antarctic sea ice, which is thinner and more seasonal compared to Arctic sea ice, and whether the ability to reproduce sea ice fractures has an impact on simulating Antarctic sea ice properties. Here, we introduce a new 50-km grid-spacing Antarctic configuration of neXtSIM, neXtSIM-Ant, using the BBM rheology. We evaluate this simulation against observations of sea ice extent, drift, and thickness and compare it with identically-forced neXtSIM simulations that use the standard modified Elastic-Visco-Plastic (mEVP) rheology. In general, using BBM results in thicker sea ice and an improved correlation of sea ice drift with observations than mEVP. We suggest that this is related to short-duration breakup events caused by Antarctic storms that are not well-simulated in the viscous-plastic model.
Publisher: John Wiley & Sons, Ltd Article number: e2024MS004584
Keywords: Sørishavet; havis; klimamodeller; klimatologi; meteorologi; oseanografi; sjøis

Sex Differentiation and Long-Distance Gene Flow in the Elusive Antarctic Fish Aethotaxis mitopteryx - Schiavon, Luca; Desvignes, Thomas; Ronco, Fabrizia; Matschiner, Michael; Gastaldi, Martina; Koppetsch, Thore; Schrøder-Nielsen, Audun; Postlethwait, John H.; Prestanti, Alessia; Stranci, Federica; Ceballos, Santiago G.; Mark, Felix C.; et al. (Ecology and Evolution, 2025)
Understanding population connectivity in the marine realm is crucial for conserving biodiversity, managing fisheries, and predicting species responses to environmental change. This is particularly important in Antarctic waters, where unique evolutionary histories and extreme conditions shape marine biodiversity. The longfin icedevil Aethotaxis mitopteryx is an elusive notothenioid fish endemic to Antarctic waters. To explore population connectivity in A. mitopteryx, we used RAD-seq to investigate the genetic differentiation of two populations, one from the Eastern Weddell Sea and the other from the Eastern Antarctic Peninsula, two regions of ecological relevance greatly impacted by climate change. Despite spatial separation, analyses revealed no significant genetic differentiation between the two populations, suggesting extensive gene flow. A pronounced genetic distinction was, however, observed between males and females. This differentiation was largely localized to a specific chromosome, implying a genetic sex determination system with males being the heterogametic sex. These findings contribute novel insights into the genetic structure of A. mitopteryx populations and expand our understanding of genetic mechanisms in Antarctic fish. This study provides a foundation for further investigations into the evolutionary and ecological implications of sex chromosome differentiation in extreme environments.
Publisher: John Wiley & Sons, Ltd Article Number: e71847
Keywords: Sørishavet; Weddellhavet; biodiversitet; fiskerier; genetikk; klimaendringer; marin biologi; marin økologi

Sex Differentiation and Long-Distance Gene Flow in the Elusive Antarctic Fish Aethotaxis mitopteryx - Schiavon, Luca; Desvignes, Thomas; Ronco, Fabrizia; Matschiner, Michael; Gastaldi, Martina; Koppetsch, Thore; Schrøder-Nielsen, Audun; Postlethwait, John H.; Prestanti, Alessia; Stranci, Federica; Ceballos, Santiago G.; Mark, Felix C.; et al. (Ecology and Evolution, 2025)
Understanding population connectivity in the marine realm is crucial for conserving biodiversity, managing fisheries, and predicting species responses to environmental change. This is particularly important in Antarctic waters, where unique evolutionary histories and extreme conditions shape marine biodiversity. The longfin icedevil Aethotaxis mitopteryx is an elusive notothenioid fish endemic to Antarctic waters. To explore population connectivity in A. mitopteryx, we used RAD-seq to investigate the genetic differentiation of two populations, one from the Eastern Weddell Sea and the other from the Eastern Antarctic Peninsula, two regions of ecological relevance greatly impacted by climate change. Despite spatial separation, analyses revealed no significant genetic differentiation between the two populations, suggesting extensive gene flow. A pronounced genetic distinction was, however, observed between males and females. This differentiation was largely localized to a specific chromosome, implying a genetic sex determination system with males being the heterogametic sex. These findings contribute novel insights into the genetic structure of A. mitopteryx populations and expand our understanding of genetic mechanisms in Antarctic fish. This study provides a foundation for further investigations into the evolutionary and ecological implications of sex chromosome differentiation in extreme environments.
Publisher: John Wiley & Sons, Ltd Article number: e71847
Keywords: Sørishavet; Weddellhavet; biodiversitet; fiskerier; genetikk; marin biologi; marin økologi

Decline of Antarctic Circumpolar Current due to polar ocean freshening - Sohail, Taimoor; Gayen, Bishakhdatta; Klocker, Andreas (Environmental Research Letters, 2025)
The Antarctic Circumpolar Current (ACC) is the world’s strongest ocean current and plays a disproportionate role in the climate system due to its role as a conduit for major ocean basins. This current system is linked to the ocean’s vertical overturning circulation, and is thus pivotal to the uptake of heat and CO2 in the ocean. The strength of the ACC has varied substantially across warm and cold climates in Earth’s past, but the exact dynamical drivers of this change remain elusive. This is in part because ocean models have historically been unable to adequately resolve the small-scale processes that control current strength. Here, we assess a global ocean model simulation which resolves such processes to diagnose the impact of changing thermal, haline and wind conditions on the strength of the ACC. Our results show that, by 2050, the strength of the ACC declines by ∼20% for a high-emissions scenario. This decline is driven by meltwater from ice shelves around Antarctica, which is exported to lower latitudes via the Antarctic Intermediate Water. This process weakens the zonal density stratification historically supported by surface temperature gradients, resulting in a slowdown of sub-surface zonal currents. Such a decline in transport, if realised, would have major implications on the global ocean circulation.
Publisher: IOP Publishing Article number: 034046
Keywords: Sørishavet; Sørishavsstrømmen; klimaendringer; klimamodeller; oseanografi

Giant pit craters on the modern seafloor above magma-induced hydrothermal vent complexes of Scotia Sea, offshore Antarctica - Somoza, L.; Andreassen, K. M.; Plaza-Faverola, A.; Medialdea, T.; Gafeira, J.; González, F. J.; Dickens, G. R. (Scientific Reports, 2025)
Massive injection of 13C depleted carbon to the ocean and atmosphere coincided with major environmental upheaval multiple times in the geological record. For several events, the source of carbon has been attributed to explosive venting of gas produced when magmatic sills intruded organic-rich sediment. The concept mostly derives from studies of a few ancient sedimentary basins with numerous hydrothermal vent complexes (HTVCs) where craters appear to have formed across large areas of the seafloor at the same time, but good examples remain rare in strata younger than the Early Eocene. We present geophysical data documenting at least 150 large (km-scale) craters on the modern seafloor across ∼148,000 km2 of Scan Basin in the southern Scotia Sea, a remote region offshore Antarctica. Seismic and bathymetric information reveals the craters relate to vertical fluid pipes extending above dome-shaped forced folds and saucer-shaped igneous sills. Presumably, magmatic intrusions deform overlying sediment and produce thermogenic gas, where buoyant hydrothermal fluids migrate upwards from sill flanks through V-shaped gas chimneys to the seafloor. Fluid expulsion, driven by excess pore pressure, enhances vertical conduits and creates collapse structures on the seafloor. Age estimates for sill emplacement and crater formation come from correlations of seismic reflectors with bore hole data collected on IODP Expedition 382. Sills intruded into sediment at least two times, first about 12–13 Ma (Middle Miocene), which occurred with deep intrusions of stacked composite sills, and once about 0.9 Ma and associated with volcanism along Discovery Bank, which may have reactivated previous fluid venting. Crater reactivation has occurred since 0.9 Ma, although probably episodically. Importantly, at present-day, numerous craters related to sills and fluid pipes populate the seafloor above a young sedimentary basin, and the ocean and atmosphere are receiving massive quantities of 13C depleted carbon. The two phenomena are unrelated but, with changes in global climate and sedimentation, the craters could be filled simultaneously and give an impression in the rock record of rapid and coeval formation coincident with carbon emission. Interpretations of ancient HTVCs and their significance to global carbon cycling needs revision with consideration of modern seafloor regions with HTVCs, notably Scan Basin.
Article Number: 3139
Keywords: Scotiahavet; Sørishavet; chronostratigrafi; geologi; klimaendringer; marin geologi; vulkanologi

Automated krill body length estimation based on stereo camera images - Svantemann, Mette M; Krafft, Bjørn A; Thompson, Fletcher F; Zhang, Guosong; Krag, Ludvig A (ICES Journal of Marine Science, 2025)
The fishery for Antarctic krill (Euphausia superba) is the largest by tonnage in the Southern Ocean, and understanding its population dynamics is essential for the sustainable management of this fishery. The standard method for calculating Antarctic krill biomass relies on hydroacoustic survey data and incorporates krill body length data collected concurrently. Traditional scientific acoustic surveys involve manually measuring the body lengths of individual krill caught using fine- meshed nets or trawls along acoustic transects. This work is resource-demanding and could represent a source of human error. To address these challenges, we develop and test an alternative, more automated method for estimating krill body length data by employing an in-trawl stereo camera system. This system collects images that are automatically processed by a custom-trained machine learning model. The results from the machine learning model are then compared to manually measured krill subsampled from the total catch of the corresponding trawl hauls. We demonstrated the ability to extract body lengths from underwater images. However, our results highlighted uncertainties, which we propose addressing by incorporating more advanced camera technology and optimizing the observation section of the small-meshed two-layer krill trawl.
Article number: fsaf058
Keywords: Sørishavet; ekkolodd; fiskerier; fiskeriforvaltning; krill; marin biologi; plankton

Untangling the complexities of larval Antarctic krill overwintering success under climate change - Sylvester, Zephyr T; Veytia, Devi; Bahl, Alexis A; Bahlburg, Dominik; Benkort, Deborah; Bestley, Sophie; Cagdas, Bulut; Cleary, Alison C; Constable, Andrew; Corney, Stuart; Fach, Bettina A; Hellessey, Nicole; et al. (ICES Journal of Marine Science, 2025)
Antarctic krill (Euphausia superba) are integral to Southern Ocean pelagic ecosystems. Winters with extensive sea ice have been linked to high post-larval krill recruitment the following spring, suggesting that sea ice plays a critical role in larval overwinter survival. As the ocean warms and sea ice declines under climate change, understanding the mechanisms linking sea ice and krill recruitment is increasingly urgent. To address this, we developed a qualitative network model (QNM) that integrates evidence-based and hypothesized interactions to explore larval overwinter survival and growth under future climate scenarios in the southwest Atlantic sector. Our model highlights habitat-specific impacts, with substantial declines predicted for the North Antarctic Peninsula continental shelf due to reduced autumn primary productivity and warming. In contrast, survival may improve in open-ocean habitats under cooler scenarios that enhance sea-ice-associated processes, such as food availability and refuge. The inclusion of hypothesized mechanisms, such as sea-ice terraces providing refuge from predation, strengthened these conclusions and highlighted critical uncertainties, including the influence of glacial melt on food web dynamics. These findings demonstrate the value of QNMs in complementing quantitative approaches, offering a framework for identifying critical mechanisms, addressing knowledge gaps, and guiding future field and laboratory studies to improve predictions of krill responses to climate change.
Article Number: fsaf049
Keywords: Sørishavet; fiskerier; klimaendringer; krill; oseanografi; plankton

Surface darkening by abundant and diverse algae on an Antarctic ice cap - Thomson, Alex Innes; Gray, Andrew; Colesie, Claudia; Thomas, Naomi; Moulton, Hannah; Convey, Peter; Smith, Alison G.; Fretwell, Peter; Peck, Lloyd; Davey, Matthew P. (Nature Communications, 2025)
Algal blooms play important roles in physical and biological processes on glacial surfaces. Despite this, their occurrence and impacts within an Antarctic context remain understudied. Here, we present evidence of the large-scale presence, diversity and bioalbedo effects of algal blooms on Antarctic ice cap systems based on fieldwork conducted on Robert Island (South Shetland Islands, Antarctica). Algal blooms are observed covering up to 2.7 km2 (~20%) of the measured area of the Robert Island ice cap, with cell densities of up to 1.4 × 106 cells ml−1. Spectral characterisation reveal that these blooms increase melting of the ice cap surface, contributing up to 2.4% of total melt under the observed conditions. Blooms are composed of typical cryoflora taxa, dominated by co-occurring Chlorophyceae, Trebouxiophyceae, and Ancylonema. However, morphological variation and genetic diversity in Ancylonema highlight the influence of regional endemism and point to a large and under-characterised diversity in Antarctic cryoflora.
Article Number: 2647
Keywords: Antarktis; Sør-Shetlandsøyene; biogeografi; biologi; kryosfæren; snøalger; økologi

Impact of krill (Euphausia superba) meal on growth performance of aquatic animals: A meta-analysis and prospective directions - Tran, Hung Quang; Nguyen, Tram Thi; Prokešová, Markéta Dvořáková; Øverland, Margareth; Gasco, Laura; Kumar, Vikas; Van Doan, Hien; Stejskal, Vlastimil (Animal Nutrition, 2025)
Antarctic krill meal (KM) (Euphausia superba) as a substitute for fishmeal in aquatic animal diets is gaining popularity worldwide. A quantitative approach investigating the efficacy of using this protein on the production performance of aquatic animals remains widely limited. Here, we employed a meta-analysis to quantify the overall effects (Hedges’g [g] value effect size) of KM on the specific growth rate (SGR), feed conversion ratio (FCR), protein efficiency ratio (PER), and survival rate (SR) of several aquaculture species. A total of 22 records published during 2006 to 2022 from different countries, targeting 14 aquatic species, were employed in the present study. Overall, KM has a high nutritional value relative to fishmeal, particularly from the high protein and amino acid composition. Dietary KM significantly increased the overall effect size of SGR (g = 1.92) (P = 0.001); the positive effect was illustrated in marine species (g = 1.32 to 9.10) (P < 0.05) and sturgeon (Acipenser gueldenstaedtii) (g = 6.59) (P < 0.001). The overall g value for FCR (−2.42) was significantly improved compared to the control group (P < 0.001). The inclusion of KM in aquatic animal diets did not affect g value of PER (1.52, 95% confidence interval: −1.04 to 4.07) and survival rate (0.08, 95% confidence interval: −0.63 to 0.79) (P = 0.252 and 0.208, respectively). The meta-regression models indicated that SGR of rainbow trout (Oncorhynchus mykiss) was significantly correlated with dietary KM by a positive linear model (P = 0.022). The cod and sturgeon (A. gueldenstaedtii) appeared to efficiently utilize krill-containing diets as illustrated by a negative linear model (P = 0.011 and P = 0.024, respectively) between dietary KM and FCR. Dietary KM positively correlated with PER for Atlantic cod (P = 0.021). Our meta-analysis highlighted the significant outcome of KM in diets for aquaculture species by reducing pressure on forage fish from marine resources and sparing edible foods. Specifically, including KM significantly reduced economic fish-in fish-out (eFIFO) in four taxa—the top forage fish consumers (P < 0.05): marine fish, salmon, shrimp, and trout. The meta-analysis revealed the decreased food-competition feedstuff in diets for important aquaculture species (P < 0.05) fed dietary KM. The outlook for efficient use of KM from marine resources in aquafeeds was elucidated in the present work.
Keywords: Sørishavet; akvakultur; fiskerier; krill; marin biologi; marin økologi; plankton

Impact of Ocean, Sea Ice or Atmosphere Initialization on Seasonal Prediction of Regional Antarctic Sea Ice - Xiu, Yongwu; Wang, Yiguo; Luo, Hao; Garcia-Oliva, Lilian; Yang, Qinghua (Journal of Advances in Modeling Earth Systems, 2025)
Dynamical modeling is widely utilized for Antarctic sea ice prediction. However, the relative impact of initializing different model components remains unclear. We compare three sets of hindcasts of the Norwegian Climate Prediction Model (NorCPM), which are initialized by ocean, ocean/sea-ice, or atmosphere data and referred to as the OCN, OCNICE, and ATM hindcasts hereafter. The seasonal cycle of sea ice extent (SIE) in the ATM reanalysis shows a slightly better agreement with observations than the OCN and OCNICE reanalyzes. The trends of sea ice concentration (SIC) in the OCN and OCNICE reanalyzes compare well to observations, but the ATM reanalysis is poor over the western Antarctic. The OCNICE reanalysis yields the most accurate estimation of sea ice variability, while the OCN and ATM reanalyzes are comparable. Evaluation of the hindcasts reveals the predictive skill varies with region and season. Austral winter SIE of the western Antarctic can be skillfully predicted 12 months ahead, while the predictive skill in the eastern Antarctic is low. Austral winter SIE predictability can be largely attributed to high sea surface temperature predictability, thanks to skillful initialization of ocean heat content. The ATM hindcast from July or October performs best due to the effective initialization of sea-ice thickness, which enhances prediction skills until early austral summer via its long memory. Meanwhile, the stratosphere-troposphere coupling contributes to the prediction of springtime. The comparable skill between the OCN and OCNICE hindcasts implies limited benefits from SIC data on prediction when using ocean data.
Publisher: John Wiley & Sons, Ltd Article number: e2024MS004382
Keywords: Sørishavet; atmosfæren; havis; klimamodeller; klimatologi; meteorologi; oseanografi; sjøis

Extended seasonal prediction of Antarctic sea ice concentration using ANTSIC-UNet - Yang, Z.; Liu, J.; Song, M.; Hu, Y.; Yang, Q.; Fan, K.; Graversen, R. G.; Zhou, L. (The Cryosphere, 2025)
Antarctic sea ice has experienced rapid change in recent years, with the total sea ice extent abruptly decreasing after a period of gradual increase from the late 1970s until 2014. Accurate long-term predictions of Antarctic sea ice concentration by dynamical or machine learning models are crucial for supporting the expanding activities in the Southern Ocean, related to for instance scientific research, tourism and fisheries. However, dynamical models often face difficulties in accurately predicting Antarctic sea ice due to limited representations of air-ice-sea interactions, especially on seasonal timescales and during the summer months. In addition, existing deep learning approaches typically rely on historical sea ice data, neglecting the complex interactions between sea ice and other climate variables, and lack interpretability of the underlying physical processes. Moreover, little attention has been paid to extended seasonal forecasts, and systematic evaluations of the predictive skill during extreme years remain scarce. To address these challenges and gaps, we here develop a deep learning model (named ANTSIC-UNet), trained by multiple climate variables, and evaluate its skill for extended up-to-six-months seasonal prediction of Antarctic sea ice concentration. We compare the predictive skill of ANTSIC-UNet in the Pan- and regional Antarctic with two benchmark models (a linear trend and an anomaly persistence model) and a dynamical model (SEAS5). In terms of root-mean-square error (RMSE) of sea ice concentration and integrated ice-edge error (IIEE), ANTSIC-UNet shows much better skills relative to the other models for the extended seasonal prediction, especially for the extreme events in recent years. Sea ice prediction errors increase with lead time, and are smaller during autumn and winter than in summer. The Pacific and Indian Oceans show accurate prediction performance at the sea ice edge during summer, and ANTSIC-UNet provides high predictive skill in capturing the interannual variability of Pan-Antarctic and regional sea ice extent anomalies. In addition, we quantify the importance of variables through a post-hoc interpretation method. This analysis suggests that the ANTSIC-UNet prediction at short lead times is sensitive to sea surface temperature, radiative flux, and atmospheric circulation in addition to sea ice conditions. At longer lead times, zonal wind in the stratosphere appears to be an important influencing factor for the prediction. Building on these findings, we further demonstrate that incorporating physical constraints into deep learning models potentially leads to a gain in the accuracy of the Antarctic sea ice edge prediction on extended seasonal timescales.
Publisher: Copernicus Publications
Keywords: Sørishavet; havis; klimamodeller; klimatologi; kryosfæren; maskinlæring; oseanografi; sjøis

Enhanced basal melting in winter and spring: seasonal ice–ocean interactions at the Ekström Ice Shelf, East Antarctica - Zeising, O.; Hattermann, T.; Kaleschke, L.; Berger, S.; Boebel, O.; Drews, R.; Ershadi, M. R.; Fromm, T.; Pattyn, F.; Steinhage, D.; Eisen, O. (The Cryosphere, 2025)
Basal melting of Antarctic ice shelves significantly contributes to ice sheet mass loss, with distinct regional disparities in melt rates driven by ocean properties. In Dronning Maud Land (DML), East Antarctica, cold water predominantly fills the ice shelf cavities, resulting in generally low annual melt rates. In this study, we present a 4-year record of basal melt rates at the Ekström Ice Shelf, measured using an autonomous phase-sensitive radio-echo sounder (ApRES). Observations reveal a low mean annual melt rate of 0.44 m a−1, with a seasonal variability. Enhanced melting occurs in winter and spring, peaking at over 1 m a−1, while rates are decreased in summer and autumn. We hypothesise that the dense water formed during sea-ice formation erodes the water column stratification during late winter and spring, leading to an increase in the buoyancy of the ice shelf water plume. An idealised plume model supports this hypothesis, indicating that the plume velocity is the primary driver of seasonal basal melt rate variability, while changes in ambient water temperature play a secondary role in the range of oceanographic conditions that are observed below the Ekström Ice Shelf. These findings offer new insights into the dynamics of ice–ocean interactions in East Antarctica, emphasising the need for further observations to refine our understanding of ocean variability within ice shelf cavities and improve assessments of ice shelf mass balance.
Publisher: Copernicus Publications
Keywords: Dronning Maud Land; ekkolodd; glasiologi; havis; isshelf; oseanografi; sjøis

Enhanced basal melting in winter and spring: seasonal ice–ocean interactions at the Ekström Ice Shelf, East Antarctica - Zeising, O.; Hattermann, T.; Kaleschke, L.; Berger, S.; Boebel, O.; Drews, R.; Ershadi, M. R.; Fromm, T.; Pattyn, F.; Steinhage, D.; Eisen, O. (The Cryosphere, 2025)
Basal melting of Antarctic ice shelves significantly contributes to ice sheet mass loss, with distinct regional disparities in melt rates driven by ocean properties. In Dronning Maud Land (DML), East Antarctica, cold water predominantly fills the ice shelf cavities, resulting in generally low annual melt rates. In this study, we present a 4-year record of basal melt rates at the Ekström Ice Shelf, measured using an autonomous phase-sensitive radio-echo sounder (ApRES). Observations reveal a low mean annual melt rate of 0.44 m a−1, with a seasonal variability. Enhanced melting occurs in winter and spring, peaking at over 1 m a−1, while rates are decreased in summer and autumn. We hypothesise that the dense water formed during sea-ice formation erodes the water column stratification during late winter and spring, leading to an increase in the buoyancy of the ice shelf water plume. An idealised plume model supports this hypothesis, indicating that the plume velocity is the primary driver of seasonal basal melt rate variability, while changes in ambient water temperature play a secondary role in the range of oceanographic conditions that are observed below the Ekström Ice Shelf. These findings offer new insights into the dynamics of ice–ocean interactions in East Antarctica, emphasising the need for further observations to refine our understanding of ocean variability within ice shelf cavities and improve assessments of ice shelf mass balance.
Publisher: Copernicus Publications
Keywords: Dronning Maud Land; glasiologi; oseanografi

Community estimate of global glacier mass changes from 2000 to 2023 - Zemp, Michael; Jakob, Livia; Dussaillant, Inés; Nussbaumer, Samuel U.; Gourmelen, Noel; Dubber, Sophie; A, Geruo; Abdullahi, Sahra; Andreassen, Liss Marie; Berthier, Etienne; Bhattacharya, Atanu; Blazquez, Alejandro; et al. (Nature, 2025)
Glaciers are indicators of ongoing anthropogenic climate change1. Their melting leads to increased local geohazards2, and impacts marine3 and terrestrial4,5 ecosystems, regional freshwater resources6, and both global water and energy cycles7,8. Together with the Greenland and Antarctic ice sheets, glaciers are essential drivers of present9,10 and future11–13 sea-level rise. Previous assessments of global glacier mass changes have been hampered by spatial and temporal limitations and the heterogeneity of existing data series14–16. Here we show in an intercomparison exercise that glaciers worldwide lost 273 ± 16 gigatonnes in mass annually from 2000 to 2023, with an increase of 36 ± 10% from the first (2000–2011) to the second (2012–2023) half of the period. Since 2000, glaciers have lost between 2% and 39% of their ice regionally and about 5% globally. Glacier mass loss is about 18% larger than the loss from the Greenland Ice Sheet and more than twice that from the Antarctic Ice Sheet17. Our results arise from a scientific community effort to collect, homogenize, combine and analyse glacier mass changes from in situ and remote-sensing observations. Although our estimates are in agreement with findings from previous assessments14–16 at a global scale, we found some large regional deviations owing to systematic differences among observation methods. Our results provide a refined baseline for better understanding observational differences and for calibrating model ensembles12,16,18, which will help to narrow projection uncertainty for the twenty-first century11,12,18.
Keywords: Antarktis; fjernmåling; glasiologi; havnivåstigning; hydrologi; isbreer; klimaendringer; kryosfæren; polarområdene

Spatial Variations of Atmospheric Alkylated Polycyclic Aromatic Hydrocarbons across the Western Pacific to the Southern Ocean: Unexpected Increasing Deposition - Zhu, Fu-Jie; Lu, Xi-Mei; Jia, Jing-Wen; Zhang, Xue; Xing, De-Feng; Cai, Ming-Hong; Kallenborn, Roland; Li, Yi-Fan; Muir, Derek C. G.; Zhang, Zi-Feng; Zhang, Xianming (Environmental Science & Technology, 2025)
Spatial variations of atmospheric alkylated polycyclic aromatic hydrocarbons (Alk-PAHs) are key to understanding their long-range atmospheric transport (LRAT). However, limited Alk-PAHs data have hindered their LRAT characterizations on a global scale. In this study, 49 Alk-PAHs were measured in the atmospheric samples collected across the Western Pacific to the Southern Ocean. The summed concentration of 39 frequently detected Alk-PAHs (Σ39Alk-PAHs) was 25.8 ± 25.3 ng m–3. The concentrations of Σ39Alk-PAHs significantly declined with the decrease in latitude (°N). Higher concentrations (55.8 ± 33.8 ng m–3) were linked to continental air mass compared to oceanic/Antarctica air mass (17.0 ± 13.6 ng m–3), highlighting continental emissions as the primary source of marine atmospheric Alk-PAHs. An unexpected increase in the G/P partitioning ratio (KP) was found in samples farther away from the continent, which cannot be explained by the influence of temperature on the partitioning process. Deposition analysis suggested that gaseous concentrations and the G/P partitioning largely influenced deposition patterns. Hypothetical scenario analysis indicated that increased KP under snowy conditions could enhance the total Alk-PAH deposition. These findings emphasize the need for accurate characterization of partitioning and deposition processes when studying the global fate of Alk-PAHs, particularly in remote and polar regions.
Publisher: American Chemical Society
Keywords: Sørishavet; atmosfæren; biokjemi; forurensning; kjemi; miljøgifter

Observation of wave propagation over 1,000 km into Antarctica winter pack ice - Nose, Takehiko; Katsuno, Tomotaka; Waseda, Takuji; Ushio, Shuki; Rabault, Jean; Kodaira, Tsubasa; Voermans, Joey (Coastal Engineering Journal, 2024)
A drifting wave-ice buoy (Medusa-766) was deployed at the Lützow-Holm Bay (LHB) marginal ice zone in Antarctica during the 63rd Japanese Antarctic Research Expedition to study the wave influence on the unstable LHB fast ice. Medusa-766 survived the Antarctic winter as it was located deep in the ice cover with the shortest distance to the ice-free Southern Ocean over 1,000?km; at this time, there was evidence of 8-cm-height wave signal at the buoy position. Using the the ECMWF?s reanalysis wave data, we show that the incoming waves were likely 4-m waves that were generated by an extratropical cyclone in the Southern Ocean. Wave-induced ice breakup potential for this event could extend hundreds of kilometres into the ice field. When Medusa-766 was in LHB in the summer months, it did not detect sizable wave energy despite the low sea ice concentration extent even during on-ice wave events. Understanding the wave attenuation characteristics is needed to elucidate the ocean wave effect to the unstable LHB fast ice. The success of Medusa-766 demonstrates the robustness of the general design and the high sensitivity of the sensor used, which is promising for future LHB wave?ice interaction research.
Publisher: Taylor & Francis
Keywords: Sørishavet; havis; isshelf

Global biochemical profiling of fast-growing Antarctic bacteria isolated from meltwater ponds by high-throughput FTIR spectroscopy - Akulava, Volha; Tafintseva, Valeria; Blazhko, Uladzislau; Kohler, Achim; Miamin, Uladzislau; Valentovich, Leonid; Shapaval, Volha (PLOS ONE, 2024)
Fourier transform infrared (FTIR) spectroscopy is a biophysical technique used for non-destructive biochemical profiling of biological samples. It can provide comprehensive information about the total cellular biochemical profile of microbial cells. In this study, FTIR spectroscopy was used to perform biochemical characterization of twenty-nine bacterial strains isolated from the Antarctic meltwater ponds. The bacteria were grown on two forms of brain heart infusion (BHI) medium: agar at six different temperatures (4, 10, 18, 25, 30, and 37°C) and on broth at 18°C. Multivariate data analysis approaches such as principal component analysis (PCA) and correlation analysis were used to study the difference in biochemical profiles induced by the cultivation conditions. The observed results indicated a strong correlation between FTIR spectra and the phylogenetic relationships among the studied bacteria. The most accurate taxonomy-aligned clustering was achieved with bacteria cultivated on agar. Cultivation on two forms of BHI medium provided biochemically different bacterial biomass. The impact of temperature on the total cellular biochemical profile of the studied bacteria was species-specific, however, similarly for all bacteria, lipid spectral region was the least affected while polysaccharide region was the most affected by different temperatures. The biggest temperature-triggered changes of the cell chemistry were detected for bacteria with a wide temperature tolerance such Pseudomonas lundensis strains and Acinetobacter lwoffii BIM B-1558.
Publisher: Public Library of Science Article number: e0303298
Keywords: Antarktis; bakterier; biokjemi; mikrobielle organismer; mikrobiologi

Microplastics in Southern Ocean sea ice: a pan-Antarctic perspective - Anna Kelly; Thomas Rodemann; Klaus M. Meiners; Heidi J. Auman; Sebastien Moreau; Francois Fripiat; Bruno Dellile; Delphine Lannuzel (Water Emerging Contaminants & Nanoplastics, 2024)
Microplastic (MP; plastic particles < 5 mm) pollution is pervasive in the marine environment, including remote polar environments. This study provides the first pan-Antarctic survey of MP pollution in Southern Ocean sea ice by analyzing sea ice cores from several diverse Antarctic regions. Abundance, chemical composition, and particle size data were obtained from 19 archived ice core samples. The cores were melted, filtered, and chemically analyzed using Fourier-transform infrared spectroscopy and 4,090 MP particles were identified. Nineteen polymer types were found across all samples, with an average concentration of 44.8 (± 50.9) particles·L-1. Abundance and composition varied with ice type and geographical location. Pack ice exhibited significantly higher particle concentrations than landfast ice, suggesting open ocean sources of pollution. Winter sea ice cores had significantly more MPs than spring and summer-drilled cores, suggesting ice formation processes play a role in particle incorporation. Smaller particles dominated across samples. Polyethylene (PE) and polypropylene (PP) were the most common polymers, mirroring those most identified across marine habitats. Higher average MP concentrations in developing sea ice during autumn and winter, contrasting lower levels observed in spring and summer, suggest turbulent conditions and faster growth rates are likely responsible for the increased incorporation of particles. Southern Ocean MP contamination likely stems from both local and distant sources. However, the circulation of deep waters and long-range transport likely contribute to the accumulation of MPs in regional gyres, coastlines, and their eventual incorporation into sea ice. Additionally, seasonal sea ice variations likely influence regional polymer compositions, reflecting the MP composition of the underlying waters.
Keywords: Sørishavet; forurensning; havis; iskjerner; mikroplast; sjøis

Field comparison of Antarctic krill (Euphausia superba) backscatter and aggregation types using NORTEK and SIMRAD echosounders - Annasawmy, Pavanee; Horne, John K.; Reiss, Christian S.; Cutter, George R.; Macaulay, Gavin J. (ICES Journal of Marine Science, 2024)
Temporal distributions of Antarctic krill (Euphausia superba) density and aggregation types were characterized and compared using Nortek Signature100 and SIMRAD Wideband Autonomous Transceiver (WBAT) upward-looking echosounders. Noise varied between the two echosounders. With the Signature100, it was necessary to correct data for background, transient, and impulse noises, while the WBAT data needed to be corrected for background noise only. For selected regions with no visible backscatter, the signal-to-noise ratio of Sv values (i.e. the ratio between the signal and the background noise level) did not vary between the two echosounders. Surface echo backscatter was similar during similar time periods. Descriptive metrics were used to quantify spatial and temporal krill vertical distributions: volume backscatter, mean depth, center of mass, inertia, equivalent area, aggregation index, and proportion occupied. Krill backscatter density differed between the two instruments but was detected at similar mean depths. Krill aggregations were identified at each mooring location and classified in three types based on morphological characteristics. Each type of aggregation shape differed at the two spatially separated moorings, while the acoustic density of each aggregation type was similar. The Signature100 detected a lower number of krill aggregations (n = 133) compared to the WBAT (n = 707). Although both instruments can be used for autonomous deployment and sampling of krill over extended periods, there is a strong caveat for the use of the Signature100 due to significant differences in noise characteristics and krill detection.
Keywords: Sørishavet; dataanalyse; ekkolodd; fiskerier; krill; marin biologi; plankton

Characterizing Antarctic air-breathing predator dive patterns on a common prey base from stationary echosounders - Annasawmy, Pavanee; Horne, John K.; Reiss, Christian S.; Macaulay, Gavin J. (Polar Science, 2024)
Diving patterns of air-breathing predators were monitored from three moored subsurface upward-looking echosounders. Complete and partial dive profiles were visible on active acoustic records as echoes that started and/or returned to the surface. Dive metrics: maximum dive depths, durations, and wiggle count were measured and angles, distances, and velocities, were calculated at each site. Dive shapes ‘U’, ‘V’ and ‘W’ were derived using the number of wiggles and the percentage of dive bottom time. Dive profiles were classified into four types with type 1 dives being short in total duration and distance, low velocities, small angles, shallow, and linked to ‘U’ and ‘W’ shapes. Type 2 dives were short in distance, had low velocities, shallow depths, and were linked to ‘V’ dives. Dive types 3 and 4 had higher velocities, larger angles, longer total durations, and were deeper than types 1 and 2. Observed dive types could correspond to travelling, exploring, and foraging predator behaviors. Significant predator-prey overlaps occurred with predator dive profile counts correlated with krill aggregation thickness, density, and depth. This study demonstrates the utility of using stationary active acoustics to identify predator dive profiles with a simultaneous characterization of the potential prey field.
Article number: 100974
Keywords: Deceptionøya; Sør-Shetlandsøyene; Sørishavet; batymetri; hydroakustikk; marin biologi; marine økosystemer; oseanografi

Seasonal acoustic presence of marine mammals at the South Orkney Islands, Scotia Sea - Åsvestad, Linn; Ahonen, Heidi; Menze, Sebastian; Lowther, Andrew; Lindstrøm, Ulf; Krafft, Bjørn A. (Royal Society Open Science, 2024)
Increased knowledge about marine mammal seasonal distribution and species assemblage from the South Orkney Islands waters is needed for the development of management regulations of the commercial fishery for Antarctic krill (Euphausia superba) in this region. Passive acoustic monitoring (PAM) data were collected during the autumn and winter seasons in two consecutive years (2016, 2017), which represented highly contrasting environmental conditions due to the 2016 El Niño event. We explored differences in seasonal patterns in marine mammal acoustic presence between the two years in context of environmental cues and climate variability. Acoustic signals from five baleen whale species, two pinniped species and odontocete species were detected and separated into guilds. Although species diversity remained stable over time, the ice-avoiding and ice-affiliated species dominated before and after the onset of winter, respectively, and thus demonstrating a shift in guild composition related to season. Herein, we provide novel information about local marine mammal species diversity, community structure and residency times in a krill hotspot. Our study also demonstrates the utility of PAM data and its usefulness in providing new insights into the marine mammal habitat use and responses to environmental conditions, which are essential knowledge for the future development of a sustainable fishery management in a changing ecosystem.
_eprint: https://royalsocietypublishing.org/doi/pdf/10.1098/rsos.230233
Keywords: Sørishavet; marin biologi; pattedyr; zoologi

Outlining three arguments for Rights of Antarctica - Baard, Patrik; Mancilla, Alejandra (The Polar Journal, 2024)
In this article, we investigate three arguments for Rights of Antarctica (RoA), understood as recognising the whole continent as a rights-holder with legal standing. For this, we draw inspiration from the Antarctica Declaration, a text developed by an interdisciplinary and international group of scholars and activists. We scrutinise three justifications that could potentially be used in support of RoA. First, we investigate whether arguments for Rights of Nature (RoN) elsewhere can support RoA. RoN has been accepted in several domestic legislations. Unfortunately, we discover important disanalogies between RoA and RoN, defeating the purpose of justifying RoA with reference to RoN. Second, we scrutinise potential arguments that focus on giving rights to specific Antarctic ecoregions or places. However, such arguments would only cover parts of the continent, thus going against the holistic approach of RoA, and they would require using a broader understanding of ?attachments? as grounds for justifying rights for parts of Antarctica. In contrast, we construct an argument for accepting RoA based on four components: (1) Antarctica?s intrinsic value, (2) wider forms of human attachments, (3) Antarctica?s substantial role as a global systemic resource, and (4) the fact that Antarctica is under recurrent and substantial threats. While none of these are individually sufficient for recognising RoA, they can jointly make RoA appropriate. We conclude that it remains an open question whether international law or, more specifically, the Antarctic Treaty, would be open to such conceptual and normative innovation, adopting a new paradigm in our treatment of the nonhuman natural world. At the same time, we hope to kickstart a discussion of what RoA would require and how it should relate more generally to RoN discourses.
Publisher: Routledge
Keywords: Antarktis; Antarktistraktaten; jus

Sources of low-frequency variability in observed Antarctic sea ice - Bonan, D. B.; Dörr, J.; Wills, R. C. J.; Thompson, A. F.; Årthun, M. (The Cryosphere, 2024)
Antarctic sea ice has exhibited significant variability over the satellite record, including a period of prolonged and gradual expansion, as well as a period of sudden decline. A number of mechanisms have been proposed to explain this variability, but how each mechanism manifests spatially and temporally remains poorly understood. Here, we use a statistical method called low-frequency component analysis to analyze the spatiotemporal structure of observed Antarctic sea ice concentration variability. The identified patterns reveal distinct modes of low-frequency sea ice variability. The leading mode, which accounts for the large-scale, gradual expansion of sea ice, is associated with the Interdecadal Pacific Oscillation and resembles the observed sea surface temperature trend pattern that climate models have trouble reproducing. The second mode is associated with the central Pacific El Niño–Southern Oscillation (ENSO) and the Southern Annular Mode and accounts for most of the sea ice variability in the Ross Sea. The third mode is associated with the eastern Pacific ENSO and Amundsen Sea Low and accounts for most of the pan-Antarctic sea ice variability and almost all of the sea ice variability in the Weddell Sea. The third mode is also related to periods of abrupt Antarctic sea ice decline that are associated with a weakening of the circumpolar westerlies, which favors surface warming through a shoaling of the ocean mixed layer and decreased northward Ekman heat transport. Broadly, these results suggest that climate model biases in long-term Antarctic sea ice and large-scale sea surface temperature trends are related to each other and that eastern Pacific ENSO variability is a key ingredient for abrupt Antarctic sea ice changes.
Publisher: Copernicus Publications
Keywords: Sørishavet; havis; klimamodeller; klimatologi; meteorologi; oseanografi; sjøis

Glacial–interglacial Circumpolar Deep Water temperatures during the last 800 000 years: estimates from a synthesis of bottom water temperature reconstructions - Chandler, D. M.; Langebroek, Petra M. (Clim. Past, 2024)
Future climate and sea level projections depend sensitively on the response of the Antarctic Ice Sheet to ocean-driven melting and the resulting freshwater fluxes into the Southern Ocean. Circumpolar Deep Water (CDW) transport across the Antarctic continental shelf and into cavities beneath ice shelves is increasingly recognised as a crucial heat source for ice shelf melt. Quantifying past changes in the temperature of CDW is therefore of great benefit for modelling ice sheet response to past warm climates, for validating paleoclimate models, and for putting recent and projected changes in CDW temperature into context. Here we compile the available bottom water temperature reconstructions representative of CDW over the past 800 kyr. Estimated interglacial warming reached anomalies of +0.6 +/- 0.4 degrees C (MIS 11) and +0.5 +/- 0.5 degrees C (MIS 5) relative to present. Glacial cooling typically reached anomalies of ca. -1.5 to -2 degrees C, therefore maintaining positive thermal forcing for ice shelf melt even during glacials in the Amundsen Sea region of West Antarctica. Despite high variance amongst a small number of records and poor (4 kyr) temporal resolution, we find persistent and close relationships between our estimated CDW temperature and Southern Ocean sea surface temperature, Antarctic surface air temperature, and global deep-water temperature reconstructions at glacial-cycle timescales. Given the important role that CDW plays in connecting the world's three main ocean basins and in driving Antarctic Ice Sheet mass loss, additional temperature reconstructions targeting CDW are urgently needed to increase temporal and spatial resolution and to decrease uncertainty in past CDW temperatures - whether for use as a boundary condition, for model validation, or for understanding past oceanographic changes.
Publisher: Copernicus Publications
Keywords: Sørishavet; klimamodeller; klimatologi; oseanografi; paleoklimatologi

Observations of the Antarctic Slope Current in the Southeastern Weddell Sea: A Bottom-Enhanced Current and Its Seasonal Variability - Darelius, Elin; Fer, Ilker; Janout, Markus; Daae, Kjersti; Steiger, Nadine (Journal of Geophysical Research: Oceans, 2024)
Abstract The Antarctic Slope Front and the associated Antarctic Slope Current dynamically regulate the exchanges of heat across the continental shelf break around Antarctica. Where the front is weak, relatively warm deep waters reach the ice shelf cavities, contributing to basal melting and ultimately affecting sea level rise. Here, we present new 2017?2021 records from two moorings deployed on the upper continental slope (530 and 738 m depth) just upstream of the Filchner Trough in the southeastern Weddell Sea. The structure and seasonal variability of the frontal system in this region, central to the inflow of warm water toward the large Filchner-Ronne Ice Shelf, is previously undescribed. We use the records to describe the mean state and the seasonal variability of the regional hydrography and the southern part of the Antarctic Slope Current. We find that (a) the current is, contrary to previous assumptions, bottom-enhanced, (b) the isotherms slope upwards toward the shelf break, and more so for warmer isotherms, and (c) the monthly mean thermocline depth is shallowest in February-March and deepest in May-June while (d) the current is strongest in April-June. On monthly timescales, we show that (e) positive temperature anomalies of the de-seasoned records are associated with weaker-than-average currents. We propose that the upward-sloping isotherms are linked to the local topography and conservation of potential vorticity. Our results contribute to the understanding of how warm ocean waters propagate southward and potentially affect basal melt rates at the Filchner-Ronne Ice Shelf.
Publisher: John Wiley & Sons, Ltd Article number: e2023JC020666
Keywords: Sørishavet; Weddellhavet; havstrømmer; oseanografi

A virtual geobibliography of polar tourism and climate change - Demiroglu, O. Cenk; Bohn, Dorothee; Dannevig, Halvor; Hall, C. Michael; Hehir, Christy; Lundmark, Linda; Nilsson, Robert O.; Olsen, Julia; Tervo-Kankare, Kaarina; Vereda, Marisol; Welling, Johannes (Journal of Sustainable Tourism, 2024)
The polar regions are increasingly at the center of attention as the hot spots of climate crisis as well as tourism development. The recent IPCC reports highlight several climate change risks for the rather carbon-intensive and weather-based/dependent polar tourism industry in the Arctic and the Antarctic. This study presents the scholarly state-of-knowledge on tourism and climate change in the polar regions with a literature survey extending beyond the Anglophone publications. As a supporting tool, we provide a live web GIS application based on the geographical coverages of the publications and filterable by various spatial, thematic and bibliographical attributes. The final list of 137 publications indicates that, regionally, the Arctic has been covered more than the Antarctic, whilst an uneven distribution within the Arctic also exists. In terms of the climate change risks themes, climate risk research, i.e. impact and adaptation studies, strongly outnumbers the carbon risk studies especially in the Arctic context, and, despite a balance between the two main risk themes, climate risk research in the Antarctic proves itself outdated. Accordingly, the review ends with a research agenda based on these spatial and thematic gaps and their detailed breakdowns.
Publisher: Routledge
Keywords: Antarktis; bibliografi; geobibliografi; klimaendringer; polarområdene; turisme

Southern Ocean sea ice, icebergs, and meteorological data from maritime sources for the period 1929 to 1940 - Divine, Dmitry V.; Divina, Svetlana; Bjørge, Ole Edvard; Isaksson, Elisabeth; Jølle, Harald Dag; Stokkeland, Ivar; Vasquez Guzman, Mariela; Wilkinson, Sally; Wilkinson, Clive (Geoscience Data Journal, 2024)
Maritime historical documentary sources of weather and state of sea surface including sea ice can aid in filling a known climate knowledge gap for the Southern Ocean and Antarctica for the first half of the 20th century. This study presents a data set of marine climate, sea ice and icebergs recovered from a collection of logbooks from mainly Norwegian whaling factory ships that operated in the Southern Ocean during 1929-1940. The data set comprises some 8000 weather and 4000 sea ice/open sea records from austral summers of the study period. This paper further discusses the structure and content of most common Norwegian maritime documentary sources of the period along with the practices of logging information relevant for the study, such as time keeping, positioning and making weather observations. An emphasis was made on recovery of notes on sea ice and icebergs and their interpretation in terms of WMO categories of sea ice concentration. Data, including ship-related metadata from all individual documents are homogenized and structured to a common machine-readable format that simplifies its ingestion into relevant climate data depositories.
Publisher: John Wiley & Sons, Ltd
Keywords: Sørishavet; hvalfangst; isberg; klima; meteorologi; sjøis; skipsloggbøker

Early aerial expedition photos reveal 85 years of glacier growth and stability in East Antarctica - Dømgaard, Mads; Schomacker, Anders; Isaksson, Elisabeth; Millan, Romain; Huiban, Flora; Dehecq, Amaury; Fleischer, Amanda; Moholdt, Geir; Andersen, Jonas K.; Bjørk, Anders A. (Nature Communications, 2024)
During the last few decades, several sectors in Antarctica have transitioned from glacial mass balance equilibrium to mass loss. In order to determine if recent trends exceed the scale of natural variability, long-term observations are vital. Here we explore the earliest, large-scale, aerial image archive of Antarctica to provide a unique record of 21 outlet glaciers along the coastline of East Antarctica since the 1930s. In Lützow-Holm Bay, our results reveal constant ice surface elevations since the 1930s, and indications of a weakening of local land-fast sea-ice conditions. Along the coastline of Kemp and Mac Robertson, and Ingrid Christensen Coast, we observe a long-term moderate thickening of the glaciers since 1937 and 1960 with periodic thinning and decadal variability. In all regions, the long-term changes in ice thickness correspond with the trends in snowfall since 1940. Our results demonstrate that the stability and growth in ice elevations observed in terrestrial basins over the past few decades are part of a trend spanning at least a century, and highlight the importance of understanding long-term changes when interpreting current dynamics.
Article number: 4466
Keywords: Antarktis; Thorshavn ekspedisjon; flyfotografering; geografi; glasiologi; kartlegging; klimaendringer; klimatologi; kryosfæren; topografi

Conjugate aurora observations by the Gjøa and Discovery expeditions - Egeland, Alv (Hist. Geo Space. Sci., 2024)
From 1901 to 1912 – known as the “heroic period” of Arctic and Antarctic exploration – great inroads were made (not only geographic but also scientific) to our knowledge of the continent. At Amundsen's Expedition through the Northwest Passage, measurements of the geomagnetic field and visual auroras were carried out for 19 months at Gjoa Haven (Gjøahavn in Norwegian; geographic coordinates 68°37′10′′ N, 95°53′25′′ W). Scott's Discovery Expedition – at Cape Armitage, McMurdo (coordinates 77.86° S, 166.69° E), Antarctica – carried out the same type of measurements. Their observations were carried out geomagnetically conjugate to Gjoa Haven, with both stations close to 78° magnetic latitude. In addition, measurements were overlapping in time during 1903–1904. However, these two stations are located at different longitudes, so there is a difference in local time between the stations of about 6.5 h. Gjoa Haven and Cape Armitage are conveniently located for separating disturbances in the polar cap regions caused by solar electromagnetic radiations or the solar wind. Auroras were observed during 7 months per year. This gave a unique possibility to compare conjugate characteristics of polar cap auroras. Comparing conjugate geophysical data introduces some difficulties. During the winter season at Gjoa Haven, they had a bright summer in Antarctica, and visa versa. Thus, simultaneous temporal and spatial ionospheric variations can be marked differently. Still, the average diurnal and seasonal variations were similar. The quantity of the auroral data from Cape Armitage was larger because there they had a continuous watch of the sky. The main findings regarding polar cap auroras are the following. Three different auroral forms dominate the polar cap. Low-intensity auroral bands – then called streamers – were the dominating auroral forms morning and afternoon. The number of auroral events in 1903 was nearly twice that in 1902 and 1904. A marked midwinter maximum was observed at both stations. Many displays were observed poleward of the oval. The large fraction was associated with weak magnetic disturbances. Some forms of polar cap aurora have special magnetic signatures and seem to be anti-correlated with Kp. They can be mapped even if they are not seen. According to recent satellite measurements (Newell et al., 2009), they are probably caused by polar rain and/or photoelectrons.
Publisher: Copernicus Publications
Keywords: Antarktis; Discoveryekspedisjonen; fysikk; polarfarere; polarområdene; romfysikk; sørlys

Features and processes of rock weathering in central Dronning Maud Land, Antarctica - Elvevold, Synnøve; Engvik, Ane K.; Sunde, Øyvind (Geomorphology, 2024)
In this study, we have investigated rock weathering phenomena in the central part of Dronning Maud Land, Antarctica. The area is characterized by low mean annual temperatures (−18 °C), strong katabatic winds, and minimal liquid water at the surface. Weathering features, including ventifacts, tafoni, and grus accumulations, are characterized through field observations, rock surface temperature measurements, and microscopic analysis. Abrasion by sand and ice particles transported by strong winds has locally resulted in ridge-shaped ventifacts and rock surfaces with elongated pits, furrows, and grooves. The abrasion-caused features, such as polished facets, keels, and grooves, indicate a northeast-facing wind direction, aligning with the present-day wind regime. The dominant weathering processes in coarse-grained intrusive rocks are oxidation and granular disintegration. Fe-oxidation induces cracking, increasing the porosity and enhancing susceptibility to further weathering. Additionally, temperature fluctuations on rock surfaces caused by solar radiation create thermal stress, which can lead to the formation of microcracks. These microcracks, formed due to thermal expansion, are likely to propagate through subcritical cracking, which is a slow, long-term process. Together, Fe-oxidation, thermal expansion, and subcritical cracking are important mechanisms contributing to long-term weathering and rock decay. Salt weathering, facilitated by snow and ice meltwater, particularly within tafoni, leads to flaking and disintegration of the parent rock. These findings shed light on the complex interactions shaping the geomorphology of central Dronning Maud Land and provide insights into long-term weathering processes operating in Antarctica's extreme environment.
Article number: 109435
Keywords: Dronning Maud Land; geologi; geomorfologi

Observed water-mass characteristics and circulation off Prydz Bay, East Antarctica - Foppert, Annie; Bestley, Sophie; Shadwick, Elizabeth H.; Klocker, Andreas; Vives, Clara R.; Liniger, Guillaume; Westwood, Karen J. (Frontiers in Marine Science, 2024)
Circulation and water masses in the greater Prydz Bay region were surveyed in the austral summer 2021 (January-March) during the ‘Trends in Euphausiids off Mawson, Predators and Oceanography’ (TEMPO) experiment, and are described in this paper. The Southern Antarctic Circumpolar Current Front is found in the northern part of the survey area, generally near 63-64°S, whereas the Southern Boundary Front is located between 64 and 65.5°S. The westward flowing Antarctic Slope Front (ASF) is found in the southern part of the survey area near the continental slope on most transects. Highest concentrations of oxygen (> 300 µmol kg−1) are found in shelf waters at stations in Prydz Bay, south of 67°S along 75°E, whereas the lowest oxygen values are found in the Circumpolar Deep Water layer, with an average of roughly 215 µmol kg−1. North of the northern extension of the ASF, surface mixed layers are between 20 and 60 m deep. Mixed layers tend to deepen slightly in the northern part of the survey, generally increasing north of 64°S where the ocean has been ice-free the longest. We find evidence of upwelling of waters into the surface layers, based on temperature anomaly, particularly strong along 80°E. Enhanced variability of biogeochemical properties - nutrients, DIC, DO - in the AASW layer is driven by a combination of sea-ice and biological processes. Antarctic Bottom Water, defined as water with neutral density > 28.3 kg m-3, was sampled at all the offshore full-depth stations, with a colder/fresher variety along western transects and a warmer/saltier variety in the east. Newly formed Antarctic Bottom Water – the coldest, freshest, and most recently ventilated – is mostly found in the deep ocean along 65°E, in the base of the Daly Canyon.
Keywords: AABW; Sørishavet; klimatologi; oseanografi; vannmasser

An Assessment of Subseasonal Prediction Skill of the Antarctic Sea Ice Edge - Gao, Yuchun; Xiu, Yongwu; Nie, Yafei; Luo, Hao; Yang, Qinghua; Zampieri, Lorenzo; Lv, Xianqing; Uotila, Petteri (Journal of Geophysical Research: Oceans, 2024)
Abstract In this study, the subseasonal Antarctic sea ice edge prediction skill of the Copernicus Climate Change Service (C3S) and Subseasonal to Seasonal (S2S) projects was evaluated by a probabilistic metric, the spatial probability score (SPS). Both projects provide subseasonal to seasonal scale forecasts of multiple coupled dynamical systems. We found that predictions by individual dynamical systems remain skillful for up to 38 days (i.e., the ECMWF system). Regionally, dynamical systems are better at predicting the sea ice edge in the West Antarctic than in the East Antarctic. However, the seasonal variations of the prediction skill are partly system-dependent as some systems have a freezing-season bias, some had a melting-season bias, and some had a season-independent bias. Further analysis reveals that the model initialization is the crucial prerequisite for skillful subseasonal sea ice prediction. For those systems with the most realistic initialization, the model physics dictates the propagation of initialization errors and, consequently, the temporal length of predictive skill. Additionally, we found that the SPS-characterized prediction skill could be improved by increasing the ensemble size to gain a more realistic ensemble spread. Based on the C3S systems, we constructed a multi-model forecast from the above principles. This forecast consistently demonstrated a superior prediction skill compared to individual dynamical systems or statistical observation-based benchmarks. In summary, our results elucidate the most important factors (i.e., the model initialization and the model physics) affecting the currently available subseasonal Antarctic sea ice prediction systems and highlighting the opportunities to improve them significantly.
Publisher: John Wiley & Sons, Ltd
Keywords: Sørishavet; havis; klimaendringer; klimatologi; oseanografi; sjøis

Museomics analyses inform about Channichthys icefish species diversity - Garmann-Aarhus, Benedicte; Nikolaeva, Ekaterina; Desvignes, Thomas; Straube, Nicolas; Matschiner, Michael (bioRxiv, 2024)
The rapid diversification of notothenioid fishes in the waters surrounding the Antarctic continent is a prime example of the process of adaptive radiation. Within around 10 million years, Antarctic notothenioids have diversified into over 100 species with a broad range of lifestyles and ecological adaptations. However, the exact number of species within this radiation has long been unclear. Particularly challenging is the taxonomy of the genus Channichthys, for which between one and nine species have been recognized by different authors. The putative species from this genus are known from a limited number of representative specimens, of which most were sampled decades ago. Here, we investigated the mitochondrial genomes of museum specimens representing the four recently recognized species Unicorn Icefish (C. rhinoceratus), Red Icefish (C. rugosus), Sailfish Pike (C. velifer), and Charcoal Icefish (C. panticapaei), complemented by morphological analyses. All analyzed specimens were collected in the 1960s and 1970s and fixed in formaldehyde, and their DNA has thus been heavily degraded. Applying ancient-DNA protocols for DNA extraction and single-stranded library preparation, we were nevertheless able to obtain sufficient endogenous DNA to reconstruct the mitochondrial genomes of one specimen of each species. These mitochondrial genome sequences were nearly identical for the three specimens assigned to Unicorn Icefish, Red Icefish, and Sailfish Pike, while greater mitochondrial divergence was observed for the Charcoal Icefish specimens. We discuss possible explanations of the contrast between these molecular results and the recognizable morphological variation found among the four species, and recommend that at least the Charcoal Icefish be included the list of valid icefish and notothenioid species.Competing Interest StatementThe authors have declared no competing interest.
Article Number: 32
Keywords: Sørishavet; fisker; genetisk analyse; marin biologi; morfologi; taksonomi; zoologi; økologi

Machine learning applied to species occurrence and interactions: the missing link in biodiversity assessment and modelling of Antarctic plankton distribution - Grillo, Marco; Schiaparelli, Stefano; Durazzano, Tiziana; Guglielmo, Letterio; Granata, Antonia; Huettmann, Falk (Ecological Processes, 2024)
Background: Plankton is the essential ecological category that occupies the lower levels of aquatic trophic networks, representing a good indicator of environmental change. However, most studies deal with distribution of single spe- cies or taxa and do not take into account the complex of biological interactions of the real world that rule the ecologi- cal processes. Results: This study focused on analyzing Antarctic marine phytoplankton, mesozooplankton, and microzooplankton, examining their biological interactions and co-existences. Field data yielded 1053 biological interaction values, 762 coexistence values, and 15 zero values. Six phytoplankton assemblages and six copepod species were selected based on their abundance and ecological roles. Using 23 environmental descriptors, we modelled the distribution of taxa to accurately represent their occurrences. Sampling was conducted during the 2016–2017 Italian National Antarctic Programme (PNRA) ‘P-ROSE’ project in the East Ross Sea. Machine learning techniques were applied to the occurrence data to generate 48 predictive species distribution maps (SDMs), producing 3D maps for the entire Ross Sea area. These models quantitatively predicted the occurrences of each copepod and phytoplankton assemblage, providing crucial insights into potential variations in biotic and trophic interactions, with significant implications for the man- agement and conservation of Antarctic marine resources. The Receiver Operating Characteristic (ROC) results indi- cated the highest model efficiency, for Cyanophyta (74%) among phytoplankton assemblages and Paralabidocera antarctica (83%) among copepod communities. The SDMs revealed distinct spatial heterogeneity in the Ross Sea area, with an average Relative Index of Occurrence values of 0.28 (min: 0; max: 0.65) for phytoplankton assemblages and 0.39 (min: 0; max: 0.71) for copepods. Conclusion: The results of this study are essential for a science-based management for one of the world’s most pris- tine ecosystems and addressing potential climate-induced alterations in species interactions. Our study emphasizes the importance of considering biological interactions in planktonic studies, employing open access and machine learning for measurable and repeatable distribution modelling, and providing crucial ecological insights for informed conservation strategies in the face of environmental change.
Article number: 56 (2024)
Keywords: Rosshavet; Sørishavet; biodiversitet; fytoplankton; marin biologi

Short- and long-term variability of the Antarctic and Greenland ice sheets - Hanna, Edward; Topál, Dániel; Box, Jason E.; Buzzard, Sammie; Christie, Frazer D. W.; Hvidberg, Christine; Morlighem, Mathieu; De Santis, Laura; Silvano, Alessandro; Colleoni, Florence; Sasgen, Ingo; Banwell, Alison F.; et al. (Nature Reviews Earth & Environment, 2024)
The variability of the Antarctic and Greenland ice sheets occurs on various timescales and is important for projections of sea level rise; however, there are substantial uncertainties concerning future ice-sheet mass changes. In this Review, we explore the degree to which short-term fluctuations and extreme glaciological events reflect the ice sheets’ long-term evolution and response to ongoing climate change. Short-term (decadal or shorter) variations in atmospheric or oceanic conditions can trigger amplifying feedbacks that increase the sensitivity of ice sheets to climate change. For example, variability in ocean-induced and atmosphere-induced melting can trigger ice thinning, retreat and/or collapse of ice shelves, grounding-line retreat, and ice flow acceleration. The Antarctic Ice Sheet is especially prone to increased melting and ice sheet collapse from warm ocean currents, which could be accentuated with increased climate variability. In Greenland both high and low melt anomalies have been observed since 2012, highlighting the influence of increased interannual climate variability on extreme glaciological events and ice sheet evolution. Failing to adequately account for such variability can result in biased projections of multi-decadal ice mass loss. Therefore, future research should aim to improve climate and ocean observations and models, and develop sophisticated ice sheet models that are directly constrained by observational records and can capture ice dynamical changes across various timescales.
Keywords: Antarktis; glasiologi; innlandsis; klimaendringer; polarområdene

Drivers of phytoplankton distribution, abundance and community composition off East Antarctica, from 55-80°E (CCAMLR Division 58.4.2 East) - Heidemann, Asta C.; Westwood, Karen J.; Foppert, Annie; Wright, Simon W.; Klocker, Andreas; Vives, Clara R.; Wotherspoon, Simon; Bestley, Sophie (Frontiers in Marine Science, 2024)
Southern Ocean phytoplankton form the base of the Antarctic food web, influencing higher trophic levels through biomass and community structure. We examined phytoplankton distribution and abundance in the Indian Sector of the Southern Ocean during austral summer as part a multidisciplinary ecosystem survey: Trends in Euphausiids off Mawson, Predators and Oceanography (TEMPO, 2021). Sampling covered six meridional transects from 55-80°E, and from 62°S or 63°S to the ice edge. To determine phytoplankton groups, CHEMTAX analysis was undertaken on pigments measured using HPLC. Diatoms were the dominant component of phytoplankton communities, explaining 56% of variation in chlorophyll a (Chl a), with haptophytes also being a major component. Prior to sampling the sea ice had retreated in a south-westerly direction, leading to shorter ice-free periods in the west (< 44 days, ≤65°E) compared to east (> 44 days, ≥70°E), inducing a strong seasonal effect. The east was nutrient limited, indicated by low-iron forms of haptophytes, and higher silicate:nitrate drawdown ratios (5.1 east vs 4.3 west), pheophytin a (phaeo) concentrations (30.0 vs 18.4 mg m-2) and phaeo:Chl a ratios (1.06 vs 0.53). Biological influences were evident at northern stations between 75-80°E, where krill “super-swarms” and feeding whales were observed. Here, diatoms were depleted from surface waters likely due to krill grazing, as indicated by high phaeo:Chl a ratios (> 0.75), and continued presence of haptophytes, associated with inefficient filtering or selective grazing by krill. Oceanographic influences included deeper mixed layers reducing diatom biomass, and a bloom to the north of the southern Antarctic Circumpolar Current Front in the western survey area thought to be sinking as waters flowed from west to east. Haptophytes were influenced by the Antarctic Slope Front with high-iron forms prevalent to the south only, showing limited iron transfer from coastal waters. Cryptophytes were associated with meltwater, and greens (chlorophytes + prasinophytes) were prevalent below the mixed layer. The interplay of seasonal, biological and oceanographic influences on phytoplankton populations during TEMPO had parallels with processes observed in the BROKE and BROKE-West voyages conducted 25 and 15 years earlier, respectively. Our research consolidates understanding of the krill ecosystem to ensure sustainable management in East Antarctic waters.
Keywords: Sørishavet; fytoplankton; krill; marin biologi; marine økosystemer; oseanografi; phytoplankton

The Use of Weather, Water, Ice, and Climate (WWIC) Information in the Polar Regions: What Is Known after the Decadelong Polar Prediction Project? - Heinrich, Victoria J.; Stewart, Emma J.; Liggett, Daniela; Carrasco, Jorge F.; Dawson, Jackie; Lamers, Machiel; Ljubicic, Gita J.; Jeuring, Jelmer; Thoman, Rick (Weather, Climate, and Society, 2024)
The polar regions are facing a wide range of compounding challenges, from climate change to increased human activity. Infrastructure, rescue services, and disaster response capabilities are limited in these remote environments. Relevant and usable weather, water, ice, and climate (WWIC) information is vital for safety, activity success, adaptation, and environmental protection. This has been a key focus for the World Meteorological Organization’s (WMO) Polar Prediction Project (PPP), and in particular its “Societal and Economic Research and Applications” (PPP-SERA) Task Team, which together over a decade have sought to understand polar WWIC information use in relation to operational needs, constraints, and decision contexts to inform the development of relevant services. To understand research progress and gaps on WWIC information use during the PPP (2013–23), we undertook a systematic bibliometric review of aligned scholarly peer-reviewed journal articles (n = 43), examining collaborations, topics, methods, and regional differences. Themes to emerge included activity and context, human factors, information needs, situational awareness, experience, local and Indigenous knowledge, and sharing of information. We observed an uneven representation of disciplinary backgrounds, geographic locations, research topics, and sectoral foci. Our review signifies an overall lack of Antarctic WWIC services research and a dominant focus on Arctic sea ice operations and risks. We noted with concern a mismatch between user needs and services provided. Our findings can help to improve WWIC services’ dissemination, communication effectiveness, and actionable knowledge provision for users and guide future research as the critical need for salient weather services across the polar regions remains beyond the PPP. Significance Statement Every day, people in the Arctic and Antarctic use weather, water, ice, and climate information to plan and carry out outdoor activities and operations in a safe way. Despite advances in numerical weather prediction, technology, and product development, barriers to accessing and effectively communicating high-quality usable observations, forecasts, and actionable knowledge remain. Poorer services, prediction accuracy, and interpretation are exacerbated by a lack of integrated social science research on relevant topics and a mismatch between the services provided and user needs. As a result, continued user engagement, research focusing on information use, risk communication, decision-making processes, and the application of science for services remain highly relevant to reducing risks and improving safety for people living, visiting, and working in the polar regions.
Place: Boston MA, USA Publisher: American Meteorological Society
Keywords: Antarktis; klimaendringer; klimatologi; meteorologi; polarområdene

Arctic copepod copper sensitivity and comparison with Antarctic and temperate copepods - Heuschele, Jan; Dinh, Khuong V.; Lode, Torben; Jager, Tjalling; Borgå, Katrine (Ecotoxicology, 2024)
The ongoing global climate crisis increases temperatures in polar regions faster and with greater magnitude than elsewhere. The decline of Arctic sea ice opens up new passages, eventually leading to higher anthropogenic activities such as shipping, fishing, and mining. Climate change and anthropogenic activities will increase contaminant transport from temperate to Arctic regions. The shipping industry uses copper as an antifouling coating. Copper is an essential element but becomes toxic at excess concentrations, and its use may inadvertently affect non-target organisms such as copepods. Copper affects copepods by lowering reproductive output, prolonging developmental time, and causing increased mortality. As data on copper sensitivity of polar copepods at low temperatures are rare, we conducted onboard survival experiments with the Arctic region’s most common copepod species (Calanus finmarchicus, C. glacialis, C. hyperboreus). Acute survival tests were done for up to 8 days on individuals in 70 ml bottles at 1 °C with nominal copper concentrations ranging from 3 to 480 μg L−1. We used a reduced General Unified Threshold model for Survival (GUTS) to analyse the data, and placed our results in the context of the few published copper sensitivity data of the Antarctic and temperate copepod species at low temperatures. The sensitivity of Cu exposure was similar between the three Calanus species. However, a model comparison suggests that the tested C. glacialis population is less sensitive than the other two species in our experiments. Compared to published data, the three Arctic species appear slightly less sensitive to copper compared to their Antarctic counterparts but more compared to their temperate ones. Our literature search revealed only a few available studies on the copper sensitivity of polar copepods. In the future, this species group will be exposed to more pollutants, which warrants more studies to predict potential risks, especially given possible interactions with environmental factors.
Keywords: Antarktis; copepoder; forurensning; hoppekreps; klimaendringer; marin biologi; miljøgifter; polarområdene; økotoksikologi

Ocean warming as a trigger for irreversible retreat of the Antarctic ice sheet - Hill, Emily A.; Gudmundsson, G. Hilmar; Chandler, David M. (Nature Climate Change, 2024)
Warmer ocean conditions could impact future ice loss from Antarctica due to their ability to thin and reduce the buttressing of laterally confined ice shelves. Previous studies highlight the potential for a cold to warm ocean regime shift within the sub-shelf cavities of the two largest Antarctic ice shelves—the Filchner–Ronne and Ross. However, how this impacts upstream ice flow and mass loss has not been quantified. Here using an ice sheet model and an ensemble of ocean-circulation model sub-shelf melt rates, we show that transition to a warm state in those ice shelf cavities leads to a destabilization and irreversible grounding line retreat in some locations. Once this ocean shift takes place, ice loss from the Filchner–Ronne and Ross catchments is greatly accelerated, and conditions begin to resemble those of the present-day Amundsen Sea sector—responsible for most current observed Antarctic ice loss—where this thermal shift has already occurred.
Keywords: Amundsenhavet; Antarktis; Sørishavet; global oppvarming; innlandsis; klimaendringer; klimatologi

Stepwise Oligocene–Miocene breakdown of subpolar gyres and strengthening of the Antarctic Circumpolar Current - Hoem, F. S.; van den Broek, K.; López-Quirós, A.; van de Lagemaat, S. H. A.; Bohaty, S. M.; Hillenbrand, C.-D.; Larter, R. D.; van Peer, T. E.; Brinkhuis, H.; Sangiorgi, F.; Bijl, P. K. (J. Micropalaeontol., 2024)
Through the Cenozoic (66–0 Ma), the dominant mode of ocean surface circulation in the Southern Ocean transitioned from two large subpolar gyres to circumpolar circulation with a strong Antarctic Circumpolar Current (ACC) and complex ocean frontal system. Recent investigations in the southern Indian and Pacific oceans show warm Oligocene surface water conditions with weak frontal systems that started to strengthen and migrate northwards during the late Oligocene. However, due to the paucity of sedimentary records and regional challenges with traditional proxy methods, questions remain about the southern Atlantic oceanographic transition from gyral to circumpolar circulation, with associated development of frontal systems and sea ice cover in the Weddell Sea. Our ability to reconstruct past Southern Ocean surface circulation and the dynamic latitudinal positions of the frontal systems has improved over the past decade. Specifically, increased understanding of the modern ecologic affinity of organic-walled dinoflagellate cyst (dinocyst) assemblages from the Southern Ocean has improved reconstructions of distinct past oceanographic conditions (sea surface temperature, salinity, nutrients, and sea ice) using downcore assemblages from marine sediment records. Here we present new late Oligocene to latest Miocene (∼ 26–5 Ma) dinocyst assemblage data from marine sediment cores in the southwestern Atlantic Ocean (International Ocean Discovery Program (IODP) Site U1536, Ocean Drilling Program (ODP) Site 696 and piston cores from Maurice Ewing Bank). We compare these to previously published latest Eocene–latest Miocene (∼ 37–5 Ma) dinocyst assemblage records and sea surface temperature (SST) reconstructions available from the SW Atlantic Ocean in order to reveal oceanographic changes as the Southern Ocean gateways widen and deepen. The observed dinocyst assemblage changes across the latitudes suggest a progressive retraction of the subpolar gyre and southward migration of the subtropical gyre in the Oligocene–early Miocene, with strengthening of frontal systems and progressive cooling since the middle Miocene (∼ 14 Ma). Our data are in line with the timing of the removal of bathymetric and geographic obstructions in the Drake Passage and Tasmanian Gateway regions, which enhanced deep-water throughflow that broke down gyral circulation into the Antarctic circumpolar flow. Although the geographic and temporal coverage of the data is relatively limited, they provide a first insight into the surface oceanographic evolution of the late Cenozoic southern Atlantic Ocean.
Publisher: Copernicus Publications
Keywords: Sørishavet; Sørishavsstrømmen; Weddellhavet; mikropaleontologi; oseanografi

Revisiting Winter Southern Ocean CO2 Uptake Based on CALIPSO Observations - Huang, Hao; Zhang, Ke; Zhang, Zhaoru; Smith Jr., Walker; He, Jianfeng; Liu, Na; Le, Chengfeng (Geophysical Research Letters, 2024)
The absorption of atmospheric carbon dioxide (CO2) in the Southern Ocean represents a critical component of the global oceanic carbon budget. Previous assessments of air-sea carbon flux variations and long-term trends in polar regions during winter have faced limitations due to scarce field data and the lack of ocean color satellite imagery, causing uncertainties in estimating CO2 flux estimation. This study utilized the Cloud-Aerosol Lidar and Infrared Pathfinder Satellite Observation satellite to construct a continuous 16-year (2006?2021) time series of sea surface partial pressure of CO2 (pCO2) in the Southern Ocean. Our findings revealed that the polar region in South Ocean acts as a carbon sink in winter, with CO2 flux of ?30 TgC in high-latitude areas (South of 50°S). This work highlights the efficacy of active remote sensing for monitoring sea surface pCO2 and contributes insights into the dynamic carbonate systems of the Southern Ocean.
Publisher: John Wiley & Sons, Ltd Article Number: e2024GL108335
Keywords: Sørishavet; karbon syklus; karbondioksid; klimaendringer; oseanografi

Sensitivity of the stock assessment for the Antarctic krill fishery to time-varying natural and fishing mortality - Johannessen, Elling Deehr; Krafft, Bjørn A.; Donovan, Carl R.; Wiff, Rodrigo; Caneco, Bruno; Lowther, Andrew (Fisheries Management and Ecology, 2024)
The stock assessment model for the Antarctic krill fishery is a population model operating on daily timesteps, which permits modeling within-year patterns of some population dynamics. We explored the effects of including within-year patterns in natural and fishing mortality on catch limits of krill, by incorporating temporal presence of key predator species and contemporary temporal trends of the fishing fleet. We found that inclusion of within-year variation in natural and fishing mortalities increased catch limits. Fishing mortality had a greater effect than natural mortality despite differences in top-down predation on krill, and potentially increased catch limits by 24% compared to the baseline model. Additionally, the stock assessment model allowed a higher catch limit when fishing was during peak summer months than autumn. Number of days with active fishing was negatively related to precautionary catch limits. Future stock assessments should incorporate contemporary spatiotemporal fishing trends and consider implementing additional ecosystem components into the model.
Publisher: John Wiley & Sons, Ltd
Keywords: Sørishavet; fiskeriforvaltning; krill; marin økologi; marine økosystemer; plankton

SMOS-derived Antarctic thin sea ice thickness: data description and validation in the Weddell Sea - Kaleschke, L.; Tian-Kunze, X.; Hendricks, S.; Ricker, R. (Earth Syst. Sci. Data, 2024)
Accurate satellite measurements of the thickness of Antarctic sea ice are urgently needed but pose a particular challenge. The Antarctic data presented here were produced using a method to derive the sea ice thickness from 1.4 GHz brightness temperatures previously developed for the Arctic, with only modified auxiliary data. The ability to observe the thickness of thin sea ice using this method is limited to cold conditions, meaning it is only reasonable during the freezing period, typically March to October. The Soil Moisture and Ocean Salinity (SMOS) level-3 sea ice thickness product contains estimates of the sea ice thickness and its uncertainty up to a thickness of about 1 m. The sea ice thickness is provided as a daily average on a polar stereographic projection grid with a sample resolution of 12.5 km, while the SMOS brightness temperature data used have a footprint size of about 35–40 km in diameter. Data from SMOS have been available since 2010, and the mission's operation has been extended to continue until at least the end of 2025. Here we compare two versions of the SMOS Antarctic sea ice thickness product which are based on different level-1 input data (v3.2 based on SMOS L1C v620 and v3.3 based on SMOS L1C 724). A validation is performed to generate a first baseline reference for future improvements of the retrieval algorithm and synergies with other sensors. Sea ice thickness measurements to validate the SMOS product are particularly rare in Antarctica, especially during the winter season and for the valid range of thicknesses. From the available validation measurements, we selected datasets from the Weddell Sea that have varying degrees of representativeness: Helicopter-based EM Bird (HEM), Surface and Under-Ice Trawl (SUIT), and stationary Upward-Looking Sonars (ULS). While the helicopter can measure hundreds of kilometres, SUIT's use is limited to distances of a few kilometres and thus only captures a small fraction of an SMOS footprint. Compared to SMOS, the ULS are point measurements and multi-year time series are necessary to enable a statistically representative comparison. Only four of the ULS moorings have a temporal overlap with SMOS in the year 2010. Based on selected averaged HEM flights and monthly ULS climatologies, we find a small mean difference (bias) of less than 10 cm and a root mean square deviation of about 20 cm with a correlation coefficient R > 0.9 for the valid sea ice thickness range between 0 and about 1 m. The SMOS sea ice thickness showed an underestimate of about 40 cm with respect to the less representative SUIT validation data in the marginal ice zone. Compared with sea ice thickness outside the valid range, we find that SMOS strongly underestimates the real values, which underlines the need for combination with other sensors such as altimeters. In summary, the overall validity of the SMOS sea ice thickness for thin sea ice up to a thickness of about 1 m has been demonstrated through validation with multiple datasets. To ensure the quality of the SMOS product, an independent regional sea ice extent index was used for control. We found that the new version, v3.3, is slightly improved in terms of completeness, indicating fewer missing data. However, it is worth noting that the general characteristics of both datasets are very similar, also with the same limitations.
Publisher: Copernicus Publications
Keywords: Sørishavet; Weddellhavet; havis; klimatologi; meteorologi; sjøis

Radar internal reflection horizons from multisystem data reflect ice dynamic and surface accumulation history along the Princess Ragnhild Coast, Dronning Maud Land, East Antarctica - Koch, Inka; Drews, Reinhard; Franke, Steven; Jansen, Daniela; Oraschewski, Falk Marius; Muhle, Leah Sophie; Višnjević, Vjeran; Matsuoka, Kenichi; Pattyn, Frank; Eisen, Olaf (Journal of Glaciology, 2024)
Ice shelves, which regulate ice flow from the Antarctic ice sheet towards the ocean, are shaped by spatiotemporal patterns of surface accumulation, surface/basal melt and ice dynamics. Therefore, an ice dynamic and accumulation history are imprinted in the internal ice stratigraphy, which can be imaged by radar in the form of internal reflection horizons (IRHs). Here, IRHs were derived from radar data combined across radar platforms (airborne and ground-based) in coastal eastern Dronning Maud Land (East Antarctica), comprising three ice rises and adjacent two ice shelves. To facilitate interpretation of dominant spatiotemporal patterns of processes shaping the local IRH geometry, traced IRHs are classified into three different types (laterally continuous, discontinuous or absent/IRH-free). Near-surface laterally continuous IRHs reveal local accumulation patterns, reflecting the mean easterly wind direction, and correlate with surface slopes. Areas of current and past increased ice flow and internal deformation are marked by discontinuous or IRH-free zones, and can inform about paleo ice-stream dynamics. The established IRH datasets extend continent-wide mapping efforts of IRHs to an important and climatically sensitive ice marginal region of Antarctica and are ready for integration into ice-flow models to improve predictions of Antarctic ice drainage.
Edition: 2023/12/12 Publisher: Cambridge University Press
Keywords: Dronning Maud Land; Sørishavet; glasiologi; isshelf; teknologi

Permafrost and ground-ice conditions in the Untersee Oasis, Queen Maud Land, East Antarctica - Lacelle, Denis; Verret, Marjolaine; Faucher, Benoit; Fisher, David; Gaudreau, Adam; Pellerin, André; Ecclestone, Miles; Andersen, Dale T. (Antarctic Science, 2024)
Knowledge of Antarctic permafrost is mainly derived from the Antarctic Peninsula and Victoria Land. This study examines the 2019–2023 temperature and humidity conditions, distribution and development of polygonal terrain and the origin of ground ice in soils of the Untersee Oasis. In this region, the surface offset (MAAT ≅ MAGST) and the thermal offset (MAGST ≤ TTIT) reflect the lack of vegetation, absence of persistent snow and a dry soil above the ice table. The mean annual vapour pressure at the ground surface is approximately ~2× higher than in the air but is ~0.67× lower than at the ice table. The size of polygons appears to be in equilibrium with the ice-table depth, and numerical modelling suggests that the depth of the ice table is in turn in equilibrium with the ground surface temperature and humidity. The ground ice at the ice table probably originates from the partial evaporation of snowmelt that infiltrated the dry soil column. As such, the depth of the ice table in this region is set by the water vapour density gradient between the ground surface and the ice-bearing ground, but it is recharged periodically by evaporating snowmelt.
Edition: 2024/12/17 Publisher: Cambridge University Press
Keywords: Dronning Maud Land; fysisk geografi; geologi; permafrost

Hydrography and circulation below Fimbulisen Ice Shelf, East Antarctica, from 14 years of moored observations - Lauber, Julius; Hattermann, Tore; de Steur, Laura; Darelius, Elin; Fransson, Agneta (Ocean Sci., 2024)
Future mass loss from the East Antarctic Ice Sheet represents a major uncertainty in projections of future sea level rise. Recent studies have highlighted the potential vulnerability of the East Antarctic Ice Sheet to atmospheric and oceanic changes, but long-term observations inside the ice shelf cavities are rare. Here, we present new insights from observations from three oceanic moorings below Fimbulisen Ice Shelf from 2009 to 2023. We examine the characteristics of intrusions of modified Warm Deep Water (mWDW) across a sill connecting the cavity to the open ocean and investigate seasonal variability of the circulation and water masses inside the cavity using an optimum multiparameter analysis. In autumn, the water below the 345 m deep central part of the ice shelf is composed of up to 30 % solar-heated, buoyant Antarctic Surface Water (ASW), separating colder Ice Shelf Water from the ice base and affecting the cavity circulation on seasonal timescales. At depth, the occurrence of mWDW is associated with the advection of cyclonic eddies across the sill into the cavity. These eddies reach up to the ice base. The warm intrusions are observed most often from January to March and from September to November, and traces of mWDW-derived meltwater close to the ice base imply an overturning of these warm intrusions inside the cavity. We suggest that this timing is set by both the offshore thermocline depth and the interactions of the Antarctic Slope Current with the ice shelf topography over the continental slope. Our findings provide a better understanding of the interplay between shallow inflows of ASW contributions and deep inflows of mWDW for basal melting at Fimbulisen Ice Shelf, with implications for the potential vulnerability of the ice shelf to climate change.
Publisher: Copernicus Publications
Keywords: Dronning Maud Land; hydrografi; isshelf; klimaendringer; klimatologi; oseanografi

ALBATROSS: Advancing Southern Ocean tide modelling with high resolution and enhanced bathymetry - Le Merle, Eva; Belot, Carole; Fouchet, Ergane; Cancet, Mathilde; Andersen, Ole Baltazar; Lyard, Florent; Moholdt, Geir; Tsamados, Michel; El Hajj, Mahmoud; Maton, Josephine; Benveniste, Jérôme; Restano, Marco (Polar Science, 2024)
The knowledge of bathymetry and ocean tides plays a pivotal role at the crossroads of various scientific fields, especially in the Polar regions. Its significance extends to ocean circulation modeling and understanding the coupled dynamical response of the ocean, sea-ice and ice-sheet systems. In the Southern Ocean, conventional satellite altimetry measurements are rare below the 66° parallel. Hydrodynamic models are thus useful tools to provide spatially continuous information about ocean tides. However, the accuracy of ocean tide models around the Antarctic continent is currently limited by the quality of bathymetry. Recent reprocessing of decade-long CryoSat-2 data has facilitated a new computation of bathymetry around Antarctica, bringing innovative information on bathymetry gradients. This, combined with new compilations of bathymetry, ice draft, coastline, and grounding line datasets in ice-shelf regions, allows improving models and knowledge of ocean tides in the Southern Ocean. We developed a new high-resolution tidal model that implements the improved bathymetry data and includes data assimilation of satellite-altimetry tidal retrievals computed from CryoSat-2, filling the gap between the 66°S-limited coverage of the TOPEX-Jason suite missions and the Antarctic coast. Comparisons with tidal estimates derived from tide gauge measurements showed very good consistencies with an RMSE of 3 cm.
Article number: 101124
Keywords: Sørishavet; batymetri; geofysikk

Phytoplankton bloom distribution and succession driven by sea-ice melt in the Kong Håkon VII Hav - Lenss, Megan; Moreau, Sebastien; Hattermann, Tore; Wiktor, Jozef; Różańska, Magdalena; Claeys, Philippe; Brion, Natacha; Chierici, Melissa; Fransson, Agneta; Campbell, Karley (Elementa: Science of the Anthropocene, 2024)
The existence of ice-edge phytoplankton blooms in the Southern Ocean is well described, yet direct observations of the mechanisms of phytoplankton bloom development following seasonal sea-ice melt remain scarce. This study constrains such responses using biological and biogeochemical datasets collected along a coastal-to-offshore transect that bisects the receding sea-ice zone in the Kong Håkon VII Hav (off the coast of Dronning Maud Land). We documented that the biogeochemical growing conditions for phytoplankton vary on a latitudinal gradient of sea-ice concentration, where increased sea-ice melting creates optimal conditions for growth with increased light availability and potentially increased iron supply. The zones of the study area with the least ice cover were associated with diatom dominance, the greatest chlorophyll a concentrations, net community production, and dissolved inorganic carbon drawdown, as well as lower sea surface fugacity of CO2. Together, these associations imply higher potential for an oceanic CO2 sink due, at least in part, to more advanced bloom phase and/or larger bloom magnitude stemming from a relatively longer period of light exposure, as compared to the more ice-covered zones in the study area. From stable oxygen isotope fractions, sea-ice meltwater fractions were highest in the open ocean zone and meteoric meltwater fractions were highest in the coastal and polynya zones, suggesting that potential iron sources may also change on a latitudinal gradient across the study area. Variable phytoplankton community compositions were related to changing sea-ice concentrations, with a typical species succession from sympagic flagellate species (Pyramimonas sp. and Phaeocystis antarctica) to pelagic diatoms (e.g., Dactyliosolen tenuijunctus) observed across the study area. These results fill a spatiotemporal gap in the Southern Ocean, as sea-ice melting plays a larger role in governing phytoplankton bloom dynamics in the future Southern Ocean due to changing sea-ice conditions caused by anthropogenic global warming.
Article Number: 00122
Keywords: Sørishavet; biogeokjemi; fytoplankton; havis; oseanografi; sjøis

Diversity, toxicity, and distribution of potentially toxic diatoms in Antarctic waters––With description of Pseudo-nitzschia meridionalis sp. nov. and P. glacialis sp. nov. - Lundholm, Nina; Christensen, Anneliese L.; Olesen, Anna K.J.; Beszteri, Bánk; Eggers, Sarah Lena; Krock, Bernd; Altenburger, Andreas (Harmful Algae, 2024)
Diatoms of the genus Pseudo-nitzschia, known for their potential toxicity, are integral to the phytoplankton community of the Southern Ocean, which surrounds Antarctica. Despite their ecological importance, the diversity and toxicity of Pseudo-nitzschia in this region remain underexplored. Globally, these diatoms are notorious for forming harmful algal blooms in temperate and tropical waters, causing significant impacts on marine life, ecosystems, and coastal economies. However, detailed information on the diversity, morphology, and toxicity of Pseudo-nitzschia species in Antarctic waters is limited, with molecular characterizations of these species being particularly scarce. During three research expeditions to the Southern Ocean, monoclonal strains of Pseudo-nitzschia were isolated and cultivated. Stored samples from a fourth expedition, the Brategg expedition, were used to complete the description of particularly P. turgidula. Through electron microscopy and molecular analysis, two novel species were identified—Pseudo-nitzschia meridionalis sp. nov. and Pseudo-nitzschia glacialis sp. nov.—alongside the previously described species P. subcurvata, P. turgiduloides, and P. turgidula. Toxin assays revealed no detectable levels of domoic acid in P. turgiduloides, P. turgidula, P. meridionalis sp. nov. and P. glacialis sp. nov. Conversely, P. subcurvata was reported in a related study to produce domoic acid and its isomer, isodomoic acid C. These findings emphasize the need for comprehensive research on the phytoplankton of Antarctic waters, which is currently a largely uncharted domain. With the looming threat of climate change, understanding the dynamics of potentially harmful algal populations in this region is becoming increasingly critical.
Article Number: 102724
Keywords: Rosshavet; Sørishavet; alger; biodiversitet; diatomeer; fytoplankton; marin biologi

Supraglacial lake evolution and its drivers in Dronning Maud Land, East Antarctica - Mahagaonkar, Anirudha; Moholdt, Geir; Glaude, Quentin; Schuler, Thomas Vikhamar (Journal of Glaciology, 2024)
Supraglacial lakes on Antarctic ice shelves can have far-reaching implications for ice-sheet stability, highlighting the need to understand their dynamics, controls and role in the ice-sheet mass budget. We combine a detailed satellite-based record of seasonal lake evolution in Dronning Maud Land with a high-resolution simulation from the regional climate model Modèle Atmosphérique Régional to identify drivers of lake variability between 2014 and 2021. Correlations between summer lake extents and climate parameters reveal complex relationships that vary both in space and time. Shortwave radiation contributes positively to the energy budget during summer melt seasons, but summers with enhanced longwave radiation are more prone to surface melting and ponding, which is further enhanced by advected heat from summer precipitation. In contrast, previous winter precipitation has a negative effect on summer lake extents, presumably by increasing albedo and pore space, delaying the accumulation of meltwater. Downslope katabatic or föhn winds promote ponding around the grounding zones of some ice shelves. At a larger scale, we find that summers during periods of negative southern annular mode are associated with increased ponding in Dronning Maud Land. The high variability in seasonal lake extents indicates that these ice shelves are highly sensitive to future warming or intensified extreme events.
Edition: 2024/10/02 Publisher: Cambridge University Press
Keywords: Dronning Maud Land; fjernmåling; glasiologi; innlandsis; isshelf; klimamodeller; subglasial innsjø

The case for a Framework for UnderStanding Ice-Ocean iNteractions (FUSION) in the Antarctic-Southern Ocean system - McCormack, Felicity S.; Cook, Sue; Goldberg, Daniel N.; Nakayama, Yoshihiro; Seroussi, Hélène; Nias, Isabel; An, Lu; Slater, Donald; Hattermann, Tore (Elementa: Science of the Anthropocene, 2024)
We are in a period of rapidly accelerating change across the Antarctic continent and Southern Ocean, with land ice loss leading to sea level rise and multiple other climate impacts. The ice-ocean interactions that dominate the current ice loss signal are a key underdeveloped area of knowledge. The paucity of direct and continuous observations leads to high uncertainty in the glaciological, oceanographic and atmospheric fields required to constrain ice-ocean interactions, and there is a lack of standardised protocols for reconciling observations across different platforms and technologies and modelled outputs. Funding to support observational campaigns is under increasing pressure, including for long-term, internationally coordinated monitoring plans for the Antarctic continent and Southern Ocean. In this Practice Bridge article, we outline research priorities highlighted by the international ice-ocean community and propose the development of a Framework for UnderStanding Ice-Ocean iNteractions (FUSION), using a combined observational-modelling approach, to address these issues. Finally, we propose an implementation plan for putting FUSION into practice by focusing first on an essential variable in ice-ocean interactions: ocean-driven ice shelf melt.
Article number: 00036
Keywords: Antarktis; Sørishavet; glasiologi; innlandsis; klimamodeller; klimatologi; oseanografi

Miocene ice sheet dynamics and sediment deposition in the central Ross Sea, Antarctica - McKay, Robert; Cockrell, Jay; Shevenell, Amelia E.; Laberg, Jan Sverre; Burns, Julianne; Patterson, Molly; Kim, Sunghan; Naish, Tim; Harwood, David; Levy, Richard; Marschalek, James; van de Flierdt, Tina; et al. (GSA Bulletin, 2024)
Drill cores from the Antarctic continental shelf are essential for directly constraining changes in past Antarctic Ice Sheet extent. Here, we provide a sedimentary facies analysis of drill cores from International Ocean Discovery Program (IODP) Site U1521 in the Ross Sea, which reveals a unique, detailed snapshot of Antarctic Ice Sheet evolution between ca. 18 Ma and 13 Ma. We identify distinct depositional packages, each of which contains facies successions that are reflective of past baseline shifts in the presence or absence of marine-terminating ice sheets on the outermost Ross Sea continental shelf. The oldest depositional package (>18 Ma) contains massive diamictites stacked through aggradation and deposited in a deep, actively subsiding basin that restricted marine ice sheet expansion on the outer continental shelf. A slowdown in tectonic subsidence after 17.8 Ma led to the deposition of progradational massive diamictites with thin mudstone beds/laminae, as several large marine-based ice sheet advances expanded onto the mid- to outer continental shelf between 17.8 Ma and 17.4 Ma. Between 17.2 Ma and 15.95 Ma, packages of interbedded diamictite and diatom-rich mudstone were deposited during a phase of highly variable Antarctic Ice Sheet extent and volume. This included periods of Antarctic Ice Sheet advance near the outer shelf during the early Miocene Climate Optimum (MCO)—despite this being a well-known period of peak global warmth between ca. 17.0 Ma and 14.6 Ma. Conversely, there were periods of peak warmth within the MCO during which diatom-rich mudstones with little to no ice-rafted debris were deposited, which indicates that the Antarctic Ice Sheet was greatly reduced in extent and had retreated to a smaller terrestrial-terminating ice sheet, most notably between 16.3 Ma and 15.95 Ma. Post-14.2 Ma, diamictites and diatomites contain unambiguous evidence of subglacial shearing in the core and provide the first direct, well-dated evidence of highly erosive marine ice sheets on the outermost continental shelf during the onset of the Middle Miocene Climate Transition (MMCT; 14.2–13.6 Ma). Although global climate forcings and feedbacks influenced Antarctic Ice Sheet advances and retreats during the MCO and MMCT, we propose that this response was nonlinear and heavily influenced by regional feedbacks related to the shoaling of the continental shelf due to reduced subsidence, sediment infilling, and local sea-level changes that directly influenced oceanic influences on melting at the Antarctic Ice Sheet margin. Although intervals of diatom-rich muds and diatomite indicating open-marine interglacial conditions still occurred during (and following) the MMCT, repeated advances of marine-based ice sheets since that time have resulted in widespread erosion and overdeepening in the inner Ross Sea, which has greatly enhanced sensitivity to marine ice sheet instability since 14.2 Ma.
Keywords: Rosshavet; Sørishavet; geologi; oseanografi; paleoklimatologi

KRILLSCAN: An automated open-source software for processing and analysis of echosounder data from the Antarctic krill fishery - Menze, Sebastian; Macaulay, Gavin J.; Zhang, Guosong; Lowther, Andrew D.; Krafft, Bjørn A. (Fisheries Management and Ecology, 2024)
Krillscan software was developed to automatically process echosounder data and achieve an accelerated and transparent analysis of backscatter data that allows calculation of target biomass. Herein, the fishery for Antarctic krill (Euphausia superba, Henceforth Krill) was used as a case study to develop the approach. Implementation of a sustainable management strategy for the krill fishery is complicated by a lack of regularly updated krill abundance data on spatiotemporal scales of the fishery. To increase krill biomass data availability, automatic echosounder data processing and swarm detection software was tested against traditional manual scrutinization with LSSS software and agreed with only minor offsets in estimated nautical area scattering coefficients. In addition to automatic processing and data transfer, Krillscan also has a graphical user interface to supervise automatic krill swarm detection. Echogram size can be compressed up to 100 times and raw data are processed faster than generated, thereby enabling near-real time analysis and data transfer. Compressed data can be transmitted online to allow fishing vessels to conduct surveys without having scientific personnel with special expertise on board.
Publisher: John Wiley & Sons, Ltd Article number: e12739
Keywords: Sørishavet; dataanalyse; ekkolodd; fiskerier; krill; plankton

Antarctic sonobuoy surveys for blue whales from 2006-2021 reveal contemporary distribution, changes over time, and paths to further our understanding of their distribution and biology - Miller, Brian S.; Andrews-Goff, Virginia; Barlow, Jay; Bell, Elanor; Calderan, Susannah; Double, Michael C.; Gedamke, Jason; Kelly, Nat; Laverick, Sarah; Leaper, Russell; Miller, Elanor J.; Reeve, Kym; et al. (Frontiers in Marine Science, 2024)
Seven passive acoustic surveys for marine mammal sounds were conducted by deploying sonobuoys along ship tracks during Antarctic voyages spanning years 2006-2021. These surveys included nearly 330° of longitude throughout Antarctic (south of 60°S) and sub-Antarctic (between 50-60°S) latitudes. Here, we summarise the presence of calls from critically endangered Antarctic blue whales (Balaenoptera musculus intermedia) detected on all seven of these surveys. We describe and compare the spatial distribution of detections of three different types of Antarctic blue whale calls: unit-A, Z-calls, and D-calls. Three sets of voyages partially overlapped spatially but in different years, providing three regions (Indian Sector, Dumont d’Urville Sea, Ross Sea) to investigate differences over time for these three different call types. The proportion of sonobuoys with calls present was significantly higher in the more recent years for seven of the 15 combinations of years, regions, and call type. The proportion of sonobuoys with calls present was significantly lower only for one of the 15 combinations (unit A in the Ross Sea between 2015 vs 2017), and not significantly different for the remaining seven pairwise comparisons. We discuss possible explanations for these observations including: differences in probability of detection, whale behaviour, whale distribution, and abundance. These explanations are not mutually exclusive and cannot yet be resolved without application of complex analytical methods and collection of additional data. Lastly, we discuss future work that could help clarify the contributions of each of these potential drivers of acoustic detection. We propose continued acoustic data collection, application of new analytical methods, and collection of other synergistic data from Antarctic blue whales on their feeding grounds as a basis for future work on this species. This could provide a cost effective and holistic means of monitoring their status after the effects of 20th century industrial whaling, as well as their responses to natural and anthropogenic changes to their main prey, Antarctic krill, and a changing climate.
Keywords: Sørishavet; hvaler; hydroakustikk; marin biologi

Antarctic Blue Ice Areas are hydrologically active, nutrient rich and contain microbially diverse cryoconite holes - Nowak, Aga; Isaksson, Elisabeth; Sunde, Øyvind; Elvevold, Synnøve; Sandven, Håkon; Moholdt, Geir; Hudson, Stephen R.; Urset, Anne; Edwards, Arwyn; Rassner, Sara M. E.; Pearce, David; Hamre, Børge; et al. (Communications Earth & Environment, 2024)
Antarctica is the coldest, windiest and least inhabited place on Earth. One of its most enigmatic regions is scoured by katabatic winds blue ice that covers 235,000 km2 of the Antarctic fringe. Here, we demonstrate that contrary to common belief, high-altitude inland blue ice areas are not dry, nor barren. Instead, they promote sub-surface melting that enables them to become “powerplants” for water, nutrients, carbon and major ions production. Mapping cryoconite holes at an unprecedented scale of 62 km2 also revealed a regionally significant resource of dissolved nitrogen, phosphorus (420 kg km−2), dissolved carbon (1323 kg km−2), and major ions (6672 kg km−2). We discovered that unlike on glaciers, creation of cryoconite holes and their chemical signature on the ice sheet is governed by ice movement and bedrock geology. Blue ice areas are near-surface hotspots of microbial life within cryoconite holes. Bacterial communities they support are unexpectedly diverse. We also show that near-surface aquifers can exist in blue ice outside cryoconite holes. Identifying blue ice areas as active ice sheet ecosystems will help us understand the role ice sheets play in Antarctic carbon cycle, development of near-surface drainage system, and will expand our perception of the limits of life.
Keywords: Antarktis; biogeokjemi; geografi; geologi; mikrobielle organismer; mikrobiologi

The Troll Observing Network (TONe): A contribution to improving observations in the data-sparse region of Dronning Maud Land, Antarctica - Pedersen, Christina A.; Njåstad, Birgit; Aas, Wenche; Darelius, Elin; Descamps, Sébastien; Flått, Stig; Hattermann, Tore; Hudson, Stephen R.; Miloch, Wojciech J.; Rykkje, Simen; Schweitzer, Johannes; Storvold, Rune; et al. (Polar Research, 2024)
Understanding how Antarctica is changing and how these changes influence the rest of the Earth is fundamental to the future robustness of human society. Strengthening our understanding of these changes and their implications requires dedicated, sustained and coordinated observations of key Antarctic indicators. The Troll Observing Network (TONe), now under development, is Norway’s contribution to the global need for sustained, coordinated, complementary and societally relevant observations from Antarctica. When fully implemented within the coming three years, TONe will be a state-of-the-art, multi-platform, multi-disciplinary observing network in data-sparse Dronning Maud Land. A critical part of the network is a data management system that will ensure broad, free access to all TONe data to the international research community.
Section: Perspectives
Keywords: Antarktis; Dronning Maud Land; Sørishavet; Troll forskningsstasjon; biologi; datainnsamling; forskningsinfrastruktur; fysikk; geologi; internasjonal samarbeid; kjemi

TerrANTALife 1.0 Biodiversity data checklist of known Antarctic terrestrial and freshwater life forms - Pertierra, Luis R.; Varliero, Gilda; Barbosa, Andrés; Biersma, Elisabeth M.; Convey, Peter; Chown, Steven L.; Cowan, Don; De Los Rios, Asunción; Escribano-Alvarez, Pablo; Fontaneto, Diego; Fraser, Ceridwen; Harris, Mathew; et al. (Biodiversity Data Journal, 2024)
Incomplete species inventories for Antarctica represent a key challenge for comprehensive ecological research and conservation in the region. Additionally, data required to understand population dynamics, rates of evolution, spatial ranges, functional traits, physiological tolerances and species interactions, all of which are fundamental to disentangle the different functional elements of Antarctic biodiversity, are mostly missing. However, much of the fauna, flora and microbiota in the emerged ice-free land of the continent have an uncertain presence and/or unresolved status, with entire biodiversity compendia of prokaryotic groups (e.g. bacteria) being missing. All the available biodiversity information requires consolidation, cross-validation, re-assessment and steady systematic inclusion in order to create a robust catalogue of biodiversity for the continent.We compiled, completed and revised eukaryotic species inventories present in terrestrial and freshwater ecosystems in Antarctica in a new living database: terrANTALife (version 1.0). The database includes the first integration in a compendium for many groups of eukaryotic microorganisms. We also introduce a first catalogue of amplicon sequence variants (ASVs) of prokaryotic biodiversity. Available compendia and literature to date were searched for Antarctic terrestrial and freshwater species, integrated, taxonomically harmonised and curated by experts to create comprehensive checklists of Antarctic organisms. The final inventories comprises 470 animal species (including vertebrates, free-living invertebrates and parasites), 306 plants (including all Viridiplantae: embryophytes and green algae), 997 fungal species and 434 protists (sensu lato). We also provide a first account for many groups of microorganisms, including non-lichenised fungi and multiple groups of eukaryotic unicellular species (Stramenophila, Alveolata and Rhizaria (SAR), Chromists and Amoeba), jointly referred to as "protists". In addition, we identify 1753 bacterial (obtained from 348117 ASVs) and 34 archaeal genera (from 1848 ASVs), as well as, at least, 14 virus families. We formulate a basic tree of life in Antarctica with the main lineages listed in the region and their “known-accepted-species” numbers.
Publisher: Pensoft Publishers
Keywords: Antarktis; Sørishavet; biodiversitet; database; fauna; flora; mikroorganismer

The Late Holocene deglaciation of James Ross Island, Antarctic Peninsula: OSL and 14C-dated multi-proxy sedimentary record from Monolith Lake - Roman, Matěj; Píšková, Anna; Sanderson, David C.W.; Cresswell, Alan J.; Bulínová, Marie; Pokorný, Matěj; Kavan, Jan; Jennings, Stephen J.A.; Lirio, Juan M.; Nedbalová, Linda; Sacherová, Veronika; Kopalová, Kateřina; et al. (Quaternary Science Reviews, 2024)
Lentic waterbodies provide terrestrial sedimentary archives of palaeoenvironmental change in deglaciated areas of the Antarctic. Knowledge of the long-term evolution of Antarctic palaeoenvironments affords important context to the current marked impacts of climate change in the Polar regions. Here, we present a comprehensively dated, multi-proxy sedimentary record from Monolith Lake, a distal proglacial lake in one of the largest ice-free areas of the Antarctic Peninsula region. Of the two defined sedimentary units in the cores studied, the lower Unit 1 exhibits a homogeneous composition and unvarying proxy data profiles, suggesting rapid clastic deposition under uniform, ice-proximal conditions with a sedimentation rate of ∼1 mm yr−1. 14C and optically stimulated luminescence (OSL) dating bracket the deposition interval to 1.5–2.5 ka BP, with the older age being more probable when compared to independent dating of the local deglaciation. The uppermost 11 cm of the record spans the last ∼2.2 ka BP (maximum age), suggesting a markedly decreased sedimentation rate of ∼0.05 mm yr−1 within Unit 2. Whereas Unit 1 shows only scarce evidence of biological activity, Unit 2 provides an uninterrupted record of diatoms (with 29 species recorded) and faunal subfossils, including the fairy shrimp Branchinecta gaini. Concentrations of organically-derived elements, as well as diatoms and faunal remains, are consistent, implying a gradual increase in lake productivity. These results provide an example of long-term Antarctic ‘greening’ (i.e. increasing organic productivity in terrestrial habitats) from a palaeolimnological perspective. The boundary between Units 1 and 2, therefore, marks the timing of local deglaciation at the final stages of a period of negative glacier mass balance, i.e. the Mid-Late Holocene Hypsithermal. Subsequent Neoglacial cooling is evidenced by the abated influence of glacial meltwater streams and turbidity decline linked to reduced glacier runoff, although most proxy responses mirror the natural proglacial lake ontogeny.
Keywords: Antarktis; diatomeer; geografi; geologi; holocene; innsjøer; paleolimnologi; paleoøkologi

Permafrost Hydrogeology of Taylor Valley, Antarctica: Insights From Deep Electrical Resistivity Tomography - Romano, Valentina; Fischanger, Federico; Wilson, Gary; Sciarra, Alessandra; Mazzini, Adriano; Mazzoli, Claudio; Florindo, Fabio; Tartarello, Maria Chiara; Ascani, Massimiliano; Anderson, Jacob; Worthington, Rachel; Hardie, Richard; et al. (Geophysical Research Letters, 2024)
Abstract Global warming has prompted globally widespread permafrost thawing, resulting in enhanced greenhouse gas release into the atmosphere. Studies conducted in the Northern Hemisphere reveal an alarming increase in permafrost thawing. However, similar data from Antarctica are scarce. We conducted a 2-D Deep Electrical Resistivity Tomography (DERT) survey in Taylor Valley, Antarctica, to image the distribution of permafrost, its thicknesses, lower boundaries, and hydrogeology. Results show resistive, discontinuous domains that we suggest represent permafrost units. We also find highly conductive layers (5?10 Ω·m), between 300?350 m and 600?650 m below ground level and a shallower (?50?100 m depth) conductive layer. The combined data set reveals a broad brine system in Taylor Valley, implying multi-tiered groundwater circulation: a shallow, localized system linked with surface water bodies and a separate deeper, regional circulation system. The arrangement of these brines across different levels, coupled with the uneven permafrost distribution, underscores potential interplay between the two systems.
Publisher: John Wiley & Sons, Ltd Article Number: e2023GL106912
Keywords: Antarktis; geologi; global oppvarming; hydrogeologi; klimaendringer; permafrost

Combined physical and biogeochemical assessment of mesoscale eddy parameterisations in ocean models: Eddy-induced advection at eddy-permitting resolutions - Ruan, X.; Couespel, D.; Lévy, M.; Li, J.; Mak, J.; Wang, Y. (Ocean Modelling, 2024)
Ocean general circulation models at the eddy-permitting regime are known to under-resolve the mesoscale eddy activity and associated eddy-mean interaction. Under-resolving the mesoscale eddy field has consequences for the resulting mean state, affecting the modelled ocean circulation and biogeochemical responses, and impacting the quality of climate projections. There is an ongoing debate on whether and how a parameterisation should be utilised in the eddy-permitting regime. Focusing on the Gent–McWilliams (GM) based parameterisations, it is known that, on the one hand, not utilising a parameterisation leads to insufficient eddy feedback and results in biases. On the other hand, utilising a parameterisation leads to double-counting of the eddy feedback, and introduces other biases. A recently proposed approach, known as splitting, modifies the way GM-based schemes are applied in eddy-permitting regimes, and has been demonstrated to be effective in an idealised Southern Ocean channel model. In this work, we evaluate whether the splitting approach can lead to improvements in the physical and biogeochemical responses in an idealised double gyre model. Compared with a high resolution mesoscale eddy resolving model truth, the use of the GM-based GEOMETRIC parameterisation together with splitting in the eddy-permitting regime leads to broad improvements in the control pre-industrial scenario and an idealised climate change scenario, over models with and models without the GM-based GEOMETRIC parameterisation active. While there are still some deficiencies, particularly in the subtropical region where the transport is too weak and may need momentum re-injection to reduce the biases, the present work provides further evidence in support of using the splitting procedure together with a GM-based parameterisation in ocean general circulation models at eddy-permitting resolutions.
Article number: 102396
Keywords: Sørishavet; havstrømmer; klimaendringer; oseanografi

Identifying prey capture events of a free-ranging marine predator using bio-logger data and deep learning - Schoombie, Stefan; Jeantet, Lorène; Chimienti, Marianna; Sutton, Grace J.; Pistorius, Pierre A.; Dufourq, Emmanuel; Lowther, Andrew D.; Oosthuizen, W. Chris (Royal Society Open Science, 2024)
Marine predators are integral to the functioning of marine ecosystems, and their consumption requirements should be integrated into ecosystem-based management policies. However, estimating prey consumption in diving marine predators requires innovative methods as predator-prey interactions are rarely observable. We developed a novel method, validated by animal-borne video, that uses tri-axial acceleration and depth data to quantify prey capture rates in chinstrap penguins (Pygoscelis antarctica). These penguins are important consumers of Antarctic krill (Euphausia superba), a commercially harvested crustacean central to the Southern Ocean food web. We collected a large data set (n = 41 individuals) comprising overlapping video, accelerometer and depth data from foraging penguins. Prey captures were manually identified in videos, and those observations were used in supervised training of two deep learning neural networks (convolutional neural network (CNN) and V-Net). Although the CNN and V-Net architectures and input data pipelines differed, both trained models were able to predict prey captures from new acceleration and depth data (linear regression slope of predictions against video-observed prey captures = 1.13; R2 approximate to 0.86). Our results illustrate that deep learning algorithms offer a means to process the large quantities of data generated by contemporary bio-logging sensors to robustly estimate prey capture events in diving marine predators.
Publisher: Royal Society
Keywords: Sørishavet; biologging; krill; marin biologi; marin zoologi; marine økosystemer; pingviner; plankton

Evolution of the Antarctic Ice Sheet Over the Next Three Centuries From an ISMIP6 Model Ensemble - Seroussi, Hélène; Pelle, Tyler; Lipscomb, William H.; Abe-Ouchi, Ayako; Albrecht, Torsten; Alvarez-Solas, Jorge; Asay-Davis, Xylar; Barre, Jean-Baptiste; Berends, Constantijn J.; Bernales, Jorge; Blasco, Javier; Caillet, Justine; et al. (Earth's Future, 2024)
Abstract The Ice Sheet Model Intercomparison Project for CMIP6 (ISMIP6) is the primary effort of CMIP6 (Coupled Model Intercomparison Project?Phase 6) focusing on ice sheets, designed to provide an ensemble of process-based projections of the ice-sheet contribution to sea-level rise over the twenty-first century. However, the behavior of the Antarctic Ice Sheet beyond 2100 remains largely unknown: several instability mechanisms can develop on longer time scales, potentially destabilizing large parts of Antarctica. Projections of Antarctic Ice Sheet evolution until 2300 are presented here, using an ensemble of 16 ice-flow models and forcing from global climate models. Under high-emission scenarios, the Antarctic sea-level contribution is limited to less than 30 cm sea-level equivalent (SLE) by 2100, but increases rapidly thereafter to reach up to 4.4 m SLE by 2300. Simulations including ice-shelf collapse lead to an additional 1.1 m SLE on average by 2300, and can reach 6.9 m SLE. Widespread retreat is observed on that timescale in most West Antarctic basins, leading to a collapse of large sectors of West Antarctica by 2300 in 30%?40% of the ensemble. While the onset date of retreat varies among ice models, the rate of upstream propagation is highly consistent once retreat begins. Calculations of sea-level contribution including water density corrections lead to an additional ?10% sea level and up to 50% for contributions accounting for bedrock uplift in response to ice loading. Overall, these results highlight large sea-level contributions from Antarctica and suggest that the choice of ice sheet model remains the leading source of uncertainty in multi-century projections.
Publisher: John Wiley & Sons, Ltd
Keywords: Antarktis; geovitenskap; glasiologi; innlandsis; klimamodeller

Observed Pathways and Interannual Variability of the Warm Inflow Onto the Continental Shelf in the Southern Weddell Sea - Steiger, N.; Sallée, J. B.; Darelius, Elin; Janout, Markus; Østerhus, Svein (Journal of Geophysical Research: Oceans, 2024)
Model projections suggest that the continental shelf in the southern Weddell Sea may experience a shift from today's near-freezing temperature to a much warmer state, where warm water floods the shelf and basal melt rates beneath the Filchner Ronne Ice Shelf increase dramatically. Today, the Filchner Trough serves as a conduit for the southward flow of Warm Deep Water (WDW) during summer and, thus, requires continuous monitoring of its hydrographic conditions. An extensive network of moorings was installed at key sites along the inflow pathway from 2017 to 2021, to expand on existing mooring records starting in 2014. The moorings complemented with under-ice profiling floats reveal two inflow pathways, where WDW enters along the eastern flank of the Filchner Trough as well as through a smaller trough east of there. Within the observed period, 2017 and 2018 feature anomalously warm inflows. The inflow is regulated by the heaving of isopycnals over the continental slope, and the southward propagation toward Filchner Ice Shelf is two times faster during these warm years. Furthermore, the warm years coincide with low summer sea ice concentration, which enhances surface stratification through increased freshwater input and modifies sea ice-ocean stresses that both act to lift the warm water layer and increase the temperatures on the continental shelf. Finally, the recent record low sea ice conditions around the Antarctic emphasize the importance of our findings and raise concerns regarding a potentially increasing presence of WDW on the southern Weddell Sea shelf.
Publisher: John Wiley & Sons, Ltd
Keywords: Sørishavet; Weddellhavet; havis; isshelf; oseanografi; sjøis

The Southern Ocean sea-ice ecosystem is important to humans - Steiner, Nadja; Eronen-Rasimus, Eeva; Falardeau, Marianne; Moreau, Sebastien; Steiner, Finn (Frontiers for young minds, 2024)
Did you know that ecosystems support the wellbeing of humans by simply existing? An ecosystem describes the living things in an area, their interactions, and their environment. The ways that ecosystems benefit the wellbeing of humans are called ecosystem services. There are several types of ecosystem services: supporting (they support animals and their homes), provisioning (they provide food and other materials), cultural (they support our hobbies and cultural activities, such as tourism and arts), or regulating (they regulate our climate, for example by taking up carbon dioxide). Understanding the importance of an ecosystem through its ecosystem services helps guide decisions regarding the environment, such as how much fishing or ship traffic should be allowed in an area, or if an area or species should be protected. In this article, we describe the specific ecosystem services of the sea ice and Southern Ocean around Antarctica.
Article number : 1046644
Keywords: Sørishavet; havis; marine økosystemer; populærvitenskap; sjøis; økosystemer

Suppression of Mesoscale Eddy Mixing by Topographic PV Gradients - Sterl, Miriam F.; LaCasce, Joseph H.; Groeskamp, Sjoerd; Nummelin, Aleksi; Isachsen, Pål E.; Baatsen, Michiel L. J. (Journal of Physical Oceanography, 2024)
Oceanic mesoscale eddy mixing plays a crucial role in Earth’s climate system by redistributing heat, salt, and carbon. For many ocean and climate models, mesoscale eddies still need to be parameterized. This is often done via an eddy diffusivity K , which sets the strength of turbulent downgradient tracer fluxes. A well-known effect is the modulation of K in the presence of background potential vorticity (PV) gradients, which suppresses cross-PV gradient mixing. Topographic slopes can induce such suppression through topographic PV gradients. However, this effect has received little attention, and topographic effects are often not included in parameterizations for K . In this study, we show that it is possible to describe the effect of topography on K analytically in a barotropic framework, using a simple stochastic representation of eddy–eddy interactions. We obtain an analytical expression for the depth-averaged K as a function of the bottom slope, which we validate against diagnosed eddy diffusivities from a numerical model. The obtained analytical expression can be generalized to any constant barotropic PV gradient. Moreover, the expression is consistent with empirical parameterizations for eddy diffusivity over topography from previous studies and provides a physical rationalization for these parameterizations. The new expression helps to understand how eddy diffusivities vary across the ocean, and thus how mesoscale eddies impact ocean mixing processes.
Place: Boston MA, USA Publisher: American Meteorological Society
Keywords: Sørishavet; klimamodeller; oseanografi

Geographical distribution of close kin in southern right whales on feeding grounds - Takahashi, Megumi; Førland, Brage; Pastene, Luis A.; Skaug, Hans J. (PLOS ONE, 2024)
This study investigated the close kinship structure of southern right whales on feeding grounds during austral summer seasons. The study was based on biopsy samples of 171 individual whales, which were genotyped with 14 microsatellite DNA loci. Kinship was investigated by using the LOD (Log Odds) score, a relatedness index for a pair of genotypes. Based on a cut-off point of LODPO > 6, which was chosen to balance false positives and negatives, a total of 28 dyads were inferred. Among these, 25 were classified as parent-offspring pairs. Additional genetic (mitochondrial DNA haplotypes) and biological (estimated body length, sex) data were used to provide additional information on the inferred close kin pairs. The elapsed time between sampling varied from 0 (close kin detected in the same austral summer season) to 17 years. All the kin pairs occurred within the Antarctic Indo sector (85°-135°E) and no pair occurred between whales within and outside of this sector. Six pairs were between individuals in high (Antarctic) and lower latitudes. Results of the present analysis on kinship are consistent with the views that whales in the Indo sector of the Antarctic are related with the breeding ground in Southwest Australia, and that whales from this population can occupy different feeding grounds. The present study has the potential to contribute to the conservation of the southern right whales through the monitoring of important population parameters such as population sizes and growth rate, in addition to assist the interpretation of stock structure derived from standard population genetic analyses.
Publisher: Public Library of Science
Keywords: Sørishavet; genetikk; hvaler; marin biologi; zoogeografi

Eccentricity pacing and rapid termination of the early Antarctic ice ages - van Peer, Tim E.; Liebrand, Diederik; Taylor, Victoria E.; Brzelinski, Swaantje; Wolf, Iris; Bornemann, André; Friedrich, Oliver; Bohaty, Steven M.; Xuan, Chuang; Lippert, Peter C.; Wilson, Paul A. (Nature Communications, 2024)
Earth’s obliquity and eccentricity cycles are strongly imprinted on Earth’s climate and widely used to measure geological time. However, the record of these imprints on the oxygen isotope record in deep-sea benthic foraminifera (δ18Ob) shows contradictory signals that violate isotopic principles and cause controversy over climate-ice sheet interactions. Here, we present a δ18Ob record of high fidelity from International Ocean Drilling Program (IODP) Site U1406 in the northwest Atlantic Ocean. We compare our record to other records for the time interval between 28 and 20 million years ago, when Earth was warmer than today, and only Antarctic ice sheets existed. The imprint of eccentricity on δ18Ob is remarkably consistent globally whereas the obliquity signal is inconsistent between sites, indicating that eccentricity was the primary pacemaker of land ice volume. The larger eccentricity-paced early Antarctic ice ages were vulnerable to rapid termination. These findings imply that the self-stabilizing hysteresis effects of large land-based early Antarctic ice sheets were strong enough to maintain ice growth despite consecutive insolation-induced polar warming episodes. However, rapid ice age terminations indicate that resistance to melting was weaker than simulated by numerical models and regularly overpowered, sometimes abruptly.
Article number: 10600
Keywords: Antarktis; geologi; paleoklimatologi; paleoseanografi

Swirls and scoops: Ice base melt revealed by multibeam imagery of an Antarctic ice shelf - Wåhlin, Anna; Alley, Karen E.; Begeman, Carolyn; Hegrenæs, Øyvind; Yuan, Xiaohan; Graham, Alastair G. C.; Hogan, Kelly; Davis, Peter E. D.; Dotto, Tiago S.; Eayrs, Clare; Hall, Robert A.; Holland, David M.; et al. (Science Advances, 2024)
Knowledge gaps about how the ocean melts Antarctica's ice shelves, borne from a lack of observations, lead to large uncertainties in sea level predictions. Using high-resolution maps of the underside of Dotson Ice Shelf, West Antarctica, we reveal the imprint that ice shelf basal melting leaves on the ice. Convection and intermittent warm water intrusions form widespread terraced features through slow melting in quiescent areas, while shear-driven turbulence rapidly melts smooth, eroded topographies in outflow areas, as well as enigmatic teardrop-shaped indentations that result from boundary-layer flow rotation. Full-thickness ice fractures, with bases modified by basal melting and convective processes, are observed throughout the area. This new wealth of processes, all active under a single ice shelf, must be considered to accurately predict future Antarctic ice shelf melt. A unique dataset from beneath an Antarctic ice shelf shows a varied icescape created by differential melt mechanisms.
Publisher: American Association for the Advancement of Science Article number: eadn9188
Keywords: Sørishavet; brehylle; havstrømmer; isbrem; oseanografi

A satellite-derived baseline of photosynthetic life across Antarctica - Walshaw, Charlotte V.; Gray, Andrew; Fretwell, Peter T.; Convey, Peter; Davey, Matthew P.; Johnson, Joanne S.; Colesie, Claudia (Nature Geoscience, 2024)
Terrestrial vegetation communities across Antarctica are characteristically sparse, presenting a challenge for mapping their occurrence using remote sensing at the continent scale. At present there is no continent-wide baseline record of Antarctic vegetation, and large-scale area estimates remain unquantified. With local vegetation distribution shifts now apparent and further predicted in response to environmental change across Antarctica, it is critical to establish a baseline to document these changes. Here we present a 10 m-resolution map of photosynthetic life in terrestrial and cryospheric habitats across the entire Antarctic continent, maritime archipelagos and islands south of 60° S. Using Sentinel-2 imagery (2017–2023) and spectral indices, we detected terrestrial green vegetation (vascular plants, bryophytes, green algae) and lichens across ice-free areas, and cryospheric green snow algae across coastal snowpacks. The detected vegetation occupies a total area of 44.2 km2, with over half contained in the South Shetland Islands, altogether contributing just 0.12% of the total ice-free area included in the analysis. Due to methodological constraints, dark-coloured lichens and cyanobacterial mats were excluded from the study. This vegetation map improves the geospatial data available for vegetation across Antarctica, and provides a tool for future conservation planning and large-scale biogeographic assessments.
Keywords: Antarktis; alger; biodiversitet; botanikk; lav; planter

Highly stratified mid-Pliocene Southern Ocean in PlioMIP2 - Weiffenbach, J. E.; Dijkstra, H. A.; von der Heydt, A. S.; Abe-Ouchi, A.; Chan, W.-L.; Chandan, D.; Feng, R.; Haywood, A. M.; Hunter, S. J.; Li, X.; Otto-Bliesner, B. L.; Peltier, W. R.; et al. (Clim. Past, 2024)
During the mid-Pliocene warm period (mPWP; 3.264–3.025 Ma), atmospheric CO2 concentrations were approximately 400 ppm, and the Antarctic Ice Sheet was substantially reduced compared to today. Antarctica is surrounded by the Southern Ocean, which plays a crucial role in the global oceanic circulation and climate regulation. Using results from the Pliocene Model Intercomparison Project (PlioMIP2), we investigate Southern Ocean conditions during the mPWP with respect to the pre-industrial period. We find that the mean sea surface temperature (SST) warming in the Southern Ocean is 2.8 °C, while global mean SST warming is 2.4 °C. The enhanced warming is strongly tied to a dramatic decrease in sea ice cover over the mPWP Southern Ocean. We also see a freshening of the ocean (sub)surface, driven by an increase in precipitation over the Southern Ocean and Antarctica. The warmer and fresher surface leads to a highly stratified Southern Ocean that can be related to weakening of the deep abyssal overturning circulation. Sensitivity simulations show that the decrease in sea ice cover and enhanced warming is largely a consequence of the reduction in the Antarctic Ice Sheet. In addition, the mPWP geographic boundary conditions are responsible for approximately half of the increase in mPWP SST warming, sea ice loss, precipitation, and stratification increase over the Southern Ocean. From these results, we conclude that a strongly reduced Antarctic Ice Sheet during the mPWP has a substantial influence on the state of the Southern Ocean and exacerbates the changes that are induced by a higher CO2 concentration alone. This is relevant for the long-term future of the Southern Ocean, as we expect melting of the western Antarctic Ice Sheet in the future, an effect that is not currently taken into account in future projections by Coupled Model Intercomparison Project (CMIP) ensembles.
Publisher: Copernicus Publications
Keywords: Sørishavet; geologi; klimamodeller; klimatologi; oseanografi; paleoklimatologi

Gross Primary Production of Antarctic Landfast Sea Ice: A Model-Based Estimate - Wongpan, Pat; Meiners, K. M.; Vancoppenolle, M.; Fraser, A. D.; Moreau, Sebastien; Saenz, B. T.; Swadling, K. M.; Lannuzel, D. (Journal of Geophysical Research: Oceans, 2024)
Much of the Antarctic coast is covered by seasonal landfast sea ice (fast ice), which serves as an important habitat for ice algae. Fast-ice algae provide a key early season food source for pelagic and benthic food webs, and contribute to biogeochemical cycling in Antarctic coastal ecosystems. Summertime fast ice is undergoing a decline, leading to more seasonal fast ice with unknown impacts on interconnected Earth system processes. Our understanding of the spatiotemporal variability of Antarctic fast ice, and its impact on polar ecosystems is currently limited. Evaluating the overall productivity of fast-ice algae has historically been hampered by limitations in observations and models. By linking new fast-ice extent maps with a one-dimensional sea-ice biogeochemical model, we provide the first estimate of the spatio-seasonal variability of Antarctic fast-ice algal gross primary production (GPP) and its annual primary production on a circum-Antarctic scale. Experiments conducted for the 2005?2006 season provide a mean fast ice-algal production estimate of 2.8 Tg C/y. This estimate represents about 12% of overall Southern Ocean sea-ice algae production (estimated in a previous study), with the mean fast-ice algal production per area being 3.3 times higher than that of pack ice. Our Antarctic fast-ice GPP estimates are probably underestimated in the Ross Sea and Weddell Sea sectors because the sub-ice platelet layer habitats and their high biomass are not considered.
Publisher: John Wiley & Sons, Ltd Article Number: e2024JC021348
Keywords: Sørishavet; alger; biogeokjemi; geofysikk; havis; oseanografi; sjøis

Re-evaluating winter carbon sink in Southern Ocean by recovering MODIS-Aqua chlorophyll-a product at high solar zenith angles - Zhang, Ke; Zhang, Zhaoru; He, Jianfeng; Smith, Walker O.; Liu, Na; Le, Chengfeng (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)
Satellite ocean color observations are extensively utilized in global carbon sink evaluation. However, the valid coverage of chlorophyll-a concentration (Chla, mg m−3) measurements from these observations is severely limited during autumn and winter in high latitude oceans. The high solar zenith angle (SZA) stands as one of the primary contributors to the reduced quality of Chla products in the high-latitude Southern Ocean during these seasons. This study addresses this challenge by employing a random forest-based regression ensemble (RFRE) method to enhance the quality of Moderate Resolution Imaging Spectroradiometer (MODIS) Chla products affected by high SZA conditions. The RFRE model incorporates the color index (CI), band-ratio index (R), SZA, sensor zenith angle (senz), and Rayleigh-corrected reflectance at 869 nm (Rrc(869)) as predictors. The results indicate that the RFRE model significantly increased the MODIS observed Chla coverage (1.03 to 3.24 times) in high-latitude Southern Ocean regions to the quality of standard Chla products. By applying the recovered Chla to re-evaluate the carbon sink in South Ocean, results showed that the Southern Ocean’s ability to absorb carbon dioxide (CO2) in winter has been underestimated (5.9–18.6 Tg C year−1) in previous assessments. This study underscores the significance of improving the Chla products for a more accurate estimation of winter carbon sink in the Southern Ocean.
Keywords: Sørishavet; fjernmåling; fotogrammetri; karbon syklus; karbondioksid; oseanografi

Dynamic Response to Ice Shelf Basal Meltwater Relevant to Explain Observed Sea Ice Trends Near the Antarctic Continental Shelf - Huneke, Wilma G. C.; Hobbs, William R.; Klocker, Andreas; Naughten, Kaitlin A. (Geophysical Research Letters, 2023)
Abstract Observed Antarctic sea ice trends up to 2015 have a distinct regional and seasonal pattern, with a loss during austral summer and autumn in the Bellingshausen and Amundsen Seas, and a year-round increase in the Ross Sea. Global climate models generally failed to reproduce the magnitude of sea ice trends implying that the models miss relevant mechanisms. One possible mechanism is basal meltwater, which is generally not included in the current generation of climate models. Previous work on the effects of meltwater on sea ice has focused on thermodynamic processes. However, local freshening also leads to dynamic changes, affecting ocean currents through geostrophic balance. Using a coupled ocean/sea-ice/ice-shelf model, we demonstrate that basal melting can intensify coastal currents in West Antarctica and the westward transport of sea ice. This change in transport results in sea ice anomalies consistent with observations, and may explain the disparity between climate models and observations.
Publisher: John Wiley & Sons, Ltd
Keywords: Sørishavet; havis; oseanografi

Deep Convection as the Key to the Transition From Eocene to Modern Antarctic Circumpolar Current - Xing, Qianjiang; Klocker, Andreas; Munday, David; Whittaker, Joanne (Geophysical Research Letters, 2023)
From the Eocene (?50 million years ago) to today, Southern Ocean circulation has evolved from the existence of two ocean gyres to the dominance of the Antarctic Circumpolar Current (ACC). It has generally been thought that the opening of Southern Ocean gateways in the late Eocene, in addition to the alignment of westerly winds with these gateways or the presence of the Antarctic ice sheet, was a sufficient requirement for the transition to an ACC of similar strength to its modern equivalent. Nevertheless, models representing these changes produce a much weaker ACC. Here we show, using an eddying ocean model, that the missing ingredient in the transition to a modern ACC is deep convection around the Antarctic continent. This deep convection is caused by cold temperatures and high salinities due to sea-ice production around the Antarctic continent, leading to both the formation of Antarctic Bottom Water and a modern-strength ACC.
Publisher: John Wiley & Sons, Ltd
Keywords: Sørishavet; oseanografi

Macronutrient biogeochemistry in Antarctic land-fast sea ice: Insights from a circumpolar data compilation - Henley, Sian F.; Cozzi, Stefano; Fripiat, François; Lannuzel, Delphine; Nomura, Daiki; Thomas, David N.; Meiners, Klaus M.; Vancoppenolle, Martin; Arrigo, Kevin; Stefels, Jacqueline; van Leeuwe, Maria; Moreau, Sebastien; et al. (Marine Chemistry, 2023)
Antarctic sea ice plays an important role in Southern Ocean biogeochemistry and mediating Earth's climate system. Yet our understanding of biogeochemical cycling in sea ice is limited by the availability of relevant data over sufficient temporal and spatial scales. Here we present a new publicly available compilation of macronutrient concentration data from Antarctic land-fast sea ice, covering the full seasonal cycle using datasets from around Antarctica, as well as a smaller dataset of macronutrient concentrations in adjacent seawater. We show a strong seasonal cycle whereby nutrient concentrations are high during autumn and winter, due to supply from underlying surface waters, and then are utilised in spring and summer by mixed ice algal communities consisting of diatoms and non-siliceous species. Our data indicate some degree of nutrient limitation of ice algal primary production, with silicon limitation likely being most prevalent, although uncertainties remain around the affinities of sea-ice algae for each nutrient. Remineralisation of organic matter and nutrient recycling drive substantial accumulations of inorganic nitrogen, phosphate and to a lesser extent silicic acid in some ice cores to concentrations far in excess of those in surface waters. Nutrient supply to fast ice is enhanced by brine convection, platelet ice accumulation and incorporation into the ice matrix, and under-ice tidal currents, whilst nutrient adsorption to sea-ice surfaces, formation of biofilms, and abiotic mineral precipitation and dissolution can also influence fast-ice nutrient cycling. Concentrations of nitrate, ammonium and silicic acid were generally higher in fast ice than reported for Antarctic pack ice, and this may support the typically observed higher algal biomass in fast-ice environments.
Keywords: Sørishavet; alger; havis; kjemi; marin biologi

Quantifying circumpolar summer habitat for Antarctic krill and Ice krill, two key species of the Antarctic marine ecosystem - Merkel, B; Trathan, P; Thorpe, S; Murphy, E J; Pehlke, H; Teschke, K; Griffith, G P (ICES Journal of Marine Science, 2023)
Antarctic krill (Euphausia superba) and Ice krill (Euphausia crystallorophias) are key species within Southern Ocean marine ecosystems. Given their importance in regional food webs, coupled with the uncertain impacts of climate change, the on-going recovery of krill-eating marine mammals, and the expanding commercial fishery for Antarctic krill, there is an increasing need to improve current estimates of their circumpolar habitat distribution. Here, we provide an estimate of the austral summer circumpolar habitat distribution of both species using an ensemble of habitat models and updated environmental covariates. Our models were able to resolve the segregated habitats of both species. We find that extensive potential habitat for Antarctic krill is mainly situated in the open ocean and concentrated in the Atlantic sector of the Southern Ocean, while Ice krill habitat was concentrated more evenly around the continent, largely over the continental shelf. Ice krill habitat was mainly predicted by surface oxygen concentration and water column temperature, while Antarctic krill was additionally characterized by mixed layer depth, distance to the continental shelf edge, and surface salinity. Our results further improve understanding about these key species, helping inform sustainable circumpolar management practices.
Keywords: Sørishavet; krill; marin biologi

Perspectives on the economic and political history of the Ross Sea - Basberg, Bjørn L.; Lintott, Bryan (The Polar Journal, 2023)
The paper analyses the economic and political history of the Ross Sea, where exploration, science, commercial exploitation, politics and adventure became highly interlinked and interwoven. Expedition accounts and the extensive literature on Antarctic history and politics inform the contextual aspects. The archives of the Norwegian whaling company A/S Rosshavet, established in 1923, and the United States of America and New Zealand archival material from the 1950s are key sources. From the first whaling season onwards, the impact of Antarctic whaling, and later scientific bases, highlights and illustrates the tensions between Antarctic commerce, territorial claims and international politics.
Publisher: Routledge
Keywords: Sørishavet; historie; hvalfangst; politikk; økonomi

Slowdown of Antarctic Bottom Water export driven by climatic wind and sea-ice changes - Zhou, Shenjie; Meijers, Andrew J. S.; Meredith, Michael P.; Abrahamsen, E. Povl; Holland, Paul R.; Silvano, Alessandro; Sallée, Jean-Baptiste; Østerhus, Svein (Nature Climate Change, 2023)
Antarctic Bottom Water (AABW) is pivotal for oceanic heat and carbon sequestrations on multidecadal to millennial timescales. The Weddell Sea contributes nearly a half of global AABW through Weddell Sea Deep Water and denser underlying Weddell Sea Bottom Water that form on the continental shelves via sea-ice production. Here we report an observed 30% reduction of Weddell Sea Bottom Water volume since 1992, with the largest decrease in the densest classes. This is probably driven by a multidecadal reduction in dense-water production over southern continental shelf associated with a >40% decline in the sea-ice formation rate. The ice production decrease is driven by northerly wind trend, related to a phase transition of the Interdecadal Pacific Oscillation since the early 1990s, superposed by Amundsen Sea Low intrinsic variability. These results reveal key influences on exported AABW to the Atlantic abyss and their sensitivity to large-scale, multidecadal climate variability.
Keywords: Sørishavet; havis; oseanografi

Monitoring persistent organic chemicals in Antarctica in support of global chemical policy: a horizon scan of priority actions and challenges - Bengtson Nash, Susan; Bohlin-Nizzetto, Pernilla; Galban-Malagon, Cristobal; Corsolini, Simonetta; Cincinelli, Alessandra; Lohmann, Rainer (The Lancet Planetary Health, 2023)
Summary Global production and emission of chemicals exceeds societal capacities for assessment and monitoring. This situation calls for improved chemical regulatory policy frameworks and increased support for expedited decision making within existing frameworks. The polar regions of the Earth represent unique sentinel areas for the study of global chemical behaviour, and data arising from these areas can strengthen existing policy frameworks. However, chemical pollution research and monitoring in the Antarctic is underdeveloped, with geopolitical complexities and the absence of legal recognition of international chemical policy serving to neutralise progress made in other global regions. This Personal View represents a horizon scan by the action group Input Pathways of Persistent Organic Pollutants to Antarctica, of the Scientific Committee for Antarctic Research. Four priority research and research facilitation gaps are outlined, with recommendations for Antarctica Treaty parties for strategic action against these priorities.
Keywords: Antarktis; Sørishavet; forskning; forvaltning; helse; miljøgifter

Wind-driven upwelling of iron sustains dense blooms and food webs in the eastern Weddell Gyre - Moreau, Sebastien; Hattermann, Tore; de Steur, Laura; Kauko, Hanna M.; Ahonen, Heidi; Ardelan, Murat; Assmy, Philipp; Chierici, Melissa; Descamps, Sebastien; Dinter, Tilman; Falkenhaug, Tone; Fransson, Agneta; et al. (Nature Communications, 2023)
The Southern Ocean is a major sink of anthropogenic CO2 and an important foraging area for top trophic level consumers. However, iron limitation sets an upper limit to primary productivity. Here we report on a considerably dense late summer phytoplankton bloom spanning 9000 km2 in the open ocean of the eastern Weddell Gyre. Over its 2.5 months duration, the bloom accumulated up to 20 g C m−2 of organic matter, which is unusually high for Southern Ocean open waters. We show that, over 1997–2019, this open ocean bloom was likely driven by anomalies in easterly winds that push sea ice southwards and favor the upwelling of Warm Deep Water enriched in hydrothermal iron and, possibly, other iron sources. This recurring open ocean bloom likely facilitates enhanced carbon export and sustains high standing stocks of Antarctic krill, supporting feeding hot spots for marine birds and baleen whales.
Keywords: Sørishavet; kjemi; marin biologi; oseanografi; plankton

Observational evidence for on-shelf heat transport driven by dense water export in the Weddell Sea - Darelius, Elin; Daae, Kjersti; Dundas, Vår; Fer, Ilker; Hellmer, Hartmut H.; Janout, Markus; Nicholls, Keith W.; Sallée, Jean-Baptiste; Østerhus, Svein (Nature Communications, 2023)
The transport of oceanic heat towards the Antarctic continental margin is central to the mass balance of the Antarctic Ice Sheet. Recent modeling efforts challenge our view on where and how the on-shelf heat flux occurs, suggesting that it is largest where dense shelf waters cascade down the continental slope. Here we provide observational evidence supporting this claim. Using records from moored instruments, we link the downslope flow of dense water from the Filchner overflow to upslope and on-shelf flow of warm water.
Keywords: Sørishavet; oseanografi

Physical and Biogeochemical Properties of Rotten East Antarctic Summer Sea Ice - Corkill, M.; Moreau, S.; Janssens, J.; Fraser, A. D.; Heil, P.; Tison, J.-L.; Cougnon, E. A.; Genovese, C.; Kimura, N.; Meiners, K. M.; Wongpan, P.; Lannuzel, D. (Journal of Geophysical Research: Oceans, 2023)
Sea ice forms a barrier to the exchange of energy, gases, moisture and particles between the ocean and atmosphere around Antarctica. Ice temperature, salinity and the composition of ice crystals determine whether a particular slab of sea ice is habitable for microorganisms and permeable to exchanges between the ocean and atmosphere, allowing, for example, carbon dioxide (CO2) from the atmosphere to be absorbed or outgassed by the ocean. Spring sea ice can have high concentrations of algae and absorb atmospheric CO2. In the summer of 2016?2017 off East Antarctica, we found decayed and porous granular ice layers in the interior of the ice column, which showed high algal pigment concentrations. The maximum chlorophyll a observed in the interior of the ice column was 67.7 ?g/L in a 24% porous granular ice layer between 0.8 and 0.9 m depth in 1.7 m thick ice, compared to an overall mean sea-ice chlorophyll a (± one standard deviation) of 13.5 ± 21.8 ?g/L. We also found extensive surface melting, with instances of snow meltwater apparently percolating through the ice, as well as impermeable superimposed ice layers that had refrozen along with melt ponds on top of the ice. With future warming, the structures we describe here could occur earlier and/or become more persistent, meaning that sea ice would be more often characterized by patchy permeability and interior ice algal accumulations.
Publisher: John Wiley & Sons, Ltd
Keywords: Sørishavet; biogeokjemi; havis; isfjell

A topographic hinge-zone divides coastal and inland ice dynamic regimes in East Antarctica - Andersen, Jane L.; Newall, Jennifer C.; Fredin, Ola; Glasser, Neil F.; Lifton, Nathaniel A.; Stuart, Finlay M.; Fabel, Derek; Caffee, Marc; Pedersen, Vivi K.; Koester, Alexandria J.; Suganuma, Yusuke; Harbor, Jonathan M.; et al. (Communications Earth & Environment, 2023)
The impact of late Cenozoic climate on the East Antarctic Ice Sheet is uncertain. Poorly constrained patterns of relative ice thinning and thickening impair the reconstruction of past ice-sheet dynamics and global sea-level budgets. Here we quantify long-term ice cover of mountains protruding the ice-sheet surface in western Dronning Maud Land, using cosmogenic Chlorine-36, Aluminium-26, Beryllium-10, and Neon-21 from bedrock in an inverse modeling approach. We find that near-coastal sites experienced ice burial up to 75–97% of time since 1 Ma, while interior sites only experienced brief periods of ice burial, generally <20% of time since 1 Ma. Based on these results, we suggest that the escarpment in Dronning Maud Land acts as a hinge-zone, where ice-dynamic changes driven by grounding-line migration are attenuated inland from the coastal portions of the East Antarctic Ice Sheet, and where precipitation-controlled ice-thickness variations on the polar plateau taper off towards the coast.
Keywords: Dronning Maud Land; glasiologi

Regional polar warming linked to poleward moisture transport variability - Bintanja, Richard; Graversen, Rune Grand; Kolbe, Marlen (Environmental Research: Climate, 2023)
Polar warming, ice melt and strong precipitation events are strongly affected by episodic poleward advection of warm and moist air (Woods and Caballero 2016 J. Clim. 29 4473–85; Wille et al 2019 Nat. Geosci. 12 911–6), which, in turn, is linked to variability in poleward moisture transport (PMT) (Nash et al 2018 J. Geophys. Res. Atmos. 123 6804–21). However, processes governing regional impacts of PMT as well as long-term trends remain largely unknown. Here we use an ensemble of state-of-the-art global climate models in standardized scenario simulations (1850–2100) to show that both the Arctic and the Antarctic exhibit distinct geographical patterns of PMT-related warming. Specifically, years with high PMT experience considerable warming over subarctic Eurasia and West-Antarctica (Raphael et al 2016 Bull. Am. Meteorol. Soc. 97 111–21), whereas precipitation is distributed more evenly over the polar regions. The warming patterns indicate preferred routes of atmospheric rivers (Woods and Caballero 2016 J. Clim. 29 4473–85), which may regionally enhance atmospheric moisture content, cloud cover, and downward longwave radiative heating in years with comparatively high PMT (Scott et al 2019 J. Clim. 32 665–84). Trend-analyses reveal that the link between PMT-variability and regional precipitation patterns will weaken in both polar regions. Even though uncertainties associated with intermodel differences are considerable, the advection of warm and moist air associated with PMT-variability is likely to increasingly cause mild conditions in both polar regions, which in the Arctic will reinforce sea-ice melt. Similarly, the results suggest that warm years in West-Antarctica disproportionally contribute to ice sheet melt (Trusel et al 2015 Nat. Geosci. 8 927–32), enhancing the risk of ice-sheet instabilities causing accelerated and sudden sea-level rise.
Publisher: IOP Publishing
Keywords: Antarktis; global oppvarming; klimamodeller; meteorologi; polarområdene

Genomics of cold adaptations in the Antarctic notothenioid fish radiation - Bista, Iliana; Wood, Jonathan M. D.; Desvignes, Thomas; McCarthy, Shane A.; Matschiner, Michael; Ning, Zemin; Tracey, Alan; Torrance, James; Sims, Ying; Chow, William; Smith, Michelle; Oliver, Karen; et al. (Nature Communications, 2023)
Numerous novel adaptations characterise the radiation of notothenioids, the dominant fish group in the freezing seas of the Southern Ocean. To improve understanding of the evolution of this iconic fish group, here we generate and analyse new genome assemblies for 24 species covering all major subgroups of the radiation, including five long-read assemblies. We present a new estimate for the onset of the radiation at 10.7 million years ago, based on a time-calibrated phylogeny derived from genome-wide sequence data. We identify a two-fold variation in genome size, driven by expansion of multiple transposable element families, and use the long-read data to reconstruct two evolutionarily important, highly repetitive gene family loci. First, we present the most complete reconstruction to date of the antifreeze glycoprotein gene family, whose emergence enabled survival in sub-zero temperatures, showing the expansion of the antifreeze gene locus from the ancestral to the derived state. Second, we trace the loss of haemoglobin genes in icefishes, the only vertebrates lacking functional haemoglobins, through complete reconstruction of the two haemoglobin gene clusters across notothenioid families. Both the haemoglobin and antifreeze genomic loci are characterised by multiple transposon expansions that may have driven the evolutionary history of these genes.
Article number: 3412
Keywords: Sørishavet; fisker; marin biologi; zoologi

Investigating the spatial representativeness of East Antarctic ice cores: a comparison of ice core and radar-derived surface mass balance over coastal ice rises and Dome Fuji - Cavitte, M. G. P.; Goosse, H.; Matsuoka, K.; Wauthy, S.; Goel, V.; Dey, R.; Pratap, B.; Van Liefferinge, B.; Meloth, T.; Tison, J.-L. (The Cryosphere, 2023)
Surface mass balance (SMB) of the Antarctic Ice Sheet must be better understood to document the current Antarctic contribution to sea-level rise. In situ point data using snow stakes and ice cores are often used to evaluate the state of the ice sheet's mass balance, as well as to assess SMB derived from regional climate models, which are then used to produce future climate projections. However, spatial representativeness of individual point data remains largely unknown, particularly in the coastal regions of Antarctica with highly variable terrain. Here, we compare ice core data collected at the summit of eight ice rises along the coast of Dronning Maud Land, as well as at the Dome Fuji site, and shallow ice-penetrating radar data over these regions. Shallow radar data have the advantage of being spatially extensive, with a temporal resolution that varies between a yearly and multi-year resolution, from which we can derive a SMB record over the entire radar survey. This comparison therefore allows us to evaluate the spatial variability of SMB and the spatial representativeness of ice-core-derived SMB. We found that ice core mean SMB is very local, and the difference with radar-derived SMB increases in a logarithmic fashion as the surface covered by the radar data increases, with a plateau ∼ 1–2 km away from the ice crest for most ice rises, where there are strong wind–topography interactions, and ∼ 10 km where the ice shelves begin. The relative uncertainty in measuring SMB also increases rapidly as we move away from the ice core sites. Five of our ice rise sites show a strong spatial representativeness in terms of temporal variability, while the other three sites show that it is limited to a surface area between 20–120 km2. The Dome Fuji site, on the other hand, shows a small difference between pointwise and area mean SMB, as well as a strong spatial representativeness in terms of temporal variability. We found no simple parameterization that could represent the spatial variability observed at all the sites. However, these data clearly indicate that local spatial SMB variability must be considered when assessing mass balance, as well as comparing modeled SMB values to point field data, and therefore must be included in the estimate of the uncertainty of the observations.
Keywords: Dronning Maud Land; glasiologi; isshelf; smelting

Reduced Deep Convection and Bottom Water Formation Due To Antarctic Meltwater in a Multi-Model Ensemble - Chen, Jia-Jia; Swart, Neil C.; Beadling, Rebecca; Cheng, Xuhua; Hattermann, Tore; Jüling, André; Li, Qian; Marshall, John; Martin, Torge; Muilwijk, Morven; Pauling, Andrew G.; Purich, Ariaan; et al. (Geophysical Research Letters, 2023)
Abstract The additional water from the Antarctic ice sheet and ice shelves due to climate-induced melt can impact ocean circulation and global climate. However, the major processes driving melt are not adequately represented in Coupled Model Intercomparison Project phase 6 (CMIP6) models. Here, we analyze a novel multi-model ensemble of CMIP6 models with consistent meltwater addition to examine the robustness of the modeled response to meltwater, which has not been possible in previous single-model studies. Antarctic meltwater addition induces a substantial weakening of open-ocean deep convection. Additionally, Antarctic Bottom Water warms, its volume contracts, and the sea surface cools. However, the magnitude of the reduction varies greatly across models, with differing anomalies correlated with their respective mean-state climatology, indicating the state-dependency of the climate response to meltwater. A better representation of the Southern Ocean mean state is necessary for narrowing the inter-model spread of response to Antarctic meltwater.
Publisher: John Wiley & Sons, Ltd Article number: e2023GL106492
Keywords: Sørishavet; klimamodeller; oseanografi

A continent-wide detailed geological map dataset of Antarctica - Cox, Simon C.; Smith Lyttle, Belinda; Elkind, Samuel; Smith Siddoway, Christine; Morin, Paul; Capponi, Giovanni; Abu-Alam, Tamer; Ballinger, Matilda; Bamber, Lauren; Kitchener, Brett; Lelli, Luigi; Mawson, Jasmine; et al. (Scientific Data, 2023)
A dataset to describe exposed bedrock and surficial geology of Antarctica has been constructed by the GeoMAP Action Group of the Scientific Committee on Antarctic Research (SCAR) and GNS Science. Our group captured existing geological map data into a geographic information system (GIS), refined its spatial reliability, harmonised classification, and improved representation of glacial sequences and geomorphology, thereby creating a comprehensive and coherent representation of Antarctic geology. A total of 99,080 polygons were unified for depicting geology at 1:250,000 scale, but locally there are some areas with higher spatial resolution. Geological unit definition is based on a mixed chronostratigraphic- and lithostratigraphic-based classification. Description of rock and moraine polygons employs the international Geoscience Markup Language (GeoSciML) data protocols to provide attribute-rich and queryable information, including bibliographic links to 589 source maps and scientific literature. GeoMAP is the first detailed geological map dataset covering all of Antarctica. It depicts ‘known geology’ of rock exposures rather than ‘interpreted’ sub-ice features and is suitable for continent-wide perspectives and cross-discipline interrogation.
Keywords: Antarktis; geologi; geomorfologi

Antarctica – What role for the EU? - Dodds, Klaus; Raspotnik, Andreas (European Parliament, 2023)
Keywords: Antarktis; geopolitikk; politikk

Antarctic Bedmap data: Findable, Accessible, Interoperable, and Reusable (FAIR) sharing of 60 years of ice bed, surface, and thickness data - Frémand, A. C.; Fretwell, P.; Bodart, J. A.; Pritchard, H. D.; Aitken, A.; Bamber, J. L.; Bell, R.; Bianchi, C.; Bingham, R. G.; Blankenship, D. D.; Casassa, G.; Catania, G.; et al. (Earth System Science Data, 2023)
One of the key components of this research has been the mapping of Antarctic bed topography and ice thickness parameters that are crucial for modelling ice flow and hence for predicting future ice loss and the ensuing sea level rise. Supported by the Scientific Committee on Antarctic Research (SCAR), the Bedmap3 Action Group aims not only to produce new gridded maps of ice thickness and bed topography for the international scientific community, but also to standardize and make available all the geophysical survey data points used in producing the Bedmap gridded products. Here, we document the survey data used in the latest iteration, Bedmap3, incorporating and adding to all of the datasets previously used for Bedmap1 and Bedmap2, including ice bed, surface and thickness point data from all Antarctic geophysical campaigns since the 1950s. More specifically, we describe the processes used to standardize and make these and future surveys and gridded datasets accessible under the Findable, Accessible, Interoperable, and Reusable (FAIR) data principles. With the goals of making the gridding process reproducible and allowing scientists to re-use the data freely for their own analysis, we introduce the new SCAR Bedmap Data Portal (https://bedmap.scar.org, last access: 1 March 2023) created to provide unprecedented open access to these important datasets through a web-map interface. We believe that this data release will be a valuable asset to Antarctic research and will greatly extend the life cycle of the data held within it. Data are available from the UK Polar Data Centre: https://data.bas.ac.uk (last access: 5 May 2023​​​​​​​). See the Data availability section for the complete list of datasets.
Keywords: Antarktis; database; glasiologi

Assessing the viability of estimating baleen whale abundance from tourist vessels - Henderson, Angus Fleetwood; Hindell, Mark Andrew; Wotherspoon, Simon; Biuw, Martin; Lea, Mary-Anne; Kelly, Nat; Lowther, Andrew Damon (Frontiers in Marine Science, 2023)
Many populations of southern hemisphere baleen whales are recovering and are again becoming dominant consumers in the Southern Ocean. Key to understanding the present and future role of baleen whales in Southern Ocean ecosystems is determining their abundance on foraging grounds. Distance sampling is the standard method for estimating baleen whale abundance but requires specific logistic requirements which are rarely achieved in the remote Southern Ocean. We explore the potential use of tourist vessel-based sampling as a cost-effective solution for conducting distance sampling surveys for baleen whales in the Southern Ocean. We used a dataset of tourist vessel locations from the southwest Atlantic sector of the Southern Ocean and published knowledge from Southern Ocean sighting surveys to determine the number of tourist vessel voyages required for robust abundance estimates. Second, we simulated the abundance and distributions of four baleen whale species for the study area and sampled them with both standardized line transect surveys and non-standardized tourist vessel-based surveys, then compared modeled abundance and distributions from each survey to the original simulation. For the southwest Atlantic, we show that 12-22 tourist vessel voyages are likely required to estimate abundance for humpback and fin whales, with relative estimates for blue, sei, Antarctic minke, and southern right whales. Second, we show tourist vessel-based surveys outperformed standardized line transect surveys at reproducing simulated baleen whale abundances and distribution. These analyses suggest tourist vessel-based surveys are a viable method for estimating baleen whale abundance in remote regions. For the southwest Atlantic, the relatively cost-effective nature of tourist vessel-based survey and regularity of tourist vessel voyages could allow for annual and intra-annual estimates of abundance, a fundamental improvement on current methods, which may capture spatiotemporal trends in baleen whale movements on forging grounds. Comparative modeling of sampling methods provided insights into the behavior of general additive model-based abundance modeling, contributing to the development of detailed guidelines of best practices for these approaches. Through successful engagement with tourist company partners, this method has the potential to characterize abundance across a variety of marine species and spaces globally, and deliver high-quality scientific outcomes relevant to management organizations.
Keywords: Sørishavet; kval; marin biologi

The stability of present-day Antarctic grounding lines – Part 1: No indication of marine ice sheet instability in the current geometry - Hill, E. A.; Urruty, B.; Reese, R.; Garbe, J.; Gagliardini, O.; Durand, G.; Gillet-Chaulet, F.; Gudmundsson, G. H.; Winkelmann, R.; Chekki, M.; Chandler, D.; Langebroek, P. M. (The Cryosphere, 2023)
Theoretical and numerical work has shown that under certain circumstances grounding lines of marine-type ice sheets can enter phases of irreversible advance and retreat driven by the marine ice sheet instability (MISI). Instances of such irreversible retreat have been found in several simulations of the Antarctic Ice Sheet. However, it has not been assessed whether the Antarctic grounding lines are already undergoing MISI in their current position. Here, we conduct a systematic numerical stability analysis using three state-of-the-art ice sheet models: Úa, Elmer/Ice, and the Parallel Ice Sheet Model (PISM). For the first two models, we construct steady-state initial configurations whereby the simulated grounding lines remain at the observed present-day positions through time. The third model, PISM, uses a spin-up procedure and historical forcing such that its transient state is close to the observed one. To assess the stability of these simulated states, we apply short-term perturbations to submarine melting. Our results show that the grounding lines around Antarctica migrate slightly away from their initial position while the perturbation is applied, and they revert once the perturbation is removed. This indicates that present-day retreat of Antarctic grounding lines is not yet irreversible or self-sustained. However, our accompanying paper (Part 2, Reese et al., 2023a) shows that if the grounding lines retreated further inland, under present-day climate forcing, it may lead to the eventual irreversible collapse of some marine regions of West Antarctica.
Keywords: Antarktis; Sørishavet; glasiologi; isshelf

Communicating the best available science to inform Antarctic policy and management: a practical introduction for researchers - Hughes, Kevin A.; Lowther, Andrew; Gilbert, Neil; Waluda, Claire M.; Lee, Jasmine R. (Antarctic Science, 2023)
Communication at the science-policy interface can be bewildering not only for early-career researchers, but also for many within the research community. In the context of Antarctica and the Southern Ocean, decision-makers operating within the Antarctic Treaty System (ATS) aspire to use the best available science as a basis for their decision-making. Therefore, to maximize the impact of Antarctic Treaty Parties' substantial investment in southern polar research, researchers wishing to contribute to policy and management must understand 1) how their work relates to and can potentially inform Antarctic and/or global policy and 2) the available mechanisms by which their research can be communicated to decision-makers. Recognizing these needs, we describe the main legal instruments relevant to Antarctic governance (primarily the ATS) and the associated meetings and stakeholders that contribute to policy development for the region. We highlight effective mechanisms by which Antarctic researchers may communicate their science into the policy realm, including through National Delegations or the Scientific Committee on Antarctic Research (SCAR), and we detail the key contemporary topics of interest to decision-makers, including those issues where further research is needed. Finally, we describe challenges at the Antarctic science-policy interface that may potentially slow or halt policy development.
Edition: 2023/10/18 Publisher: Cambridge University Press
Keywords: Antarktis; Antarktistraktaten; Sørishavet; forskning; forvaltning; kommunikasjon

Warming beneath an East Antarctic ice shelf due to increased subpolar westerlies and reduced sea ice - Lauber, Julius; Hattermann, Tore; de Steur, Laura; Darelius, Elin; Auger, Matthis; Nøst, Ole Anders; Moholdt, Geir (Nature Geoscience, 2023)
Understanding how climate change influences ocean-driven melting of the Antarctic ice shelves is one of the greatest challenges for projecting future sea level rise. The East Antarctic ice shelf cavities host cold water masses that limit melting, and only a few short-term observational studies exist on what drives warm water intrusions into these cavities. We analyse nine years of continuous oceanographic records from below Fimbulisen and relate them to oceanic and atmospheric forcing. On monthly time scales, warm inflow events are associated with weakened coastal easterlies reducing downwelling in front of the ice shelf. Since 2016, however, we observe sustained warming, with inflowing Warm Deep Water temperatures reaching above 0 °C. This is concurrent with an increase in satellite-derived basal melt rates of 0.62 m yr−1, which nearly doubles the basal mass loss at this relatively cold ice shelf cavity. We find that this transition is linked to a reduction in coastal sea ice cover through an increase in atmosphere–ocean momentum transfer and to a strengthening of remote subpolar westerlies. These results imply that East Antarctic ice shelves may become more exposed to warmer waters with a projected increase of circum-Antarctic westerlies, increasing this region’s relevance for sea level rise projections.
Keywords: Sørishavet; glasiologi; oseanografi

Turned 60, is the Antarctic treaty system in good health? - Mancilla, Alejandra; Jabour, Julia Ann (The Geographical Journal, 2023)
Signed in 1959, the Antarctic Treaty is usually hailed as an example of what states can achieve when they leave aside their interests and truly collaborate. It was over 30?years ago, however, that the last significant legal instrument of the Antarctic Treaty System (namely, the Protocol on Environmental Protection) was signed. Since then, no new legal instruments have been drafted, despite a number of growing internal and external challenges. In this special issue, an interdisciplinary group of scholars examine some of these challenges and evaluate whether the system is well prepared to tackle them. Their point of agreement is that, if not severely ill, the system's chronic ailments?particularly laggardness?must be addressed if it is to respond satisfactorily to rapid social, political, environmental and economic changes on a global scale.
Publisher: John Wiley & Sons, Ltd
Keywords: Antarktis; Antarktistraktaten; miljøvern; politikk

A thicker Antarctic ice stream during the mid-Pliocene warm period - Mas e Braga, Martim; Jones, Richard S.; Bernales, Jorge; Andersen, Jane Lund; Fredin, Ola; Morlighem, Mathieu; Koester, Alexandria J.; Lifton, Nathaniel A.; Harbor, Jonathan M.; Suganuma, Yusuke; Glasser, Neil F.; Rogozhina, Irina; et al. (Communications Earth & Environment, 2023)
Ice streams regulate most ice mass loss in Antarctica. Determining ice stream response to warmer conditions during the Pliocene could provide insights into their future behaviour, but this is hindered by a poor representation of subglacial topography in ice-sheet models. We address this limitation using a high-resolution model for Dronning Maud Land (East Antarctica). We show that contrary to dynamic thinning of the region’s ice streams following ice-shelf collapse, the largest ice stream, Jutulstraumen, thickens by 700 m despite lying on a retrograde bed slope. We attribute this counterintuitive thickening to a shallower Pliocene subglacial topography and inherent high lateral stresses at its flux gate. These conditions constrict ice drainage and, combined with increased snowfall, allow ice accumulation upstream. Similar stress balances and increased precipitation projections occur across 27% of present-day East Antarctica, and understanding how lateral stresses regulate ice-stream discharge is necessary for accurately assessing Antarctica’s future sea-level rise contribution.
Article number: 321
Keywords: Dronning Maud Land; glasiologi; klimaendringer; paleoklimatologi

Antarctic sea-ice low resonates in the ecophysiology of humpback whales - Nash, Susan Bengtson; Groβ, Jasmin; Castrillon, Juliana; Casa, Maria Valeria; Luche, Greta Dalle; Meager, Justin; Ghosh, Ruma; Eggebo, June; Bohlin-Nizzetto, Pernilla (Science of The Total Environment, 2023)
The past six years have been marked by some of the most dramatic climatic events observed in the Antarctic region in recent history, commencing with the 2017 sea-ice extreme low. The Humpback Whale Sentinel Programme is a circum-polar biomonitoring program for long term surveillance of the Antarctic sea-ice ecosystem. It has previously signalled the extreme La Niña event of 2010/11, and it was therefore of interest to assess the capacity of existing biomonitoring measures under the program to detect the impacts of 2017 anomalous climatic events. Six ecophysiological markers of population adiposity, diet, and fecundity were targeted, as well as calf and juvenile mortality via stranding records. All indicators, with the exception of bulk stable isotope dietary tracers, indicated a negative trend in 2017, whilst C and N bulk stable isotopes appeared to indicate a lag phase resulting from the anomalous year. The collation of multiple biochemical, chemical, and observational lines of evidence via a single biomonitoring platform provides comprehensive information for evidence-led policy in the Antarctic and Southern Ocean region.
Keywords: Sørishavet; bioovervåking; havis; klimaendringer; knølhvaler; marine økosystemer; miljøgifter; økofysiologi

Large-scale seabird community structure along oceanographic gradients in the Scotia Sea and northern Antarctic Peninsula - Ollus, Victoria Marja Sofia; Biuw, Martin; Lowther, Andrew; Fauchald, Per; Deehr Johannessen, John Elling; Martín López, Lucía Martina; Gkikopoulou, Kalliopi C.; Oosthuizen, W. Chris; Lindstrøm, Ulf (Frontiers in Marine Science, 2023)
Introduction: The Scotia Sea and Antarctic Peninsula are warming rapidly and changes in species distribution are expected. In predicting habitat shifts and considering appropriate management strategies for marine predators, a community-level understanding of how these predators are distributed is desirable. Acquiring such data, particularly in remote areas, is often problematic given the cost associated with the operation of research vessels. Here we use cruise vessels as sampling platforms to explore seabird distribution relative to habitat characteristics. Methods: Data on seabird at-sea distribution were collected using strip-transect counts throughout the Antarctic Peninsula and Scotia Sea in the austral summer of 2019-2020. Constrained correspondence analysis (CCA) and generalized additive models (GAM) were used to relate seabird community composition, density, and species richness to environmental covariates. Results: Species assemblages differed between oceanographic areas, with sea surface temperature and distance to coast being the most important predictors of seabird distribution. Our results further revealed a geographic separation of distinct communities rather than hotspot regions in the study area in summer. Discussion: These findings highlight the importance of large-scale environmental characteristics in shaping seabird community structure, presumably through underlying prey distribution and interspecific interactions. The present study contributes to the knowledge of seabird distribution and habitat use as well as the baseline for assessing the response of Antarctic seabird communities to climate warming. We argue that cruise vessels, when combined with structured research surveys, can provide a cost-effective additional tool for the monitoring of community and ecosystem level changes.
Keywords: Antarktis; Sørishavet; marin biologi; marin zoologi; marine økosystemer; sjøfugler

Quantifying dissolution rates of Antarctic icebergs in open water - Orheim, Olav; Giles, A. Barry; Jacka, T. H. (Jo); Moholdt, Geir (Annals of Glaciology, 2023)
At any one time 130 000 icebergs are afloat in the Southern Ocean; 97% of these are too small to be registered in current satellite-based databases, yet the melting of these small icebergs provides a major input to the Southern Ocean. We use a unique set of visual size observations of 53 000 icebergs in the South Atlantic Ocean, the SCAR International Iceberg Database, to derive average iceberg dissolution rates. Fracture into two parts is the dominant dissolution process for tabular icebergs, with an average half-life of 30 days for icebergs <4 km length and 60 days for larger icebergs. Complete shatter producing many icebergs <1 km length is rare. A side attrition rate of 0.23 m d−1 combined with drift speed of 6 km d−1, or any proportional change in both numbers fits the observed changes in iceberg distribution. The largest injection into the Southern Ocean of fresh water and any iceberg-transported material takes place in a ~2.3 × 10⁶ km2 zone extending east-northeast from the Antarctic Peninsula to the Greenwich meridian. The iceberg contribution to salinities and temperatures, with maximum contribution north of the Weddell Sea, differs in some regions, from those indicated by tracking large icebergs.
Edition: 2023/05/03 Publisher: Cambridge University Press
Keywords: Sørishavet; glasiologi; iceberg calving; isfjell; oseanografi

Antarctic iceberg distribution revealed through three decades of systematic ship-based observations in the SCAR International Iceberg Database - Orheim, Olav; Giles, A. Barry; Moholdt, Geir; (Jo) Jacka, T. H.; Bjørdal, Are (Journal of Glaciology, 2023)
In 1981, the Scientific Committee on Antarctic Research endorsed a program for ship-based collection of Antarctic iceberg data, to be coordinated by the Norwegian Polar Institute (NPI). From the austral summers 1982/1983 to 1997/1998, icebergs were recorded from most, and up to 2009/10 by fewer research vessels. The NPI database makes up 80% of the SCAR International Iceberg Database presented here, the remainder being Australian National Antarctic Research Expedition observations. The database contains positions of 374 142 icebergs resulting from 34 662 observations. Within these, 298 235 icebergs are classified into different size categories. The ship-based data are particularly useful because they include systematic observations of smaller icebergs not covered by current satellite-based datasets. Here, we assess regional and seasonal variations in iceberg density and total quantities, we identify drift patterns and exit zones from the continent, and we discuss iceberg dissolution rates and calving rates. There are significant differences in the extent of icebergs observed over the 30 plus years of observations, but much of these can be ascribed to differences in observation density and location. In the summer, Antarctic icebergs >10 m in length number ~130 000 of which 1000 are found north of the Southern Ocean boundary.
Edition: 2022/10/03 Publisher: Cambridge University Press
Keywords: Antarktis; Sørishavet; database; glasiologi; isfjell

Characteristics of Surface “Melt Potential” over Antarctic Ice Shelves based on Regional Atmospheric Model Simulations of Summer Air Temperature Extremes from 1979/80 to 2018/19 - Orr, Andrew; Deb, Pranab; Clem, Kyle R.; Gilbert, Ella; Bromwich, David H.; Boberg, Fredrik; Colwell, Steve; Hansen, Nicolaj; Lazzara, Matthew A.; Mooney, Priscilla A.; Mottram, Ruth; Niwano, Masashi; et al. (Journal of Climate, 2023)
We calculate a regional surface “melt potential” index (MPI) over Antarctic ice shelves that describes the frequency (MPI-freq; %) and intensity (MPI-int; K) of daily maximum summer temperatures exceeding a melt threshold of 273.15 K. This is used to determine which ice shelves are vulnerable to melt-induced hydrofracture and is calculated using near-surface temperature output for each summer from 1979/80 to 2018/19 from two high-resolution regional atmospheric model hindcasts (using the MetUM and HIRHAM5). MPI is highest for Antarctic Peninsula ice shelves (MPI-freq 23%–35%, MPI-int 1.2–2.1 K), lowest (2%–3%, <0 K) for the Ronne–Filchner and Ross ice shelves, and around 10%–24% and 0.6–1.7 K for the other West and East Antarctic ice shelves. Hotspots of MPI are apparent over many ice shelves, and they also show a decreasing trend in MPI-freq. The regional circulation patterns associated with high MPI values over West and East Antarctic ice shelves are remarkably consistent for their respective region but tied to different large-scale climate forcings. The West Antarctic circulation resembles the central Pacific El Niño pattern with a stationary Rossby wave and a strong anticyclone over the high-latitude South Pacific. By contrast, the East Antarctic circulation comprises a zonally symmetric negative Southern Annular Mode pattern with a strong regional anticyclone on the plateau and enhanced coastal easterlies/weakened Southern Ocean westerlies. Values of MPI are 3–4 times larger for a lower temperature/melt threshold of 271.15 K used in a sensitivity test, as melting can occur at temperatures lower than 273.15 K depending on snowpack properties.
Place: Boston MA, USA Publisher: American Meteorological Society
Keywords: Antarktis; glasiologi; klima; smelting

The stability of present-day Antarctic grounding lines – Part 2: Onset of irreversible retreat of Amundsen Sea glaciers under current climate on centennial timescales cannot be excluded - Reese, R.; Garbe, J.; Hill, E. A.; Urruty, B.; Naughten, K. A.; Gagliardini, O.; Durand, G.; Gillet-Chaulet, F.; Gudmundsson, G. H.; Chandler, D.; Langebroek, P. M.; Winkelmann, R. (The Cryosphere, 2023)
Observations of ocean-driven grounding-line retreat in the Amundsen Sea Embayment in Antarctica raise the question of an imminent collapse of the West Antarctic Ice Sheet. Here we analyse the committed evolution of Antarctic grounding lines under the present-day climate. To this aim, we first calibrate a sub-shelf melt parameterization, which is derived from an ocean box model, with observed and modelled melt sensitivities to ocean temperature changes, making it suitable for present-day simulations and future sea level projections. Using the new calibration, we run an ensemble of historical simulations from 1850 to 2015 with a state-of-the-art ice sheet model to create model instances of possible present-day ice sheet configurations. Then, we extend the simulations for another 10 000 years to investigate their evolution under constant present-day climate forcing and bathymetry. We test for reversibility of grounding-line movement in the case that large-scale retreat occurs. In the Amundsen Sea Embayment we find irreversible retreat of the Thwaites Glacier for all our parameter combinations and irreversible retreat of the Pine Island Glacier for some admissible parameter combinations. Importantly, an irreversible collapse in the Amundsen Sea Embayment sector is initiated at the earliest between 300 and 500 years in our simulations and is not inevitable yet – as also shown in our companion paper (Part 1, Hill et al., 2023). In other words, the region has not tipped yet. With the assumption of constant present-day climate, the collapse evolves on millennial timescales, with a maximum rate of 0.9 mm a−1 sea-level-equivalent ice volume loss. The contribution to sea level by 2300 is limited to 8 cm with a maximum rate of 0.4 mm a−1 sea-level-equivalent ice volume loss. Furthermore, when allowing ice shelves to regrow to their present geometry, we find that large-scale grounding-line retreat into marine basins upstream of the Filchner–Ronne Ice Shelf and the western Siple Coast is reversible. Other grounding lines remain close to their current positions in all configurations under present-day climate.
Keywords: Antarktis; Sørishavet; glasiologi; isshelf

Antarctic permafrost degassing in Taylor Valley by extensive soil gas investigation - Ruggiero, L.; Sciarra, A.; Mazzini, A.; Florindo, F.; Wilson, G.; Tartarello, M.C.; Mazzoli, C.; Anderson, J.T.H.; Romano, V.; Worthington, R.; Bigi, S.; Sassi, R.; et al. (Science of The Total Environment, 2023)
Ongoing studies conducted in northern polar regions reveal that permafrost stability plays a key role in the modern carbon cycle as it potentially stores considerable quantities of greenhouse gases. Rapid and recent warming of the Arctic permafrost is resulting in significant greenhouse gas emissions, both from physical and microbial processes. The potential impact of greenhouse gas release from the Antarctic region has not, to date, been investigated. In Antarctica, the McMurdo Dry Valleys comprise 10 % of the ice-free soil surface areas in Antarctica and like the northern polar regions are also warming albeit at a slower rate. The work presented herein examines a comprehensive sample suite of soil gas (e.g., CO2, CH4 and He) concentrations and CO2 flux measurements conducted in Taylor Valley during austral summer 2019/2020. Analytical results reveal the presence of significant concentrations of CO2, CH4 and He (up to 3.44 vol%, 18,447 ppmv and 6.49 ppmv, respectively) at the base of the active layer. When compared with the few previously obtained measurements, we observe increased CO2 flux rates (estimated CO2 emissions in the study area of 21.6 km2 ≈ 15 tons day−1). We suggest that the gas source is connected with the deep brines migrating from inland (potentially from beneath the Antarctic Ice Sheet) towards the coast beneath the permafrost layer. These data provide a baseline for future investigations aimed at monitoring the changing rate of greenhouse gas emissions from Antarctic permafrost, and the potential origin of gases, as the southern polar region warms.
Keywords: Antarktis; drivhusgasser; geofysikk; geologi; geostatistikk; isbreer; permafrost

Southern ocean carbon and heat impact on climate - Sallée, J. B.; Abrahamsen, E. P.; Allaigre, C.; Auger, M.; Ayres, H.; Badhe, R.; Boutin, J.; Brearley, J. A.; de Lavergne, C.; ten Doeschate, A. M. M.; Droste, E. S.; du Plessis, M. D.; et al. (Philosophical Transactions of the Royal Society A: Mathematical, Physical and Engineering Sciences, 2023)
The Southern Ocean greatly contributes to the regulation of the global climate by controlling important heat and carbon exchanges between the atmosphere and the ocean. Rates of climate change on decadal timescales are therefore impacted by oceanic processes taking place in the Southern Ocean, yet too little is known about these processes. Limitations come both from the lack of observations in this extreme environment and its inherent sensitivity to intermittent processes at scales that are not well captured in current Earth system models. The Southern Ocean Carbon and Heat Impact on Climate programme was launched to address this knowledge gap, with the overall objective to understand and quantify variability of heat and carbon budgets in the Southern Ocean through an investigation of the key physical processes controlling exchanges between the atmosphere, ocean and sea ice using a combination of observational and modelling approaches. Here, we provide a brief overview of the programme, as well as a summary of some of the scientific progress achieved during its first half. Advances range from new evidence of the importance of specific processes in Southern Ocean ventilation rate (e.g. storm-induced turbulence, sea–ice meltwater fronts, wind-induced gyre circulation, dense shelf water formation and abyssal mixing) to refined descriptions of the physical changes currently ongoing in the Southern Ocean and of their link with global climate. This article is part of a discussion meeting issue ‘Heat and carbon uptake in the Southern Ocean: the state of the art and future priorities’.
_eprint: https://royalsocietypublishing.org/doi/pdf/10.1098/rsta.2022.0056
Keywords: Sørishavet; atmosfæren; havis; klimaforskning; oseanografi

Insights into the vulnerability of Antarctic glaciers from the ISMIP6 ice sheet model ensemble and associated uncertainty - Seroussi, H.; Verjans, V.; Nowicki, S.; Payne, A. J.; Goelzer, H.; Lipscomb, W. H.; Abe-Ouchi, A.; Agosta, C.; Albrecht, T.; Asay-Davis, X.; Barthel, A.; Calov, R.; et al. (The Cryosphere, 2023)
The Antarctic Ice Sheet represents the largest source of uncertainty in future sea level rise projections, with a contribution to sea level by 2100 ranging from −5 to 43 cm of sea level equivalent under high carbon emission scenarios estimated by the recent Ice Sheet Model Intercomparison for CMIP6 (ISMIP6). ISMIP6 highlighted the different behaviors of the East and West Antarctic ice sheets, as well as the possible role of increased surface mass balance in offsetting the dynamic ice loss in response to changing oceanic conditions in ice shelf cavities. However, the detailed contribution of individual glaciers, as well as the partitioning of uncertainty associated with this ensemble, have not yet been investigated. Here, we analyze the ISMIP6 results for high carbon emission scenarios, focusing on key glaciers around the Antarctic Ice Sheet, and we quantify their projected dynamic mass loss, defined here as mass loss through increased ice discharge into the ocean in response to changing oceanic conditions. We highlight glaciers contributing the most to sea level rise, as well as their vulnerability to changes in oceanic conditions. We then investigate the different sources of uncertainty and their relative role in projections, for the entire continent and for key individual glaciers. We show that, in addition to Thwaites and Pine Island glaciers in West Antarctica, Totten and Moscow University glaciers in East Antarctica present comparable future dynamic mass loss and high sensitivity to ice shelf basal melt. The overall uncertainty in additional dynamic mass loss in response to changing oceanic conditions, compared to a scenario with constant oceanic conditions, is dominated by the choice of ice sheet model, accounting for 52 % of the total uncertainty of the Antarctic dynamic mass loss in 2100. Its relative role for the most dynamic glaciers varies between 14 % for MacAyeal and Whillans ice streams and 56 % for Pine Island Glacier at the end of the century. The uncertainty associated with the choice of climate model increases over time and reaches 13 % of the uncertainty by 2100 for the Antarctic Ice Sheet but varies between 4 % for Thwaites Glacier and 53 % for Whillans Ice Stream. The uncertainty associated with the ice–climate interaction, which captures different treatments of oceanic forcings such as the choice of melt parameterization, its calibration, and simulated ice shelf geometries, accounts for 22 % of the uncertainty at the ice sheet scale but reaches 36 % and 39 % for Institute Ice Stream and Thwaites Glacier, respectively, by 2100. Overall, this study helps inform future research by highlighting the sectors of the ice sheet most vulnerable to oceanic warming over the 21st century and by quantifying the main sources of uncertainty.
Keywords: Antarktis; glasiologi; isbreer; klimamodeller; smelting

Stochastic Simulations of Bed Topography Constrain Geothermal Heat Flow and Subglacial Drainage Near Dome Fuji, East Antarctica - Shackleton, Calvin; Matsuoka, Kenichi; Moholdt, Geir; Van Liefferinge, Brice; Paden, John (Journal of Geophysical Research: Earth Surface, 2023)
Abstract Topographic variability beneath ice sheets regulates ice flow, basal melting, refreezing processes, and meltwater drainage. The preservation of old ice layers and basal ice stratigraphy is sensitive to these subglacial processes, and Dome Fuji, inland East Antarctica, is one of the few regions where 1.5-Ma old ice can be preserved for investigating a major climatic change that occurred in the mid-Pleistocene. We used stochastic simulation methods and radar data to generate an ensemble of simulated bed topography with the continuous and realistic roughness necessary to assess basal conditions. Ensemble analysis reveals the magnitude and spatial distribution of topographic uncertainty, facilitating uncertainty-constrained assessments of subglacial drainage and topographic adjustments to geothermal heat flow (GHF). We find that topographic variability can lead to widespread local GHF variations of ±20% of the background value, which aggregate to raise the regional value and suggest previously underestimated distributions and rates of basal melting. We also find that survey profile spacing has an increasing influence on topographic uncertainty for rougher bed, deriving an empirical relationship that could guide future survey planning based on uncertainty tolerance.
_eprint: https://agupubs.onlinelibrary.wiley.com/doi/pdf/10.1029/2023JF007269
Keywords: Dronning Maud Land; glasiologi; hydrologi

Observing Antarctic Bottom Water in the Southern Ocean - Silvano, Alessandro; Purkey, Sarah; Gordon, Arnold L.; Castagno, Pasquale; Stewart, Andrew L.; Rintoul, Stephen R.; Foppert, Annie; Gunn, Kathryn L.; Herraiz-Borreguero, Laura; Aoki, Shigeru; Nakayama, Yoshihiro; Naveira Garabato, Alberto C.; et al. (Frontiers in Marine Science, 2023)
Dense, cold waters formed on Antarctic continental shelves descend along the Antarctic continental margin, where they mix with other Southern Ocean waters to form Antarctic Bottom Water (AABW). AABW then spreads into the deepest parts of all major ocean basins, isolating heat and carbon from the atmosphere for centuries. Despite AABW’s key role in regulating Earth’s climate on long time scales and in recording Southern Ocean conditions, AABW remains poorly observed. This lack of observational data is mostly due to two factors. First, AABW originates on the Antarctic continental shelf and slope where in situ measurements are limited and ocean observations by satellites are hampered by persistent sea ice cover and long periods of darkness in winter. Second, north of the Antarctic continental slope, AABW is found below approximately 2 km depth, where in situ observations are also scarce and satellites cannot provide direct measurements. Here, we review progress made during the past decades in observing AABW. We describe 1) long-term monitoring obtained by moorings, by ship-based surveys, and beneath ice shelves through bore holes; 2) the recent development of autonomous observing tools in coastal Antarctic and deep ocean systems; and 3) alternative approaches including data assimilation models and satellite-derived proxies. The variety of approaches is beginning to transform our understanding of AABW, including its formation processes, temporal variability, and contribution to the lower limb of the global ocean meridional overturning circulation. In particular, these observations highlight the key role played by winds, sea ice, and the Antarctic Ice Sheet in AABW-related processes. We conclude by discussing future avenues for observing and understanding AABW, impressing the need for a sustained and coordinated observing system.
Keywords: Sørishavet; oseanografi

Absence of photophysiological response to iron addition in autumn phytoplankton in the Antarctic sea-ice zone - Singh, A.; Fietz, S.; Thomalla, S. J.; Sanchez, N.; Ardelan, M. V.; Moreau, S.; Kauko, H. M.; Fransson, A.; Chierici, M.; Samanta, S.; Mtshali, T. N.; Roychoudhury, A. N.; et al. (Biogeosciences, 2023)
Keywords: Sørishavet; kjemi; marin biologi; oseanografi; plankton

New cold-adapted bacteria for efficient hydrolysis of feather waste at low temperature - Smirnova, Margarita; Losada, Cristian Bolaño; Akulava, Volha; Zimmermann, Boris; Kohler, Achim; Miamin, Uladzislau; Oostindjer, Marije; Shapaval, Volha (Bioresource Technology Reports, 2023)
A novel cold-adapted bacteria Arthrobacter oryzae BIM B-1663 isolated from Antarctic green snow showed keratinase activity and efficient poultry feather degradation. A. oryzae strain degraded more than 80 % of chicken feathers within 7 days of cultivation at 25 °C. The optimal keratinase activity for A. oryzae BIM B-1663 was observed at 50 °C, both for α-keratin (44.86 U/mL) and for β-keratin (94 mU/mL). The obtained results from sulfite and thiol groups tests and Fourier transform infrared spectroscopy (FTIR) showed that A. oryzae strain has a different keratin degradation mechanism than the reference strain Bacillus licheniformis CCM 2145T. FTIR fingerprinting can be used for monitoring of feather hydrolysis as it showed distinct chemical differences in feather meal hydrolysates, retentate and permeate from A. oryzae and B. licheniformis strains.
Article number: 101530
Keywords: Antarktis; bakterier; biokjemi; kjemi; mikrobiologi

The Southern Ocean Freshwater Input from Antarctica (SOFIA) Initiative: scientific objectives and experimental design - Swart, Neil C.; Martin, Torge; Beadling, Rebecca; Chen, Jia-Jia; Danek, Christopher; England, Matthew H.; Farneti, Riccardo; Griffies, Stephen M.; Hattermann, Tore; Hauck, Judith; Haumann, F. Alexander; Jüling, André; et al. (Geoscientific Model Development, 2023)
As the climate warms, the grounded ice sheet and floating ice shelves surrounding Antarctica are melting and releasing additional freshwater into the Southern Ocean. Nonetheless, almost all existing coupled climate models have fixed ice sheets and lack the physics required to represent the dominant sources of Antarctic melt. These missing ice dynamics represent a key uncertainty that is typically unaccounted for in current global climate change projections. Previous modelling studies that have imposed additional Antarctic meltwater have demonstrated regional impacts on Southern Ocean stratification, circulation, and sea ice, as well as remote changes in atmospheric circulation, tropical precipitation, and global temperature. However, these previous studies have used widely varying rates of freshwater forcing, have been conducted using different climate models and configurations, and have reached differing conclusions on the magnitude of meltwater–climate feedbacks. The Southern Ocean Freshwater Input from Antarctica (SOFIA) initiative brings together a team of scientists to quantify the climate system response to Antarctic meltwater input along with key aspects of the uncertainty. In this paper, we summarize the state of knowledge on meltwater discharge from the Antarctic ice sheet and ice shelves to the Southern Ocean and explain the scientific objectives of our initiative. We propose a series of coupled and ocean–sea ice model experiments, including idealized meltwater experiments, historical experiments with observationally consistent meltwater input, and future scenarios driven by meltwater inputs derived from stand-alone ice sheet models. Through coordinating a multi-model ensemble of simulations using a common experimental design, open data archiving, and facilitating scientific collaboration, SOFIA aims to move the community toward better constraining our understanding of the climate system response to Antarctic melt.
Keywords: Sørishavet; geovitenskap; havnivåstigning; klimaendringer; klimamodeller; oseanografi

Linking timescale-dependent Antarctic sea ice kinematic observations to ice thickness - Tian, Tian R.; Fraser, Alexander D.; Lavergne, Thomas; Fiddes, Sonya L.; Zhao, Chen; Heil, Petra (Remote Sensing of Environment, 2023)
Sea ice kinematics impacts the global ocean–atmosphere system in numerous ways: modification of albedo, ice cover, and ice mass; heat transmission between atmosphere and ocean; and ice thickness distribution. Such research is often conducted using in situ and remotely-sensed observations of ice motion. In recent work, an ice motion product generated from overlapping sections of multiple individual swath pairs – the so-called swath-to-swath (S2S) approach – has been favourably evaluated by buoys in the Arctic. This new product is better able to represent drifting buoy trajectories, however, it has yet to be applied to ice kinematics research. In this study, we investigate the Antarctic sea ice differential kinematic parameters (DKPs) represented by divergence and maximum shear rate computed from the new S2S ice motion product, and compare these with the daily-map (DM)-derived DKP magnitudes. Results indicate that S2S-derived DKP magnitudes are highly timescale-dependent and well represented by an exponential relationship. Furthermore, the exponential DKP curve parameters in this work are shown to correspond well to ice thickness, thus enabling a new class of Antarctic ice thickness proxy observations. This technique lays the groundwork for the possibility of new proxy measurement of ice thickness back to at least 1991, when the high-accuracy S2S measurements of ice motion become available.
Article number: 113813
Keywords: Sørishavet; fysikk; havis

BVLOS UAV missions for vegetation mapping in maritime Antarctic - Zmarz, Anna; Karlsen, Stein Rune; Kycko, Marlena; Korczak-Abshire, Małgorzata; Gołębiowska, Izabela; Karsznia, Izabela; Chwedorzewska, Katarzyna (Frontiers in Environmental Science, 2023)
Polar areas are among the regions where climate change occurs faster than on most of the other areas on Earth. To study the effects of climate change on vegetation, there is a need for knowledge on its current status and properties. Both classic field observation methods and remote sensing methods based on manned aircraft or satellite image analysis have limitations. These include high logistic operation costs, limited research areas, high safety risks, direct human impact, and insufficient resolution of satellite images. Fixed-wing unmanned aerial vehicle beyond the visual line of sight (UAV BVLOS) missions can bridge the scale gap between field-based observations and full-scale airborne or satellite surveys. In this study the two operations of the UAV BVLOS, at an altitude of 350 m ASL, have been successfully performed in Antarctic conditions. Maps of the vegetation of the western shore of Admiralty Bay (King George Island, South Shetlands, Western Antarctic) that included the Antarctic Specially Protected Area No. 128 (ASPA 128) were designed. The vegetation in the 7.5 km2 area was mapped in ultra-high resolution (<5 cm and DEM of 0.25 m GSD), and from the Normalized Difference Vegetation Index (NDVI), four broad vegetation units were extracted: “dense moss carpets” (covering 0.14 km2, 0.8% of ASPA 128), “Sanionia uncinata moss bed” (0.31 km2, 1.7% of ASPA 128), “Deschampsia antarctica grass meadow” (0.24 km2, 1.3% of ASPA 128), and “Deschampsia antarctica–Usnea antarctica heath” (1.66 km2, 9.4% of ASPA 128). Our results demonstrate that the presented UAV BVLOS–based surveys are time-effective (single flight lasting 2.5 h on a distance of 300 km) and cost-effective when compared to classical field-based observations and are less invasive for the ecosystem. Moreover, unmanned airborne vehicles significantly improve security, which is of particular interest in polar region research. Therefore, their development is highly recommended for monitoring areas in remote and fragile environments.
Keywords: Sørishavet; kartlegging; logistikk; teknologi; vegetasjon

Threat management priorities for conserving Antarctic biodiversity - Lee, Jasmine R.; Terauds, Aleks; Carwardine, Josie; Shaw, Justine D.; Fuller, Richard A.; Possingham, Hugh P.; Chown, Steven L.; Convey, Peter; Gilbert, Neil; Hughes, Kevin A.; McIvor, Ewan; Robinson, Sharon A.; et al. (PLOS Biology, 2022)
Antarctic terrestrial biodiversity faces multiple threats, from invasive species to climate change. Yet no large-scale assessments of threat management strategies exist. Applying a structured participatory approach, we demonstrate that existing conservation efforts are insufficient in a changing world, estimating that 65% (at best 37%, at worst 97%) of native terrestrial taxa and land-associated seabirds are likely to decline by 2100 under current trajectories. Emperor penguins are identified as the most vulnerable taxon, followed by other seabirds and dry soil nematodes. We find that implementing 10 key threat management strategies in parallel, at an estimated present-day equivalent annual cost of US$23 million, could benefit up to 84% of Antarctic taxa. Climate change is identified as the most pervasive threat to Antarctic biodiversity and influencing global policy to effectively limit climate change is the most beneficial conservation strategy. However, minimising impacts of human activities and improved planning and management of new infrastructure projects are cost-effective and will help to minimise regional threats. Simultaneous global and regional efforts are critical to secure Antarctic biodiversity for future generations.
Publisher: Public Library of Science
Keywords: Antarktis; biodiversitet; forvaltning; pingviner

Southern Ocean biogenic blooms freezing-in Oligocene colder climates - Hochmuth, Katharina; Whittaker, Joanne M.; Sauermilch, Isabel; Klocker, Andreas; Gohl, Karsten; LaCasce, Joseph H. (Nature Communications, 2022)
Crossing a key atmospheric CO2 threshold triggered a fundamental global climate reorganisation ~34 million years ago (Ma) establishing permanent Antarctic ice sheets. Curiously, a more dramatic CO2 decline (~800–400 ppm by the Early Oligocene(~27 Ma)), postdates initial ice sheet expansion but the mechanisms driving this later, rapid drop in atmospheric carbon during the early Oligocene remains elusive and controversial. Here we use marine seismic reflection and borehole data to reveal an unprecedented accumulation of early Oligocene strata (up to 2.2 km thick over 1500 × 500 km) with a major biogenic component in the Australian Southern Ocean. High-resolution ocean simulations demonstrate that a tectonically-driven, one-off reorganisation of ocean currents, caused a unique period where current instability coincided with high nutrient input from the Antarctic continent. This unrepeated and short-lived environment favoured extreme bioproductivity and enhanced sediment burial. The size and rapid accumulation of this sediment package potentially holds ~1.067 × 1015 kg of the ‘missing carbon’ sequestered during the decline from an Eocene high CO2-world to a mid-Oligocene medium CO2-world, highlighting the exceptional role of the Southern Ocean in modulating long-term climate.
Keywords: Sørishavet; geologi; glasiologi; klimaendringer; sedimenter

Regional sea-level highstand triggered Holocene ice sheet thinning across coastal Dronning Maud Land, East Antarctica - Suganuma, Yusuke; Kaneda, Heitaro; Mas e Braga, Martim; Ishiwa, Takeshige; Koyama, Takushi; Newall, Jennifer C.; Okuno, Jun’ichi; Obase, Takashi; Saito, Fuyuki; Rogozhina, Irina; Andersen, Jane Lund; Kawamata, Moto; et al. (Communications Earth & Environment, 2022)
The East Antarctic Ice Sheet stores a vast amount of freshwater, which makes it the single largest potential contributor to future sea-level rise. However, the lack of well-constrained geological records of past ice sheet changes impedes model validation, hampers mass balance estimates, and inhibits examination of ice loss mechanisms. Here we identify rapid ice-sheet thinning in coastal Dronning Maud Land from Early to Middle Holocene (9000–5000 years ago) using a deglacial chronology based on in situ cosmogenic nuclide surface exposure dates from central Dronning Maud Land, in concert with numerical simulations of regional and continental ice-sheet evolution. Regional sea-level changes reproduced from our refined ice-load history show a highstand at 9000–8000 years ago. We propose that sea-level rise and a concomitant influx of warmer Circumpolar Deep Water triggered ice shelf breakup via the marine ice sheet instability mechanism, which led to rapid thinning of upstream coastal ice sheet sectors.
Keywords: Antarktis; Sørishavet; glasiologi; havis; havnivå; isshelf

Genomic insights into the secondary aquatic transition of penguins - Cole, Theresa L.; Zhou, Chengran; Fang, Miaoquan; Pan, Hailin; Ksepka, Daniel T.; Fiddaman, Steven R.; Emerling, Christopher A.; Thomas, Daniel B.; Bi, Xupeng; Fang, Qi; Ellegaard, Martin R.; Feng, Shaohong; et al. (Nature Communications, 2022)
Penguins lost the ability to fly more than 60 million years ago, subsequently evolving a hyper-specialized marine body plan. Within the framework of a genome-scale, fossil-inclusive phylogeny, we identify key geological events that shaped penguin diversification and genomic signatures consistent with widespread refugia/recolonization during major climate oscillations. We further identify a suite of genes potentially underpinning adaptations related to thermoregulation, oxygenation, diving, vision, diet, immunity and body size, which might have facilitated their remarkable secondary transition to an aquatic ecology. Our analyses indicate that penguins and their sister group (Procellariiformes) have the lowest evolutionary rates yet detected in birds. Together, these findings help improve our understanding of how penguins have transitioned to the marine environment, successfully colonizing some of the most extreme environments on Earth.
Keywords: Sørishavet; evolusjon; fylogenetikk; ornitologi; pingviner

Plastic occurrence, sources, and impacts in Antarctic environment and biota - Caruso, Gabriella; Bergami, Elisa; Singh, Neelu; Corsi, Ilaria (Water Biology and Security, 2022)
Several studies have documented that plastic pollution is affecting one of the most remote and pristine regions of our planet, Antarctica. Plastics of different size and polymeric composition have been retrieved in Antarctic sea ice, surface waters and sediments, with microplastics (mostly fibers) found both in terrestrial and marine organisms. Such evidence raises concerns about potential detrimental effects on biodiversity and ecosystem functions. The present review aims to report the most up-to-date knowledge on occurrence and distribution of plastic pollution in the Antarctic environment and biota including interaction with microorganisms, potential sources, and its impact on Antarctic biota. Our understanding of plastic pollution in this polar region will help us define the human footprint in Antarctica and predict future ecological risks.
Keywords: Sørishavet; forurensning; plastpartikler; økotoksikologi

The foraging behavior of nonbreeding Adélie penguins in the western Antarctic Peninsula during the breeding season - Oosthuizen, W. Chris; Pistorius, Pierre A.; Korczak-Abshire, Malgorzata; Hinke, Jefferson T.; Santos, Mercedes; Lowther, Andrew D. (Ecosphere, 2022)
Abstract Information on marine predator at-sea distributions is key to understanding ecosystem and community dynamics and an important component of spatial management frameworks that aim to identify regions important for conservation. Tracking data from seabirds are widely used to define priority areas for conservation, but such data are often restricted to the breeding population. This also applies to penguins in Antarctica, where identification of important habitat for nonbreeders has received limited attention. Nonbreeding penguins are expected to have larger foraging distributions than breeding conspecifics, which may alter their interactions with physical environmental factors, conspecifics, other marine predators, and threats. We studied the movement behavior of nonbreeding Adélie penguins tracked during the 2016/2017 breeding season at King George Island in the South Shetland Islands, Antarctica. We quantify how nonbreeding penguins' horizontal moment behavior varies in relation to environmental conditions and assess the extent of spatial overlap in the foraging ranges of nonbreeders and breeders, which were tracked over several years. Nonbreeders increased their prey search and area-restricted foraging behavior as sea surface temperature and bottom depths decreased, and in response to increasing sea ice concentration. Nonbreeders tended to transit (high directional movement) over the relatively deep Central Basin of the Bransfield Strait. The majority of foraging behavior occurred within the colder, Weddell Sea?sourced water of the Antarctic Coastal Current (incubation) and in the Weddell Sea (crèche). The utilization distributions of breeders and nonbreeders overlapped in the central Bransfield Strait. Spatial segregation was greater during the crèche stage of breeding compared to incubation and brood, because chick provisioning still constrained the foraging range of breeders to a scale of a few tens of kilometers, while nonbreeders commenced with premolt foraging trips into the Weddell Sea. Our results show that breeding and nonbreeding penguins may not be impacted similarly by local environmental variability, given that their spatial and temporal scales of foraging differ during some part of the austral summer. Our study highlights the need to account for different life history stages when characterizing foraging behavior of marine predator populations. This is particularly important for ?sentinel? species monitored as part of marine conservation and ecosystem-based management programs.
Publisher: John Wiley & Sons, Ltd
Keywords: Antarktis; ornitologi; pingviner; sjøfugler; økologi

Characterization of fin whale song off the Western Antarctic Peninsula - Wood, Megan; Širović, Ana (PLOS ONE, 2022)
Song is produced by a variety of terrestrial and marine animals and is particularly common among baleen whales. Fin whale (Balaenoptera physalus) song is comprised of relatively simple 20 Hz pulses produced at regular intervals. The timing of these intervals, in addition to the presence and frequency of overtones, appears to be unique to each population. The purpose of this study was to characterize Western Antarctic Peninsula fin whale song and describe temporal pattern variations in song type and occurrence. Recordings were collected in the area from 2001–2004 and again 2014–2016. One song type was identified with a primary inter-pulse interval (IPI) of approximately 14 s and secondary IPI of 12.5 s. This song occurred in three pattern variants: singlet, doublet, and long triplet. The interval between pulses increased by 1.5 s between recording periods while the frequency of the overtones decreased from 89 Hz to 86 Hz. Song was never recorded in August and while it was recorded at other times in some years, it was consistently present in recordings from April through June across all years. While multiple pattern variants were present each year, singlets were generally the most prevalent variant. Doublets and triplets occurred from February through June, with highest levels of variants in February. In later years the triplet variant presence increased and in 2016 it comprised 53% of recorded song bouts. Further research is needed to understand the reasons why song changes over time and to examine the feasibility of using song to delineate and identify populations.
Publisher: Public Library of Science
Keywords: Sørishavet; kval; marin biologi

Xenobiotic metabolism and its physiological consequences in high-Antarctic Notothenioid fishes - Strobel, Anneli; Lille-Langøy, Roger; Segner, Helmut; Burkhardt-Holm, Patricia; Goksøyr, Anders; Karlsen, Odd André (Polar Biology, 2022)
The Antarctic ecosystem is progressively exposed to anthropogenic contaminants, such as polycyclic aromatic hydrocarbons (PAHs). So far, it is largely unknown if PAHs leave a mark in the physiology of high-Antarctic fish. We approached this issue via two avenues: first, we examined the functional response of the aryl hydrocarbon receptor (Ahr), which is a molecular initiating event of many toxic effects of PAHs in biota. Chionodraco hamatus and Trematomus loennbergii served as representatives for high-Antarctic Notothenioids, and Atlantic cod, Gadus morhua as non-polar reference species. We sequenced and cloned the Ahr ligand binding domain (LBD) of the Notothenioids and deployed a GAL4-based luciferase reporter gene assay expressing the Ahr LBD. Benzo[a]pyrene (BaP), beta-naphthoflavone and chrysene were used as ligands for the reporter gene assay. Second, we investigated the energetic costs of Ahr activation in isolated liver cells of the Notothenioids during acute, non-cytotoxic BaP exposure. In the reporter assay, the Ahr LBD of Atlantic cod and the Antarctic Notothenioids were activated by the ligands tested herein. In the in vitro assays with isolated liver cells of high-Antarctic Notothenioids, BaP exposure had no effect on overall respiration, but caused shifts in the respiration dedicated to protein synthesis. Thus, our study demonstrated that high-Antarctic fish possess a functional Ahr that can be ligand-activated in a concentration-dependent manner by environmental contaminants. This is associated with altered cost for cellular protein synthesis. Future studies have to show if the toxicant-induced activation of the Ahr pathway may lead to altered organism performance of Antarctic fish.
Keywords: Sørishavet; fisker; marin zoologi; marinbiologi

Bioaccumulation of Per and Polyfluoroalkyl Substances in Antarctic Breeding South Polar Skuas (Catharacta maccormicki) and Their Prey - Alfaro Garcia, Laura Andrea; Descamps, Sébastien; Herzke, Dorte; Chastel, Olivier; Carravieri, Alice; Cherel, Yves; Labadie, Pierre; Budzinski, Hélène; Munoz, Gabriel; Bustamante, Paco; Polder, Anuschka; Gabrielsen, Geir Wing; et al. (Frontiers in Marine Science, 2022)
Per and polyfluoroalkyl substances (PFASs) are found in Antarctic wildlife, with high levels in the avian top predator south polar skua (Catharacta maccormicki). As increasing PFAS concentrations were found in the south polar skua during the breeding season in Antarctica, we hypothesised that available prey during the breeding period contributes significantly to the PFAS contamination in skuas. To test this, we compared PFAS in south polar skuas and their main prey from two breeding sites on opposite sides of the Antarctic continent: Antarctic petrel (Thalassoica antarctica) stomach content, eggs, chicks, and adults from Svarthamaren in Dronning Maud Land and Adélie penguin chicks (Pygoscelis adeliae) from Dumont d’Urville in Adélie Land. Of the 22 PFAS analysed, seven were present in the majority of samples, except petrel stomach content [only perfluoroundecanoate (PFUnA) present] and Adélie penguins (only four compounds present), with increasing concentrations from the prey to the skuas. The biomagnification factors (BMFs) were higher at Dumont d’Urville than Svarthamaren. When adjusted to reflect one trophic level difference, the BMFs at Svarthamaren remained the same, whereas the ones at Dumont d’Urville doubled. At both the colonies, the skua PFAS pattern was dominated by perfluorooctanesulfonic acid (PFOS), followed by PFUnA, but differed with the presence of branched PFOS and perfluorotetradecanoate (PFTeA) and lack of perfluorononanoate (PFNA) and perfluorodecanoate (PFDA) at Dumont d’Urville. At Svarthamaren, the pattern in the prey was comparable to the skuas, but with a higher relative contribution of PFTeA in prey. At Dumont d’Urville, the pattern in the prey differed from the skuas, with the domination of PFUnA and the general lack of PFOS in prey. Even though the PFAS levels are low in Antarctic year-round resident prey, the three lines of evidence (pattern, BMF difference, and BMF adjusted to one trophic level) suggest that the Antarctic petrel are the significant source of PFAS in the Svarthamaren skuas, whereas the skuas in Dumont d’Urville have other important sources to PFAS than Adélie penguin, either in the continent or external on the inter-breeding foraging grounds far from Antarctica.
Keywords: Antarktis; fugler; miljøgifter; økotoksikologi

Bioaccumulation of Per and Polyfluoroalkyl Substances in Antarctic Breeding South Polar Skuas (Catharacta maccormicki) and Their Prey - Alfaro Garcia, Laura Andrea; Descamps, Sébastien; Herzke, Dorte; Chastel, Olivier; Carravieri, Alice; Cherel, Yves; Labadie, Pierre; Budzinski, Hélène; Munoz, Gabriel; Bustamante, Paco; Polder, Anuschka; Gabrielsen, Geir Wing; et al. (Frontiers in Marine Science, 2022)
Per and polyfluoroalkyl substances (PFASs) are found in Antarctic wildlife, with high levels in the avian top predator south polar skua (Catharacta maccormicki). As increasing PFAS concentrations were found in the south polar skua during the breeding season in Antarctica, we hypothesised that available prey during the breeding period contributes significantly to the PFAS contamination in skuas. To test this, we compared PFAS in south polar skuas and their main prey from two breeding sites on opposite sides of the Antarctic continent: Antarctic petrel (Thalassoica antarctica) stomach content, eggs, chicks, and adults from Svarthamaren in Dronning Maud Land and Adélie penguin chicks (Pygoscelis adeliae) from Dumont d’Urville in Adélie Land. Of the 22 PFAS analysed, seven were present in the majority of samples, except petrel stomach content [only perfluoroundecanoate (PFUnA) present] and Adélie penguins (only four compounds present), with increasing concentrations from the prey to the skuas. The biomagnification factors (BMFs) were higher at Dumont d’Urville than Svarthamaren. When adjusted to reflect one trophic level difference, the BMFs at Svarthamaren remained the same, whereas the ones at Dumont d’Urville doubled. At both the colonies, the skua PFAS pattern was dominated by perfluorooctanesulfonic acid (PFOS), followed by PFUnA, but differed with the presence of branched PFOS and perfluorotetradecanoate (PFTeA) and lack of perfluorononanoate (PFNA) and perfluorodecanoate (PFDA) at Dumont d’Urville. At Svarthamaren, the pattern in the prey was comparable to the skuas, but with a higher relative contribution of PFTeA in prey. At Dumont d’Urville, the pattern in the prey differed from the skuas, with the domination of PFUnA and the general lack of PFOS in prey. Even though the PFAS levels are low in Antarctic year-round resident prey, the three lines of evidence (pattern, BMF difference, and BMF adjusted to one trophic level) suggest that the Antarctic petrel are the significant source of PFAS in the Svarthamaren skuas, whereas the skuas in Dumont d’Urville have other important sources to PFAS than Adélie penguin, either in the continent or external on the inter-breeding foraging grounds far from Antarctica.
Keywords: Antarktis; Dronning Maud Land; biologi; ornitologi; petreller; sjøfugler

Strong and lasting impacts of past global warming on baleen whales and their prey - Cabrera, Andrea A; Schall, Elena; Bérubé, Martine; Anderwald, Pia; Bachmann, Lutz; Berrow, Simon; Best, Peter B; Clapham, Phillip J; Cunha, Haydée A.; Dalla Rosa, Luciano; Dias, Carolina; Findlay, Kenneth P.; et al. (Global Change Biology, 2022)
Global warming is affecting the population dynamics and trophic interactions across a wide range of ecosystems and habitats. Translating these real-time effects into their long-term consequences remains a challenge. The rapid and extreme warming period that occurred after the Last Glacial Maximum (LGM) during the Pleistocene–Holocene transition (7–12 thousand years ago) provides an opportunity to gain insights into the long-term responses of natural populations to periods with global warming. The effects of this post-LGM warming period have been assessed in many terrestrial taxa, whereas insights into the impacts of rapid global warming on marine taxa remain limited, especially for megafauna. In order to understand how large-scale climate fluctuations during the post-LGM affected baleen whales and their prey, we conducted an extensive, large-scale analysis of the long-term effects of the post-LGM warming on abundance and inter-ocean connectivity in eight baleen whale and seven prey (fish and invertebrates) species across the Southern and the North Atlantic Ocean; two ocean basins that differ in key oceanographic features. The analysis was based upon 7032 mitochondrial DNA sequences as well as genome-wide DNA sequence variation in 100 individuals. The estimated temporal changes in genetic diversity during the last 30,000 years indicated that most baleen whale populations underwent post-LGM expansions in both ocean basins. The increase in baleen whale abundance during the Holocene was associated with simultaneous changes in their prey and climate. Highly correlated, synchronized and exponential increases in abundance in both baleen whales and their prey in the Southern Ocean were indicative of a dramatic increase in ocean productivity. In contrast, the demographic fluctuations observed in baleen whales and their prey in the North Atlantic Ocean were subtle, varying across taxa and time. Perhaps most important was the observation that the ocean-wide expansions and decreases in abundance that were initiated by the post-LGM global warming, continued for millennia after global temperatures stabilized, reflecting persistent, long-lasting impacts of global warming on marine fauna.
Keywords: Sørishavet; klimaendringer; marin biologi; polarområdene

The Impact of a Southern Ocean Cyclonic Eddy on Mesopelagic Micronekton - Della Penna, Alice; Llort, Joan; Moreau, Sebastien; Patel, Ramkrushnbhai; Kloser, Rudy; Gaube, Peter; Strutton, Peter; Boyd, Philip W (Journal of Geophysical Research: Oceans, 2022)
Mesoscale eddies shape the foraging ecology of predators such as marine mammals and seabirds. A growing number of animal tracking studies show that predators alter their swimming, diving, and foraging behavior within mesoscale eddies. However, little is known about how Southern Ocean eddies influence the distribution of mesopelagic micronekton (fish, squid, and crustaceans), which are major prey items of megafauna. Studies in other oceanic regions have found that eddies can influence the abundance and community composition of micronekton. Here, we analyze acoustic observations from a 14-day survey of a cyclonic mesoscale eddy, its surrounding waters, and the Polar Frontal Zone (PFZ) waters where the eddy formed. We report and interpret spatial patterns of acoustic backscatter at 18 and 75 kHz, proxies indicating combined changes in species, size, and abundance of micronekton. We find that the vertical distribution of acoustic backscatter matched the underwater light conditions characteristic of the eddy core, periphery, and surrounding waters, at scales smaller than 10 km. The median water-column integrated acoustic backscatter values in the eddy core were only half of those measured in the Sub-Antarctic Zone waters surrounding the eddy, but similar to those measured in the PFZ, where the eddy originated 27 days prior. These results suggest that, as for physical and chemical tracers, the eddy maintained its biological characteristics from its source waters creating a unique habitat compared to its surroundings.
Keywords: Sørishavet; marin biologi; oseanografi

Variation in Antarctic Petrel Foraging Ecology: Not All Individuals Specialize on Krill - Descamps, Sébastien; Harris, Stephanie; Fluhr, Julie; Bustamante, Paco; Cherel, Yves; Trevail, Alice; Brault-Favrou, Maud; Patrick, Samantha (Frontiers in Marine Science, 2022)
Individual heterogeneity in foraging behaviour determines how individuals and populations respond to changes in the availability and distribution of resources. Antarctic krill Euphausia superba is a pivotal species in Southern Ocean food webs and an important target for Southern Ocean fisheries. Changes in its abundance could dramatically impact marine predators, with effects depending on the extent to which all individuals rely on krill as prey. The Antarctic petrel Thalassoica antarctica is a high latitude seabird thought to be dependent on krill in part of its breeding range. Here, by combining fine-scale GPS tracking of petrel foraging trips with diet data, we examined the level and consistency of inter-individual variation in foraging strategies in breeding Antarctic petrels in Dronning Maud Land, Antarctica, and assessed whether all individuals share a similar reliance on Antarctic krill. We found that Antarctic petrels showed high levels of repeatability in their diet and foraging movements at sea, indicating consistent individual differences in foraging strategies. During consecutive foraging trips, petrels tend to make trips of similar lengths and durations to reach similar terminal locations and to feed on similar prey. These individual differences in diet were spatially structured, with individuals travelling towards the west consuming a more fish-based diet. These different foraging tactics did not appear to be associated with different costs and/or benefits as adult body mass, chick survival and chick growth were unrelated to birds’ foraging movements and diet. Our results show that, even if a large part of the population may be dependent on krill, some individuals specialize on fish. Such inter-individual variation in foraging suggests that this population could be more resilient to changes in the marine environment, such as a decline in krill abundance or a shift in krill distributions.
Keywords: Dronning Maud Land; biologi; ornitologi; petreller; sjøfugler; zoologi

Cavernous Decay of Granite and Granitic Gneiss, Central Dronning Maud Land, Antarctica - Engvik, Ane K; Elvevold, Synnøve; Myhre, Per Inge (The Journal of Geology, 2022)
Tafoni are a type of cavernous weathering that is found in a variety of rock types and locations around the world. Tafoni have been documented in a number of climatic zones ranging from hot and cold deserts to moist coastal environments. Despite the widespread distribution of tafoni, the major processes controlling tafoni weathering are not well understood and are still a matter of discussion. This study addresses the frequent distribution of well-developed tafoni in the cold, arid environment of the inland mountain range of central Dronning Maud Land, Antarctica. The aim is to document and characterize the nature of tafoni present in Gjelsvikfjella (2°E) eastward to Filchnerfjella (8°E) and to discuss formation processes. The cavities occur in groups and are typically spherical to oval shaped. They range in diameter and depth from 1 dm up to 1.5 m. The cold, arid environment of this region favors mechanical weathering mechanisms such as freeze-thaw actions and wind abrasion. Furthermore, the structural, textural, and mineralogical properties of the parent rock can potentially have a strong control on weathering and cavity development. Observed tafoni are typically formed in massive granitoid intrusives and granitic gneisses and migmatites. Chemical dissolution of pyroxene to iddingsite and radiation from rare earth element–bearing accessory minerals cause microfracturing, which facilitates freeze-thaw actions and accordingly enhances the weathering.
Keywords: Dronning Maud Land; geologi

Synthesis of field and satellite data to elucidate recent mass balance of five ice rises in Dronning Maud Land, Antarctica - Goel, Vikram; Morris, Ashley; Moholdt, Geir; Matsuoka, Kenichi (Frontiers in Earth Science, 2022)
We investigated mass balance changes over five ice rises in the last few decades near Fimbul and Nivl ice shelves in central Dronning Maud Land. We use the Input-Output Method constrained using field-based geophysical measurements conducted during the austral summers of 2012–14 over three ice rises near the Fimbul Ice Shelf. Further, we use satellite altimetry data (ICESat, ICESat-2, and CryoSat-2) to estimate geodetic mass balance over all five ice rises in recent decades. Both field- and satellite-based estimates show that until 2010, three out of five ice rises were thickening (0.4–0.2 m_ieq a^−1) while two were close to balance. However, over the last decade, the ice rises thickening previously started to thin (−0.2–−0.6 m_ieq a^−1) while the other two remained close to balance. Much of this variability is likely associated with regional surface mass balance trends, with each ice rise exhibiting its characteristics depending on its local glaciological settings.
Keywords: Dronning Maud Land; geofysikk; glasiologi

Reviews and syntheses: A framework to observe, understand and project ecosystem response to environmental change in the East Antarctic Southern Ocean - Gutt, Julian; Arndt, Stefanie; Barnes, David Keith Alan; Bornemann, Horst; Brey, Thomas; Eisen, Olaf; Flores, Hauke; Griffiths, Huw; Haas, Christian; Hain, Stefan; Hattermann, Tore; Held, Christoph; et al. (Biogeosciences (Online), 2022)
Systematic long-term studies on ecosystem dynamics are largely lacking from the East Antarctic Southern Ocean, although it is well recognized that they are indispensable to identify the ecological impacts and risks of environmental change. Here, we present a framework for establishing a long-term cross-disciplinary study on decadal timescales. We argue that the eastern Weddell Sea and the adjacent sea to the east, off Dronning Maud Land, is a particularly well suited area for such a study, since it is based on findings from previous expeditions to this region. Moreover, since climate and environmental change have so far been comparatively muted in this area, as in the eastern Antarctic in general, a systematic long-term study of its environmental and ecological state can provide a baseline of the current situation, which will be important for an assessment of future changes from their very onset, with consistent and comparable time series data underpinning and testing models and their projections. By establishing an Integrated East Antarctic Marine Research (IEAMaR) observatory, long-term changes in ocean dynamics, geochemistry, biodiversity, and ecosystem functions and services will be systematically explored and mapped through regular autonomous and ship-based synoptic surveys. An associated long-term ecological research (LTER) programme, including experimental and modelling work, will allow for studying climate-driven ecosystem changes and interactions with impacts arising from other anthropogenic activities. This integrative approach will provide a level of long-term data availability and ecosystem understanding that are imperative to determine, understand, and project the consequences of climate change and support a sound science-informed management of future conservation efforts in the Southern Ocean.
Publisher: Copernicus Publications
Keywords: Sørishavet; klimaendringer; miljøendringer; økosystemer

Ant-ICON - ‘Integrated Science to Inform Antarctic and Southern Ocean Conservation’: a new SCAR Scientific Research Programme - Hughes, Kevin A.; Santos, Mercedes; Caccavo, Jilda A.; Chignell, Stephen M.; Gardiner, Natasha B.; Gilbert, Neil; Howkins, Adrian; Van Vuuren, Bettine Jansen; Lee, Jasmine R.; Liggett, Daniela; Lowther, Andrew; Lynch, Heather; et al. (Antarctic Science, 2022)
Antarctic and Southern Ocean environments are facing increasing pressure from multiple threats. The Antarctic Treaty System regularly looks to the Scientific Committee on Antarctic Research (SCAR) for the provision of independent and objective advice based on the best available science to support decision-making, policy development and effective environmental management. The recently approved SCAR Scientific Research Programme Ant-ICON - ‘Integrated Science to Inform Antarctic and Southern Ocean Conservation‘ - facilitates and coordinates high-quality transdisciplinary research to inform the conservation and management of Antarctica, the Southern Ocean and the sub-Antarctic in the context of current and future impacts. The work of Ant-ICON focuses on three research themes examining 1) the current state and future projections of Antarctic systems, species and functions, 2) human impacts and sustainability and 3) socio-ecological approaches to Antarctic and Southern Ocean conservation, and one synthesis theme that seeks to facilitate the provision of timely scientific advice to support effective Antarctic conservation. Research outputs will address the most pressing environmental challenges facing Antarctica and offer high-quality science to policy and advisory bodies including the Antarctic Treaty Consultative Meeting, the Committee for Environmental Protection and the Scientific Committee of the Commission for the Conservation of Antarctic Marine Living Resources.
Edition: 2022/12/02 Publisher: Cambridge University Press
Keywords: Antarktis; Antarktistraktaten; Sørishavet; forvaltning; human impact; miljøvern

Intra-season variations in distribution and abundance of humpback whales in the West Antarctic Peninsula using cruise vessels as opportunistic platforms - Johannessen, John Elling Deehr; Biuw, Martin; Lindstrøm, Ulf; Ollus, Victoria Marja Sofia; Martín López, Lucía Martina; Gkikopoulou, Kalliopi C; Oosthuizen, Wessel Chris; Lowther, Andrew (Ecology and Evolution, 2022)
Fine-scale knowledge of spatiotemporal dynamics in cetacean distribution and abundance throughout the Western Antarctic Peninsula (WAP) is sparse yet essential for effective ecosystem-based management (EBM). Cruise vessels were used as platforms of opportunity to collect data on the distribution and abundance of humpback whales (Megaptera novaeangliae) during the austral summer of 2019/2020 in a region that is also important for the Antarctic krill (Euphausia superba) fishery, to assess potential spatiotemporal interactions for future use in EBM. Data were analyzed using traditional design-based line transect methodology and spatial density surface hurdle models fitted using a set of physical environmental covariates to estimate the abundance and distribution of whales in the area, and to describe their temporal dynamics. Our results indicate a rapid increase in humpback whale abundance in the Bransfield and Gerlache Straits through December, reaching a stable abundance by mid-January. The distribution of humpback whales appeared to change from a patchier distribution in the northern Gerlache Strait to a significantly concentrated presence in the central Gerlache and southern Bransfield Straits, followed by a subsequent dispersion throughout the area. Abundance estimates agreed well with previous literature, increasing from approximately 7000 individuals in 2000 to a peak of 19,107 in 2020. Based on these estimates, we project a total krill consumption of between 1.4 and 3.7 million tons based on traditional and contemporary literature on per capita krill consumption of whales, respectively. When taken in the context of krill fishery catch data in the study area, we conclude that there is minimal spatiotemporal overlap between humpback whales and fishery activity during our study period of November–January. However, there is potential for significant interaction between the two later in the feeding season, but cetacean survey efforts need to be extended into late season in order to fully characterize this potential overlap.
Keywords: Sørishavet; hvaler; marin biologi

Bycatch in the Antarctic krill (Euphausia superba) trawl fishery - Krafft, Bjørn A.; Lowther, Andrew; Krag, Ludvig A. (Fisheries Management and Ecology, 2022)
Bycatch of nontarget species can contribute to overfishing and slow efforts to rebuild fish stocks. Controlling bycatch is fundamental to sustainable fishing and maintaining healthy populations of target species. The Antarctic krill (Euphausia superba) fishery is the largest volume fishery in the Southern Ocean. Understanding the significance of bycatch and its diversity is critical to managing this keystone species. Registered bycatch data from the Antarctic krill fishery in the southwest Atlantic sector of the Southern Ocean were analysed. Observers collected data following an internationally agreed method during the 2010–2020 fishing seasons, with a 20 (± 9) % coverage of fishing activity of Total catch of Antarctic krill which increased from 200,000 tonnes to 450,000 tonnes, with the greatest increase over the last 3 years. Except in 2010 (2.2%), the bycatch ratio was stable and ranged 0.1–0.3%. Fish dominated the bycatch, followed by tunicates and other crustaceans. Observer coverage was high, and bycatch levels were generally low across gear types. Given that accurate information on bycatch is important for sustaining developing fisheries, maintaining high observer coverage of this fishery will be important for detecting impacts from a warming climate and for moving back into historical fishing grounds.
Keywords: Sørishavet; fiskeri; krill; plankton

A review of the scientific knowledge of the seascape off Dronning Maud Land, Antarctica - Lowther, Andrew; von Quillfeldt, Cecilie; Assmy, Philipp; De Steur, Laura; Descamps, Sebastien; Divine, Dmitry; Elvevold, Synnøve; Forwick, Matthias; Fransson, Agneta; Fraser, Alexander; Gerland, Sebastian; Granskog, Mats; et al. (Polar Biology, 2022)
Despite the exclusion of the Southern Ocean from assessments of progress towards achieving the Convention on Biological Diversity (CBD) Strategic Plan, the Commission for the Conservation of Antarctic Marine Living Resources (CCAMLR) has taken on the mantle of progressing efforts to achieve it. Within the CBD, Aichi Target 11 represents an agreed commitment to protect 10% of the global coastal and marine environment. Adopting an ethos of presenting the best available scientific evidence to support policy makers, CCAMLR has progressed this by designating two Marine Protected Areas in the Southern Ocean, with three others under consideration. The region of Antarctica known as Dronning Maud Land (DML; 20°W to 40°E) and the Atlantic sector of the Southern Ocean that abuts it conveniently spans one region under consideration for spatial protection. To facilitate both an open and transparent process to provide the vest available scientific evidence for policy makers to formulate management options, we review the body of physical, geochemical and biological knowledge of the marine environment of this region. The level of scientific knowledge throughout the seascape abutting DML is polarized, with a clear lack of data in its eastern part which is presumably related to differing levels of research effort dedicated by national Antarctic programmes in the region. The lack of basic data on fundamental aspects of the physical, geological and biological nature of eastern DML make predictions of future trends difficult to impossible, with implications for the provision of management advice including spatial management. Finally, by highlighting key knowledge gaps across the scientific disciplines our review also serves to provide guidance to future research across this important region.
Keywords: Dronning Maud Land; Sørishavet; biofysikk; biogeokjemi; biologi; oseanografi

The influence of energetic particle precipitation on Antarctic stratospheric chlorine and ozone over the 20th century - Maliniemi, V.; Arsenovic, P.; Seppälä, A.; Nesse Tyssøy, H. (Atmospheric Chemistry and Physics, 2022)
Keywords: Antarktis; kjemi; ozon; stratosfæren

Foraging behaviour of sympatrically breeding macaroni (Eudyptes chrysolophus) and chinstrap (Pygoscelis antarcticus) penguins at Bouvetøya, Southern Ocean - Narvestad, Audun; Kovacs, Kit M.; Lydersen, Christian; Lowther, Andrew D. (Polar Research, 2022)
Species with similar ecological requirements that overlap in range tend to segregate their niches to minimize competition for resources. However, the niche segregation possibilities for centrally foraging predators that breed on isolated Subantarctic islands may be reduced by spatial constraints and limitations in the availability of alternative prey. In this study we examined spatial and trophic aspects of the foraging niches of two sympatrically breeding penguin species, macaroni (Eudyptes chrysolophus; MAC) and chinstrap (Pygoscelis antarcticus; CHIN) penguins, at Bouvetøya over two breeding seasons. To measure at-sea movements and diving behaviour, 90 MACs and 49 CHINs were equipped with GPS loggers and dive recorders during two austral summer breeding seasons (2014/15 and 2017/18). In addition, blood samples from tracked birds were analysed for stable isotopes to obtain dietary information. CHINs displayed marked interannual variation in foraging behaviour, diving deeper, utilizing a larger foraging area and displaying enriched values of δ15N in 2014/15 compared to the 2017/18 breeding season. In contrast, MACs dove to similar depths and showed similar δ15N values, while consistently utilizing larger foraging areas compared to CHINs. We suggest that low krill abundances in the waters around Bouvetøya during the 2014/15 season resulted in CHINs shifting toward a diet that increased their niche overlap with MACs. Our findings may partly explain the decreasing number of breeding CHINs at the world’s most remote island, Bouvetøya, while also highlighting the importance of characterizing niche overlap of species using multi-season data sets.
Keywords: Bouvetøya; NARE ekspedisjoner; biotelemetri; marin biologi; pingviner

Experimental warming increases fungal alpha diversity in an oligotrophic maritime Antarctic soil - Newsham, Kevin K.; Misiak, Marta; Goodall-Copestake, William P.; Dahl, Malin Stapnes; Boddy, Lynne; Hopkins, David W.; Davey, Marie L. (Frontiers in Microbiology, 2022)
The climate of maritime Antarctica has altered since the 1950s. However, the effects of increased temperature, precipitation and organic carbon and nitrogen availability on the fungal communities inhabiting the barren and oligotrophic fellfield soils that are widespread across the region are poorly understood. Here, we test how warming with open top chambers (OTCs), irrigation and the organic substrates glucose, glycine and tryptone soy broth (TSB) influence a fungal community inhabiting an oligotrophic maritime Antarctic fellfield soil. In contrast with studies in vegetated soils at lower latitudes, OTCs increased fungal community alpha diversity (Simpson’s index and evenness) by 102–142% in unamended soil after 5 years. Conversely, OTCs had few effects on diversity in substrate-amended soils, with their only main effects, in glycine-amended soils, being attributable to an abundance of Pseudogymnoascus. The substrates reduced alpha and beta diversity metrics by 18–63%, altered community composition and elevated soil fungal DNA concentrations by 1–2 orders of magnitude after 5 years. In glycine-amended soil, OTCs decreased DNA concentrations by 57% and increased the relative abundance of the yeast Vishniacozyma by 45-fold. The relative abundance of the yeast Gelidatrema declined by 78% in chambered soil and increased by 1.9-fold in irrigated soil. Fungal DNA concentrations were also halved by irrigation in TSB-amended soils. In support of regional- and continental-scale studies across climatic gradients, the observations indicate that soil fungal alpha diversity in maritime Antarctica will increase as the region warms, but suggest that the accumulation of organic carbon and nitrogen compounds in fellfield soils arising from expanding plant populations are likely, in time, to attenuate the positive effects of warming on diversity.
Keywords: Antarktis; kjemi; klimaendringer; mikrobiologi; sopper

Distribution and export of particulate organic carbon in East Antarctic coastal polynyas - Ratnarajah, Lavenia; Puigcorbé, Viena; Moreau, Sébastien; Roca-Martí, Montserrat; Janssens, Julie; Corkill, Matthew; Duprat, Luis; Genovese, Cristina; Lieser, Jan; Masqué, Pere; Lannuzel, Delphine (Deep Sea Research Part I: Oceanographic Research Papers, 2022)
Polynyas represent regions of enhanced primary production because of the low, or absent, sea-ice cover coupled with the proximity of nutrient sources. However, studies throughout the Southern Ocean suggest elevated primary production does not necessarily result in increased carbon export. Three coastal polynyas in East Antarctica and an off-shelf region were visited during the austral summer from December 2016 to January 2017 to examine the vertical distribution and concentration of particulate organic carbon (POC). Carbon export was also examined using thorium-234 (234Th) as a proxy at two of the polynyas. Our results show that concentrations and integrated POC stocks were higher within the polynyas compared to the off-shelf sites. Within the polynyas, vertical POC concentrations were higher in the Mertz and Ninnis polynyas compared to the Dalton polynya. Similarly, higher carbon export was measured in the diatom-dominated Mertz polynya, where large particles (>53 μm) represented a significant fraction of the particulate 234Th and POC (average 50% and 39%, respectively), compared to the small flagellate-dominated Dalton polynya, where almost all the particulate 234Th and POC were found in the smaller size fraction (1–53 μm). The POC to Chlorophyll-a ratios suggest that organic matter below the mixed layer in the polynyas consisted largely of fresh phytoplankton at this time of the year. In combination with a parallel study on phytoplankton production at these sites, we find that increased primary production at these polynyas does lead to greater concentrations and export of POC and a higher POC export efficiency.
Keywords: Sørishavet; marin biologi; oseanografi

Evaluation of Temperature-Dependent Complex Refractive Indices of Supercooled Liquid Water Using Downwelling Radiance and In-Situ Cloud Measurements at South Pole - Rowe, Penny M; Walden, Von P; Brandt, Richard E; Town, Michael S; Hudson, Stephen R; Neshyba, Steven (Journal of Geophysical Research: Atmospheres, 2022)
Clouds have a large effect on the radiation budget and represent a major source of uncertainty in climate models. Supercooled liquid clouds can exist at temperatures as low as 235 K, and the radiative effect of these clouds depends on the complex refractive index (CRI) of liquid water. Laboratory measurements have demonstrated that the liquid-water CRI is temperature-dependent, but corroboration with field measurements is difficult. Here we present measurements of the downwelling infrared radiance and in-situ measurements of supercooled liquid water in a cloud at temperatures as low as 240 K, made at South Pole Station in 2001. These results demonstrate that including the temperature dependence of the liquid-water CRI is essential for accurate calculations of radiative transfer through supercooled liquid clouds. Furthermore, we show that when cloud properties are retrieved from infrared radiances (using the spectral range 500–1,200 cm−1) spurious ice may be retrieved if the 300 K CRI is used for cold liquid clouds (∼240 K). These results have implications for radiative transfer in climate models as well as for retrievals of cloud properties from infrared radiance spectra.
Keywords: Antarktis; Sydpolen; atmosfæren; geofysikk; klimamodeller

Allometric relationships of ecologically important Antarctic and Arctic zooplankton and fish species - Schaafsma, Fokje L.; David, Carmen L.; Kohlbach, Doreen; Ehrlich, Julia; Castellani, Giulia; Lange, Benjamin A.; Vortkamp, Martina; Meijboom, André; Fortuna-Wünsch, Anna; Immerz, Antonia; Cantzler, Hannelore; Klasmeier, Apasiri; et al. (Polar Biology, 2022)
Allometric relationships between body properties of animals are useful for a wide variety of purposes, such as estimation of biomass, growth, population structure, bioenergetic modelling and carbon flux studies. This study summarizes allometric relationships of zooplankton and nekton species that play major roles in polar marine food webs. Measurements were performed on 639 individuals of 15 species sampled during three expeditions in the Southern Ocean (winter and summer) and 2374 individuals of 14 species sampled during three expeditions in the Arctic Ocean (spring and summer). The information provided by this study fills current knowledge gaps on relationships between length and wet/dry mass of understudied animals, such as various gelatinous zooplankton, and of animals from understudied seasons and maturity stages, for example, for the krill Thysanoessa macrura and larval Euphausia superba caught in winter. Comparisons show that there is intra-specific variation in length–mass relationships of several species depending on season, e.g. for the amphipod Themisto libellula. To investigate the potential use of generalized regression models, comparisons between sexes, maturity stages or age classes were performed and are discussed, such as for the several krill species and T. libellula. Regression model comparisons on age classes of the fish E. antarctica were inconclusive about their general use. Other allometric measurements performed on carapaces, eyes, heads, telsons, tails and otoliths provided models that proved to be useful for estimating length or mass in, e.g. diet studies. In some cases, the suitability of these models may depend on species or developmental stages.
Keywords: Sørishavet; biomasse; dyreplankton; fisker; marin biologi; marin økologi; polarområdene; zooplankton

Spatial and interspecific variation of accumulated highly toxic trace elements between fifteen bird species feathers from Antarctic, Arctic and China - Sun, Yayue; Lu, Zhibo; Xiao, Kaiyan; Zeng, Lingyun; Wang, Juan; Zhang, Yanyun; Gabrielsen, Geir Wing (Environmental Technology & Innovation, 2022)
To assess the impact of human activities and other factors on the levels of highly toxic trace elements in the environment, the contents of eight highly toxic trace elements (arsenic (As), cadmium (Cd), chromium (Cr), copper (Cu), mercury (Hg), nickel (Ni), lead (Pb) and zinc (Zn)) in feathers of 15 bird species from the Prydz Bay region in the Antarctic, Ny-Alsund region in the Arctic, and eastern China were evaluated in this study. Results showed that feathers collected from the Antarctic showed the highest As, Cu, and Hg contents (1.65–2.85, 9.58–18.56, and 4.77–8.76 μg/g dw, respectively) of the different study areas, whereas Arctic feathers exhibited the highest mean Pb levels (1.82–3.19 μg/g dw), and feathers from China showed significantly lower accumulations of Cr, Ni, Pb, and Zn compared with the other two areas. Overall, most of the studied highly toxic trace element contents in bird feathers from the densely populated and polluted area of eastern China were lower than those from remote polar regions, which are negligibly affected by human activities. In addition, feathers from the Arctic did not show higher highly toxic trace element contents than those of the more remote Antarctic. These results are thus inferred to reflect differences in the dietary structure of birds in the different habitats, as well as historical climate change. Carbon (δ13C) and nitrogen (δ15N) stable isotope ratios of feathers were also measured to evaluate the relationship between diet and highly toxic trace elements. Results showed that highly toxic trace element contents did not increase with increasing trophic levels. Moreover, the methylmercury content accounted for 87.57%–98.59% of the total mercury in all feather samples, regardless of location and species, confirming that most of the mercury entering the feathers is methylated. This finding suggests that the form of mercury changes during the process of transference from internal tissues to feathers, which improves our understanding of the mechanism by which feathers excrete mercury, this behavior greatly reduces the harm to bird health caused by mercury. This study confirms that measuring contaminants in feathers is a long-term and effective method for monitoring highly toxic trace elements pollution in particular environments, making future monitoring of highly toxic trace elements pollution in the polar regions, as well as more typical environments, more convenient.
Keywords: Antarktis; miljøgifter; polarområdene; sjøfugler; økotoksikologi

Geologisk feltarbeid i Antarktis - Sunde, Øyvind; Elvevold, Synnøve; Engvik, Ane K.; Tholfsen, Audun (Geonytt : et medlemsblad for Norsk geologisk forening, 2022)
Dronning Maud Land, som er Norges territoriale krav i Antarktis, utgjør nærmere 1/6 av det antarktiske kontinentet. Geologisk kartlegging og forskning i Dronning Maud Land er en nasjonal oppgave og i Antarktis-sammenheng kan det betraktes som en måte å vise fortsatt interesse i Norges territoriale krav.
Publisher: Norsk Geologisk Forening
Keywords: Dronning Maud Land; geologi

Aerosol optical properties calculated from size distributions, filter samples and absorption photometer data at Dome C, Antarctica, and their relationships with seasonal cycles of sources - Virkkula, A.; Grythe, H.; Backman, J.; Petäjä, T.; Busetto, M.; Lanconelli, C.; Lupi, A.; Becagli, S.; Traversi, R.; Severi, M.; Vitale, V.; Sheridan, P.; et al. (Atmospheric Chemistry and Physics, 2022)
Keywords: Antarktis; atmosfæren; forurensning

Evaluation of an emergent feature of sub-shelf melt oscillations from an idealized coupled ice sheet–ocean model using FISOC (v1.1) – ROMSIceShelf (v1.0) – Elmer/Ice (v9.0) - Zhao, Chen; Gladstone, Rupert; Galton-Fenzi, Benjamin Keith; Gwyther, David; Hattermann, Tore (Geosci. Model Dev., 2022)
Changes in ocean-driven basal melting have a key influence on the stability of ice shelves, the mass loss from the ice sheet, ocean circulation, and global sea level rise. Coupled ice sheet–ocean models play a critical role in understanding future ice sheet evolution and examining the processes governing ice sheet responses to basal melting. However, as a new approach, coupled ice sheet–ocean systems come with new challenges, and the impacts of solutions implemented to date have not been investigated. An emergent feature in several contributing coupled models to the 1st Marine Ice Sheet–Ocean Model Intercomparison Project (MISOMIP1) was a time-varying oscillation in basal melt rates. Here, we use a recently developed coupling framework, FISOC (v1.1), to connect the modified ocean model ROMSIceShelf (v1.0) and ice sheet model Elmer/Ice (v9.0), to investigate the origin and implications of the feature and, more generally, the impact of coupled modeling strategies on the simulated basal melt in an idealized ice shelf cavity based on the MISOMIP setup. We found the spatial-averaged basal melt rates (3.56 m yr−1) oscillated with an amplitude ∼0.7 m yr−1 and approximate period of ∼6 years between year 30 and 100 depending on the experimental design. The melt oscillations emerged in the coupled system and the standalone ocean model using a prescribed change of cavity geometry. We found that the oscillation feature is closely related to the discretized ungrounding of the ice sheet, exposing new ocean, and is likely strengthened by a combination of positive buoyancy–melt feedback and/or melt–geometry feedback near the grounding line, and the frequent coupling of ice geometry and ocean evolution. Sensitivity tests demonstrate that the oscillation feature is always present, regardless of the choice of coupling interval, vertical resolution in the ocean model, tracer properties of cells ungrounded by the retreating ice sheet, or the dependency of friction velocities to the vertical resolution. However, the amplitude, phase, and sub-cycle variability of the oscillation varied significantly across the different configurations. We were unable to ultimately determine whether the feature arises purely due to numerical issues (related to discretization) or a compounding of multiple physical processes amplifying a numerical artifact. We suggest a pathway and choices of physical parameters to help other efforts understand the coupled ice sheet–ocean system using numerical models.
Publisher: Copernicus Publications
Keywords: Antarktis; Sørishavet; glasiologi; havnivåstigning; innlandsis; oseanografi

Banded Charnockite: The Result of Crustal Magma Generation, Piecemeal Emplacement, and Fluid-Driven Mineral Replacement in High-Grade Crust (Central Dronning Maud Land, Antarctica) - Engvik, Ane K.; Corfu, Fernando; Kleinhanns, Ilka C.; Elvevold, Synnøve (The Journal of Geology, 2021)
AbstractOur study of a banded charnockite complex of the Mühlig-Hofmannfjella in Dronning Maud Land, Antarctica, illustrates how the combination of high-temperature (re-)crystallization processes, melts, and volatile fluids leads to complex intrusive, metasomatic, and structural relationships. The igneous complex consists of gently dipping sets of charnockite interlayered with dolerite and leucogranite. The banded complex formed primarily by magmatic processes, but with superimposed modifications by metasomatism. The charnockite has a ferroan composition and contains both orthopyroxene (Fs80?84) and olivine (Fa94?96). Zircon U-Pb dates the emplacement of charnockite at 515 Ma, and inherited zircon cores and negative εNd values of ?3 to ?5 indicate that the age of the source of the magma was about 1100 Ma. Neodymium isotopes were not homogenized during the Cambrian magmatic event, which suggests that the generation and emplacement of the magma took place in separate batches during construction of the banded complex. By contrast, the Rb-Sr system in the charnockite was extensively homogenized, likely because of the superimposed late-magmatic fluid activity, which also produced the bands and networks of leucogranites. These events occurred during the late stages of the assembly of Gondwana, with postcollisional extension and mantle upwelling maintaining a high heat flow.
Publisher: The University of Chicago Press
Keywords: Dronning Maud Land; geologi

Observed interannual changes beneath Filchner-Ronne Ice Shelf linked to large-scale atmospheric circulation - Hattermann, Tore; Nicholls, Keith W.; Hellmer, Hartmut H.; Davis, Peter E. D.; Janout, Markus A.; Østerhus, Svein; Schlosser, Elisabeth; Rohardt, Gerd; Kanzow, Torsten (Nature Communications, 2021)
Floating ice shelves are the Achilles’ heel of the Antarctic Ice Sheet. They limit Antarctica’s contribution to global sea level rise, yet they can be rapidly melted from beneath by a warming ocean. At Filchner-Ronne Ice Shelf, a decline in sea ice formation may increase basal melt rates and accelerate marine ice sheet mass loss within this century. However, the understanding of this tipping-point behavior largely relies on numerical models. Our new multi-annual observations from five hot-water drilled boreholes through Filchner-Ronne Ice Shelf show that since 2015 there has been an intensification of the density-driven ice shelf cavity-wide circulation in response to reinforced wind-driven sea ice formation in the Ronne polynya. Enhanced southerly winds over Ronne Ice Shelf coincide with westward displacements of the Amundsen Sea Low position, connecting the cavity circulation with changes in large-scale atmospheric circulation patterns as a new aspect of the atmosphere-ocean-ice shelf system.
Keywords: Antarktis; Sørishavet; glasiologi; isshelf; meteorologi; oseanografi

The effectiveness of Virkon® S disinfectant against an invasive insect and implications for Antarctic biosecurity practices - Bartlett, Jesamine C; Radcliffe, Richard James; Convey, Pete; Hughes, Kevin A; Hayward, Scott A L (Antarctic Science, 2021)
The flightless midge Eretmoptera murphyi is thought to be continuing its invasion of Signy Island via the treads of personnel boots. Current boot-wash biosecurity protocols in the Antarctic region rely on microbial biocides, primarily Virkon® S. As pesticides have limited approval for use in the Antarctic Treaty area, we investigated the efficacy of Virkon® S in controlling the spread of E. murphyi using boot-wash simulations and maximum threshold exposures. We found that E. murphyi tolerates over 8 h of submergence in 1% Virkon® S. Higher concentrations increased effectiveness, but larvae still exhibited > 50% survival after 5 h in 10% Virkon® S. Salt and hot water treatments (without Virkon® S) were explored as possible alternatives. Salt water proved ineffective, with mortality only in first-instar larvae across multi-day exposures. Larvae experienced 100% mortality when exposed for 10 s to 50°C water, but they showed complete survival at 45°C. Given that current boot-wash protocols alone are an ineffective control of this invasive insect, we advocate hot water (> 50°C) to remove soil, followed by Virkon® S as a microbial biocide on ‘clean’ boots. Implications for the spread of invasive invertebrates as a result of increased human activity in the Antarctic region are discussed.
Publisher: Cambridge University Press
Keywords: Antarktis; biologi; biosikkerhet; fjærmygg; forurensning; klimaendringer; miljøpåvirkning; økologi; økosystemer

Brominated Flame Retardants in Antarctic Air in the Vicinity of Two All-Year Research Stations - Bengtson Nash, Susan Maria; Wild, Seanan; Broomhall, Sara; Bohlin-Nizzetto, Pernilla (Atmosphere, 2021)
Continuous atmospheric sampling was conducted between 2010–2015 at Casey station in Wilkes Land, Antarctica, and throughout 2013 at Troll Station in Dronning Maud Land, Antarctica. Sample extracts were analyzed for polybrominated diphenyl ethers (PBDEs), and the naturally converted brominated compound, 2,4,6-Tribromoanisole, to explore regional profiles. This represents the first report of seasonal resolution of PBDEs in the Antarctic atmosphere, and we describe conspicuous differences in the ambient atmospheric concentrations of brominated compounds observed between the two stations. Notably, levels of BDE-47 detected at Troll station were higher than those previously detected in the Antarctic or Southern Ocean region, with a maximum concentration of 7800 fg/m3. Elevated levels of penta-formulation PBDE congeners at Troll coincided with local building activities and subsided in the months following completion of activities. The latter provides important information for managers of National Antarctic Programs for preventing the release of persistent, bioaccumulative, and toxic substances in Antarctica.
Keywords: Dronning Maud Land; Troll forskningsstasjon; atmosfæren; menneskelig påvirkning; miljøgifter; miljøovervåking; målinger

First discrete iron(II) records from Dome C (Antarctica) and the Holtedahlfonna glacier (Svalbard) - Burgay, François; Barbaro, Elena; Cappelletti, David; Turetta, Clara; Gallet, Jean-Charles; Isaksson, Elisabeth; Stenni, Barbara; Dreossi, Giuliano; Scoto, Federico; Barbante, Carlo; Spolaor, Andrea (Chemosphere, 2021)
Fe(II) is more soluble and bioavailable than Fe(III) species, therefore the investigation of their relative abundance and redox processes is relevant to better assess the supply of bioavailable iron to the ocean and its impact on marine productivity. In this context, we present a discrete chemiluminescence-based method for the determination of Fe(II) in firn matrices. The method was applied on discrete samples from a snow pit collected at Dome C (DC, Antarctica) and on a shallow firn core from the Holtedahlfonna glacier (HDF, Svalbard), providing the first Fe(II) record from both Antarctica and Svalbard. The method showed low detection limits (0.006 ng g−1 for DC and 0.003 ng g−1 for the HDF) and a precision ranging from 3% to 20% RSD. Fe(II) concentrations ranged between the LoD and 0.077 ng g−1 and between the LoD and 0.300 ng g−1 for the Antarctic and Arctic samples, respectively. The Fe(II) contribution with respect to the total dissolved Fe was comparable in both sites accounting, on average, for 5% and 3%, respectively. We found that Fe(II) correctly identified the Pinatubo/Cerro Hudson eruption in the DC record, demonstrating its reliability as volcanic tracer, while, on the HDF core, we provided the first preliminary insight on the processes that might influence Fe speciation in firn matrices (i.e. organic ligands and pH influences).
Keywords: Antarktis; glasiologi; kjemi; polarområdene

Trophic and fitness correlates of mercury and organochlorine compound residues in egg-laying Antarctic petrels - Carravieri, Alice; Warner, Nicholas A; Herzke, Dorte; Brault-Favrou, Maud; Tarroux, Arnaud; Fort, Jérôme; Bustamante, Paco; Descamps, Sébastien (Environmental Research, 2021)
Understanding the drivers and effects of exposure to contaminants such as mercury (Hg) and organochlorine compounds (OCs) in Antarctic wildlife is still limited. Yet, Hg and OCs have known physiological and fitness effects in animals, with consequences on their populations. Here we measured total Hg (a proxy of methyl-Hg) in blood cells and feathers, and 12 OCs (seven polychlorinated biphenyls, PCBs, and five organochlorine pesticides, OCPs) in plasma of 30 breeding female Antarctic petrels Thalassoica antarctica from one of the largest colonies in Antarctica (Svarthamaren, Dronning Maud Land). This colony is declining and there is poor documentation on the potential role played by contaminants on individual physiology and fitness. Carbon (δ13C) and nitrogen (δ15N) stable isotope values measured in the females' blood cells and feathers served as proxies of their feeding ecology during the pre-laying (austral spring) and moulting (winter) periods, respectively. We document feather Hg concentrations (mean ± SD, 2.41 ± 0.83 μg g−1 dry weight, dw) for the first time in this species. Blood cell Hg concentrations (1.38 ± 0.43 μg g−1 dw) were almost twice as high as those reported in a recent study, and increased with pre-laying trophic position (blood cell δ15N). Moulting trophic ecology did not predict blood Hg concentrations. PCB concentrations were very low (Σ7PCBs, 0.35 ± 0.31 ng g−1 wet weight, ww). Among OCPs, HCB (1.02 ± 0.36 ng g−1 ww) and p, p’-DDE (1.02 ± 1.49 ng g−1 ww) residues were comparable to those of ecologically-similar polar seabirds, while Mirex residues (0.72 ± 0.35 ng g−1 ww) were higher. PCB and OCP concentrations showed no clear relationship with pre-laying or moulting feeding ecology, indicating that other factors overcome dietary drivers. OC residues were inversely related to body condition, suggesting stronger release of OCs into the circulation of egg-laying females upon depletion of their lipid reserves. Egg volume, hatching success, chick body condition and survival were not related to maternal Hg or OC concentrations. Legacy contaminant exposure does not seem to represent a threat for the breeding fraction of this population over the short term. Yet, exposure to contaminants, especially Mirex, and other concurring environmental stressors should be monitored over the long-term in this declining population.
Keywords: Dronning Maud Land; forurensning; miljøendringer; miljøgifter; ornitologi; petreller; sjøfugler

Multi-decadal trends in Antarctic sea-ice extent driven by ENSO–SAM over the last 2,000 years - Crosta, Xavier; Etourneau, Johan; Orme, Lisa C; Dalaiden, Quentin; Campagne, Philippine; Swingedouw, Didier; Goosse, Hugues; Massé, Guillaume; Miettinen, Arto; McKay, Robert M; Dunbar, Robert B; Escutia, Carlota; et al. (Nature Geoscience, 2021)
Antarctic sea ice has paradoxically become more extensive over the past four decades despite a warming climate. The regional expression of this trend has been linked to changes in vertical redistribution of ocean heat and large-scale wind-field shifts. However, the short length of modern observations has hindered attempts to attribute this trend to anthropogenic forcing or natural variability. Here, we present two new decadal-resolution records of sea ice and sea surface temperatures that document pervasive regional climate heterogeneity in Indian Antarctic sea-ice cover over the last 2,000 years. Data assimilation of our marine records in a climate model suggests that the reconstructed dichotomous regional conditions were driven by the multi-decadal variability of the El Niño Southern Oscillation and Southern Annular Mode (SAM). For example, during an El Niño/SAM– combination, the northward sea-ice transport was reduced while heat advection from the subtropics to the Southern Ocean increased, which resulted in reduced sea-ice extent in the Indian sector as sea ice was compacted along the Antarctic coast. Our results therefore indicate that natural variability is large in the Southern Ocean and suggest that it has played a crucial role in the recent sea-ice trends and their decadal variability in this region.
Keywords: Sørishavet; havis; klimaendringer; klimamodeller; sjøis

Decline in body condition in the Antarctic minke whale (Balaenoptera bonaerensis) in the Southern Ocean during the 1990s - Cunen, Céline; Walløe, Lars; Konishi, Kenji; Hjort, Nils Lid (Polar Biology, 2021)
Keywords: Sørishavet; hvaler; krill; marin biologi

Sea-ice habitat minimizes grazing impact and predation risk for larval Antarctic krill - David, Carmen L; Schaafsma, Fokje L; van Franeker, Jan A; Pakhomov, Evgeny A; Hunt, Brian P V; Lange, Benjamin A; Castellani, Giulia; Brandt, Angelika; Flores, Hauke (Polar Biology, 2021)
Survival of larval Antarctic krill (Euphausia superba) during winter is largely dependent upon the presence of sea ice as it provides an important source of food and shelter. We hypothesized that sea ice provides additional benefits because it hosts fewer competitors and provides reduced predation risk for krill larvae than the water column. To test our hypothesis, zooplankton were sampled in the Weddell-Scotia Confluence Zone at the ice-water interface (0–2 m) and in the water column (0–500 m) during August–October 2013. Grazing by mesozooplankton, expressed as a percentage of the phytoplankton standing stock, was higher in the water column (1.97 ± 1.84%) than at the ice-water interface (0.08 ± 0.09%), due to a high abundance of pelagic copepods. Predation risk by carnivorous macrozooplankton, expressed as a percentage of the mesozooplankton standing stock, was significantly lower at the ice-water interface (0.83 ± 0.57%; main predators amphipods, siphonophores and ctenophores) than in the water column (4.72 ± 5.85%; main predators chaetognaths and medusae). These results emphasize the important role of sea ice as a suitable winter habitat for larval krill with fewer competitors and lower predation risk. These benefits should be taken into account when considering the response of Antarctic krill to projected declines in sea ice. Whether reduced sea-ice algal production may be compensated for by increased water column production remains unclear, but the shelter provided by sea ice would be significantly reduced or disappear, thus increasing the predation risk on krill larvae.
Keywords: Sørishavet; krill; marin biologi; zooplankton

Interactive effects of body mass changes and species-specific morphology on flight behavior of chick-rearing Antarctic fulmarine petrels under diurnal wind patterns - Dehnhard, Nina; Klekociuk, Andrew R; Emmerson, Louise (Ecology and Evolution, 2021)
For procellariiform seabirds, wind and morphology are crucial determinants of flight costs and flight speeds. During chick-rearing, parental seabirds commute frequently to provision their chicks, and their body mass typically changes between outbound and return legs. In Antarctica, the characteristic diurnal katabatic winds, which blow stronger in the mornings, form a natural experimental setup to investigate flight behaviors of commuting seabirds in response to wind conditions. We GPS-tracked three closely related species of sympatrically breeding Antarctic fulmarine petrels, which differ in wing loading and aspect ratio, and investigated their flight behavior in response to wind and changes in body mass. Such information is critical for understanding how species may respond to climate change. All three species reached higher ground speeds (i.e., the speed over ground) under stronger tailwinds, especially on return legs from foraging. Ground speeds decreased under stronger headwinds. Antarctic petrels (Thalassoica antarctica; intermediate body mass, highest wing loading, and aspect ratio) responded stronger to changes in wind speed and direction than cape petrels (Daption capense; lowest body mass, wing loading, and aspect ratio) or southern fulmars (Fulmarus glacialoides; highest body mass, intermediate wing loading, and aspect ratio). Birds did not adjust their flight direction in relation to wind direction nor the maximum distance from their nests when encountering headwinds on outbound commutes. However, birds appeared to adjust the timing of commutes to benefit from strong katabatic winds as tailwinds on outbound legs and avoid strong katabatic winds as headwinds on return legs. Despite these adaptations to the predictable diurnal wind conditions, birds frequently encountered unfavorably strong headwinds, possibly as a result of weather systems disrupting the katabatics. How the predicted decrease in Antarctic near-coastal wind speeds over the remainder of the century will affect flight costs and breeding success and ultimately population trajectories remains to be seen.
Keywords: Antarktis; fôring; klimaendringer; ornitologi; petreller; zoologi; økofysiologi; økologi

Svarthamaren seabirds, sentinels of the Southern Ocean - Descamps, Sébastien; Moreau, Sébastien; Tarroux, Arnaud; Lorensten, Svein-Håkon; Bustnes, Jan-Ove; Yoccoz, Nigel G; Borgå, Katrine; Carravieri, Alice; Patrick, Samantha (Fram forum, 2021)
Keywords: Sørishavet; forurensning; klimaendringer; marin biologi; marine økosystemer; miljøendringer; observasjoner; ornitologi; sjøfugler; zoologi; økologi

Projected land ice contributions to twenty-first-century sea level rise - Edwards, Tamsin L; Nowicki, Sophie; Marzeion, Ben; Hock, Regine; Goelzer, Heiko; Seroussi, Hélène; Jourdain, Nicolas C; Slater, Donald A; Turner, Fiona E; Smith, Christopher J; McKenna, Christine M; Simon, Erika; et al. (Nature, 2021)
The land ice contribution to global mean sea level rise has not yet been predicted using ice sheet and glacier models for the latest set of socio-economic scenarios, nor using coordinated exploration of uncertainties arising from the various computer models involved. Two recent international projects generated a large suite of projections using multiple models, but primarily used previous-generation scenarios and climate models, and could not fully explore known uncertainties. Here we estimate probability distributions for these projections under the new scenarios using statistical emulation of the ice sheet and glacier models. We find that limiting global warming to 1.5 degrees Celsius would halve the land ice contribution to twenty-first-century sea level rise, relative to current emissions pledges. The median decreases from 25 to 13 centimetres sea level equivalent (SLE) by 2100, with glaciers responsible for half the sea level contribution. The projected Antarctic contribution does not show a clear response to the emissions scenario, owing to uncertainties in the competing processes of increasing ice loss and snowfall accumulation in a warming climate. However, under risk-averse (pessimistic) assumptions, Antarctic ice loss could be five times higher, increasing the median land ice contribution to 42 centimetres SLE under current policies and pledges, with the 95th percentile projection exceeding half a metre even under 1.5 degrees Celsius warming. This would severely limit the possibility of mitigating future coastal flooding. Given this large range (between 13 centimetres SLE using the main projections under 1.5 degrees Celsius warming and 42 centimetres SLE using risk-averse projections under current pledges), adaptation planning for twenty-first-century sea level rise must account for a factor-of-three uncertainty in the land ice contribution until climate policies and the Antarctic response are further constrained.
Keywords: Antarktis; glasiologi; havnivåstigning; innlandsis; klimaendringer; klimatologi; polarområdene; smelting

Moving mountains - when rocks and fluids interact - Engvik, Ane K.; Elvevold, Synnøve; Myhre, Per Inge; Sunde, Øyvind; Austrheim, Håkon (Fram forum, 2021)
Keywords: Dronning Maud Land; fjellene; forskning; geologi; mineralogi; nunataker

Evaluation of interannual variability of Arctic and Antarctic ozone loss since 1989 - Goutail, Florence; Pazmino, Andrea; Pommereau, Jean-Pierre; Lefèvre, Franck; Godin-Beekmann, Sophie; Hauchecorne, Alain; Lecouffe, Audrey; Clerbaux, Cathy; Boynard, Anne; Hadji-Lazaro, Juliette; Chipperfield, Martyn; Feng, Wuhu; et al. (2021)
Ozone depletion over Polar Regions is monitored each year by satellite and ground-based instruments. The first signs of healing of the ozone layer linked to the decrease of ozone destructive substances (ODSs) were observed in Antarctica using different metrics (ozone mean values, ozone mass deficit, area of the ozone hole) and simple or sophisticated models. Chemistry climate models predict that climate change will not affect expected ozone recovery over Antarctica but will accelerate recovery in the Arctic due to the possible enhancement of the Brewer Dobson circulation. However, ozone loss observations by SAOZ UV-Vis spectrometers do not show a clear sign of recovery in the latter region. In addition, a record of 38% ozone loss in 2010/2011 and 2019/2020 was estimated. In this study, the vortex-averaged ozone loss in the last three decades will be evaluated for both Polar Regions using the passive ozone tracer of two chemical transport models (REPROBUS and SLIMCAT CTMs) and total ozone observations from SAOZ and satellite observations (IASI/METOP and Multi-Sensor Reanalysis (MSR-2)). The tracer method allows us to determine the evolution of the daily rate of ozone destruction, and the amplitude of the cumulative loss at the end of the winter. The cumulative ozone destruction in the Artic varies between 0-10% in relatively warm winters with short vortex duration to up to 25-38% in colder winters with longer vortex persistence, while in Antarctica it is mostly stable, around 50%. Interannual variability of 10-days average rate will be analyzed and compared between both hemispheres as well as the timing to reach different thresholds of absolute ozone loss values. Finally, linear trend of ozone loss and temperature since 2000 will be estimated in both Polar Regions in order to evaluate possible ozone recovery.
Publication Title: EGU General Assembly 2021 Place: Online, Germany
Keywords: Antarktis; klimaendringer; miljøovervåking; ozonlaget; polarområdene

Marine Important Bird and Biodiversity Areas for Penguins in Antarctica, Targets for Conservation Action - Handley, Jonathan; Rouyer, Marie-Morgane; Pearmain, Elizabeth J; Warwick-Evans, Victoria; Teschke, Katharina; Hinke, Jefferson T; Lynch, Heather; Emmerson, Louise; Southwell, Colin; Griffith, Gary; Cárdenas, César A; Franco, Aldina M A; et al. (Frontiers in Marine Science, 2021)
Global targets for area-based conservation and management must move beyond threshold-based targets alone and must account for the quality of such areas. In the Southern Ocean around Antarctica, a region where key biodiversity faces unprecedented risks from climate change and where there is a growing demand to extract resources, a number of marine areas have been afforded enhanced conservation or management measures through two adopted marine protected areas (MPAs). However, evidence suggests that additional high quality areas could benefit from a proposed network of MPAs. Penguins offer a particular opportunity to identify high quality areas because these birds, as highly visible central-place foragers, are considered indicator species whose populations reflect the state of the surrounding marine environment. We compiled a comprehensive dataset of the location of penguin colonies and their associated abundance estimates in Antarctica. We then estimated the at-sea distribution of birds based on information derived from tracking data and through the application of a modified foraging radius approach with a density decay function to identify some of the most important marine areas for chick-rearing adult penguins throughout waters surrounding Antarctica following the Important Bird and Biodiversity Area (IBA) framework. Additionally, we assessed how marine IBAs overlapped with the currently adopted and proposed network of key management areas (primarily MPAs), and how the krill fishery likely overlapped with marine IBAs over the past five decades. We identified 63 marine IBAs throughout Antarctic waters and found that were the proposed MPAs to be adopted, the permanent conservation of high quality areas for penguin species would increase by between 49 and 100% depending on the species. Furthermore, our data show that, despite a generally contracting range of operation by the krill fishery in Antarctica over the past five decades, a consistently disproportionate amount of krill is being harvested within marine IBAs compared to the total area in which the fishery operates. Our results support the designation of the proposed MPA network and offer additional guidance as to where decision-makers should act before further perturbation occurs in the Antarctic marine ecosystem.
Keywords: Antarktis; Sørishavet; biodiversitet; klimaendringer; marin biologi; miljøvern

Evidence for a grounding line fan at the onset of a basal channel under the ice shelf of Support Force Glacier, Antarctica, revealed by reflection seismics - Hofstede, Coen; Beyer, Sebastian; Corr, Hugh; Eisen, Olaf; Hattermann, Tore; Helm, Veit; Neckel, Niklas; Smith, Emma C; Steinhage, Daniel; Zeising, Ole; Humbert, Angelika (The Cryosphere, 2021)
Curvilinear channels on the surface of an ice shelf indicate the presence of large channels at the base. Modelling studies have shown that where these surface expressions intersect the grounding line, they coincide with the likely outflow of subglacial water. An understanding of the initiation and the ice–ocean evolution of the basal channels is required to understand the present behaviour and future dynamics of ice sheets and ice shelves. Here, we present focused active seismic and radar surveys of a basal channel, ∼950 m wide and ∼200 m high, and its upstream continuation beneath Support Force Glacier, which feeds into the Filchner Ice Shelf, West Antarctica. Immediately seaward from the grounding line, below the basal channel, the seismic profiles show an ∼6.75 km long, 3.2 km wide and 200 m thick sedimentary sequence with chaotic to weakly stratified reflections we interpret as a grounding line fan deposited by a subglacial drainage channel directly upstream of the basal channel. Further downstream the seabed has a different character; it consists of harder, stratified consolidated sediments, deposited under different glaciological circumstances, or possibly bedrock. In contrast to the standard perception of a rapid change in ice shelf thickness just downstream of the grounding line, we find a flat topography of the ice shelf base with an almost constant ice thickness gradient along-flow, indicating only little basal melting, but an initial widening of the basal channel, which we ascribe to melting along its flanks. Our findings provide a detailed view of a more complex interaction between the ocean and subglacial hydrology to form basal channels in ice shelves.
Publisher: Copernicus Publications
Keywords: Antarktis; geovitenskap; glasiologi; isshelf

FRIS Revisited in 2018: On the Circulation and Water Masses at the Filchner and Ronne Ice Shelves in the Southern Weddell Sea - Janout, Markus A; Hellmer, Hartmut H; Hattermann, Tore; Huhn, Oliver; Sültenfuss, Jürgen; Østerhus, Svein; Stulic, Lukrecia; Ryan, Svenja; Schröder, Michael; Kanzow, Torsten (Journal of Geophysical Research: Oceans, 2021)
The Filchner-Ronne Ice Shelf (FRIS) is characterized by moderate basal melt rates due to the near-freezing waters that dominate the wide southern Weddell Sea continental shelf. We revisited the region in austral summer 2018 with detailed hydrographic and noble gas surveys along FRIS. The FRIS front was characterized by High Salinity Shelf Water (HSSW) in Ronne Depression, Ice Shelf Water (ISW) on its eastern flank, and an inflow of modified Warm Deep Water (mWDW) entering through Central Trough. Filchner Trough was dominated by Ronne HSSW-sourced ISW, likely forced by a recently intensified circulation beneath FRIS due to enhanced sea ice production in the Ronne polynya since 2015. Glacial meltwater fractions and tracer-based water mass dating indicate two separate ISW outflow cores, one hugging the Berkner slope after a two-year travel time, and the other located in the central Filchner Trough following a ∼six year-long transit through the FRIS cavity. Historical measurements indicate the presence of two distinct modes, in which water masses in Filchner Trough were dominated by either Ronne HSSW-derived ISW (Ronne-mode) or more locally derived Berkner-HSSW (Berkner-mode). While the dominance of these modes has alternated on interannual time scales, ocean densities in Filchner Trough have remained remarkably stable since the first surveys in 1980. Indeed, geostrophic velocities indicated outflowing ISW-cores along the trough's western flank and onto Berkner Bank, which suggests that Ronne-ISW preconditions Berkner-HSSW production. The negligible density difference between Berkner- and Ronne-mode waters indicates that each contributes cold dense shelf waters to protect FRIS against inflowing mWDW.
Keywords: Sørishavet; Weddellhavet; oseanografi; vannmasser

Norway's path to the Antarctic Treaty - Jølle, Harald Dag (Fram forum, 2021)
Keywords: Antarktis; Antarktistraktaten 1959; Norge; ekspedisjoner; historie; hvalfangst; internasjonal; jus; politikk

Evaluation of Three Numerical Weather Prediction Models for the Weddell Sea Region for the Austral Winter 2013 - Jonassen, Marius O; Nygård, Tiina; Vihma, Timo (Journal of Geophysical Research: Atmospheres, 2021)
It is widely recognized that numerical weather prediction (NWP) results for the Antarctic are relatively poor compared to the mid-latitudes. In this study, we evaluate output from three operational NWP systems: the ECMWF, Global Forecast System (GFS) and Antarctic Mesoscale Prediction System (AMPS), for the Austral winter (June-August) of 2013 for the Weddell Sea region, paying special attention to regional patterns of error statistics. This is the first evaluation of NWP systems over the Southern Ocean that also addresses the accuracy of forecasted vertical profiles. In the evaluation, we use data from land- and ship-based automatic weather stations (AWS) and radiosoundings. While the ECMWF and AMPS forecasts are on average biased cold and dry near the surface, the GFS forecasts are on average biased warm and moist. The near-surface wind speed is on average overestimated by the AMPS forecasts, whereas it is slightly underestimated by the forecasts of the other two NWP systems. Among the variables investigated, all three NWP systems forecast the near-surface specific humidity most accurately, followed by the temperature and then the wind speed. The forecast quality for the near-surface and upper-air wind speed degrades the most rapidly with increasing lead time, compared to the other variables. ECMWF is the overall best NWP system when compared against both the near-surface and upper-air observations, followed by AMPS and then GFS. The generally poorest model performance is found in locations with complex terrain along the coast of the Antarctic continent, and the best over the ocean.
Keywords: Sørishavet; Weddellhavet; geofysikk; meteorologi

Phenology and Environmental Control of Phytoplankton Blooms in the Kong Håkon VII Hav in the Southern Ocean - Kauko, Hanna M; Hattermann, Tore; Ryan-Keogh, Thomas; Singh, Asmita; de Steur, Laura; Fransson, Agneta; Chierici, Melissa; Falkenhaug, Tone; Hallfredsson, Elvar H; Bratbak, Gunnar; Tsagaraki, Tatiana; Berge, Terje; et al. (Frontiers in Marine Science, 2021)
Knowing the magnitude and timing of pelagic primary production is important for ecosystem and carbon sequestration studies, in addition to providing basic understanding of phytoplankton functioning. In this study we use data from an ecosystem cruise to Kong Håkon VII Hav, in the Atlantic sector of the Southern Ocean, in March 2019 and more than two decades of satellite-derived ocean color to study phytoplankton bloom phenology. During the cruise we observed phytoplankton blooms in different bloom phases. By correlating bloom phenology indices (i.e., bloom initiation and end) based on satellite remote sensing to the timing of changes in environmental conditions (i.e., sea ice, light, and mixed layer depth) we studied the environmental factors that seemingly drive phytoplankton blooms in the area. Our results show that blooms mainly take place in January and February, consistent with previous studies that include the area. Sea ice retreat controls the bloom initiation in particular along the coast and the western part of the study area, whereas bloom end is not primarily connected to sea ice advance. Light availability in general is not appearing to control the bloom termination, neither is nutrient availability based on the autumn cruise where we observed non-depleted macronutrient reservoirs in the surface. Instead, we surmise that zooplankton grazing plays a potentially large role to end the bloom, and thus controls its duration. The spatial correlation of the highest bloom magnitude with marked topographic features indicate that the interaction of ocean currents with sea floor topography enhances primary productivity in this area, probably by natural fertilization. Based on the bloom timing and magnitude patterns, we identified five different bloom regimes in the area. A more detailed understanding of the region will help to highlight areas with the highest relevance for the carbon cycle, the marine ecosystem and spatial management. With this gained understanding of bloom phenology, it will also be possible to study potential shifts in bloom timing and associated trophic mismatch caused by environmental changes.
Keywords: Sørishavet; fytoplankton; havis; marin biologi; marine økosystemer; miljøendringer; planteplankton; sjøis

Antarctic krill (Euphausia superba) exhibit positive phototaxis to white LED light - Krafft, Bjørn A; Krag, Ludvig A (Polar Biology, 2021)
Keywords: Sørishavet; fototaxis; krill; marin biologi; plankton

Standing stock of Antarctic krill (Euphausia superba Dana, 1850) (Euphausiacea) in the Southwest Atlantic sector of the Southern Ocean, 2018–19 - Krafft, Bjørn A; Macaulay, Gavin J; Skaret, Georg; Knutsen, Tor; Bergstad, Odd A; Lowther, Andrew; Huse, Geir; Fielding, Sophie; Trathan, Philip; Murphy, Eugene; Choi, Seok-Gwan; Chung, Sangdeok; et al. (Journal of Crustacean Biology, 2021)
Estimates of the distribution and density of Antarctic krill (Euphausia superba Dana, 1850) were derived from a large-scale survey conducted during the austral summer in the Southwest Atlantic sector of the Southern Ocean and across the Scotia Sea in 2018–19, the ‘2018–19 Area 48 Survey’. Survey vessels were provided by Norway, the Association of Responsible Krill harvesting companies and Aker BioMarine AS, the United Kingdom, Ukraine, Republic of Korea, and China. Survey design followed the transects of the Commission for the Conservation of Antarctic Marine Living Resources synoptic survey, carried out in 2000 and from regular national surveys performed in the South Atlantic sector by the U.S., China, Republic of Korea, Norway, and the U.K. The 2018–19 Area 48 Survey represents only the second large-scale survey performed in the area and this joint effort resulted in the largest ever total transect line (19,500 km) coverage carried out as one single exercise in the Southern Ocean. We delineated and integrated acoustic backscatter arising from krill swarms to produce distribution maps of krill areal biomass density and standing stock (biomass) estimates. Krill standing stock for the Area 48 was estimated to be 62.6 megatonnes (mean density of 30 g m–2 over 2 million km2) with a sampling coefficient variation of 13%. The highest mean krill densities were found in the South Orkney Islands stratum (93.2 g m–2) and the lowest in the South Georgia Island stratum (6.4 g m–2). The krill densities across the strata compared to those found during the previous survey indicate some regional differences in distribution and biomass. It is currently not possible to assign any such differences or lack of differences between the two survey datasets to longer term trends in the environment, krill stocks or fishing pressure.
Keywords: Sørishavet; krill; marin biologi; marine økosystemer; plankton

Subglacial discharge weakens the stability of the Ross Ice Shelf around the grounding line - Li, Yan; Shi, Hongling; Lu, Yang; Zhang, Zizhan; Xi, Hui (Polar Research, 2021)
In this paper, we examine potential impact of discharge in Subglacial Lake Engelhardt, West Antarctica, on the stability of the Ross Ice Shelf around the grounding line by combining satellite altimetry and remote sensing images. According to satellite altimetry data from the Ice, Cloud and Land Elevation Satellite (ICESat; 2003–06), Subglacial Lake Engelhardt (SLE) discharged ca. 1.91 ± 0.04 km3 of water into the downstream region. The ice-surface record derived from ICESat (2006–09) and CryoSat-2 (2011–17) data shows that the lake gained ca. 2.09 ± 0.05 km3 of water during the refilling event following the drainage event, taking three times as much time to reach the previous water level before the discharge; the calculation demonstrates that water input from an upstream lake is unable to sustain water increase in SLE, indicating that the subglacial, hydrologic system and groundwater flow could have contributed to water increase in SLE via hydrologic networks. Satellite images captured surface depressions and crevasses at the drainage outlet point of hydrologic networks around the grounding line; satellite altimetry data show that the ice surface there is still depressing even though the subglacial discharge has finished, potentially reflecting the long-term impact of subglacial discharge on the stability of the immediate Ross Ice Shelf around the grounding line. Keywords: Antarctic subglacial lakes; water storage change; satellite altimetry; remote sensing; hydraulic potential method.
Keywords: Antarktis; geodesi; hydrologi; isbreer; satellitt bilder; subglasial innsjø

Case Study of Blowing Snow Impacts on the Antarctic Peninsula Lower Atmosphere and Surface Simulated With a Snow/Ice Enhanced WRF Model - Luo, Liping; Zhang, Jing; Hock, Regine; Yao, Yao (Journal of Geophysical Research: Atmospheres, 2021)
To better capture the air-snow-ice interaction, a snow/ice enhanced Weather Research and Forecasting (WRF-ice) model has been developed. This study examines the performance of WRF-ice and its blowing snow component during a strong cyclone event from October 23 to 27, 2017 over the Antarctic Peninsula, which is characterized by a synoptic cyclone crossing the northern part of the Peninsula and an embodied mesoscale cyclone over the Weddell Sea. Evolution of the cyclone is accurately reproduced in the 5-km resolution WRF-ice simulation, and the simulated near-surface conditions agree well with station and satellite observations. Numerical simulations show that the process of blowing snow sublimation can be prominent within the lower atmosphere when the air is dry, and produces moistening and cooling effects. Over relatively warm and humid areas, cloud enhancement by blowing snow can lead to either colder or warmer surfaces because of competing effects of longwave and shortwave cloud radiative forcings. In particular, additional moisture from blowing snow sublimation can slightly intensify precipitation over the mountains. Surface energy budget analysis indicates that absorbed shortwave (Sa), incoming longwave (Ld), and outgoing longwave (Lu) are dominant components of surface energy budget. When increases in Ld, Lu, and sensible heat flux are combined with decreases in Sa and latent heat flux due to blowing snow effects, a negative surface net heat flux (∼0.5 W/m2) occurs during daytime. A positive domain-total surface mass balance (∼0.43 Gt) is generated during the simulated cyclone event due to increases in precipitation, decreases in runoff, and decreases in sublimation.
Keywords: Antarktis; akkumulasjon; atmosfæren; geofysikk; geovitenskap; is; meteorologi; polarområdene; satellite; snø

Quantarctica, an integrated mapping environment for Antarctica, the Southern Ocean, and sub-Antarctic islands - Matsuoka, Kenichi; Skoglund, Anders; Roth, George; de Pomereu, Jean; Griffiths, Huw; Headland, Robert; Herried, Brad; Katsumata, Katsuro; Le Brocq, Anne; Licht, Kathy; Morgan, Fraser; Neff, Peter D; et al. (Environmental Modelling & Software, 2021)
Quantarctica (https://www.npolar.no/quantarctica) is a geospatial data package, analysis environment, and visualization platform for the Antarctic Continent, Southern Ocean (>40oS), and sub-Antarctic islands. Quantarctica works with the free, cross-platform Geographical Information System (GIS) software QGIS and can run without an Internet connection, making it a viable tool for fieldwork in remote areas. The data package includes basemaps, satellite imagery, terrain models, and scientific data in nine disciplines, including physical and biological sciences, environmental management, and social science. To provide a clear and responsive user experience, cartography and rendering settings are carefully prepared using colour sets that work well for typical data combinations and with consideration of users with common colour vision deficiencies. Metadata included in each dataset provides brief abstracts for non-specialists and references to the original data sources. Thus, Quantarctica provides an integrated environment to view and analyse multiple Antarctic datasets together conveniently and with a low entry barrier.
Keywords: Antarktis; Sørishavet; geografi; kartografi; polarområdene

Antarctic krill Euphausia superba: spatial distribution, abundance, and management of fisheries in a changing climate - McBride, Margaret M; Schram Stokke, Olav; Renner, Angelika H H; Krafft, Bjørn A; Bergstad, Odd A; Biuw, Martin; Lowther, Andrew D; Stiansen, Jan E (Marine Ecology Progress Series, 2021)
Antarctic krill Euphausia superba, a keystone species in the Southern Ocean, is highly relevant for studying effects of climate-related shifts on management systems. Krill provides a key link between primary producers and higher trophic levels and supports the largest regional fishery. Any major perturbation in the krill population would have severe ecological and economic ramifications. We review the literature to determine how climate change, in concert with other environmental changes, alters krill habitat, affects spatial distribution/abundance, and impacts fisheries management. Findings recently reported on the effects of climate change on krill distribution and abundance are inconsistent, however, raising questions regarding methods used to detect changes in density and biomass. One recent study reported a sharp decline in krill densities near their northern limit, accompanied by a poleward contraction in distribution in the Southwest Atlantic sector. Another recent study found no evidence of long-term decline in krill density or biomass and reported no evidence of a poleward shift in distribution. Moreover, with predicted decreases in phytoplankton production, vertical foraging migrations to the seabed may become more frequent, also impacting krill production and harvesting. Potentially cumulative impacts of climate change further compound the management challenge faced by CCAMLR, the organization responsible for conservation of Antarctic marine living resources: to detect changes in the abundance, distribution, and reproductive performance of krill and krill-dependent predator stocks and to respond to such change by adjusting its conservation measures. Based on CCAMLR reports and documents, we review the institutional framework, outline how climate change has been addressed within this organization, and examine the prospects for further advances toward ecosystem risk assessment and an adaptive management system.
Keywords: Sørishavet; fiskeri; klimaendringer; marin biologi; zooplankton; økosystemer

Hemispheric black carbon increase after the 13th-century Māori arrival in New Zealand - McConnell, Joseph R; Chellman, Nathan J; Mulvaney, Robert; Eckhardt, Sabine; Stohl, Andreas; Plunkett, Gill; Kipfstuhl, Sepp; Freitag, Johannes; Isaksson, Elisabeth; Gleason, Kelly E; Brugger, Sandra O; McWethy, David B; et al. (Nature, 2021)
New Zealand was among the last habitable places on earth to be colonized by humans. Charcoal records indicate that wildfires were rare prior to colonization and widespread following the 13th- to 14th-century Māori settlement, but the precise timing and magnitude of associated biomass-burning emissions are unknown, as are effects on light-absorbing black carbon aerosol concentrations over the pristine Southern Ocean and Antarctica. Here we used an array of well-dated Antarctic ice-core records to show that while black carbon deposition rates were stable over continental Antarctica during the past two millennia, they were approximately threefold higher over the northern Antarctic Peninsula during the past 700 years. Aerosol modelling demonstrates that the observed deposition could result only from increased emissions poleward of 40° S—implicating fires in Tasmania, New Zealand and Patagonia—but only New Zealand palaeofire records indicate coincident increases. Rapid deposition increases started in 1297 (±30 s.d.) in the northern Antarctic Peninsula, consistent with the late 13th-century Māori settlement and New Zealand black carbon emissions of 36 (±21 2 s.d.) Gg y−1 during peak deposition in the 16th century. While charcoal and pollen records suggest earlier, climate-modulated burning in Tasmania and southern Patagonia, deposition in Antarctica shows that black carbon emissions from burning in New Zealand dwarfed other preindustrial emissions in these regions during the past 2,000 years, providing clear evidence of large-scale environmental effects associated with early human activities across the remote Southern Hemisphere.
Keywords: Antarktis; iskjerner; miljø; paleoklimatologi

Southern Ocean Food Web Modelling: Progress, Prognoses, and Future Priorities for Research and Policy Makers - McCormack, Stacey A; Melbourne-Thomas, Jessica; Trebilco, Rowan; Griffith, Gary; Hill, Simeon L; Hoover, Carie; Johnston, Nadine M; Marina, Tomás I; Murphy, Eugene J; Pakhomov, Evgeny A; Pinkerton, Matt; Plagányi, Éva; et al. (Frontiers in Ecology and Evolution, 2021)
Globally important services are supported by Southern Ocean ecosystems, underpinned by the structure, function, and dynamics of complex interconnected and regionally distinctive food webs. These food webs vary in response to a combination of physical and chemical processes that alter productivity, species composition and the relative abundance and dynamics of organisms. Combined with regional and seasonal variability, climate-induced changes and human activities have and are expected to continue to drive important structural and functional changes to Southern Ocean food webs. However, our current understanding of food web structure, function, status, and trends is patchy in space and time, and methods for systematically assessing and comparing community-level responses to change within and across regional and temporal scales are not well developed. Insights gained from food web modelling studies—ranging from theoretical analyses of ecosystem resilience and adaptation, to qualitative and quantitative descriptions of the system—can assist in resolving patterns of energy flow and the ecological mechanisms that drive food web structure, function, and responses to drivers (such as fishing and climate change). This understanding is required to inform robust management strategies to conserve Southern Ocean food webs and the ecosystem services they underpin in the face of change. This paper synthesises the current state of knowledge regarding Southern Ocean pelagic food webs, highlighting the distinct regional food web characteristics, including key drivers of energy flow, dominant species, and network properties that may indicate system resilience. In particular, the insights, gaps, and potential integration of existing knowledge and Southern Ocean food web models are evaluated as a basis for developing integrated food web assessments that can be used to test the efficacy of alternative management and policy options. We discuss key limitations of existing models for assessing change resulting from various drivers, summarise priorities for model development and identify that significant progress could be made to support policy by advancing the development of food web models coupled to projected biogeochemical models, such as in Earth System models.
Keywords: Sørishavet; marin biologi; marine økosystemer

Cancellation of the Precessional Cycle in δ18O Records During the Early Pleistocene - Morée, Anne L; Sun, Tianyi; Bretones, Anaïs; Straume, Eivind O; Nisancioglu, Kerim; Gebbie, Geoffrey (Geophysical Research Letters, 2021)
The dominant pacing of glacial-interglacial cycles in deep-ocean δ18O records changed substantially during the Mid-Pleistocene Transition. The precessional cycle (∼23 ky) is absent during the Early Pleistocene, which we show can be explained by cancellation of the hemispherically antiphased precessional cycle in the Early Pleistocene interior ocean. Such cancellation develops due to mixing of North Atlantic and Southern Ocean δ18O signals at depth, and shows characteristic spatial patterns. We explore the cancellation potential for different North Atlantic and Southern Ocean deep-water source δ18O values using a tracer transport ocean model. Cancellation of precession occurs for all signal strengths and is widespread for a signal strength typical for the Early Pleistocene. Early Pleistocene precessional power is therefore likely incompletely archived in deep-sea δ18O records, concealing the true periodicity of the glacial cycles in the two hemispheres.
Keywords: Sørishavet; geofysikk; innlandsis; oseanografi; paleontologi; polarområdene

Variability of Sea-Air Carbon Dioxide Flux in Autumn Across the Weddell Gyre and Offshore Dronning Maud Land in the Southern Ocean - Ogundare, Margaret Ojone; Fransson, Agneta; Chierici, Melissa; Joubert, Warren R.; Roychoudhury, Alakendra N. (Frontiers in Marine Science, 2021)
Sea surface fugacity of carbon dioxide (fCO2ssw) was measured across the Weddell gyre and the eastern sector in the Atlantic Southern Ocean in autumn. During the occupation between February and April 2019, the region of the study transect was a potential ocean CO2 sink. A net CO2 flux (FCO2) of −6.2 (± 8; sink) mmol m–2 d–1 was estimated for the entire study region, with the largest average CO2 sink of −10.0 (± 8) mmol m–2 d–1 in the partly ice-covered Astrid Ridge (AR) region near the coast at 68°S and −6.1 (± 8) mmol m–2d–1 was observed in the Maud Rise (MR) region. A CO2 sink was also observed south of 66°S in the Weddell Sea (WS). To assess the main drivers describing the variability of fCO2ssw, a correlation model using fCO2 and oxygen saturation was considered. Spatial distributions of the fCO2 saturation/O2 saturation correlations, described relative to the surface water properties of the controlling variables (chlorophyll a, apparent oxygen utilization (AOU), sea surface temperature, and sea surface salinity) further constrained the interplay of the processes driving the fCO2ssw distributions. Photosynthetic CO2 drawdown significantly offsets the influence of the upwelling of CO2-rich waters in the central Weddell gyre and enhanced the CO2 sink in the region. FCO2 of −6.9 mmol m–2 d–1 estimated for the Weddell gyre in this study was different from FCO2 of −2.5 mmol m–2 d–1 in autumn estimated in a previous study. Due to low CO2 data coverage during autumn, limited sea-air CO2 flux estimates from direct sea-surface CO2 observations particularly for the Weddell gyre region are available with which to compare the values estimated in this study. This highlights the importance of increasing seasonal CO2 observations especially during autumn/winter to improving the seasonal coverage of flux estimates in the seasonal sea ice-covered regions of the Southern Ocean.
Keywords: Sørishavet; karbondioksid; kjemi

Future sea level change under CMIP5 and CMIP6 scenarios from the Greenland and Antarctic ice sheets - Payne, Antony J; Nowicki, Sophie; Abe-Ouchi, Ayako; Agosta, Cécile; Alexander, Patrick; Albrecht, Torsten; Asay-Davis, Xylar; Aschwanden, Andy; Barthel, Alice; Bracegirdle, Thomas J; Calov, Reinhard; Chambers, Christopher; et al. (Geophysical Research Letters, 2021)
Projections of the sea level contribution from the Greenland and Antarctic ice sheets rely on atmospheric and oceanic drivers obtained from climate models. The Earth System Models participating in the Coupled Model Intercomparison Project phase 6 (CMIP6) generally project greater future warming compared with the previous CMIP5 effort. Here we use four CMIP6 models and a selection of CMIP5 models to force multiple ice sheet models as part of the Ice Sheet Model Intercomparison Project for CMIP6 (ISMIP6). We find that the projected sea level contribution at 2100 from the ice sheet model ensemble under the CMIP6 scenarios falls within the CMIP5 range for the Antarctic ice sheet but is significantly increased for Greenland. Warmer atmosphere in CMIP6 models results in higher Greenland mass loss due to surface melt. For Antarctica, CMIP6 forcing is similar to CMIP5 and mass gain from increased snowfall counteracts increased loss due to ocean warming.
Keywords: Antarktis; glasiologi; havnivåstigning; innlandsis; klimaendringer; klimatologi; polarområdene; smelting

Evidence for the Impact of Climate Change on Primary Producers in the Southern Ocean - Pinkerton, Matthew H; Boyd, Philip W; Deppeler, Stacy; Hayward, Alex; Höfer, Juan; Moreau, Sebastien (Frontiers in Ecology and Evolution, 2021)
Within the framework of the Marine Ecosystem Assessment for the Southern Ocean (MEASO), this paper brings together analyses of recent trends in phytoplankton biomass, primary production and irradiance at the base of the mixed layer in the Southern Ocean and summarises future projections. Satellite observations suggest that phytoplankton biomass in the mixed-layer has increased over the last 20 years in most (but not all) parts of the Southern Ocean, whereas primary production at the base of the mixed-layer has likely decreased over the same period. Different satellite models of primary production (Vertically Generalised versus Carbon Based Production Models) give different patterns and directions of recent change in net primary production (NPP). At present, the satellite record is not long enough to distinguish between trends and climate-related cycles in primary production. Over the next 100 years, Earth system models project increasing NPP in the water column in the MEASO northern and Antarctic zones but decreases in the Subantarctic zone. Low confidence in these projections arises from: (1) the difficulty in mapping supply mechanisms for key nutrients (silicate, iron); and (2) understanding the effects of multiple stressors (including irradiance, nutrients, temperature, pCO_2, pH, grazing) on different species of Antarctic phytoplankton. Notwithstanding these uncertainties, there are likely to be changes to the seasonal patterns of production and the microbial community present over the next 50–100 years and these changes will have ecological consequences across Southern Ocean food-webs, especially on key species such as Antarctic krill and silverfish.
Keywords: Sørishavet; biogeokjemi; fytoplankton; klimaendringer; marine økosystemer; phytoplankton

Internal Ocean Dynamics Control the Long-Term Evolution of Weddell Sea Polynya Activity - Rheinlænder, Jonathan W.; Smedsrud, Lars H.; Nisanciouglu, Kerim H. (Frontiers in Climate, 2021)
Open-ocean polynyas effectively couple the ocean and atmosphere through large ice-free areas within the sea-ice cover, release vast quantities of oceanic heat, and impact deep ocean ventilation. Changes in polynya activity, particularly in the Weddell Sea, may be key to longer time-scale climate fluctuations, feedbacks and abrupt change. While changes in the occurrence of Weddell Sea polynyas are generally attributed to changes in the atmospheric surface forcing, the role of internal ocean dynamics for polynya variability is not well-resolved. In this study we employ a global coupled ocean-sea ice model with a repeating annual atmospheric cycle to explore changes in Weddell Sea water mass properties, stratification and ocean circulation driven by open-ocean polynyas. During the 1300-year long simulation, two large polynyas occur in the central Weddell Sea. Our results suggest that Weddell polynyas may be triggered without inter-annual changes in the atmospheric forcing. This highlights the role of ocean processes in preconditioning and triggering open-ocean polynyas on multi-centennial time-scales. The simulated polynyas form due to internal ocean-sea ice dynamics associated with a slow build-up and subsequent release of subsurface heat. A strong stratification and weak vertical mixing is necessary for building the subsurface heat reservoir. Once the water column turns unstable, enhanced vertical mixing of warm and saline waters into the surface layer causes efficient sea ice melt and the polynya appears. Subsequent, vigorous deep convection is maintained through upwelling of warm deep water leading to enhanced bottom water formation. We find a cessation of simulated deep convection and polynya activity due to long-term cooling and freshening of the subsurface heat reservoir. As subsurface waters in the Southern Ocean are now becoming warmer and saltier, we speculate that larger and more persistent Weddell polynyas could become more frequent in the future.
Keywords: Sørishavet; havis; klimamodeller; klimatologi; polynja; sjøis

Hvordan vet vi det vi vet om global oppvarming? - Seip, Knut Lehre (Naturen, 2021)
Hvordan vet vi det vi vet om global oppvarming? Denne artikkelen diskuterer grunnlaget for det vi vet med stor sikkerhet. I artikkelen diskuterer vi 12 temaer, og velger ut én eller to metoder som illustrerer hvordan kunnskap er skaffet til veie for hvert av temaene.
Keywords: Antarktis; global oppvarming; klimaendringer; klimatologi; polarområdene

Substantial spatial variation in glacial erosion rates in the Dronning Maud Land Mountains, East Antarctica - Sirevaag, Hallgeir; Jacobs, Joachim; Ksienzyk, Anna K (Communications Earth & Environment, 2021)
The coast-parallel Dronning Maud Land (DML) mountains represent a key nucleation site for the protracted glaciation of Antarctica. Their evolution is therefore of special interest for understanding the formation and development of the Antarctic ice sheet. Extensive glacial erosion has clearly altered the landscape over the past 34 Myr. Yet, the total erosion still remains to be properly constrained. Here, we investigate the power of low-temperature thermochronology in quantifying glacial erosion in-situ. Our data document the differential erosion along the DML escarpment, with up to c. 1.5 and 2.4 km of erosion in western and central DML, respectively. Substantial erosion at the escarpment foothills, and limited erosion at high elevations and close to drainage divides, is consistent with an escarpment retreat model. Such differential erosion suggests major alterations of the landscape during 34 Myr of glaciation and should be implemented in future ice sheet models.
Keywords: Dronning Maud Land; geologi; geomorfologi

Antarctic icebergs reorganize ocean circulation during Pleistocene glacials - Starr, Aidan; Hall, Ian R.; Barker, Stephen; Rackow, Thomas; Zhang, Xu; Hemming, Sidney R.; van der Lubbe, H. J. L.; Knorr, Gregor; Berke, Melissa A.; Bigg, Grant R.; Cartagena-Sierra, Alejandra; Jiménez-Espejo, Francisco J.; et al. (Nature, 2021)
The dominant feature of large-scale mass transfer in the modern ocean is the Atlantic meridional overturning circulation (AMOC). The geometry and vigour of this circulation influences global climate on various timescales. Palaeoceanographic evidence suggests that during glacial periods of the past 1.5 million years the AMOC had markedly different features from today1; in the Atlantic basin, deep waters of Southern Ocean origin increased in volume while above them the core of the North Atlantic Deep Water (NADW) shoaled2. An absence of evidence on the origin of this phenomenon means that the sequence of events leading to global glacial conditions remains unclear. Here we present multi-proxy evidence showing that northward shifts in Antarctic iceberg melt in the Indian–Atlantic Southern Ocean (0–50° E) systematically preceded deep-water mass reorganizations by one to two thousand years during Pleistocene-era glaciations. With the aid of iceberg-trajectory model experiments, we demonstrate that such a shift in iceberg trajectories during glacial periods can result in a considerable redistribution of freshwater in the Southern Ocean. We suggest that this, in concert with increased sea-ice cover, enabled positive buoyancy anomalies to ‘escape’ into the upper limb of the AMOC, providing a teleconnection between surface Southern Ocean conditions and the formation of NADW. The magnitude and pacing of this mechanism evolved substantially across the mid-Pleistocene transition, and the coeval increase in magnitude of the ‘southern escape’ and deep circulation perturbations implicate this mechanism as a key feedback in the transition to the ‘100-kyr world’, in which glacial–interglacial cycles occur at roughly 100,000-year periods.
Keywords: Sørishavet; havstrømmer; isfjell; paleoklimatologi; paleoseanografi

Climate change impacts on sea-ice ecosystems and associated ecosystem services - Steiner, Nadja S; Bowman, Jeff; Campbell, Karley; Chierici, Melissa; Eronen-Rasimus, Eeva; Falardeau, Marianne; Flores, Hauke; Fransson, Agneta; Herr, Helena; Insley, Stephen J; Kauko, Hanna M; Lannuzel, Delphine; et al. (Elementa: Science of the Anthropocene, 2021)
A rigorous synthesis of the sea-ice ecosystem and linked ecosystem services highlights that the sea-ice ecosystem supports all 4 ecosystem service categories, that sea-ice ecosystems meet the criteria for ecologically or biologically significant marine areas, that global emissions driving climate change are directly linked to the demise of sea-ice ecosystems and its ecosystem services, and that the sea-ice ecosystem deserves specific attention in the evaluation of marine protected area planning. The synthesis outlines (1) supporting services, provided in form of habitat, including feeding grounds and nurseries for microbes, meiofauna, fish, birds and mammals (particularly the key species Arctic cod, Boreogadus saida, and Antarctic krill, Euphausia superba, which are tightly linked to the sea-ice ecosystem and transfer carbon from sea-ice primary producers to higher trophic level fish, mammal species and humans); (2) provisioning services through harvesting and medicinal and genetic resources; (3) cultural services through Indigenous and local knowledge systems, cultural identity and spirituality, and via cultural activities, tourism and research; (4) (climate) regulating services through light regulation, the production of biogenic aerosols, halogen oxidation and the release or uptake of greenhouse gases, for example, carbon dioxide. The ongoing changes in the polar regions have strong impacts on sea-ice ecosystems and associated ecosystem services. While the response of sea-ice–associated primary production to environmental change is regionally variable, the effect on ice-associated mammals and birds is predominantly negative, subsequently impacting human harvesting and cultural services in both polar regions. Conservation can help protect some species and functions. However, the key mitigation measure that can slow the transition to a strictly seasonal ice cover in the Arctic Ocean, reduce the overall loss of sea-ice habitats from the ocean, and thus preserve the unique ecosystem services provided by sea ice and their contributions to human well-being is a reduction in carbon emissions.
Keywords: Sørishavet; klimaendringer; marin biologi; marine økosystemer

An ocean of possibilities: antarctic petrel's foraging in the Southern Ocean - Tarroux, Arnaud; Fauchald, Per; Varpe, Øystein; Yoccoz, Nigel G; Descamps, Sébastien (Fram forum, 2021)
Keywords: Sørishavet; fôring; marin biologi; observasjoner; ornitologi; petreller; sjøfugler; zoologi

Linking Sub-Tropical Evaporation and Extreme Precipitation Over East Antarctica: An Atmospheric River Case Study - Terpstra, Annick; Gorodetskaya, Irina V; Sodemann, Harald (Journal of Geophysical Research: Atmospheres, 2021)
We investigate an intense snowfall event between 15 and 18 February 2011 over the East Antarctic coastal region which contributed to roughly 24% of the annual snow accumulation. The event was previously associated with an atmospheric river, and here we use both Eulerian and Lagrangian analysis to gain an understanding of the processes contributing to the atmospheric river signature. The planetary-scale configuration during the event consisted of a persistent blocking situation resulting in a sustained meridional flow from the sub-tropics to the Antarctic ice sheet between 20 and 50°E. Within this configuration, synoptic-scale cyclogenesis contributed to slantwise ascent of moisture loaded air parcels toward Antarctica. Landfall of this cyclone’s warm sector coincided with the onset of Antarctic precipitation. Subsequently, a secondary cyclone developed along a pre-existing baroclinic zone. The rapid intensification and propagation speed of this mesoscale cyclone alongside the warm, moist air mass resulted in strong moisture flux convergence ahead of the cyclone, providing additional poleward moisture transport. The poleward progression of warm moist air and a corresponding decrease of sea-surface temperatures implied downward surface sensible and latent heat fluxes throughout the region of intense poleward moisture, roughly between 40 and 60°S. Hence, moisture uptake via surface evaporation was suppressed between the sub-tropics and the polar continent, favoring long-range transport. Identification of the surface moisture uptake region by tracing changes in moisture in air parcels confirmed the limited uptake of moisture during the poleward transport in this case study, with the primary moisture source for Antarctic precipitation located in the sub-tropics.
Keywords: Antarktis; akkumulasjon; atmosfæren; geofysikk; meteorologi; nedbør; snøfall

Satellite and ground based estimates for ice surface velocities in the part of central Dronning Maud Land, East Antarctica: Implications for ice flux calculations - Thakur, Praveen K; Swain, Ashit K; Dhote, Pankaj R; Kumar, Pradeep; Kaushik, Suvrat; Gajbhiye, Deepak; Mahagaonkar, Anirudha; Sharma, Vishal; Dharwadkar, Amit; Aggarwal, S P; Beg, Javed; Chauhan, Prakash; et al. (Polar Science, 2021)
The ice sheet and glaciers of Antarctica and Greenland represent the largest sources of freshwater on planet Earth. The understanding and quantification of their dynamic properties such as albedo, precipitation, ice mass movement, and ice elevation changes are critical for the improved climate and mass balance models. The present study utilizes space-borne optical and synthetic aperture radar (SAR) imagery to measure the ice surface velocity at high spatial resolution for a part of the central Dronning Maud Land (cDML), East Antarctica. The datasets from Landsat-8 and Sentinel-1 SAR satellite are used for ice stream velocity estimation using feature-offset tracking and differential interferometric SAR (DInSAR) methods. The derived velocity products are validated with ground based stakes network at annual time scale. The fundamental ice flow laws are used to estimate the ice outflux or discharge for selected ice stream drainage basins of cDML at fluxgate locations. The ice stream basin has been delineated using combination of elevation, slope and continental scale velocity maps. The ice influx for study area is estimated using ECMWF fifth generation reanalysis (ERA5) and Regional Atmospheric Climate Model (RACMO) v2.3 model outputs. The estimated influx and outflux are in the ranges of 0.18–4.167 Gt/y and 0.201 to 1.278 Gt/y respectively, indicating net positive mass balance for the selected area.
Keywords: Dronning Maud Land; glasiologi; innlandsis; polarområdene

Surface Mass Balance Controlled by Local Surface Slope in Inland Antarctica: Implications for Ice-Sheet Mass Balance and Oldest Ice Delineation in Dome Fuji - Van Liefferinge, Brice; Taylor, Drew; Tsutaki, Shun; Fujita, Shuji; Gogineni, Prasad; Kawamura, Kenji; Matsuoka, Kenichi; Moholdt, Geir; Oyabu, Ikumi; Abe-Ouchi, Ayako; Awasthi, Abhishek; Buizert, Christo; et al. (Geophysical Research Letters, 2021)
The limited number of surface mass balance (SMB) observations in the Antarctic inland hampers estimates of ice-sheet contribution to global sea level and locations with million-year-old ice. We present finely resolved SMB over the past three centuries in a low-accumulation region with significant depth hoar formation on Dome Fuji derived from ∼1,100 km of microwave radar stratigraphy dated with a firn core. The regional-mean SMB over the past 264 years is estimated to ∼22.5 ± 3.3 kg m−2 a−1, but with large local variability of up to 30%. We found that local SMB is negatively correlated with surface slope at scales of a few hundred meters, resulting in anomalous zones of low SMB which represent as much as 8–10% of the total SMB on the inland plateau if the SMB-slope relationship is more widely valid. This impact should be investigated further to improve estimates of Antarctic mass balance and sea-level contribution.
Keywords: Antarktis; glasiologi

Legitimacy of the Antarctic Treaty System: is it time for a reform? - Yermakova, Yelena (The Polar Journal, 2021)
The Antarctic Treaty System (ATS) has governed the Antarctic for the last six decades ensuring it to be a place of peace and scientific cooperation. Like any institution, the ATS exists in order to solve collective action problems through coordination and the creation of norms. But how do we know if a particular institution is the right one to solve a specific problem or address issues regarding the governance of a region? And when is it time to replace or reform such an institution? To answer these questions, we need an account of institutional legitimacy. An assessment of the legitimacy of the ATS is necessary in order to determine whether it is worthy of being empowered through support, or if it is time to reform some aspects of it. Building on the account of legitimacy of global governance institutions proposed by Buchanan and Keohane, the paper assesses the legitimacy of the ATS and argues that it is time to reform some components of it. Specifically, the paper assesses the legitimacy of the ATS based on the following criteria: minimal moral acceptability; comparative benefit; institutional integrity; and accountability. The paper highlights the ATS? shortcomings based on these criteria and suggests reforms that will strengthen the legitimacy of the ATS
Publisher: Routledge
Keywords: Antarktis; Antarktistraktaten

Ice surface changes during recent glacial cycles along the Jutulstraumen and Penck Trough ice streams in western Dronning Maud Land, East Antarctica - Andersen, J.L.; Newall, J.C.; Blomdin, R.; Sams, S.E.; Fabel, D.; Koester, A.J.; Lifton, N.A.; Fredin, O.; Caffee, M.W.; Glasser, Neil F.; Rogozhina, I.; Suganuma, Y.; et al. (Quaternary Science Reviews, 2020)
Reconstructing past ice-sheet surface changes is key to testing and improving ice-sheet models. Data constraining the past behaviour of the East Antarctic Ice Sheet are sparse, limiting our understanding of its response to past, present and future climate change. Here, we report the first cosmogenic multi-nuclide (10Be, 26Al, 36Cl) data from bedrock and erratics on nunataks along the Jutulstraumen and Penck Trough ice streams in western Dronning Maud Land, East Antarctica. Spanning elevations between 741 and 2394 m above sea level, the samples have apparent exposure ages between 2 ka and 5 Ma. The highest-elevation bedrock sample indicates (near-) continuous minimum exposure since the Pliocene, with a low apparent erosion rate of 0.15 ± 0.03 m Ma−1, which is similar to results from eastern Dronning Maud Land. In contrast to studies in eastern Dronning Maud Land, however, our data show clear indications of a thicker-than-present ice sheet within the last glacial cycle, with a thinning of ∼35–120 m during the Holocene (∼2–11 ka). Difficulties in separating suitable amounts of quartz from the often quartz-poor rock-types in the area, and cosmogenic nuclides inherited from exposure prior to the last deglaciation, prevented robust thinning estimates from elevational profiles. Nevertheless, the results clearly demonstrate ice-surface fluctuations of several hundred meters between the current grounding line and the edge of the polar plateau for the last glacial cycle, a constraint that should be considered in future ice-sheet model simulations.
Keywords: Antarctica; Cosmogenic isotopes; Dronning Maud Land; Glaciation; Quaternary; glasiologi

Remote assessment of the fate of phytoplankton in the Southern Ocean sea-ice zone - Moreau, Sébastien; Boyd, Philip W.; Strutton, Peter G. (Nature Communications, 2020)
In the Southern Ocean, large-scale phytoplankton blooms occur in open water and the sea-ice zone (SIZ). These blooms have a range of fates including physical advection, downward carbon export, or grazing. Here, we determine the magnitude, timing and spatial trends of the biogeochemical (export) and ecological (foodwebs) fates of phytoplankton, based on seven BGC-Argo floats spanning three years across the SIZ. We calculate loss terms using the production of chlorophyll—based on nitrate depletion—compared with measured chlorophyll. Export losses are estimated using conspicuous chlorophyll pulses at depth. By subtracting export losses, we calculate grazing-mediated losses. Herbivory accounts for ~90% of the annually-averaged losses (169 mg C m−2 d−1), and phytodetritus POC export comprises ~10%. Furthermore, export and grazing losses each exhibit distinctive seasonality captured by all floats spanning 60°S to 69°S. These similar trends reveal widespread patterns in phytoplankton fate throughout the Southern Ocean SIZ.
Keywords: Sørishavet; marin biologi; plankton; økologi

Meridional Ocean Carbon Transport - Aldama-Campino, Aitor; Fransner, Filippa; Ödalen, Malin; Groeskamp, Sjoerd; Yool, Andrew; Döös, Kristofer; Nycander, Jonas (Global Biogeochemical Cycles, 2020)
The ocean's ability to take up and store CO2 is a key factor for understanding past and future climate variability. However, qualitative and quantitative understanding of surface-to-interior pathways, and how the ocean circulation affects the CO2 uptake, is limited. Consequently, how changes in ocean circulation may influence carbon uptake and storage and therefore the future climate remains ambiguous. Here we quantify the roles played by ocean circulation and various water masses in the meridional redistribution of carbon. We do so by calculating streamfunctions defined in dissolved inorganic carbon (DIC) and latitude coordinates, using output from a coupled biogeochemical-physical model. By further separating DIC into components originating from the solubility pump and a residual including the biological pump, air-sea disequilibrium, and anthropogenic CO2, we are able to distinguish the dominant pathways of how carbon enters particular water masses. With this new tool, we show that the largest meridional carbon transport occurs in a pole-to-equator transport in the subtropical gyres in the upper ocean. We are able to show that this pole-to-equator DIC transport and the Atlantic meridional overturning circulation (AMOC)-related DIC transport are mainly driven by the solubility pump. By contrast, the DIC transport associated with deep circulation, including that in Antarctic bottom water and Pacific deep water, is mostly driven by the biological pump. As these two pumps, as well as ocean circulation, are widely expected to be impacted by anthropogenic changes, these findings have implications for the future role of the ocean as a climate-buffering carbon reservoir.
Keywords: Sørishavet; biogeokjemi; bunnvann; karbon syklus; karbondioksid; klimatologi; oseanografi; vannmasser

Global biogeography of marine amphipod crustaceans: latitude, regionalization, and beta diversity - Arfianti, Tri; Costello, Mark J (Marine Ecology Progress Series, 2020)
Studying the biogeography of amphipod crustaceans is of interest because they play an important role at lower trophic levels in ecosystems. Because they lack a planktonic larval stage, it has been hypothesized that marine benthic amphipod crustaceans may have short dispersal distances, high endemicity, and spatial turnover in species composition, and consequently high global species richness. In this study, we examined over 400000 distribution records of 4876 amphipod species, and identified 12 regions of endemicity. The number and percent of endemic species peaked at 30°-35°S and coincided with 3 of these regions of high endemicity: Australia, New Zealand, and southern Africa. Pelagic species of marine amphipod crustaceans were more cosmopolitan than benthic species. The latitudinal patterns of richness (alpha, gamma, and ES50) and species turnover were at least bimodal. Most occurrence records and greater alpha and gamma richness were in mid-latitudes, reflecting sampling bias. Both ES50 and beta diversity had similar richness in the tropics, mid-latitudes, and on the Antarctic shelf around 70°S. These 2 indices exhibited a sharp dip in the deep Southern Ocean at 55°S. ES50 peaked at 30°-35°S and a small dip was apparent near the equator at 5°-10°N. Beta diversity was driven mostly by turnover rather than nestedness. These findings support the need for conservation in each realm of species endemicity and for amphipods, particularly in Antarctica and the coastal mid-latitudes (30°-35°S) of the Southern Hemisphere. KEYWORDS: Endemicity · Latitudinal gradients · Conservation · Species richness · Species turnover
Keywords: Sørishavet; biogeografi; crustacea; krepsdyr; marin biologi; marine økosystemer; zoogeografi

Solar UV radiation measurements in Marambio, Antarctica, during years 2017–2019 - Aun, Margit; Lakkala, Kaisa; Sanchez, Ricardo; Asmi, Eija; Nollas, Fernando; Meinander, Outi; Sogacheva, Larisa; De Bock, Veerle; Arola, Antti; de Leeuw, Gerrit; Aaltonen, Veijo; Bolsee, David; et al. (Atmospheric Chemistry and Physics (Print), 2020)
In March 2017, measurements of downward global irradiance of ultraviolet (UV) radiation were started with a multichannel GUV-2511 radiometer in Marambio, Antarctica (64.23∘ S; 56.62∘ W), by the Finnish Meteorological Institute (FMI) in collaboration with the Servicio Meteorológico Nacional (SMN). These measurements were analysed and the results were compared to previous measurements performed at the same site with the radiometer of the Antarctic NILU-UV network during 2000–2008 and to data from five stations across Antarctica. In 2017/2018 the monthly-average erythemal daily doses from October to January were lower than those averaged over 2000–2008 with differences from 2.3 % to 25.5 %. In 2017/2018 the average daily erythemal dose from September to March was 1.88 kJ m−2, while in 2018/2019 it was 23 % larger (2.37 kJ m−2). Also at several other stations in Antarctica the UV radiation levels in 2017/2018 were below average. The maximum UV indices (UVI) in Marambio were 6.2 and 9.5 in 2017/2018 and 2018/2019, respectively, whereas during years 2000–2008 the maximum was 12. Cloud cover, the strength of the polar vortex and the stratospheric ozone depletion are the primary factors that influence the surface UV radiation levels in Marambio. The lower UV irradiance values in 2017/2018 are explained by the high ozone concentrations in November, February and for a large part of October. The role of cloud cover was clearly seen in December, and to a lesser extent in October and November, when cloud cover qualitatively explains changes which could not be ascribed to changes in total ozone column (TOC). In this study, the roles of aerosols and albedo are of minor influence because the variation of these factors in Marambio was small from one year to the other. The largest variations of UV irradiance occur during spring and early summer when noon solar zenith angle (SZA) is low and the stratospheric ozone concentration is at a minimum (the so-called ozone hole). In 2017/2018, coincident low total ozone column and low cloudiness near solar noon did not occur, and no extreme UV indices were measured.
Publisher: Copernicus Publications
Keywords: Antarktis; forskningsstasjoner; meteorologi; målinger; ozonlaget; ultrafiolett stråling

CO2 Increase Experiments Using the CESM: Relationship to Climate Sensitivity and Comparison of CESM1 to CESM2 - Bacmeister, Julio; Hannay, Cecile; Medeiros, Brian; Gettelman, Andrew; Neale, Richard; Fredriksen, Hege-Beate; Lipscomb, William H; Simpson, Isla; Bailey, David; Holland, Marika; Lindsay, Keith; Otto-Bliesner, Bette (Journal of Advances in Modeling Earth Systems, 2020)
We examine the response of the Community Earth System Model Versions 1 and 2 (CESM1 and CESM2) to abrupt quadrupling of atmospheric CO2 concentrations (4xCO2) and to 1% annually increasing CO2 concentrations (1%CO2). Different estimates of equilibrium climate sensitivity (ECS) for CESM1 and CESM2 are presented. All estimates show that the sensitivity of CESM2 has increased by 1.5 K or more over that of CESM1. At the same time the transient climate response (TCR) of CESM1 and CESM2 derived from 1%CO2 experiments has not changed significantly—2.1 K in CESM1 and 2.0 K in CESM2. Increased initial forcing as well as stronger shortwave radiation feedbacks are responsible for the increase in ECS seen in CESM2. A decomposition of regional radiation feedbacks and their contribution to global feedbacks shows that the Southern Ocean plays a key role in the overall behavior of 4xCO2 experiments, accounting for about 50% of the total shortwave feedback in both CESM1 and CESM2. The Southern Ocean is also responsible for around half of the increase in shortwave feedback between CESM1 and CESM2, with a comparable contribution arising over tropical ocean. Experiments using a thermodynamic slab-ocean model (SOM) yield estimates of ECS that are in remarkable agreement with those from fully coupled Earth system model (ESM) experiments for the same level of CO2 increase. Finally, we show that the similarity of TCR in CESM1 and CESM2 masks significant regional differences in warming that occur in the 1%CO2 experiments for each model.
Keywords: Sørishavet; atmosfæren; fysikk; karbondioksid; klimaendringer; klimagasser; klimamodeller; klimatologi; menneskelig påvirkning; meteorologi; skyer

Surviving the Antarctic Winter—Life Stage Cold Tolerance and Ice Entrapment Survival in The Invasive Chironomid Midge Eretmoptera murphyi - Bartlett, Jesamine C; Convey, Peter; Hayward, Scott A L (Insects, 2020)
Keywords: Antarktis; fjærmygg; insektfysiologi; invasjonsbiologi; kuldeeksponering; kuldetoleranse; mikroklima; overvintring; termiske terskler; zoologi

Signature of Ocean Warming at the Mixed Layer Base - Clément, Louis; McDonagh, Elaine L; Marzocchi, Alice; Nurser, A J George (Geophysical Research Letters, 2020)
The warming climate influences the ocean by changing its wind-driven dynamics and by inputting extra heat. This study analyzes the warming where temperature anomalies penetrate the ocean interior, that is, by focusing on the winter mixed layer base. This allows to distinguish regions where ocean circulation contributes to warm anomalies from locations where density-compensated temperature anomalies locally enter the ocean along isopycnals. Multidecadal (1980–2018) local temperature trends from a hydrographic data set are examined at the winter mixed layer base and partitioned into components relating to isopycnal movement (heave) and change along isopycnals (spice). Subtropical gyres and western boundary currents show warming larger than the global average that mostly projects onto heave. This is the result of the strengthening of the circulation in the Southern Hemisphere subtropical gyres and is related to both wind-driven changes and Southern Ocean warming. Subtropical regions of surface salinity maxima are influenced by warm anomalies along isopycnals.
Keywords: Sørishavet; havet; havstrømmer; klimaendringer; oppvarming; oseanografi

The ice flux to the Lambert Glacier and Amery Ice Shelf along the Chinese inland traverse and implications for mass balance of the drainage basins, East Antarctica - Cui, Xiangbin; Du, Wenjia; Xie, Huan; Sun, Bo (Polar Research, 2020)
Study of the mass balance of the Antarctic Ice Sheet is critical to estimate its potential contribution to global sea-level rise in the future. As the largest drainage system, the Lambert Glacier–Amery Ice Shelf drainage system plays an important role in the mass balance of the Antarctic Ice Sheet. In this study, the ice thickness measured by airborne ice-penetrating radar with high spatial resolution and accuracy and accurate ice velocity measured by in situ GPS stations along the route of the Chinese National Antarctic Research Expedition inland traverse were used to calculate the ice flux with unprecedented accuracy. This transverse is from Zhongshan Station to Dome A, passing through the east side of the Lambert Glacier and the smaller coastal glacier in the C-Cp basin. The results show that the ice flux across the entire traverse is 24.7 ± 2.8 Gt a−1, along which the section in drainage basin B–C (Lambert Glacier) has an ice flux of 20.9 ± 1.9 Gt a−1 and the section in drainage basin C–Cp (basin adjacent to Lambert Glacier) contributed 3.8 ± 0.4 Gt a−1. The ice flux values in both regions are coincident with the mass balance calculated from the Ice, Cloud, and Land Elevation Satellite, Earth Observing System. Meanwhile, the C–Cp basin shows an ice flux value of 6.6 ± 0.8 Gt a−1 across the grounding line.
Keywords: Antarktis; havnivåstigning; innlandsis; klimaendringer; målinger

Necessary Conditions for Warm Inflow Toward the Filchner Ice Shelf, Weddell Sea - Daae, Kjersti; Hattermann, Tore; Darelius, Elin Maria K; Mueller, Rachael D; Naughten, Kaitlin A; Timmermann, Ralph; Hellmer, Hartmut H (Geophysical Research Letters, 2020)
Understanding changes in Antarctic ice shelf basal melting is a major challenge for predicting future sea level. Currently, warm Circumpolar Deep Water surrounding Antarctica has limited access to the Weddell Sea continental shelf; consequently, melt rates at Filchner-Ronne Ice Shelf are low. However, large-scale model projections suggest that changes to the Antarctic Slope Front and the coastal circulation may enhance warm inflows within this century. We use a regional high-resolution ice shelf cavity and ocean circulation model to explore forcing changes that may trigger this regime shift. Our results suggest two necessary conditions for supporting a sustained warm inflow into the Filchner Ice Shelf cavity: (i) an extreme relaxation of the Antarctic Slope Front density gradient and (ii) substantial freshening of the dense shelf water. We also find that the on-shelf transport over the western Weddell Sea shelf is sensitive to the Filchner Trough overflow characteristics.
Keywords: Sørishavet; Weddellhavet; glasiologi; havnivåstigning; innlandsis; isbrem; isshelf; klimaendringer

High inter- and intraspecific niche overlap among three sympatrically breeding, closely related seabird species: Generalist foraging as an adaptation to a highly variable environment? - Dehnhard, Nina; Achurch, Helen; Clarke, Judy; Michel, Loïc N; Southwell, Colin; Sumner, Michael D; Eens, Marcel; Emmerson, Louise (Journal of Animal Ecology, 2020)
Ecological niche theory predicts sympatric species to show segregation in their spatio-temporal habitat utilization or diet as a strategy to avoid competition. Similarly, within species individuals may specialize on specific dietary resources or foraging habitats. Such individual specialization seems to occur particularly in environments with predictable resource distribution and limited environmental variability. Still, little is known about how seasonal environmental variability affects segregation of resources within species and between closely related sympatric species. The aim of the study was to investigate the foraging behaviour of three closely related and sympatrically breeding fulmarine petrels (Antarctic petrels Thalassoica antarctica, cape petrels Daption capense and southern fulmars Fulmarus glacialoides) in a seasonally highly variable environment (Prydz Bay, Antarctica) with the aim of assessing inter- and intraspecific overlap in utilized habitat, timing of foraging and diet and to identify foraging habitat preferences. We used GPS loggers with wet/dry sensors to assess spatial habitat utilization over the entire breeding season. Trophic overlap was investigated using stable isotope analysis based on blood, feathers and egg membranes. Foraging locations were identified using wet/dry data recorded by the GPS loggers and expectation-maximization binary clustering. Foraging habitat preferences were modelled using generalized additive models and model cross-validation. During incubation and chick-rearing, the utilization distribution of all three species overlapped significantly and species also overlapped in the timing of foraging during the day—partly during incubation and completely during chick-rearing. Isotopic centroids showed no significant segregation between at least two species for feathers and egg membranes, and among all species during incubation (reflected by blood). Within species, there was no individual specialization in foraging sites or environmental space. Furthermore, no single environmental covariate predicted foraging activity along trip trajectories. Instead, best-explanatory environmental covariates varied within and between individuals even across short temporal scales, reflecting a highly generalist behaviour of birds. Our results may be explained by optimal foraging theory. In the highly productive but spatio-temporally variable Antarctic environment, being a generalist may be key to finding mobile prey—even though this increases the potential for competition within and among sympatric species.
Keywords: Antarktis; biologging; klimaendringer; observasjoner; ornitologi; overvåking; sjøfugler; stabile isotoper; zoologi; økologi; økosystemer

Antarctic petrels ‘on the ice rocks’: wintering strategy of an Antarctic seabird - Delord, Karine; Kato, Akiko; Tarroux, Arnaud; Orgeret, Florian; Cotté, Cedric; Ropert-Coudert, Yan; Cherel, Yves; Descamps, Sébastien (Royal Society Open Science, 2020)
There is a paucity of information on the foraging ecology, especially individual use of sea-ice features and icebergs, over the non-breeding season in many seabird species. Using geolocators and stable isotopes, we defined the movements, distribution and diet of adult Antarctic petrels Thalassoica antarctica from the largest known breeding colony, the inland Svarthamaren, Antarctica. More specifically, we examined how sea-ice concentration and free-drifting icebergs affect the distribution of Antarctic petrels. After breeding, birds moved north to the marginal ice zone (MIZ) in the Weddell sector of the Southern Ocean, following its northward extension during freeze-up in April, and they wintered there in April–August. There, the birds stayed predominantly out of the water (60–80% of the time) suggesting they use icebergs as platforms to stand on and/or to rest. Feather δ15N values encompassed one full trophic level, indicating that birds fed on various proportions of crustaceans and fish/squid, most likely Antarctic krill Euphausia superba and the myctophid fish Electrona antarctica and/or the squid Psychroteuthis glacialis. Birds showed strong affinity for the open waters of the northern boundary of the MIZ, an important iceberg transit area, which offers roosting opportunities and rich prey fields. The strong association of Antarctic petrels with sea-ice cycle and icebergs suggests the species can serve, year-round, as a sentinel of environmental changes for this remote region.
Keywords: Sørishavet; Weddellhavet; biologi; geolokalisering; havis; isberg; isfjell; klimaendringer; miljøendringer; ornitologi; petreller; sjøfugler; sjøis; økologi

Atmospheric and Oceanographic Signatures in the Ice Shelf Channel Morphology of Roi Baudouin Ice Shelf, East Antarctica, Inferred From Radar Data - Drews, Reinhard; Schannwell, Clemens; Ehlers, Todd A; Gladstone, Rupert; Pattyn, Frank; Matsuoka, Kenichi (Journal of Geophysical Research: Earth Surface, 2020)
Ice shelves around Antarctica can provide back stress for outlet glaciers and control ice sheet mass loss. They often contain narrow bands of thin ice termed ice shelf channels. Ice shelf channel morphology can be interpreted through surface depressions and exhibits junctions and deflections from flowlines. Using ice flow modeling and radar, we investigate ice shelf channels in the Roi Baudouin Ice Shelf. These are aligned obliquely to the prevailing easterly winds. In the shallow radar stratigraphy, syncline and anticline stacks occur beneath the upwind and downwind side, respectively. The structures are horizontally and vertically coherent, except near an ice shelf channel junction where patterns change structurally with depth. Deeper layers truncate near basal incisions. Using ice flow modeling, we show that the stratigraphy is ∼9 times more sensitive to atmospheric variability than to oceanic variability. This is due to the continual adjustment toward flotation. We propose that syncline-anticline pairs in the shallow stratigraphy are caused by preferential snow deposition on the windward side and wind erosion at the downwind side. This drives downwind deflection of ice shelf channels of several meters per year. The depth variable structures indicate formation of an ice shelf channel junction by basal melting. We conclude that many ice shelf channels are seeded at the grounding line. Their morphology farther seaward is shaped on different length scales by ice dynamics, the ocean, and the atmosphere. These processes act on finer (subkilometer) scales than are captured by most ice, atmosphere, and ocean models, yet the dynamics of ice shelf channels may have broader implications for ice shelf stability.
Keywords: Sørishavet; brehylle; geofysikk; glasiologi; innlandsis; isbrem; isshelf

Nutrient Distribution in East Antarctic Summer Sea Ice: A Potential Iron Contribution From Glacial Basal Melt - Duprat, Luis; Corkill, Matthew; Genovese, Cristina; Townsend, Ashley T; Moreau, Sébastien; Meiners, Klaus M; Lannuzel, Delphine (Journal of Geophysical Research: Oceans, 2020)
Antarctic sea ice can incorporate high levels of iron (Fe) during its formation and has been suggested as an important source of this essential micronutrient to Southern Ocean surface waters during the melt season. Over the last decade, a limited number of studies have quantified the Fe pool in Antarctic sea ice, with a focus on late winter and spring. Here we study the distribution of operationally defined dissolved and particulate Fe from nine sites sampled between Wilkes Land and King George V Land during austral summer 2016/2017. Results point toward a net heterotrophic sea-ice community, consistent with the observed nitrate limitation (<1 μM). We postulate that the recycling of the high particulate Fe pool in summer sea ice supplies sufficient (∼3 nM) levels of dissolved Fe to sustain ice algal growth. The remineralization of particulate Fe is likely favored by high concentrations of exopolysaccharides (113–16,290 μg xeq L−1) which can serve as a hotspot for bacterial activity. Finally, results indicate a potential relationship between glacial meltwater discharged from the Moscow University Ice Shelf and the occurrence of Fe-rich (∼4.3 μM) platelet ice in its vicinity. As climate change is expected to result in enhanced Fe-rich glacial discharge and changes in summer sea-ice extent and quality, the processes influencing Fe distribution in sea ice that persists into summer need to be better constrained.
Keywords: Sørishavet; alger; fytoplankton; havis; klimaendringer; marin biologi; oseanografi; sjøis

Prolonged high-grade metamorphism of supracrustal gneisses from Mühlig-Hofmannfjella, central Dronning Maud Land (East Antarctica) - Elvevold, Synnøve; Engvik, Ane K.; Abu-Alam, Tamer S.; Myhre, Per Inge; Corfu, Fernando (Precambrian Research, 2020)
The bedrock of Mühlig-Hofmannfjella, central Dronning Maud Land in eastern Antarctica, is part of the high-grade Maud Belt and comprises a deep-seated metamorphic-plutonic complex. The P-T-t evolution of anatectic supracrustal gneisses has been recovered through a study of mineral assemblages, textural relationships and U-Pb ID TIMS geochronology on zircon and monazite followed by pseudosection modelling. Peak conditions reached granulite facies conditions (T ≥ 810–820 °C) at moderate crustal depths (P = ca. 8 kbar) and resulted in partial melting. Peak-pressure conditions were followed by isothermal decompression at elevated temperatures. After exhumation to crustal levels of about 4–5 kbar, the area underwent a final near-isobaric cooling, which is documented by a secondary growth of garnet. Zircons indicate a period of growth at 570–566 Ma, whereas monazite ages range from 610 to 525 Ma. A likely heat source for the granulite facies metamorphism is decay of radioactive heat-producing elements in the core of the orogen. The combined geochronology and metamorphic data indicate a prolonged, clockwise P-T path, which reflects collision and formation of a long-lived orogenic plateau.
Article number: 105618
Keywords: Antarktis; Dronning Maud Land; geologi

Full-Depth Global Estimates of Ocean Mesoscale Eddy Mixing From Observations and Theory - Groeskamp, Sjoerd; LaCasce, Joseph H; McDougall, Trevor J; Rogé, Marine (Geophysical Research Letters, 2020)
Mixing by mesoscale eddies profoundly impacts climate and ecosystems by redistributing and storing dissolved tracers such as heat and carbon. Eddy mixing is parameterized in most numerical models of the ocean and climate. To reduce known sensitivity to such parameterizations, observational estimates of mixing are needed. However, logistical and technological limitations obstruct our ability to measure global time-varying mixing rates. Here, we extend mixing length theory with mean-flow suppression theory, and first surface modes, to estimate mixing from readily available observational-based climatological data, of salinity, temperature, pressure, and eddy kinetic energy at the sea surface. The resulting full-depth global maps of eddy mixing can reproduce the few available direct estimates and confirm the importance of mean-flow suppression of mixing. The results also emphasize the significant effect of eddy surface intensification and its relation to the vertical density stratification. These new insights in mixing dynamics will improve future mesoscale eddy mixing parameterizations.
Keywords: Sørishavet; geovitenskap; havet; klimatologi; polarområdene; vannvirvler; økosystemer

Supercooled Southern Ocean Waters - Haumann, F Alexander; Moorman, Ruth; Riser, Stephen C; Smedsrud, Lars H; Maksym, Ted; Wong, Annie P S; Wilson, Earle A; Drucker, Robert; Talley, Lynne D; Johnson, Kenneth S; Key, Robert M; Sarmiento, Jorge L (Geophysical Research Letters, 2020)
In cold polar waters, temperatures sometimes drop below the freezing point, a process referred to as supercooling. However, observational challenges in polar regions limit our understanding of the spatial and temporal extent of this phenomenon. We here provide observational evidence that supercooled waters are much more widespread in the seasonally ice-covered Southern Ocean than previously reported. In 5.8% of all analyzed hydrographic profiles south of 55°S, we find temperatures below the surface freezing point (“potential” supercooling), and half of these have temperatures below the local freezing point (“in situ” supercooling). Their occurrence doubles when neglecting measurement uncertainties. We attribute deep coastal-ocean supercooling to melting of Antarctic ice shelves and surface-induced supercooling in the seasonal sea-ice region to wintertime sea-ice formation. The latter supercooling type can extend down to the permanent pycnocline due to convective sinking plumes—an important mechanism for vertical tracer transport and water-mass structure in the polar ocean.
Keywords: Sørishavet; havis; hydrografi; isbrem; isshelf; oseanografi; polarområdene; sjøis; superkjøling

The Role of Tides in Ocean-Ice Shelf Interactions in the Southwestern Weddell Sea - Hausmann, Ute; Sallée, Jean-Baptiste; Jourdain, Nicolas; Mathiot, Pierre; Rousset, Clément; Madec, Gurvan; Deshayes, Julie; Hattermann, Tore (Journal of Geophysical Research: Oceans, 2020)
To investigate the role of tides in Weddell Sea ocean-ice shelf melt interactions, and resulting consequences for ocean properties and sea ice interactions, we develop a regional ocean-sea ice model configuration, with time-varying ocean boundary and atmospheric forcing, including the deep open ocean (at 2.5–4 km horizontal resolution), the southwestern continental shelf (≈2.5 km), and the adjacent cavities of eastern Weddell, Larsen, and Filchner-Ronne ice shelves (FRIS, 1.5–2.5 km). Simulated circulation, water mass, and ice shelf melt properties compare overall well with available open ocean and cavity observational knowledge. Tides are shown to enhance the kinetic energy of the time-varying flow in contact with the ice shelves, thereby increasing melt. This dynamically driven impact of tides on net melting is to almost 90% compensated by cooling through the meltwater that is produced but not quickly exported from regions of melting in the Weddell Sea cold-cavity regime. The resulting systematic tide-driven enhancement of both produced meltwater and its refreezing on ascending branches of, especially the FRIS, cavity circulation acts to increase net ice shelf melting (by 50% in respect to the state without tides, ≈50 Gt yr−1). In addition, tides also increase the melt-induced FRIS cavity circulation, and the meltwater export by the FRIS outflow. Simulations suggest attendant changes on the open-ocean southwestern continental shelf, characterized by overall freshening and small year-round sea ice thickening, as well as in the deep southwestern Weddell Sea in the form of a marked freshening of newly formed bottom waters.
Keywords: Sørishavet; Weddellhavet; brehylle; geofysikk; havis; isbrem; isshelf; klimaendringer; klimamodeller; klimatologi; oseanografi; sjøis; tidevann

Tracking of marine predators to protect Southern Ocean ecosystems - Hindell, Mark A; Reisinger, Ryan R; Ropert-Coudert, Yan; Hückstädt, Luis A; Trathan, Philip N; Bornemann, Horst; Charrassin, Jean-Benoît; Chown, Steven L; Costa, Daniel P; Danis, Bruno; Lea, Mary-Anne; Thompson, David; et al. (Nature, 2020)
Southern Ocean ecosystems are under pressure from resource exploitation and climate change1,2. Mitigation requires the identification and protection of Areas of Ecological Significance (AESs), which have so far not been determined at the ocean-basin scale. Here, using assemblage-level tracking of marine predators, we identify AESs for this globally important region and assess current threats and protection levels. Integration of more than 4,000 tracks from 17 bird and mammal species reveals AESs around sub-Antarctic islands in the Atlantic and Indian Oceans and over the Antarctic continental shelf. Fishing pressure is disproportionately concentrated inside AESs, and climate change over the next century is predicted to impose pressure on these areas, particularly around the Antarctic continent. At present, 7.1% of the ocean south of 40°S is under formal protection, including 29% of the total AESs. The establishment and regular revision of networks of protection that encompass AESs are needed to provide long-term mitigation of growing pressures on Southern Ocean ecosystems.
Keywords: Sørishavet; klimaendringer; marin biologi; marine økosystemer; miljøvern; overvåking

Neoproterozoic geodynamic evolution of easternmost Kalahari: Constraints from U-Pb-Hf-O zircon, Sm-Nd isotope and geochemical data from the Schirmacher Oasis, East Antarctica - Jacobs, Joachim; Mikhalsky, Evgeny; Henjes-Kunst, Friedhelm; Läufer, Andreas; Thomas, Robert J; Elburg, Marlina; Wang, Chengcheng; Estrada, Solveig; Skublov, S G (Precambrian Research, 2020)
Late Tonian (ca. 785–760 Ma) granodioritic to granitic orthogneisses of the Schirmacher Oasis region in Dronning Maud Land (DML), East Antarctica, are interpreted as recording an active continental margin setting at the periphery of Kalahari and Rodinia. The rocks probably represent exposures of a significant tectonic province hidden beneath the ice, the erosional remnants of which are recorded as detrital zircons in late Tonian-Cryogenian metasedimentary rocks throughout central and eastern DML, as well as in ice-rafted debris from recent sediments offshore Dronning Maud Land. The orthogneisses have single-stage Sm-Nd model ages of ca. 1.3–1.5 Ga and zircon Hf-signatures (εHft = +2 – +5), indistinguishable from the adjacent Grenville-age basement rocks of easternmost Kalahari. Their geochemistry suggests that they evolved in the late stages of a continental margin magmatic arc and possibly within a roll-back tectonic framework, suggestive of subduction of relatively old oceanic lithosphere. The eastern Kalahari continental arc is one of a number of continental arcs that characterize the western part of the fragmenting Rodinia and document the supercontinent “turning inside out” after its formation at ca. 1000 Ma and a period of relative tectonic quiescence between ca. 900 and 800 Ma. The rocks show an ultra-high temperature metamorphic overprint that was accompanied by syn-tectonic magmatism from ca. 650 to 600 Ma. The high temperature metamorphism is interpreted to relate to back-arc extension that also led to major anorthosite magmatism elsewhere, prior to continental collision in the region. The rocks lack the subsequent widespread high-grade metamorphic overprint at ca. 590–500 Ma which occurs in the adjacent regions due to Himalayan-style continental collision along the East African-Antarctic Orogen during Gondwana assembly.
Keywords: Dronning Maud Land; geokronologi; geologi

Networks of international co-authorship in journal articles about Antarctic research, 1998–2015 - Jang, Duckhee; Doh, Soogwan; Choi, Yongjin (Polar Research, 2020)
This study seeks insight into the social structure of Antarctic research from 1998 to 2015 by examining peer-reviewed journal articles listed in the Science Citation Index of the Web of Science database. This study identifies leading countries in peer-reviewed journal article output and applies social network analysis methods to identify countries where authors are collaborating with those affiliated with organizations in different countries. The results show that the number of publications on Antarctica and the proportion of international research collaboration increased from 23.0 to 33.2% during the period of time being considered. The number of articles published by authors affiliated with institutions in emerging countries such as China, Turkey, Brazil and South Korea rose, whereas the proportion of articles published by authors affiliated with institutions in the United States decreased. The largest proportion of academic publications pertaining to Antarctic research was within the natural sciences. Within this broad field, the majority of publications fell within Earth and related environmental sciences and the biological sciences. Social network analysis shows that Antarctic research moved towards a network, in which researchers are internationally more connected than ever before, with countries such as the United States, the United Kingdom, Germany, France and Australia in central positions. Sweden, Belgium and the Netherlands did not account for a high percentage of academic contributions but were still notable for their multinational collaborative research.
Keywords: Antarktis; forskning; publikasjoner; vitenskap

Interhemispheric Asymmetry of Large-Scale Electron Density Gradients in the Polar Cap Ionosphere: UT and Seasonal Variations - Jin, Yaqi; Xiong, Chao (Journal of Geophysical Research: Space Physics, 2020)
The high-latitude ionosphere is highly dynamical with significant irregularities and density gradients. However, the spatial and temporal distributions of density gradients and irregularities are very different between the Arctic and Antarctic. In this report, we study the interhemispheric asymmetry of the large-scale (100 km) density gradients in both polar caps. Our results show that density gradients in the Arctic are enhanced during local winter (December solstice) with a peak around 19 UT. The UT and spatial distributions in the Antarctic local winter (June solstice) are similar to the Arctic except that they are reversed by 12 hr, which indicates a mirror symmetry between hemispheres. The 12-hr difference in the peak density gradients can be explained by the displacements between the geographic and geomagnetic poles. The only asymmetry (anomaly) is the persistence of strong density gradients in the southern polar cap during local summer (December solstice).
Keywords: Antarktis; fysikk; geovitenskap; ionosfæren; polarområdene

Militærpsykologisk forskning i felt: En case-studie av biologiske markører under solokryssing av Antarktisk - Johnsen, Bjørn Helge; Gjeldnes, Rune; Neteland, Hans Olav Monsen; Thayer, Julian F; Phillips, Terry M (Necesse, 2020)
Tradisjonelt har registrering av blodparametere i militærpsykologisk og medisinsk forskning krevd betydelige logistiske, økonomiske og faglige ressurser. Dette har vanskeliggjort bruken av slike parametere. Imidlertid er det utviklet alternative metoder og denne case-studien undersøker anvendeligheten av «Dried Blood Spots» (DBS) under polare forhold. Det første målet med studien er en utprøving av anvendbarheten av DBS (registrering, lagring og ekstrahering av variabler), ana- lysert ved hjelp av “recycling immunoaffinity chromotography», under ekstreme polare feltmessige forhold. Det andre målet med studien var å undersøke om stress og immunparametere målt ved DBS gjenspeiler subjektive evalueringer av belastning under skimarsjen. Det tredje målet var å beskrive hormonelle og immun-responser under ekstreme polare belastninger. Metoden som ble benyttet var DBS registrert under en 90 dagers solo-ekspedisjon uten etterforsyninger, gjennomført over syd- polområdet. Ekspedisjonen var verdens lengste skitur. Resultatene viste at alle 16 planlagte parametere ble ekstrahert med suksess ni måneder etter ekspedisjonen. For å undersøke samvariasjonen mellom subjektive opplevelser og biologiske markører på belastning ble kortisolnivå og pro- og anti-inflammatoriske markører (IL-6 og IL- 10) sammenlignet med polfarerens dagbok. Basert på dagboken ble seks faser med ulik belastning identifisert. Resultatene viste at kortisol og IL-6 responser samvarierte med disse fasene. Resultatene viste også ekstreme kortisol og IL-6 responser under mestring av ekspedisjonen. DBS viste seg dermed som en relevant metode for bruk i felt, under polare betingelser.
Publisher: FHS, Sjøkrigsskolen
Keywords: Antarktis; ekspedisjoner; medisin; psykofysiologi; psykologi

Growth-related changes in salt gland mass in gentoo and chinstrap penguin chicks - Kim, Youmin; Jeong, Min-Su; Seo, Hae-Min; Kim, Hankyu; Lee, Woo-Shin; Choi, Chang-Yong (Polar Research, 2020)
The salt gland is a well-developed osmoregulation organ in marine birds, and its relative size often reflects an individual’s feeding environment and osmoregulation capability. The development and functions of salt glands have been described for the Adélie penguin (Pygoscelis adeliae), but this information has been poorly documented in the other two pygoscelid species: gentoo (P. papua) and chinstrap penguins (P. antarcticus). To describe the growth-related changes in salt gland masses in relation to chick growth, we measured the wet mass of the salt glands collected from dead gentoo and chinstrap chicks during the early breeding period. The mass of the salt glands was linearly proportional to their body measurements, especially to body mass, in both species, and no significant difference was detected between the two species. Penguins are obligate marine dwellers throughout their life cycle, and the development of the salt gland in penguin chicks suggests that their ability to regulate dietary osmotic stress begins at an early stage of development after hatching. Furthermore, the linear relationship between the gland mass and body mass also suggests that the osmoregulation capability may continue to develop as penguin chicks grow. This descriptive note provides novel and quantitative information on the early developmental pattern of salt glands in gentoo and chinstrap penguins.
Keywords: Antarktis; marine økosystemer; ornitologi; osmoregulering; osmotisk stress; pingviner; saltkjertel; zoologi

Antarctic minke whales find ice gaps along the ice edge in foraging grounds of the Indo-Pacific sector (60° E and 140° E) of the Southern Ocean - Konishi, Kenji; Isoda, Tatsuya; Bando, Takeharu; Minamikawa, Shingo; Kleivane, Lars (Polar Biology, 2020)
Keywords: Sørishavet; forskning; hvaler; krill; marin biologi; næring

Validation of the TROPOspheric Monitoring Instrument (TROPOMI) surface UV radiation product - Lakkala, Kaisa; Kujanpää, Jukka; Brogniez, Colette; Henriot, Nicolas; Arola, Antti; Aun, Margit; Auriol, Frédérique; Bais, Alkiviadis F; Bernhard, Germar; De Bock, Veerle; Catalfamo, Maxime; Deroo, Christine; et al. (Atmos. Meas. Tech., 2020)
The TROPOspheric Monitoring Instrument (TROPOMI) onboard the Sentinel-5 Precursor (S5P) satellite was launched on 13 October 2017 to provide the atmospheric composition for atmosphere and climate research. The S5P is a Sun-synchronous polar-orbiting satellite providing global daily coverage. The TROPOMI swath is 2600 km wide, and the ground resolution for most data products is 7.2×3.5 km2 (5.6×3.5 km2 since 6 August 2019) at nadir. The Finnish Meteorological Institute (FMI) is responsible for the development of the TROPOMI UV algorithm and the processing of the TROPOMI surface ultraviolet (UV) radiation product which includes 36 UV parameters in total. Ground-based data from 25 sites located in arctic, subarctic, temperate, equatorial and Antarctic areas were used for validation of the TROPOMI overpass irradiance at 305, 310, 324 and 380 nm, overpass erythemally weighted dose rate/UV index, and erythemally weighted daily dose for the period from 1 January 2018 to 31 August 2019. The validation results showed that for most sites 60 %–80 % of TROPOMI data was within ±20 % of ground-based data for snow-free surface conditions. The median relative differences to ground-based measurements of TROPOMI snow-free surface daily doses were within ±10 % and ±5 % at two-thirds and at half of the sites, respectively. At several sites more than 90 % of cloud-free TROPOMI data was within ±20 % of ground-based measurements. Generally median relative differences between TROPOMI data and ground-based measurements were a little biased towards negative values (i.e. satellite data < ground-based measurement), but at high latitudes where non-homogeneous topography and albedo or snow conditions occurred, the negative bias was exceptionally high: from −30 % to −65 %. Positive biases of 10 %–15 % were also found for mountainous sites due to challenging topography. The TROPOMI surface UV radiation product includes quality flags to detect increased uncertainties in the data due to heterogeneous surface albedo and rough terrain, which can be used to filter the data retrieved under challenging conditions.
Publisher: Copernicus Publications
Keywords: Antarktis; atmosfæren; klimatologi; meteorologi; ultrafiolett stråling

Coherent Seasonal Acceleration of the Weddell Sea Boundary Current System Driven by Upstream Winds - Le Paih, Nicolas; Hattermann, Tore; Boebel, Olaf; Kanzow, Torsten; Lüpkes, Christof; Rohardt, Gerd; Strass, Volker; Herbette, Steven (Journal of Geophysical Research: Oceans, 2020)
The Weddell Sea is of global importance in the formation of dense bottom waters associated with sea ice formation and ocean-ice sheet interaction occurring on the shelf areas. In this context, the Weddell Sea boundary current system (BCS) presents a major conduit for transporting relatively warm water to the Weddell Sea ice shelves and for exporting some modified form of Wedell Sea deep and bottom waters into the open ocean. This study investigates the downstream evolution of the structure and the seasonality of the BCS along the Weddell Sea continental slope, combining ocean data collected for the past two decades at three study locations. The interannual-mean geostrophic flow, which follows planetary potential vorticity contours, shifts from being surface intensified to bottom intensified along stream. The shift occurs due to the densification of water masses and the decreasing surface stress that occurs westward, toward the Antarctic Peninsula. A coherent along-slope seasonal acceleration of the barotropic flow exists, with maximum speed in austral autumn and minimum speed in austral summer. The barotropic flow significantly contributes to the seasonal variability in bottom velocity along the tip of the Antarctic Peninsula. Our analysis suggests that the winds on the eastern/northeastern side of the gyre determines the seasonal acceleration of the barotropic flow. In turn, they might control the export of Weddell Sea Bottom Water on seasonal time scales. The processes controlling the baroclinic seasonality of the flow need further investigation.
Keywords: Sørishavet; Weddellhavet; batymetri; havstrømmer; innlandsis; kontinentalmargin; oseanografi

CloudSat-Inferred Vertical Structure of Snowfall Over the Antarctic Continent - Lemonnier, Florentin; Madeleine, Jean-Baptiste; Claud, Chantal; Palerme, Cyril; Genthon, Christophe; L'Ecuyer, Tristan; Wood, Norman B (Journal of Geophysical Research: Atmospheres, 2020)
Current global warming is causing significant changes in snowfall in polar regions, directly impacting the mass balance of the ice caps. The only water supply in Antarctica, precipitation, is poorly estimated from surface measurements. The onboard cloud-profiling radar of the CloudSat satellite provided the first real opportunity to estimate solid precipitation at continental scale. Based on CloudSat observations, we propose to explore the vertical structure of precipitation in Antarctica over the 2007–2010 period. A first division of this data set following a topographical approach (continent vs. peripheral regions, with a 2,250 m topographical criterion) shows a high snowfall rate (275 mm yr at 1,200 m above ground level) with low relative seasonal variation ( ) over the peripheral areas. Over the plateau, the snowfall rate is low (34 mm yr at 1,200 m above ground level) with a much larger relative seasonal variation ( ). A second study that follows a geographical division highlights the average vertical structure of precipitation and temperature depending on the regions and their interactions with topography. In particular, over ice shelves, we see a strong dependence of the distribution of snowfall on the sea ice coverage. Finally, the relationship between precipitation and temperature is analyzed and compared with a simple analytical relationship. This study highlights that precipitation is largely dependent on the advection of air masses along the topographic slopes with an average vertical wind of 0.02 m s . This provides new diagnostics to evaluate climate models with a three-dimensional approach of the atmospheric structure of precipitation.
Keywords: Antarktis; global oppvarming; klimamodeller; klimatologi; meteorologi; nedbør; polarområdene; snøfall

Calving Event Led to Changes in Phytoplankton Bloom Phenology in the Mertz Polynya, Antarctica - Liniger, Guillaume; Strutton, Peter G.; Lannuzel, Delphine; Moreau, Sebastien (Journal of Geophysical Research: Oceans, 2020)
Polynyas are subject to variability in winds and ocean circulation and are important sites of ecological productivity. In February 2010, the B09B iceberg collided with the Mertz Glacier Tongue (MGT), calving a 78 × 40-km giant iceberg which modified the icescape and primary productivity of the Mertz polynya. In this study, we use satellite ocean color and sea ice concentration to investigate the variability, trends, and drivers of phytoplankton blooms in the Mertz polynya since 1997. During the bloom, over 21 years, we found (i) a later ice retreat time, (ii) an increase in sea ice concentration, (iii) a decrease in open-water period, (iv) a later bloom start, and (v) a decrease in bloom duration. Our results suggest that major postcalving changes in the physical characteristics of the polynya, mainly its icescape, are the primary drivers of phytoplankton phenology. More specifically, the MGT calving event resulted in significant seasonal and regional changes, with higher eastern chl-a and mean summer chl-a postcalving. While satellite data are useful to study long-term variability in these inhospitable areas, they only focus on the ocean surface and are obscured by ice and clouds. Additional subsurface parameters from seal tags, gliders and moorings in the southernmost polar regions would strengthen our comprehension of phytoplankton and physical changes in ocean dynamics that may have far-reaching consequences, from global circulation to carbon export.
Keywords: Sørishavet; fytoplankton; havsirkulasjon; isbre; kalving; marin biologi; marine økosystemer; oseanografi; polynja

Distribution and source of glycerol dialkyl glycerol tetraethers (GDGTs) and the applicability of GDGT-based temperature proxies in surface sediments of Prydz Bay, East Antarctica - Liu, Ruijuan; Han, Zhengbing; Zhao, Jun; Zhang, Haifeng; Li, Dong; Ren, Jianye; Pan, Jianming; Zhang, Haisheng (Polar Research, 2020)
Reliable records of Southern Ocean seawater palaeotemperatures are important because this region plays a significant role in regulating global climate change. Biomarkers such as GDGT-based indices have been effectively used to reconstruct seawater temperatures. We analysed the composition and distribution of iGDGTs, OH-GDGTs and brGDGTs and calculated GDGT-based temperature indices in surface sediments from Prydz Bay, East Antarctica. Our results showed that iGDGTs, OH-GDGTs and brGDGTs are all produced in situ, with iGDGTs and OH-GDGTs mostly synthesized by Thaumarchaeota. Concentrations of iGDGTs, OH-GDGTs and brGDGTs showed similar spatial distributions and decreased from the continental shelf towards the deep ocean. The highest concentrations were in the inner bay, which is attributed to a combination of (1) bathymetry that reduces water exchange, (2) the Prydz Bay Gyre stabilizing the upper water column and (3) sea ice that releases archaea and bacteria. Among the temperature indices based on iGDGTs, OH-GDGTs and combinations therein, those based on OH-GDGTs showed the strongest correlation with seawater temperature. Some OH-GDGT-based indices (e.g., OH-0/OHs, OH-1/OHs, OH-2/OHs and RI-OH′) exhibited a stronger correlation with annual subsurface ocean temperature (100–200 m), which may be related to archaeal habitats and production mechanisms. Our study suggests that RI-OH′ and OH-0/OHs could be used as indicators of annual subsurface ocean temperature in Antarctic marginal seas.
Keywords: Sørishavet; arkebakterier; batymetri; biomarkører; klimaendringer; oseanografi; sjøvann; temperatur; økosystemer

Will Climate Change Impact Polar NOx Produced by Energetic Particle Precipitation? - Maliniemi, Ville; Marsh R., Daniel; Tyssøy, Hilde Nesse; Smith-Johnsen, Christine (Geophysical Research Letters, 2020)
Energetic electron precipitation (EEP) is an important source of polar nitrogen oxides (NOx) in the upper atmosphere. During winter, mesospheric NOx has a long chemical lifetime and is transported to the stratosphere by the mean meridional circulation. Climate change is expected to accelerate this circulation and therefore increase polar mesospheric descent rates. We investigate the Southern Hemispheric polar NOx distribution during the 21st century under a variety of future scenarios using simulations of the Whole Atmosphere Community Climate Model (WACCM). We simulate stronger polar mesospheric descent in all future scenarios that increase the atmospheric radiative forcing. Polar NOx in the upper stratosphere is significantly enhanced in two future scenarios with the largest increase in radiative forcing. This indicates that the ozone depleting NOx cycle will become more important in the future, especially if stratospheric chlorine species decline. Thus, EEP-related atmospheric effects may become more prominent in the future.
Keywords: Antarktis; geofysikk; klimaendringer; klimatologi; ozonlaget; polarområdene; romvitenskap

Deep glacial troughs and stabilizing ridges unveiled beneath the margins of the Antarctic ice sheet - Morlighem, Mathieu; Rignot, Eric; Binder, Tobias; Blankenship, Donald; Drews, Reinhard; Eagles, Graeme; Eisen, Olaf; Ferraccioli, Fausto; Forsberg, René; Fretwell, Peter; Goel, Vikram; Greenbaum, Jamin S; et al. (Nature Geoscience, 2020)
The Antarctic ice sheet has been losing mass over past decades through the accelerated flow of its glaciers, conditioned by ocean temperature and bed topography. Glaciers retreating along retrograde slopes (that is, the bed elevation drops in the inland direction) are potentially unstable, while subglacial ridges slow down the glacial retreat. Despite major advances in the mapping of subglacial bed topography, significant sectors of Antarctica remain poorly resolved and critical spatial details are missing. Here we present a novel, high-resolution and physically based description of Antarctic bed topography using mass conservation. Our results reveal previously unknown basal features with major implications for glacier response to climate change. For example, glaciers flowing across the Transantarctic Mountains are protected by broad, stabilizing ridges. Conversely, in the marine basin of Wilkes Land, East Antarctica, we find retrograde slopes along Ninnis and Denman glaciers, with stabilizing slopes beneath Moscow University, Totten and Lambert glacier system, despite corrections in bed elevation of up to 1 km for the latter. This transformative description of bed topography redefines the high- and lower-risk sectors for rapid sea level rise from Antarctica; it will also significantly impact model projections of sea level rise from Antarctica in the coming centuries.
Keywords: Antarktis; glasiologi; innlandsis; klimaendringer

The glacial geomorphology of western Dronning Maud Land, Antarctica - Newall, Jennifer C H; Dymova, Taisiya; Serra, Elena; Blomdin, Robin; Fredin, Hans Ola; Glasser, Neil F; Suganuma, Yusuke; Harbor, Jonathan M; Stroeven, Arjen P (Journal of Maps, 2020)
Reconstructing the response of present-day ice sheets to past global climate change is important for constraining and refining the numerical models which forecast future contributions of these ice sheets to sea-level change. Mapping landforms is an essential step in reconstructing glacial histories. Here we present a new map of glacial landforms and deposits on nunataks in western Dronning Maud Land, Antarctica. Nunataks are mountains or ridges that currently protrude through the ice sheet and may provide evidence that they have been wholly or partly covered by ice, thus indicating a formerly more extensive (thicker) ice sheet. The map was produced through a combination of mapping from Worldview satellite imagery and ground validation. The sub-metre spatial resolution of the satellite imagery enabled mapping with unprecedented detail. Ten landform categories have been mapped, and the landform distributions provide evidence constraining spatial patterns of a previously thicker ice sheet.
Publisher: Taylor & Francis
Keywords: Dronning Maud Land; geomorfologi; innlandsis; klimaendringer; nunataker; paleoglasiologi

Post-depositional loss of nitrate and chloride in Antarctic snow by photolysis and sublimation: a field investigation - Noro, Kazushi; Takenaka, Norimichi (Polar Research, 2020)
Nitrate in snow is subject to post-depositional processing, which leads to a net loss and redistribution within the snowpack. The relative importance of post-depositional loss processes such as the volatilization of nitric acid (HNO3) and photolysis of nitrate has long been debated. Changes in nitrate and chloride concentrations in the snowpack were investigated at H128 (69°23.584’S, 41°33.712’E), an Antarctic coastal site approximately 100 km from Syowa Station in East Antarctica from December 2015 to February 2016. Results indicate that chloride migrated to deeper sites within the snowpack under the influence of water vapour movement. Moreover, 50% of the nitrate on surface snow was lost to photolysis, and approximately 20% of the nitrate was absent at a depth of 40 cm. To enhance our knowledge of the Antarctic geochemical cycle, this study is the first to suggest chloride ion movement in snowpacks or significant nitrate loss for any Antarctic coastal site.
Keywords: Antarktis; geokjemi; kromatografi; observasjoner; ozon; snø; temperatur

Pathogen surveillance in Southern Ocean pinnipeds - Núñez-Egido, Sandra; Lowther, Andrew; Nymo, Ingebjørg H.; Klein, Jörn; Breines, Eva M.; Tryland, Morten (Polar Research, 2020)
Knowledge of the health status and potential effect of disease outbreaks among Southern Ocean fauna may be decisive for its conservation. We assessed the exposure and infection of Antarctic fur seals (Arctocephalus gazella, AFS) and Southern elephant seals (Mirounga leonine, SES) to parapoxvirus, Phocid alphaherpesvirus-1 (PhHV-1), smooth Brucella spp. and Toxoplasma gondii. AFS (n = 65) serum and swab samples, and SES (n = 13) serum samples from the sub–Antarctic island of Bouvetøya (54°25’S, 03°22’E) were collected during two austral summers (2014/15, 2017/18). Three polymerase chain reaction (PCR) tests amplifying the DNA polymerase, B2L and GIF parapoxvirus genomic regions were performed, investigating DNA from mucosal swab samples. The glycoprotein B gene was targeted to detect PhHV-1 viral DNA. Sera were assayed for T. gondii and smooth Brucella spp. antibodies with indirect enzyme-linked immunosorbent assays. Parapoxvirus PCR amplicons of the expected size were generated in two of the 29 AFS pups (nasal swabs, 2014/15), targeting the B2L (n = 2) and DNA polymerase (n = 1) genes, whereas the GIF PCR did not amplify target sequences. The PCR amplicons were sequenced and blasted in GenBank, revealing highest similarity with a seal parapoxvirus, confirming the presence of the virus in AFS for the first time. No PhHV-1 amplicons were generated, and antibodies against T. gondii or smooth Brucella spp. were not detected. Our data indicate that these seals are host for parapoxvirus but are neither exposed to smooth Brucella spp. nor T. gondii. Evidence of PhHV-1 shedding was not detected.
Keywords: Bouvetøya; Sørishavet; epidemiologi; fylogenetikk; infeksjon; marin biologi; marin zoologi; pelsseler; pinnipedier; serologi; sjøelefanter; virologi

New Antarctic clawed lobster species (Crustacea: Decapoda: Nephropidae) from the Upper Cretaceous of James Ross Island - Pinheiro, Allysson P; Saraiva, Antônio Álamo Feitosa; Santana, William; Sayão, Juliana Manso; Figueiredo, Rodrigo Giesta; Rodrigues, Taissa; Weinschütz, Luiz Carlos; Ponciano, Luiza Corral Martins de Oliveira; Kellner, Alexander Wilhelm Armin (Polar Research, 2020)
A new species of nephropid lobster, Hoploparia echinata sp. nov., from the James Ross Island in the Antarctic Peninsula is here described and illustrated. The material was collected in the Santa Marta Formation (Santonian–-Campanian), the basal unit of the Marambio Group, Larsen Basin, located in the western portion of the Antarctic Peninsula. Hoploparia echinata sp. nov. can easily be differentiated from its congeners by the presence of distinct short spines on dorsal and ventral margins on the third maxillipeds, merus of the chelipeds and pereopods; these are the characters not described in other Hoploparia species so far.
Keywords: Antarktis; fossiler; geologi; langhalekreps; paleobiologi; paleogeografi; paleontologi; zoologi

Discovery of a large population of Hygrolembidium isophyllum (Lepidoziaceae, Marchantiophyta) in the South Shetland Islands, Antarctica - Putzke, Jair; Ramos Ferrari, Flávia; Schaefer, Carlos E. G. R. (Polar Research, 2020)
In February 2019, during fieldwork at Harmony Point, Nelson Island, South Shetland Islands, Antarctica, a large population of the rare liverwort Hygrolembidium isophyllum (Lepidoziaceae) was discovered. The occurrence of this rare species reinforces the need to preserve Antarctic Specially Protected Area 133.
Keywords: Antarktis; biologi; levermoser; miljøvern; planter

The retrospective analysis of Antarctic tracking data project - Ropert-Coudert, Yan; Van de Putte, Anton P; Reisinger, Ryan R; Bornemann, Horst; Charrassin, Jean-Benoît; Costa, Daniel P; Danis, Bruno; Hückstädt, Luis A; Jonsen, Ian D; Lea, Mary-Anne; Thompson, David; Torres, Leigh G; et al. (Scientific Data, 2020)
The Retrospective Analysis of Antarctic Tracking Data (RAATD) is a Scientific Committee for Antarctic Research project led jointly by the Expert Groups on Birds and Marine Mammals and Antarctic Biodiversity Informatics, and endorsed by the Commission for the Conservation of Antarctic Marine Living Resources. RAATD consolidated tracking data for multiple species of Antarctic meso- and top-predators to identify Areas of Ecological Significance. These datasets and accompanying syntheses provide a greater understanding of fundamental ecosystem processes in the Southern Ocean, support modelling of predator distributions under future climate scenarios and create inputs that can be incorporated into decision making processes by management authorities. In this data paper, we present the compiled tracking data from research groups that have worked in the Antarctic since the 1990s. The data are publicly available through biodiversity.aq and the Ocean Biogeographic Information System. The archive includes tracking data from over 70 contributors across 12 national Antarctic programs, and includes data from 17 predator species, 4060 individual animals, and over 2.9 million observed locations.
Keywords: Antarktis; Sørishavet; biologi; økologi; økosystem

Exceptionally Warm and Prolonged Flow of Warm Deep Water Toward the Filchner-Ronne Ice Shelf in 2017 - Ryan, Svenja; Hellmer, Hartmut H; Janout, Markus; Darelius, Elin; Vignes, Lucie; Schröder, Michael (Geophysical Research Letters, 2020)
The Filchner-Ronne Ice Shelf, fringing the southern Weddell Sea, is Antarctica's second largest ice shelf. At present, basal melt rates are low due to active dense water formation; however, model projections suggest a drastic increase in the future due to enhanced inflow of open-ocean warm water. Mooring observations from 2014 to 2016 along the eastern flank of the Filchner Trough (76°S) revealed a distinct seasonal cycle with inflow if Warm Deep Water during summer and autumn. Here we present extended time series showing an exceptionally warm and long inflow in 2017, with maximum temperatures exceeding 0.5°C. Warm temperatures persisted throughout winter, associated with a fresh anomaly, which lead to a change in stratification over the shelf, favoring an earlier inflow in the following summer. We suggest that the fresh anomaly developed upstream after anomalous summer sea ice melting and contributed to a shoaling of the shelf break thermocline.
Keywords: Sørishavet; Weddellhavet; batymetri; brehylle; geofysikk; havis; isbrem; kontinentalsokkel; oseanografi; sjøis; smelting

Modeling of the Influence of Sea Ice Cycle and Langmuir Circulation on the Upper Ocean Mixed Layer Depth and Freshwater Distribution at the West Antarctic Peninsula - Schultz, Cristina; Doney, Scott C.; Zhang, Weifeng Gordon; Regan, Heather; Holland, Paul R.; Meredith, Michael P.; Stammerjohn, Sharon (Journal of Geophysical Research: Oceans, 2020)
The Southern Ocean is chronically undersampled due to its remoteness, harsh environment, and sea ice cover. Ocean circulation models yield significant insight into key processes and to some extent obviate the dearth of data; however, they often underestimate surface mixed layer depth (MLD), with consequences for surface water-column temperature, salinity, and nutrient concentration. In this study, a coupled circulation and sea ice model was implemented for the region adjacent to the West Antarctic Peninsula, a climatically sensitive region which has exhibited decadal trends towards higher ocean temperature, shorter sea ice season, and increasing glacial freshwater input, overlain by strong interannual variability. Hindcast simulations were conducted with different air-ice drag coefficients and Langmuir circulation parameterizations to determine the impact of these factors on MLD. Including Langmuir circulation deepened the surface mixed layer, with the deepening being more pronounced in the shelf and slope regions. Optimal selection of an air-ice drag coefficient also increased modeled MLD by similar amounts and had a larger impact in improving the reliability of the simulated MLD interannual variability. This study highlights the importance of sea ice volume and redistribution to correctly reproduce the physics of the underlying ocean, and the potential of appropriately parameterizing Langmuir circulation to help correct for biases towards shallow MLD in the Southern Ocean. The model also reproduces observed freshwater patterns in the West Antarctic Peninsula during late summer and suggests that areas of intense summertime sea ice melt can still show net annual freezing due to high sea ice formation during the winter.
Keywords: Sørishavet; havis; klimatologi; langmuirsirkulasjon; oseanografi; sjøis

Snowfall and Water Stable Isotope Variability in East Antarctica Controlled by Warm Synoptic Events - Servettaz, Aymeric P M; Orsi, Anais J; Curran, Mark A J; Moy, Andrew D; Landais, Amaelle; Agosta, Cécile; Winton, V Holly L; Touzeau, Alexandra; McConnell, Joseph R; Werner, Martin; Baroni, Mélanie (Journal of Geophysical Research: Atmospheres, 2020)
Understanding climate proxy records that preserve physical characteristics of past climate is a prerequisite to reconstruct long-term climatic conditions. Water stable isotope ratios (δ18O) constitute a widely used proxy in ice cores to reconstruct temperature and climate. However, the original climate signal is altered between the formation of precipitation and the ice, especially in low-accumulation areas such as the East Antarctic Plateau. Atmospheric conditions under which the isotopic signal is acquired at Aurora Basin North (ABN), East Antarctica, are characterized with the regional atmospheric model Modèle Atmosphérique Régional (MAR). The model shows that 50% of the snow is accumulated in less than 24 days year−1. Snowfall occurs throughout the year and intensifies during winter, with 64% of total accumulation between April and September, leading to a cold bias of −0.86°C in temperatures above inversion compared to the annual mean of −29.7°C. Large snowfall events are associated with high-pressure systems forcing warm oceanic air masses toward the Antarctic interior, which causes a warm bias of +2.83°C. The temperature-δ18O relationship, assessed with the global atmospheric model ECHAM5-wiso, is primarily constrained by the winter variability, but the observed slope is valid year-round. Three snow δ18O records covering 2004–2014 indicate that the anomalies recorded in the ice core are attributable to the occurrence of warm winter storms bringing precipitation to ABN and support the interpretation of δ18O in this region as a marker of temperature changes related to large-scale atmospheric conditions, particularly blocking events and variations in the Southern Annular Mode.
Keywords: Antarktis; iskjerner; meteorologi; nedbør; paleoklimatologi; vannstabile isotoper

Ionosfæriske scintillasjoner på GNSS-signaler over Dronning Maud Land, Antarktis: statistikk og kasusstudier - Skjæveland, Arnlaug Høgås (Universitetet i Oslo, 2020)
I denne oppgaven er forekomsten av fasescintillasjoner på GNSS-signaler over deler av Dronning Maud Land i Antarktis kartlagt, ved bruk av scintillasjonsmottakere på Troll stasjonen (geografiske koordinater: 72.0◦S, 2.5◦Ø, magnetiske koordinater: 62.8◦S, 47.8◦Ø) og SANAE IV (geografiske koordinater: 71.7◦S, 2.8◦V, magnetiske koordinater: 62.0◦S, 45.0◦Ø). Ionosfæren i dette området er lite studert tidligere, og dette er de første resultatene som presenteres fra det nylig etablerte Troll ionosfæriske observatoriet. Den første delen av oppgaven er en statistisk studie hvor forekomsten av scintillasjoner i 2018 er kartlagt. Hovedfunnet i denne studien er at høye fasescintillasjoner kun forekommer ved høy geomagnetisk aktivitet, forekomsten av scintillasjoner er høyere postmidnatt enn premidnatt og at scintillasjoner forekommer både innenfor og nord for den statistiske auroraovalen. I denne oppgaven er det også gjennomført to kasusstudier, en fra februar 2018 og en fra mars 2018. Kasusstudiene brukte satellittdata fra solvinden, Swarm, DMSP og bakkebaserte instrumenter: scintillasjonsmottakere, magnetometere og Superdarn, fra både den nordlige og sørlige halvkule. Hovedfunnene fra kasusstudiene er at scintillasjoner på Troll og Sanae kan assosieres med partikkelnedbør, sterke vestgående strømmer og høye konveksjonshastigheter. De viste også en hvis symmetri i forekomsten av scintillasjoner, men scintillasjonene var kraftigere og var til stede over en lengre tidsperiode i Antarktis enn på Færøyene.
Publication Title: Institutt for fysikk. Det matematisk-naturvitenskapelige fakultet Volume: M.Sc.
Keywords: Antarktis; Dronning Maud Land; Troll forskningsstasjon; aurora; geomagnetiske stormer; ionosfæren; romfysikk; sørlys

Detailed Seismic Bathymetry Beneath Ekström Ice Shelf, Antarctica: Implications for Glacial History and Ice-Ocean Interaction - Smith, Emma C; Hattermann, Tore; Kuhn, Gerhard; Gaedicke, Christoph; Berger, Sophie; Drews, Reinhard; Ehlers, Todd A; Franke, Dieter; Gromig, Rapahel; Hofstede, Coen; Lambrecht, Astrid; Läufer, Andreas; et al. (Geophysical Research Letters, 2020)
The shape of ice shelf cavities are a major source of uncertainty in understanding ice-ocean interactions. This limits assessments of the response of the Antarctic ice sheets to climate change. Here we use vibroseis seismic reflection surveys to map the bathymetry beneath the Ekström Ice Shelf, Dronning Maud Land. The new bathymetry reveals an inland-sloping trough, reaching depths of 1,100 m below sea level, near the current grounding line, which we attribute to erosion by palaeo-ice streams. The trough does not cross-cut the outer parts of the continental shelf. Conductivity-temperature-depth profiles within the ice shelf cavity reveal the presence of cold water at shallower depths and tidal mixing at the ice shelf margins. It is unknown if warm water can access the trough. The new bathymetry is thought to be representative of many ice shelves in Dronning Maud Land, which together regulate the ice loss from a substantial area of East Antarctica.
Keywords: Dronning Maud Land; batymetri; brehylle; glasiologi; havnivåstigning; innlandsis; isbrem; issmelting; klimaendringer; kontinentalsokkel; seismologi

Isfrontene i Antarktis blokkerer varme havstrømmer - Steiger, Nadine (forskersonen.no, 2020)
Antarktis kan virke som det sover under en beskyttende dyne av snø og is. Kontinentet har vært lite påvirket av menneskelig aktivitet, men har nå begynt å våkne. Klimaendringene har nådd fram til det frosne kontinentet ved Sørpolen. Relativt varme og salte havstrømmer kommer seg nå helt inn til isen. Men satellitter viser at det smelter mindre is enn det som hadde vært mulig med den tilgjengelige mengden varme. Vi har brukt observasjoner og resultater fra laboratoriet for å forklare hvor det varme vannet blir av.
Keywords: Antarktis; havnivåstigning; issmelting; klimaendringer; menneskelig påvirkning; populærvitenskap

Ground-based measurements of total ozone column amount with a multichannel moderate-bandwidth filter instrument at the Troll research station, Antarctica - Sztipanov, Milos; Tumeh, Lubna; Li, Wei; Svendby, Tove; Kylling, Arve; Dahlback, Arne; Stamnes, Jakob J; Hansen, Georg; Stamnes, Knut (Applied Optics, 2020)
Combining information from several channels of the Norwegian Institute for Air Research (NILU-UV) irradiance meter, one may determine the total ozone column (TOC) amount. A NILU-UV instrument has been deployed and operated on two locations at Troll research station in Jutulsessen, Queen Maud Land, Antarctica, for several years. The method used to determine the TOC amount is presented, and the derived TOC values are compared with those obtained from the Ozone Monitoring Instrument (OMI) located on NASA’s AURA satellite. The findings show that the NILU-UV TOC amounts correlate well with the results of the OMI and that the NILU-UV instruments are suitable for monitoring the long-term change and development of the ozone hole. Because of the large footprint of OMI, NILU-UV is a more suitable instrument for local measurements.
Publisher: OSA
Keywords: Dronning Maud Land; Troll forskningsstasjon; meteorologi; overvåkning; ozonhull; ozonlaget; ultrafiolett stråling

Foraging tactics in dynamic sea-ice habitats affect individual state in a long-ranging seabird - Tarroux, Arnaud; Cherel, Yves; Fauchald, Per; Kato, Akiko; Love, Oliver P; Ropert-Coudert, Yan; Spreen, Gunnar; Varpe, Øystein; Weimerskirch, Henri; Yoccoz, Nigel G; Zahn, Sandrine; Descamps, Sébastien (Functional Ecology, 2020)
Abstract Individual heterogeneity in diet and foraging behaviour is common in wild animal populations, and can be a strong determinant of how populations respond to environmental changes. Within populations, variation in foraging behaviour and the occurrence of individual tactics in relation to resources distribution can help explain differences in individual fitness, and ultimately identify important factors affecting population dynamics. We examined how foraging behaviour and habitat during the breeding period related to the physiological state of a long-ranging seabird adapted to sea ice, the Antarctic petrel Thalassoica antarctica. Firstly, using GPS tracking and state-switching movement modelling (hidden Markov models) on 124 individual birds, we tested for the occurrence of distinct foraging tactics within our study population. Our results highlight a large variation in the movement and foraging behaviour of a very mobile seabird, and delineate distinct foraging tactics along a gradient from foraging in dense pack ice to foraging in open water. Secondly, we investigated the effects of these foraging tactics on individual state at return from a foraging trip. We combined movement data with morphometric and physiological measurements of a suite of plasma metabolites that provided a general picture of a bird's individual state. Foraging in denser sea ice was associated with lower gain in body mass during brooding, as well as lower level of energy acquisition (plasma triacylglycerol) during both brooding and incubation. We found no clear relationship between the foraging tactic in relation to sea ice and the energetic stress (changes in plasma corticosterone), energetic balance (β-hydroxybutyrate) or trophic level (δ15N). However, a shorter foraging range was related to both the energetic balance (positively) and the trophic level (negatively). Our results highlight a diverse range of foraging tactics in relation to sea ice in Antarctic petrels. While the various foraging tactics do not seem to strongly alter energetic balance, they may affect other aspects of Antarctic petrels' physiology. Future changes in sea-ice habitats can thus be expected to have an impact on the individual state of seabirds such as Antarctic petrels, which could ultimately affect their population dynamics. Nonetheless, strong individual heterogeneity in the use of sea-ice habitats by a typical pagophilic species might strengthen its resilience to environmental changes and in particular to forecasted sea-ice loss. A free Plain Language Summary can be found within the Supporting Information of this article.
Keywords: Sørishavet; fôring; havis; marin biologi; miljøendringer; observasjoner; ornitologi; petreller; sjøfugler; sjøis; smelting; zoologi

Microcontinents and Continental Fragments Associated With Subduction Systems - van den Broek, Joost M; Gaina, Carmen (Tectonics, 2020)
Microcontinents and continental fragments are small pieces of continental crust that are surrounded by oceanic lithosphere. Although classically associated with passive margin formation, here we present several preserved microcontinents and continental fragments associated with subduction systems. They are located in the Coral Sea, South China Sea, central Mediterranean and Scotia Sea regions, and a “proto-microcontinent,” in the Gulf of California. Reviewing the tectonic history of each region and interpreting a variety of geophysical data allows us to identify parameters controlling the formation of microcontinents and continental fragments in subduction settings. All these tectonic blocks experienced long, complex tectonic histories with an important role for developing inherited structures. They tend to form in back-arc locations and separate from their parent continent by oblique or rotational kinematics. The separated continental pieces and associated marginal basins are generally small and their formation is quick (<50 Myr). Microcontinents and continental fragments formed close to large continental masses tend to form faster than those created in systems bordered by large oceanic plates. A common triggering mechanism for their formation is difficult to identify, but seems to be linked with rapid changes of complex subduction dynamics. The young ages of all contemporary pieces found in situ suggest that microcontinents and continental fragments in these settings are short lived. Although presently the amount of in-situ subduction-related microcontinents is meager (an area of 0.56% and 0.28% of global, non-cratonic, continental crustal area and crustal volume, respectively), through time microcontinents contributed to terrane amalgamation and larger continent formation.
Keywords: Sørishavet; batymetri; geofysikk; geologi; geovitenskap; litosfæren; tektonikk

Sea Ice CO2 Dynamics Across Seasons: Impact of Processes at the Interfaces - Van der Linden, Fanny; Tison, Jean-Louis; Champenois, Willy; Moreau, Sébastien; Carnat, Gauthier; Kotovitch, Marie; Fripiat, François; Deman, Florian; Roukaerts, Arnout; Dehairs, Frank; Wauthy, Sarah; Lourenço, Antonio; et al. (Journal of Geophysical Research: Oceans, 2020)
Winter to summer CO2 dynamics within landfast sea ice in McMurdo Sound (Antarctica) were investigated using bulk ice pCO2 measurements, air-snow-ice CO2 fluxes, dissolved inorganic carbon (DIC), total alkalinity (TA), and ikaite saturation state. Our results suggest depth-dependent biotic and abiotic controls that led us to discriminate the ice column in three layers. At the surface, winter pCO2 supersaturation drove CO2 release to the atmosphere while spring-summer pCO2 undersaturation led to CO2 uptake most of the time. CO2 fluxes showed a diel pattern superimposed upon this seasonal pattern which was potentially assigned to either ice skin freeze-thaw cycles or diel changes in net community production. In the ice interior, the pCO2 decrease across the season was driven by physical processes, mainly independent of the autotrophic and heterotrophic phases. Bottom sea ice was characterized by a massive biomass build-up counterintuitively associated with transient heterotrophic activity and nitrate plus nitrite accumulation. This inconsistency is likely related to the formation of a biofilm. This biofilm hosts both autotrophic and heterotrophic activities at the bottom of the ice during spring and may promote calcium carbonate precipitation.
Keywords: Sørishavet; biofilm; biomasse; geokjemi; karbon syklus; karbondioksid; landfast havis; landfast sjøis; oseanografi

Ice front blocking of ocean heat transport to an Antarctic ice shelf - Wåhlin, Anna K; Steiger, Nadine; Darelius, Elin; Assmann, Karen M; Glessmer, Mirjam; Ha, Ho Kyung; Herraiz-Borreguero, Laura; Heuzé, Céline; Jenkins, Adrian; Kim, Tae-Wan; Mazur, Aleksandra K; Sommeria, Joël; et al. (Nature, 2020)
Mass loss from the Antarctic Ice Sheet to the ocean has increased in recent decades, largely because the thinning of its floating ice shelves has allowed the outflow of grounded ice to accelerate. Enhanced basal melting of the ice shelves is thought to be the ultimate driver of change, motivating a recent focus on the processes that control ocean heat transport onto and across the seabed of the Antarctic continental shelf towards the ice. However, the shoreward heat flux typically far exceeds that required to match observed melt rates, suggesting that other critical controls exist. Here we show that the depth-independent (barotropic) component of the heat flow towards an ice shelf is blocked by the marked step shape of the ice front, and that only the depth-varying (baroclinic) component, which is typically much smaller, can enter the sub-ice cavity. Our results arise from direct observations of the Getz Ice Shelf system and laboratory experiments on a rotating platform. A similar blocking of the barotropic component may occur in other areas with comparable ice–bathymetry configurations, which may explain why changes in the density structure of the water column have been found to be a better indicator of basal melt rate variability than the heat transported onto the continental shelf. Representing the step topography of the ice front accurately in models is thus important for simulating ocean heat fluxes and induced melt rates.
Keywords: Antarktis; glasiologi; global oppvarming; innlandsis; issmelting; klimaendringer

Late Neoproterozoic–Cambrian magmatism in Dronning Maud Land (East Antarctica): U–Pb zircon geochronology, isotope geochemistry and implications for Gondwana assembly - Wang, Cheng-Cheng; Jacobs, Joachim; Elburg, Marlina A.; Läufer, Andreas; Elvevold, Synnøve (Precambrian Research, 2020)
Dronning Maud Land (DML) is a key area for the better understanding of the geotectonic history and amalgamation processes of the southern part of Gondwana. Here, we present comprehensive new zircon U–Pb–Hf–O, whole-rock Sm–Nd isotopic and geochemical data for late Neoproterozoic-Cambrian igneous rocks along a profile from central to eastern DML, which provides new insights into the crustal evolution and tectonics of the region. In central DML, magmatism dominantly occurred at 530–485 Ma, with 650–600 Ma charnockite and anorthosite locally distributed at its eastern periphery. In contrast, eastern DML experienced long-term and continuous granitic magmatism from ca. 650 Ma to 500 Ma. In central DML, the 650–600 Ma samples are characterized by highly elevated δ18O (7.5–9.5‰) associated with slightly negative to positive εHf(t) values (−1 to +3), indicating significant addition of high-δ18O crustal components, such as sedimentary material at the margin of the Kalahari Craton. Evolved Hf isotopic signatures (εHf(t) = −15 to −6) and moderately elevated O isotopic data (δ18O = 6–8‰) of the Cambrian granitic rocks from central DML indicate a significant incorporation of the pre-existing, old continental crust. In eastern DML, the suprachondritic Hf–Nd isotope signatures and moderate δ18O values of the late Neoproterozoic granites (650–550 Ma) from the Sør Rondane Mountains support the view that they mainly originated from crust of the Tonian Oceanic Arc Super Terrane (TOAST). The post-540 Ma granites, however, have more evolved Hf and Nd isotopic compositions, suggesting an increasing involvement of older continental components during Cambrian magmatism. Nd isotopes of the Cambrian granitic rocks in DML display an increasingly more radiogenic composition towards the east with model ages ranging from late Archean to Mesoproterozoic times, which is in line with the isotopic trend of the Precambrian basement in this region. The late Neoproterozoic (>600 Ma) igneous rocks in central and eastern DML were emplaced in two independent subduction systems, at the periphery of the eastern Kalahari Craton and somewhere within the Mozambique Ocean respectively. The accretion and assembly of the TOAST to the eastern margin of the Kalahari Craton and their collision with surrounding continental blocks was followed by extensive post-collisional magmatism due to delamination tectonics and orogenic collapse in the Cambrian. The late Neoproterozoic–Cambrian igneous rocks in DML thus record an orogenic cycle from subduction-accretion, continental collision to post-collisional process during and after the assembly of Gondwana.
Article number: 105880
Keywords: Dronning Maud Land; geokjemi; geokronologi; geologi

Grenville-age continental arc magmatism and crustal evolution in central Dronning Maud Land (East Antarctica): Zircon geochronological and Hf–O isotopic evidence - Wang, Cheng-Cheng; Jacobs, Joachim; Elburg, Marlina A.; Läufer, Andreas; Thomas, Robert J.; Elvevold, Synnøve (Gondwana Research, 2020)
This study focusses on the Grenville-age Maud Belt in Dronning Maud Land (DML), East Antarctica, which was located at the margin of the Proto-Kalahari Craton during the assembly of Rodinia. We present new U–Pb zircon ages and Hf–O isotope analyses of mafic and granitic gneisses exposed in the Orvin-Wohlthat Mountains and Gjelsvikfjella, central DML (cDML). The geochronological data indicate continuous magmatic activity from 1160 to 1070 Ma which culminated at 1110–1090 Ma, followed by high-grade metamorphism between 1080 and 1030 Ma. The majority of zircons from the Orvin-Wohlthat Mountains exhibit radiogenic Hf isotopic compositions corresponding to suprachondritic εHf (t) values and Mesoproterozoic model ages, indicating crystallization from predominantly juvenile magmas. However, the involvement of ancient sedimentary material, which were most likely derived from the adjacent Proto-Kalahari Craton, is revealed by a few samples with negative to neutral εHf (t) and significantly elevated δ18O values (8–10‰). Samples from further west, in Gjelsvikfjella have more mantle-like zircon O isotopic compositions and late Paleoproterozoic Hf model ages, indicating the incorporation of ancient, previously mantle-derived continental crust. The rocks in cDML, thus define part of an extensive Mesoproterozoic magmatic arc with subduction under the Proto-Kalahari margin. This involved significant growth of new continental crust, possibly related to slab retreat, accompanied by subordinate recycling of older crustal components. The Maud Belt has previously been correlated with the 1250–1030 Ma Natal Belt in southern Africa, which lay to the west in the context of Gondwana, although this assertion has recently been questioned. Our study supports the latter view in demonstrating that the continental arc magmatism in the Maud Belt appears to be temporally and tectonically unconnected to the accretion of (slightly older) juvenile oceanic islands in the Natal Belt, which, in contrast to the Maud Belt, show subduction polarity away from the craton. We thus speculate that the Namaqua-Natal to Maud Belt contact (exposed in the Heimefront Shear Zone) may represent a changed tectonic environment from arc/continent-continent collision to slightly younger continental margin orogenesis at the westernmost termination of this part of the global Grenville Orogen. The Maud Belt marks the beginning of a major, long-lived accretionary Andean-type tectonic regime on the eastern margin of Proto-Kalahari in the Meso-Neoproterozoic during Rodinia assembly and break-up until the formation of Gondwana.
Keywords: Dronning Maud Land; geologi

High-precision ice-flow velocities from ground observations on Dalk Glacier, Antarctica - Ai, Songtao; Wang, Shansi; Li, Yuansheng; Moholdt, Geir; Zhou, Chunxia; Liu, Leibao; Yang, Yuande (Polar Science, 2019)
Dalk Glacier, which has been monitored by CHINARE since 2007, is a calving outlet glacier near the Chinese Zhongshan Station in East Antarctica. Using in situ observational azimuthal data from 2007 to 2012, 67 high-precision spatial intersection points were calculated. Consequently, the ice-flow features of the tongue of Dalk Glacier were explored via ground measurements. The maximum observed ice-flow velocity (IV) was 192.72 m/a, at stake P9. The velocities then decreased with the distance from the central flow line on both sides of the glacier in a cross section. Further analysis showed the following: the velocities of each stake increased annually; the closer to the terminus, the faster the ice flowed; and the ascent ratio of the IVs was approximately 10.67 m/a2 in the main flow area. We also observed seasonal variations in the ice-flow velocities, including a speed-up in January 2009 preceding an ice-calving event. The elevation change measurements at the stakes showed fluctuations along the central flow line, which indicates ice-shelf grounding over a seamount that had not been previously identified.
Keywords: Antarktis; glasiologi

What and who is an Antarctic ambassador? - Alexander, Karen A.; Liggett, Daniela; Leane, Elizabeth; Nielsen, Hanne E. F.; Bailey, Jennifer L.; Brasier, Madeline J.; Haward, Marcus (Polar Record, 2019)
The term “Antarctic ambassadorship” is increasingly used to represent an individual’s connection to Antarctica and their subsequent advocacy. However, there is little clarity regarding the concept. To address this, we combined a literature review with an expert elicitation workshop. We argue that (i) the concept of Antarctic ambassador has been understood in myriad ways; (ii) Antarctic ambassadors have a connection to, knowledge of and passion for Antarctica; (iii) they also have a commitment to defending and advancing Antarctic values and (iv) Antarctic ambassadorship is about more than advocacy. We propose the first comprehensive definition of Antarctic ambassadorship. We hope this will provide a cornerstone upon which future research, and a more informed governance of Antarctic tourism, can be built.
Edition: 2020/05/20 Publisher: Cambridge University Press
Keywords: Antarktis; samfunnsfag

Warm Circumpolar Deep Water at the Western Getz Ice Shelf Front, Antarctica - Assmann, Karen; Darelius, Elin Maria K; Wåhlin, Anna K; Kim, Tae Wan; Lee, Sang Hoon (Geophysical Research Letters, 2019)
The Getz Ice Shelf is one of the largest sources of fresh water from ice shelf basal melt in Antarctica. We present new observations from three moorings west of Siple Island 2016–2018. All moorings show a persistent flow of modified Circumpolar Deep Water toward the western Getz Ice Shelf. Unmodified Circumpolar Deep Water with temperatures up to 1.5 °C reaches the ice shelf front in frequent episodes. These represent the warmest water observed at any ice shelf front in the Amundsen Sea. Mean currents within the warm bottom layer of 18–20 cm/s imply an advection time scale of 7 days from shelf break to ice shelf front. Zonal wind stress at the shelf break affects heat content at the ice shelf front on weekly to monthly time scales. Our 2-year mooring records also evince that upwelling over the shelf break controls thermocline depth on subannual to annual time scales.
Keywords: Antarktis; geofysikk; glasiologi; isbrem; isshelf; observasjoner

Chr. Christensen and C. A. Larsen: A comparative analysis of two whaling entrepreneurs - Basberg, Bjørn L (International Journal of Maritime History, 2019)
Keywords: Antarktis; historie; hvalfangere; hvalfangst

The Four Ladies of Prydz Bay: notes on the naming of a submarine formation in Australian Antarctic Territory - Bathie, Carol; Pett, Janet (The Victorian Naturalist, 2019)
Publisher: Field Naturalists Club of Victoria
Keywords: Antarktis; Nordmenn; ekspedisjoner; oppdagelsesreiser

Nitrogen isotope fractionation explains the 15N enrichment of Antarctic cryptogams by volatilized ammonia from penguin and seal colonies - Bokhorst, Stef; van Logtestijn, Richard; Convey, Peter; Aerts, Rien (Polar Research, 2019)
Vegetation near bird and seal rookeries typically has high δ15N signatures and these high values are linked to the enriched δ15N values of rookery soils. However, Antarctic cryptogams are mostly dependent on atmospheric ammonia (NH3) and volatized NH3 from rookeries is severely depleted in δ15N-NH3. So there is an apparent discrepancy between the isotopically depleted source (NH3) and δ15N-enriched vegetation. In this article, we aim to resolve this discrepancy to better understand the mechanisms and processes involved in isotopic changes during nitrogen transfer between Antarctic marine and terrestrial ecosystems. Under laboratory conditions, we quantified whether volatized NH3 affects the isotopic signature of cryptogams. NH3 volatilizing from penguin guano and elephant seal dung was depleted (44–49‰) in δ15N when captured on acidified filters, compared to the source itself. Cryptogams exposed to the volatized NH3 were enriched (18.8–23.9‰) in δ15N. The moss Andreaea regularis gained more nitrogen (0.9%) than the lichen Usnea antarctica (0.4%) from volatilized NH3, indicating a potential difference in atmospheric NH3 acquisition that is consistent with existing field differences in nitrogen concentrations and δ15N between mosses and lichens in general. This study clarifies the δ15N enrichment of cryptogams resulting from one of the most important nitrogen pathways for Antarctic vegetation.
Keywords: Antarktis; fugler; kjemiske analyser; kryptogamer; lav; moser; planter; seler; økologi

Diversity and community structure of bacterioplankton in surface waters off the northern tip of the Antarctic Peninsula - Cao, Shunan; He, Jianfeng; Zhang, Fang; Lin, Ling; Gao, Yuan; Zhou, Qiming (Polar Research, 2019)
Global climate change is significantly affecting marine life off the northern tip of the Antarctic Peninsula, but little is known about microbial ecology in this area. The main goal of this study was to investigate the bacterioplankton community structure in surface waters using pyrosequencing and to determine factors influencing this community. Pelagibacterales and Rhodobacterales (Alphaproteobacteria), Oceanospirillales and Alteromonadales (Gammaproteobacteria), and Flavobacteriales (Bacteroidetes) were the core taxa in our samples, and the five most relatively abundant genera were Pelagibacter, Polaribacter, Octadecabacter, group HTCC2207 and Sulfitobacter. Although nutrients and chlorophyll a (chl a) contributed more to bacterioplankton community structure than water masses or depth, only 30.39% of the variance could be explained by the investigated environmental factors, as revealed by RDA and pRDA. No significant difference with respect to nutrients and chl a was observed among water masses or depth, as indicated by ANOVA. Furthermore, significant correlations among the dominant bacterial genera were more common than correlations between dominant genera and environmental factors, as revealed by Spearman analysis. We conclude that nutrients and chl a become homogeneous and that interpopulation interactions may have a central role in influencing the bacterial community structure in surface waters off the northern tip of the Antarctic Peninsula during the summer.
Keywords: Sørishavet; bakterier; bakterioplankton; fytoplankton; klimaendringer; marin biologi; plankton; pyrosekvensering; zooplankton

Ecological niche modelling of cold-water corals in the Southern Ocean (N Antarctic), present distribution and future projections due to temperature changes - Chaabani, Safa; López-González, Pablo J; Casado-Amezua, Pilar; Pehlke, Hendrik; Weber, Lukas; Martínez-Baraldés, Irene; Jerosch, Kerstin (Marine Ecology Progress Series, 2019)
An urgent necessity to understand the effect of climatic change on scleractinian cold-water coral (CWC) ecosystems has arisen due to increasing ocean warming and acidification over the last decades. Here, presence-absence records of 12 scleractinian CWC species from research expeditions and the literature were compiled and merged with model-generated pseudo-absence data and 14 environmental variables. The best-fitting results of 9 species distribution models (SDMs) were combined to an ensemble habitat suitability model for CWCs in the northern Southern Ocean (Weddell Sea and Antarctic Peninsula) by means of the open-source R package "biomod2". Furthermore, 2 future scenarios of increasing bottom sea temperature were used to investigate the spatial response of scleractinians to temperature change. The resulting (current scenario) potential ecological niches were evaluated with good to excellent statistical measures. The results predict that present areas of highest probability of CWC occurrence are around the Antarctic Peninsula, South Orkney Islands and Queen Maud Land, with preference to geomorphic features such as seamounts. The distribution of CWC habitats is mainly driven by distance to coast and ice shelves, bathymetry, benthic calcium carbonate, and temperature. Under warming conditions, CWCs are predicted to expand their distribution range by 6 and 10% in 2037 and 2150, respectively, compared to the present distribution. The future models using increased bottom temperature revealed a stable CWC distribution for most parts of the study area. However, habitat shifts are expected to the Filchner Trough region, the adjacent continental shelves, as well as to the eastern side of the Antarctic Peninsula. KEYWORDS: Scleractinian coral · Ensemble models · Environmental change · Habitat suitability model · Spatial distribution · Weddell Sea. Antarctica
Keywords: Sørishavet; Weddellhavet; batymetri; biodiversitet; global oppvarming; klimaendringer; marin biologi; miljøendringer; oseanografi; økosystemer

Prey differences drive local genetic adaptation in Antarctic fur seals - Cleary, Alison C; Bester, Marthán; Forcada, Jaume; Goebel, Michael; Goldsworthy, Simon D; Guinet, Christophe; Hoffman, Joseph I; Kovacs, Kit M; Lydersen, Christian; Lowther, Andrew D (Marine Ecology Progress Series, 2019)
Antarctic fur seal (Arctocephalus gazella) colonies are found on sub-Antarctic islands around the continent. These islands experience a range of conditions in terms of physical and biological habitat, creating a natural laboratory to investigate local genetic adaptation. One striking habitat difference is in the availability of Euphausia superba krill as prey, which has led to A. gazella exhibiting a range of diets. A. gazella in some colonies consume exclusively krill, while their conspecifics in other colonies feed mainly on fish and consume few to no krill. To investigate potential adaptations to these different prey fields, reduced representation genome sequencing was conducted on A. gazella from the 8 major colonies. Twenty-seven genomic regions exhibiting signatures of natural selection were identified. Two of these genomic regions were clearly associated with seals living in krill-dominated areas or those in fish-dominated areas. Twenty-two additional genomic regions under selection showed a pattern consistent with prey differences as the driver of selection after historical migrations from krill-dominated habitats where lineages evolved to present krill-poor habitat areas were taken into account. Only 1 of the genomic regions identified appeared to be explained by any other environmental variable analysed (depth). Genomic regions under prey-driven selection included genes associated with regulation of gene expression, skeletal development, and lipid metabolism. Adaptation to local prey has implications for spatial management of this species and for the potential impacts of climate- or harvest-driven reductions in krill abundance on these seals. KEY WORDS: Arctocephalus gazella · Double digest restriction-site associated DNA sequencing · ddRAD · Diet · Euphausia superba · Natural selection
Keywords: Bouvetøya; Sørishavet; genetikk; krill; marin biologi; pelsseler; plankton; zoologi; økosystemer

Patchy Lakes and Topographic Origin for Fast Flow in the Recovery Glacier System, East Antarctica - Diez, Anja; Matsuoka, Kenichi; Jordan, Tom A; Kohler, Jack; Ferraccioli, Fausto; Corr, Hugh F; Olesen, Arne V; Forsberg, René; Casal, Tania G (Journal of Geophysical Research: Earth Surface, 2019)
The Recovery subglacial basin, with its largest glacier Recovery Glacier, has been identified as potentially the biggest contributor to future sea level rise from East Antarctica. Subglacial lakes along the main trunk have been detected from satellite data, with four giant lakes (Recovery Lakes A, B, C, and D) located at the onset of the fast ice flow (≥15 m/yr) and multiple smaller lakes along the glacier. The presence of subglacial water potentially plays a key role in the control of fast ice flow of Recovery Glacier. We present new insights on the Recovery Lakes from airborne radar data collected in 2013 and 2015. Using an adjusted classification scheme, we show that a single large area consisting of smaller lakes connected by likely saturated sediment, referred to as Lake AB, exists in the originally proposed area of the Recovery Lakes A and B. We estimate that the current size of Lake AB is ∼4,320 km2. Water likely leaks from the western shore of Lake AB lubricating the bed initiating fast ice flow at this location. The difference in the outlines of Lake AB and the Lakes A and B previously derived from surface features suggested that a larger paleolake existed here in the past. From our data, we find Recovery Lake C to be dry; we attribute fast ice flow originating from this area to be due to a topographic step and thus an increase in ice thickness rather than enhanced lubrication at the bed.
Keywords: Antarktis; glasiologi; havnivåstigning; innlandsis; radar observasjoner; satellite bilder; subglasial innsjø; topografi

The Norwegian-British-Swedish Antarctic Expedition. Science and politics - Domaas, Christel Misund; Drivenes, Einar-Arne; Bones, Stian (UiT Norges arktiske universitet, 2019)
Publication Title: Institutt for arkeologi, historie, religionsvitenskap og teologi (AHR) Volume: M.Sc. Issue: HIS-3900
Keywords: Dronning Maud Land; Maudheim (Antarktis); Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; forskning; historie; internasjonal; klimaendringer; politikk; samarbeid; vitenskap

Variability of Sediment Accumulation Rates in an Antarctic Fjord - Eidam, Emily F.; Nittrouer, Charles; Lundesgaard, Øyvind; Homolka, Khadijah; Smith, Craig (Geophysical Research Letters, 2019)
Fjords on the West Antarctic Peninsula (WAP) serve as sediment traps, preserving histories of glacial sediment supply. Regional warming trends are expected to change sediment supplies, altering water quality, depositional history, and ecosystem drivers. Our ability to assess magnitudes of these changes is limited by sparse data on modern sediment accumulation. Twelve new cores and four existing cores from Andvord Bay were used to characterize variability in sediment accumulation rates. These range from 1.5 to 7.9 mm/year (0.12 to 0.56 g·cm−2·year−1). Spatial differences and a weak down-fjord gradient in rates suggest diverse sediment sources, including from outside the fjord. This data set provides a comprehensive assessment of sedimentation during the past century, indicating little change in rates due to recent WAP warming, and sets a benchmark for assessing climate-related changes in sediment delivery and ecosystem drivers (e.g., burial disturbance) in the fjord over coming decades.
Keywords: Antarktis; akkumulasjon; bentiske organismer; biodiversitet; fjord; glasiologi; sedimenter; sedimentologi; tidevannsbreen

Geological mapping of Norway's least explored mountains - Elvevold, Synnøve; Myhre, Per Inge; Engvik, Ane K; Jacobs, Joachim (Fram forum, 2019)
Keywords: Dronning Maud Land; ekspedisjoner; geologi; kartlegging; nunataker

Vannet som forandret fjellene - Engvik, Ane K (Bergtatt - Ane K. Engviks blogg, 2019)
Keywords: Dronning Maud Land; fjellene; forskning; geologi; mineralogi; nunataker

Annekteringen av Bouvetøya: Norge og Storbritannia, forhandlingene og de politiske konsekvensene av anneksjonen - Hultin, Jonathan Wegger (Universitetet i Oslo, 2019)
Publication Title: Institutt for arkeologi, konservering og historie Volume: M.Sc.
Keywords: Bouvetøya; Lars Christensen; Norvegia ekspedisjonen; hvalfangst; internasjonal politikk; skipsfart; utenrikspolitikk; økonomi

Assessment of Atmospheric Reanalyses With Independent Observations in the Weddell Sea, the Antarctic - Jonassen, Marius O; Välisuo, Ilona; Vihma, Timo; Uotila, Petteri; Makshtas, Alexander P; Launiainen, Jouko (Journal of Geophysical Research: Atmospheres, 2019)
Surface layer and upper-air in situ observations from two research vessel cruises and an ice station in the Weddell Sea from 1992 and 1996 are used to validate four current atmospheric reanalysis products: ERA-Interim, CFSR, JRA-55, and MERRA-2. Three of the observation data sets were not available for assimilation, providing a rare opportunity to validate the reanalyses in the otherwise datasparse region of the Antarctic against independent data. All four reanalyses produce 2 m temperatures warmer than the observations, and the biases vary from +2.0 K in CFSR to +2.8 K in MERRA-2. All four reanalyses are generally too warm also higher up in the atmospheric boundary layer (ABL), with biases up to +1.4 K (ERA-Interim). Cloud fractions are relatively poorly reproduced by the reanalyses, MERRA-2 and JRA-55 having the strongest positive and negative biases of about +30 % and −17 %, respectively. Skill scores of the error statistics reveal that ERA-Interim compares generally the most favorably against both the surface layer and the upper-air observations. CFSR compares the second best and JRA-55 and MERRA-2 have the least favorable scores. The ABL warm bias is consistent with previous evaluation studies in high latitudes, where more recent observations have been applied. As the amount of observations has varied depending on the decade, season, and region, the consistency of the warm bias suggests a need to improve the modeling systems, including data assimilation as well as ABL and surface parameterizations.
Keywords: Sørishavet; Weddellhavet; atmosfæren; geofysikk; meteorologi; observasjoner

Two species of Lumbricillus (Enchytraeidae, Annelida) new to Antarctica - Lee, Jeounghee; Klinth, Mårten J; Jung, Jongwoo (Polar Research, 2019)
The intertidal fauna of the Antarctic Peninsula has a relatively high species diversity, due to its warmer environment compared to other parts of Antarctica. Marine oligochaetes are, in general, one of the most diverse and ecologically important benthic organism groups, at least in the littoral zone. Antarctica has been one of the least studied areas with regard to oligochaete diversity. Here we report two Lumbricillus species (Lumbricillus antarcticus Stephenson, 1932 and Lumbricillus sejongensis sp. nov.) new to Antarctica, found in a tidal pool on the Barton Peninsula, King George Island. The diversity of this genus remains poorly known for Antarctica and the Subantarctic islands, and what we know is based on a few patchy studies.
Keywords: Sørishavet; belteormer; bentiske organismer; biodiversitet; fauna; marin biologi; tidevann

Field Observations and Physical-Biogeochemical Modeling Suggest Low Silicon Affinity for Antarctic Fast Ice Diatoms - Lim, Stephanie; Moreau, Sébastien; Vancoppenolle, Martin; Deman, Florian; Roukaerts, Arnout; Meiners, K M; Janssens, Julie; Lannuzel, Delphine (Journal of Geophysical Research: Oceans, 2019)
We use field observations from late spring and a one-dimensional sea-ice model to explore a high nutrient, high chlorophyll system in Antarctic land-fast ice. Lack of variability in chlorophyll a concentration and organic carbon content over the 17-day sampling period suggests a balance between macronutrient sources and biological uptake. Nitrate, nitrite, phosphate, and ammonium were measured at concentrations well above salinity-predicted levels, indicating nutrient accumulation fueled by remineralization processes. However, silicic acid (DSi) was depleted relative to seawater and was potentially limiting. One-dimensional physical-biogeochemical sea-ice model simulations at the observation site achieve extremely high algal growth and DSi uptake with a DSi half-saturation constant used for pelagic diatoms (KSi = 3.9 μM) and are not sufficiently improved by tuning the DSi:carbon ratio or DSi remineralization rate. In contrast, diatom biomass in the bottom ice, which makes up 70% of the observed chlorophyll, is simulated using KSi an order of magnitude higher (50 μM), a value similar to that measured in a few Antarctic diatom cultures. Some sea-ice diatoms may therefore experience limitation at relatively high ambient DSi concentrations compared to pelagic diatoms. Our study highlights the urgent need for observational data on sea-ice algal affinity for DSi to further support this hypothesis. A lower algal growth rate increases model predictions of DSi in the upper sea ice to more accurate concentrations. The model currently does not account for the non-diatom communities that dominate those layers, and thus, modeling diatom communities overpredicts DSi uptake in the upper ice.

Quantarctica 3 released - Matsuoka, Kenichi; Skoglund, Anders; Roth, George; Melvær, Yngve; Tronstad, Stein (Fram forum, 2019)
Keywords: Antarktis; geofysikk; geografi; glasiologi; innlandsis; kartografi; satellite bilder

The life cycle of small- to medium-sized icebergs in the Amundsen Sea Embayment - Mazur, Aleksandra K.; Wåhlin, Anna K.; Kalén, Ola (Polar Research, 2019)
An object-based method for automatic iceberg detection has been applied to Advanced Synthetic Aperture Radar images in the Amundsen Sea Embayment (ASE), Antarctica. The images were acquired between 1 January 2006 and 8 April 2012 under varying meteorological, oceanographic and sea-ice conditions. During this time period, the icebergs were counted (average 1370 ± 50) and their surface area was estimated (average 1537.5 km2). The average surface area was about 2.5 times larger than the annual calved area (620 km2), indicating that the average iceberg age in the ASE is about 2.5 years, which was confirmed by observed residence times based on drift tracks. Most of the ASE icebergs were less than 1500 m long, and almost 90% of them were smaller than 2 km2. The proportion of small- and medium-sized icebergs (84.4%) was significantly higher than in the open ocean, where large icebergs (>10 km2) account for nearly the whole iceberg surface area. The opposite was true for the freshly calved icebergs in the ASE. The data indicate that the creation of icebergs in the ASE is dominated by steady small- to medium-scale calving from ice shelves fringing the embayment. In addition, rare calving events of giant icebergs occur on a decadal timescale. There is also some import of icebergs from the Bellingshausen Sea further east along the coast, in particular after large calving events there.
Keywords: Amundsenhavet; Sørishavet; batymetri; fjernmåling; havis; hydrologi; isberg; isbrem; isfjell; kalving; oseanografi; sjøis

A note on digital elevation model smoothing and driving stresses - McCormack, Felicity S; Roberts, Jason L; Jong, Lenneke M; Young, Duncan A; Beem, Lucas H (Polar Research, 2019)
Ice-flow fields, including the driving stress, provide important information on the current state and evolution of Antarctic and Greenland ice-sheet dynamics. However, computation of flow fields from continent-scale DEMs requires the use of smoothing functions and scales, the choice of which can be ad hoc. This study evaluates smoothing functions and scales for robust calculations of driving stress from Antarctic DEMs. Our approach compares a variety of filters and scales for their capacity to minimize the residual between predicted and observed flow direction fields. We find that a spatially varying triangular filter with a width of 8–10 ice thicknesses provides the closest match between the observed and predicted flow direction fields. We use the predicted flow direction fields to highlight artefacts in observed Antarctic velocities, demonstrating that comparison of multiple observational data sets has utility for quality control of continent-scale data sets.
Keywords: Antarktis; geofysikk; glasiologi; innlandsis; isbreer; istykkelse

Review of The life of José María Sobral: scientist, diarist, and pioneer in Antarctica, by Mary R. Tahan (2018). Cham, Switzerland: Springer International Publishing. 336 pp. ISBN 978-3-319-67267-0 - Millar, Pat (Polar Research, 2019)
Keywords: Antarktis; Otto Nordenskjöld; bokanmeldelser; dagbøker; ekspedisjoner; geodesi; magnetisme; meteorologi; oppdagelsesreiser

Sea Ice Meltwater and Circumpolar Deep Water Drive Contrasting Productivity in Three Antarctic Polynyas - Moreau, Sebastien; Lannuzel, Delphine; Janssens, J.; Arroyo, Mar; Corkill, M; Cougnon, Eva; Genovese, C.; Legresy, Benoit; Lenton, Andrew; Puigcorbe, V.; Ratnarajah, L.; Rintoul, Steve; et al. (Journal of Geophysical Research: Oceans, 2019)
In the Southern Ocean, polynyas exhibit enhanced rates of primary productivity and represent large seasonal sinks for atmospheric CO2. Three contrasting east Antarctic polynyas were visited in late December to early January 2017: the Dalton, Mertz, and Ninnis polynyas. In the Mertz and Ninnis polynyas, phytoplankton biomass (average of 322 and 354 mg chlorophyll a (Chl a)/m2, respectively) and net community production (5.3 and 4.6 mol C/m2, respectively) were approximately 3 times those measured in the Dalton polynya (average of 122 mg Chl a/m2 and 1.8 mol C/m2). Phytoplankton communities also differed between the polynyas. Diatoms were thriving in the Mertz and Ninnis polynyas but not in the Dalton polynya, where Phaeocystis antarctica dominated. These strong regional differences were explored using physiological, biological, and physical parameters. The most likely drivers of the observed higher productivity in the Mertz and Ninnis were the relatively shallow inflow of iron-rich modified Circumpolar Deep Water onto the shelf as well as a very large sea ice meltwater contribution. The productivity contrast between the three polynyas could not be explained by (1) the input of glacial meltwater, (2) the presence of Ice Shelf Water, or (3) stratification of the mixed layer. Our results show that physical drivers regulate the productivity of polynyas, suggesting that the response of biological productivity and carbon export to future change will vary among polynyas.
Keywords: Sørishavet; biomasse; brehylle; fytoplankton; havis; isbrem; isshelf; marin biologi; oseanografi; polynja; sjøis

First evidence of a tetrapod footprint from the Triassic of northern Victoria Land, Antarctica - Mörs, Thomas; Niedźwiedzki, Grzegorz; Crispini, Laura; Läufer, Andreas; Bomfleur, Benjamin (Polar Research, 2019)
Here, we report on a tetrapod footprint from the Transantarctic Basin in the far north of Victoria Land, which marks the first record of terrestrial vertebrates for this region. The single specimen derives from a previously unknown lithological unit of Middle or Late Triassic age of the Beacon Supergroup in the Helliwell Hills in the central Rennick Glacier area. It differs in both size and morphology clearly from Middle Triassic trackway types from the upper Fremouw Formation of the Queen Alexandra Range in southern Victoria Land, and likely represents a primitive amniote, procolophonid or therapsid. The footprint is the third evidence of fossil vertebrate trackways in Antarctica.
Keywords: Antarktis; fossiler; paleobiologi; paleontologi; terrestriske virveldyr

An interannual study of foraging behaviour in sympatrically breeding macaroni Eudyptes chrysolophus and chinstrap penguins Pygoscelis antarcticus at Bouvetøya - Narvestad, Audun (UiT Norges arktiske universitet, 2019)
Species are likely to segregate their ecological niches to minimize competition for resources, but for centrally foraging predators that breed on sub-Antarctic islands in the Southern Ocean the possibility of niche segregation may be minimal. This study is the first to examine the spatial and trophic aspects of the foraging niche of sympatrically breeding macaroni and chinstrap penguins at the poorly-studied sub-Antarctic island Bouvetøya over multiple years. To measure at-sea movements and dive behavior, 90 breeding macaroni Eudyptes chrysolophus and 49 breeding chinstrap penguins Pygoscelis antarcticus were deployed with satellite transmitters and time-depth recorders over two austral summer breeding seasons, 2015 and 2018. In addition, tracked birds were sampled for blood for biogeochemical dietary analysis. Chinstrap penguins displayed large interannual variation in foraging behavior between the two years, and dove deeper, utilized larger foraging areas during late breeding stages and showed enriched values of δ15N in the first- compared to the second- year. Conversely, macaroni penguins dove to similar depths and displayed similar values of δ15N in both years. Our results suggest that potentially low krill abundances in the waters around Bouvetøya in 2015 forced the chinstrap penguins to search for alternative prey, like myctophid fishes, which resulted in increased overlap in the two species' foraging niche. Consequently, the chinstrap penguins may have faced increased interspecific competition for prey or catabolism from food shortage. Irrespective, our findings may partly explain the decreasing number of breeding chinstrap penguins at the world's most remote island, Bouvetøya.
Publication Title: Faculty of Biosciences, Fisheries and Economics. Department of Arctic and Marine Biology Volume: M.Sc. Issue: BIO-3950
Keywords: Bouvetøya; biokjemi; biotelemetri; marin biologi; pingviner; zoologi

Two-Timescale Carbon Cycle Response to an AMOC Collapse - Nielsen, Søren B; Jochum, Markus; Pedro, Joel B; Eden, Carsten; Nuterman, Roman (Paleoceanography and Paleoclimatology, 2019)
Atmospheric CO2 concentrations (pCO2) varied on millennial timescales in phase with Antarctic temperature during the last glacial period. A prevailing view has been that carbon release and uptake by the Southern Ocean dominated this millennial-scale variability in pCO2. Here, using Earth System Model experiments with an improved parameterization of ocean vertical mixing, we find a major role for terrestrial and oceanic carbon releases in driving the pCO2 trend. In our simulations, a change in Northern Hemisphere insolation weakens the Atlantic Meridional Overturning Circulation (AMOC) leading to increasing pCO2 and Antarctic temperatures. The simulated rise in pCO2 is caused in equal parts by increased CO2 outgassing from the global ocean due to a reduced biological activity and changed ventilation rates, and terrestrial carbon release as a response to southward migration of the Intertropical Convergence Zone. The simulated terrestrial release of carbon could explain stadial declines in organic carbon reservoirs observed in recent ice core δ13C measurements. Our results show that parallel variations in Antarctic temperature and pCO2 do not necessitate that the Southern Ocean dominates carbon exchange; instead, changes in carbon flux from the global ocean and land carbon reservoirs can explain the observed pCO2 (and δ13C) changes.
Keywords: Sørishavet; atmosfæren; biogeokjemi; karbon syklus; karbondioksid; klimatologi; paleoklimatologi; paleoseanografi; temperatur

Very Strong Atmospheric Methane Growth in the 4 Years 2014–2017: Implications for the Paris Agreement - Nisbet, Euan G; Manning, Martin; Dlugokencky, Ed; Fisher, Rebecca; Lowry, Dave; Michel, Sylvia; Myhre, Cathrine Lund; Platt, Stephen Matthew; Allen, Grant; Bousquet, Philippe; Brownlow, Rebecca; Cain, Michelle; et al. (Global Biogeochemical Cycles, 2019)
Atmospheric methane grew very rapidly in 2014 (12.7 ± 0.5 ppb/year), 2015 (10.1 ± 0.7 ppb/year), 2016 (7.0 ± 0.7 ppb/year), and 2017 (7.7 ± 0.7 ppb/year), at rates not observed since the 1980s. The increase in the methane burden began in 2007, with the mean global mole fraction in remote surface background air rising from about 1,775 ppb in 2006 to 1,850 ppb in 2017. Simultaneously the 13C/12C isotopic ratio (expressed as δ13CCH4) has shifted, now trending negative for more than a decade. The causes of methane's recent mole fraction increase are therefore either a change in the relative proportions (and totals) of emissions from biogenic and thermogenic and pyrogenic sources, especially in the tropics and subtropics, or a decline in the atmospheric sink of methane, or both. Unfortunately, with limited measurement data sets, it is not currently possible to be more definitive. The climate warming impact of the observed methane increase over the past decade, if continued at >5 ppb/year in the coming decades, is sufficient to challenge the Paris Agreement, which requires sharp cuts in the atmospheric methane burden. However, anthropogenic methane emissions are relatively very large and thus offer attractive targets for rapid reduction, which are essential if the Paris Agreement aims are to be attained.
Keywords: Antarktis; atmosfæren; atmosfærisk metan; fossilt brensel; global klimamodell; global oppvarming; klimaendringer; klimagasser; metanisotoper; metanutslipp; meteorologi; polarområdene

Groundwater discharge to the western Antarctic coastal ocean - Null, Kimberly A; Corbett, D Reide; Crenshaw, Jared; Peterson, Richard N; Peterson, Leigha E; Lyons, W Berry (Polar Research, 2019)
Submarine groundwater discharge (SGD) measurements have been limited along the Antarctic coast, although groundwater discharge is becoming recognized as an important process in the Antarctic. Quantifying this meltwater pathway is important for hydrologic budgets, ice mass balances and solute delivery to the coastal ocean. Here, we estimate the combined discharge of subglacial and submarine groundwater to the Antarctic coastal ocean. SGD, including subglacial and submarine groundwater, is quantified along the WAP at the Marr Glacier terminus using the activities of naturally occurring radium isotopes (223Ra, 224Ra). Estimated SGD fluxes from a 224Ra mass balance ranged from (0.41 ± 0.14)×104 and (8.2 ± 2.3)×104m3 d−1. Using a salinity mass balance, we estimate SGD contributes up to 32% of the total freshwater to the coastal environment near Palmer Station. This study suggests that a large portion of the melting glacier may be infiltrating into the bedrock and being discharged to coastal waters along the WAP. Meltwater infiltrating as groundwater at glacier termini is an important solute delivery mechanism to the nearshore environment that can influence biological productivity. More importantly, quantifying this meltwater pathway may be worthy of attention when predicting future impacts of climate change on retreat of tidewater glaciers.
Keywords: Sørishavet; biologi; geologi; grunnvann; hydrologi; isbreer; klimaendringer; tidevann

Influence of Summer Sublimation on δD, δ18O, and δ17O in Precipitation, East Antarctica, and Implications for Climate Reconstruction From Ice Cores - Pang, Hongxi; Hou, Shugui; Landais, Amaelle; Masson-Delmotte, Valérie; Jouzel, Jean; Steen-Larsen, Hans Christian; Risi, Camille; Zhang, Wangbin; Wu, Shuangye; Li, Yuansheng; An, Chunlei; Wang, Yetang; et al. (Journal of Geophysical Research: Atmospheres, 2019)
In central Antarctica, where accumulation rates are very low, summer sublimation of surface snow is a key element of the surface mass balance, but its fingerprint in isotopic composition of water (δD, δ18O, and δ17O) remains unclear. In this study, we examined the influence of summer sublimation on δD, δ18O, and δ17O in precipitation using data sets of isotopic composition of precipitation at various sites on the inland East Antarctica. We found unexpectedly low δ18O values in the summer precipitation, decoupled from surface air temperatures. This feature can be explained by the combined effects of weak or nonexistent temperature inversion and moisture recycling associated with sublimation-condensation processes in summer. Isotopic fractionation during the moisture-recycling process also explains the observed high values of d-excess and 17O-excess in summer precipitation. Our results suggest that the local cycle of sublimation-condensation in summer is an important process for the isotopic composition of surface snow, water vapor, and consequently precipitation on inland East Antarctica.
Keywords: Antarktis; geofysikk; iskjerner; paleoklimatologi; stabile isotoper

Subglacial Geology and Geomorphology of the Pensacola-Pole Basin, East Antarctica - Paxman, Guy J G; Jamieson, Stewart S R; Ferraccioli, Fausto; Jordan, Tom A; Bentley, Michael J; Ross, Neil; Forsberg, René; Matsuoka, Kenichi; Steinhage, Daniel; Eagles, Graeme; Casal, Tania G (Geochemistry, Geophysics, Geosystems, 2019)
The East Antarctic Ice Sheet (EAIS) is underlain by a series of low-lying subglacial sedimentary basins. The extent, geology, and basal topography of these sedimentary basins are important boundary conditions governing the dynamics of the overlying ice sheet. This is particularly pertinent for basins close to the grounding line wherein the EAIS is grounded below sea level and therefore potentially vulnerable to rapid retreat. Here we analyze newly acquired airborne geophysical data over the Pensacola-Pole Basin (PPB), a previously unexplored sector of the EAIS. Using a combination of gravity and magnetic and ice-penetrating radar data, we present the first detailed subglacial sedimentary basin model for the PPB. Radar data reveal that the PPB is defined by a topographic depression situated ~500 m below sea level. Gravity and magnetic depth-to-source modeling indicate that the southern part of the basin is underlain by a sedimentary succession 2–3 km thick. This is interpreted as an equivalent of the Beacon Supergroup and associated Ferrar dolerites that are exposed along the margin of East Antarctica. However, we find that similar rocks appear to be largely absent from the northern part of the basin, close to the present-day grounding line. In addition, the eastern margin of the basin is characterized by a major geological boundary and a system of overdeepened subglacial troughs. We suggest that these characteristics of the basin may reflect the behavior of past ice sheets and/or exert an influence on the present-day dynamics of the overlying EAIS.
Keywords: Antarktis; Sydpolen; Sørpolen; geofysikk; geomorfologi; glasiologi; innlandsis; subglasial geologi; subglasial topografi

Comparison of elastic moduli from seismic diving-wave and ice-core microstructure analysis in Antarctic polar firn - Schlegel, Rebecca; Diez, Anja; Löwe, Henning; Mayer, Christoph; Lambrecht, Astrid; Freitag, Johannes; Miller, Heinrich; Hofstede, Coen; Eisen, Olaf (Annals of Glaciology, 2019)
We compared elastic moduli in polar firn derived from diving wave refraction seismic velocity analysis, firn-core density measurements and microstructure modelling based on firn-core data. The seismic data were obtained with a small electrodynamic vibrator source near Kohnen Station, East Antarctica. The analysis of diving waves resulted in velocity–depth profiles for different wave types (P-, SH- and SV-waves). Dynamic elastic moduli of firn were derived by combining P- and S-wave velocities and densities obtained from firn-core measurements. The structural finite-element method (FEM) was used to calculate the components of the elastic tensor from firn microstructure derived from X-ray tomography of firn-core samples at depths of 10, 42, 71 and 99 m, providing static elastic moduli. Shear and bulk moduli range from 0.39 to 2.42 GPa and 0.68 to 2.42 GPa, respectively. The elastic moduli from seismic observations and the structural FEM agree within 8.5% for the deepest achieved values at a depth of 71 m, and are within the uncertainty range. Our observations demonstrate that the elastic moduli of the firn can be consistently obtained from two independent methods which are based on dynamic (seismic) and static (tomography and FEM) observations, respectively, for deeper layers in the firn below ~10 m depth.
Publisher: Cambridge University Press
Keywords: Antarktis; glasiologi; seismologi

GlobSed: Updated Total Sediment Thickness in the World's Oceans - Straume, Eivind O; Gaina, Carmen; Medvedev, Sergei; Hochmuth, Katharina; Gohl, Karsten; Whittaker, Joanne; Abdul Fattah, R; Doornenbal, J C; Hopper, John R (Geochemistry, Geophysics, Geosystems, 2019)
We present GlobSed, a new global 5-arc-minute total sediment thickness grid for the world's oceans and marginal seas. GlobSed covers a larger area than previously published global grids and incorporates updates for the NE Atlantic, Arctic, Southern Ocean, and Mediterranean regions, which results in a 29.7% increase in estimated total oceanic sediment volume. We use this new global grid and a revised global oceanic lithospheric age grid to assess the relationship between the total sediment thickness and age of the underlying oceanic lithosphere and its latitude. An analytical approximation model is used to mathematically describe sedimentation trends in major oceanic basins and to allow paleobathymetric reconstructions at any given geological time. This study provides a much-needed update of the sediment thickness distribution of the world oceans and delivers a model for sedimentation rates on oceanic crust through time that agrees well with selected drill data used for comparison.
Keywords: Sørishavet; batymetri; litosfæren; marin geofysikk; marin geologi; sedimenter; sedimentologi

Topographic Shelf Waves Control Seasonal Melting Near Antarctic Ice Shelf Grounding Lines - Sun, Sainan; Hattermann, Tore; Pattyn, Frank; Nicholls, Keith W; Drews, Reinhard; Berger, Sophie (Geophysical Research Letters, 2019)
The buttressing potential of ice shelves is modulated by changes in subshelf melting, in response to changing ocean conditions. We analyze the temporal variability in subshelf melting using an autonomous phase-sensitive radio-echo sounder near the grounding line of the Roi Baudouin Ice Shelf in East Antarctica. When combined with additional oceanographic evidence of seasonal variations in the stratification and the amplification of diurnal tides around the shelf break topography (Gunnerus Bank), the results suggest an intricate mechanism in which topographic waves control the seasonal melt rate variability near the grounding line. This mechanism has not been considered before and has the potential to enhance local melt rates without advecting different water masses. As topographic waves seem to strengthen in a stratified ocean, the freshening of Antarctic surface water, predicted by observations and models, is likely to increase future basal melting in this area.
Keywords: Sørishavet; glasiologi; isshelf; klimatologi; oseanografi; smelting; vannmasser

The Weddell Gyre, Southern Ocean: Present Knowledge and Future Challenges - Vernet, M; Geibert, Walter; Hoppema, Mario; Brown, Peter J; Haas, Christian; Hellmer, Hartmut H; Jokat, Wilfried; Jullion, L; Mazloff, M; Bakker, D C E; Brearley, J A; Croot, Peter L; et al. (Reviews of Geophysics, 2019)
The Weddell Gyre (WG) is one of the main oceanographic features of the Southern Ocean south of the Antarctic Circumpolar Current which plays an influential role in global ocean circulation as well as gas exchange with the atmosphere. We review the state-of-the art knowledge concerning the WG from an interdisciplinary perspective, uncovering critical aspects needed to understand this system's role in shaping the future evolution of oceanic heat and carbon uptake over the next decades. The main limitations in our knowledge are related to the conditions in this extreme and remote environment, where the polar night, very low air temperatures, and presence of sea ice year-round hamper field and remotely sensed measurements. We highlight the importance of winter and under-ice conditions in the southern WG, the role that new technology will play to overcome present-day sampling limitations, the importance of the WG connectivity to the low-latitude oceans and atmosphere, and the expected intensification of the WG circulation as the westerly winds intensify. Greater international cooperation is needed to define key sampling locations that can be visited by any research vessel in the region. Existing transects sampled since the 1980s along the Prime Meridian and along an East-West section at ~62°S should be maintained with regularity to provide answers to the relevant questions. This approach will provide long-term data to determine trends and will improve representation of processes for regional, Antarctic-wide, and global modeling efforts—thereby enhancing predictions of the WG in global ocean circulation and climate.
Keywords: Sørishavet; Weddellhavet; biologi; brehylle; geologi; havis; havstrømmer; isbrem; isshelf; kjemi; oseanografi; sjøis; vannmasser; vannvirvler

Project and Community Management in Polar Sciences – Challenges and Opportunities - Werner, Kirstin; Zaika, Yulia; Pavlov, Alexey K; Lidström, Sven; Pope, Allen; Badhe, Renuka; Brückner, Marlen; Cristini, Luisa (Adv. Geosci., 2019)
Because geoscientific research often occurs via community-instigated bursts of activity with multi-investigator collaborations variously labelled as e.g., years (The International Polar Year IPY), experiments (World Ocean Circulation Experiment WOCE), programs (International Ocean Discovery Program), missions (CRYOSAT spacecraft), or decades (The International Decade of Ocean Exploration IDOE), successful attainment of research goals generally requires skilful scientific project management. In addition to the usual challenges of matching scientific ambitions to limited resources, on-going coordination and specifically project management, planning and implementation of polar science projects often involve many uncertainties caused by, for example, unpredictable weather or ocean and sea ice conditions, large-scale logistical juggling; and often these collaborations are spatially distributed and take place virtually. Large amounts of funding are needed to procure the considerable infrastructure and technical equipment required for polar expeditions; permissions to enter certain regions must be requested; and potential risks for expedition members as well as technical issues in extreme environments need to be considered. All these aspects are challenging for polar science projects, which therefore need a well thought-through program including a realistic alternative “plan B” and possibly also a “plan C” and “plan D”. The four most challenging overarching themes in polar science project management have been identified: international cooperation, interdisciplinarity, infrastructure, and community management. In this paper, we address ongoing challenges and opportunities in polar science project management based on a survey among 199 project and community managers and an additional of 85 project team members active in the field of polar sciences. Case studies and survey results are discussed with the conclusive goal to provide recommendations on how to fully reach the potential of polar sciences project and community management.
Publisher: Copernicus Publications
Keywords: Antarktis; geovitenskap; internasjonal samarbeid; klimaendringer; miljøendringer; polarområdene

Surface heat budget in the Southern Ocean from 42°S to the Antarctic marginal ice zone: four atmospheric reanalyses versus icebreaker Aurora Australis measurements - Yu, Lisan; Jin, Xiangze; Schulz, Eric W (Polar Research, 2019)
Surface heat fluxes from four atmospheric reanalyses in the Southern Ocean are evaluated using air–sea measurements obtained from the Aurora Australis during off-winter seasons in 2010–12. The icebreaker tracked between Hobart, Tasmania (ca. 42°S), and the Antarctic continent, providing in situ benchmarks for the surface energy budget change in the Subantarctic Southern Ocean (58–42°S) and the eastern Antarctic marginal ice zone (MIZ, 68–58°S). We find that the reanalyses show a high-level agreement among themselves, but this agreement reflects a universal bias, not a “truth.” Downward shortwave radiation (SW↓) is overestimated (warm biased) and downward longwave radiation (LW↓) is underestimated (cold biased), an indication that the cloud amount in all models is too low. The ocean surface in both regimes shows a heat gain from the atmosphere when averaged over the seven months (October–April). However, the ocean heat gain in reanalyses is overestimated by 10–36 W m−2 (80–220%) in the MIZ but underestimated by 6–20 W m−2 (7–25%) in the Subantarctic. The biases in SW↓ and LW↓ cancel out each other in the MIZ, causing the surface heat budget to be dictated by the underestimation bias in sensible heat loss. These reanalyses biases affect the surface energy budget in the Southern Ocean by meaningfully affecting the timing of the seasonal transition from net heat gain to net heat loss at the surface and the relative strength of SW↓ at different regimes in summer, when the length-of-day effect can lead to increased SW↓ at high latitudes.
Keywords: Sørishavet; havis; klima; meteorologi; oseanografi

A nematode in the mist: Scottnema lindsayae is the only soil metazoan in remote Antarctic deserts, at greater densities with altitude - Zawierucha, Krzysztof; Marshall, Craig J; Wharton, David; Janko, Karel (Polar Research, 2019)
A decrease in biodiversity and density of terrestrial organisms with increasing altitude and latitude is a well-known ecogeographical pattern. However, studies of these trends are often taxonomically-biased toward well-known organisms and especially those with relatively large bodies, and environmental variability at the local scale may perturb these general effects. Here, we focus on understudied organisms—soil invertebrates—in Antarctic deserts, which are among the driest and coldest places on Earth. We sampled two remote Antarctic sites in the Darwin Glacier area and established an altitudinal gradient running from 210 to 836 m a.s.l. We measured soil geochemistry and organic matter content and linked these parameters with the presence of soil invertebrates. We found three general outcomes, two of which are consistent with general assumptions: (a) the hostile climatic condition of the Darwin Glacier region supports an extremely low diversity of soil metazoans represented by a single nematode species—Scottnema lindsayae; (b) soil geochemistry is the main factor influencing distribution of nematodes at the local scale. Contrary to our expectations, a positive correlation was found between nematode density and altitude. This last observation could be explained by an additional effect of soil moisture as we found this increased with altitude and may be caused by orographic clouds, which are present in this region. To the best of our knowledge such effects have been described in tropical and temperate regions. Potential effect of orographic clouds on soil properties in polar deserts may be a fruitful area of ecological research on soil fauna.
Keywords: Antarktis; biodiversitet; geokjemi; jord; metazoan; rundormer; økogeografi; økosystemer

Verification and Improvement of the Ability of CFSv2 to Predict the Antarctic Oscillation in Boreal Spring - Zhang, Dapeng; Huang, Yanyan; Sun, Bo; Li, Fei; Wang, Huijun (Advances in Atmospheric Sciences, 2019)
The boreal spring Antarctic Oscillation (AAO) has a significant impact on the spring and summer climate in China. This study evaluates the capability of the NCEP’s Climate Forecast System, version 2 (CFSv2), in predicting the boreal spring AAO for the period 1983–2015. The results indicate that CFSv2 has poor skill in predicting the spring AAO, failing to predict the zonally symmetric spatial pattern of the AAO, with an insignificant correlation of 0.02 between the predicted and observed AAO Index (AAOI). Considering the interannual increment approach can amplify the prediction signals, we firstly establish a dynamical–statistical model to improve the interannual increment of the AAOI (DY AAOI), with two predictors of CFSv2-forecasted concurrent spring sea surface temperatures and observed preceding autumn sea ice. This dynamical–statistical model demonstrates good capability in predicting DY AAOI, with a significant correlation coefficient of 0.58 between the observation and prediction during 1983–2015 in the two-year-out cross-validation. Then, we obtain an improved AAOI by adding the improved DY AAOI to the preceding observed AAOI. The improved AAOI shows a significant correlation coefficient of 0.45 with the observed AAOI during 1983–2015. Moreover, the unrealistic atmospheric response to March–April–May sea ice in CFSv2 may be the possible cause for the failure of CFSv2 to predict the AAO. This study gives new clues regarding AAO prediction and short-term climate prediction.
Keywords: Antarktis; atmosfæren; klimatologi; meteorologi

PFAS bioaccumulation in Antarctic breeding south polar skua (Catharacta maccormicki) and its prey items - Alfaro Garcia, Laura Andrea; Borgå, Katrine (Universitetet i Oslo, 2018)
Per- og polyfluorerte alkylstoffer (PFAS) har blitt funnet i blodprøver fra sørjo (Catharacta maccormicki) tatt i løpet av hekkesesongen i kolonien i Svarthamaren (Dronning Mauds land, Antarktis). For å undersøke om disse konsentrasjonene i sørjo stammer fra dietten i hekkesesongen, sammenligner denne oppgaven biomagnifisering i to næringskjeder. Ved innenlands kolonien Svarthamaren spiser sørjoene nesten utelukkende egg og unger fra antarktisk petrell (Thalassoica antarctica), og petrellene spiser fisk og krepsdyr. I den kystnære kolonien ved Dumont D’Urville (DDU, Adélie Land), spiser sørjoene hovedsakelig egg og unger fra Adélie pingviner (Pygoscelis adeliae). Væskekromatografi-massespektrometri (LC/MS) ble brukt for å måle PFAS i mageinnhold og egg fra antarktisk petrell, og i blodprøver fra sørjo, Adélie pingvin-unger, og antarktisk petrellunger og -voksne. Stabile isotoper (δ13C and δ15N) ble også analysert som diettdeskriptorer. Resultatene ble slått sammen med resultater fra tidligere studier fra begge koloniene for å oppnå et datasett for sørjo og dens diett ved både Svarthamaren og DDU. Datasettet ble brukt for å beregne biomagnifiseringsfaktor (BMF) og trofisk magnifisering faktor (TMF) for de detekterte PFASene i de to næringskjedene. Ved Svarthamaren var PFUnA over deteksjonsgrensen i alle matriksene, men var ikke tilstede i enkelte prøver. Andre detekterte PFASer var Perfluoroktyl sulfonat (PFOS), Perfluorononanoate (PFNA), Perfluorodecanoate (PFDcA), Perfluoroundecanoate (PFUnA), Perfluorododecanoate (PFDoA), Perfluorotridecanoate (PFTriA) and Perfluorotetradecanoate (PFTeA). PFAS konsentrasjonene økte oppover i næringskjeden, hvorav nivåene for alle detekterte PFASer var høyest hos sørjo. Ved DDU var PFAS konsentrasjonene lavere, men mønsteret var sammenlignbart med det i Svarthamaren. Forgrenet PFOS ble kvantifisert i sørjo fra DDU, men var ikke over deteksjonsgrense i andre matrikser. Byttedyrene hadde flere PFASer over deteksjonsgrensen i Svarthamaren sammenliknet med DDU. Vi beregnet BMF og TMF for alle detekterte PFASer i Svarthamaren, men kun for PFOS, PFNA, PFDcA og PFUnA i DDU fordi bare disse ble funnet i både sørjo og pingvinene. BMF for PFOS var høyere enn forventet i vanlige predator-bytte forhold i begge koloniene, noe som peker på en ukjent kilde. Biomagnifikasjonsverdiene for andre PFASer var varierende, men sammenliknbare mellom koloniene. PFAS-konsentrasjonene i sørjo fra begge kolonier og i antarktisk petrell reflekterer sannsynligvis eksponering utenfor Antarktis i løpet av vinteren. De detekterte konsentrasjoner i Adélie pingviner er ikke høye nok for å forklare de høye PFAS-nivåene i sørjoene i DDU. Derfor, i DDU, disse PFAS-nivåer kommer fra andre byttedyr enten innenfor regioner eller mest sannsynligvis fra utenfor Antarktis.
Publication Title: Institute of Biosciences. Faculty of Mathematics and Natural Sciences Volume: M.Sc.
Keywords: Dronning Maud Land; kjemiske analyser; ornitologi; petreller; pingviner; sjøfugler; toksikologi

Signals from the south; humpback whales carry messages of Antarctic sea-ice ecosystem variability - Bengtson Nash, Susan M; Castrillon, Juliana; Eisenmann, Pascale; Fry, Brian; Shuker, Jon D; Cropp, Roger A; Dawson, Amanda; Bignert, Anders; Bohlin-Nizzetto, Pernilla; Waugh, Courtney A; Polkinghorne, Bradley J; Dalle Luche, Greta; et al. (Global Change Biology, 2018)
Abstract Southern hemisphere humpback whales (Megaptera novaeangliae) rely on summer prey abundance of Antarctic krill (Euphausia superba) to fuel one of the longest-known mammalian migrations on the planet. It is hypothesized that this species, already adapted to endure metabolic extremes, will be one of the first Antarctic consumers to show measurable physiological change in response to fluctuating prey availability in a changing climate; and as such, a powerful sentinel candidate for the Antarctic sea-ice ecosystem. Here, we targeted the sentinel parameters of humpback whale adiposity and diet, using novel, as well as established, chemical and biochemical markers, and assembled a time trend spanning 8 years. We show the synchronous, inter-annual oscillation of two measures of humpback whale adiposity with Southern Ocean environmental variables and climate indices. Furthermore, bulk stable isotope signatures provide clear indication of dietary compensation strategies, or a lower trophic level isotopic change, following years indicated as leaner years for the whales. The observed synchronicity of humpback whale adiposity and dietary markers, with climate patterns in the Southern Ocean, lends strength to the role of humpback whales as powerful Antarctic sea-ice ecosystem sentinels. The work carries significant potential to reform current ecosystem surveillance in the Antarctic region.
Keywords: Sørishavet; havis; hvaler; marin biologi; marine økosystemer; plankton; sjøis; stabile isotoper

SuperDARN Radar-Derived HF Radio Attenuation During the September 2017 Solar Proton Events - Bland, Emma C; Heino, Erkka; Kosch, Michael J; Partamies, Noora (Space Weather, 2018)
Two solar proton events in September 2017 had a significant impact on the operation of the Super Dual Auroral Radar Network (SuperDARN), a global network of high-frequency (HF) radars designed for observing F region ionospheric plasma convection. Strong polar cap absorption caused near-total loss of radar backscatter, which prevented the primary SuperDARN data products from being determined for a period of several days. During this interval, the high-latitude and polar cap radars measured unusually low levels of background atmospheric radio noise. We demonstrate that these background noise measurements can be used to observe the spatial and temporal evolution of the polar cap absorption region, using an approach similar to riometry. We find that the temporal evolution of the SuperDARN radar-derived HF attenuation closely follows that of the cosmic noise absorption measured by a riometer. Attenuation of the atmospheric noise up to 10 dB at 12 MHz is measured within the northern polar cap, and up to 14 dB in the southern polar cap, which is consistent with the observed backscatter loss. Additionally, periods of enhanced attenuation lasting 2–4 hr are detected by the midlatitude radars in response to M- and X-class solar flares. Our results demonstrate that SuperDARN's routine measurements of atmospheric radio noise can be used to monitor 8- to 20-MHz radio attenuation from middle to polar latitudes, which may be used to supplement riometer data and also to investigate the causes of SuperDARN backscatter loss during space weather events.
Keywords: Antarktis; astronomi; energiske partikler; geofysikk; ionosfæren; polarområdene; radiostøy

Variable Melt Production Rate of the Kerguelen HotSpot Due To Long-Term Plume-Ridge Interaction - Bredow, Eva; Steinberger, Bernhard (Geophysical Research Letters, 2018)
For at least 120 Myr, the Kerguelen plume has distributed enormous amounts of magmatic rocks over various igneous provinces between India, Australia, and Antarctica. Previous attempts to reconstruct the complex history of this plume have revealed several characteristics that are inconsistent with properties typically associated with plumes. To explore the geodynamic behavior of the Kerguelen hotspot, and in particular address these inconsistencies, we set up a regional viscous flow model with the mantle convection code ASPECT. Our model features complex time-dependent boundary conditions in order to explicitly simulate the surrounding conditions of the Kerguelen plume. We show that a constant plume influx can result in a variable magma production rate if the plume interacts with nearby spreading ridges and that a dismembered plume, multiple plumes, or solitary waves in the plume conduit are not required to explain the fluctuating magma output and other unusual characteristics attributed to the Kerguelen hotspot.
Keywords: Den antarktiske kontinentalplaten; Sørishavet; geodynamiske modeller; geovitenskap; plategrenser; platetektonikk; tektoniske plater; vulkaner

Climate controlled sedimentary processes in the Riiser Larsen Sea offshore Queen Maud Land, Antarctica: master's thesis in geology - Brekken, Rita (UiT: University of Tromsø, 2018)
Publication Title: Faculty of science and technology Volume: M.Sc.
Keywords: Sørishavet; geologi; sedimenter

Contextualizing the 1997 warm event observed at Patriot Hills in the interior of West Antarctica - Carrasco, Jorge F (Polar Research, 2018)
Between 5 and 8 December 1997, the surface air temperature increased up to 3°C in the interior of West Antarctica, at Patriot Hills (PH), located at about 80°08’S, 81°16ʹ W, at an elevation of 855 m a.s.l. This was about 15°C warmer than the mean air temperature (−12°C) for this location at this time of the year. The ice surface field along the hills used as a runway for large aircraft melted, forming small ponds at the foot of the slope. This warm event was associated with a passing mid-tropospheric ridge that reached the interior of West Antarctica, whose anticyclonic circulation advected warm air towards the PH area. The foehn effect of the descending airflow on the northern slope of PH did not significantly contribute to the warming. The El Niño–Southern Oscillation (ENSO) was reaching its mature phase during the last quarter of 1997 and the warming/melting episode may be related to large-scale circulation associated with ENSO occurrence. However, warm events in the interior of West Antarctica may occur during any phase of ENSO. In contrast, the negative phase of the Antarctic Oscillation seems to support the development of the mid-tropospheric ridges that can advect warm maritime air towards the interior of West Antarctica. The 3°C registered at PH may be one of the highest near-surface air temperatures measured below 2500 m a.s.l. in the far interior coastal area of West Antarctica. This suggests a new subregion for determining air temperature records in Antarctica may need to be considered.
Keywords: Antarktis; føhn; føn; lufttemperatur; meteorologi; oppvarming; smelting; snø; sørlig oscillasjon

Response of Antarctic sea-ice algae to an experimental decrease in pH: a preliminary analysis from chlorophyll fluorescence imaging of melting ice - Castrisios, Katerina; Martin, Andrew; Müller, Marius N; Kennedy, Fraser; McMinn, Andrew; Ryan, Ken G (Polar Research, 2018)
Microorganisms confined to annual sea ice in the Southern Ocean are exposed to highly variable oxygen and carbonate chemistry dynamics because of the seasonal increase in biomass and limited exchange with the underlying water column. For sea-ice algae, physiological stress is likely to be exacerbated when the ice melts; however, variation in carbonate speciation has rarely been monitored during this important state-transition. Using pulse amplitude modulated fluorometry (Imaging-PAM, Walz), we documented in situ changes in the maximum quantum yield of photosystem II ( F v / F m ) of sea-ice algae melting out into seawater with initial pH values ranging from 7.66 to 6.39. Although the process of ice-melt elevated seawater pH by 0.2–0.55 units, we observed a decrease in F v / F m between 0.02 and 0.06 for each unit drop in pH during real-time fluorescence imaging. These results are considered preliminary but provide context for including carbonate chemistry monitoring in the design of future sea ice state-transition experiments. Imaging-PAM is a reliable technology for determining F v / F m , but is of limited use for obtaining additional photosynthetic parameters when imaging melting ice.
Keywords: Sørishavet; alger; fotosyntese; fysiologi; havis; karbonatkjemi; marin biologi; sjøis; økofysiologi

Feeding by Antarctic krill Euphausia superba in the West Antarctic Peninsula: differences between fjords and open waters - Cleary, Alison C; Durbin, Edward G; Casas, Maria C (Marine Ecology Progress Series, 2018)
Antarctic krill Euphausia superba are key components of Antarctic ecosystems, serving as the major prey item for most of the megafauna in the region. Coastal fjords along the West Antarctic Peninsula have been identified as biological hotspots, areas in which high biomasses of both E. superba and their megafauna predators are consistently observed. We investigated feeding by E. superba in fjords and adjacent open waters of the West Antarctic Peninsula. Next generation sequencing of stomach contents from 174 krill indicated a diverse diet, with broad patterns consistent with previous understanding of E. superba feeding. Diatom sequence reads were frequent and abundant, indicating a largely diatom-based diet, while the occasional presence of high abundances of copepod sequence reads suggests carnivory supplemented the diet. Striking differences were observed between the stomach contents of krill collected in fjords and those of krill collected in adjacent open waters. Chaetoceros spp. diatoms made up 71% of the stomach contents sequences of krill collected in fjords, but less than 10% of the stomach contents sequences of krill collected in open waters. These differences could not be explained by differences in the surface water phytoplankton communities, as in both open waters and fjords Chaetoceros spp. made up less than 10% of the surface water sequence read assemblages. These feeding differences highlight the importance of taking into account regional differences in krill feeding when considering E. superba’s roles in Southern Ocean ecosystems, and suggest krill in fjords may make use of vertical structure in phytoplankton assemblages.
Keywords: Sørishavet; biomasse; fytoplankton; krill; marin biologi; oseanografi; zoologi; økosystemer

Wind Stress Mediated Variability of the Filchner Trough Overflow, Weddell Sea - Daae, Kjersti Birkeland; Darelius, Elin Maria K; Fer, Ilker; Østerhus, Svein; Ryan, Svenja (Journal of Geophysical Research: Oceans, 2018)
Keywords: Sørishavet; Weddellhavet; forskning; havstrømmer; oseanografi

Seasonal Outflow of Ice Shelf Water Across the Front of the Filchner Ice Shelf, Weddell Sea, Antarctica - Darelius, Elin Maria K; Sallée, Jean-Baptiste (Geophysical Research Letters, 2018)
Keywords: Sørishavet; Weddellhavet; bunnvann; isfront; isshelf; oseanografi

On the long-ignored scientific achievements of the Belgica expedition 1897–1899 - De Deckker, Patrick (Polar Research, 2018)
The Belgica expedition, which left Belgium in August 1897, was the first to spend 13 months continuously in Antarctic waters, before returning in late 1899. This was not only an exploratory venture, as new lands and oceans were charted, but more importantly it was an exceptional and successful scientific voyage. After the return of the expedition, a vast array of scientific data was processed and eventually 92 publications in some nine volumes funded by the Belgica Commission appeared over 40 years as a series called Résultats du voyage de la Belgica en 1897–99 sous le commandement de A. de Gerlache de Gomery – rapports scientifiques. Disappointingly, those significant results have been mostly ignored in the scientific literature and the paper here aims to inform scientists of the achievements of the Belgica expedition and where to obtain the information. Many of the climatological and oceanographic data obtained by the expeditioners ought to be examined in line with the changes that are occurring today in the Antarctic Peninsula region as a result of global warming. Some of the Belgica data form an important database to critically assess environmental changes over 120 years in the region of the Antarctic Peninsula.
Keywords: Antarktis; Belgica ekspedisjon; glasiologi; global oppvarming; klimaendringer; klimatologi; meteorologi; miljøendringer; oppdagelsesreiser; oseanografi; vitenskap

Basal Settings Control Fast Ice Flow in the Recovery/Slessor/Bailey Region, East Antarctica - Diez, Anja; Matsuoka, Kenichi; Ferraccioli, Fausto; Jordan, Tom A; Corr, Hugh F; Kohler, Jack; Olesen, Arne V; Forsberg, René (Geophysical Research Letters, 2018)
The region of Recovery Glacier, Slessor Glacier, and Bailey Ice Stream, East Antarctica, has remained poorly explored, despite representing the largest potential contributor to future global sea level rise on a centennial to millennial time scale. Here we use new airborne radar data to improve knowledge about the bed topography and investigate controls of fast ice flow. Recovery Glacier is underlain by an 800 km long trough. Its fast flow is controlled by subglacial water in its upstream and topography in its downstream region. Fast flow of Slessor Glacier is controlled by the presence of subglacial water on a rough crystalline bed. Past ice flow of adjacent Recovery and Slessor Glaciers was likely connected via the newly discovered Recovery-Slessor Gate. Changes in direction and speed of past fast flow likely occurred for upstream parts of Recovery Glacier and between Slessor Glacier and Bailey Ice Stream. Similar changes could also reoccur here in the future.
Keywords: Antarktis; geofysikk; geologi; glasiologi; havnivåstigning; isbre; isstrøm

A hut too far: history of the Argentine Ventimiglia shelter on Peter I Øy - Fontana, Pablo Gabriel (Polar Research, 2018)
This paper addresses the barely known history of an Argentine Antarctic hut: the Teniente Luis Ventimiglia hut, installed by the Argentine Antarctic Institute on Peter I Øy (Peter I Island) in March 1971. In examining the history of the only Argentine Antarctic facility outside of the Argentine Antarctic Sector, this article describes the reasons behind the establishment of the hut and the scientific work that took place there as well as previous Argentine expeditions to Peter I.
Keywords: Argentina; Peter I. Øy; ekspedisjoner; forskningsstasjoner; meteorologi; oseanografi

A preliminary survey of the terrestrial arthropods of the Rosenthal Islands, Antarctica - Gantz, J D; Spacht, Drew E; Lee, Richard E (Polar Research, 2018)
The Rosenthal Islands lie along the western edge of the Antarctic Peninsula. They are largely inaccessible and the few research projects in the area have focused on seabird colonies, so nothing has been known about the arthropod fauna on these islands. We conducted a preliminary survey of the arthropods associated with large penguin colonies. We identified two species of Collembola (Cryptopygus antarcticus and Friesea grisea), four species of mites (Alaskozetes antarcticus, Hydrogamasellus racovitzai, Tectopenthalodes villosus and Rhagidia sp.) and one insect (Belgica antarctica). The mite A. antarcticus and the collembolan C. antarcticus were common in large aggregations at our collecting sites and were occasionally observed on the surface of penguin guano without vegetative cover. The insect, a chironomid midge, was less common and found only in vegetated areas.
Keywords: Antarktis; biologi; fauna; leddyr; midder; pingviner; zoologi

Facing the climate change conundrum at the South Pole: actors’ perspectives on the implications of global warming for Chilean Antarctic governance - Gladkova, Ekaterina; Blanco-Wells, Gustavo; Nahuelhual, Laura (Polar Research, 2018)
Antarctica is recognized as being geopolitically and scientifically important, and as one of the regions with the greatest potential to affect and be affected by global climate change. Still, little is known in practice about how climate change will be handled within the main governance framework of the continent: the Antarctic Treaty System (ATS). Using qualitative interviews, participant observations and policy document analysis, this paper explores the perspectives of Chilean scientific, political and non-governmental actors regarding the implications of climate change for the current Antarctic governance framework. Results corroborate a misalignment of the climate change agenda and the ATS, stemming from the divergent views displayed by a wide network of actors. From the interviews, two predominant visions emerge: (i) climate change as an opportunity, where actors recognize the role of Antarctica in regulating global climate and stress greater opportunities to conduct Antarctic-based climate change research, the need for strategic international collaboration, and the reinforcement of Chile’s position in Antarctica through science; (ii) climate change as a burden where actors acknowledge climate change as a global problem, largely external to Antarctica, express disbelief regarding the effectiveness of local actions to tackle climate change and do not associate with climate change governance. The study concludes that climate change may become a dividing, rather than a unifying, field of action in Chilean Antarctic governance, reinforcing previously existing geopolitical tendencies.
Keywords: Antarktis; Antarktistraktaten; geopolitikk; klimaendringer; vitenskap

Di(2-ethylhexyl) adipate (DEHA) detection in Antarctic krill (Euphasia superba Dana) - Han, Xiangning; Liu, Daicheng (Polar Research, 2018)
In this reported study, a novel high-performance thin-layer chromatography (HPTLC) method was developed for the detection and quantification of the toxic substance di(2-ethylhexyl) adipate (DEHA) in Antarctic krill. This procedure was based on the extraction of DEHA by ultrasonic solvent extraction with anhydrous ethanol, silica-gel column chromatographic separation, HPTLC detection and quantification using petroleum ether/ethyl acetate/ acetone/glacial acetic acid (29:1:0.5:2d*, v/v/v/v) as the developing solvent and bromine thymol blue solution as the chromogenic agent. The content of DEHA in freeze-dried Antarctic krill was found to be ca. 0.63 ± 0.05 mg/g. The structure of DEHA in the Antarctic krill was subsequently determined by gas chromatography–mass spectrometry (GC-MS) and infrared chromatography, which verified the presence of this compound in the krill. The HPTLC method exhibited excellent accuracy, with a recovery of 97.1–101.6% and good precision with a relative standard deviation of 2.47–4.90%. The DEHA in Antarctic krill oil was extracted by n-hexane and detected using the same method described above, which verified that DEHA was also present in krill oil at a concentration of ca. 2.16 ± 0.08 mg/g. The presence of DEHA in kill oil is very concerning because of its demonstrated harmful ecotoxicity, and since Antarctic krill is the key link in the food chain in the Antarctic coastal marine ecosystem. The adverse effects of DEHA on Antarctic krill and the source of DEHA will be explored in future research.
Keywords: Sørishavet; krill; marin forurensning; plankton; plastpartikler; økotoksikologi; økotoksiner

A Model-Based Evaluation of the Inverse Gaussian Transit-Time Distribution Method for Inferring Anthropogenic Carbon Storage in the Ocean - He, Yan-Chun; Tjiputra, Jerry; Langehaug, Helene R.; Jeansson, Emil; Gao, Yongqi; Schwinger, Jörg; Olsen, Are (Journal of Geophysical Research: Oceans, 2018)
The Inverse Gaussian approximation of transit time distribution method (IG-TTD) is widely used to infer the anthropogenic carbon (Cant) concentration in the ocean from measurements of transient tracers such as chlorofluorocarbons (CFCs) and sulfur hexafluoride (SF6). Its accuracy relies on the validity of several assumptions, notably (i) a steady state ocean circulation, (ii) a prescribed age tracer saturation history, e.g., a constant 100% saturation, (iii) a prescribed constant degree of mixing in the ocean, (iv) a constant surface ocean air-sea CO2 disequilibrium with time, and (v) that preformed alkalinity can be sufficiently estimated by salinity or salinity and temperature. Here, these assumptions are evaluated using simulated “model-truth” of Cant. The results give the IG-TTD method a range of uncertainty from 7.8% to 13.6% (11.4 Pg C to 19.8 Pg C) due to above assumptions, which is about half of the uncertainty derived in previous model studies. Assumptions (ii), (iv) and (iii) are the three largest sources of uncertainties, accounting for 5.5%, 3.8% and 3.0%, respectively, while assumptions (i) and (v) only contribute about 0.6% and 0.7%. Regionally, the Southern Ocean contributes the largest uncertainty, of 7.8%, while the North Atlantic contributes about 1.3%. Our findings demonstrate that spatial-dependency of , and temporal changes in tracer saturation and air-sea CO2 disequilibrium have strong compensating effect on the estimated Cant. The values of these parameters should be quantified to reduce the uncertainty of IG-TTD; this is increasingly important under a changing ocean climate.
Keywords: Sørishavet; antropogenisk CO2; fossilt brensel; karbondioksid; karbonlagring; klimaendringer; klimatologi

Provenance, transport and diagenesis of sediment in polar areas: a case study in Profound Lake, King George Island, Antarctica - Hernández, Ana C; Bastias, Joaquin; Matus, Daniela; Mahaney, William C (Polar Research, 2018)
Detailed scanning electron microscopy (SEM) micro-texture and mineralogical analysis of lacustrine sediment recovered from Profound Lake (also known as Uruguay Lake), Antarctica, was conducted in the foreland area of the Collins Glacier, King George Island. Very coarse and coarse sand grade size fractions (2 mm – 600 μm) were examined with SEM/ energy dispersive spectrometry, while the total sand fraction and fines (silt + clay) were examined using x-ray diffraction to determine relationships to source rock, weathering and transport history and long-term clay mineral weathering, all of which are poorly understood in polar areas. The mineralogy of these sediments was compared with petrographical information of the country rock to identify potential detrital sources. The association of recovered detrital minerals, sometimes strongly pre-weathered, supports release from source rock of basaltic and andesitic compositions. The micro-texture analysis of quartz, magnetite and various plagioclase grains show micro-features that reveal a complex weathering–diagenesis history tentatively extending into the Paleogene. The bedrock was eroded mostly by glacial processes and mechanical action presumed to result from glacial crushing. Alteration minerals, likely the product of pre-weathering, are probably sourced from weathered bedrock during contact with the sub-aerial atmosphere prior to entrainment. However, amorphous silica precipitation indicates weathering subsequent to glacial erosion from the source bedrock. Cracks of variable dimensions are mostly characteristic of either frost weathering or glacial transport, and involve mechanical and chemical processes.
Keywords: Antarktis; geologi; mineralogi; petrografi; polarområdene; sedimentologi

Current logistical capacity is sufficient to deliver the implementation and management of a representative Antarctic protected area system - Hughes, Kevin A; Grant, Susie M (Polar Research, 2018)
Antarctica’s terrestrial ecosystems are vulnerable to impacts resulting from climate change and local human activities. The Antarctic Treaty System (ATS) provides for the designation of protected areas through the Protocol on Environmental Protection to the Antarctic Treaty. Unsystematic use of agreed management tools, including Antarctic Specially Protected Areas (ASPAs), has resulted in a protected area system lacking representation across the full range of Antarctic terrestrial ecosystems and Antarctic Conservation Biogeographic Regions (ACBRs). Systematic Conservation Planning (SCP) methods provide established mechanisms to fulfil ATS protected area designation goals. However, how would a continent-wide ASPA system be delivered should appropriate sites be identified using SCP or other methods? Although the rate of area protection has slowed recently, we show that newer Consultative Parties to the Antarctic Treaty are increasingly active as ASPA proponents and may have scope for further engagement with protected area management activities. Furthermore, all 16 ACBRs were found to be within the operational footprint of at least two Parties, indicating that this current logistical footprint could support the implementation and management of a continent-wide ASPA system. Effective management of a representative Antarctic protected areas system could be delivered through greater participation by those Parties with currently more limited protected area management responsibilities and greater use of remote-sensing technologies for protected area monitoring, where appropriate. Crucially, political will to implement an ASPA system identified through SCP approaches may be greater once a pragmatic means of delivery and effective management has been identified.
Keywords: Antarktis; Antarktistraktaten; biodiversitet; forvaltning; klimaendringer; menneskelig påvirkning; miljøvern; områdevern; økosystemer

Basal Melt and Freezing Rates From First Noble Gas Samples Beneath an Ice Shelf - Huhn, Oliver; Hattermann, Tore; Davis, Peter E D; Dunker, Erich; Hellmer, Hartmut H; Nicholls, Keith W; Østerhus, Svein; Rhein, Monika; Schröder, Michael; Sültenfuß, Jürgen (Geophysical Research Letters, 2018)
A climatically induced acceleration in ocean-driven melting of Antarctic ice shelves would have consequences for both the discharge of continental ice into the ocean and thus global sea level, and for the formation of Antarctic Bottom Water and the oceanic meridional overturning circulation. Using a novel gas-tight in situ water sampler, noble gas samples have been collected from six locations beneath the Filchner Ice Shelf, the first such samples from beneath an Antarctic ice shelf. Helium and neon are uniquely suited as tracers of glacial meltwater in the ocean. Basal meltwater fractions range from 3.6% near the ice shelf base to 0.5% near the sea floor, with distinct regional differences. We estimate an average basal melt rate for the Filchner-Ronne Ice Shelf of 177 ± 95 Gt/year, independently confirming previous results. We calculate that up to 2.7% of the meltwater has been refrozen, and we identify a local source of crustal helium.
Keywords: Sørishavet; Weddellhavet; bunnvann; glasiologi; havnivå; innlandsis; isbrem; klimatologi; oseanografi; smelting; vannmasser

Deriving micro- to macro-scale seismic velocities from ice-core c axis orientations - Kerch, Johanna; Diez, Anja; Weikusat, Ilka; Eisen, Olaf (The Cryosphere, 2018)
One of the great challenges in glaciology is the ability to estimate the bulk ice anisotropy in ice sheets and glaciers, which is needed to improve our understanding of ice-sheet dynamics. We investigate the effect of crystal anisotropy on seismic velocities in glacier ice and revisit the framework which is based on fabric eigenvalues to derive approximate seismic velocities by exploiting the assumed symmetry. In contrast to previous studies, we calculate the seismic velocities using the exact c axis angles describing the orientations of the crystal ensemble in an ice-core sample. We apply this approach to fabric data sets from an alpine and a polar ice core. Our results provide a quantitative evaluation of the earlier approximative eigenvalue framework. For near-vertical incidence our results differ by up to 135 m s−1 for P-wave and 200 m s−1 for S-wave velocity compared to the earlier framework (estimated 1 % difference in average P-wave velocity at the bedrock for the short alpine ice core). We quantify the influence of shear-wave splitting at the bedrock as 45 m s−1 for the alpine ice core and 59 m s−1 for the polar ice core. At non-vertical incidence we obtain differences of up to 185 m s−1 for P-wave and 280 m s−1 for S-wave velocities. Additionally, our findings highlight the variation in seismic velocity at non-vertical incidence as a function of the horizontal azimuth of the seismic plane, which can be significant for non-symmetric orientation distributions and results in a strong azimuth-dependent shear-wave splitting of max. 281 m s−1 at some depths. For a given incidence angle and depth we estimated changes in phase velocity of almost 200 m s−1 for P wave and more than 200 m s−1 for S wave and shear-wave splitting under a rotating seismic plane. We assess for the first time the change in seismic anisotropy that can be expected on a short spatial (vertical) scale in a glacier due to strong variability in crystal-orientation fabric (±50 m s−1 per 10 cm). Our investigation of seismic anisotropy based on ice-core data contributes to advancing the interpretation of seismic data, with respect to extracting bulk information about crystal anisotropy, without having to drill an ice core and with special regard to future applications employing ultrasonic sounding.
Publisher: Copernicus Publications
Keywords: Antarktis; glasiologi

Mapping glacier-related research in polar regions: a bibliometric analysis of research output from 1987 to 2016 - Liang, Qi; Peng, Sha; Niu, Beibei; Zhou, Chunxia; Wang, Zhen (Polar Research, 2018)
We carried out a bibliometric analysis of literature related to glaciers in polar regions from the period 1987–2016 indexed in the Science Citation Index Expanded database. A comprehensive review was performed by analysing the research output trends, publication categories, main journals, leading countries and their collaborations, leading scientists, author keywords and Keywords Plus. The results indicated that the number of publications related to glaciers in polar regions has increased rapidly. The USA and several European countries, including the UK, France, Germany and Switzerland, are the leaders in the field of glacial studies, as reflected both in the productivity measures and in the distribution of core scientists. Quaternary Science Reviews, the Journal of Glaciology, and Geophysical Research Letters were the most productive journals for glacial studies. The synthesized analysis of the keywords demonstrated the current research emphases and hinted at future research trends. Reconstructing past climate changes through studies of ice-core records is one of the most important research subjects. Numerical modelling has become a commonly used tool in polar region glacial research. A better understanding of the responses of glaciers to widespread climatic warming is needed now and in the future.
Keywords: Antarktis; bibliometri; glasiologi; isbreer; klimaendringer; litteratur; miljøendringer; polarområdene

Observations of Ice Nucleating Particles Over Southern Ocean Waters - McCluskey, Christina S; Hill, Thomas C J; Humphries, Ruhi S; Rauker, Anne M; Moreau, Sebastien; Strutton, P G; Chambers, Scott Dudley; Williams, Alastair G; McRobert, I; Ward, J; Keywood, Melita D; Harnwell, J; et al. (Geophysical Research Letters, 2018)
A likely important feature of the poorly understood aerosol-cloud interactions over the Southern Ocean (SO) is the dominant role of sea spray aerosol, versus terrestrial aerosol. Ice nucleating particles (INPs), or particles required for heterogeneous ice nucleation, present over the SO have not been studied in several decades. In this study, boundary layer aerosol properties and immersion freezing INP number concentrations (nINPs) were measured during a ship campaign that occurred south of Australia (down to 53°S) in March–April 2016. Ocean surface chlorophyll a concentrations ranged from 0.11 to 1.77 mg/m3, and nINPs were a factor of 100 lower than historical surveys, ranging from 0.38 to 4.6 m−3 at −20 °C. The INP population included organic heat-stable material, with contributions from heat-labile material. Lower INP source potentials of SO seawater samples compared to Arctic seawater were consistent with lower ice nucleating site densities in this study compared to north Atlantic air masses.
Keywords: Sørishavet; atmosfæren; iskjerner; iskrystaller; klimatologi; marin organisk aerosol; meteorologi; skyer

Chinstrap penguin population genetic structure: one or more populations along the Southern Ocean? - Mura-Jornet, Isidora; Pimentel, Carolina; Dantas, Gisele P M; Petry, Maria Virginia; González-Acuña, Daniel; Barbosa, Andrés; Lowther, Andrew D; Kovacs, Kit M; Poulin, Elie; Vianna, Juliana A (BMC Evolutionary Biology, 2018)
Keywords: Bouvetøya; Sørishavet; fugler; genetikk; marin biologi; ornitologi; pingviner

Net Community Production in the Southern Ocean: Insights From Comparing Atmospheric Potential Oxygen to Satellite Ocean Color Algorithms and Ocean Models - Nevison, Cynthia; Munro, David; Lovenduski, Nicole; Cassar, Nicolas; Keeling, Ralph; Krummel, Paul; Tjiputra, Jerry (Geophysical Research Letters, 2018)
The contribution of oceanic net community production (NCP) to the observed seasonal cycle in atmospheric potential oxygen (APO) is estimated at Cape Grim, Tasmania. The resulting APONCP signal is compared to satellite and ocean model-based estimates of POC export and NCP across the Southern Ocean. The satellite products underestimate the amplitude of the observed APONCP seasonal cycle by more than a factor of 2. Ocean models suggest two reasons for this underestimate: (1) Current satellite products substantially underestimate the magnitude of NCP in early spring. (2) Seasonal O2 outgassing is supported in large part by storage of carbon in DOC and living biomass. More DOC observations are needed to help evaluate this latter model prediction. Satellite products could be improved by developing seasonally dependent relationships between remote sensing chlorophyll data and in situ NCP, recognizing that the former is a measure of mass, the latter of flux.
Keywords: Sørishavet; biogeokjemi; biomasse; fytoplankton; karboneksport; marin biologi; oseanografi

Mesospheric Nitric Acid Enhancements During Energetic Electron Precipitation Events Simulated by WACCM-D - Orsolini, Yvan J.; Smith-Johnsen, Christine; Marsh, Daniel R.; Stordal, Frode; Rodger, Craig J.; Verronen, Pekka T.; Clilverd, Mark A. (Journal of Geophysical Research: Atmospheres, 2018)
While observed mesospheric polar nitric acid enhancements have been attributed to energetic particle precipitation through ion cluster chemistry in the past, this phenomenon is not reproduced in current whole-atmosphere chemistry-climate models. We investigate such nitric acid enhancements resulting from energetic electron precipitation events using a recently developed variant of the Whole Atmosphere Community Climate Model (WACCM) that includes a sophisticated ion chemistry tailored for the D-layer of the ionosphere (50–90 km), namely, WACCM-D. Using the specified dynamics mode, that is, nudging dynamics in the troposphere and stratosphere to meteorological reanalyses, we perform a 1-year-long simulation (July 2009–June 2010) and contrast WACCM-D with the standard WACCM. Both WACCM and WACCM-D simulations are performed with and without forcing from medium-to-high energy electron precipitation, allowing a better representation of the energetic electrons penetrating into the mesosphere. We demonstrate the effects of the strong particle precipitation events which occurred during April and May 2010 on nitric acid and on key ion cluster species, as well as other relevant species of the nitrogen family. The 1-year-long simulation allows the event-related changes in neutral and ionic species to be placed in the context of their annual cycle. We especially highlight the role played by medium-to-high energy electrons in triggering ion cluster chemistry and ion-ion recombinations in the mesosphere and lower thermosphere during the precipitation event, leading to enhanced production of nitric acid and raising its abundance by 2 orders of magnitude from 10−4 to a few 10−2 ppb.
Keywords: Antarktis; elektroner; energiske partikler; geomagnetiske stormer; geovitenskap; ionosfæren; klimamodeller; meteorologi; polarområdene; salpetersyre; stratosfæren

Vil isen i Antarktis smelte? - Østerhus, Svein (2018)
Isen i Antarktis smelter ikkje med det første, men store endringar er undervegs i havet. Havvatnet rundt Antarktis er iskaldt, men nå observerer vi at varmare vatn strøymer innunder den flytande delen av is-kappen. Om denne utviklinga ikkje stopper vil meir innlandsis strøyme ut i havet og føre til at havnivået vil stige med fleire meter. Det er langt frå sikkert at dette vil skje, men det er eit veldig viktig klimaspørsmål som vi må forstå betre. Difor har Uni Research med støtte av Forskingsrådet og Polarinstituttet bygd fleire havobservatorium for å kunne gi eit tidleg varsel dramatisk endringar.
Publication Title: Forskning.no
Keywords: Sørishavet; havnivåstigning; issmelting; klimaendringer; populærvitenskap

Psoroma antarcticum, a new lichen species from Antarctica and neighbouring areas - Park, Chae Haeng; Hong, Soon Gyu; Elvebakk, Arve (Polar Biology, 2018)
Keywords: Antarktis; biodiversitet; botanikk; lav; moser; planter

Multi-temporal variation of the Ross Sea Polynya in response to climate forcings - Park, Jinku; Kim, Hyun-Cheol; Kidwell, Autumn; Hwang, Jihyun (Polar Research, 2018)
The multi-temporal scales of two physical characteristics (areas and occurrence time) of the Ross Sea Polynya (RSP) in Antarctica were analysed using a sea-ice concentration data set (1979–2014) derived from the Scanning Multichannel Microwave Radiometer, the Special Sensor Microwave Imager and Sensor Microwave Imager Sounder. Then, the Ensemble Empirical Mode Decomposition (EEMD) was applied to the data sets to decompose signals into finite numbers of intrinsic mode functions and a residual mode: long time trend. This approach allowed us to understand the long-term variability of the RSP area and occurrence in response to atmospheric forcing through teleconnections between low and high latitudes by comparing the Nino3.4 and Southern Annular Mode (SAM) indices. The nonlinear trend of the RSP areas derived from the EEMD residual had an upward trending shift in the early 1990s and was fairly consistent with the nonlinear trend of Nino3.4. However, the trend of RSP occurrence time progressively increased and had a significant effect on the long time scale. The trend of the RSP area is significantly correlated (+0.98) with the ratio of the trend of the meridional to zonal wind components related with the nonlinearity of Nino3.4, suggesting that meridional wind stress dominated the changes of the polynya area in the Ross Sea. In addition, the nonlinear trends between the SAM and RSP occurrence time show a strong positive correlation, contributing to the earlier onset of polynya expansion and delayed connection with the open ocean owing to enhanced southerly winds.
Keywords: Sørishavet; havis; klimaendringer; klimatologi; oseanografi; polynja; sjøis; sørlig oscillasjon

Influence of meteorological parameters on atmospheric CO2 at Bharati, the Indian Antarctic research station - Pathakoti, Mahesh; Gaddamidi, Sreenivas; Gharai, Biswadip; Sudhakaran Syamala, Prijith; Venkata Narasimha Rao, Pamaraju; Choudhury, Saroj Bandh; Venkata Raghavendra, Kaila; Dadhwal, Vinay Kumar (Polar Research, 2018)
During the 35th Indian Scientific Expedition to Antarctica, measurements of atmospheric carbon dioxide (CO 2 ) were carried out using a Li-Cor CO 2 /H 2 O analyser at Bharati, the Indian Antarctic research station. This study examines the short-term variability of atmospheric CO 2 during the austral summer (January–February) of 2016. An average of 396.25 ± 4.20 ppm was observed during the study period. Meteorological parameters such as relative humidity, precipitation, wind speed, air temperature and atmospheric boundary layer height in conjunction with photosynthetically active radiation, the biological activity indicator which modulates atmospheric CO 2 concentration have been investigated. High wind speed (>20 m s −1 ) combined with precipitation scavenges CO 2 in the atmosphere, resulting in low concentrations at the study site. The lowest CO 2 concentration of 385 ppm coincided with heavy precipitation of 15 mm during study period. Statistical analysis of the data shows that precipitation and relative humidity independently correlated 55% (r = −0.55) and 32% (r = −0.32), respectively, with the variability of CO 2 mixing in the atmosphere at the study site. Atmospheric CO 2 was significantly correlated with precipitation alone with a p value of 0.003. Further, multiple regression analysis was performed to test the significant relation between variability of atmospheric CO 2 and meteorological parameters. Long-range air-mass transport analysis depicted that the majority of the air masses are reaching the study site through the oceanic region.
Keywords: Antarktis; atmosfæren; drivhuseffekt; drivhusgasser; forskning; karbondioksid; klimagasser; luftmassetransport; meteorologi; nedbør; polarområdene

Planktonic food web structure at SSTF and PF in the Indian sector of the Southern Ocean during austral summer 2011 - Pillai, H U K; Anilkumar, N; Achuthankutty, C T; Mendes, C R; Sabu, P; Jayalakshmi, K V; Devi, C R Asha; Dessai, Deepti; George, Jenson; Pavithran, Sini; Hari Devi, C K; Tripathy, S C; et al. (Polar Research, 2018)
This study aims to describe the planktonic food web structure with respect to phytoplankton biomass (chlorophyll a ) and prevailing environmental conditions at the South Subtropical Front (SSTF) and the Polar Front (PF) in the Indian sector of the Southern Ocean. Sampling was carried out at each front for 72 hrs, at 6-hr intervals, during the austral summer 2011. Considerable variations were observed in the hydrography between these two fronts. A strong temperature minimum layer was observed at the PF. Although the surface primary production and chlorophyll a values showed similar trends at both the fronts, the water column values of these parameters showed major disparities. The phytoplankton composition also revealed marked difference between the fronts. A deep chlorophyll maximum concordant with the upper limit of the temperature minimum layer was prominent at the PF. The microzooplankton abundance at the SSTF was twice as high as at the PF. The mesozooplankton biovolume and population density also showed considerable variations between these fronts. Noticeable diel variations were observed in the surface mesozooplankton biovolumes at both the fronts and the copepod Pleuromamma gracilis showed active diel vertical migration at SSTF. Both the grazing and senescence indices showed significant variations between these fronts, suggesting a disparity in the ecological efficiency of the two regions. The variability observed in the plankton community structure with respect to the hydrography and the biological components measured suggests that a multivorous food web at the SSTF and a conventional food web at the PF prevailed during the period of study.
Keywords: Sørishavet; biomasse; fytoplankton; hydrografi; marin biologi; zooplankton; økosystemer

Interhemispheric Survey of Polar Cap Aurora - Reidy, Jade; Fear, Robert; Whiter, Daniel; Lanchester, Betty; Kavanagh, Andrew John; Milan, Steve; Carter, Jennifer; Paxton, Larry; Zhang, Yongliang (Journal of Geophysical Research: Space Physics, 2018)
This study investigates the interhemispheric nature of polar cap auroras via ultraviolet imaging, combined with particle data, to determine whether they occur on open or closed field lines. Data from the SSUSI (Special Sensor Ultraviolet Spectrographic Imager) instrument on board the DMSP (Defence Meteorological Satellite Program) spacecraft are examined. The DMSP spacecraft are in 90-min orbits; hence, images of each hemisphere are separated by 45 min providing a good opportunity for interhemispheric study. 21 polar cap arc (PCA) events are recorded in December 2015 which have particle data from the SSJ/4 particle spectrometer associated with an arc in at least one hemisphere. Nine events are found to contain 'arcs' consistent with a closed field line mechanism, that is, arcs associated with an ion signature present in both hemispheres. Six events contained arcs that were consistent with an 'open field line' mechanism, that is, they were associated with electron-only precipitation. Events containing arcs that were not consistent with either of these expectations are also explored, including an example of a 'non-conjugate' theta aurora and an interesting example of auroral morphology similar to a PCA which is associated with a geomagnetic storm. Seasonal effects are also investigated through a statistical analysis of PCAs over 4 months in 2015. It is found that PCAs are visible in the SSUSI data at least 20% of the time and that it is likely some are missed due to the spacecraft field of view and poor sensitivity in the summer hemisphere due to increased solar illumination.
Keywords: Antarktis; astronomi; energiske partikler; geomagnetiske stormer; meteorologi; polarlys; polarområdene; solvind

Increasing temperature may shift availability of euphausiid prey in the Southern Ocean - Richerson, Kate; Driscoll, Ryan; Mangel, Marc (Marine Ecology Progress Series, 2018)
Climate change is predicted to affect Southern Ocean biota in complex ways. Euphausiids play a crucial role in the trophodynamics of the ecosystem, and their status under future environmental scenarios is the subject of much concern. Thysanoessa macrura is the most widely distributed, numerically abundant, and ubiquitous euphausiid south of the Polar Front and may be an underappreciated prey species. T. macrura is eurythermic and may be better able to tolerate warming ocean temperatures in comparison to the more stenothermic Antarctic krill Euphausia superba. We use temperature-dependent growth models and biomass per recruit to investigate how the availability of this euphausiid to predators may change under a range of temperature scenarios. We contrast this with the availability of E. superba and find that, under some ranges of temperature change, increasing T. macrura growth may be able to partially compensate for decreasing E. superba growth in terms of biomass available for predators. However, in spite of its considerable biomass, other aspects of this species, such as its size and habitat, may limit its potential to replace E. superba in the diet of many predators. KEYWORDS: Thysanoessa macrura · Euphausia superba · Growth · Temperature · Climate change · Krill predators · Southern Ocean · Euphausiids · Modeling
Keywords: Sørishavet; biomasse; havoppvarming; klimaendringer; krill; marin biologi; marine økosystemer; miljøendringer; plankton

A New Bathymetry for the Southeastern Filchner-Ronne Ice Shelf: Implications for Modern Oceanographic Processes and Glacial History - Rosier, Sebastian H R; Hofstede, Coen; Brisbourne, Alex Mark; Hattermann, Tore; Nicholls, Keith William; Davis, Peter E D; Anker, Paul; Hillenbrand, Claus-Dieter; Smith, Andrew M; Corr, Hugh F (Journal of Geophysical Research: Oceans, 2018)
The Filchner-Ronne Ice Shelf, the ocean cavity beneath it, and the Weddell Sea that bounds it, form an important part of the global climate system by modulating ice discharge from the Antarctic Ice Sheet and producing cold dense water masses that feed the global thermohaline circulation. A prerequisite for modeling the ice sheet and oceanographic processes within the cavity is an accurate knowledge of the sub-ice sheet bedrock elevation, but beneath the ice shelf where airborne radar cannot penetrate, bathymetric data are sparse. This paper presents new seismic point measurements of cavity geometry from a particularly poorly sampled region south of Berkner Island that connects the Filchner and Ronne ice shelves. An updated bathymetric grid formed by combining the new data with existing data sets reveals several new features. In particular, a sill running between Berkner Island and the mainland could alter ocean circulation within the cavity and change our understanding of paleo-ice stream flow in the region. Also revealed are deep troughs near the grounding lines of Foundation and Support Force ice streams, which provide access for seawater with melting potential. Running an ocean tidal model with the new bathymetry reveals large differences in tidal current velocities, both within the new gridded region and further afield, potentially affecting sub-ice shelf melt rates.
Keywords: Sørishavet; batymetri; brehylle; innlandsis; isbrem; isshelf; klima; oseanografi; tidevann

Description of plant communities on Half Moon Island, Antarctica - Schmitz, Daniela; Putzke, Jair; Pereira de Albuquerque, Margéli; Schünemann, Adriano Luis; Costa Beber Vieira, Frederico; de Carvalho Victoria, Filipe de Carvalho Victoria; Batista Pereira, Antônio (Polar Research, 2018)
During February–March of the austral summers of 2013/14 and 2014/2015, fieldwork was performed on Half Moon Island, South Shetland Archipelago, Antarctica, to evaluate the distribution and abundance of mosses and lichens, as well as to describe and map the plant communities there. The quadrat (20 × 20 cm) sampling method was employed in a phytosociological study that aimed to describe these communities. The area was mapped using an Astech Promark II® DGPS, yielding sub-metric precision after post-processing with software. The number of species totalled 38 bryophytes, 59 lichens, only one flowering plant (Deschampsia antarctica Desv.), and two macroscopic terrestrial algae. Five types of plant communities were identified on the island, as follows: (1) fruticose lichen and moss cushion, (2) moss carpet, (3) muscicolous lichen, (4) crustose lichen and (5) moss turf.
Keywords: Antarktis; botanikk; bryozoa; flora; fytososiologi; lav; moser; planter; økologi

Remarkable structural resistance of a nanoflagellate-dominated plankton community to iron fertilization during the Southern Ocean experiment LOHAFEX - Schulz, Isabelle; Montresor, Marina; Klaas, Christine; Assmy, Philipp; Wolzenburg, Sina; Gauns, Mangesh; Sarkar, Amit; Thiele, Stefan; Wolf-Gladrow, Dieter; Naqvi, Wajih; Smetacek, Victor (Marine Ecology Progress Series, 2018)
The genesis of phytoplankton blooms and the fate of their biomass in iron-limited, high-nutrient-low-chlorophyll regions can be studied under natural conditions with ocean iron fertilization (OIF) experiments. The Indo-German OIF experiment LOHAFEX was carried out over 40 d in late summer 2009 within the cold core of a mesoscale eddy in the productive south-west Atlantic sector of the Southern Ocean. Silicate concentrations were very low, and phytoplankton biomass was dominated by autotrophic nanoflagellates (ANF) in the size range 3-10 µm. As in all previous OIF experiments, the phytoplankton responded to iron fertilization by increasing the maximum quantum yield (Fv/Fm) and cellular chlorophyll levels. Within 3 wk, chlorophyll levels tripled and ANF biomass doubled. With the exception of some diatoms and dinoflagellates, the biomass levels of all other groups of the phyto- and protozooplankton (heterotrophic nanoflagellates, dinoflagellates and ciliates) remained remarkably stable throughout the experiment both inside and outside the fertilized patch. We attribute the unusually high biomass attained and maintained by ANF to the absence of their grazers, the salps, and to constraints on protozooplankton grazers by heavy predation exerted by the large copepod stock. The resistance to change of the ecosystem structure over 38 d after fertilization, indicated by homogeneity at regional and temporal scales, suggests that it was locked into a stable, mature state that had evolved in the course of the seasonal cycle. The LOHAFEX bloom provides a case study of a resistant/robust dynamic equilibrium between auto- and heterotrophic ecosystem components resulting in low vertical flux both inside and outside the patch despite high biomass levels. KEYWORDS: Antarctic · Protists · Fe-limitation · Si-limitation · Ecology-biogeochemistry relationship · Carbon:chlorophyll ratios · Ecosystem stability
Keywords: Sørishavet; biogeokjemi; biomasse; fytoplankton; marin biologi; økologi; økosystemer

A continent-wide search for Antarctic petrel breeding sites with satellite remote sensing - Schwaller, Mathew R; Lynch, Heather J; Tarroux, Arnaud; Prehn, Brandon (Remote Sensing of Environment, 2018)
The Antarctic petrel (Thalassoica antarctica) has been identified as a key species for monitoring the status and health of the Southern Ocean and Antarctic ecosystems. Breeding colonies of the Antarctic petrel are often found on isolated nunataks far from inhabited stations, some up to hundreds of kilometers from the shoreline. It is difficult therefore to monitor and census known colonies, and it is believed that undiscovered breeding locations remain to be found. We developed an algorithm that can detect Antarctic petrel colonies and used it to complete a continent-wide survey using Landsat-8 Operational Line Imager (OLI) imagery in Antarctica up to the southernmost extent of Landsat's orbital view at 82.68°S. Our survey successfully identified 8 known Antarctic petrel colonies containing 86% of the known population of Antarctic petrels. The survey also identified what appears to be a significant population of breeding birds in areas not known to host breeding Antarctic petrel colonies. Our survey suggests that the breeding population at Mt. Biscoe (66°13′S 51°21′E), currently reported to be in the 1000s, may actually be on the order of 400,000 breeding pairs, which would make it the largest known Antarctic petrel breeding colony in the world. The algorithm represents a first-ever attempt to apply satellite remote sensing to assess the distribution and abundance of the Antarctic petrel on a continent-wide basis. As such, we note several algorithm shortcomings and identify research topics for algorithm improvement. Even with these caveats, our algorithm for identifying Antarctic petrel colonies with Landsat imagery demonstrates the feasibility of monitoring their populations using satellite remote sensing and identifies breeding locations, including Mt. Biscoe, that should be considered high priorities for validation with directed field surveys.
Keywords: Antarktis; hekkekoloni; jordobservasjon; ornitologi; petreller; sjøfugler; zoologi

Nighttime mesospheric ozone enhancements during the 2002 southern hemispheric major stratospheric warming - Smith-Johnsen, Christine; Orsolini, Yvan; Stordal, Frode; Limpasuvan, Varavut; Pérot, Kristell (Journal of Atmospheric and Solar-Terrestrial Physics, 2018)
Sudden Stratospheric Warmings (SSW) affect the chemistry and dynamics of the middle atmosphere. Major warmings occur roughly every second winter in the Northern Hemisphere (NH), but has only been observed once in the Southern Hemisphere (SH), during the Antarctic winter of 2002. Observations by the Global Ozone Monitoring by Occultation of Stars (GOMOS, an instrument on board Envisat) during this rare event, show a 40% increase of ozone in the nighttime secondary ozone layer at subpolar latitudes compared to non-SSW years. This study investigates the cause of the mesospheric nighttime ozone increase, using the National Center for Atmospheric Research (NCAR) Whole Atmosphere Community Climate Model with specified dynamics (SD-WACCM). The 2002 SH winter was characterized by several reductions of the strength of the polar night jet in the upper stratosphere before the jet reversed completely, marking the onset of the major SSW. At the time of these wind reductions, corresponding episodic increases can be seen in the modelled nighttime secondary ozone layer. This ozone increase is attributed largely to enhanced upwelling and the associated cooling of the altitude region in conjunction with the wind reversal. This is in correspondence to similar studies of SSW induced ozone enhancements in NH. But unlike its NH counterpart, the SH secondary ozone layer appeared to be impacted less by episodic variations in atomic hydrogen. Seasonally decreasing atomic hydrogen plays however a larger role in SH compared to NH.
Keywords: Antarktis; atmosfæren; geovitenskap; ozonlaget

Revisiting perceptions and evolving culture: a community dialogue on women in polar research - Starkweather, Sandra; Seag, M; Lee, O; Pope, A (Polar Research, 2018)
Women have made outstanding contributions to polar research in recent decades, though full engagement may be hindered by persistent inequities, including notably the prevalence of workplace harassment. Remote field settings, such as those pervasive in polar research, have been identified as particularly susceptible to cultures of harassment. It was therefore timely at the Polar 2018 Open Science Conference in Davos, Switzerland, to convene a discussion focused on women’s perspectives and experiences. A panel discussion—“From Entering the Field to Taking the Helm: Perspectives of Women in Polar Research”—took place on 20 June 2018 and featured five women undertaking work from marine biotechnology to organizational leadership, across career levels. Over 300 conference attendees joined the lunchtime panel. The panellists’ perspectives on historical barriers, current challenges and future prospects revealed that while challenges persist, experiences vary greatly. Audience engagement underscored the need to sustain dialogue at polar meetings, to bring visibility to the statistics related to workplace harassment and to encourage polar science organizations to assume leadership on promoting equitable workplace culture.
Keywords: Antarktis; arbeidsmiljø; kjønn; kultur; likestilling; polarforskning; sosiologi; trakassering; vitenskap

Precipitation instruments at Rothera Station, Antarctic Peninsula: a comparative study - Tang, Malcolm S Y; Nettukandy Chenoli, Sheeba; Colwell, Steve; Grant, Rosey; Simms, Mairi; Law, John; Abu Samaha, Azizan (Polar Research, 2018)
Direct measurement of precipitation in the Antarctic using ground-based instruments is important to validate the results from climate models, reanalyses and satellite observations. Quantifying precipitation in Antarctica faces many unique challenges such as wind and other technical difficulties due to the harsh environment. This study compares a variety of precipitation measurements in Antarctica, including satellite data and reanalysis fields at Rothera Station, Antarctica Peninsula. The tipping bucket gauges (TBGs) were less sensitive than laserbased sensors (LBSs). The most sensitive LBS (Visibility and Present Weather Sensor, VPF-730) registered 276 precipitation days, while the most sensitive TBG (Universal Precipitation Gauge, UPG-1000) detected 152 precipitation days. Case studies of the precipitation and seasonal accumulation results show the VPF-730 to be the most reliable precipitation sensor of the evaluated instruments. The precipitation amounts given by the reanalyses were positively correlated with wind speed. The precipitation from the Japanese 55-year Reanalysis was most affected by wind speed. Case studies also show that during low wind periods, precipitation measurements from the instruments were very close to the precipitation measurement given by the Global Precipitation Climatology Project (GPCP) 1-degreedaily (1DD) data. During strong wind events, the GPCP 1DD did not fully capture the effect of wind, accounting for the relatively small precipitation amount. The Laser Precipitation Monitor (LPM) and Campbell Scientific-700 (CS700H) experienced instrumental errors during the study, which caused the precipitation readings to become exceedingly high and low, respectively. Installing multiple LBSs in different locations (in close proximity) can help identify inconsistency in the readings.
Keywords: Antarktis; analyser; klimatologi; meteorologi; nedbør; satellitt observasjoner

Temporal variation in trophic relationships among three congeneric penguin species breeding in sympatry - Tarroux, Arnaud; Lydersen, Christian; Trathan, Philip N; Kovacs, Kit M. (Ecology and Evolution, 2018)
Penguins are a monophyletic group in which many species are found breeding sympatrically, raising questions regarding how these species coexist successfully. Here, the isotopic niche of three sympatric pygoscelid penguin species was investigated at Powell Island, South Orkney Islands, during two breeding seasons (austral summers 2013–2014 and 2015–2016). Measurements of carbon (δ13C) and nitrogen (δ15N) stable isotope ratios were obtained from blood (adults) or feather (chicks) samples collected from Adélie Pygoscelis adeliae, chinstrap P. antarctica, and gentoo P. papua penguins. Isotopic niche regions (a proxy for the realized trophic niches) were computed to provide estimates of the trophic niche width of the studied species during the breeding season. The isotopic niche regions of adults of all three species were similar, but gentoo chicks had noticeably wider isotopic niches than the chicks of the other two species. Moderate to strong overlap in isotopic niche among species was found during each breeding season and for both age groups, suggesting that the potential for competition for shared food sources was similar during the two study years, although the actual level of competition could not be determined owing to the lack of data on resource abundance. Clear interannual shifts in isotopic niche were seen in all three species, though of lower amplitude for adult chinstrap penguins. These shifts were due to variation in carbon, but not nitrogen, isotopic ratios, which could indicate either a change in isotopic signature of their prey or a switch to an alternative food web. The main conclusions of this study are that (1) there is a partial overlap in the isotopic niches of these three congeneric species and that (2) they responded similarly to changes that likely occurred at the base of their food chain between the 2 years of the study.
Keywords: Antarktis; fôring; hekkekoloni; klimaendringer; krill; miljøendringer; pingviner; plankton; stabile isotoper; zoologi

Investigation of Babesia sp. in pygoscelid penguins at the South Shetland Islands - Thijl Vanstreels, Ralph Eric; Ferreira Junior, Francisco C; de Angeli Dutra, Daniela; Epiphanio, Sabrina; Braga, Érika M; Pistorius, Pierre A; Catão-Dias, José Luiz (Polar Research, 2018)
Babesia spp. are tick-borne parasites, and 16 avian-infecting species have been described to date, including one species ( Babesia peircei ) that infects penguins. Considering the results of a recent study reporting Babesia sp. in penguins on Deception Island, South Shetland Islands, we re-examined the samples obtained in a previous investigation on the occurrence of blood parasites in adult Adélie ( Pygoscelis adeliae ), chinstrap ( Pygoscelis antarcticus ) and gentoo penguins ( Pygoscelis papua ) on King George and Elephant islands, South Shetland Islands. Notwithstanding a comprehensive re-examination of the blood smears, Babesia sp. was not detected. When we employed two nested PCR tests targeting the 18S rRNA gene of Babesia , a considerable proportion of the samples produced positive results; however, gene sequencing revealed these were due to cross-amplification of non-target organisms. We therefore did not detect Babesia sp. infection in penguins on King George and Elephant islands. Additional studies will be valuable to clarify the distribution and epidemiology of tick-borne pathogens in sub-Antarctic and Antarctic seabirds.
Keywords: Antarktis; biologi; epidemiologi; ornitologi; parasitter; pingviner; sjøfugler; zoologi

Topographic Steering of Enhanced Ice Flow at the Bottleneck Between East and West Antarctica - Winter, Kate; Ross, Neil; Ferraccioli, Fausto; Jordan, Tom A; Corr, Hugh F J; Forsberg, René; Matsuoka, Kenichi; Olesen, Arne V; Casal, Tania G (Geophysical Research Letters, 2018)
Hypothesized drawdown of the East Antarctic Ice Sheet through the “bottleneck” zone between East and West Antarctica would have significant impacts for a large proportion of the Antarctic Ice Sheet. Earth observation satellite orbits and a sparseness of radio echo sounding data have restricted investigations of basal boundary controls on ice flow in this region until now. New airborne radio echo sounding surveys reveal complex topography of high relief beneath the southernmost Weddell/Ross ice divide, with three subglacial troughs connecting interior Antarctica to the Foundation and Patuxent Ice Streams and Siple Coast ice streams. These troughs route enhanced ice flow through the interior of Antarctica but limit potential drawdown of the East Antarctic Ice Sheet through the bottleneck zone. In a thinning or retreating scenario, these topographically controlled corridors of enhanced flow could however drive ice divide migration and increase mass discharge from interior West Antarctica to the Southern Ocean.
Keywords: Antarktis; glasiologi; innlandsis; isgjennomtrengende; isstrøm; radarundersøkelser

Global Cooling Contributed to the Establishment of a Modern-Like East Asian Monsoon Climate by the Early Miocene - Zhang, Ran; Zhang, Zhongshi; Jiang, Dabang (Geophysical Research Letters, 2018)
The establishment of a modern-like monsoon climate in East Asia by the early Miocene was a complex process forced by several factors, and previous studies paid less attention to global cooling. Here we investigate this process using climate modeling by considering changes in topography and global cooling under the early Miocene boundary conditions. Using early Miocene paleogeography and an atmospheric CO2 concentration of 560 ppmv, our model results indicate that a nonzonal climate pattern has appeared in East China but that this climate exhibits weak precipitation and wind seasonality. Such seasonality strengthens as the concentration of atmospheric CO2 decreases from 560 to 420 ppmv and resembles the modern-like condition after the growth of the Antarctic ice sheet. Although the development of East Asian topography can further strengthen this seasonality, our results indicate that global cooling is also pivotal for the establishment of a modern-like monsoon climate in East Asia.
Keywords: Antarktis; innlandsis; klimamodeller; klimatologi; nedbør; paleogeografi

Abnormal gonads in the Antarctic toothfish (Dissostichus mawsoni Norman, 1937 [Perciformes: Nototheniidae]): the first record and histological description - Zhukova, Kristina A; Gordeev, Ilya I; Kuznetsova, Elena N (Polar Research, 2018)
This paper describes the morphology and histology of abnormal gonads in Antarctic toothfish (Dissostichus mawsoni) and the possibility of intersexuality and senescence of some individuals. Two old (approximately 25 years) and large (184–185 cm) specimenswith abnormal gonadswere caught in the Antarctic during commercial fishing for toothfish and studied using histological methods. Although D. mawsoni is well-known and extensively studied, this is the first study dealing with abnormal gonads in the species. The histological analysis revealed that the gonads of the first specimen contained both male and female germ cells (ovotestis), the testicular and ovarian tissues being separated by a thick layer of connective tissue. The female portion was composed of secondary vitellogenic oocytes, primary vitellogenic, cortical alveolar and primary growth oocytes, while the testes contained cysts of spermatogonia and primary spermatocyte. The gonads of the second specimen were small, filiform and showed massive growth of the connective tissue, which occupied almost the entire gonad; a few spermatogonia without visible cystswere found. This study extends our understanding of sexual development in Antarctic toothfish, documenting the possibility of long-term interruptions in the reproductive cycle of this species.
Keywords: Sørishavet; fisker; gonader; histologi; marin biologi; morfologi; oseanografi; reproduksjon

Keynes, Trouton and the Hector Whaling Company. A personal and professional relationship - Basberg, Bjørn L (Business History, 2017)
John Maynard Keynes’ activities on the stock market are well known. One company in which he bought stocks was the Hector Whaling Company Ltd., London – a comparatively small and little known company founded in 1928. The director of this company was Rupert Trouton. He had worked with Keynes for the Government during the First World War, was his student at Cambridge, and became a close partner in the City from the 1920s and onwards. The reason why Keynes invested in Hector was obviously his association with Rupert Trouton. The first part of this paper explores briefly the development of the Hector Whaling Company and its origins in Norway. The main part analyses the relationship between Trouton and Keynes. The focus is on their co-operation relating to Hector Whaling, but their relationship regarding various other businesses, as well as on the personal level, is also described. The paper is based on studies of the Keynes archives in Cambridge as well as newly available archives of the Hector company. The analysis provides new insights to the more general question on the motivations and decisions behind Keynes’ stock market investments as well as the internationalization of the whaling industry in the 1920s and 30s.
Publisher: Routledge
Keywords: Sørishavet; hvalfangstindustri; hvalfangstselskaper; hvalindustri; pelagisk; økonomi

Persistent Organic Pollutants in the East Antarctic Atmosphere: Inter-Annual Observations from 2010 to 2015 Using High-Flow-Through Passive Sampling - Bengtson Nash, Susan M; Wild, Sean J; Hawker, Darryl W; Cropp, Roger A; Hung, Hayley; Wania, Frank; Xiao, Hang; Bohlin-Nizzetto, Pernilla; Bignert, Anders; Broomhall, Sara (Environmental Science & Technology, 2017)
In the first multiyear sampling effort for POPs in the eastern Antarctic atmosphere, 32 PCBs and 38 organochlorine pesticides were targeted in air collected with a high-flow-through passive sampler. Agricultural chemicals were found to dominate atmospheric profiles, in particular HCB and endosulfan-I, with average concentrations of 12 600 and 550 fg/m3, respectively. HCB showed higher concentrations in the austral summer, indicative of local, temperature-dependent volatilisation, while endosulfan-I appeared to show fresh, late-austral-summer input followed by temporally decreasing levels throughout the year. The current-use herbicide, trifluralin, and the legacy pesticides mirex and toxaphene, were detected in Antarctic air for the first time. Trifluralin was observed at low but increasing levels over the five-year period. Its detection in the Antarctic atmosphere provides evidence of its persistence and long-range environmental transport capability. While a time frame of five years exceeds the duration of most Antarctic air monitoring efforts, it is projected that continuous monitoring at the decadal scale is required to detect an annual 10% change in atmospheric concentrations of key analytes. This finding emphasizes the importance of continuous, long-term monitoring efforts in polar regions, that serve a special role as sentinel environments of hemispheric chemical usage trends.
Publisher: American Chemical Society
Keywords: Antarktis; atmosfæren; forurensning; kjemiske analyser; miljøgifter

Ontogenetic changes in the feeding strategy of Lepidonotothen nudifrons (Pisces, Nototheniidae) off the South Shetland Islands and the Antarctic Peninsula - Blasina, Gabriela; Cazorla, Andrea Lopez; Antoni, Mariana Deli; Bruno, Daniel; Delpiani, Matías; Díaz de Astarloa, Juan Martín (Polar Research, 2017)
The diet and feeding strategy of Lepidonotothen nudifrons off the South Shetland Islands and the Antarctic Peninsula, as well as their variation in relation to ontogenetic stage (juvenile– adult) and sampling area, were determined by stomach contents analysis. Additionally, the trophic level of this species was estimated to determine its position within the Antarctic food web. Out of 247 specimens with prey in their stomachs, 144 were caught near the South Shetland Islands and 103 off the Antarctic Peninsula. Ontogenetic changes in the trophic ecology of L. nudifrons were observed in both areas and were mainly related to a decrease of copepods and an increase of euphausiids in the diet. The diet of juveniles from the South Shetland Islands was characterized by the dominance of calanoid copepods, followed by isopods and amphipods, whereas diet off the Antarctic Peninsula was dominated by amphipods and cyclopoid copepods. The diet in adults was dominated by amphipods and euphausiids in both areas. The specialization of individual predators on different prey types was observed when considering the whole population of L. nudifrons, but when ontogenetic stages were considered separately it showed a more mixed feeding strategy, with different dominant prey for each class. Although the trophic level increased with fish size, L. nudifrons can be classified as secondary consumer throughout its lifespan.
Keywords: Sørishavet; amfipoder; copepoder; euphausiacea; fauna; fisker; isopoder; marin zoologi; økosystemer

Fracture propagation and stability of ice shelves governed by ice shelf heterogeneity - Borstad, Chris; McGrath, Daniel; Pope, Allen (Geophysical Research Letters, 2017)
Tabular iceberg calving and ice shelf retreat occurs after full-thickness fractures, known as rifts, propagate across an ice shelf. A quickly evolving rift signals a threat to the stability of Larsen C, the Antarctic Peninsula's largest ice shelf. Here we reveal the influence of ice shelf heterogeneity on the growth of this rift, with implications that challenge existing notions of ice shelf stability. Most of the rift extension has occurred in bursts after overcoming the resistance of suture zones that bind together neighboring glacier inflows. We model the stresses in the ice shelf to determine potential rift trajectories. Calving perturbations to ice flow will likely reach the grounding line. The stability of Larsen C may hinge on a single suture zone that stabilizes numerous upstream rifts. Elevated fracture toughness of suture zones may be the most important property that allows ice shelves to modulate Antarctica's contribution to sea level rise.
Keywords: Antarktis; geofysikk; glasiologi; havnivåstigning; is; isberg; isbrem; isfjell; isshelf; kalv; kalving

Tsunami and infragravity waves impacting Antarctic ice shelves - Bromirski, Peter D; Chen, Zhao; Stephen, Ralph A; Gerstoft, Peter; Arcas, Diego; Diez, Anja; Aster, Richard C; Wiens, Douglas A; Nyblade, Andrew Arnold (Journal of Geophysical Research: Oceans, 2017)
The responses of the Ross Ice Shelf (RIS) to the 16 September 2015 8.3 (Mw) Chilean earthquake tsunami (>75 s period) and to oceanic infragravity (IG) waves (50–300 s period) were recorded by a broadband seismic array deployed on the RIS from November 2014 to November 2016. Here we show that tsunami and IG-generated signals within the RIS propagate at gravity wave speeds (∼70 m/s) as water-ice coupled flexural-gravity waves. IG band signals show measureable attenuation away from the shelf front. The response of the RIS to Chilean tsunami arrivals is compared with modeled tsunami forcing to assess ice shelf flexural-gravity wave excitation by very long period (VLP; >300 s) gravity waves. Displacements across the RIS are affected by gravity wave incident direction, bathymetry under and north of the shelf, and water layer and ice shelf thicknesses. Horizontal displacements are typically about 10 times larger than vertical displacements, producing dynamical extensional motions that may facilitate expansion of existing fractures. VLP excitation is continuously observed throughout the year, with horizontal displacements highest during the austral winter with amplitudes exceeding 20 cm. Because VLP flexural-gravity waves exhibit no discernable attenuation, this energy must propagate to the grounding zone. Both IG and VLP band flexural-gravity waves excite mechanical perturbations of the RIS that likely promote tabular iceberg calving, consequently affecting ice shelf evolution. Understanding these ocean-excited mechanical interactions is important to determine their effect on ice shelf stability to reduce uncertainty in the magnitude and rate of global sea level rise.
Keywords: Sørishavet; brehylle; havnivåstigning; is; isbrem; isshelf; kalv; kalving; oseanografi; seismologi

Patterns of fungal–algal symbiont association in Usnea aurantiaco-atra reveal the succession of lichen–moss communities in Fildes Peninsula, Antarctica - Cao, Shunan; Peng, Fang; Zheng, Hongyuan; Liu, Chuanpeng; Zhou, Qiming (Polar Research, 2017)
Usnea aurantiaco-atra is the most widespread flora in Fildes Peninsula. There are two growth types of U. aurantiaco-atra: the erect form on rocks and the prostrate form associated with mosses. Phylogenetic analysis showed that individuals of the two growth forms share genotypes. Moreover, haploid disequilibrium testing indicated no significant genetic difference for the two growth forms when fungal and algal internal transcribed spacer rDNA were treated as two alleles of one lichen individual. The two growth forms of U. aurantiaco-atra appear to reflect different stages of lichen–moss community succession. A mode is proposed for demonstrating the occurrence of this succession.
Keywords: Antarktis; botanikk; flora; fylogenetikk; lav; moser; planter

Microplastic in the surface waters of the Ross Sea (Antarctica): Occurrence, distribution and characterization by FTIR - Cincinelli, Alessandra; Scopetani, Costanza; Chelazzi, David; Lombardini, Emilia; Martellini, Tania; Katsoyiannis, Athanasios; Fossi, Maria Cristina; Corsolini, Simonetta (Chemosphere, 2017)
This is the first survey to investigate the occurrence and extent of microplastic (MPs) contamination in sub surface waters collected near-shore and off-shore the coastal area of the Ross Sea (Antarctica). Moreover, a non-invasive method to analyze MPs, consisting in filtration after water sampling and analysis of the dried filter through Fourier Transform Infrared Spectroscopy (FTIR) 2D Imaging, using an FPA detector, was proposed. The non-invasiveness of analytical set-up reduces potential bias and allows subsequent analysis of the filter sample for determination of other classes of contaminants. MPs ranged from 0.0032 to 1.18 particle per m3 of seawater, with a mean value of 0.17 ± 0.34 particle m−3, showing concentrations lower than those found in the oceans worldwide. MPs included fragments (mean 71.9 ± 21.6%), fibers (mean 12.7 ± 14.3%), and others (mean 15.4 ± 12.8%). The presence of different types of MPs was confirmed by FTIR spectroscopy, with predominant abundance of polyethylene and polypropylene. The potential environmental impact arising from scientific activities, such as marine activities for scientific purposes, and from the sewage treatment plant, was also evidenced.
Keywords: Rosshavet; Sørishavet; forurensning; mikroplast; miljøgifter

On the effect of topography and wind on warm water inflow—An idealized study of the southern Weddell Sea continental shelf system - Daae, Kjersti; Hattermann, Tore; Darelius, Elin; Fer, Ilker (Journal of Geophysical Research: Oceans, 2017)
An idealized eddy-resolving numerical model, with topographic features common to the southern Weddell Sea, is constructed to study mechanisms through which warm deep water enters a wide continental shelf with a trough. The open ocean, represented by a 1700 m deep channel, is connected to a 400 m deep shelf with a continental slope. The shelf is narrow (50 km) in the east but widens to 300 km at the center of the model domain. Over the narrow shelf, the slope front is balanced by wind-driven Ekman downwelling and counteracting eddy overturning, favoring on-shelf transport of warm water in summer scenarios when fresher surface water is present. Over the wide shelf, the Ekman downwelling ceases, and the mesoscale eddies relax the front. Inflow of warm water is sensitive to along-shelf salinity gradients and is most efficient when denser water over the wide shelf favors up-slope eddy transport along isopycnals of the V-shaped slope front. Inflow along the eastern side of the trough cannot penetrate the sill region due to potential vorticity constraints, while along the western trough flank, eddy-induced inflow crosses the sill and reaches the ice front. The warm inflow into the trough is sensitive to the density of the outflowing dense shelf water. For weaker winds, absence of the dense water outflow leads to a reversal of the trough circulation and a strong inflow of warm water, while for stronger winds, baroclinic effects become less important and the inflow is similar to experiments including dense water outflow.
Keywords: Sørishavet; Weddellhavet; batymetri; geofysikk; havstrømmer; hydrografi; klimamodeller; klimatologi; kontinentalsokkel; vannvirvler

A global ocean climatology of preindustrial and modern ocean δ13C - Eide, Marie; Olsen, Are; Ninnemann, Ulysses S; Johannessen, Truls (Global Biogeochemical Cycles, 2017)
We present a global ocean climatology of dissolved inorganic carbon δ13C (‰) corrected for the 13C-Suess effect, preindustrial δ13C. This was constructed by first using Olsen and Ninnemann's (2010) back-calculation method on data from 25 World Ocean Circulation Experiment cruises to reconstruct the preindustrial δ13C on sections spanning all major oceans. Next, we developed five multilinear regression equations, one for each major ocean basin, which were applied on the World Ocean Atlas data to construct the climatology. This reveals the natural δ13C distribution in the global ocean. Compared to the modern distribution, the preindustrial δ13C spans a larger range of values. The maxima, of up to 1.8‰, occurs in the subtropical gyres of all basins, in the upper and intermediate waters of the North Atlantic, as well as in mode waters with a Southern Ocean origin. Particularly strong gradients occur at intermediate depths, revealing a strong potential for using δ13C as a tracer for changes in water mass geometry at these levels. Further, we identify a much tighter relationship between δ13C and apparent oxygen utilization (AOU) than between δ13C and phosphate. This arises because, in contrast to phosphate, AOU and δ13C are both partly reset when waters are ventilated in the Southern Ocean and underscore that δ13C is a highly robust proxy for past changes in ocean oxygen content and ocean ventilation. Our global preindustrial δ13C climatology is openly accessible and can be used, for example, for improved model evaluation and interpretation of sediment δ13C records.
Keywords: Sørishavet; klimatologi; uorganisk karbon; vannmasser

Spring phenology shapes the spatial foraging behavior of Antarctic petrels - Fauchald, Per; Tarroux, Arnaud; Tveraa, Torkild; Cherel, Yves; Ropert-Coudert, Yan; Kato, Akiko; Love, Oliver P; Varpe, Øystein; Descamps, Sébastien (Marine Ecology Progress Series, 2017)
In polar seas, the seasonal melting of ice triggers the development of an open-waterecosystem characterized by short-lived algal blooms, the grazing and development of zooplank-ton, and the influx of avian and mammalian predators. Spatial heterogeneity in the timing of icemelt generates temporal variability in the development of these events across the habitat, offeringa natural framework to assess how foraging marine predators respond to the spring phenology.We combined 4 yr of tracking data of Antarctic petrels Thalassoica antarcticawith synopticremote-sensing data on sea ice and chlorophyll ato test how the development of melting ice andprimary production drive Antarctic petrel foraging. Cross-correlation analyses of first-passagetime revealed that Antarctic petrels utilized foraging areas with a spatial scale of 300 km. Theseareas changed position or disappeared within 10 to 30 d and showed no spatial consistency amongyears. Generalized additive model (GAM) analyses suggested that the presence of foraging areaswas related to the time since ice melt. Antarctic petrels concentrated their search effort in meltingareas and in areas that had reached an age of 50 to 60 d from the date of ice melt. We found nosignificant relationship between search effort and chlorophyll aconcentration. We suggest thatthese foraging patterns were related to the vertical distribution and profitability of the main prey,the Antarctic krill Euphausia superba. Our study demonstrates that the annual ice melt in theSouthern Ocean shapes the development of a highly patchy and elusive food web, underscoringthe importance of flexible foraging strategies among top predators. KEY WORDS: Area-restricted search · Euphausia superba· Marginal ice zone · Phytoplanktonbiomass · Procellariiformes · Sea ice dynamics · Southern Ocean · Thalassoica antarctica
Keywords: Sørishavet; Weddellhavet; biologi; biomasse; fenologi; fytoplankton; fôring; havis; klima; petreller; sjøis; smelting; økosystemer

Channelized Melting Drives Thinning Under a Rapidly Melting Antarctic Ice Shelf - Gourmelen, Noel; Goldberg, Dan N; Snow, Kate; Henley, Sian F; Bingham, Robert G; Kimura, Satoshi; Hogg, Anna E; Shepherd, Andrew; Mouginot, Jeremie; Lenaerts, Jan T M; Ligtenberg, Stefan R M; van de Berg, Willem Jan (Geophysical Research Letters, 2017)
Ice shelves play a vital role in regulating loss of grounded ice and in supplying freshwater to coastal seas. However, melt variability within ice shelves is poorly constrained and may be instrumental in driving ice shelf imbalance and collapse. High-resolution altimetry measurements from 2010 to 2016 show that Dotson Ice Shelf (DIS), West Antarctica, thins in response to basal melting focused along a single 5 km-wide and 60 km-long channel extending from the ice shelf's grounding zone to its calving front. If focused thinning continues at present rates, the channel will melt through, and the ice shelf collapse, within 40–50 years, almost two centuries before collapse is projected from the average thinning rate. Our findings provide evidence of basal melt-driven sub-ice shelf channel formation and its potential for accelerating the weakening of ice shelves.
Keywords: Sørishavet; glasiologi; havnivå; innlandsis; isbrem; isshelf; smelting

Volcanic passive continental margin beneath Maitri station in central DML, East Antarctica: constraints from crustal shear velocity through receiver function modelling - Gupta, Sandeep; Kanna, Nagaraju; Akilan, A (Polar Research, 2017)
Dronning Maud Land (DML) in East Antarctica is considered to be a key area for the reconstruction of the Gondwana supercontinent. We investigate the crustal shear wave velocity (Vs) model beneath the Maitri station, situated in the central DML of East Antarctica, through receiver function modelling. The analysis shows an average crustal thickness of 38.50 ± 0.5 km and a Vp/Vs ratio of 1.784 ± 0.002. The obtained Vs structure suggests that the topmost ca. 2.5 km of the crust contains ice and sediments with low Vs (1.5–2.0 km/s). This layer is underlain by a thick (ca. 12.5 km) layer of Vs = 2.25–2.6 km/s, suggestive of an extrusive igneous rock (rhyolite) at this depth range. Between 16 and 28 km depth, the Vs increases from 2.9 to 3.4 km/s. In the lower crust, a 7 km thick layer of Vs = 3.9 km/s is followed by 6 km thick underplated layer (Vs = 4.1 km/s) at the crust–mantle boundary. The uppermost mantle Vs is ca. 4.3 km/s. With the observation of underplated material in the lowermost crust, extrusive volcanic rocks in the upper crust, seaward dipping reflectors in the surrounding and a general paucity of seismicity, we believe the crust beneath the Maitri station represents a volcanic passive continental margin. We also believe that after its origin in the Precambrian and during its subsequent evolution it might have been affected by the post-Precambrian tectono-thermal event(s) responsible for the Gondwana supercontinent break-up.
Keywords: Dronning Maud Land; geofysikk; kontinentalmargin; seismologi; tektonikk; vulkaner

Distribution, density and abundance of Antarctic ice seals off Queen Maud Land and the eastern Weddell Sea - Gurarie, Eliezer; Bengtson, John L; Bester, Marthán N; Blix, Arnoldus Schytte; Cameron, Michael; Bornemann, Horst; Nordøy, Erling S; Plötz, Joachim; Steinhage, Daniel; Boveng, Peter (Polar Biology, 2017)
Keywords: Sørishavet; Weddellhavet; marin biologi; observasjoner; pattedyr; seler; sjøpattedyr; zoologi

Microbes influence the biogeochemical and optical properties of maritime Antarctic snow - Hodson, Andrew; Nowak, Aga; Cook, Joseph; Sabacka, Marie; Wharfe, Emma S; Pearce, David Anthony; Convey, Peter; Vieira, Gonçalo (Journal of Geophysical Research: Biogeosciences, 2017)
Snowmelt in the Antarctic Peninsula region has increased significantly in recent decades, leading to greater liquid water availability across a more expansive area. As a consequence, changes in the biological activity within wet Antarctic snow require consideration if we are to better understand terrestrial carbon cycling on Earth's coldest continent. This paper therefore examines the relationship between microbial communities and the chemical and physical environment of wet snow habitats on Livingston Island of the maritime Antarctic. In so doing, we reveal a strong reduction in bacterial diversity and autotrophic biomass within a short (<1 km) distance from the coast. Coastal snowpacks, fertilized by greater amounts of nutrients from rock debris and marine fauna, develop obvious, pigmented snow algal communities that control the absorption of visible light to a far greater extent than with the inland glacial snowpacks. Absorption by carotenoid pigments is most influential at the surface, while chlorophyll is most influential beneath it. The coastal snowpacks also indicate higher concentrations of dissolved inorganic carbon and CO2 in interstitial air, as well as a close relationship between chlorophyll and dissolved organic carbon (DOC). As a consequence, the DOC resource available in coastal snow can support a more diverse bacterial community that includes microorganisms from a range of nearby terrestrial and marine habitats. Therefore, since further expansion of the melt zone will influence glacial snowpacks more than coastal ones, care must be taken when considering the types of communities that may be expected to evolve there.
Keywords: Antarktis; biogeokjemi; mikrobiologi; mikroorganismer; snøalger; snøpakke; snøsmelting

Om C.A. Larsen og starten på pelagisk hvalfangst - Iversen, Ragnar (Skipet, 2017)
Keywords: Sørishavet; historie; hvalfangst

An enigmatic fossil penguin from the Eocene of Antarctica - Jadwiszczaka, Piotr; Mörs, Thomas (Polar Research, 2017)
Tarsometatarsi are key skeletal elements in penguin palaeontology. They constitute, among others, type specimens of all 10 widely accepted species of fossil penguins from the Eocene La Meseta Formation on Seymour Island (Graham Land, Antarctic Peninsula). Here, we report on a recently collected large-sized tarsometatarsus from this formation that represents a new morphotype. We are convinced that the morphotype corresponds to a new species, but the material is too scarce for a taxonomic act. Undoubtedly, the bone discussed here is a valuable addition to our knowledge on diversity of early penguins.
Keywords: Antarktis; fossiler; paleobiologi; paleontologi; pingviner

Oceanographic Controls on the Variability of Ice-Shelf Basal Melting and Circulation of Glacial Meltwater in the Amundsen Sea Embayment, Antarctica - Kimura, Satoshi; Jenkins, Adrian; Regan, Heather; Holland, Paul R; Assmann, Karen M; Whitt, Daniel B; Van Wessem, Melchoir; van de Berg, Willem Jan; Reijmer, Carleen H; Dutrieux, Pierre (Journal of Geophysical Research: Oceans, 2017)
Ice shelves in the Amundsen Sea Embayment have thinned, accelerating the seaward flow of ice sheets upstream over recent decades. This imbalance is caused by an increase in the ocean-driven melting of the ice shelves. Observations and models show that the ocean heat content reaching the ice shelves is sensitive to the depth of thermocline, which separates the cool, fresh surface waters from warm, salty waters. Yet the processes controlling the variability of thermocline depth remain poorly constrained. Here we quantify the oceanic conditions and ocean-driven melting of Cosgrove, Pine Island Glacier (PIG), Thwaites, Crosson, and Dotson ice shelves in the Amundsen Sea Embayment from 1991 to 2014 using a general circulation model. Ice-shelf melting is coupled to variability in the wind field and the sea-ice motions over the continental shelf break and associated onshore advection of warm waters in deep troughs. The layer of warm, salty waters at the calving front of PIG and Thwaites is thicker in austral spring (June–October) than in austral summer (December–March), whereas the seasonal cycle at the calving front of Dotson is reversed. Furthermore, the ocean-driven melting in PIG is enhanced by an asymmetric response to changes in ocean heat transport anomalies at the continental shelf break: melting responds more rapidly to increases in ocean heat transport than to decreases. This asymmetry is caused by the inland deepening of bathymetry and the glacial meltwater circulation around the ice shelf.
Keywords: Amundsenhavet; Sørishavet; batymetri; brehylle; glasiologi; isbrem; ismeltvann; isshelf; klimatologi; oseanografi

Lessons from the Arctic : how Roald Amundsen won the race to the South Pole - Kløver, Geir Olav (Fram Museum, 2017)
Keywords: Antarktis; Belgica ekspedisjon; Sydpolsekspedisjonen; oppdagelsesreiser; polarhistorie

Forskrift om etablering, drift og bruk av jordstasjon for satellitt i Antarktis - Kommunaldepartementet (Lovdata, 2017)
Place: Oslo
Keywords: Dronning Maud Land; jus; kommunikasjon; teknologi

Antarctic ice rises: small in size but big on impact - Matsuoka, Kenichi (Fram forum, 2017)
Ice discharge from the Antarctic Ice Sheet directly impacts global sea level, making ice sheet dynamics a central topic in antarctic research. Glaciologists are studying a poorly understood but potentially important phenomenon that looks like a little hill of ice. They call these hills “ice rises”.
Keywords: Antarktis; glasiologi; havnivåstigning; innlandsis; isbrem; isshelf

Autonomous observing platform CO2 data shed new light on the Southern Ocean carbon cycle - Olsen, Are (Global Biogeochemical Cycles, 2017)
While the number of surface ocean CO2 partial pressure (pCO2) measurements has soared the recent decades, the Southern Ocean remains undersampled. Williams et al. (2017, https://doi.org/10.1002/2016GB005541) now present pCO2 estimates based on data from pH-sensor equipped Bio-Argo floats, which have been measuring in the Southern Ocean since 2014. The authors demonstrate the utility of these data for understanding the carbon cycle in this region, which has a large influence on the distribution of CO2 between the ocean and atmosphere. Biogeochemical sensors deployed on autonomous platforms hold the potential to shape our view of the ocean carbon cycle in the coming decades.
Keywords: Sørishavet; atmosfæren; biogeokjemi; karbon syklus; karbondioksid; kartlegging; klimaendringer; klimatologi; observasjoner

Occurrence and average behavior of pulsating aurora - Partamies, Noora; Whiter, Daniel; Kadokura, Akira; Kauristie, Kirsti; Nesse Tyssøy, Hilde; Massetti, Stefano; Stauning, Peter; Raita, Tero (Journal of Geophysical Research: Space Physics, 2017)
Motivated by recent event studies and modeling efforts on pulsating aurora, which conclude that the precipitation energy during these events is high enough to cause significant chemical changes in the mesosphere, this study looks for the bulk behavior of auroral pulsations. Based on about 400 pulsating aurora events, we outline the typical duration, geomagnetic conditions, and change in the peak emission height for the events. We show that the auroral peak emission height for both green and blue emission decreases by about 8 km at the start of the pulsating aurora interval. This brings the hardest 10% of the electrons down to about 90 km altitude. The median duration of pulsating aurora is about 1.4 h. This value is a conservative estimate since in many cases the end of event is limited by the end of auroral imaging for the night or the aurora drifting out of the camera field of view. The longest durations of auroral pulsations are observed during events which start within the substorm recovery phases. As a result, the geomagnetic indices are not able to describe pulsating aurora. Simultaneous Antarctic auroral images were found for 10 pulsating aurora events. In eight cases auroral pulsations were seen in the southern hemispheric data as well, suggesting an equatorial precipitation source and a frequent interhemispheric occurrence. The long lifetimes of pulsating aurora, their interhemispheric occurrence, and the relatively high-precipitation energies make this type of aurora an effective energy deposition process which is easy to identify from the ground-based image data.
Keywords: Antarktis; astronomi; atmosfæren; geofysikk; geomagnetiske stormer; mesosfæren; meteorologi; polarlys

Observation-Based Trends of the Southern Ocean Carbon Sink - Ritter, Rebecca; Landschützer, Peter; Gruber, Nicolas; Fay, Amanda R; Iida, Yosuke; Jones, Stephen Daniel; Nakaoka, Shin-ichiro; Park, Geun-Ha; Peylin, Philippe; Rödenbeck, Christian; Rodgers, Keith B; Shutler, Jamie D; et al. (Geophysical Research Letters, 2017)
The Southern Ocean (SO) carbon sink has strengthened substantially since the year 2000, following a decade of a weakening trend. However, the surface ocean pCO2 data underlying this trend reversal are sparse, requiring a substantial amount of extrapolation to map the data. Here we use nine different pCO2 mapping products to investigate the SO trends and their sensitivity to the mapping procedure. We find a robust temporal coherence for the entire SO, with eight of the nine products agreeing on the sign of the decadal trends, that is, a weakening CO2 sink trend in the 1990s (on average 0.22 ± 0.24 Pg C yr−1 decade−1), and a strengthening sink trend during the 2000s (−0.35 ± 0.23 Pg C yr−1 decade−1). Spatially, the multiproduct mean reveals rather uniform trends, but the confidence is limited, given the small number of statistically significant trends from the individual products, particularly during the data-sparse 1990–1999 period.
Keywords: Sørishavet; biogeokjemi; global oppvarming; karbondioksid; klimaendringer; klimatologi; meteorologi

Molluscan assemblages associated with Gigartina beds in the Strait of Magellan and the South Shetland Islands (Antarctica): a comparison of composition and abundance - Rosenfeld, Sebastián; Aldea, Cristian; Ojeda, Jaime; Marambio, Johanna; Hüne, Mathias; Troncoso, Jesús S; Mansilla, Andrés (Polar Research, 2017)
In this paper we evaluated the composition and abundance of molluscs associated with beds of the red algae Gigartina, located in the South Shetland Islands (Antarctic Peninsula) and the Strait of Magellan (southern Chile). During the summer season of 2013, samples were obtained by scuba diving using a 0.25 m2 quadrat, arranged randomly within the bed. We extracted a total of 15 quadrats per sampling site. For Antarctic Peninsula beds the most abundant species were the bivalve Lissarca miliaris (233 individuals) and the gastropod Laevilacunaria antarctica (94 individuals), while for Strait of Magellan beds the most abundant species was the polyplacophoran Callochiton puniceus (36 individuals). Comparative analysis between the two molluscan assemblages showed significant differences in the faunal composition between the Antarctic Peninsula and Strait of Magellan (f = 64.474; p = 0.0001). Therefore, molluscs reported in both areas are characteristic of their respective biogeographic area. Finally, Gigartina species play an important role in the formation of patterns of abundance and diversity of the communities associated with them.
Keywords: Sørishavet; alger; biodiversitet; biogeokjemi; bløtdyr; havbunnen; muslinger; snegler

Seasonal cycle of hydrography on the eastern shelf of the Filchner Trough, Weddell Sea, Antarctica - Ryan, Svenja; Hattermann, Tore; Darelius, Elin Maria K; Schröder, Michael (Journal of Geophysical Research: Oceans, 2017)
Keywords: Sørishavet; Weddellhavet; hydrografi; isshelf; kontinentalsokkel; kontinentalsokler

Potential chemical defenses of Antarctic benthic organisms against marine bacteria - Sacristán-Soriano, Oriol; Angulo-Preckler, Carlos; Vázquez, Jennifer; Avila, Conxita (Polar Research, 2017)
The continental shelf of Antarctica harbours rich suspension-feeding macroinvertebrate communities that are continuously exposed to large populations of free-living microbes. To avoid settlement or fouling by undesirable microorganisms that could cause infection or collapse filter-feeding systems, these macroinvertebrates might regulate the epibiotic microbial mat through chemical interactions. In Antarctic chemical ecology, the antibacterial roles of natural products remain mostly unknown. A necessary first step is to identify organisms that produce compounds with potential ecological relevance. For that reason, we tested the crude organic extracts of 116 taxa of Antarctic benthic organisms for antibacterial activity against a panel of seven strains of marine bacteria. Nine out of 11 phyla tested had antibacterial properties. However, inhibitory activity was quite selective and species-specific. These patterns suggest that Antarctic benthic organisms may produce diverse bioactive metabolites with different antibacterial activities or, alternatively, those contrasting profiles may be shaped by environmental and biological interactions acting at a small spatial scale. The reasons of such selectivity remain to be further investigated and may contribute to the identification of bioactive compounds with pharmaceutical applications.
Keywords: Sørishavet; alger; biodiversitet; biologi; fauna; kjemisk; kontinentalsokkel; makrovirvelløse dyr; mikrober; mikroorganismer; økologi

Benchmarks: February 5, 1931 and February 20, 1935: Antarctic firsts for women - Zalzal, Kate S (Earth, 2017)
Publisher: American Geological Institute Place: Alexandria
Keywords: Antarktis; Nordmenn; ekspedisjoner; kvinner; oppdagelsesreiser

Geomorphic and shallow-acoustic investigation of an Antarctic Peninsula fjord system using high-resolution ROV and shipboard geophysical observations: Ice dynamics and behaviour since the Last Glacial Maximum - García, Marga; Dowdeswell, J.A.; Noormets, R.; Hogan, K.A.; Evans, J.; Ó Cofaigh, C.; Larter, R.D. (Quaternary Science Reviews, 2016)
Detailed bathymetric and sub-bottom acoustic observations in Bourgeois Fjord (Marguerite Bay, Antarctic Peninsula) provide evidence on sedimentary processes and glacier dynamics during the last glacial cycle. Submarine landforms observed in the 50 km-long fjord, from the margins of modern tidewater glaciers to the now ice-distal Marguerite Bay, are described and interpreted. The landforms are grouped into four morpho-sedimentary systems: (i) glacial advance and full-glacial; (ii) subglacial and ice-marginal meltwater; (iii) glacial retreat and neoglaciation; and (iv) Holocene mass-wasting. These morpho-sedimentary systems have been integrated with morphological studies of the Marguerite Bay continental shelf and analysed in terms of the specific sedimentary processes and/or stages of the glacial cycle. They demonstrate the action of an ice-sheet outlet glacier that produced drumlins and crag-and-tail features in the main and outer fjord. Meltwater processes eroded bedrock channels and ponds infilled by fine-grained sediments. Following the last deglaciation of the fjord at about 9000 yr BP, subsequent Holocene neoglacial activity involved minor readvances of a tidewater glacier terminus in Blind Bay. Recent stillstands and/or minor readvances are inferred from the presence of a major transverse moraine that indicates grounded ice stabilization, probably during the Little Ice Age, and a series of smaller landforms that reveal intermittent minor readvances. Mass-wasting processes also affected the walls of the fjord and produced scars and fan-shaped deposits during the Holocene. Glacier-terminus changes during the last six decades, derived from satellite images and aerial photographs, reveal variable behaviour of adjacent tidewater glaciers. The smaller glaciers show the most marked recent retreat, influenced by regional physiography and catchment-area size.
Keywords: Antarctic Peninsula; Antarktis; Fjord systems; Geomorphology; Glacial sedimentary processes; Last Glacial Maximum; ROV-Derived bathymetry; Sørishavet; batymetri; geomorfologi

Naturen 1916 Roald Amundsens sydpolsfærd og dens videnskabelige resultater (Naturen, 2016)
Efterat kaptein James Ross i 1841 hadde opdaget det sydpolare eller antarktiske fastland og den store isbarriere under sin seilas i det hav som efter ham har faat navn av Ross-Havet, blev den øvrige del av dette fastland fremdeles ukjendt indtil 1898. Fra dette aar av har en række ekspeditioner med større og mindre held forsøkt at finde beliggenheten av det antarktiske fastlands kyster, og av disse har nogen opnaadd at trænge ind i det indre, endog like til sydpolen. Imidlertid er der endnu store strækninger hvor havisen har stængt seilasen og gjort det umulig at naa ind til det faste land.
Keywords: Antarktis; Roald Amundsen; Sydpolsekspedisjonen; historie; oppdagelsesreiser; vitenskap

Den nyttige taperen - Scotts plass i norske nyhetsmediers fortellinger om erobringen av Sørpolen - Alnæs, Jørgen; Simonsen, Anne Hege (Norsk medietidsskrift, 2016)
Hundre år etter at Roald Amundsen nådde Sørpolen, ble han behørig feiret både av det offisielle Norge og av norske nyhetsmedier. Robert F. Scott, som nådde polen om lag en måned seinere, var en del av omtalen. Han fikk rollen som motstander og taper, og slik ble han en nyttig brikke når forestillingene om Norge som en rettmessig stormakt i Antarktis skulle etableres. Det er imidlertid mange måter å framstille Scott på, og norske aviser har ikke alltid hatt det samme synet på ham.
Publisher: Universitetsforlaget
Keywords: Antarktis; Roald Amundsen; Robert Falcon Scott; Sydpolsekspedisjonen; ekspedisjoner; historie; kappløpet; mediefortelling; oppdagelsesreiser

Transpression and tectonic exhumation in the Heimefrontfjella, western orogenic front of the East African/Antarctic Orogen, revealed by quartz textures of high strain domains - Bauer, Wilfried; Siemes, Heinrich; Spaeth, Gerhard; Jacobs, Joachim (Polar Research, 2016)
The metamorphic basement of the Heimefrontfjella in western Dronning Maud Land (Antarctica) forms the western margin of the major ca. 500 million year old East African/East Antarctic Orogen that resulted from the collision of East Antarctica and greater India with the African cratons. The boundary between the tectonothermally overprinted part of the orogen and its north-western foreland is marked by the subvertical Heimefront Shear Zone. North-west of the Heimefront Shear Zone, numerous low-angle dipping ductile thrust zones cut through the Mesoproterozoic basement. Petrographic studies, optical quartz c-axis analyses and x-ray texture goniometry of quartz-rich mylonites were used to reveal the conditions that prevailed during the deformation. Mineral assemblages in thrust mylonites show that they were formed under greenschist-facies conditions. Quartz microstructures are characteristic of the subgrain rotation regime and oblique quartz lattice preferred orientations are typical of simple shear-dominated deformation. In contrast, in the Heimefront Shear Zone, quartz textures indicate mainly flattening strain with a minor dextral rotational component. These quartz microstructures and lattice preferred orientations show signs of post-tectonic annealing following the tectonic exhumation. The spatial relation between the sub-vertical Heimefront Shear Zone and the low-angle thrusts can be explained as being the result of strain partitioning during transpressive deformation. The pure-shear component with a weak dextral strike-slip was accommodated by the Heimefront Shear Zone, whereas the north–north-west directed thrusts accommodate the simple shear component with a tectonic transport towards the foreland of the orogen. Keywords: Dronning Maud Land; quartz microfabrics; X-ray texture goniometry; shear zones; mylonites.
Keywords: Dronning Maud Land; geologi; mylonitter; petrografi; tektonikk

On Roald Amundsen’s scientific achievements - Blix, Arnoldus Schytte (Polar Research, 2016)
This paper describes the significant direct and indirect contributions to science made by the Norwegian polar explorer Roald Amundsen in the period 1897–1924. It documents that his expeditions through the North-west Passage (1903–06) with Gjøa, to the South Pole (1910–12) with Fram and through the North-east Passage (1918–1920) and the Chukchi and East Siberian seas (1921–25) with Maud yielded vast amounts of published scientific material on meteorology, terrestrial magnetism, geology, palaeontology, oceanography, ethnography, zoology and botany, which, though celebrated at the time, have since received scant recognition in more recent assessments of Amundsen’s achievements. Keywords: Fridtjof Nansen; polar exploration; South Pole; North-west Passage; North-east Passage; H.U. Sverdrup.
Keywords: Antarktis; Roald Amundsen; Sydpolsekspedisjonen; ekspedisjoner; forskning; geologi; meteorologi; oseanografi

Algal biomass and pigments along a latitudinal gradient in Victoria Land lakes, East Antarctica - Borghini, Francesca; Colacevich, Andrea; Caruso, Tancredi; Bargagli, Roberto (Polar Research, 2016)
It is generally accepted that Antarctic terrestrial diversity decreases as latitude increases, but latitudinal patterns of several organisms are not always as clear as expected. The Victoria Land region is rich in lakes and ponds and spans 8 degrees of latitude that encompasses gradients in factors such as solar radiation, temperature, ice cover and day length. An understanding of the links between latitudinally driven environmental and biodiversity changes is essential to the understanding of the ecology and evolution of Antarctic biota and the formulation of hypotheses about likely future changes in biodiversity. As several studies have demonstrated that photosynthetic pigments are an excellent, although underused, tool for the study of lacustrine algal communities, the aim of the present study was to investigate variations in algal biomass and biodiversity across the latitudinal gradient of Victoria Land using sedimentary pigments. We test the hypothesis that the biodiversity of freshwater environments decreases as latitude increases. On the basis of our results, we propose using the number of sedimentary pigments as a proxy for algal diversity and the sum of chlorophyll a and bacteriochlorophyll a with their degradation derivatives as an index of biomass. Overall, our data show that biomass and diversity decrease as latitude increases but local environmental conditions, in particular, natural levels of eutrophy, can affect both productivity and diversity. Keywords: Biodiversity; photosynthetic pigments; proxy; continental Antarctica; sediments; biogeography.
Keywords: Antarktis; alger; biodiversitet; biogeografi; biomasse; ferskvann; fotosyntese; innsjø; sedimenter; økologi

A constitutive framework for predicting weakening and reduced buttressing of ice shelves based on observations of the progressive deterioration of the remnant Larsen B Ice Shelf - Borstad, Chris; Khazendar, Ala; Scheuchl, Bernd; Morlighem, Mathieu; Larour, Eric; Rignot, Eric (Geophysical Research Letters, 2016)
The increasing contribution of the Antarctic Ice Sheet to sea level rise is linked to reductions in ice shelf buttressing, driven in large part by basal melting of ice shelves. These ocean-driven buttressing losses are being compounded as ice shelves weaken and fracture. To date, model projections of ice sheet evolution have not accounted for weakening ice shelves. Here we present the first constitutive framework for ice deformation that explicitly includes mechanical weakening, based on observations of the progressive degradation of the remnant Larsen B Ice Shelf from 2000 to 2015. We implement this framework in an ice sheet model and are able to reproduce most of the observed weakening of the ice shelf. In addition to predicting ice shelf weakening and reduced buttressing, this new framework opens the door for improved understanding and predictions of iceberg calving, meltwater routing and hydrofracture, and ice shelf collapse.
Keywords: Antarktis; glasiologi; global oppvarming; havnivåstigning; innlandsis; isbrem; isshelf; smelting

Winter distribution and size structure of Antarctic krill Euphausia superba populations in-shore along the West Antarctic Peninsula - Cleary, Alison C; Durbin, Edward G; Casas, Maria C; Zhou, Meng (Marine Ecology Progress Series, 2016)
Antarctic krill Euphausia superba are a key component of food webs in the maritime West Antarctic Peninsula, and their life history is tied to the seasonal cycles of sea ice and primary production in the region. Previous work has shown a general in-shore migration of krill in winter in this region; however, the very near-shore has not often been sampled as part of these surveys. We investigated distribution, abundance, and size structure of krill in 3 fjordic bays along the peninsula, and in the adjacent Gerlache Strait area using vertically stratified MOCNESS net tows and ADCP acoustic biomass estimates. Krill abundance was high within bays, with net estimated densities exceeding 60 krill m-3, while acoustic estimates were an order of magnitude higher. Krill within bays were larger than krill in the Gerlache Strait. Within bays, krill aggregations were observed near the seafloor during the day with aggregations extending to the sediment interface, and exhibited diel vertical migration higher into the water column at night. We suggest these high winter krill abundances within fjords are indicative of an active seasonal migration by krill in the peninsula region. Potential drivers for such a migration include reduced advective losses and costs, and availability of sediment food resources within fjords. Seasonally near-shore krill may also affect stock and recruitment assessments and may have implications for managing the krill fishery in this area. KEYWORDS: Euphausiid · Abundance · Diel vertical migration · DVM · WAP · Fjord.
Keywords: Sørishavet; biomasse; hydrografi; krill; marin biologi; oseanografi; zooplankton

Observed vulnerability of Filchner-Ronne Ice Shelf to wind-driven inflow of warm deep water - Darelius, Elin Maria K; Fer, Ilker; Nicholls, Keith William (Nature Communications, 2016)
Keywords: Antarktis; Weddellhavet; isshelf; oseanografi; sjøvann

Tourism and Arctic Observation Systems: exploring the relationships - de la Barre, Suzanne; Maher, Patrick; Dawson, Jackie; Hillmer-Pegram, Kevin; Huijbens, Edward; Lamers, Machiel; Liggett, Daniela; Müller, Dieter; Pashkevich, Albina; Stewart, Emma (Polar Research, 2016)
The Arctic is affected by global environmental change and also by diverse interests from many economic sectors and industries. Over the last decade, various actors have attempted to explore the options for setting up integrated and comprehensive trans-boundary systems for monitoring and observing these impacts. These Arctic Observation Systems (AOS) contribute to the planning, implementation, monitoring and evaluation of environmental change and responsible social and economic development in the Arctic. The aim of this article is to identify the two-way relationship between AOS and tourism. On the one hand, tourism activities account for diverse changes across a broad spectrum of impact fields. On the other hand, due to its multiple and diverse agents and far-reaching activities, tourism is also well-positioned to collect observational data and participate as an actor in monitoring activities. To accomplish our goals, we provide an inventory of tourism-embedded issues and concerns of interest to AOS from a range of destinations in the circumpolar Arctic region, including Alaska, Arctic Canada, Iceland, Svalbard, the mainland European Arctic and Russia. The article also draws comparisons with the situation in Antarctica. On the basis of a collective analysis provided by members of the International Polar Tourism Research Network from across the polar regions, we conclude that the potential role for tourism in the development and implementation of AOS is significant and has been overlooked. Keywords: Arctic; Antarctic; citizen science; observation systems; tourism; IPTRN
Keywords: Antarktis; klimaendringer; miljøendringer; polarområdene; turisme

Gastrointestinal helminths of Adélie penguins (Pygoscelis adeliae) from Antarctica - Diaz, Julia Inés; Fusaro, Bruno; Longarzo, Lucrecia; Coria, Néstor Rubén; Vidal, Virginia; D'Amico, Verónica; Barbosa, Andrés (Polar Research, 2016)
Knowledge about parasitic organisms in Antarctica is scarce and fragmentary. The study reported here adds to the knowledge of gastrointestinal parasites of the Adélie penguin (Pygoscelis adeliae) (Sphenisciformes), from 25 de Mayo/King George Island (South Shetlands), Bahia Esperanza (Hope Bay) and Avian Island (Antarctica). Thirty-five freshly dead specimens (20 chicks and 15 adults) were collected from December 2007 to December 2014 and examined for internal macroparasites. Three adult parasite species were found: one Cestoda, Parorchites zederi, and two Nematoda, Stegophorus macronectes and Tetrameres sp. Immature Tetrabothrius sp. were found in hosts from Avian Island. Helminth communities are known to be related to host feeding behaviours. Low parasite richness observed in Adélie penguins could be related to the stenophagic and pelagic diet of this host species, which feeds almost exclusively on krill. Keywords: Parorchites zederi; Stegophorus macronectes; Tetrameres sp.; parasites; ecosystem health.
Keywords: Antarktis; krill; parasitter; pingviner; plankton; zoologi; økosystemer

Re-assessment of recent (2008 - 2013) surface mass balance over Dome Argus, Antarctica - Ding, Minghu; Xiao, Cunde; Yang, Yuande; Wang, Yetang; Li, Chuanjin; Yuan, Naiming; Shi, Guitao; Sun, Weijun; Ming, Jing (Polar Research, 2016)
At Dome Argus, East Antarctica, the surface mass balance (SMB) from 2008 to 2013 was evaluated using 49 stakes installed across a 30×30 km area. Spatial analysis showed that at least 12 and 20 stakes are needed to obtain reliable estimates of SMB at local scales (a few hundred square metres) and regional scales (tens of square kilometres), respectively. The estimated annual mean SMB was 22.9±5.9 kg m−2 yr−1, including a net loss by sublimation of −2.22±0.02 kg m−2 yr−1 and a mass gain by deposition of 1.37±0.01 kg m−2 yr−1. Therefore, ca. 14.3% of precipitation was modified after deposition, which should be considered when interpreting snow or ice core records produced by future drilling projects. The surface snow density and SMB in the western portion of Dome Argus are higher than in other areas, and these differences are likely related to the katabatic wind, which is strengthened by topography in this sector. A new digital elevation model (DEM) of Dome Argus was generated, confirming that both peaks of the dome can be considered as the summit of the East Antarctic Ice Sheet. Findings from this study should be valuable for validating SMB estimates obtained from regional climate models and DEMs established using remote-sensing data. Keywords: Snow accumulation; Kunlun Station; CHINARE; digital elevation model; deep ice core sites; East Antarctic Ice Sheet.
Keywords: Antarktis; glasiologi; innlandsis; meteorologi; snø akkumulasjon; topografi

Observations of energetic turbulence on the Weddell Sea continental slope - Fer, Ilker; Darelius, Elin; Daae, Kjersti B (Geophysical Research Letters, 2016)
Turbulence profile measurements made on the upper continental slope and shelf of the southeastern Weddell Sea reveal striking contrasts in dissipation and mixing rates between the two sites. The mean profiles of dissipation rates from the upper slope are 1–2 orders of magnitude greater than the profiles collected over the shelf in the entire water column. The difference increases toward the bottom where the dissipation rate of turbulent kinetic energy and the vertical eddy diffusivity on the slope exceed 10−7 W kg−1 and 10−2 m2 s−1, respectively. Elevated levels of turbulence on the slope are concentrated within a 100 m thick bottom layer, which is absent on the shelf. The upper slope is characterized by near-critical slopes and is in close proximity to the critical latitude for semidiurnal internal tides. Our observations suggest that the upper continental slope of the southern Weddell Sea is a generation site of semidiurnal internal tide, which is trapped along the slope along the critical latitude, and dissipates its energy in a 100 m thick layer near the bottom and within 10 km across the slope.
Keywords: Sørishavet; Weddellhavet; geofysikk; havbunnen; havstrømmer; hydrografi; kontinentalsokkel

Tilt signals at Mount Melbourne, Antarctica: evidence of a shallow volcanic source - Gambino, Salvatore; Aloisi, Marco; Falzone, Giuseppe; Ferro, Angelo (Polar Research, 2016)
Mount Melbourne (74°21′ S, 164°43′ E) is a quiescent volcano located in northern Victoria Land, Antarctica. Tilt signals have been recorded on Mount Melbourne since early 1989 by a permanent shallow borehole tiltmeter network comprising five stations. An overall picture of tilt, air and permafrost temperatures over 15 years of continuous recording data is reported. We focused our observations on long-term tilt trends that at the end of 1997 showed coherent changes at the three highest altitude stations, suggesting the presence of a ground deformation source whose effects are restricted to the summit area of Mount Melbourne. We inverted these data using a finite spherical body source, thereby obtaining a shallow deflation volume source located under the summit area. The ground deformation observed corroborates the hypothesis that the volcanic edifice of Mount Melbourne is active and should be monitored multidisciplinarily.Keywords: Tilt monitoring; volcanic dynamics; physics volcanology; ground deformation; Victoria Land.
Keywords: Antarktis; geofysikk; tektonikk; vulkaner

Parasites of the Antarctic toothfish (Dissostichus mawsoni Norman, 1937) (Perciformes, Nototheniidae) in the Pacific sector of the Antarctic - Gordeev, Ilya I; Sokolov, Sergey G (Polar Research, 2016)
The Antarctic toothfish (Dissostichus mawsoni Norman, 1937) is one of the main target species of commercial fisheries in the Antarctic. It is an endemic and is found along the shelf of Antarctica, as well as on the slopes of seamounts, underwater elevations and islands in the sub-Antarctic. It feeds on a variety of fish and cephalopods and can be an intermediate/paratenic host of some helminthes, whose final hosts are whales, seals, large rays and sharks. This article presents new data on toothfish infection in the Pacific sector of the Antarctic. Specimens were examined during commercial longline fishing in the Ross Sea and the Amundsen Sea in January–February 2013. Fourteen species of parasites were found using standard parasitological methods and genetic analysis. Keywords: Toothfish; parasites; Antarctic fisheries; CCAMLR; infection; Southern Ocean.
Keywords: Rosshavet; Sørishavet; fiskeri; infeksjon; parasitter; parasittologi

In memory of Torgny Vinje - a genuine polar scientist - Isaksson, Elisabeth; Gerland, Sebastian; Divine, Dmitry (Polar Research, 2016)
Keywords: Antarktis; Norsk Polarinstitutt; biografi; forskning; geofysikk; geologi; glasiologi; meteorologi; polarområdene

Regurgitation of the koilin layer in chinstrap penguins (Pygoscelis antarcticus) and its association with gastric parasites - Kim, Han-Kyu; Choi, Chang-Yong; Jeong, Min-Su; Kang, Hwa-Yeon; Lee, Woo-Shin (Polar Research, 2016)
The koilin membrane, formed by the secretions of the ventricular and pyloric glands, functions as a protective layer in the gizzards of most bird species. However, the ecological functions of koilin have never been studied in free-ranging penguins. During the two austral summers from 2012 to 2014, we observed the regurgitated koilins of chinstrap penguins (Pygoscelis antarcticus) at Narębski Point on King George Island, South Shetland Islands, and we detected a significant difference in the daily accumulation of regurgitated koilins between the pre-hatching and post-hatching periods in the rookery. We also found 233 gastrointestinal parasites, all Stegophorus macronectes (Nematoda, Acuariidae), from 26 out of 45 koilins freshly regurgitated by chinstrap penguins. We suggest that the regurgitation of koilins may benefit adult chinstrap penguins in the wild by reducing parasitic loads when they fast during incubation; it may also help decrease the risk of parasite transmission to chicks. Our results present the first observations of regurgitated koilins among breeding chinstrap penguins. How koilin regurgitation functions in penguins requires further study. Among the gentoo penguins (P. papua) co-occurring at the study site, we observed no regurgitated koilin layers. Keywords: Cuticula gastris; host-parasite interaction; nematodes; parasitic load; regurgitation; Stegophorus macronectes.
Keywords: Antarktis; biologi; gastrointestinale parasitter; ornitologi; pingviner; zoologi

Ocean mixing beneath Pine Island Glacier ice shelf, West Antarctica - Kimura, Satoshi; Jenkins, Adrian; Dutrieux, Pierre; Forryan, Alexander; Naveira Garabato, Alberto C; Firing, Yvonne (Journal of Geophysical Research: Oceans, 2016)
Ice shelves around Antarctica are vulnerable to an increase in ocean-driven melting, with the melt rate depending on ocean temperature and the strength of flow inside the ice-shelf cavities. We present measurements of velocity, temperature, salinity, turbulent kinetic energy dissipation rate, and thermal variance dissipation rate beneath Pine Island Glacier ice shelf, West Antarctica. These measurements were obtained by CTD, ADCP, and turbulence sensors mounted on an Autonomous Underwater Vehicle (AUV). The highest turbulent kinetic energy dissipation rate is found near the grounding line. The thermal variance dissipation rate increases closer to the ice-shelf base, with a maximum value found ∼0.5 m away from the ice. The measurements of turbulent kinetic energy dissipation rate near the ice are used to estimate basal melting of the ice shelf. The dissipation-rate-based melt rate estimates is sensitive to the stability correction parameter in the linear approximation of universal function of the Monin-Obukhov similarity theory for stratified boundary layers. We argue that our estimates of basal melting from dissipation rates are within a range of previous estimates of basal melting.
Keywords: Sørishavet; batymetri; brehylle; isbrem; isshelf; klimatologi; målinger; oseanografi; smeltevann; vannmasser

The impact of sunlight on high-latitude equivalent currents - Laundal, Karl M; Gjerloev, Jesper; Østgaard, Nikolai; Reistad, Jone Peter; Haaland, Stein; Snekvik, Kristian; Tenfjord, Paul; Ohtani, Shin-ichi; Milan, Steve (Journal of Geophysical Research: Space Physics, 2016)
Ground magnetic field measurements can be mathematically related to an overhead ionospheric equivalent current. In this study we look in detail at how the global equivalent current, calculated using more than 30 years of SuperMAG magnetometer data, changes with sunlight conditions. The calculations are done using spherical harmonic analysis in quasi-dipole coordinates, a technique which leads to improved accuracy compared to previous studies. Sorting the data according to the location of the sunlight terminator and orientation of the interplanetary magnetic field (IMF), we find that the equivalent current resembles ionospheric convection patterns on the sunlit side of the terminator but not on the dark side. On the dark side, with southward IMF, the current is strongly dominated by a dawn cell and the current across the polar cap has a strong dawnward component. The contrast between the sunlit and dark side increases with increasing values of the F10.7 index, showing that increasing solar EUV flux changes not only the magnitude but also the morphology of the equivalent current system. The results are consistent with a recent study showing that Birkeland currents indirectly determine the equivalent current in darkness and that Hall currents dominate in sunlight. This has implication for the interpretation of ground magnetic field measurements and suggests that the magnetic disturbances at conjugate points will be asymmetrical when the solar illumination is different.
Keywords: Antarktis; geomagnetiske stormer; ionosfæren; ionosfæriske strømmer; polarlys; polarområdene; sollys; solvind

The seasonal evolution of shelf water masses around Bouvetøya, a sub-Antarctic island in the mid-Atlantic sector of the Southern Ocean, determined from an instrumented southern elephant seal - Lowther, Andrew D.; Lydersen, Christian; Kovacs, Kit M. (Polar Research, 2016)
Our study makes use of a fortuitous oceanographic data set collected around the remote sub-Antarctic island of Bouvetøya by a conductivity–temperature–depth recorder (CTD) integrated with a satellite-relayed data logger deployed on an adult female southern elephant seal (Mirounga leonina) to describe the seasonal evolution of the western shelf waters. The instrumented seal remained in waters over the shelf for 259 days, collecting an average of 2.6 (±0.06) CTD profiles per day, providing hydrographic data encompassing the late austral summer and the entire winter. These data document the thermal stratification of the upper water layer due to summer surface heating of the previous year's Antarctic Surface Water, giving way to a cold subsurface layer at about 100 m as the austral winter progressed, with a concomitant increase in salinity of the upper layer. Upper Circumpolar Deep Water was detected at a depth of approximately 200 m along the western shelf of Bouvetøya throughout the year. These oceanographic data represent the only seasonal time series for this region and the second such animal–instrument oceanographic time series in the sub-Antarctic domain of the Southern Ocean.
Publisher: Routledge
Keywords: AABW; Bouvetøya; biotelemetri; hydrografi; marin biologi; oseanografi; seler

Adjustment of pigment composition in Desmarestia (Desmarestiaceae) species along a sub-Antarctic to Antarctic latitudinal gradient - Mansilla, Andrés; Méndez, Fabio; Murcia, Silvia; Rodriguez, Juan Pablo; Marambio, Johanna; Rosenfeld, Sebastián; Yokoya, Nair; Bischof, Kai (Polar Research, 2016)
Photosynthesis at high latitudes demands efficient strategies of light utilization to maintain algal fitness and performance. The fitness, and physiological adaptation, of a plant or algae species depends in part on the abundance and efficiency of the pigments it can produce to utilize the light resource from its environment. We quantified pigment composition and concentration in six species of the brown macroalgal genus Desmarestia, collected from sub-Antarctic sites (Strait of Magellan, Beagle Channel–Cape Horn Province) and sites on the Antarctic Peninsula and adjacent islands. Sub-Antarctic Desmarestia species exhibited lower concentrations of chlorophyll a, chlorophyll c and fucoxanthin than endemic Antarctic species. Antarctic samples of D. menziesii and D. antarctica collected along a decreasing latitudinal gradient showed spatial and interspecific differences in light-harvesting pigment composition. Our results suggest distinct physiological adjustments in Desmarestia species in response to heterogeneous abiotic environmental conditions. The marine sub-Antarctic and Antarctic ecosystems are characterized by harsh environments (e.g., extreme irradiance, photoperiod, temperature, salinity) to which the physiology of macroalgal species must adapt. Keywords: Macroalgae; Phaeophyceae; photosynthesis; physiology; environmental heterogeneity; Chile.
Keywords: Antarktis; alger; fotosyntese; fysiologi; planter

Can reducing the incoming energy flux over the Southern Ocean in a CGCM improve its simulation of tropical climate? - Mechoso, Carlos R; Losada, Teresa; Koseki, Shunya; Mohino-Harris, Elsa; Keenlyside, Noel; Castaño-Tierno, Antonio; Myers, Timothy A; Rodriguez-Fonseca, Belen; Toniazzo, Thomas (Geophysical Research Letters, 2016)
Atmosphere-ocean general circulation models (CGCMs) show important systematic errors. Simulated precipitation in the tropics is generally overestimated over the oceans south of the equator, and stratocumulus (SCu) clouds are underestimated above too warm sea surface temperatures (SSTs). In the extratropics, SSTs are also too warm over the Southern Ocean. We argue that ameliorating these extratropical errors in a CGCM can result in an improved model's performance in the tropics depending upon the success in simulating the sensitivity of SCu to underlying SST. Our arguments are supported by the very different response obtained with two CGCMs to an idealized reduction of solar radiation flux incident at the top of the atmosphere over the Southern Ocean. It is shown that local perturbation impacts are very similar in the two models but that SST reductions in the SCu regions of the southern subtropics are stronger in the model with the stronger SCu-SST feedbacks.

Troll green station: integration of a solar powered fuel saver at Troll Station, Antarctica - Merlet, Stanislas (Multiconsult, 2016)
Keywords: Dronning Maud Land; bygninger; energi

Local controls on sediment accumulation and distribution in a fjord in the West Antarctic Peninsula: implications for palaeoenvironmental interpretations - Munoz, Yuribia P.; Wellner, Julia S. (Polar Research, 2016)
We analyse surface sediment and its distribution in Flandres Bay, West Antarctic Peninsula, in order to understand modern day sediment dispersal patterns in a fjord with retreating, tidewater glaciers. The surface sediment descriptions of 41 cores are included in this study. The sediment facies described include muddy diatomaceous ooze, diatomaceous mud, pebbly mud, sandy mud and mud, with scattered pebbles present in most samples. In contrast to a traditional conceptual model of glacial sediment distribution in fjords, grain size in Flandres Bay generally coarsens from the inner to outer bay. The smallest grain size sediments were found in the bay head and are interpreted as fine-grained deposits resulting from meltwater plumes and sediment gravity flows occurring close to the glacier front. The middle of the bay is characterized by a high silt percentage, which correlates to diatom-rich sediments. Sediments in the outer bay have a high component of coarse material, which is interpreted as being the result of winnowing from currents moving from the Bellingshausen Sea into the Gerlache Strait. Palaeoenvironmental reconstructions of glacial environments often use grain size as an indicator of proximity to the ice margin. After a detailed analysis of a large number of cores collected in the study area, our findings highlight the variability in sedimentation patterns within a fjord and provide a valuable evidence of the complexity that may occur in the sedimentary record. Keywords: Flandres Bay; Antarctic Peninsula; sediment distribution; grain size.
Keywords: Antarktis; havbunnen; isbreer; miljøvitenskap; sedimenter; sedimentologi; topografi

Evaluating CMIP5 ocean biogeochemistry and Southern Ocean carbon uptake using atmospheric potential oxygen: Present-day performance and future projection - Nevison, Cynthia; Manizza, Manfredi; Keeling, Ralph; Stephens, Britton; Bent, Jonathan; Dunne, John P; Ilyina, Tatiana; Long, Matthew; Resplandy, Laure; Tjiputra, Jerry; Yukimoto, Seiji (Geophysical Research Letters, 2016)
Observed seasonal cycles in atmospheric potential oxygen (APO ~ O2 + 1.1 CO2) were used to evaluate eight ocean biogeochemistry models from the Coupled Model Intercomparison Project (CMIP5). Model APO seasonal cycles were computed from the CMIP5 air-sea O2 and CO2 fluxes and compared to observations at three Southern Hemisphere monitoring sites. Four of the models captured either the observed APO seasonal amplitude or phasing relatively well, while the other four did not. Many models had an unrealistic seasonal phasing or amplitude of the CO2 flux, which in turn influenced APO. By 2100 under RCP8.5, the models projected little change in the O2 component of APO but large changes in the seasonality of the CO2 component associated with ocean acidification. The models with poorer performance on present-day APO tended to project larger net carbon uptake in the Southern Ocean, both today and in 2100.
Keywords: Sørishavet; atmosfæren; biogeokjemi; karbon syklus; karbondioksid; klimatologi; meteorologi; oseanografi

Magnetotelluric investigation of the Vestfold Hills and Rauer Group, East Antarctica - Peacock, Jared; Selway, Kate (Journal of Geophysical Research: Solid Earth, 2016)
The Vestfold Hills and Rauer Group in East Antarctica have contrasting Archean to Neoproterozoic geological histories and are believed to be juxtaposed along a suture zone that now lies beneath the Sørsdal Glacier. Exact location and age of this suture zone are unknown, as is its relationship to regional deformation associated with the amalgamation of East Gondwana. To image the suture zone, magnetotelluric (MT) data were collected in Prydz Bay, East Antarctica, mainly along a profile crossing the Sørsdal Glacier and regions inland of the Vestfold Hills and Rauer Group islands. Time-frequency analysis of the MT time series yielded three important observations: (1) Wind speeds in excess of ∼8 m/s reduce coherence between electric and magnetic fields due to charged wind-blown particles of ice and snow. (2) Estimation of the MT transfer function is best between 1000 and 1400 UT when ionospheric Hall currents enhance the magnetic source field. (3) Nonplanar source field effects were minimal but detectable and removed from estimation of the MT transfer function. Inversions of MT data in 2-D and 3-D produce similar resistivity models, where structures in the preferred 3-D resistivity model correlate strongly with regional magnetic data. The electrically conductive Rauer Group is separated from the less conductive Vestfold Hills by a resistive zone under the Sørsdal Glacier, which is interpreted to be caused by oxidation during suturing. Though a suture zone has been imaged, no time constrains on suturing can be made from the MT data.
Keywords: Antarktis; geofysikk; geologi; magnetotelluriske målinger

Scleractinian corals recorded in the Argentinean Antarctic expeditions between 2012 and 2014, with comments on Flabellum (Flabellum) areum Cairns, 1982 - Schejter, Laura; Bremec, Claudia S; Cairns, Stephen D (Polar Research, 2016)
In this contribution, we provide a list of the scleractinian corals recorded during the Argentinean Antarctic expeditions on board the oceanographic vessel Puerto Deseado (Argentina) in the austral summers in 2012, 2013 and 2014. The identified taxa consist of six solitary species (Flabellum impensum, F. flexuosum, F. areum, Caryophyllia antarctica, Paraconotrochus antarcticus and Javania antarctica), recorded from 19 sampling sites located off the Antarctic Peninsula and South Shetland and South Orkney islands. We also update the information of F. areum, previously known only from south-west Atlantic waters, extending its distribution range to Antarctic waters and its upper bathymetric range to 218 m. Keywords: cold-water corals; Antarctica; range extension; bathymetric range extension; Scleractinia.
Keywords: Sørishavet; ekspedisjoner; koraller; marin zoologi; oseanografi

Den langsomme polare vippen - Sorokina, Svetlana (Naturen, 2016)
De siste 20 årene har vært de varmeste siden globale temperaturmålinger startet i 1880 (Figur 1). FNs klimapanel konkluderer med at hovedårsaken til den observerte temperaturøkningen er menneskeskapte utslipp av klimagasser. I nordområdene har temperaturen økt nesten dobbelt så raskt som i resten av verden. Isdekket er nær halvert og isvolumet er redusert til en tredjedel. Men på den andre siden av jorden, altså i Antarktis, er situasjonen en helt annen. Temperaturen har vært fallende de siste årene og isdekket har vært rekordstort. Dette paradokset brukes ofte som et argument mot menneskeskapte endring av klima. For hvordan kan det ha seg at temperaturen i Antarktis faller når klimagassutslippene øker?
Keywords: Antarktis; global oppvarming; klimaendringer; klimagasser; polarområdene

Temporal shift in the isotopic niche of female Antarctic fur seals from Bouvetøya - Tarroux, Arnaud; Lowther, Andrew D; Lydersen, Christian; Kovacs, Kit M. (Polar Research, 2016)
The Antarctic fur seal (Arctocephalus gazella) is a key marine predator in the Southern Ocean, a region that has recently started to show changes as a result of global climate change. Here, carbon (δ 13 C) and nitrogen (δ 15 N) stable isotope analyses on whole blood and plasma samples were used to examine the isotopic niche of lactating female Antarctic fur seals. Using recently developed Bayesian approaches to determine changes in isotopic niche, a significant increase in δ 13 C and δ 15 N was found between 1997 and 2015; this change occurred at an average rate of 0.067‰ (δ 13 C) and 0.072‰ (δ 15 N) per year over this period. This suggests that a marked isotopic niche shift has occurred over this period, which very likely corresponds to a shift in diet towards prey at a higher trophic level, such as fish (replacing krill). Although our sampling design prevented us from exploring a seasonal trend in a conclusive manner, our data suggest that concurrent increases in δ 13 C and δ 15 N might occur as the breeding season progresses. At a seasonal scale, an average decrease of −0.7‰ per month (95% confidence interval=[−0.9; −0.6]) in δ 13 C might have occurred, concurrently with an average increase of 1.1‰ per month in δ 15 N. The results of this study constitute the first isotopic assessment for female Antarctic fur seals from Bouvetøya and provide a baseline for the use of this predator species as a sentinel of the marine trophic system in one of the least studied areas within this species' distributional range.
Publisher: Routledge
Keywords: Bouvetøya; Sørishavet; klimaendringer; krill; marin biologi; pelsseler; plankton; stabile isotoper; zoologi

Pacific-Atlantic Circumpolar Deep Water coupling during the last 500 ka - Ullermann, Johannes; Lamy, Frank; Ninnemann, Ulysses; Lembke-Jene, Lester; Gersonde, Rainer; Tiedemann, Ralf (Paleoceanography, 2016)
Investigating the interbasin deepwater exchange between the Pacific and Atlantic Oceans over glacial-interglacial climate cycles is important for understanding circum-Antarctic Southern Ocean circulation changes and their impact on the global Meridional Overturning Circulation. We use benthic foraminiferal δ13C records from the southern East Pacific Rise to characterize the δ13C composition of Circumpolar Deep Water in the South Pacific, prior to its transit through the Drake Passage into the South Atlantic. A comparison with published South Atlantic deepwater records from the northern Cape Basin suggests a continuous water mass exchange throughout the past 500 ka. Almost identical glacial-interglacial δ13C variations imply a common deepwater evolution in both basins suggesting persistent Circumpolar Deep Water exchange and homogenization. By contrast, deeper abyssal waters occupying the more southern Cape Basin and the southernmost South Atlantic have lower δ13C values during most, but not all, stadial periods. We conclude that these values represent the influence of a more southern water mass, perhaps Antarctic Bottom Water (AABW). During many interglacials and some glacial periods, the gradient between Circumpolar Deep Water and the deeper southern Cape Basin bottom water disappears suggesting either no presence of AABW or indistinguishable δ13C values of both water masses.
Keywords: AABW; Sørishavet; Sørishavsstrømmen; klimatologi; oseanografi; paleoseanografi

Investigating uncertainty in the simulation of the Antarctic ice sheet during the mid-Piacenzian - Yan, Qing; Zhang, Zhongshi; Wang, Huijun (Journal of Geophysical Research: Atmospheres, 2016)
The mid-Piacenzian (~3 Ma) represents the most recent warm period in Earth's history on a geological time scale; it is characterized by a significant rise of global sea level. The simulation of the size and location of the ice sheets and the investigation of the uncertainty in the simulations are potentially helpful for constraining reconstructed sea level changes. In this study, we focus on the behavior of the Antarctic ice sheet (AIS) in the mid-Piacenzian. We investigate the influence of topography correction, model parameters, climate forcings, and model resolution on the modeled AIS and explore the isolated role of atmospheric and oceanic forcings. Forced by the simulated climate changes with the Norwegian Earth System Model, the Parallel Ice Sheet Model (15 km × 15 km) produces a nearly collapsed West AIS (WAIS) in the mid-Piacenzian, with no significant retreat of the East AIS (EAIS). The role of increased air temperature plays a key role in the mass loss of the mid-Piacenzian AIS, while its role is comparable to the role of ocean warming on the melting of the WAIS. In terms of the range of sea level changes, the largest source of uncertainty in the modeled AIS is derived from ice sheet model parameters and climate forcings. Although the employed model parameters, topography correction factors, and model resolution affect the simulated AIS in the mid-Piacenzian, large-scale deglaciation of the EAIS in our sensitivity experiments may only be possible with additional warming.
Keywords: Antarktis; atmosfæren; geologi; havnivåstigning; innlandsis; klimaendringer; paleontologi

The impact of energetic electron precipitation on mesospheric hydroxyl during a year of solar minimum - Zawedde, Annet Eva; Nesse Tyssøy, Hilde; Hibbins, Robert; Espy, Patrick J; Ødegaard, Linn-Kristine Glesnes; Sandanger, Marit Irene; Stadsnes, Johan (Journal of Geophysical Research: Space Physics, 2016)
In 2008 a sequence of geomagnetic storms occurred triggered by high-speed solar wind streams from coronal holes. Improved estimates of precipitating fluxes of energetic electrons are derived from measurements on board the NOAA/POES 18 satellite using a new analysis technique. These fluxes are used to quantify the direct impact of energetic electron precipitation (EEP) during solar minimum on middle atmospheric hydroxyl (OH) measured from the Aura satellite. During winter, localized longitudinal density enhancements in the OH are observed over northern Russia and North America at corrected geomagnetic latitudes poleward of 55°. Although the northern Russia OH enhancement is closely associated with increased EEP at these longitudes, the strength and location of the North America enhancement appear to be unrelated to EEP. This OH density enhancement is likely due to vertical motion induced by atmospheric wave dynamics that transports air rich in atomic oxygen and atomic hydrogen downward into the middle atmosphere, where it plays a role in the formation of OH. In the Southern Hemisphere, localized enhancements of the OH density over West Antarctica can be explained by a combination of enhanced EEP due to the local minimum in Earth's magnetic field strength and atmospheric dynamics. Our findings suggest that even during solar minimum, there is substantial EEP-driven OH production. However, to quantify this effect, a detailed knowledge of where and when the precipitation occurs is required in the context of the background atmospheric dynamics.
Keywords: Antarktis; astronomi; energiske partikler; geofysikk; geomagnetiske stormer; planetbølger; solvind

Antarktis - kort fortalt - Balto, Ann Kristin; Hallanger, Ingeborg Gammelsæter; Jenssen, Elin Vinje (Norsk polarinstitutt, 2015)
Keywords: Antarktis; biologi; fauna; flora; historie; klima; miljø; natureklima; naturhistorie

Innovasjonsteori, patenter og teknologisk utvikling i norsk hvalfangst ca. 1860-1968 - Basberg, Bjørn L (Novus, 2015)
Keywords: Sørishavet; hvalfangstindustri; innovasjon; patenter; pelagisk; teknologi

Advancements in decadal climate predictability: The role of nonoceanic drivers - Bellucci, Alessio; Haarsma, Rein; Bellouin, Nicolas; Booth, Ben B; Cagnazzo, Chiara; van den Hurk, Bart; Keenlyside, Noel; Koenigk, Torben; Massonnet, François; Materia, Stefano; Weiss, M (Reviews of Geophysics, 2015)
We review recent progress in understanding the role of sea ice, land surface, stratosphere, and aerosols in decadal-scale predictability and discuss the perspectives for improving the predictive capabilities of current Earth system models (ESMs). These constituents have received relatively little attention because their contribution to the slow climatic manifold is controversial in comparison to that of the large heat capacity of the oceans. Furthermore, their initialization as well as their representation in state-of-the-art climate models remains a challenge. Numerous extraoceanic processes that could be active over the decadal range are proposed. Potential predictability associated with the aforementioned, poorly represented, and scarcely observed constituents of the climate system has been primarily inspected through numerical simulations performed under idealized experimental settings. The impact, however, on practical decadal predictions, conducted with realistically initialized full-fledged climate models, is still largely unexploited. Enhancing initial-value predictability through an improved model initialization appears to be a viable option for land surface, sea ice, and, marginally, the stratosphere. Similarly, capturing future aerosol emission storylines might lead to an improved representation of both global and regional short-term climatic changes. In addition to these factors, a key role on the overall predictive ability of ESMs is expected to be played by an accurate representation of processes associated with specific components of the climate system. These act as “signal carriers,” transferring across the climatic phase space the information associated with the initial state and boundary forcings, and dynamically bridging different (otherwise unconnected) subsystems. Through this mechanism, Earth system components trigger low-frequency variability modes, thus extending the predictability beyond the seasonal scale.
Keywords: Sørishavet; geofysikk; havis; klimaendringer; klimamodeller; meteorologi; polarområdene; sjøis

Mass balance of the Sør Rondane glacial system, East Antarctica - Callens, Denis; Thonnard, Nicolas; Lenaerts, Jan T M; Van Wessem, Jan M; Van de Berg, Willem Jan; Matsuoka, Kenichi; Pattyn, Frank (Annals of Glaciology, 2015)
Mass changes of polar ice sheets have an important societal impact, because they affect global sea level. Estimating the current mass budget of ice sheets is equivalent to determining the balance between surface mass gain through precipitation and outflow across the grounding line. For the Antarctic ice sheet, grounding line outflow is governed by oceanic processes and outlet glacier dynamics. In this study, we compute the mass budget of major outlet glaciers in the eastern Dronning Maud Land sector of the Antarctic ice sheet using the input/output method. Input is given by recent surface accumulation estimates (SMB) of the whole drainage basin. The outflow at the grounding line is determined from the radar data of a recent airborne survey and satellite-based velocities using a flow model of combined plug flow and simple shear. This approach is an improvement on previous studies, as the ice thickness is measured, rather than being estimated from hydrostatic equilibrium. In line with the general thickening of the ice sheet over this sector, we estimate the regional mass balance in this area at 3.15 ± 8.23 Gt a−1 according to the most recent SMB model results.
Publisher: Cambridge University Press
Keywords: Dronning Maud Land; glasiologi

On-site and in situ remediation technologies applicable to petroleum hydrocarbon contaminated sites in the Antarctic and Arctic - Camenzuli, Danielle; Freidman, Benjamin L (Polar Research, 2015)
Petroleum hydrocarbon contaminated sites, associated with the contemporary and legacy effects of human activities, remain a serious environmental problem in the Antarctic and Arctic. The management of contaminated sites in these regions is often confounded by the logistical, environmental, legislative and financial challenges associated with operating in polar environments. In response to the need for efficient and safe methods for managing contaminated sites, several technologies have been adapted for on-site or in situ application in these regions. This article reviews six technologies which are currently being adapted or developed for the remediation of petroleum hydrocarbon contaminated sites in the Antarctic and Arctic. Bioremediation, landfarming, biopiles, phytoremediation, electrokinetic remediation and permeable reactive barriers are reviewed and discussed with respect to their advantages, limitations and potential for the long-term management of soil and groundwater contaminated with petroleum hydrocarbons in the Antarctic and Arctic. Although these technologies demonstrate potential for application in the Antarctic and Arctic, their effectiveness is dependent on site-specific factors including terrain, soil moisture and temperature, freeze–thaw processes and the indigenous microbial population. The importance of detailed site assessment prior to on-site or in situ implementation is emphasized, and it is argued that coupling of technologies represents one strategy for effective, long-term management of petroleum hydrocarbon contaminated sites in the Antarctic and Arctic. Keywords: Petroleum hydrocarbons; remediation; Antarctica; Arctic; cold regions; contaminated site.
Keywords: Antarktis; forurensning; hydrokarboner; miljøvern; petroleum; polarområdene

Mapping lichen distribution on the Antarctic Peninsula using remote sensing, lichen spectra and photographic documentation by citizen scientists - Casanovas, Paula; Black, Martin; Fretwell, Peter; Convey, Peter (Polar Research, 2015)
On the Antarctic Peninsula, lichens are the most diverse botanical component of the terrestrial ecosystem. However, detailed information on the distribution of lichens on the Antarctic Peninsula region is scarce, and the data available exhibit significant heterogeneity in sampling frequency and effort. Satellite remote sensing, in particular the use of the Normalized Difference Vegetation Index (NDVI), has facilitated determination of vegetation richness and cover distribution in some remote and otherwise inaccessible environments. However, it is known that using NDVI for the detection of vegetation can overlook the presence of lichens even if their land cover is extensive. We tested the use of known spectra of lichens in a matched filtering technique for the detection and mapping of lichen-covered land from remote sensing imagery on the Antarctic Peninsula, using data on lichen presence collected by citizen scientists and other non-specialists as ground truthing. Our results confirm that the use of this approach allows for the detection of lichen flora on the Antarctic Peninsula, showing an improvement over the use of NDVI alone for the mapping of flora in this area. Keywords: Antarctica; NDVI; matched filtering; Landsat; remote sensing.
Keywords: Antarktis; botanikk; flora; lav; satellitt bilder; økosystemer

Evolution of Derwael Ice Rise in Dronning Maud Land, Antarctica, over the last millennia - Drews, Reinhard; Matsuoka, Kenichi; Martín, Carlos; Callens, D; Bergeot, Nicolas; Pattyn, Frank (Journal of Geophysical Research: Earth Surface, 2015)
Ice rises situated in the ice-shelf belt around Antarctica have a spatially confined flow regime with local ice divides. Beneath the divides, ice stratigraphy often develops arches with amplitudes that record the divide's horizontal residence time and surface elevation changes. To investigate the evolution of Derwael Ice Rise, Dronning Maud Land, Antarctica, we combine radar and GPS data from three consecutive surveys, with a two-dimensional, full Stokes, thermomechanically coupled, transient ice-flow model. We find that the surface mass balance (SMB) is higher on the upwind and lower on the downwind slopes. Near the crest, the SMB is anomalously low and causes arches to form in the shallow stratigraphy, observable by radar. In deeper ice, arches are consequently imprinted by both SMB and ice rheology (Raymond effect). The data show how arch amplitudes decrease as along-ridge slope increases, emphasizing that the lateral positioning of radar cross sections is important for the arch interpretation. Using the model with three rheologies (isotropic with n=3,4.5 and anisotropic with n=3), we show that Derwael Ice Rise is close to steady state but is best explained using ice anisotropy and moderate thinning. Our preferred, albeit not unique, scenario suggests that the ice divide has existed for at least 5000 years and lowered at approximately 0.03 m a−1 over the last 3400 years. Independent of the specific thinning scenario, our modeling suggests that Derwael Ice Rise has exhibited a local flow regime at least since the Mid-Holocene.
Keywords: Dronning Maud Land; fjernmåling; glasiologi; innlandsis; isbreer; stratigrafi

Kaptein Melsom. Et spennende liv som hvalfanger og skipsreder - Dyrhaug, Tore (Njotarøy : årsskrift, 2015)
1912 fikk Nøtterøy en ny innbygger. Hvalfangeren H. G. Melsom var vendt hjem fra et hvalfangerliv i det fjerne Østen og kjøpte hus på Ørsnes. Her startet han opp en ny fase i livet, som skipsreder. Høydepunktet i hans karriere var trolig da hvalskuta «Lancing» dro om bord den første hvalen fra en opphalingsslipp i hekken på båten. Med dette var den virkelige pelagiske hvalfangsten i gang. Historien om «Lancing» som det første hvalkokeriet som kunne dra en hel hval om bord, er vel kjent og beskrevet. Dette var starten på den pelagiske hvalfangsten som brakte hvalfangsten inn i en ny fase. Men historien om hvalfangeren og rederen fra Nøtterøy, som var en av dem som sto bak, har ikke vært særlig kjent. Med god hjelp fra barnebarnet Henrik Melsom Henriksen, har Tore Dyrhaug skrevet ned denne historien.
Publisher: Nøtterøy historielag
Keywords: Nordmenn; Norge; Sørishavet; dagbøker; hvalfangere; hvalfangst; pelagisk

On-ice vibroseis and snowstreamer systems for geoscientific research - Eisen, Olaf; Hofstede, Coen; Diez, Anja; Kristoffersen, Yngve; Lambrecht, Astrid; Mayer, Christoph; Blenkner, Rick; Hilmarsson, Sverrir (Recent Advance in Polar Seismology: Global Impact of the International Polar Year, 2015)
We present implementations of vibroseis system configurations with a snowstreamer for over-ice long-distance seismic traverses (>100 km). The configurations have been evaluated in Antarctica on ice sheet and ice shelf areas in the period 2010–2014. We discuss results of two different vibroseis sources: Failing Y-1100 on skis with a peak force of 120 kN in the frequency range 10–110 Hz; IVI EnviroVibe with a nominal peak force of 66 kN in the nominal frequency range 10–300 Hz. All measurements used a well-established 60 channel 1.5 km snowstreamer for the recording. Employed forces during sweeps were limited to less than 80% of the peak force. Maximum sweep frequencies, with a typical duration of 10 s, were 100 and 250 Hz for the Failing and EnviroVibe, respectively. Three different concepts for source movement were employed: the Failing vibrator was mounted with wheels on skis and pulled by a Pistenbully snow tractor. The EnviroVibe was operated self-propelled on Mattracks on the Antarctic plateau. This lead to difficulties in soft snow. For later implementations the EnviroVibe with tracks was put on a polyethylene (PE) sled. The sled had a hole in the center to lower the vibrator baseplate directly onto the snow surface. With the latter setup, data production varied between 20 km/day for 6-fold and 40 km/day for single fold for 9 h/day of measurements. The combination of tracks with the PE-sled was especially advantageous on hard and rough surfaces because of the flexibility of each component and the relatively lose mounting. The systems presented here are suitable to obtain data of subglacial and sub-seabed sediment layers and englacial layering in comparable quality as obtained from marine geophysics and land-based explosive surveys. The large offset aperture of the streamer overcomes limitations of radar systems for imaging of steep along-track subglacial topography. With joint international scientific and logistic efforts, large-scale mapping of Antarctica's and Greenland's subglacial geology, ice-shelf cavity geometries and sea-bed strata, as well as englacial structures can be achieved.
Keywords: Dronning Maud Land; isshelf; seismologi; teknologi

Van Allen probes, NOAA, GOES, and ground observations of an intense EMIC wave event extending over 12 h in magnetic local time - Engebretson, Mark J; Posch, J L; Wygant, J R; Kletzing, Craig A; Lessard, M R; Huang, C.-L.; Spence, Harlan; Smith, C W; Singer, H J; Omura, Yoshiharu; Horne, R B; Reeves, Geoffrey; et al. (Journal of Geophysical Research: Space Physics, 2015)
Although most studies of the effects of electromagnetic ion cyclotron (EMIC) waves on Earth's outer radiation belt have focused on events in the afternoon sector in the outer plasmasphere or plume region, strong magnetospheric compressions provide an additional stimulus for EMIC wave generation across a large range of local times and L shells. We present here observations of the effects of a wave event on 23 February 2014 that extended over 8 h in UT and over 12 h in local time, stimulated by a gradual 4 h rise and subsequent sharp increases in solar wind pressure. Large-amplitude linearly polarized hydrogen band EMIC waves (up to 25 nT p-p) appeared for over 4 h at both Van Allen Probes, from late morning through local noon, when these spacecraft were outside the plasmapause, with densities ~5–20 cm−3. Waves were also observed by ground-based induction magnetometers in Antarctica (near dawn), Finland (near local noon), Russia (in the afternoon), and in Canada (from dusk to midnight). Ten passes of NOAA-POES and METOP satellites near the northern foot point of the Van Allen Probes observed 30–80 keV subauroral proton precipitation, often over extended L shell ranges; other passes identified a narrow L shell region of precipitation over Canada. Observations of relativistic electrons by the Van Allen Probes showed that the fluxes of more field-aligned and more energetic radiation belt electrons were reduced in response to both the emission over Canada and the more spatially extended emission associated with the compression, confirming the effectiveness of EMIC-induced loss processes for this event.
Keywords: Antarktis; astronomi; elektromagnetiske ionesyklotronbølger; fysikk; magnetosfæriske kompresjoner; strålingsbelter

Interhemispheric differences in ionospheric convection: Cluster EDI observations revisited - Förster, Matthias; Haaland, Stein (Journal of Geophysical Research: Space Physics, 2015)
The interaction between the interplanetary magnetic field and the geomagnetic field sets up a large-scale circulation in the magnetosphere. This circulation is also reflected in the magnetically connected ionosphere. In this paper, we present a study of ionospheric convection based on Cluster Electron Drift Instrument (EDI) satellite measurements covering both hemispheres and obtained over a full solar cycle. The results from this study show that average flow patterns and polar cap potentials for a given orientation of the interplanetary magnetic field can be very different in the two hemispheres. In particular during southward directed interplanetary magnetic field conditions, and thus enhanced energy input from the solar wind, the measurements show that the southern polar cap has a higher cross polar cap potential. There are persistent north-south asymmetries, which cannot easily be explained by the influence of external drivers. These persistent asymmetries are primarily a result of the significant differences in the strength and configuration of the geomagnetic field between the Northern and Southern Hemispheres. Since the ionosphere is magnetically connected to the magnetosphere, this difference will also be reflected in the magnetosphere in the form of different feedback from the two hemispheres. Consequently, local ionospheric conditions and the geomagnetic field configuration are important for north-south asymmetries in large regions of geospace.
Keywords: Antarktis; astrofysikk; geovitenskap; ionosfæren; magnetosfæren; polarområdene; solvind

Haematological values of three Antarctic penguins: gentoo (Pygoscelis papua), Adélie (P. adeliae) and chinstrap (P. antarcticus) - Ibañez, Andrés E; Najle, Roberto; Larsen, Karen; Pari, Marcela; Figueroa, Amalia; Montalti, Diego (Polar Research, 2015)
It is established that haematological and biochemical parameters provide important data to assess the physiological condition and health status of wild birds. To undertake conservation physiology or ecophysiology work, it is therefore essential to establish baseline physiological parameters and how these parameters change with age and life history events. In this work, we determined and compared baseline haematology and serum biochemistry between adults and chicks of three Antarctic penguin species of the genus Pygoscelis: gentoo (P. papua), Adélie (P. adeliae) and chinstrap (P. antarcticus). Differences in adults among species were observed in haemoglobin and biochemical parameters such as total proteins, glucose and alkaline phosphatase activity. In addition, differences between adults and chicks in haematocrit, haemoglobin, total proteins and glucose concentration were determined. Moreover, we evaluated the electrophoretic protein profiles between adults and chicks of the genus Pygoscelis, and a conserved protein pattern was observed among species and ages in the genus. Altogether, the results suggest that biochemical and haematological differences among pygoscelids may be related to the nutritional status and energetic expenditure during breeding as well as their feeding habits and development stage. Keywords: Antarctic; haematology; physiology; Pygoscelis; penguins; serum biochemistry.
Keywords: Antarktis; biokjemi; biologi; fysiologi; hematologi; pingviner; zoologi

Two distinct Late Mesoproterozoic/Early Neoproterozoic basement provinces in central/eastern Dronning Maud Land, East Antarctica: The missing link, 15–21°E - Jacobs, Joachim; Elburg, Marlina; Läufer, Andreas; Kleinhanns, Ilka C; Henjes-Kunst, Friedhelm; Estrada, Solveig; Ruppel, Antonia S; Damaske, Detlef; Montero, Pilar; Bea, Fernando (Precambrian Research, 2015)
This article highlights the field geology, geochronology and geochemistry of an important and previously unstudied region between eastern (Sør Rondane Mountains) and central Dronning Maud Land (DML). The area allows the characterisation and ground-truthing of a large and mostly ice-covered area that is geophysically distinct and which was previously interpreted as a potentially older cratonic block south of a Late Neoproterozoic/Early Paleozoic (LN/EP) mobile belt, as exposed in the Sør Rondane Mts. (SRM). SHRIMP/SIMS zircon analyses of 20 samples together with new geochemistry indicate that the exposed basement consists of a ca. 1000–900Ma juvenile terrane that is very similar to the juvenile rocks of the SW-Terrane of the SRM, a characteristic gabbro–trondhjemite–tonalite–granite (GTTG) suite, with normalised trace element patterns typical for subduction-related magmas and mostly positive initial epsilon Nd values. The area shows strong LN/EP crustal reworking, migmatisation and melt production, including 560–530Ma A-type magmatism. Therefore, this area is very similar to the SW-Terrane and differs only in the degree of LN/EP reworking. We interpret the SW-Terrane of Sør Rondane as a mega-boudin sandwiched in between rheologically weaker portions of similar oceanic arc terranes. Therefore, the study area, and thereby the aeromagnetically distinct SE DML province does neither represent the foreland of a LN/EP mobile belt, nor a craton, as speculated based on geophysical data alone. Instead, a large Tonian Oceanic Arc Super Terrane (TOAST) with significant extent emerges. Its western limit is represented by the Forster Magnetic Anomaly, which represents a suture to the Grenville-age Maud Belt. East of the TOAST, the Rayner Complex is similar in age but otherwise distinctly different. The Rayner Complex has a much longer history of island arc accretions with continent–continent collision at ca. 950Ma and it has markedly more evolved crust. In contrast, the TOAST has a pronounced juvenile character without significant inheritance and lacks metamorphic overprint immediately following crust formation. This indicates that it has not been an integral part of Rodinia. The eastern boundary of the TOAST is probably in the vicinity of the Yamato Mts., whilst its northern extension might be seen in the Vohibori Terrane (SW Madagascar), which in turn could correlate with the Arabian Nubian Shield. The LN/EP tectono-metamorphic overprint of the TOAST shows a slight decrease in ages from W to E, possibly indicating that it first amalgamated on its Kalahari side before it was attached to Rukerland/Indo-Antarctica.
Keywords: Dronning Maud Land; geokjemi; geokronologi; geologi

Application of remotely piloted aircraft systems in observing the atmospheric boundary layer over Antarctic sea ice in winter - Jonassen, Marius O; Tisler, Priit; Altstädter, Barbara; Scholtz, Andreas; Vihma, Timo; Lampert, Astrid; König-Langlo, Gert; Lüpkes, Christof (Polar Research, 2015)
The main aim of this paper is to explore the potential of combining measurements from fixed- and rotary-wing remotely piloted aircraft systems (RPAS) to complement data sets from radio soundings as well as ship and sea-ice-based instrumentation for atmospheric boundary layer (ABL) profiling. This study represents a proof-of-concept of RPAS observations in the Antarctic sea-ice zone. We present first results from the RV Polarstern Antarctic winter expedition in the Weddell Sea in June–August 2013, during which three RPAS were operated to measure temperature, humidity and wind; a fixed-wing small unmanned meteorological observer (SUMO), a fixed-wing meteorological mini-aerial vehicle, and an advanced mission and operation research quadcopter. A total of 86 RPAS flights showed a strongly varying ABL structure ranging from slightly unstable temperature stratification near the surface to conditions with strong surface-based temperature inversions. The RPAS observations supplement the regular upper air soundings and standard meteorological measurements made during the campaign. The SUMO and quadcopter temperature profiles agree very well and, excluding cases with strong temperature inversions, 70% of the variance in the difference between the SUMO and quadcopter temperature profiles can be explained by natural, temporal, temperature fluctuations. Strong temperature inversions cause the largest differences, which are induced by SUMO’s high climb rates and slow sensor response. Under such conditions, the quadcopter, with its slower climb rate and faster sensor, is very useful in obtaining accurate temperature profiles in the lowest 100 m above the sea ice. Keywords: Remotely piloted aircraft systems; unmanned aerial vehicles; Weddell Sea; polar meteorology; Antarctic; boundary layer meteorology.
Keywords: Sørishavet; Weddellhavet; fjernstyrte flysystemer; havis; meteorologi; målinger; observasjoner; sjøis; ubemannede luftfartøyer

A roadmap for Antarctic and Southern Ocean science for the next two decades and beyond - Kennicutt, M.C.; Chown, S.L.; Cassano, J.J.; Liggett, D.; Peck, L.S.; Massom, R.; Rintoul, S.R.; Storey, J.; Vaughan, D.G.; Wilson, T.J.; Allison, I.; Ayton, J.; et al. (Antarctic Science, 2015)
Antarctic and Southern Ocean science is vital to understanding natural variability, the processes that govern global change and the role of humans in the Earth and climate system. The potential for new knowledge to be gained from future Antarctic science is substantial. Therefore, the international Antarctic community came together to ‘scan the horizon’ to identify the highest priority scientific questions that researchers should aspire to answer in the next two decades and beyond. Wide consultation was a fundamental principle for the development of a collective, international view of the most important future directions in Antarctic science. From the many possibilities, the horizon scan identified 80 key scientific questions through structured debate, discussion, revision and voting. Questions were clustered into seven topics: i) Antarctic atmosphere and global connections, ii) Southern Ocean and sea ice in a warming world, iii) ice sheet and sea level, iv) the dynamic Earth, v) life on the precipice, vi) near-Earth space and beyond, and vii) human presence in Antarctica. Answering the questions identified by the horizon scan will require innovative experimental designs, novel applications of technology, invention of next-generation field and laboratory approaches, and expanded observing systems and networks. Unbiased, non-contaminating procedures will be required to retrieve the requisite air, biota, sediment, rock, ice and water samples. Sustained year-round access to Antarctica and the Southern Ocean will be essential to increase winter-time measurements. Improved models are needed that represent Antarctica and the Southern Ocean in the Earth System, and provide predictions at spatial and temporal resolutions useful for decision making. A co-ordinated portfolio of cross-disciplinary science, based on new models of international collaboration, will be essential as no scientist, programme or nation can realize these aspirations alone.
Edition: 2014/09/18 Publisher: Cambridge University Press
Keywords: Antarktis; Sørishavet; forskning; teknologi

The significant inputs of trace elements and rare earth elements from melting glaciers in Antarctic coastal waters - Kim, Intae; Kim, Guebuem; Choy, Eun Jung (Polar Research, 2015)
To evaluate the impact of modern glacier melting on the chemical enrichment of Antarctic coastal waters, we measured trace elements, including dissolved iron (Fe) and rare earth elements (REEs), together with dissolved inorganic nitrogen, phosphorous, silicate and dissolved organic carbon (DOC) in ice, snow and coastal seawater of Marian Cove in the northernmost part of Antarctica (62°S). There was an increase in the concentrations of Fe and other trace elements (Al, Mn, Cr, Ni, Co, Pb and REEs) between the bay mouth and the glacier valleys. Good correlations between salinity and these chemical elements indicate that the trend was mainly due to the influence of glacier meltwater (GMW). When the effect of GMW was quantified based on plots of its presence (average 5.7%) in the surface water of the cove, the concentrations of trace elements in seawater increased 18-fold for Fe, eight- to 10-fold for Al and Mn and up to four-fold for Cr, Ni, Co, Pb and REEs by GMW. However, the contribution of GMW to inorganic nutrients and DOC was negligible. The significance of GMW-borne REE contribution in this cove was further evidenced by middle REE enrichment in cove water. Our results suggest that the currently increasing glacier melting in Antarctica has a significant influence on the level of trace elements, particularly Fe, in cove water, which in turn may have a significant impact on the biogeochemistry of coastal seawater in Antarctica. Keywords: Iron; trace elements; rare earth elements; glacier melting; Antarctica; Marian Cove.
Keywords: Antarktis; biogeokjemi; isbreer; kjemiske analyser; sjøvann; smelting

An Antarctic krill (Euphausia superba) hotspot: population characteristics, abundance and vertical structure explored from a krill fishing vessel - Krafft, Bjørn Arne; Skaret, Georg; Knutsen, Tor (Polar Biology, 2015)
Keywords: Sørishavet; krill; marin biologi; plankton; zooplankton

Western Australia-Kalahari (WAlahari) connection in Rodinia: Not supported by U/Pb detrital zircon data from the Maud Belt (East Antarctica) and the Northampton Complex (Western Australia) - Ksienzyk, Anna K; Jacobs, Joachim (Precambrian Research, 2015)
The Kalahari Craton is an important building block of the supercontinent Rodinia, but its position with respect to other cratons is still controversially discussed. The Maud Belt in East Antarctica is part of the extensive Namaqua-Natal-Maud Orogen along which Kalahari collided with another continent during Rodinia assembly. One of the continents that have been suggested as collision partners for Kalahari is Western Australia, with the Pinjarra Orogen as the counterpart to the Maud Belt. We investigate this connection from a geochronological point of view. SHRIMP U/Pb zircon analyses of three metasedimentary samples from the Maud Belt date Grenville-age metamorphism within the orogen at ca. 1100–1060Ma. One sample was later affected by Pan-African metamorphism at ca. 540Ma. A second sample is interpreted as a molasse of the Maud Belt and was deposited in the Neoproterozoic. Detrital zircons from all three samples are consistent with derivation of the sediments predominantly from within the Namaqua-Natal-Maud Belt, with minor contributions from the Kalahari Craton. No clear Western Australian fingerprint could be detected in the detrital ages and a direct comparison between detrital zircon ages from the Maud Belt and the Northampton Complex (Pinjarra Orogen, Western Australia) showed distinct differences in the age spectra. Altogether, we consider a collision between Kalahari and south-western Laurentia a more likely scenario.
Keywords: Dronning Maud Land; geokronologi; geovitenskap

Birkeland current effects on high-latitude ground magnetic field perturbations - Laundal, Karl M; Haaland, Stein; Lehtinen, N; Gjerloev, Jesper; Østgaard, Nikolai; Tenfjord, Paul; Reistad, Jone Peter; Snekvik, Kristian; Milan, Steve; Ohtani, Shin-ichi; Anderson, B J (Geophysical Research Letters, 2015)
Magnetic perturbations on ground at high latitudes are directly associated only with the divergence-free component of the height-integrated horizontal ionospheric current, J⊥,df. Here we show how J⊥,df can be expressed as the total horizontal current J⊥ minus its curl-free component, the latter being completely determined by the global Birkeland current pattern. Thus, in regions where J⊥=0, the global Birkeland current distribution alone determines the local magnetic perturbation. We show with observations from ground and space that in the polar cap, the ground magnetic field perturbations tend to align with the Birkeland current contribution in darkness but not in sunlight. We also show that in sunlight, the magnetic perturbations are typically such that the equivalent overhead current is antiparallel to the convection, indicating that the Hall current system dominates. Thus, the ground magnetic field in the polar cap relates to different current systems in sunlight and in darkness.
Keywords: Antarktis; Birkelandstrømmer; ionosfæren; ionosfæriske strømmer; polarområdene; sollys

Reliability of VHF telemetry data for measuring attendance patterns of marine predators: a comparison with time depth recorder data - Lowther, A D; Ahonen, H; Hofmeyr, G; Oosthuizen, W C; De Bruyn, P J N; Lydersen, C; Kovacs, K M (Marine Ecology Progress Series, 2015)
Very high frequency (VHF) radiotelemetry data has been used for over 30 yr to monitor the behavior patterns of otariid seals. These data have been used in a wide variety of ways, from characterizing the reproductive and foraging ecology of these species to inferring ecosystem changes based on variation in attendance patterns. Yet the accuracy of VHF data has never been appropriately evaluated. Our study compares VHF data collected on 16 lactating Antarctic fur seals to assess onshore attendance with concurrently collected time depth recorder (TDR) data used as the true measurement of time spent onshore. Within the retrieved datasets, 25% of the VHF data could not be interpreted with any reliability. Additionally, there were significant differences in the number and duration of attendance bouts between the 2 instrument types, with VHF data overestimating attendance bout duration by approximately 8.9 h on average. Importantly, the magnitude and direction of errors between VHF and TDR measurements were not systematic, suggesting that VHF data is an inappropriate method for collecting attendance data. Modelling the raw VHF data in a state-space framework elicited mean attendance durations that were indistinguishable from TDR-derived measurements, suggesting this approach may provide a means to re-examine historic VHF data. Moreover, given the evolution of electronic tags in terms of sophistication, miniaturization, longevity and decreasing cost over the last 30 yr, TDRs are a more appropriate means of collecting attendance data on centrally foraging marine mammals such as otariids.
Keywords: Bouvetøya; NARE ekspedisjoner; Sørishavet; marin zoologi; overvåking; pelsseler; pinnipedier; radio telemetri; økosystemer

The potential response of the hydrate reservoir in the South Shetland Margin, Antarctic Peninsula, to ocean warming over the 21st century - Marín-Moreno, Hector; Giustiniani, Michela; Tinivella, Umberta (Polar Research, 2015)
In the South Shetland Margin (SSM), Antarctic Peninsula, a bottom-simulating reflector indicates the presence of hydrate between ca. 500 and 3000 m water depth (mwd). The cold seabed temperatures allow hydrate stability at shallower water depths. During the past five decades, the Antarctic Peninsula has been warming up faster than any other part of the Southern Hemisphere, and long-term ocean warming could affect the stability of the SSM hydrate reservoir at shallow waters. Here, we model the transient response of the SSM hydrate reservoir between 375 and 450 mwd to ocean warming for the period 1958–2100. For the period 1958–2010, seabed temperatures are given by oceanographic measurements in the area, and for 2010–2100 by two temperature scenarios represented by the observed trends for the periods 1960–2010 (0.0034°C y−1) and 1980–2010 (0.023°C y−1). Our results show no hydrate-sourced methane emissions for an ocean warming rate at the seabed of 0.0034 °C y−1. For a rate of 0.023°C y−1, emissions start in 2028 at 375 mwd and extend to 442 mwd at an average rate of about 0.91 mwd y−1, releasing ca. 1.13×103 mol y−1 of methane per metre along the margin by 2100. These emissions originate from dissociation at the top of the hydrate layer, a physical process that steady-state modelling cannot represent. Our results are speculative on account of the lack of direct evidence of a shallow water hydrate reservoir, but they illustrate that the SSM is a key area to observe the effects of ocean warming-induced hydrate dissociation in the coming decades. Keywords: Hydrate; ocean warming; methane emissions; transient modelling; South Shetland Margin; Antarctic Peninsula.
Keywords: Sørishavet; geofysikk; havbunnen; havoppvarming; metanutslipp; oseanografi

Antarctic ice rises and rumples: their properties and significance for ice-sheet dynamics and evolution - Matsuoka, Kenichi; Hindmarsh, Richard C A; Moholdt, Geir; Bentley, Michael J; Pritchard, Hamish D; Brown, Joel; Conway, Howard; Drews, Reinhard; Durand, Gaël; Goldberg, Daniel; Hattermann, Tore; Kingslake, Jonathan; et al. (Earth-Science Reviews, 2015)
Locally grounded features in ice shelves, called ice rises and rumples, play a key role buttressing discharge from the Antarctic Ice Sheet and regulating its contribution to sea level. Ice rises typically rise several hundreds of meters above the surrounding ice shelf; shelf flow is diverted around them. On the other hand, shelf ice flows across ice rumples, which typically rise only a few tens of meters above the ice shelf. Ice rises contain rich histories of deglaciation and climate that extend back over timescales ranging from a few millennia to beyond the last glacial maximum. Numerical model results have shown that the buttressing effects of ice rises and rumples are significant, but details of processes and how they evolve remain poorly understood. Fundamental information about the conditions and processes that cause transitions between floating ice shelves, ice rises and ice rumples is needed in order to assess their impact on ice-sheet behavior. Targeted high-resolution observational data are needed to evaluate and improve prognostic numerical models and parameterizations of the effects of small-scale pinning points on grounding-zone dynamics.
Keywords: Antarktis; Sørishavet; glasiologi; havis

Observational evidence of the influence of Antarctic stratospheric ozone variability on middle atmosphere dynamics - Narukull, Venkateswara Rao; Espy, Patrick Joseph; Hibbins, Robert; Fritts, David C; Kavanagh, Andrew John (Geophysical Research Letters, 2015)
Abstract Modeling results have suggested that the circulation of the stratosphere and mesosphere in spring is strongly affected by the perturbations in heating induced by the Antarctic ozone hole. Here using both mesospheric MF radar wind observations from Rothera Antarctica (67°S, 68°W) as well as stratospheric analysis data, we present observational evidence that the stratospheric and mesospheric wind strengths are highly anti-correlated, and show their largest variability in November. We find that these changes are related to the total amount of ozone loss that occurs during the Antarctic spring ozone hole and particularly with the ozone gradients that develop between 57.5°S and 77.5°S. The results show that with increasing ozone loss during spring, winter conditions in the stratosphere and mesosphere persist longer into the summer. These results are discussed in the light of observations of the onset and duration of the Antarctic polar mesospheric cloud season.
Keywords: Antarktis; klimatologi; meteorologi; ozonhull; ozonlaget

Methane and nitrous oxide fluxes in relation to vegetation covers and bird activity in ice-free soils of Rip Point, Nelson Island, Antarctica - Neufeld, Ângela Denise Hubert; de Godoi, Stefânia Guedes; Pereira, Antônio Batista; Bayer, Cimélio; Schünemann, Andriano Luis; de Carvalho Victoria, Filipe; de Albuquerque, Margéli Pereira; Camargo, Estefânia; Vieira, Frederico Costa Beber (Polar Research, 2015)
This study aimed to quantify the nitrous oxide (N2O) and methane (CH4) fluxes at sites with different vegetation covers and where bird activity was present or absent using the static chamber method, on Rip Point, Nelson Island, maritime Antarctic. The sites were soils covered by Sanionia uncinata, lichens, Prasiola crispa, Deschampsia antarctica and bare soil. Seabirds used the P. crispa and D. antarctica sites as nesting areas. Soil mineral N contents, air and soil temperature and water-filled pore space were measured, and the content of total organic C and particulate organic C, total N, bulk density and texture were determined to identify controlling variables of the gas emissions. The N2O and CH4 flux rates were low for all sampling events. Mean N2O flux rates ranged from 0.11±1.93 up to 21.25±22.14 µg N2O m−2 h−1 for the soils under lichen and P. crispa cover, respectively. For the CH4 fluxes, only the P. crispa site showed a low positive mean (0.47±3.61 µg CH4 m−2 h−1). The bare soil showed the greatest absorption of CH4 (−11.92±5.7 µg CH4 m−2 h−1), probably favoured by the coarse soil texture. Bare soil and S. uncinata sites had N2O accumulated emissions close to zero. Net CH4 accumulated emission was observed only at the P. crispa site, which was correlated with (p<0.001). These results indicate that seabird activity influences N2O and CH4 soil fluxes, while vegetation has little influence, and bare soil areas in maritime Antarctica could be greenhouse gas sinks. Keywords: Soil greenhouse gases; seabirds; vegetal cover; maritime Antarctica.
Keywords: Antarktis; biogeokjemi; drivhuseffekt; drivhusgasser; flora; global oppvarming; klimaendringer; klimagasser; planter; sjøfugler; økosystemer

Ozone-induced climate change propped up by the Southern Hemisphere oceanic front - Ogawa, Fumiaki; Omrani, Nour-Eddine; Nishii, Kazuaki; Nakamura, Hisashi; Keenlyside, Noel (Geophysical Research Letters, 2015)
The late twentieth century was marked by a significant summertime trend in the Southern Annular Mode (SAM), the dominant mode of tropospheric variability in the extratropical Southern Hemisphere (SH). This trend with poleward shifting tropospheric westerlies was attributed to downward propagation of stratospheric changes induced by ozone depletion. However, the role of the ocean in setting the SAM response to ozone depletion and its dynamical forcing remains unclear. Here we show, using idealized experiments with a state-of-the-art atmospheric model and analysis of Intergovernmental Panel on Climate Change climate simulations, that frontal sea surface temperature gradients in the midlatitude SH are critical for translating the ozone-induced stratospheric changes down to the surface. This happens through excitation of wave forcing, which controls the vertical connection of the tropospheric SAM with the stratosphere and shows the importance of internal tropospheric dynamics for stratosphere/troposphere coupling. Thus, improved simulation of oceanic fronts may reduce uncertainties in simulating SH ozone-induced climate changes.
Keywords: Sørishavet; geofysikk; havet; havstrømmer; klimaendringer; ozonhull; ozonlaget

First record of humpback anglerfish (Melanocetus johnsonii) (Melanocetidae) in Antarctic waters - Orlov, Alexei M.; Orlova, Svetlana Y.; Volkov, Alexander A.; Pelenev, Dmitry V. (Polar Research, 2015)
The first record of the humpback anglerfish (Melanocetus johnsonii) in Antarctic waters (Ross Sea) is documented. Species identification is confirmed by the structure of the escal bulb and analysis of the mitochondrial cytochrome oxidase subunit I (COI) gene. This record extends the known range of M. johnsonii by more than 1000 nm to the south. The taxonomic status of Melanocetus species in Antarctic waters is discussed. Keywords: Melanocetus sp.; new record; taxonomy; distribution; Ross Sea; Antarctic.
Keywords: Rosshavet; Sørishavet; fisker; genetisk analyse; marin zoologi; taksonomi; zoogeografi

More than passive drifters: a stochastic dynamic model for the movement of Antarctic krill - Richerson, Kate; Watters, George M; Santora, Jarrod A; Schroeder, Isaac D; Mangel, Marc (Marine Ecology Progress Series, 2015)
Antarctic krill Euphausia superba are a key part of the marine food web and are the target of the largest fishery in the Southern Ocean. Although ecosystem and management models typically assume that krill are passive drifters, their relatively large size and strong swimming ability suggest that the active movement of krill may play an important role in their spatial distribution. Thus, active swimming behavior by krill may influence spatial structure of food web interactions (e.g. feeding behavior of seabirds and marine mammals) and regional commercial fishery activity. The objective of this work was to model the potential for active movement to affect krill distribution, and consequently growth, reproductive success, and survival. We used state-dependent life history theory, implemented by stochastic dynamic programming, in combination with spatial information on food availability, current velocity, temperature, and predation risk, to predict krill swimming behavior near the northern Antarctic Peninsula. We found that including active krill behavior resulted in distribution patterns that are associated with increased survival, growth, and reproductive success compared to a model that treats krill as passive drifters. The expected reproductive success of actively behaving krill was about 70% greater than that of passively diffusing krill, suggesting that there are strong selective pressures for active behavior along oceanic drift trajectories. This modeling framework will benefit assessments of new catch limits as krill fishing grounds are partitioned into smaller spatial management units. KEYWORDS: Euphausia superba · Behavior · Stochastic dynamic programming · Management · Advection · Southern Ocean
Keywords: Sørishavet; krill; marin biologi; oseanografi; plankton; økosystemer

Sessile macro-epibiotic community of solitary ascidians, ecosystem engineers in soft substrates of Potter Cove, Antarctica - Rimondino, Clara; Torre, Luciana; Sahade, Ricardo; Tatián, Marcos (Polar Research, 2015)
The muddy bottoms of inner Potter Cove, King George Island (Isla 25 de Mayo), South Shetlands, Antarctica, show a high density and richness of macrobenthic species, particularly ascidians. In other areas, ascidians have been reported to play the role of ecosystem engineers, as they support a significant number of epibionts, increasing benthic diversity. In this study, a total of 21 sessile macro-epibiotic taxa present on the ascidian species Corella antarctica Sluiter, 1905, Cnemidocarpa verrucosa (Lesson, 1830) and Molgula pedunculata Herdman, 1881 were identified, with Bryozoa being the most diverse. There were differences between the three ascidian species in terms of richness, percent cover and diversity of sessile macro-epibionts. The morphological characteristics of the tunic surface, the available area for colonization (and its relation with the age of the basibiont individuals) and the pH of the ascidian tunic seem to explain the observed differences. Recent environmental changes in the study area (increase of suspended particulate matter caused by glaciers retreat) have been related to observed shifts in the benthic community structure, negatively affecting the abundance and distribution of the studied ascidian species. Considering the diversity of sessile macro-epibionts found on these species, the impact of environmental shifts may be greater than that estimated so far. Keywords: Sessile macro-epibiont; ascidian; Antarctica; ecosystem- engineer.
Keywords: Sørishavet; bentiske organismer; biodiversitet; bryozoa; havbunnen; sekkdyr; økologi; økosystemer

The Main Shear Zone in Sør Rondane, East Antarctica: Implications for the late-Pan-African tectonic evolution of Dronning Maud Land - Ruppel, Antonia S; Läufer, Andreas; Jacobs, Joachim; Elburg, Marlina; Krohne, Nicole; Damaske, Detlef; Lisker, Frank (Tectonics, 2015)
Structural investigations in western Sør Rondane, eastern Dronning Maud Land (DML), provide new insights into the tectonic evolution of East Antarctica. One of the main structural features is the approximately 120 km long and several hundred meters wide WSW-ENE trending Main Shear Zone (MSZ). It is characterized by dextral high-strain ductile deformation under peak amphibolite-facies conditions. Crosscutting relationships with dated magmatic rocks bracket the activity of the MSZ between late Ediacaran to Cambrian times (circa 560 to 530 Ma). The MSZ separates Pan-African greenschist- to granulite-facies metamorphic rocks with “East African” affinities in the north from a Rayner-age early Neoproterozoic gabbro-tonalite-trondhjemite-granodiorite complex with “Indo-Antarctic” affinities in the south. It is interpreted to represent an important lithotectonic strike-slip boundary at a position close to the eastern margin of the East African-Antarctic Orogen (EAAO), which is assumed to be located farther south in the ice-covered region. Together with the possibly coeval left-lateral South Orvin Shear Zone in central DML, the MSZ may be related to NE directed lateral escape of the EAAO, whereas the Heimefront Shear Zone and South Kirwanveggen Shear Zone of western DML are part of the south directed branch of this bilateral system.
Keywords: Dronning Maud Land; geokronologi; geologi; geovitenskap; petrografi; tektonikk

Multi-frequency observations of seawater carbonate chemistry on the central coast of the western Antarctic Peninsula - Schram, Julie B; Schoenrock, Kathryn M; McClintock, James B; Amsler, Charles D; Angus, Robert A (Polar Research, 2015)
Assessments of benthic coastal seawater carbonate chemistry in Antarctica are sparse. The studies have generally been short in duration, during the austral spring/summer, under sea ice, or offshore in ice-free water. Herein we present multi-frequency measurements for seawater collected from the shallow coastal benthos on a weekly schedule over one year (May 2012–May 2013), daily schedule over three months (March–May 2013) and semidiurnal schedule over five weeks (March–April 2013). A notable pH increase (max pH = 8.62) occurred in the late austral spring/summer (November–December 2012), coinciding with sea-ice break-out and subsequent increase in primary productivity. We detected semidiurnal variation in seawater pH with a maximum variation of 0.13 pH units during the day and 0.11 pH units during the night. Daily variation in pH is likely related to biological activity, consistent with previous research. We calculated the variation in dissolved inorganic carbon (DIC) over each seawater measurement frequency, focusing on the primary DIC drivers in the Palmer Station region. From this, we estimated net biological activity and found it accounts for the greatest variations in DIC. Our seasonal data suggest that this coastal region tends to act as a carbon dioxide source during austral winter months and as a strong sink during the summer. These data characterize present-day seawater carbonate chemistry and the extent to which these measures vary over multiple time scales. This information will inform future experiments designed to evaluate the vulnerability of coastal benthic Antarctic marine organisms to ocean acidification. Keywords: Antarctica; aragonite; calcite; pH; seawater chemistry; total alkalinity.
Keywords: Sørishavet; analyser; havis; kjemisk; sjøis; sjøvann

Polychlorinated biphenyl exposure and corticosterone levels in seven polar seabird species - Tartu, Sabrina; Angelier, Frédéric; Bustnes, Jan-Ove; Moe, Børge; Hanssen, Sven Are; Herzke, Dorte; Gabrielsen, Geir Wing; Verboven, Nanette; Verreault, J; Labadie, Pierre; Budzinski, Helene; Wingfield, John C; et al. (Environmental Pollution, 2015)
The role of polychlorinated biphenyls (PCBs) on exposure-related endocrine effects has been poorly investigated in wild birds. This is the case for stress hormones including corticosterone (CORT). Some studies have suggested that environmental exposure to PCBs and altered CORT secretion might be associated. Here we investigated the relationships between blood PCB concentrations and circulating CORT levels in seven free-ranging polar seabird species occupying different trophic positions, and hence covering a wide range of PCB exposure. Blood ∑7PCB concentrations (range: 61–115,632 ng/g lw) were positively associated to baseline or stress-induced CORT levels in three species and negatively associated to stress-induced CORT levels in one species. Global analysis suggests that in males, baseline CORT levels generally increase with increasing blood ∑7PCB concentrations, whereas stress-induced CORT levels decrease when reaching high blood ∑7PCB concentrations. This study suggests that the nature of the PCB-CORT relationships may depend on the level of PCB exposure.
Keywords: Antarktis; forurensning; miljø; nevrobiologi; ornitologi; polarområdene; sjøfugler; stresshormoner; zoologi

Corticosterone, prolactin and egg neglect behavior in relation to mercury and legacy POPs in a long-lived Antarctic bird - Tartu, Sabrina; Angelier, Frédéric; Wingfield, John C; Bustamante, Paco; Labadie, Pierre; Budzinski, Helene; Weimerskirch, Henri; Bustnes, Jan-Ove; Chastel, Olivier (Science of the Total Environment, 2015)
Seabirds often have high loads of contaminants. These contaminants have endocrine disrupting properties but their relationships with some endocrine mechanisms are still poorly investigated in free-living organisms. This is the case for the stress response which shifts energy investment away from reproduction and redirects it towards survival. In birds, this stress response is achieved through a release of corticosterone and is also accompanied by a decrease in circulating prolactin, an anterior pituitary hormone widely involved in regulating parental cares. We measured blood concentrations of some legacy persistent organic pollutants (POPs) and mercury (Hg) and examined their relationships with the corticosterone and prolactin responses of known-age (9–46years old) incubating snow petrels (Pagodroma nivea) to a standardized capture/handling stress protocol. In this Antarctic seabird, we also investigated whether high contaminant burden correlates with a higher occurrence of egg neglect, a frequently observed behavior in snow petrels. POPs and Hg were unrelated to age. Stress-induced corticosterone concentrations were positively related to POPs in both sexes, and stress-induced prolactin concentrations were negatively related to Hg in males. Egg-neglect behavior was not related to POPs burden, but males with higher Hg concentrations were more likely to neglect their egg. This suggests that in birds, relationships between age and contaminants are complex and that even low to moderate concentrations of POPs and Hg are significantly related to hormonal secretion. In this Antarctic species, exposure to legacy POPs and Hg could make individuals more susceptible to environmental stressors such as ongoing disturbances in Polar Regions.
Keywords: Antarktis; forurensning; miljø; nevrobiologi; ornitologi; petreller; polarområdene; reproduksjon; sjøfugler; zoologi

Investigating the recent apparent hiatus in surface temperature increases: 2. Comparison of model ensembles to observational estimates - Thorne, Peter; Outten, Stephen; Bethke, Ingo; Seland, Øyvind (Journal of Geophysical Research: Atmospheres, 2015)
To assess published hypotheses surrounding the recent slowdown in surface warming (hiatus), we compare five available global observational surface temperature estimates to two 30-member ensembles from the Norwegian Earth System Model (NorESM). Model ensembles are initialized in 1980 from the transient historical runs and driven with forcings used in the CMIP5 experiments and updated forcings based upon current observational understanding, described in Part 1. The ensembles' surface temperature trends are statistically indistinguishable over 1998–2012 despite differences in the prescribed forcings. There is thus no evidence that forcing errors play a significant role in explaining the hiatus according to NorESM. The observations fall either toward the lower portion of the ensembles or, for some observational estimates and regions, outside. The exception is the Arctic where the observations fall toward the upper ensemble bounds. Observational data set choices can make a large difference to findings of consistency or otherwise. Those NorESM ensemble members that exhibit Nino3.4 Sea Surface Temperature (SST) trends similar to observed also exhibit comparable tropical and to some extent global mean trends, supporting a role for El Nino Southern Oscillation in explaining the hiatus. Several ensemble members capture the marked seasonality observed in Northern Hemisphere midlatitude trends, with cooling in the wintertime and warming in the remaining seasons. Overall, we find that we cannot falsify NorESM as being capable of explaining the observed hiatus behavior. Importantly, this is not equivalent to concluding NorESM could simultaneously capture all important facets of the hiatus. Similar experiments with further, distinct, Earth System Models are required to verify our findings.
Keywords: Antarktis; atmosfæren; fjernmåling; geofysikk; klimaendringer; klimatologi; meteorologi; observasjoner; polarområdene; temperatur

Norske interesser og politikk i Antarktis - Utenriksdepartementet (2015)
Publisher: Fagbokforlaget Place: Oslo
Keywords: Dronning Maud Land; forvaltning; politikk

Comment on “Unexpected Occurrence of Volatile Dimethylsiloxanes in Antarctic Soils, Vegetation, Phytoplankton, and Krill” - Warner, Nicholas A; Krogseth, Ingjerd S; Whelan, Mick J (Environmental Science & Technology, 2015)
Sanchís et al. (2015) recently reported the occurrence of volatile methyl siloxanes (VMS) in soil, vegetation, phytoplankton, and krill samples from Antarctica. As the paper’s title suggests, findings of these chemicals in such a remote region is unexpected and of significant concern. However, our experience with the analysis of these compounds at trace concentrations suggests that the observations reported may have been influenced by artifacts. Here we present our concerns based upon known emissions, physicochemical properties and on apparent quality control measures including treatment of blank samples and detection limits.
Publisher: American Chemical Society
Keywords: Antarktis; forurensning; miljøgifter

Population-specific wintering distributions of adult south polar skuas over three oceans - Weimerskirch, Henri; Tarroux, Arnoud; Chastel, Olivier; Delord, Karine; Cherel, Yves; Descamps, Sébastien (Marine Ecology Progress Series, 2015)
Migratory routes and the areas used during winter have probably been selected to maximize fitness by providing favorable environmental conditions outside the breeding season. In polar environments, because of the extreme winter weather, most breeding species migrate to encounter better conditions in areas that can differ between and also within species. Using geolocation sensors, we found that south polar skuas Catharacta maccormicki from 2 distant populations breeding on the Antarctic continent along the Atlantic and Indian Oceans migrate northward to winter in tropical Indian Ocean and in temperate North Pacific waters, respectively. Most individuals from each population winter in different environmental conditions, with water temperatures ranging from 16 to 29°C. Nevertheless, they have very similar activity patterns, spending more than 80% of their time on the water, and their feather δ15N values suggest that they probably feed at similar trophic levels during the molt. During overwintering, the overall and constant low activity level may be partly imposed by molting constraints, but it also suggests that trophic conditions are good for skuas. The wintering areas of the species correspond to sectors of high concentrations of breeding or wintering tropical, Northern, and Southern Hemisphere seabird species that are likely to be kleptoparasitized by skuas. A certain degree of individual variation exists within each population, which induces a spatial overlap in the wintering grounds of distant breeding populations. These results have potential important consequences in terms of fitness, genetic divergence, and susceptibility to climate change and marine pollution. KEYWORDS: Catharacta maccormicki · Geolocators · Migration · Population-specific strategies · Stable isotopes.
Keywords: Dronning Maud Land; geolokalisering; klimaendringer; marin forurensning; ornitologi; polarområdene; trekkfugler; zoologi

An Antarctic Research Station as a Source of Brominated and Perfluorinated Persistent Organic Pollutants to the Local Environment - Wild, Seanan; McLagan, David; Schlabach, Martin; Bossi, Rossana; Hawker, Darryl; Cropp, Roger; King, Catherine K; Stark, Jonathan S; Mondon, Julie; Nash, Susan Bengtson (Environmental Science & Technology, 2015)
This study investigated the role of a permanently manned Australian Antarctic research station (Casey Station) as a source of contemporary persistent organic pollutants (POPs) to the local environment. Polybrominated diphenyl ethers (PBDEs) and poly- and perfluoroalkylated substances (PFASs) were found in indoor dust and treated wastewater effluent of the station. PBDE (e.g., BDE-209 26–820 ng g–1 dry weight (dw)) and PFAS levels (e.g., PFOS 3.8–2400 ng g–1 (dw)) in dust were consistent with those previously reported in homes and offices from Australia, reflecting consumer products and materials of the host nation. The levels of PBDEs and PFASs in wastewater (e.g., BDE-209 71–400 ng L–1) were in the upper range of concentrations reported for secondary treatment plants in other parts of the world. The chemical profiles of some PFAS samples were, however, different from domestic profiles. Dispersal of chemicals into the immediate marine and terrestrial environments was investigated by analysis of abiotic and biotic matrices. Analytes showed decreasing concentrations with increasing distance from the station. This study provides the first evidence of PFAS input to Polar regions via local research stations and demonstrates the introduction of POPs recently listed under the Stockholm Convention into the Antarctic environment through local human activities.
Publisher: American Chemical Society
Keywords: Antarktis; forskningsstasjoner; forurensning; menneskelig påvirkning; miljøgifter

Protists in the polar regions: comparing occurrence in the Arctic and Southern oceans using pyrosequencing - Wolf, Christian; Kilias, Estelle; Metfies, Katja (Polar Research, 2015)
In the ongoing discussion of the distribution of protists, whether they are globally distributed or endemic to one or both of the polar regions is the subject of heated debate. In this study, we compared next-generation sequencing data from the Arctic and the Southern oceans to reveal the extent of similarities and dissimilarities between the protist communities in the polar regions. We found a total overlap of operational taxonomic units (OTUs) between the two regions of 11.2%. On closer inspection of different taxonomic groups, the overlap ranged between 5.5% (haptophytes) and 14.5% (alveolates). Within the different groups, the proportion of OTUs occurring in both regions greatly differed between the polar regions. On the one hand, the overlap between these two regions is remarkable, given the geographical distance between them. On the other hand, one could expect a greater overlap of OTUs between these regions on account of the similar environmental conditions. The overlap suggests a connection between the polar regions for at least certain species or that the evolutionary divergence has been slow, relative to the timescales of isolation. The different proportions of common OTUs among the groups or regions may be a result of different life cycle strategies or environmental adaptations. Keywords: 18S rDNA; bipolar; next-generation sequencing; phytoplankton; polar regions; protist distribution.
Keywords: Sørishavet; fytoplankton; marin biologi; polarområdene; protoktister; pyrosekvensering; økosystemer

Reconstruction of changes in the Weddell Sea sector of the Antarctic Ice Sheet since the Last Glacial Maximum - Hillenbrand, Claus-Dieter; Bentley, Michael J.; Stolldorf, Travis D.; Hein, Andrew S.; Kuhn, Gerhard; Graham, Alastair G.C.; Fogwill, Christopher J.; Kristoffersen, Yngve; Smith, James. A.; Anderson, John B.; Larter, Robert D.; Melles, Martin; et al. (Reconstruction of Antarctic Ice Sheet Deglaciation (RAISED), 2014)
The Weddell Sea sector is one of the main formation sites for Antarctic Bottom Water and an outlet for about one fifth of Antarctica's continental ice volume. Over the last few decades, studies on glacial–geological records in this sector have provided conflicting reconstructions of changes in ice-sheet extent and ice-sheet thickness since the Last Glacial Maximum (LGM at ca 23–19 calibrated kiloyears before present, cal ka BP). Terrestrial geomorphological records and exposure ages obtained from rocks in the hinterland of the Weddell Sea, ice-sheet thickness constraints from ice cores and some radiocarbon dates on offshore sediments were interpreted to indicate no significant ice thickening and locally restricted grounding-line advance at the LGM. Other marine geological and geophysical studies concluded that subglacial bedforms mapped on the Weddell Sea continental shelf, subglacial deposits and sediments over-compacted by overriding ice recovered in cores, and the few available radiocarbon ages from marine sediments are consistent with major ice-sheet advance at the LGM. Reflecting the geological interpretations, different ice-sheet models have reconstructed conflicting LGM ice-sheet configurations for the Weddell Sea sector. Consequently, the estimated contributions of ice-sheet build-up in the Weddell Sea sector to the LGM sea-level low-stand of ∼130 m vary considerably. In this paper, we summarise and review the geological records of past ice-sheet margins and past ice-sheet elevations in the Weddell Sea sector. We compile marine and terrestrial chronological data constraining former ice-sheet size, thereby highlighting different levels of certainty, and present two alternative scenarios of the LGM ice-sheet configuration, including time-slice reconstructions for post-LGM grounding-line retreat. Moreover, we discuss consistencies and possible reasons for inconsistencies between the various reconstructions and propose objectives for future research. The aim of our study is to provide two alternative interpretations of glacial–geological datasets on Antarctic Ice-Sheet History for the Weddell Sea sector, which can be utilised to test and improve numerical ice-sheet models.
Keywords: Antarctica; Cosmogenic nuclide surface exposure age dating; Deglaciation; Geomorphology; Glacial history; Ice Shelf; Ice sheet; Last Glacial Maximum; Radiocarbon dating; Sea level; Sørishavet; Weddellhavet; geologi; geomorfologi; glasiologi

Oppdrag på verdens mest isolerte øy - Engås, Christopher (Svalbardposten, 2014)
Bouvetøya er kjent som verdens mest isolerte plass. Men det er langt fra livløst. - Hele bakken flyttet seg da vi kom, forteller Vidar Olsbakk.
Keywords: Bouvetøya; logistikk; stasjoner

HFC-43-10mee atmospheric abundances and global emission estimates - Arnold, Tim; Ivy, Diane J; Harth, Christina M; Vollmer, Martin K; Mühle, Jens; Salameh, Peter K; Paul Steele, L; Krummel, Paul B; Wang, Ray H J; Young, Dickon; Lunder, Chris R; Hermansen, Ove; et al. (Geophysical Research Letters, 2014)
We report in situ atmospheric measurements of hydrofluorocarbon HFC-43-10mee (C5H2F10; 1,1,1,2,2,3,4,5,5,5-decafluoropentane) from seven observatories at various latitudes, together with measurements of archived air samples and recent Antarctic flask air samples. The global mean tropospheric abundance was 0.21 ± 0.05 ppt (parts per trillion, dry air mole fraction) in 2012, rising from 0.04 ± 0.03 ppt in 2000. We combine the measurements with a model and an inverse method to estimate rising global emissions—from 0.43 ± 0.34 Gg yr−1 in 2000 to 1.13 ± 0.31 Gg yr−1 in 2012 (~1.9 Tg CO2-eq yr−1 based on a 100 year global warming potential of 1660). HFC-43-10mee—a cleaning solvent used in the electronics industry—is currently a minor contributor to global radiative forcing relative to total HFCs; however, our calculated emissions highlight a significant difference from the available reported figures and projected estimates.
Keywords: Antarktis; atmosfæren; forurensning; massespektrometri; meteorologi; målinger; utslipp

Late Holocene climate change recorded in proxy records from a Bransfield Basin sediment core, Antarctic Peninsula - Barnard, Alex; Wellner, Julia S; Anderson, John B (Polar Research, 2014)
The glacimarine environment of the Antarctic Peninsula region is one of the fastest warming places on Earth today, but details of changes in the recent past remain unknown. Large distances and widespread variability separate late Holocene palaeoclimate reconstructions in this region. This study focuses on a marine sediment core collected from ca. 2000 m below sea level in the Central Bransfield Strait that serves as a key for understanding changes in this region. The core yielded a high sedimentation rate and therefore provides an exceptional high-resolution sedimentary record composed of hemipelagic sediment, with some turbidites. An age model has been created using radiocarbon dates that span the Late Holocene: 3560 cal yr BP to present. This chronostratigraphic framework was used to establish five units, which are grouped into two super-units: a lower super-unit (3560–1600 cal yr BP) and an upper super-unit (1600 cal yr BP–present), based on facies descriptions, laser particle size analysis, x-ray analysis, multi-sensor core logger data, weight percentages and isotopic values of total organic carbon and nitrogen. We interpret the signal contained within the upper super-unit as an increase in surface water irradiance and/or shortening of the sea-ice season and the five units are broadly synchronous with climatic intervals across the Antarctic Peninsula region. While the general trends of regional climatic periods are represented in the Bransfield Basin core we have examined, each additional record that is obtained adds variability to the known history of the Antarctic Peninsula, rather than clarifying specific trends. Keywords: Antarctic Peninsula; palaeoclimate; Holocene; marine; isotopes.
Keywords: Antarktis; geofysikk; geokjemi; paleoklimatologi; sedimentologi

Thorbryn - en hvalbåts videverdige karriere - Basberg, Bjørn L (Norsk maritimt museum. Årbok, 2014)
Publisher: Norsk maritimt museum
Keywords: Sørishavet; historie; hvalbåter; hvalfangst; pelagisk; sjøfart; skipsfart

A Nutritional-Toxicological Assessment of Antarctic Krill Oil versus Fish Oil Dietary Supplements - Bengtson Nash, Susan M; Schlabach, Martin; Nichols, Peter D (Nutrients, 2014)
Fish oil dietary supplements and complementary medicines are pitched to play a role of increasing strategic importance in meeting daily requirements of essential nutrients, such as long-chain (≥C20, LC) omega-3 polyunsaturated fatty acids and vitamin D. Recently a new product category, derived from Antarctic krill, has been launched on the omega-3 nutriceutical market. Antarctic krill oil is marketed as demonstrating a greater ease of absorption due to higher phospholipid content, as being sourced through sustainable fisheries and being free of toxins and pollutants; however, limited data is available on the latter component. Persistent Organic Pollutants (POP) encompass a range of toxic, man-made contaminants that accumulate preferentially in marine ecosystems and in the lipid reserves of organisms. Extraction and concentration of fish oils therefore represents an inherent nutritional-toxicological conflict. This study aimed to provide the first quantitative comparison of the nutritional (EPA and DHA) versus the toxicological profiles of Antarctic krill oil products, relative to various fish oil categories available on the Australian market. Krill oil products were found to adhere closely to EPA and DHA manufacturer specifications and overall were ranked as containing intermediate levels of POP contaminants when compared to the other products analysed. Monitoring of the pollutant content of fish and krill oil products will become increasingly important with expanding regulatory specifications for chemical thresholds.
Keywords: Sørishavet; forurensning; krill; marine økosystemer; miljøgifter; plankton; toksikologi

A community-based geological reconstruction of Antarctic Ice Sheet deglaciation since the Last Glacial Maximum - Bentley, Michael J.; Ó Cofaigh, Colm; Anderson, John B.; Conway, Howard; Davies, Bethan; Graham, Alastair G.C.; Hillenbrand, Claus-Dieter; Hodgson, Dominic A.; Jamieson, Stewart S.R.; Larter, Robert D.; Mackintosh, Andrew; Smith, James A.; et al. (Reconstruction of Antarctic Ice Sheet Deglaciation (RAISED), 2014)
A robust understanding of Antarctic Ice Sheet deglacial history since the Last Glacial Maximum is important in order to constrain ice sheet and glacial-isostatic adjustment models, and to explore the forcing mechanisms responsible for ice sheet retreat. Such understanding can be derived from a broad range of geological and glaciological datasets and recent decades have seen an upsurge in such data gathering around the continent and Sub-Antarctic islands. Here, we report a new synthesis of those datasets, based on an accompanying series of reviews of the geological data, organised by sector. We present a series of timeslice maps for 20 ka, 15 ka, 10 ka and 5 ka, including grounding line position and ice sheet thickness changes, along with a clear assessment of levels of confidence. The reconstruction shows that the Antarctic Ice sheet did not everywhere reach the continental shelf edge at its maximum, that initial retreat was asynchronous, and that the spatial pattern of deglaciation was highly variable, particularly on the inner shelf. The deglacial reconstruction is consistent with a moderate overall excess ice volume and with a relatively small Antarctic contribution to meltwater pulse 1a. We discuss key areas of uncertainty both around the continent and by time interval, and we highlight potential priorities for future work. The synthesis is intended to be a resource for the modelling and glacial geological community.
Keywords: Antarktis; Modelling; deglasiasjon; geologi; glasiologi; innlandsis

Instrumentation and handling effects on Antarctic fur seals (Arctocephalus gazella) - Blanchet, Marie-Anne; Lydersen, Christian; Biuw, Martin; de Bruyn, P J Nico; Hofmeyr, Greg; Krafft, Bjørn A.; Kovacs, Kit M. (Polar Research, 2014)
The use of biologging instruments has greatly improved our understanding of the behaviour, physiology and ecology of free-ranging marine mammals. However, handling wild animals and attaching instruments to streamlined bodies can cause stress and potentially influence behaviour and swimming/diving energetics. The goals of this study, undertaken on Bouvetøya, were (1) to determine if the first trip to sea after instrumentation is representative of subsequent trips in lactating Antarctic fur seals, to explore potential handling effects and assess possible biases in having multiple short-duration deployments (inflating N, using a limited number of tags) and (2) to evaluate potential effects of two different instrument combinations (SMRU satellite data relay loggers and very high frequency radio transmitters versus Wildlife Computers time–depth recorders and very high frequency radio transmitters) on trip durations, dive parameters, female body condition and pup growth. Handling did not appear to have any effects on the parameters studied; data from the first and second trips did not differ significantly. This implies that multiple short-term deployments are unlikely to result in biased data in this species. Instrument type did have measurable effects; time-at-sea was greater and pup growth was lower for pairs in which mothers carried bulkier instruments. This suggests that instrument streamlining is important to avoid negative impacts and that bulkier equipment should be deployed on lactating females with caution and only for short periods. The study highlights that instrument effects should be taken into account when comparing data from experiments collected using different equipment packages. Keywords: Bioenergetics; biologging; instrument effects; SRDLs; TDRs; VHFs.
Keywords: Bouvetøya; NARE ekspedisjoner; analyser; bioenergetikk; biologging; marin zoologi; pelsseler

Polynya dynamics drive primary production in the Larsen A and B embayments following ice shelf collapse - Cape, Mattias R.; Vernet, Maria; Kahru, Mati; Spreen, Gunnar (Journal of Geophysical Research: Oceans, 2014)
The climate-driven collapses of the Larsen A and B ice shelves have opened up new regions of the coastal Antarctic to the influence of sea ice resulting in increases in seasonal primary production. In this study, passive microwave remote sensing of sea ice concentration and satellite imagery of ocean color are employed to quantify the magnitude of and variability in open water area and net primary productivity (NPP) in the Larsen embayments between 1997 and 2011. Numerical model output provides context to analyze atmospheric forcing on the coastal ocean. Following ice shelf disintegration the embayments function as coastal, sensible heat polynyas. The Larsen A and B are as productive as other Antarctic shelf regions, with seasonally averaged daily NPP rates reaching 1232 and 1127 mg C m−2 d−1 and annual rates reaching 200 and 184 g C m−2 yr−1, respectively. A persistent cross-shelf gradient in NPP is present with higher productivity rates offshore, contrasting with patterns observed along the West Antarctic Peninsula. Embayment productivity is intimately tied to sea ice dynamics, with large interannual variability in NPP rates driven by open water area and the timing of embayment opening. Opening of the embayment is linked to periods of positive Southern Annular Mode and stronger westerlies, which lead to the vertical deflection of warm, maritime air over the peninsula and down the leeward side causing increases in surface air temperature and wind velocity. High productivity in these new polynyas is likely to have ramifications for organic matter export and marine ecosystem evolution.
Keywords: Sørishavet; brehylle; fjernmåling; fytoplankton; havis; isbrem; isshelf; klimaendringer; oseanografi; polynja; satellite bilder; sjøis

Svartelisting i isødet - Christensen, Stig H (LO-Aktuelt, 2014)
Hvalfangst-eventyret i Antarktis fra 1905 kostet menneskeliv og blodslit. Hvalfangernes forsøk på å organisere seg ble møtt med svartelisting, utestengelse og arrestasjoner.
Keywords: Antarktis; Sørishavet; arbeidsforhold; fagforbund; hvalfangere; hvalfangst; pelagisk; sjøfolk

Three artotrogids (Crustacea: Copepoda: Siphonostomatoida) from the Ross Sea, Antarctica - Conradi, Mercedes (Polar Research, 2014)
The Artotrogidae, one of the most primitive of siphonostomatoid families, consists currently of 117 species in 21 genera. Most of these species (65%) are poorly or incompletely described since they have been rarely recorded in recent decades and, when encountered, have been found in very low numbers. During the 19th Italian Antarctic Expedition, with the RV Italica, to the Ross Sea in austral summer 2004, some artotrogid copepods were collected. This paper redescribes two species of artotrogid copepods, which are known only from the Southern Ocean, Neobradypontius neglectus and Cryptopontiuslatus, and describes for the first time a male of the genus Neobradypontius. Furthermore, a new species is described and added to Sestropontius, increasing the number of known species of this genus to three. The main discrepancies between the original descriptions and the specimens of the two species collected from the Ross Sea redescribed here were on the armature of the antennary exopod and leg 5. The new species, Sestropontius italicae, shares with its most similar congener, S. mckinnoni, the armature of the third endopodal segment of leg 1 and leg 2 and that of the third exopodal segment of leg 4. However, the segmentation of the antennae and the armature on the antennary exopod are different. Keywords: Antarctica; Artotrogidae; redescription; Neobradypontius; Sestropontius; Cryptopontius.
Keywords: Rosshavet; Sørishavet; copepoder; ekspedisjoner; hoppekreps; marin biologi; zoologi

Antarktis: inlandsis, shelf-is och stigande havsnivå - Darelius, Elin (Naturen, 2014)
I klimatsammanhang har strålkastarljuset länge varit riktade mot de känsliga polarområdena och smältande is. Bilder på isbjörnar som klamrar sig fast vid ett ensamt isflak figurerar varje höst i media när årets – ofta rekordlåga – minimum i utbredning av Arktisk havsis offentliggörs. Men nyligen har is-överskrifterna allt oftare kommit söderifrån, de har handlat om Antarktis, om shelf-is som smälter, om en stigande havsnivå och om möjligheten för att inlandsisen i Väst-Antarktis ska kollapsa.
Keywords: Sørishavet; brehylle; havnivåstigning; innlandsis; isbrem; isshelf; klimaendringer

Hydrography and circulation in the Filchner Depression, Weddell Sea, Antarctica - Darelius, Elin Maria K; Makinson, Keith; Daae, Kjersti Birkeland; Fer, Ilker; Holland, Paul R; Nicholls, Keith W (Journal of Geophysical Research: Oceans, 2014)
Keywords: Sørishavet; Weddellhavet; bunnvann; havstrømmer; hydrografi; isfront; isshelf

On the Seasonal Signal of the Filchner Overflow, Weddell Sea, Antarctica - Darelius, Elin Maria K; Strand, Kjersti Opstad; Østerhus, Svein; Gammelsrød, Tor; Årthun, Marius; Fer, Ilker (Journal of Physical Oceanography, 2014)
Keywords: Sørishavet; Weddellhavet; bunnvann; isshelf; kontinentalsokkel; kontinentalsokler; oseanografi; sjøvann

Contrasting strategies of resistance vs. tolerance to desiccation in two polar dipterans - Everatt, M J; Convey, P; Worland, M R; Bale, J S; Hayward, S A L (Polar Research, 2014)
Low water availability is one of the principal stressors for terrestrial invertebrates in the polar regions, determining the survival of individuals, the success of species and the composition of communities. The Arctic and Antarctic dipterans Heleomyza borealis and Eretmoptera murphyi spend the majority of their biennial life cycles as larvae, and so are exposed to the full range of environmental conditions, including low water availability, over the annual cycle. In the current study, the desiccation resistance and desiccation tolerance of larvae were investigated, as well as their capacity for cross-tolerance to temperature stress. Larvae of H. borealis showed high levels of desiccation resistance, only losing 6.9% of their body water after 12 days at 98.2% relative humidity (RH). In contrast, larvae of E. murphyi lost 46.7% of their body water after 12 days at the same RH. Survival of E. murphyi larvae remained high in spite of this loss (>80% survival). Following exposure to 98.2% RH, larvae of E. murphyi showed enhanced survival at −18°C for 2 h. The supercooling point of larvae of both species was also lowered following prior treatment at 98.2% RH. Cross-tolerance to high temperatures (37 or 38.5°C) was not noted following desiccation in E. murphyi, and survival even fell at 37°C following a 12-day pre-treatment. The current study demonstrates two different strategies of responding to low water availability in the polar regions and indicates the potential for cross-tolerance, a capacity which is likely to be beneficial in the ever-changing polar climate. Keywords: Acclimation; dipteran; supercooling point; temperature; cross-tolerance.
Keywords: Antarktis; diptera; polarområdene; temperatur; tovinger; uttørking; virvelløse dyr

Annual cycle of Antarctic baseline aerosol: controlled by photooxidation-limited aerosol formation - Fiebig, Markus; Hirdman, David; Lunder, Chris R; Ogren, John A; Solberg, Sverre; Stohl, Andreas; Thompson, Rona L (Atmospheric Chemistry and Physics (Print), 2014)
This article investigates the annual cycle observed in the Antarctic baseline aerosol scattering coefficient, total particle number concentration, and particle number size distribution (PNSD), as measured at Troll Atmospheric Observatory. Mie theory shows that the annual cycles in microphysical and optical aerosol properties have a common cause. By comparison with observations at other Antarctic stations, it is shown that the annual cycle is not a local phenomenon, but common to central Antarctic baseline air masses. Observations of ground-level ozone at Troll as well as backward plume calculations for the air masses arriving at Troll demonstrate that the baseline air masses originate from the free troposphere and lower stratosphere region, and descend over the central Antarctic continent. The Antarctic summer PNSD is dominated by particles with diameters <100 nm recently formed from the gas-phase despite the absence of external sources of condensible gases. The total particle volume in Antarctic baseline aerosol is linearly correlated with the integral insolation the aerosol received on its transport pathway, and the photooxidative production of particle volume is mostly limited by photooxidative capacity, not availability of aerosol precursor gases. The photooxidative particle volume formation rate in central Antarctic baseline air is quantified to 207 ±4 μm3/(MJ m). Further research is proposed to investigate the applicability of this number to other atmospheric reservoirs, and to use the observed annual cycle in Antarctic baseline aerosol properties as a benchmark for the representation of natural atmospheric aerosol processes in climate models.
Publisher: Copernicus Publications
Keywords: Dronning Maud Land; Troll forskningsstasjon; atmosfæren; forurensning; klimamodeller; miljøgifter

Counteracting the climate effects of volcanic eruptions using short-lived greenhouse gases - Fuglestvedt, Jan S.; Samset, Bjørn H.; Shine, Keith P. (Geophysical Research Letters, 2014)
A large volcanic eruption might constitute a climate emergency, significantly altering global temperature and precipitation for several years. Major future eruptions will occur, but their size or timing cannot be predicted. We show, for the first time, that it may be possible to counteract these climate effects through deliberate emissions of short-lived greenhouse gases, dampening the abrupt impact of an eruption. We estimate an emission pathway countering a hypothetical eruption 3 times the size of Mount Pinatubo in 1991. We use a global climate model to evaluate global and regional responses to the eruption, with and without counteremissions. We then raise practical, financial, and ethical questions related to such a strategy. Unlike the more commonly discussed geoengineering to mitigate warming from long-lived greenhouse gases, designed emissions to counter temporary cooling would not have the disadvantage of needing to be sustained over long periods. Nevertheless, implementation would still face significant challenges.
Keywords: Antarktis; drivhusgasser; global klimamodell; global oppvarming; klimatologi; nedbør; polarområdene; vulkaner

Alien invasions in Antarctica - is anyone liable? - Hughes, Kevin A; Convey, Peter (Polar Research, 2014)
The introduction of non-native species to Antarctica in association with human activities is a major threat to indigenous biodiversity and the region's unique ecosystems, as has been well-demonstrated in other ecosystems globally. Existing legislation contained in the Protocol on Environmental Protection to the Antarctic Treaty does not specifically make the eradication of non-native species mandatory, although it is implicit that human-assisted introductions should not take place. Furthermore, to date, eradications of non-native species in the Treaty area have been infrequent and slow to progress. In 2005 an additional Annex (VI) to the Protocol was agreed concerning “Liability arising from environmental emergencies.” This annex focusses on prevention of environmental emergencies, contingency planning and reclaiming costs incurred when responding to an environmental emergency caused by another operator within the Antarctic Treaty area. However, the types of environmental emergencies covered by the annex are not defined. In this paper we highlight potential difficulties with the application of Annex VI in the context of non-native species control and eradication, including, for example, whether a non-native species introduction would be classified as an “environmental emergency” and therefore be considered under the terms of the annex. Even if this were the case, we conclude that the slow pace of approval of the annex by Antarctic Treaty Parties may prevent it coming into force for many years and, once in force, in its current form it is unlikely to be useful for reclaiming costs associated with the eradication or management of a non-native species.
Keywords: Antarktis; biodiversitet; internasjonal; miljøvern; politikk; samarbeid; økosystemer

Estimating surface mass balance variability in Antarctica: examples from Fimbulisen - Isaksson, Elisabeth (Fram forum, 2014)
If all the ice in the Antarctic ice sheet were to melt, the world’s oceans would rise about 58 metres. Although nobody expects anything that dramatic to happen, current knowledge doesn’t tell us what we might actually expect. The Fimbulisen project should help eliminate some of the uncertainty.
Keywords: Dronning Maud Land; glasiologi; innlandsis; isbrem; isshelf; klimaendringer; smelting

At the root of the early penguin neck: a study of the only two cervicodorsal spines recovered from the Eocene of Antarctica - Jadwiszczak, Piotr (Polar Research, 2014)
The spinal column of early Antarctic penguins is poorly known, mainly due to the scarcity of articulated vertebrae in the fossil record. One of the most interesting segments of this part of the skeleton is the transitional series located at the root of the neck. Here, two such cervicodorsal series, comprising reinterpreted known material and a new specimen from the Eocene of Seymour Island (Antarctic Peninsula), were investigated and contrasted with those of modern penguins and some fossil bones. The new specimen is smaller than the counterpart elements in recent king penguins, whereas the second series belonged to a large-bodied penguin from the genus Palaeeudyptes. It had been assigned by earlier researchers to P. gunnari (a species of “giant” penguins) and a Bayesian analysis—a Bayes factor approach based on size of an associated tarsometatarsus—strongly supported such an assignment. Morphological and functional studies revealed that mobility within the aforementioned segment probably did not differ substantially between extant and studied fossil penguins. There were, however, intriguing morphological differences between the smaller fossil specimen and the comparative material related to the condition of the lateral excavation in the first cervicodorsal vertebra and the extremely small size of the intervertebral foramen located just prior to the first “true” thoracic vertebra. The former feature could have resulted from discrepancy in severity of external pneumatization. Both fossils provided valuable insights into the morphology and functioning of the axial skeleton in early penguins. Keywords: Antarctic Peninsula; La Meseta Formation; Palaeogene; early Sphenisciformes; cervicodorsal vertebrae.
Keywords: Antarktis; biologi; fossiler; morfologi; paleogen; pingviner

Decrease in stomach contents in the Antarctic minke whale (Balaenoptera bonaerensis) in the Southern Ocean - Konishi, Kenji; Hakamada, Takashi; Kiwada, Hiroshi; Kitakado, Toshihide; Walløe, Lars (Polar Biology, 2014)
Keywords: Sørishavet; hvaler; krill; marin biologi; observasjoner

Reassembling Gondwana: A new high quality constraint from vibroseis exploration of the sub-ice shelf geology of the East Antarctic continental margin - Kristoffersen, Yngve; Hofstede, Coen; Diez, Anja; Blenkner, Richard; Lambrecht, Astrid; Mayer, Christoph; Eisen, Olaf (Journal of Geophysical Research: Solid Earth, 2014)
The breakup of Gondwana is manifested by coeval early Jurassic Karoo magmatism in South Africa and East Antarctica. In South Africa, the large volumes of volcanic rocks of the adjoining Lebombo and Mwenetzi-Save monoclines represent a volcanic rift margin, and in East Antarctica, a corresponding feature, the Explora Wedge is buried below sediments and floating ice shelves on the continental margin of Dronning Maud Land. We use the seismic vibrator source to explore the sub-ice geology in Antarctica, and the new seismic reflection and available regional aeromagnetic data enable us to outline a dogleg landward extent of the Explora Wedge in Dronning Maud Land. The congruent inboard wedge geometries on the two continents define a high quality constraint, which facilitate for the first time, a geologically consistent and tight reconstruction of Africa relative to East Antarctica within Gondwana. The uncertainties in correlations of major geological features (mobile belts) from one continent to the other may now be of the order of ten's of kilometers rather than hundreds of kilometers.
Keywords: Antarktis; geofysikk; geologi; kontinentalmargin; seismologi; stratigrafi

Low melt rates with seasonal variability at the base of Fimbul Ice Shelf, East Antarctica, revealed by in situ interferometric radar measurements - Langley, Kirsty; Kohler, Jack; Sinisalo, Anna; Øyan, Mats Jørgen; Hamran, Svein Erik; Hattermann, Tore; Matsuoka, Kenichi; Nøst, Ole Anders; Isaksson, Elisabeth (Geophysical Research Letters, 2014)
Basal melt is a major cause of ice shelf thinning affecting the stability of the ice shelf and reducing its buttressing effect on the inland ice. The Fimbul ice shelf (FIS) in Dronning Maud Land (DML), East Antarctica, is fed by the fast-flowing Jutulstraumen glacier, responsible for 10% of ice discharge from the DML sector of the ice sheet. Current estimates of the basal melt rates of the FIS come from regional ocean models, autosub measurements, and satellite observations, which vary considerably. This discrepancy hampers evaluation of the stability of the Jutulstraumen catchment. Here, we present estimates of basal melt rates of the FIS using ground-based interferometric radar. We find a low average basal melt rate on the order of 1 m/yr, with the highest rates located at the ice shelf front, which extends beyond the continental shelf break. Furthermore, our results provide evidence for a significant seasonal variability.
Keywords: Dronning Maud Land; geofysikk; glasiologi; innlandsis; isbre; isshelf; kontinentalsokkel; smelting

Complex network of channels beneath an Antarctic ice shelf - Langley, Kirsty; von Deschwanden, Angela; Kohler, Jack; Sinisalo, Anna; Matsuoka, Kenichi; Hattermann, Tore; Humbert, Angelika; Nøst, Ole Anders; Isaksson, Elisabeth (Geophysical Research Letters, 2014)
Ice shelves play an important role in stabilizing the interior grounded ice of the large ice sheets. The thinning of major ice shelves observed in recent years, possibly in connection to warmer ocean waters coming into contact with the ice-shelf base, has focused attention on the ice-ocean interface. Here we reveal a complex network of sub ice-shelf channels under the Fimbul Ice Shelf, Antarctica, mapped using ground-penetrating radar over a 100 km2 grid. The channels are 300–500 m wide and 50 m high, among the narrowest of any reported. Observing narrow channels beneath an ice shelf that is mainly surrounded by cold ocean waters, with temperatures close to the surface freezing point, shows that channelized basal melting is not restricted to rapidly melting ice shelves, indicating that spatial melt patterns around Antarctica are likely to vary on scales that are not yet incorporated in ice-ocean models.
Keywords: Antarktis; glasiologi; innlandsis; isshelf; satellite bilder; satellite mikrobølgesensorer

Environmental influences on the at-sea behaviour of a major consumer, Mirounga leonina, in a rapidly changing environment - McIntyre, Trevor; Bornemann, Horst; de Bruyn, P J Nico; Reisinger, Ryan R; Steinhage, Daniel; Márquez, Maria E I; Bester, Marthán N; Plötz, Joachim (Polar Research, 2014)
Understanding the distribution and foraging ecology of major consumers within pelagic systems, specifically in relation to physical parameters, can be important for the management of bentho-pelagic systems undergoing rapid change associated with global climate change and other anthropogenic disturbances such as fishing (i.e., the Antarctic Peninsula and Scotia Sea). We tracked 11 adult male southern elephant seals (Mirounga leonina), during their five-month post-moult foraging migrations from King George Island (Isla 25 de Mayo), northern Antarctic Peninsula, using tags capable of recording and transmitting behavioural data and in situ temperature and salinity data. Seals foraged mostly within the Weddell–Scotia Confluence, while a few foraged along the western Antarctic Peninsula shelf of the Bellingshausen Sea. Mixed model outputs suggest that the at-sea behaviour of seals was associated with a number of environmental parameters, especially seafloor depth, sea-ice concentrations and the temperature structure of the water column. Seals increased dive bottom times and travelled at slower speeds in shallower areas and areas with increased sea-ice concentrations. Changes in dive depth and durations, as well as relative amount of time spent during the bottom phases of dives, were observed in relation to differences in overall temperature gradient, likely as a response to vertical changes in prey distribution associated with temperature stratification in the water column. Our results illustrate the likely complex influences of bathymetry, hydrography and sea ice on the behaviour of male southern elephant seals in a changing environment and highlight the need for region-specific approaches to studying environmental influences on behaviour. Keywords: Southern elephant seals; foraging ecology; satellite-relay data loggers; King George Island; Isla 25 de Mayo; at-sea behaviour.
Keywords: Sørishavet; batymetri; havis; klimaendringer; miljø; næring; seler; sjøis

Verification of a new NOAA/NSIDC passive microwave sea-ice concentration climate record - Meier, Walter N; Peng, Ge; Scott, Donna J; Savoie, Matt H (Polar Research, 2014)
A new satellite-based passive microwave sea-ice concentration product developed for the National Oceanic and Atmospheric Administration (NOAA) Climate Data Record (CDR) programme is evaluated via comparison with other passive microwave-derived estimates. The new product leverages two well-established concentration algorithms, known as the NASA Team and Bootstrap, both developed at and produced by the National Aeronautics and Space Administration (NASA) Goddard Space Flight Center (GSFC). The sea-ice estimates compare well with similar GSFC products while also fulfilling all NOAA CDR initial operation capability (IOC) requirements, including (1) self-describing file format, (2) ISO 19115-2 compliant collection-level metadata, (3) Climate and Forecast (CF) compliant file-level metadata, (4) grid-cell level metadata (data quality fields), (5) fully automated and reproducible processing and (6) open online access to full documentation with version control, including source code and an algorithm theoretical basic document. The primary limitations of the GSFC products are lack of metadata and use of untracked manual corrections to the output fields. Smaller differences occur from minor variations in processing methods by the National Snow and Ice Data Center (for the CDR fields) and NASA (for the GSFC fields). The CDR concentrations do have some differences from the constituent GSFC concentrations, but trends and variability are not substantially different. Keywords: Sea ice; Arctic and Antarctic oceans; climate data record; evaluation; passive microwave remote sensing.
Keywords: Sørishavet; evaluering; havis; klimaendringer; polarområdene; sjøis

Basal mass budget of Ross and Filchner-Ronne ice shelves, Antarctica, derived from Lagrangian analysis of ICESat altimetry - Moholdt, Geir; Padman, Laurie; Fricker, Helen Amanda (Journal of Geophysical Research: Earth Surface, 2014)
Traditional methods of deriving temporal variability of Antarctic ice-shelf elevation from satellite altimetry use a fixed (“Eulerian”) reference frame, where the measured changes include advection of ice thickness gradients between measurement epochs. We present a new method which removes advection effects by using an independent velocity field to compare elevations in a moving (“Lagrangian”) reference frame. Applying the technique to ICESat laser altimetry for the period 2003–2009 over the two largest Antarctic ice shelves, Ross and Filchner-Ronne, we show that the Lagrangian approach reduces the variability of derived elevation changes by about 50% compared to the Eulerian approach and reveals clearer spatial patterns of elevation change. The method simplifies the process of estimating basal mass budget from the residual of all other processes that contribute to ice-shelf elevation changes. We use field data and ICESat measurements over ice rises and the grounded ice sheet to account for surface accumulation and changes in firn air content, and remove the effect of ice-flow divergence using surface velocity and ice thickness data. The results show highest basal melt rates (>5 m a−1) near the deep grounding lines of major ice streams, but smaller melt rates (<5 m a−1) near the ice-shelf fronts are equally important to total meltwater production since they occur over larger areas. Integrating over the entire ice-shelf areas, we obtain basal mass budgets of −50 ± 64 Gt a−1 for Ross and −124 ± 66 Gt a−1 for Filchner-Ronne, with changes in firn air content as the largest error source.
Keywords: Sørishavet; batymetri; brehylle; geofysikk; innlandsis; isbrem; isshelf; oseanografi; satellite altimetri

Assessing the importance of human activities for the establishment of the invasive Poa annua in Antarctica - Molina-Montenegro, Marco A; Carrasco-Urra, Fernando; Acuña-Rodriguez, Ian; Oses, Rómulo; Torres-Diaz, Cristian; Chwedorzewska, Katarzyna J (Polar Research, 2014)
Because of its harsh environmental conditions and remoteness, Antarctica is often considered to be at low risk of plant invasion. However, an increasing number of reports have shown the presence and spread of non-native plants in Antarctica; it is therefore important to study which factors control the invasion process in this ecosystem. Here, we assessed the role of different human activities on the presence and abundance of the invasive Poa annua. In addition, we performed a reciprocal transplant experiment in the field, and a manipulative experiment of germination with P. annua and the natives Colobanthus quitensis and Deschampsia antarctica, in order to unravel the effects of physical soil disturbance on the establishment and survival of P. annua. We found a positive correlation between abundance of P. annua and level of soil disturbance, and that survival of P. annua was 33% higher in sites with disturbed soil than non-disturbed. Finally, we found that disturbance conditions increased germination for P. annua, whereas for native species germination in experimentally disturbed soil was either unchanged or reduced compared to undisturbed soil. Our results indicate that human activities that modify abiotic soil characteristics could play an important role in the abundance of this invasive species. If the current patterns of human activities are maintained in Antarctica, the establishment success and spread of P. annua could increase, negatively affecting native flora. Keywords: Alien species; Colobanthus quitensis; Deschampsia antarctica; human disturbance; Poa annua; tourists.
Keywords: Antarktis; biodiversitet; flora; menneskelig påvirkning; planter; turisme; økosystemer

Selected elements in surface waters of Antarctica and their relations with the natural environment - Nędzarek, Arkadiusz; Tórz, Agnieszka; Drost, Arkadiusz (Polar Research, 2014)
The aim of the study was to specify the concentration of selected chemical elements in surface waters of King George Island, off the western coast of the Antarctic Peninsula. The research encompassed six streams, a lake and an artificial water reservoir located on the western coast of Admiralty Bay. Measured hydrochemical parameters included pH, conductivity, total dissolved solids (TDS), and total and dissolved forms elements such as Al, Co, Ni, Cu, Zn, Cd, Pb, Mn, Fe, As and Se. The values of pH, conductivity and TDS had the following ranges: 6.09–8.21, 6.0–875 µS cm−1 and 7.0–975 mg/L, respectively, and were typical for surface waters of Antarctica. Wide disparities were discovered regarding concentrations of the investigated elements, ranging from <0.01 µg/L for Cd to 510 µg/L for Fe, and differing from one water body to another. The investigated elements are discussed with reference to environmental conditions and anthropogenic factors. Concentrations of total and dissolved forms of elements are considered in connection with the composition of soil in their surroundings and with atmospheric deposition, mostly such as that took place locally. The increased levels of Pb and Zn concentrations in the immediate proximity of a research station suggested anthropogenic contamination. Keywords: Antarctic surface waters; total and dissolved elements; baseline elements values; anthropogenic metal contamination.
Keywords: Antarktis; biologi; geokjemi; hydrokjemi; kjemiske analyser; overflatevann

Observations of cetaceans in the south-east Atlantic sector of the Southern Ocean, during summer 2008 - Nøttestad, Leif; Krafft, Bjørn; Søiland, Henrik; Skaret, Georg (Polar Biology, 2014)
Keywords: Sørishavet; hvaler; marin biologi; observasjoner; oseanografi

Deterrent activities in the crude lipophilic fractions of Antarctic benthic organisms: chemical defences against keystone predators - Núñez-Pons, Laura; Avila, Conxita (Polar Research, 2014)
Generalist predation constitutes a driving force for the evolution of chemical defences. In the Antarctic benthos, asteroids and omnivore amphipods are keystone opportunistic predators. Sessile organisms are therefore expected to develop defensive mechanisms mainly against such consumers. However, the different habits characterizing each predator may promote variable responses in prey. Feeding-deterrence experiments were performed with the circumpolar asteroid macropredator Odontaster validus to evaluate the presence of defences within the apolar lipophilic fraction of Antarctic invertebrates and macroalgae. A total of 51% of the extracts were repellent, yielding a proportion of 17 defended species out of the 31 assessed. These results are compared with a previous study in which the same fractions were offered to the abundant circum-Antarctic amphipod Cheirimedon femoratus. Overall, less deterrence was reported towards asteroids (51%) than against amphipods (80.8%), principally in sponge and algal extracts. Generalist amphipods, which establish casual host–prey sedentary associations with biosubstrata (preferentially sponges and macroalgae), may exert more localized predation pressure than sea stars on certain sessile prey, which would partly explain these results. The nutritional quality of prey may interact with feeding deterrents, whose production is presumed to be metabolically expensive. Although optimal defence theory posits that chemical defences are managed and distributed as to guarantee protection at the lowest cost, we found that only a few organisms localized feeding deterrents towards most exposed and/or valuable body regions. Lipophilic defensive metabolites are broadly produced in Antarctic communities to deter opportunistic predators, although several species combine different defensive traits. Keywords: Antarctic invertebrates; Antarctic algae; chemical ecology; sea star Odontaster validus; amphipod Cheirimedon femoratus; chemical defence.
Keywords: Antarktis; alger; kjemisk økologi; virvelløse dyr

Acidity decline in Antarctic ice cores during the Little Ice Age linked to changes in atmospheric nitrate and sea salt concentrations - Pasteris, Daniel; McConnell, Joseph R; Edwards, Ross; Isaksson, Elizabeth; Albert, Mary R (Journal of Geophysical Research: Atmospheres, 2014)
Acidity is an important chemical variable that impacts atmospheric and snowpack chemistry. Here we describe composite time series and the spatial pattern of acidity concentration (Acy = H+ − HCO3−) during the last 2000 years across the Dronning Maud Land region of the East Antarctic Plateau using measurements in seven ice cores. Coregistered measurements of the major ion species show that sulfuric acid (H2SO4), nitric acid (HNO3), and hydrochloric acid (HCl) determine greater than 98% of the acidity value. The latter, also described as excess chloride (ExCl−), is shown mostly to be derived from postdepositional diffusion of chloride with little net gain or loss from the snowpack. A strong inverse linear relationship between nitrate concentration and inverse accumulation rate provides evidence of spatially homogenous fresh snow concentrations and reemission rates of nitrate from the snowpack across the study area. A decline in acidity during the Little Ice Age (LIA, 1500–1900 Common Era) is observed and is linked to declines in HNO3 and ExCl− during that time. The nitrate decline is found to correlate well with published methane isotope data from Antarctica (δ13CH4), indicating that it is caused by a decline in biomass burning. The decrease in ExCl− concentration during the LIA is well correlated to published sea surface temperature reconstructions in the Atlantic Ocean, which suggests increased sea salt aerosol production associated with greater sea ice extent.
Keywords: Dronning Maud Land; glasiologi; holocene; hydrologi; iskjerner; lille istiden

Distribution of total alkalinity and pH in the Ross Sea (Antarctica) waters during austral summer 2008 - Rivaro, Paola; Messa, Roberta; Ianni, Carmela; Magi, Emanuele; Budillon, Giorgio (Polar Research, 2014)
Measurements of total alkalinity (AT) and pH were made in the Ross Sea in January–February 2008 in order to characterize the carbonate system in the Ross Sea and to evaluate the variability associated with different water masses. The main water masses of the Ross Sea, Antarctic Surface Water, High Salinity Shelf Water (HSSW), Deep Ice Shelf Water, Circumpolar Deep Water (CDW) and Antarctic Bottom Water, were identified on the basis of the physical and chemical data. In particular, the AT ranged between 2275 and 2374 µmol kg−1 with the lowest values in the surface waters (2275–2346 µmol kg−1), where the influence of the sea-ice melting and of the variability of the physical properties was significant. In the deep layers of the water column, the AT maxima were measured in correspondence to the preferential pathways of the spreading HSSW. The pH had variable values in the surface layer (7.890–8.033) with the highest values in Terra Nova Bay and Ross Sea polynyas. A low pH (7.969±0.025) traced the intrusion of the CDW in the Ross Sea shelf area. All samples revealed waters that were oversaturated with respect to both calcite and aragonite, but near corrosive levels of aragonite saturation state (Ω ca. 1.1–1.2) were associated with the entrainment of CDW over the slope. Aragonite undersaturation is of particular concern for the zooplankton species comprising to calcifying organisms such as pteropods. The partial pressure of CO2 at the sea surface was undersaturated with respect to the atmospheric value, particularly in Terra Nova Bay and the Ross Sea polynyas, but a large variability in the sea–air CO2 fluxes was observed associated with different responses in the strength of the biological and physical processes. Keywords: Total alkalinity; pH; saturation state; Terra Nova Bay polynya; Ross Sea.
Keywords: Rosshavet; Sørishavet; havis; hydrografi; hydrokjemi; kjemiske analyser; klimaendringer; kontinentalsokkel; sjøis; vannmasser; zooplankton

Norway in the Antarctic - Rognhaug, Magnus Hovind (ed.) (Norsk Polarinstitutt, Norge Utenriksdepartementet, 2014)
Keywords: Antarktis; Antarktistraktaten; Bouvetøya; Dronning Maud Land; Norge; Peter I. Øy; ekspedisjoner; forskningsstasjoner; forvaltning; hvalfangst; klima; klimaendringer; miljø; naturressursforvaltning; naturvitenskapelig; polarforskning; polarområdene

Recent climate tendencies on an East Antarctic ice shelf inferred from a shallow firn core network - Schlosser, Elisabeth; Anschütz, Helgard; Divine, Dmitry; Martma, Tõnu; Sinisalo, Anna; Altnau, Sebastian; Isaksson, Elisabeth (Journal of Geophysical Research: Atmospheres, 2014)
Nearly three decades of stable isotope ratios and surface mass balance (SMB) data from eight shallow firn cores retrieved at Fimbul Ice Shelf, East Antarctica, in the Austral summers 2009–2011 have been investigated. An additional longer core drilled in 2000/2001 extends the series back to the early eighteenth century. Isotope ratios and SMB from the stacked record of all cores were also related to instrumental temperature data from Neumayer Station on Ekström Ice Shelf. Since the second half of the twentieth century, the SMB shows a statistically significant negative trend, whereas the δ18O of the cores shows a significant positive trend. No trend is found in air temperature at the nearest suitable weather station, Neumayer (available since 1981). This does not correspond to the statistically significant positive trend in Southern Annular Mode (SAM) index, which is usually associated with a cooling of East Antarctica. SAM index and SMB are negatively correlated, which might be explained by a decrease in meridional exchange of energy and moisture leading to lower precipitation amounts. Future monitoring of climate change on the sensitive Antarctic ice shelves is necessary to assess its consequences for sea level change.
Keywords: Antarktis; brehylle; geofysikk; geologi; glasiologi; havnivåstigning; isbrem; isshelf; klimaendringer; meteorologi; stabile isotoper

Thermochronological data from the Dronning Maud Land Mountains, East Antarctica – a review - Sirevaag, Hallgeir; Jacobs, Joachim; Ksienzyk, Anna; Dunkl, István (14th International Conference on Thermochronology, 2014)
The paleo-topography of East Antarctica is highly relevant for the development of the East Antarctic ice-sheet. It is likely that the 1500 km long, coast-parallel Dronning Maud Land Mountains have resulted in a significant amount of precipitation prior to the initiation of the 34 Ma glaciation history of East Antarctica. Due to this, the paleo-topography should be used as an important input parameter for the glaciation history. The amount of quantitative measurements for the exhumation history of Antarctica is very limited as 98% of the continent is covered by ice. However, since the onset of thermochronological studies in the Dronning Maud Land Mountains in 1992, the area has been a subject of several thermochronological studies. The first thermochronological studies from Heimefrontfjella and Mannefjellknausane recorded a Jurassic thermal event associated with the Jurassic flood basalts related to the Karoo mantle plume and the rifting between East Antarctica and East Africa. Thermochronological data from Heimefrontfjella and Mannefjellknausane published by Jacobs and Lisker (1999) indicated that the Mesoproterozoic basement and the Permian sandstones were covered by 2000 meters of Jurassic flood basalt. In the Mühlig-Hofmann Mountains and the Gjelsvikfjella to the E, no significant Jurassic thermal event have been recorded. However, a combined titanite and apatite study by Emmel, et al. (2009) did not record any significant Jurassic thermal event in the Gjelsvikfjella and Mühlig-Hofmann Mountains. This has been used as a constraint for the lateral extent of the flood basalts. Also, the thermochronological analyses presented in Jacobs and Lisker (1999) indicated that the AFT ages get progressively older towards the SE. Based on these analyses; paleo-isotherms dipping towards the SE were suggested. In addition to the already published data, new, unpublished AHe data from a transect of the northern part of Jutulstraumen show relatively young ages at the rift flanks (~50 Ma) and progressively older ages further away from the rift flanks, indicating significant Cenozoic erosion (Ksienzyk et al., unpublished data). This is the basis for presently ongoing thermochronological studies.
Keywords: Dronning Maud Land; geovitenskap; paleoglasiologi; termokronologi

Accuracy assessment of global barotropic ocean tide models - Stammer, D; Ray, R D; Andersen, O B; Arbic, B K; Bosch, W; Carrère, L; Cheng, Y; Chinn, D S; Dushaw, B D; Egbert, G D; Erofeeva, S Y; Fok, H S; et al. (Reviews of Geophysics, 2014)
The accuracy of state-of-the-art global barotropic tide models is assessed using bottom pressure data, coastal tide gauges, satellite altimetry, various geodetic data on Antarctic ice shelves, and independent tracked satellite orbit perturbations. Tide models under review include empirical, purely hydrodynamic (“forward”), and assimilative dynamical, i.e., constrained by observations. Ten dominant tidal constituents in the diurnal, semidiurnal, and quarter-diurnal bands are considered. Since the last major model comparison project in 1997, models have improved markedly, especially in shallow-water regions and also in the deep ocean. The root-sum-square differences between tide observations and the best models for eight major constituents are approximately 0.9, 5.0, and 6.5 cm for pelagic, shelf, and coastal conditions, respectively. Large intermodel discrepancies occur in high latitudes, but testing in those regions is impeded by the paucity of high-quality in situ tide records. Long-wavelength components of models tested by analyzing satellite laser ranging measurements suggest that several models are comparably accurate for use in precise orbit determination, but analyses of GRACE intersatellite ranging data show that all models are still imperfect on basin and subbasin scales, especially near Antarctica. For the M2 constituent, errors in purely hydrodynamic models are now almost comparable to the 1980-era Schwiderski empirical solution, indicating marked advancement in dynamical modeling. Assessing model accuracy using tidal currents remains problematic owing to uncertainties in in situ current meter estimates and the inability to isolate the barotropic mode. Velocity tests against both acoustic tomography and current meters do confirm that assimilative models perform better than purely hydrodynamic models.

The influence of Nunataks on atmospheric boundary layer convection during summer in Dronning Maud Land, Antarctica - Stenmark, Aurora; Hole, Lars Robert; Voss, Paul; Reuder, Joachim; Jonassen, Marius O (Journal of Geophysical Research: Atmospheres, 2014)
The effects of nunataks on temperature profiles and wind patterns are studied using simulations from the Weather Research and Forecasting model. Simulations are compared to hourly observations from an automatic weather station located at the Troll Research Station in Dronning Maud Land. Areas of bare ground have been implemented in the model, and the simulations correspond well with meteorological measurements acquired during the 4 day simulation period. The nunataks are radiatively heated during daytime, and free convection occurs in the overlying atmospheric boundary layer. The inflow below the updraft forces strong horizontal convergence at the surface, whereas weaker divergence appears aloft. In a control run with a completely ice-covered surface, the convection is absent. In situ observations carried out by a remotely controlled balloon and a small model airplane compare well with model temperature profiles, but these are only available over the ice field upwind to the nunatak.
Keywords: Dronning Maud Land; atmosfæren; geofysikk; meteorologi; nunataker; observasjoner

Age-Related Mercury Contamination and Relationship with Luteinizing Hormone in a Long-Lived Antarctic Bird - Tartu, Sabrina; Bustamante, Paco; Goutte, Aurélie; Cherel, Yves; Weimerskirch, Henri; Bustnes, Jan Ove; Chastel, Olivier (PloS One, 2014)
Seabirds, as long-lived top predators, accumulate contaminants such as mercury (Hg), an established endocrine disruptor. In long lived species hormonal secretion varies with age; therefore, Hg-induced endocrine disruption may be exacerbated in some age classes. Here we investigated relationships between blood total Hg and luteinizing hormone (LH, a key pituitary hormone for the onset of breeding), in pre-laying known-age (11–45 years old) snow petrels (Pagodroma nivea) from Adélie Land, Antarctica. We predicted that 1) blood Hg would increase with advancing age as a consequence of bio-accumulation; and that 2) increasing blood Hg would be related to decreased concentrations of LH in the most Hg-contaminated individuals. Hg concentrations were higher in females than in males (p<0.001), and contrary to our prediction, decreased with advancing age in males (p = 0.009) and tended to do so in females (p = 0.06). The analysis of stable isotopes (δ13C and δ15N) suggested that this unexpected pattern could originate from age and sex-related variations in trophic niche, and hence Hg exposure. Regarding LH, our prediction was only supported in young birds (≤23 years) where baseline LH was inversely correlated with Hg concentrations (p = 0.04). Hg burden did not predict baseline LH or GnRH-induced LH in birds that were more than 23 years old. These results show that age and contaminants may interfere with major endocrine mechanisms and, together with other recent studies, support the view that Hg could be connected to LH secretion and could then impair the fitness of long-lived birds.
Publisher: Public Library of Science
Keywords: Antarktis; forurensning; kjemiske analyser; miljø; nevrobiologi; ornitologi; petreller; sjøfugler; stabile isotoper; zoologi; økologiske nisjer

Atmosphere–sea ice interaction in early summer in the Antarctic: evaluation and challenges of a regional atmospheric model - Valkonen, T.; Vihma, T.; Johansson, M. M.; Launiainen, J. (Quarterly Journal of the Royal Meteorological Society, 2014)
Antarctic sea ice areas have only been the main focus for a few studies combining observations and three-dimensional atmospheric model experiments. This study presents simulations over the Weddell Sea in early summer, applying the polar-optimized version of the Weather Research and Forecasting model (Polar WRF). The results are compared against observations from the drifting experiment Ice Station Polarstern, which took place on 28 November 2004?2 January 2005. The Polar WRF model showed good skill in simulating synoptic-scale variations. The diurnal cycles of surface variables were reproduced, but the amplitude was overestimated for most of the variables and the simulations were characterized by a cold temperature bias at night. The major challenges related to the modelling of the atmosphere over Antarctic sea ice were found to be associated with clouds, atmospheric boundary-layer processes and processes in the sea ice and snow layer. Temporal variations in the errors in cloud cover generated large errors in long-wave radiation fluxes. In the boundary layer, the overestimated downward sensible heat flux was partly compensated for by the underestimated downward long-wave radiation at the surface. The underestimated downward long-wave flux started to dominate as the stability increased and generated the cold temperature bias at the surface. Problems with the surface energy balance, as found in this study, could be reduced by applying more advanced schemes for snow and ice thermodynamics.
Publisher: John Wiley & Sons, Ltd
Keywords: Sørishavet; Weddellhavet; atmosfæren; havis; meteorologi; sjøis

Atmospheric trace elements in aerosols observed over the Southern Ocean and coastal East Antarctica - Xu, Guojie; Gao, Yuan (Polar Research, 2014)
Atmospheric aerosol samples were collected over the Southern Ocean (SO) and coastal East Antarctica (CEA) during the austral summer of 2010/11. Samples were analysed for trace elements, including Na, Mg, K, Al, Fe, Mn, Ni, Cd and Se, by inductively coupled plasma mass spectrometry (ICP-MS). The mean atmospheric concentrations over the SO were 1100 ng m−3 for Na, 190 ng m−3 for Mg, 150 ng m−3 for Al, 14 ng m−3 for Fe, 0.46 ng m−3 for Mn and 0.25 ng m−3 for Se. Over CEA, the mean concentrations were 990 ng m−3 for Na, 180 ng m−3 for Mg, 190 ng m−3 for Al, 26 ng m−3 for Fe, 0.70 ng m−3 for Mn and 0.29 ng m−3 for Se. Particle size distributions, enrichment factors (EFs) and correlation analysis indicate that Na, Mg and K mainly came from the marine source, while Al, Fe and Mn were mainly from the crustal source, which also contributed to Mg and K over CEA. High EFs were associated with Ni, Cd and Se, suggesting likely contributions from mixed sources from the Antarctic continent, long-range transport, marine biogenic emissions and anthropogenic emissions. Sea-salt elements (Na, Mg, K) were mainly accumulated in the coarse mode, and crustal elements (Al, Fe, Mn) presented a bimodal size distribution pattern. Bioactive elements (Fe, Ni, Cd) were enriched in the fine mode, especially with samples collected over the SO, possibly affecting biogeochemical cycles in this oceanic region. Keywords: Southern Ocean; coastal East Antarctica; trace elements; size distribution; sources.
Keywords: Sørishavet; atmosfærisk aerosol; biogeokjemi; kjemiske analyser; meteorologi

Wind-driven spreading of fresh surface water beneath ice shelves in the Eastern Weddell Sea - Zhou, Qiming; Hattermann, Tore; Nøst, Ole Anders; Biuw, Martin; Kovacs, Kit M; Lydersen, Christian (Journal of Geophysical Research: Oceans, 2014)
Abstract Solar heated, fresh Antarctic Surface Water (ASW) is a permanent feature along the Eastern Weddell Sea (EWS) coast in summer down to a depth of roughly 200 m. Recently, ASW has been observed beneath the Fimbul Ice Shelf, suggesting that it might play an important role in basal melting. We propose that wind-driven coastal downwelling is the main mechanism that spreads ASW beneath the ice shelf in this sector of Antarctica. We validate this hypothesis with observations, scaling analyses, and numerical modeling, along three principle lines: (i) data analyses of about 1500 salinity profiles collected by instrumented seals indicate that the observed freshening of the coastal water column is likely explained by the on-shore Ekman transport and subsequent downwelling of ASW; (ii) an analytical model of the coastal momentum balance indicates that wind-driven downwelling is capable of depressing the buoyant surface water to a depth similar to the ice shelf draft; and (iii) simulations from both idealized and regional eddy-resolving numerical ice shelf/ocean models support our proposition. Our main conclusion is that wind-driven spreading of ASW beneath the ice shelf occurs when downwelling exceeds the depth of the ice shelf base. Furthermore, our study adds to the understanding of the oceanic processes at the Antarctic Slope Front in the EWS, with possible implications for other sectors of Antarctica.
Keywords: Sørishavet; Weddellhavet; isbrem; isshelf; oseanografi; overflatevann; smelting; vannmasser; vannvirvler

Norske krav i Sørishavet - Utfordringer for Sjøforsvaret - Aase, Johnny Grøneng (Norsk Tidsskrift for Sjøvesen, 2013)
Norge gjorde i 2009 krav på økonomiske soner utenfor Bouvetøya og Dronning Maud Land. Slike krav fører i følge Lov om økonomiske soner med seg forpliktelser som over tid får konsekvenser for Sjøforsvaret. l den økonomiske sonen som ble erklært utenfor fastlands-Norge på 1970-tallet har det vært Kystvakten som har opprettholdt juridiksjon, overvåket miljøet og kontrollert fisket. Norske og utenlandsk fartøyer har alt begynt å fiske i norsk økonomisk sone utenfor Bouvetøya. Det foregår i dag en rivende utvikling av teknologi for gruvedrift på store havdyp. Statlige og kommersielle private aktører posisjonerer seg aktivt for å kunne utnytte naturressursene i Sørishavet. Denne forfatteren mener at det vil tvinge seg fram et behov for stedlig overvåkning, kontroll og miljøvern i de norske økonomiske sonene i Antarktis. Det eksisterer ingen robust søk- og redningstjeneste i Antarktis. Siden Norge har gjort territorielle krav har vi også en moralsk forpliktelse om å kunne komme skipbrudne og syke til unnsetning i disse områdene. Overvåkning og hevding av juridiksjon i slike store og fjerntliggende havområder vil bli komplisert og dyrt. Kystvakten har i dag verken fartøyer eller personell for å kunne utføre dette. Rundt 2020 vil de store kystvaktskipene Nordkapp, Senja og Andenes være rundt 40 år og nærme seg tidspunktet for utfasing. Klimaendringene fører til migrasjon av fisk nordover mot kaldere vann i Barentshavet, og det vil derfor bli behov for fiskeriinspeksjoner lenger nord enn i dag. Kystvakten trenger å anskaffe store erstatningsfartøy for Nordkapp-klassen, og ved prosjekteringen bør man ta høyde for at Norge også vil ha behov for en kystvaktkapasitet i Antarktis. For å redusere risikoen for over- eller feilinvesteringer vil jeg gjennomgå hvordan en allerede i dag kan benytte satellitter for å kartlegge skipstrafikken i de norske områdene i sør. Ut fra dette bakgrunnsmaterialet kan Forsvaret anslå hvor mange fartøyer som vil være nødvendig å ha i sør.
Publisher: Sjømilitære samfund
Keywords: Bouvetøya; Dronning Maud Land; Sørishavet; havrett; jus; miljøovervåking; miljøvern; naturressurser; økonomi

Eddy-Driven Exchange between the Open Ocean and a Sub–Ice Shelf Cavity - Årthun, Marius; Holland, Paul R; Nicholls, Keith William; Feltham, Daniel L (Journal of Physical Oceanography, 2013)
Keywords: Sørishavet; Weddellhavet; isshelf; oseanografi; sjøvirvler; vannvirvler

A Crisis that Never Came: The decline of the Antarctic Whaling Industry in the 1950s and 1960s - Basberg, Bjørn L (The Mariner's Mirror, 2013)
Publisher: Routledge
Keywords: Norge; Sørishavet; hvalfangere; hvalfangst; pelagisk; økonomi

At-sea behaviour of three krill predators breeding at Bouvetøya—Antarctic fur seals, macaroni penguins and chinstrap penguins - Blanchet, Marie-Anne; Biuw, Martin; Hofmeyr, Greg; de Bruyn, P. J. Nico; Lydersen, Christian; Kovacs, Kit M. (Marine Ecology Progress Series, 2013)
Keywords: Bouvetøya; krill; pelsseler; pingviner; pinnipedier; plankton; seler; zoologi

Changing the Look on Seals from Pole to Pole with Satellite Technology - Blix, Arnoldus Schytte; Folkow, Lars P; Nordøy, Erling S (Adaptation and Evolution in Marine Environments, Volume 2: The Impacts of Global Change on Biodiversity, 2013)
Keywords: Sørishavet; marin biologi; observasjoner; pattedyr; seler; sjøpattedyr

On-site and in situ remediation technologies applicable to metal-contaminated sites in Antarctica and the Arctic: a review - Camenzuli, Danielle; Freidman, Benjamin L; Statham, Tom M; Mumford, Kathryn A; Gore, Damian B (Polar Research, 2013)
Effective management of contaminated land requires a sound understanding of site geology, chemistry and biology. This is particularly the case for Antarctica and the Arctic, which function using different legislative frame- works to those of industrialized, temperate environments and are logistically challenging environments to operate in. This paper reviews seven remediation technologies currently used, or demonstrating potential for on-site or in situ use at metal-contaminated sites in polar environments, namely permeable reactive barriers (PRB), chemical fixation, bioremediation, phytoremediation, electrokinetic separation, land capping, and pump and treat systems. The technologies reviewed are discussed in terms of their advantages, limitations and overall potential for the management of metal-contaminated sites in Antarctica and the Arctic. This review demonstrates that several of the reviewed technologies show potential for on-site or in situ usage in Antarctica and the Arctic. Of the reviewed technologies, chemical fixation and PRB are particularly promising technologies for metal-contaminated sites in polar environments. However, further research and relevant field trials are required before these technologies can be considered proven techniques. Keywords: Polar; heavy metals; remediation; contaminants; in situ
Keywords: Antarktis; biologi; forurensning; geologi; jord; kjemi; menneskelig påvirkning; polarområdene; tungmetaller

Reading and thinking about International Polar Years: five recent books - Carlson, Dave (Polar Research, 2013)
Within the polar science community the Polar (and Geophysical) Years represent signal events. We often read, largely within geoscience literature, that those events represented positive and dramatic steps forward in international science. From five recent books - two historical compilations and three personal narratives - augmented by interviews with a few key participants, a more cautious picture emerges, of remarkable successes but also of occasional or even persistent missteps and deficiencies. An improved understanding of the IPY concept and experience can provide useful guidance for future polar and global science. Keywords: International Polar Year; International Geophysical Year; international science; history of polar science.
Keywords: Antarktis; Det internasjonale geofysiske år (IGY); IPY; bokanmeldelser; internasjonal; politikk; samarbeid; vitenskap

Dietary overlap in inshore notothenioid fish from the Danco Coast, western Antarctic Peninsula - Casaux, Ricardo; Barrera-Oro, Esteban (Polar Research, 2013)
We carried out a dietary overlap analysis between notothenioid species by examining the stomach contents of more than 900 specimens collected in a fish assemblage at the Danco Coast, western Antarctic Peninsula, in the summer of 2000. Prey reoccurrences among fish species were 32.2%, with krill Euphausia superba, salps and the gammaridean Prostebeingia longicornis the most reoccurring prey. The diet similarity between species pairs was lower than 55%, in accordance with similar fish assemblages in the South Orkney Islands, the South Shetland Islands and the Antarctic Peninsula. Whereas at those localities the higher prey overlap was between krill-feeding fish species, at the Danco Coast it was between Trematomus bernacchii and Lepidonotothen nudifrons, Notothenia coriiceps and Notothenia rossii, Notothenia coriiceps and Parachaenichthyis charcoti, and Trematomus newnesi and Notothenia rossii, which shared primarily gammaridean amphipods, algae, fish and krill, respectively. Krill is normally the main prey of fish in summer in inshore waters of the western Antarctic Peninsula, but its density in January/February 2000 was notably lower than in previous years. Therefore, at the Danco Coast, under conditions of krill shortage, most of the notothenioid species foraged more intensively on alternative prey, such as gammarideans, fish and algae. The difference between areas in the pattern of dietary overlap might be related to differences in prey availability between years and to the degree of competition for targeted prey. Keywords: Fish dietary overlap; notothenioid fish; Antarctic Peninsula.
Keywords: Sørishavet; fisker; forskning; krill; marin biologi; plankton; økosystemer

Using visible reflectance spectroscopy to reconstruct historical changes in chlorophyll a concentration in East Antarctic ponds - Chen, Qianqian; Liu, Xiaodong; Nie, Yaguang; Sun, Liguang (Polar Research, 2013)
The visible reflectance spectroscopy (VRS) and chlorophyll a concentration were determined in three sediment profiles collected from East Antarctica to investigate the potential application of VRS in reconstructing historical changes in Antarctic lake primary productivity. The results showed that the appearance of a trough at 650–700 nm is an important marker for chlorophyll a concentration and can therefore be used to distinguish the sedimentary organic matter source from guano and algae. The measured chlorophyll a content had significant positive correlations with the trough area between 650 and 700 nm, and no distinct trough was found in the sediments with organic matter completely derived from guano. Modelling results showed that the spectra spectrally inferred chlorophyll a content, and the measured data exhibit consistent trends with depth, showing that the dimensionless trough area can serve as an independent proxy for reconstructing historical fluctuations in the primary production of Antarctic ponds. The correlation of phosphorus (P) with measured and inferred chlorophyll a contents in ornithogenic sediments near penguin colonies indicates that the change in primary productivity in the Antarctic ponds investigated was closely related to the amount of guano input from these birds. Keywords: Reflectance spectroscopy; ornithogenic sediments; chlorophyll a; Antarctic ponds; primary productivity; VRS.
Keywords: Antarktis; alger; biogeokjemi; fytoplankton; innsjø; pingviner; sedimenter; sjøfugler

Tintinnid ciliates of Amundsen Sea (Antarctica) plankton communities - Dolan, John R; Yang, Eun Jin; Lee, Sang Hoon; Kim, Sun Young (Polar Research, 2013)
The Amundsen Sea has been described as one of the most productive and dynamic pelagic systems in Antarctica and is one of the least studied. Based on samples from 15 stations in the Amundsen Sea, we describe for the first time the composition of the tintinnid ciliate assemblage of the microzooplankton. We compared the species compositions of coastal polynya sites, where the phytoplankton communities are dominated by Phaeocystis, to those of the offshore deep water sites, which are dominated by diatoms. We found a total of 15 species. Polynya sites were dominated by a few species of tintinnids, mostly those endemic to the Southern Ocean. In contrast, the deep-water sites contained many widespread tintinnid species, which are known from a wide variety of systems as well as other areas of the Southern Ocean. We examined polymorphism known to characterize the Antarctic tintinnid species Cymatocylis affinis/convallaria and Codonellopsis gaussi. We found that the types or forms found appeared unrelated to the type of microplankton community, defined by the identity of the dominant phytoplankton taxa. However, the number of different morphotypes found at a site appeared related to the overall concentration of the species, suggesting that different morphologies, previously considered distinct species, may simply be developmental stages. Keywords: Zooplankton; microzooplankton; polynya; protists; Phaeocystis; diatoms.
Keywords: Sørishavet; diatomeer; fytoplankton; marin biologi; oseanografi; protoktister; zooplankton; økologi

Bedmap2: improved ice bed, surface and thickness datasets for Antarctica - Fretwell, Peter; Pritchard, Hamish; Vaughan, David; Bamber, Jonathan; Barrand, N; Bell, Robin; Bianchi, Cesidio; Bingham, R; Blankenship, D; Casassa, Gino; Catania, G; Callens, D; et al. (The Cryosphere, 2013)
We present Bedmap2, a new suite of gridded products describing surface elevation, ice-thickness and the seafloor and subglacial bed elevation of the Antarctic south of 60° S. We derived these products using data from a variety of sources, including many substantial surveys completed since the original Bedmap compilation (Bedmap1) in 2001. In particular, the Bedmap2 ice thickness grid is made from 25 million measurements, over two orders of magnitude more than were used in Bedmap1. In most parts of Antarctica the subglacial landscape is visible in much greater detail than was previously available and the improved data-coverage has in many areas revealed the full scale of mountain ranges, valleys, basins and troughs, only fragments of which were previously indicated in local surveys. The derived statistics for Bedmap2 show that the volume of ice contained in the Antarctic ice sheet (27 million km3) and its potential contribution to sea-level rise (58 m) are similar to those of Bedmap1, but the mean thickness of the ice sheet is 4.6% greater, the mean depth of the bed beneath the grounded ice sheet is 72 m lower and the area of ice sheet grounded on bed below sea level is increased by 10%. The Bedmap2 compilation highlights several areas beneath the ice sheet where the bed elevation is substantially lower than the deepest bed indicated by Bedmap1. These products, along with grids of data coverage and uncertainty, provide new opportunities for detailed modelling of the past and future evolution of the Antarctic ice sheets.
Publisher: Copernicus Publications
Keywords: Antarktis; glasiologi

Abundance and breeding distribution of seabirds in the northern part of the Danco Coast, Antarctic Peninsula - González-Zevallos, Diego; Santos, M Mercedes; Rombolá, Emilce F; Juáres, Mariana A; Coria, Néstor R (Polar Research, 2013)
Seabird abundances and breeding distribution have the potential to serve as ecological indicators. The western Antarctic Peninsula is one of the three sites in the world with the greatest increases in local temperature during the last 50 years. The aim of this study was to monitor the distribution and abundance of breeding populations of seabirds in the northern sector of the Danco Coast, north-west of the Antarctic Peninsula, during the breeding season 2010/11. The birds were the Wilson's storm petrel (Oceanites oceanicus), South Polar skua (Stercorarius maccormicki), kelp gull (Larus dominicanus), Antarctic tern (Sterna vittata), snowy sheathbill (Chionis alba), chinstrap penguin (Pygoscelis antarctica), southern giant petrel (Macronectes giganteus), gentoo penguin (Pygoscelis papua), Cape petrel (Daption capense) and Antarctic shag (Phalacrocorax bransfieldensis). Annual breeding population growth increased in pygoscelids, southern giant petrel and sheathbill, and for the remaining species, breeding population trends were stable. Given that seabird populations can provide valuable information on the conditions of their feeding and nesting environments, this study highlights the need to maintain basics monitoring studies. Keywords: Seabird abundances; breeding distribution; Danco Coast; Antarctic Peninsula.
Keywords: Antarktis; klimaendringer; ornitologi; petreller; sjøfugler; temperatur

Fornuft og følelser? : forståelser og forvaltning av hval og hvalfangst - Haugdahl, Morten (Norges teknisk-naturvitenskapelige universitet, 2013)
Norge hadde en dominerende posisjon i fortidas industrielle hvalfangst, og har også hatt en viktig rolle i konfliktene omkring den gjenværende fangsten av hval i dag. Hvalene har i løpet av denne tiden gått fra å være objekter i et økonomisk ”eventyr”, til å bli symbol for miljøbevissthet, hvor kampen om hvalfangsten har blitt framstilt som den definerende globale miljøkonflikten siden 1970-tallet. I denne avhandlingen blir endringer i forståelser av hvalen og hvalfangsten gjennom den moderne hvalfangstens historie undersøkt. Avhandlingen viser hvordan endringene kom til uttrykk i forvaltning, men også i norsk og internasjonal offentlighet, slik som i medier og i populærkultur. Teoretisk og metodisk har arbeidet gjort bruk av innrammingsbegrepet. Avhandlingen bruker i så måte innramming for å vise hvordan oppfatninger av hvalen og hvalfangsten har blitt fremstilt, forhandlet og ført til nye innramminger, og hvordan ulike forståelser og prosesser enkelte ganger har eksistert side ved side og i konflikt. For eksempel rammes hvalen inn som en økonomisk ressurs, som økologiske bestander som risikerer utryddelse, og som sansbare og sansende medskapninger. De ulike innrammingene fører igjen til vektlegging av ulike hensyn, men også til ulike former for kunnskap og forvaltning. Norway had a dominant role in the industrial whaling of the past, but has also had a central position in the conflicts around the remaining whaling of today. From being prized objects in an economic “adventure” whales have become a symbol of environmental awareness, and the disagreements on whaling has sometimes been perceived as the definite global environmental conflict since the 1970’s. This dissertation examines changes in understandings and management of whales and whaling through the history of modern whaling. The work shows how changes in perceptions of the whale have affected the administrative bodies of whaling and developed in Norwegian and international public debate, as in media and popular culture. Theoretically and methodically this work leans on the concept of “framing”. The dissertation uses framing to show how changes in the perception of whaling have been negotiated, leading to new framings of whales and whaling, and how some of these different understandings and processes have existed side by side, often in conflict with each other. The whale is for example at the same time framed as an economic resource, as scarce ecological stocks in risk of extinction, and as perceptible and sentient fellow beings. These frames lead to different considerations and emphasis, but also to different types of knowledge and management
Publication Title: Det humanistiske fakultet, Institutt for tverrfaglige kulturstudier Volume: Philosophiae doctor Issue: 2013:123 ISBN: 9788247143483
Keywords: Sørishavet; bioetikk; dyrevelferd; forvaltning; hvalfangst; hvalfangstkommisjonen; internasjonale; kulturstudier; miljøvern

Assessing the potential of calcium-based artificial ocean alkalinization to mitigate rising atmospheric CO2 and ocean acidification - Ilyina, Tatiana; Wolf-Gladrow, Dieter; Munhoven, Guy; Heinze, Christoph (Geophysical Research Letters, 2013)
Enhancement of ocean alkalinity using calcium compounds, e.g., lime has been proposed to mitigate further increase of atmospheric CO2 and ocean acidification due to anthropogenic CO2 emissions. Using a global model, we show that such alkalinization has the potential to preserve pH and the saturation state of carbonate minerals at close to today's values. Effects of alkalinization persist after termination: Atmospheric CO2 and pH do not return to unmitigated levels. Only scenarios in which large amounts of alkalinity (i.e., in a ratio of 2:1 with respect to emitted CO2) are added over large ocean areas can boost oceanic CO2 uptake sufficiently to avoid further ocean acidification on the global scale, thereby elevating some key biogeochemical parameters, e.g., pH significantly above preindustrial levels. Smaller-scale alkalinization could counteract ocean acidification on a subregional or even local scale, e.g., in upwelling systems. The decrease of atmospheric CO2 would then be a small side effect.
Keywords: Sørishavet; biogeokjemi; havalkalisering; klimatologi; meteorologi; modeller

Low frequency variability on the continental slope of the southern Weddell Sea - Jensen, Mari F; Fer, Ilker; Darelius, Elin (Journal of Geophysical Research: Oceans, 2013)
One-year long records of temperature, salinity, and currents show seasonally varying, energetic oscillations with a dominant period of approximately 35 h on the upper continental slope of the southern Weddell Sea. The data set is sampled by five moorings deployed on the slope of the Crary Fan, east of the main outflow site of the Filchner overflow plume. The characteristics of the observed oscillations are compared to idealized coastal trapped waves inferred from a numerical code. The variability at 35 h period is identified as mode 1 waves with wavelengths less than 200 km and group velocity opposing the phase speed, indicating energy propagation toward east. Filchner Depression and the nearby ridges on the slope are suggested as the generation site where the dynamics associated with the overflow plume can force the variability. Historical time series at the overflow site are revisited to identify the source of previously reported variability at 3 and 6 day time scales. Mode 2 waves at wavelengths of about 100 and 1000 km were found to bear resemblance to the 3 day and 6 day variability, respectively. The seasonal variation in the energy in the 35 h band shows small but significant correlation with the low frequency easterly winds. The presence of coastal trapped waves along the continental slope of the Weddell Sea can increase the heat exchange across the shelf break and affect the dense water production rates.
Keywords: Sørishavet; Weddellhavet; batymetri; bunnvann; geofysikk; havstrømmer; kelvinbølger; saltinnhold; temperatur måling

The impact of abrupt suspension of solar radiation management (termination effect) in experiment G2 of the Geoengineering Model Intercomparison Project (GeoMIP) - Jones, Andy; Haywood, Jim M; Alterskjær, Kari; Boucher, Olivier; Cole, Jason N S; Curry, Charles L; Irvine, Peter J; Ji, Duoying; Kravitz, Ben; Egill Kristjánsson, Jón; Moore, John C; Niemeier, Ulrike; et al. (Journal of Geophysical Research: Atmospheres, 2013)
We have examined changes in climate which result from the sudden termination of geoengineering after 50 years of offsetting a 1% per annum increase in CO2 concentrations by a reduction of solar radiation, as simulated by 11 different climate models in experiment G2 of the Geoengineering Model Intercomparison Project. The models agree on a rapid increase in global-mean temperature following termination accompanied by increases in global-mean precipitation rate and decreases in sea-ice cover. There is no agreement on the impact of geoengineering termination on the rate of change of global-mean plant net primary productivity. There is a considerable degree of consensus for the geographical distribution of temperature change following termination, with faster warming at high latitudes and over land. There is also considerable agreement regarding the distribution of reductions in Arctic sea-ice, but less so for the Antarctic. There is much less agreement regarding the patterns of change in precipitation and net primary productivity, with a greater degree of consensus at higher latitudes.
Keywords: Antarktis; global oppvarming; karbondioksid; klimaendringer; klimamodeller; klimatologi; polarområdene; solstråling

Better late than never? Interannual and seasonal variability in breeding chronology of gentoo penguins at Stranger Point, Antarctica - Juáres, Mariana A; Santos, M Mercedes; Negrete, Javier; Santos, M Rita; Mennucci, Jorge A; Rombolá, Emilce; Longarzo, Lucrecia; Coria, Néstor R; Carlini, Alejandro R (Polar Research, 2013)
Rapid climate change recorded in the western Antarctic Peninsula confronts species with less predictable conditions in the marine and terrestrial environments. We analysed the breeding chronology and nesting site selection of gentoo penguins (Pygoscelis papua) at King George Island (Isla 25 de Mayo), Antarctica, during four seasons in which differences in snow presence and persistence on the ground were observed. We recorded an overall delay as well as seasonal asynchrony at the beginning of reproduction for those years with higher snow deposition. A redistribution of breeding groups was also observed. Nevertheless, the population breeding success and chicks’ weight at fledging remained relatively constant, despite the delay in breeding chronology, the increased duration of foraging trips during the guard stage and the decreased weight of stomach contents during the crèche stage. We suggest that the plasticity of their trophic biology, along with the flexibility of their breeding phenology and relocation of breeding groups, may be complementary reasons why gentoo penguin populations in the region have remained stable in spite of the changing conditions currently registered. Keywords: Antarctica; breeding delay; breeding phenology; snow; Pygoscelis papua; Euphausia superba.
Keywords: Antarktis; klimaendringer; krill; observasjoner; pingviner; plankton; reproduksjon; snø; zoologi

Long-term monitoring of persistent organic pollutants (POPs) at the Norwegian Troll station in Dronning Maud Land, Antarctica - Kallenborn, Roland; Breivik, Knut; Eckhardt, Sabine; Lunder, C R; Manø, S; Schlabach, Martin; Stohl, Andreas (Atmospheric Chemistry and Physics (Print), 2013)
A first long-term monitoring of selected persistent organic pollutants (POPs) in Antarctic air has been conducted at the Norwegian research station Troll (Dronning Maud Land). As target contaminants 32 PCB congeners, α- and γ-hexachlorocyclohexane (HCH), trans- and cis-chlordane, trans- and cis-nonachlor, p,p'- and o,p-DDT, DDD, DDE as well as hexachlorobenzene (HCB) were selected. The monitoring program with weekly samples taken during the period 2007–2010 was coordinated with the parallel program at the Norwegian Arctic monitoring site (Zeppelin mountain, Ny-Ålesund, Svalbard) in terms of priority compounds, sampling schedule as well as analytical methods. The POP concentration levels found in Antarctica were considerably lower than Arctic atmospheric background concentrations. Similar to observations for Arctic samples, HCB is the predominant POP compound, with levels of around 22 pg m−3 throughout the entire monitoring period. In general, the following concentration distribution was found for the Troll samples analyzed: HCB > Sum HCH > Sum PCB > Sum DDT > Sum chlordanes. Atmospheric long-range transport was identified as a major contamination source for POPs in Antarctic environments. Several long-range transport events with elevated levels of pesticides and/or compounds with industrial sources were identified based on retroplume calculations with a Lagrangian particle dispersion model (FLEXPART).
Publisher: Copernicus Publications
Keywords: Dronning Maud Land; Troll forskningsstasjon; atmosfæren; forurensning; miljøgifter; miljøovervåking

Standardized algal growth potential and/or algal primary production rates of maritime Antarctic stream waters (King George Island, South Shetlands) - Kvíderová, Jana; Elster, Josef (Polar Research, 2013)
In addition to the chemical analyses providing total nutrient content, standardized water trophic status bioassays are useful in the determination of available nutrients for primary producers. The aim of the study was to determine the standardized values of algal growth potential (AGP) and algal primary productivity rate (APPR) of maritime Antarctic stream water using modified AGP/APPR protocols. The standardized values of AGP and the APPR of oligotrophic and mesotrophic water samples from snow-melt streams were measured, and possible nutrient limitation and heavy metal inhibition were evaluated at 5°C and 25°C using polar and temperate strains of Stichococcus bacillaris, respectively. The water samples were enriched for the nutrient limitation tests with 1000 mμ l-1 NO3- -N, 50 μg l-1 PO43- -P, and a mixture of 1000 μg l-1 NO3- -N + 50 μg l-1 PO43- -P, and for the heavy metal inhibition tests with 1000 mg l-1 Na2-ethylenediaminetetraacetic acid (EDTA). The AGP of oligotrophic samples was significantly lower than that of the mesotrophic ones at both temperatures. In addition, AGP was significantly higher at 5°C than at 25°C. Oligotrophic samples were identified as being nitrogen limited, while no nutrient limitation was observed in the mesotrophic samples. No statistically significant heavy metal inhibition was observed at either temperature. The positive correlation of AGP and water nutrient content indicates that the method used accurately and comprehensively monitors the changes in biological availability of mineral nutrients and can provide a standardized reference point for similar exploration of freshwater ecosystems across both polar regions. Keywords: Maritime Antarctic; microalgae; nutrient limitations; snow-melt stream water.
Keywords: Antarktis; alger; analyser; ferskvann; innsjø; kjemisk; klimaendringer; næringsstoff; polarområdene; snø; strøm; økosystemer

Recent snowfall anomalies in Dronning Maud Land, East Antarctica, in a historical and future climate perspective - Lenaerts, Jan T M; van Meijgaard, Erik; van den Broeke, Michiel R; Ligtenberg, Stefan R M; Horwath, Martin; Isaksson, Elisabeth (Geophysical Research Letters, 2013)
Enhanced snowfall on the East Antarctic ice sheet is projected to significantly mitigate 21st century global sea level rise. In recent years (2009 and 2011), regionally extreme snowfall anomalies in Dronning Maud Land, in the Atlantic sector of East Antarctica, have been observed. It has been unclear, however, whether these anomalies can be ascribed to natural decadal variability, or whether they could signal the beginning of a long-term increase of snowfall. Here we use output of a regional atmospheric climate model, evaluated with available firn core records and gravimetry observations, and show that such episodes had not been seen previously in the satellite climate data era (1979). Comparisons with historical data that originate from firn cores, one with records extending back to the 18th century, confirm that accumulation anomalies of this scale have not occurred in the past ~60 years, although comparable anomalies are found further back in time. We examined several regional climate model projections, describing various warming scenarios into the 21st century. Anomalies with magnitudes similar to the recently observed ones were not present in the model output for the current climate, but were found increasingly probable toward the end of the 21st century.
Keywords: Dronning Maud Land; glasiologi; global oppvarming; havnivåstigning; innlandsis; klimaendringer; klimatologi

Automated ice-sheet snowmelt detection using microwave radiometer measurements - Liang, Lei; Guo, Huadong; Li, Xinwu; Cheng, Xiao (Polar Research, 2013)
Monitoring ice-sheet snowmelt is fundamental to understanding global climate change. A simple and automated snowmelt detection process is critical to the establishment of an ice-sheet snowmelt monitoring system. However, different ice-sheet snowmelt detection methods are based on a variety of thresholding schemes using different melt signals for dry and wet snow; these complicate the regular operation of an ice-sheet snowmelt monitoring. We propose an automated melt signal detection method developed using melt signals derived from the cross-gradient polarization ratio snowmelt detection method over Greenland and the wavelet transformation-based snowmelt detection method over Antarctica. Initial results indicate that the proposed method not only increases computational efficiency, practicability and operability but is also more accurate. Keywords: Ice sheet; snowmelt detection; radiometer; cross-gradient polarization ratio; wavelet transformation; generalized Gaussian model.
Keywords: Antarktis; innlandsis; klimaendringer; mikrobølge; målinger; polarområdene; radiometer; snøsmelting; statistisk analyse; temperatur måling

Forskrift om miljøvern og sikkerhet i Antarktis - miljødepartementet, Klima- og (Lovdata, 2013)
Volume: 2013-04-26-412 Place: Oslo
Keywords: Antarktis; Dronning Maud Land; forurensning; forvaltning; jus; miljøvern; naturvern

Forskrift om miljøvern og sikkerhet i Antarktis - Miljøverndepartementet (Justisdep., 2013)
Pages: 1144-1160 Volume: 412 Place: Oslo
Keywords: Antarktis; jus; miljøvern

Electrical structure beneath Schirmacher Oasis, East Antarctica: a magnetotelluric study - Murthy, D N; Veeraswamy, K; Harinarayana, T; Singh, U K; Santosh, M (Polar Research, 2013)
Maitri Station (70.76°S; 11.73°E) is located in Schirmacher Oasis, a coastal nunatak in north-central Dronning Maud Land covering an area of 35 km2. Here, we report results from the first magnetotelluric experiments and delineate the deep electrical conductivity structure under Schirmacher Oasis using the data acquired during the 24th Indian Antarctic Scientific Expedition. The magnetotelluric method has the advantage of shallow to deeper level coverage as the data acquisition covers a wide frequency band of 10-3103 Hz, permitting different penetration depths depending on the frequency and conductivity of the layer under investigation. The modelling results indicate the presence of a highly resistive (8000-10 000 ohm m) upper crust, which shows a lateral variation in thickness from 20 km (below site 6) in the east to 10 km (between sites 1 and 2) in the west. It is underlain by a less resistive (500-600 ohm m) lower crust. The highly resistive upper crustal structure supports the existing notion that western Dronning Maud Land is a stable, cratonic platform. Results of free-air gravity, seismic, geomagnetic and surface wave dispersion investigations in East Antarctica also indicate a cratonic-type crust. The results of our study allow us to identify a westward thinning of the upper crust with a marked boundary between sites 1 and 2. We also find evidence for the continuity of the Mozambique mobile belt in East Antarctica on the western side of Schirmacher Oasis. Keywords: Magnetotellurics; Schirmacher Oasis crustal structure; East Antarctica; Mozambique Belt; electrical conductivity.
Keywords: Dronning Maud Land; geofysikk; geologi; magnetotelluriske eksperimenter

Observations of nitric oxide in the Antarctic middle atmosphere during recurrent geomagnetic storms - Newnham, David A; Espy, Patrick J; Clilverd, Mark A; Rodger, Craig J; Seppälä, Annika; Maxfield, David J; Hartogh, Paul; Straub, Corinne; Holmén, Kim; Horne, Richard B (Journal of Geophysical Research: Space Physics, 2013)
We report ground-based measurements of the polar middle atmosphere made using a 230–250 GHz passive microwave radiometer deployed at Troll station (72°01′S 02°32′E, L shell of L = 4.8), Antarctica. Our observations show enhanced mesospheric nitric oxide (NO) volume mixing ratio (VMR) during a series of small recurrent geomagnetic storms in the 2008 austral winter, reaching 1.2 ppmv on day 200 (18 July). The Lomb normalized periodogram of the NO VMR time series averaged over 65-80 km for days 130 to 220 of 2008 (9 May to 7 August) shows a peak exceeding the 95% confidence limit at 25.8 days, close to the synodic rotation period for low-latitude solar coronal holes. The highest correlations between the radiometer NO VMR data and trapped and quasi-trapped electron count rates for L = 3.5-5.5 from the Polar Orbiting Environment Satellites 90° telescope are for the >30 keV (90e1) channel (rmax = 0.56, lag time of 5.1 days) and >100 keV (90e2) channel (rmax = 0.57, lag time of 4.4 days). Maximum correlation between NO VMR and the >700 keV (90P6) channel data is lower but lag times are close to zero. Superposed epoch analyses for the eight most significant geomagnetic storm periods and three Carrington rotations (2070-2072) within the 90 day observation period indicate that significant NO abundance observed at 65-80 km in the Antarctic mesosphere may be produced directly by >200 keV electron precipitation or originate from a source at higher altitudes, e.g., production by >30 keV electrons followed by downward transport.
Keywords: Antarktis; atmosfæren; fysikk; geomagnetiske stormer; meteorologi; polarområdene

Arctic and Antarctic sea ice acts as a sink for atmospheric CO2 during periods of snowmelt and surface flooding - Nomura, Daiki; Granskog, Mats A; Assmy, Philipp; Simizu, Daisuke; Hashida, Gen (Journal of Geophysical Research: Oceans, 2013)
In this study, we present evidence that Antarctic and Arctic sea ice act as sink for atmospheric CO2 during periods of snowmelt and surface flooding. The CO2 flux measured directly at the flooded sea ice surface (Fflood) constituted a net CO2 sink of −1.1 ± 0.9 mmol C m−2 d−1 (mean ± 1 SD), which was an order of magnitude higher than the flux measured at the snow-air surface (Fsnow) and bare ice surface (Fice). The Fsnow/Fflood ratio decreased with increasing water equivalent of snow and superimposed-ice, suggesting that the properties of snow and superimposed-ice formation affect the magnitude of the CO2 flux. The Fsnow/Fflood ratio ranged from 0.1 to 0.5, illustrating that 50–90% of the potential flux at the flooded surface was reduced due to the presence of snow/superimposed-ice. Hence, snow cover properties and superimposed-ice play an important role in the CO2 fluxes across the sea ice-snow-atmosphere interface.
Keywords: Sørishavet; atmosfæren; gassutveksling; havis; karbondioksid; klimaendringer; klimatologi; meteorologi; polarområdene; sjøis

Microbial biogeography during austral summer 2007 in the surface waters around the South Shetland Islands, Antarctica - Olsen, Lasse Mork; Ardelan, Murat van; Hewes, Christopher D; Holm-Hansen, Osmund; Reiss, Christian; Bizsel, Nihayet; Sakshaug, Egil; Vadstein, Olav (Aquatic Microbial Ecology, 2013)
Recent studies have concluded that different water bodies in the ocean can contain different microbial communities. The goal of the present study was to determine if biogeographic patterns are present for aquatic microbes in waters which meet around the South Shetland Islands(SSI), Antarctica. Prokaryotic and eukaryotic marine microbial communities were monitored during the 2007 austral summer by use of polymerase chain reaction (PCR) and denaturing gradientgel electrophoresis (DGGE) of small subunit ribosomal DNA. Hydrographic properties, nutrients and chlorophyll a were also measured. There was an onshore to offshore gradient in temperature, salinity and iron concentration and a unimodal distribution of chlorophyll a concentration in rela-tion to the middle of this gradient that occurred near the SSI. The differences in microbial community structure among stations in the studied area were correlated with both geographical distance and environmental factors. For eukaryotes, the correlation was strongest for environment, where as it was strongest for geographical distance for the prokaryotes. Eukaryotic and prokaryotic community structures were highly correlated. Surface water from the Weddell Sea had a different community of eukaryotes than the water in the Antarctic Circumpolar Current in the Drake Passage, whereas the prokaryotic community was not significantly different. The area close to theSSI where the 2 water types mix had the highest chlorophyll concentration and significantly dif-ferent communities of eukaryotes and prokaryotes from both of the inflowing water types. These results suggest that the prokaryote community structure was more affected by productivity thanby environmental variables. KEY WORDS: Microbial biogeography. Microbial community. Natural iron enrichment. Southern Ocean.
Keywords: Sørishavet; biogeografi; marin biologi; mikroorganismer; oseanografi; overflatevann; økosystemer

New at-sea records of pelagic seabirds in the South Atlantic Ocean and Antarctica - Orgeira, José Luis; Scioscia, Gabriela; Torres, Mónica Anilía; Dellabianca, Natalia Andrea (Polar Research, 2013)
During ship-based seabird surveys in the south Atlantic and Antarctica in the austral summers of 1994/95, 2009, 2010, 2011 and 2012, we documented at-sea distributions of Buller’s albatross (Thalassarche bulleri), Atlantic petrel (Pterodroma incerta), soft-plumaged petrel (Pterodroma mollis), Kerguelen petrel (Lugensa brevirostris) and great-winged petrel (Pterodroma macroptera). In some cases, sightings were considered as extralimital, but for other species updating their distributions in the literature seems warranted. Atlantic petrel, for example, has been regularly observed in the Drake Passage and north of the Antarctic Peninsula for about 30 years, but the distribution of this species has not been updated in the literature. The observations reported here will contribute to update the at-sea distributions of these species and to changes in their distributions. Keywords: Seabirds; Antarctica; South Atlantic Ocean; distribution.
Keywords: Antarktis; Sørishavet; marin zoologi; observasjoner; ornitologi; petreller; sjøfugler

Environmental conditions, particle flux and sympagic microalgal succession in spring before the sea-ice break-up in Adélie Land, East Antarctica - Riaux-Gobin, Catherine; Dieckmann, Gerhard S; Poulin, Michel; Neveux, Jacques; Labrune, Céline; Vétion, Gilles (Polar Research, 2013)
Data pertaining to environmental conditions, sympagic (sea ice) microalgal dynamics and particle flux were collected before the spring ice break-up 2001 in Pierre Lejay Bay, adjacent to the Dumont d'Urville Station, Petrel Island, East Antarctica. An array of two multiple sediment traps and a current meter was deployed for five weeks, from 8 November to 6 December 2001. The sea-ice chlorophyll a and particulate organic carbon (POC) averaged 0.6 mg l−1 (30 mg m−2) and 20 mg l−1 (1 g m−2) near the coast. The POC export flux that reached a maximum of 79 mg m−2 d−1 during the study period was high compared to the one for the Weddell Sea. The flux was homogeneous from the surface to 47 m depth and increased sharply 33 days before the effective ice break-up. A north-western progressive vector of currents (i.e., Lagrangian drift) in the sub-ice surface waters was demonstrated. Bottom ice, platelet ice and under-ice water at 5 m were characterized by differences in colonization and short-term succession of microalgae. Keywords: Land-fast ice; oceanic short-term regime; POM flux; sympagic communities; East Antarctica.
Keywords: Sørishavet; Weddellhavet; alger; fysisk oseanografi; geokjemi; havis; sjøis; sympagisk økologi

Interpretation of new regional aeromagnetic data over Dronning Maud Land (East Antarctica) - Riedel, Sven; Jacobs, Joachim; Jokat, Wilfried (Tectonophysics, 2013)
The geology of Dronning Maud Land (East Antarctica) is so far deduced from isolated outcrops along the coast and from a major coast parallel escarpment surmounting the thick ice sheet. Large parts of Dronning Maud Land are, however, hidden underneath thick ice. In this study we attempt to connect geological information with aeromagnetic data in order to unveil the subglacial geology of this part of East Antarctica. During four austral summer campaigns (2001–2005) in Dronning Maud Land, new aeromagnetic data were gathered across an area of 1.2million square kilometers of which a portion of 65% was previously unexplored. In total 100,000 line kilometers were flown over Dronning Maud Land between 14°W/20° E and 70°S/78.5°S. A striking result was the discovery of a pronounced magnetic anomaly, named here Forster Magnetic Anomaly, east of the Jutulstraumen. It starts at approximately 72°S/007°E and strikes in southwesterly direction as far south as 75°S/1°W. The Forster Magnetic Anomaly likely forms a major tectonic block boundary and/or a suture zone within the East African–Antarctic Orogen (EAAO). The shape and distribution of other magnetic anomalies are discussed in the context of the Proterozoic to Mesozoic geological history of this part of Antarctica.
Keywords: Dronning Maud Land; innlandsis; subglasial geologi

Estimates of the Southern Ocean general circulation improved by animal-borne instruments - Roquet, Fabien; Wunsch, Carl; Forget, Gael; Heimbach, Patrick; Guinet, Christophe; Reverdin, Gilles; Charrassin, Jean-Benoit; Bailleul, Frederic; Costa, Daniel P; Huckstadt, Luis A; Goetz, Kimberly T; Kovacs, Kit M; et al. (Geophysical Research Letters, 2013)
Over the last decade, several hundred seals have been equipped with conductivity-temperature-depth sensors in the Southern Ocean for both biological and physical oceanographic studies. A calibrated collection of seal-derived hydrographic data is now available, consisting of more than 165,000 profiles. The value of these hydrographic data within the existing Southern Ocean observing system is demonstrated herein by conducting two state estimation experiments, differing only in the use or not of seal data to constrain the system. Including seal-derived data substantially modifies the estimated surface mixed-layer properties and circulation patterns within and south of the Antarctic Circumpolar Current. Agreement with independent satellite observations of sea ice concentration is improved, especially along the East Antarctic shelf. Instrumented animals efficiently reduce a critical observational gap, and their contribution to monitoring polar climate variability will continue to grow as data accuracy and spatial coverage increase.
Keywords: Sørishavet; havis; hydrografi; klimatologi; marin biologi; marin zoologi; oseanografi; polarområdene; satellite bilder; seler; sjøis

Reproductive biology of the Antarctic ‘‘sea pen’’ Malacobelemnon daytoni (Octocorallia, Pennatulacea, Kophobelemnidae) - Servetto, Natalia; Torre, Luciana; Sahade, Ricardo (Polar Research, 2013)
The reproductive biology of the sea pen Malacobelemnon daytoni was studied at Potter Cove, South Shetland Islands, where it is one of the dominant species in shallow waters. Specimens collected at 15–22 m depth were examined by histological analysis. M. daytoni is gonochoristic and exhibited a sex ratio of 1:1. Oocyte sizes (>300 µm) and the absence of embryos or newly developed larvae in the colonies suggest that this species can have lecithotrophic larvae and experience external fertilization. This life strategy is in line with other members of the group and supports the hypothesis that this could be a phylogenetically fixed trait for pennatulids. It was observed that oocytes were generated by gastrodermic tissue and released to the longitudinal canal. Thereafter, they migrate along the canal until they reach maturity and are released by autozooids at the top of the colonies. This striking feature has not yet been reported for other pennatulaceans. Mature oocytes were observed from colonies of 15 mm in length, suggesting that sexual maturity can be reached rapidly. This is contrary to what is hypothesized for the vast majority of Antarctic benthic invertebrates, namely that rates of activities associated with development, reproduction and growth are almost universally very slow. This strategy may also explain the ecological success of M. daytoni in areas with high ice impact as in the shallow waters of Potter Cove.
Keywords: Sørishavet; bentos; havbunnen; marin biologi; nesledyr; reproduksjon

Observed variations in multidecadal Antarctic sea ice trends during 1979–2012 - Simpkins, Graham R; Ciasto, Laura M; England, Matthew H (Geophysical Research Letters, 2013)
The spatiotemporal sensitivity of Antarctic sea ice season length trends are examined using satellite-derived observations over 1979–2012. While the large-scale spatial structure of multidecadal trends has varied little during the satellite record, the magnitude of trends has undergone substantial weakening over the past decade. This weakening is particularly evident in the Ross and Bellingshausen Seas, where a ∼25–50% reduction is observed when comparing trends calculated over 1979–2012 and 1979–1999. Multidecadal trends in the Bellingshausen Sea are found to be dominated by variability over subdecadal time scales, particularly the rapid decline in season length observed between 1979 and 1989. In fact, virtually no trend is detectable when the first decade is excluded from trend calculations. In contrast, the sea ice expansion in the Ross Sea is less influenced by shorter-term variability, with trends shown to be more consistent at decadal time scales and beyond. Understanding these contrasting characteristics have implications for sea ice trend attribution.
Keywords: Sørishavet; havis; klimatologi; observasjoner; satellite bilder; sjøis

Surface mass balance on Fimbul ice shelf, East Antarctica: Comparison of field measurements and large-scale studies - Sinisalo, Anna; Anschütz, Helgard; Aasen, Anne Tårånd; Langley, Kirsty; von Deschwanden, Angela; Kohler, Jack; Matsuoka, Kenichi; Hamran, Svein- Erik; Øyan, Mats-Jørgen; Schlosser, Elisabeth; Hagen, Jon Ove; Nøst, Ole Anders; et al. (Journal of Geophysical Research: Atmospheres, 2013)
Many challenges remain for estimating the Antarctic ice sheet surface mass balance (SMB), which represents a major uncertainty in predictions of future sea-level rise. Validating continental scale studies is hampered by the sparse distribution of in situ data. Here we present a 26 year mean SMB of the Fimbul ice shelf in East Antarctica between 1983–2009, and recent interannual variability since 2010. We compare these data to the results of large-scale SMB studies for similar time periods, obtained from regional atmospheric modeling and remote sensing. Our in situ data include ground penetrating radar, firn cores, and mass balance stakes and provide information on both temporal and spatial scales. The 26 year mean SMB on the Fimbul ice shelf varies between 170 and 620 kg m−2 a−1 giving a regional average value of 310 ± 70 kg m−2 a−1. Our measurements indicate higher long-term accumulation over large parts of the ice shelf compared to the large-scale studies. We also show that the variability of the mean annual SMB, which can be up to 90%, can be a dominant factor in short-term estimates. The results emphasize the importance of using a combination of ground-based validation data, regional climate models, and remote sensing over a relevant time period in order to achieve a reliable SMB for Antarctica.
Keywords: Dronning Maud Land; glasiologi; havnivåstigning; innlandsis; klimaendringer; klimatologi

The first men on the last continent – Carsten Egeberg Borchgrevink and the Southern Cross expedition, 1898 -1900 - Smelror, Morten (Fram forum, 2013)
Keywords: Antarktis; Carsten Egeberg Borchgrevink; Kapp Adare; Southern Cross; Victoria Land; ekspedisjonen; ekspedisjoner; første landgang; geologi; oppdagelsesreiser; overvintring

Trends in Antarctic ecological research in Latin America shown by publications in international journals - Stotz, Gisela C; Salgado-Luarte, Cristian; Rios, Rodrigo S; Acuña-Rodriguez, Ian S; Carrasco-Urra, Fernando; Molina-Montenegro, Marco A; Gianoli, Ernesto (Polar Research, 2013)
Antarctica is a highly interesting region for ecologists because of its extreme climatic conditions and the uniqueness of its species. In this article, we describe the trends in Antarctic ecological research participation by Latin American countries. In a survey of articles indexed by the ISI Web of Science, we searched under the categories ‘‘Ecology,’’ ‘‘Biodiversity Conservation’’ and ‘‘Evolutionary Biology’’ and found a total of 254 research articles published by Latin American countries. We classified these articles according to the country of affiliation, kingdom of the study species, level of biological organization and environment. Our main finding is that there is a steady increase in the relative contribution of Latin American countries to Antarctic ecological research. Within each category, we found that marine studies are more common than terrestrial studies. Between the different kingdoms, most studies focus on animals and most studies use a community approach. The leading countries in terms of productivity were Argentina, Chile and Brazil, with Argentina showing the highest rate of increase. Keywords: Antarctica; Argentina; Brazil; Chile; research trends; scientific productivity.
Keywords: Antarktis; biodiversitet; forskning; vitenskap; økologi

Sources and geographic heterogeneity of trace metals in the sediments of Prydz Bay, East Antarctica - Sun, Wei-Ping; Hu, Chuan-Yu; Weng, Huan-Xin; Han, Zheng-Bing; Shen, Chen; Pan, Jian-Ming (Polar Research, 2013)
In this study, we have determined the contents and distribution of zinc and cadmium in the surface sediments from Prydz Bay, East Antarctica. The main sources of the trace elements and their geographic heterogeneity, and the relation between Zn and Cd, are discussed based on the cluster analysis, principle component analysis and considerations of biogenic and lithogenic inputs. The results show that the contents of trace metals range from 34.6 to 96.6 mg kg-1 for Zn, and from 0.254 to 0.441 mg kg-1 for Cd. Calculations of the enrichment factor indicated no significant anthropogenic impact. Biogenic and lithogenic inputs are the main sources of trace metals. They are almost equal for Zn and Cd at the Amery Ice Shelf edge, while the continental shelf and deep ocean are dominated by biogenic inputs. The contribution of biogenic inputs is much higher for Zn than for Cd at the deep ocean. Calculations of biogenic trace metals revealed different relationships between biogenic Zn and biogenic Cd, which reflect the biological uptake by phytoplankton in the water column. Keywords: Trace elements; sources; enrichment factor; cluster analysis; principal component analysis; Antarctica.
Keywords: Sørishavet; fytoplankton; geografi; kjemiske analyser; kontinentalmargin; kontinentalsokkel; marin biologi; oseanografi; sedimenter; sedimentologi

Anders Jahre - Tjomsland, Audun (Tjomsland media, 2013)
Keywords: Sørishavet; biografier; historie; hvalfangstindustri; hvalfangstselskaper; hvalindustri; pelagisk; rederier; skipsfart

Inorganic C utilization and C isotope fractionation by pelagic and sea ice algal assemblages along the Antarctic continental shelf - Tortell, Philippe D; Mills, Mathew M; Payne, Christopher D; Maldonado, Maria T; Chierici, Melissa; Fransson, Agneta; Alderkamp, Anne-Carlijn; Arrigo, Kevin R (Marine Ecology Progress Series, 2013)
Physiological characteristics of inorganic C uptake were examined in Southern Ocean ice algae and phytoplankton assemblages. Ice algal and phytoplankton assemblages were largely dominated by diatoms and Phaeocystis antarctica, and showed a high capacity for HCO3- utilization, with direct HCO3- transport accounting for ~60% of total inorganic C uptake. Extracellular carbonic anhydrase (eCA) was detectable in all samples, but with significantly lower activity in sea ice algae. Neither HCO3- transport nor eCA activity was related to the in situ partial pressure of CO2 (pCO2) or taxonomic composition of samples. The half-saturation constant (KS) for inorganic C ranged from ~100 to 5000 µM, and showed significantly more variability among sea ice algae than phytoplankton assemblages. For the phytoplankton assemblages, there were significant positive correlations between in situ pCO2 and KS (higher C substrate affinity in low pCO2 waters), and also between KS and maximum C uptake rates (Vmax). In contrast, KS and Vmax in sea-ice algal assemblages were not correlated to each other, or to any other measured variables. The C isotope composition of particulate organic carbon(δ13C-POC) in the phytoplankton assemblages showed modest variability (range -30 to -24.6‰) and was significantly correlated to the ratio of inferred growth rates (derived from Vmax) and in situ CO2 concentrations, but not to any measured C uptake parameters. δ13C-POC in sea ice algal samples (range -25.7 to -12.9‰) was significantly heavier than in the phytoplankton assemblages, and not correlated to any other variables. Our results provide evidence for the widespread occurrence of carbon-concentrating mechanisms in Southern Ocean sea ice algae and phytoplankton assemblages. KEYWORDS: Phytoplankton · Sea ice algae · Inorganic carbon uptake · HCO3- · Carbonic anhydrase
Keywords: Sørishavet; alger; biokjemi; diatomeer; fytoplankton; kjemiske analyser; kontinentalsokkel; marin biologi

Characterization and mapping of plant communities at Hennequin Point, King George Island, Antarctica - Victoria, Filipe de C; de Albuquerque, Margéli P; Pereira, Antonio B; Simas, Felipe N B; Spielmann, Adriano A; Schaefer, Carlos E G R (Polar Research, 2013)
King George Island is the largest island and the principal area used for research bases in Antarctica. Argentina, Brazil, Chile, China, Poland, Russia, South Korea and Uruguay have permanent open bases on this island. Other countries have seasonal summer stations on different parts of this island, which demonstrates that human impact is strong on King George Island relative to other areas in the maritime and continental Antarctica. The objective of this work was to present a phytosociological approach for ice-free areas of Hennequin Point, eastern coast of Admiralty Bay, King George Island. The study started with the classification and description of the plant communities based primarily on phytosociological and biodiversity data. The area was mapped using an Astech Promark II® DGPS, yielding sub-metric precision after post-processing with software. The plant communities were described as follows: (1) lichen and moss cushion formation; (2) moss carpet formation; (3) fellfield formation; (4) grass and cushion chamaephyte formation; and (5) Deschampsia Antarctica–lichen formation. Characterizations and distributions of the plant communities are presented on a map at a scale of 1:5000. The plant communities found at Hennequin Point, in general, differ from those found in other areas of the Admiralty Bay region, probably because of the concentration of skua nests in the area and the relief singularities. We conclude by highlighting the importance of the study of plant species found in the ice-free areas of the Antarctic with respect to environmental monitoring and for evaluating global climate and environmental changes. Keywords: Plant communities mapping; lichens; mosses; flowering plants; Antarctic
Keywords: Antarktis; biodiversitet; fytososiologi; klimaendringer; lav; miljøendringer; moser; planter; plantesosiologi

Isolation and description of a globally distributed cryosphere cyanobacterium from Antarctica - Won Hong, Ji; Kim, Sung Hong; Choi, Han-Gu; Kang, Sung-Ho; Yoon, Ho-Sung (Polar Research, 2013)
A previously uncultured cyanobacterium, strain KNUA009, was axenically isolated from a meltwater stream on Barton Peninsula, King George Island, South Shetland Islands, Antarctica. Molecular evidences showed that the isolate belongs to groups of globally distributed cryosphere cyanobacterial clones and this new isolate represents the first laboratory culture to be assigned to these groups. Strain KNUA009 was able to thrive at low temperatures ranging between 5°C and 20°C, but did not survive at temperatures of 25°C and above. As the isolate morphologically resembled Oscillatoria species, it is suggested that this cyanobacterium may represent a new species clade with cold resistance within the genus Oscillatoria. Keywords: Barton Peninsular; cryosphere cyanobacteria; King George Island; uncultured Oscillatoria species.
Keywords: Antarktis; bakterier; biologi; ferskvann; fylogenetikk

Circulation and exchanges at high-latitude ocean margins : dynamical models and observations from instrumented seals - Zhou, Qin; Eltoft, Torbjørn (UiT The Arctic University of Norway, 2013)
Circulation and exchange processes at high-latitude ocean margins are investigated in this thesis, by using analytical models, numerical simulations and hydrographic data. In the Northern Hemisphere, the establishment of Atlantic Water transport as a topographically steered slope current has been investigated. A simplified analytical model based on geostrophic balance predicts that buoyancy loss over a sloping boundary leads to a cross-slope baroclinic flow transformed into an along-slope barotropic flow. And the resulting transport changes can be estimated from hydrographic data. Over the continental slope off Scotland, the diagnosed transport changes in the barotropic flow is in agreement with the observed transport changes. The results emphasize that geostrophy can be used to diagnose topographically steered barotropic flow, which makes it especially useful for high latitudes where topographic steering of ocean circulation is strong. In the Eastern Weddell Sea in the Atlantic Sector of Antarctica, the processes controlling the exchanges of water masses over the continental slope have been studied, by taking advantage of over 11,000 hydrographic profiles collected by instrumented seals in this region from February to November 2008. The proposed mechanism, that the wind-driven downwelling is responsible for the accumulation of Antarctic Surface Water near the ice front and its further spreading beneath the ice shelf along the coast of Eastern Weddell Sea, is revisited by a combination of detailed analysis of the data collected by the seals, an analytical model and numerical simulations. The results show that the Antarctic Surface Water enters the ice shelf cavity after being brought on-shore by wind-driven surface Ekman transport, and being spread below the depth of the ice base within a regime of coastal downwelling. The results also suggest a complex picture of water mass exchange processes along the coast of Eastern Weddell Sea, in which mesoscale eddies play a central role. Finally, the data collected by the seals are employed to evaluate the performance of a global coupled ocean-ice model incorporated with a parametrization of wave-induced mixing in simulating the upper ocean properties in the Southern Ocean. The results suggest that wave-induced mixing is important to modify the upper ocean properties. Since coastal water properties in the Eastern Weddell Sea are mainly determined by the onshore Ekman transport of surface waters, the wave-induced mixing also plays a role in preconditioning the coastal water masses in this region. I dette arbeidet er sirkulasjon og blandingsmekanismer i havområder på høge breddegrader undersøkt ved bruk av analytiske modeller, numeriske simuleringer og havobservasjoner. På den nordlige halvkulen er det undersøkt hvordan transport av Atlanterhavsvann etablerer seg som en topografisk styrt strøm langs kontinentalsokkelskråningen. En forenklet analytisk modell basert på geostrofisk balanse kan forklare hvordan varmetap i vannet som strømmer langs en skrånende bunn fører til en baroklin strøm på tvers av skråningen som igjen blir transformert til en barotrop strøm langs den skrånende bunnen. Denne transportendringen kan man beregne fra hydrografiske data. En slik beregnet transportendring over kontinentalsokkelskråningen vest for Skotland stemmer godt overens med observert transportendring i denne regionen. Resultatene understreker at geostrofi kan bli brukt til å diagnostisere topografisk styrte strømmer, noe som gjør teorien spesielt egnet for å studere oseanografi på høge breddegrader der topografisk styring av strømmene er mest tydelig. I det østlige Weddellhavet, i den atlantiske sektoren av Antarktis, har prosessene som styrer vannmasseutvekslingen på tvers av kontinentalsokkelskråningen blitt undersøkt ved å ta i bruk mer enn 11.000 havprofiler som er blitt samlet inn av seler i denne regionen fra februar til november 2008. Selene var utsyrt med temperatur-, salt- og dybde-loggere. Den foreslåtte mekanismen at vind-drevet nedstrømning er ansvarlig for oppsamling av antarktisk overflatevann nær isbremmen og for dens videre spredning under den flytende isbremmen langs kysten av den østlige Weddellhavet, er testet ved hjelp av en kombinasjon av detaljerte dataanalyser av observasjonene som ble samlet inn av selene, en analytisk modell og numeriske simuleringer. Resultatene viser at det antarktiske overflatevannet entrer hulområdet under isbremmen etter at det er blitt fraktet mot isbremmen som Ekman-transport i overflaten. Spredningen på undersiden av den flytende isbremmen kan forklares ved hjelp av samme mekanisme som nedstrømning langs en kyst. Resultatene tyder også på at vannmasseutvekslingen langs kysten av det østlige Weddellhavet er sammensatt av flere prosesser der virvler av mesoskala størrelse spiller en sentral rolle. Til slutt er dataene som ble samlet inn av selene blitt brukt til å evaluere en global hav-is-modell som har innebygget en parameterisering av bølgedrevet blanding i Sørhavet. Resultatene indikerer at bølgedrevet blanding er viktig for å modifisere hva de øvre vannmassene i Sørhavet er sammensatt av. Siden sammensetningen i kystvann i det østlige Weddellhavet er hovedsakelig bestemt av Ekmantransport inn mot kysten, vil bølgedrevet blanding også spille en rolle når det gjelder å danne kystvannmassene i denne regionen.
Publication Title: Universitetet i Tromsø, Fakultet for naturvitenskap og teknologi Volume: Ph.D. Issue: DOKTOR-004
Keywords: Sørishavet; Weddellhavet; hydrografi; klimaendringer; marin biologi; oseanografi; seler; sjøpattedyr

Seasonal inflow of warm water onto the southern Weddell Sea continental shelf, Antarctica - Årthun, Marius; Nicholls, Keith William; Makinson, Keith; Fedak, Michael A; Boehme, Lars (Geophysical Research Letters, 2012)
Keywords: Sørishavet; Weddellhavet; isshelf; kontinentalsokkel; kontinentalsokler; oseanografi

Can we use ice sheet reconstructions to constrain meltwater for deglacial simulations? - Bethke, Ingo; Li, Camille; Nisancioglu, Kerim H (Paleoceanography, 2012)
Freshwater pulses from melting ice sheets are thought to be important for driving deglacial climate variability. This study investigates challenges in simulating and understanding deglacial climate evolution within this framework, with emphasis on uncertainties in the ocean overturning sensitivity to meltwater inputs. The response of an intermediate complexity model to a single Northern Hemisphere meltwater pulse is familiar: a weakening of the ocean overturning circulation in conjunction with an expansion of sea ice cover and a meridional temperature seesaw. Nonlinear processes are vital in shaping this response and are found to have a decisive influence when more complex scenarios with a history of pulses are involved. A meltwater history for the last deglaciation (21–9 ka) was computed from the ICE-5G ice sheet reconstruction, and the meltwater was routed into the ocean through idealized ice sheet drainages. Forced with this meltwater history, model configurations with altered freshwater sensitivity produce a range of outcomes for the deglaciation, from those in which there is a complete collapse of the overturning circulation to those in which the overturning circulation weakens slightly. The different outcomes are interpreted in terms of the changing hysteresis behavior of the overturning circulation (i.e., non-stationary freshwater sensitivity) as the background climate warms through the course of the deglaciation. The study illustrates that current uncertainties in model sensitivity are limiting in efforts to forward-model deglacial climate variability. Furthermore, ice sheet reconstructions are shown to provide poor constraints on meltwater forcing for simulating the deglaciation.
Keywords: Sørishavet; global oppvarming; havnivåstigning; innlandsis; isavsmelting; klimamodeller; klimatologi; polarområdene; smeltevann

Ecosystem response to climatic change: the importance of the cold season - Bokhorst, Stef; Bjerke, Jarle W; Tømmervik, Hans; Preece, Catherine; Phoenix, Gareth K (Ambio, 2012)
Winter climate and snow cover are the important drivers of plant community development in polar regions. However, the impacts of changing winter climate and associated changes in snow regime have received much less attention than changes during summer. Here, we synthesize the results from studies on the impacts of extreme winter weather events on polar heathland and lichen communities. Dwarf shrubs, mosses and soil arthropods were negatively impacted by extreme warming events while lichens showed variable responses to changes in extreme winter weather events. Snow mould formation underneath the snow may contribute to spatial heterogeneity in plant growth, arthropod communities and carbon cycling. Winter snow cover and depth will drive the reported impacts of winter climate change and add to spatial patterns in vegetation heterogeneity. The challenges ahead lie in obtaining better predictions on the snow patterns across the landscape and how these will be altered due to winter climate change.
Publisher: Springer Netherlands
Keywords: Antarktis; biologi; botanikk; dyr; klimaendringer; leddyr; planter; snø; sopper; zoologi; økosystemer

Environmental monitoring and management proposals for the Fildes Region, King George Island, Antarctica - Braun, Christina; Mustafa, Osama; Nordt, Anja; Pfeiffer, Simone; Peter, Hans-Ulrich (Polar Research, 2012)
The Antarctic terrestrial environment is under increasing pressure from human activities. The Fildes Region is characterized by high biodiversity, but is also a major logistic centre for the northern Antarctic Peninsula. Different interests, from scientific research, nature conservation, protection of geological and historical values, station operations, transport logistics and tourism, regularly overlap in space and time. This has led to increasing conflict among the multiple uses of the region and breaches of the legal requirements for environmental protection that apply in the area. The aim of this study was to assess the impacts of human activities in the Fildes Region by monitoring the distribution of bird and seal breeding sites and recording human activities and their associated environmental impacts. Data from an initial monitoring period 200306 were compared with data from 200810. We observed similar or increased levels of air, land and ship traffic, but fewer violations of overflight limits near Antarctic Specially Protected Area No. 150 Ardley Island. Open waste dumping and oil contamination are still major environmental impacts. Scientific and outdoor leisure activities undertaken by station personnel are more frequent than tourist activities and are likely to have a commensurate level of environmental impact. Despite the initial success of some existing management measures, it is essential that scientific and environmental values continue to be safeguarded, otherwise environmental impacts will increase and the habitat will be further degraded. We argue that the Fildes Region should be considered for designation as an Antarctic Specially Managed Area, a measure that has proven effective for environmental management of vulnerable areas of the Antarctic.
Keywords: Antarktis; biodiversitet; miljøvern

The effect of energetic electron precipitation on middle mesospheric night-time ozone during and after a moderate geomagnetic storm - Daae, Marianne; Espy, Patrick J; Nesse Tyssøy, Hilde; Newnham, David A; Stadsnes, Johan; Søraas, Finn (Geophysical Research Letters, 2012)
Using a ground-based microwave radiometer at Troll Station, Antarctica (72°S, 2.5°E,L = 4.76), we have observed a decrease of 20–70% in the mesospheric ozone, coincident with increased nitric oxide, between 60 km and 75 km altitude associated with energetic electron precipitation (E > 30 keV) during a moderate geomagnetic storm (minimum Dst of −79 nT) in late July 2009. NOAA satellite data were used to identify the precipitating particles and to characterize their energy, spatial distribution and temporal variation over Antarctica during this isolated storm. Both the ozone decrease and nitric oxide increase initiate with the onset of the storm, and persist for several days after the precipitation ends, descending in the downward flow of the polar vortex. These combined data present a unique case study of the temporal and spatial morphology of chemical changes induced by electron precipitation during moderate geomagnetic storms, indicating that these commonplace events can cause significant effects on the middle mesospheric ozone distribution.
Keywords: Dronning Maud Land; Troll forskningsstasjon; geofysikk; geomagnetiske stormer; mikrobølge; ozonlaget; radiometer

Feeding grounds of the eastern South Pacific humpback whale population include the South Orkney Islands - Dalla Rosa, Luciano; Félix, Fernando; Stevick, Peter T; Secchi, Eduardo R; Allen, Judith M; Chater, Kim; Martin, Anthony R; Basso, Manuela (Polar Research, 2012)
This paper reports on two photo-identified humpback whales (Megaptera novaeangliae) that were sighted in different years in the proximity of the South Orkney Islands, at the boundary between the Scotia and Weddell seas (60o54.5’S – 46o40.4’W and 60o42.6’S – 45o33’W). One of the whales had been previously sighted off Ecuador, a breeding ground for the eastern South Pacific population. The other whale was subsequently resighted in Bransfield Strait, off the western Antarctic Peninsula, a well-documented feeding ground for the same population. These matches give support to a hypothesis that the area south of the South Orkney Islands is occupied by whales from the eastern South Pacific breeding stock. Consequently, we propose 40oW as a new longitudinal boundary between the feeding grounds associated with the eastern South Pacific and western South Atlantic breeding stocks. Keywords: Humpback whale; photo-identification; breeding stocks; migration; South Orkney Islands; Southern Ocean
Keywords: Rosshavet; Sørishavet; knølhvaler; marin zoologi; migrasjon; oseanografi

Aerosol-Mediated Transport and Deposition of Brominated Diphenyl Ethers to Antarctica - Dickhut, Rebecca M; Cincinelli, Alessandra; Cochran, Michele; Kylin, Henrik (Environmental Science & Technology, 2012)
Brominated diphenyl ethers (BDE47, 99, 100, and 209) were measured in air, snow and sea ice throughout western Antarctica between 2001 and 2007. BDEs in Antarctic air were predominantly associated with aerosols and were low compared to those in remote regions of the northern hemisphere, except in Marguerite Bay following the fire at Rothera research station in Sept 2001, indicating that this event was a local source of BDE209 to the Antarctic environment. Aerosol BDE47/100 reflects a mixture of commercial pentaBDE products; however, BDE99/100 is suggestive of photodegradation of BDE99 during long-range atmospheric transport (LRAT) in the austral summer. BDEs in snow were lower than predicted based on snow scavenging of aerosols indicating that atmospheric deposition events may be episodic. BDE47, -99, and -100 significantly declined in Antarctic sea ice between 2001 and 2007; however, BDE209 did not decline in Antarctic sea ice over the same time period. Significant losses of BDE99 and -100 from sea ice were recorded over a 19 day period in spring 2001 demonstrating that seasonal ice processes result in the preferential loss of some BDEs. BDE47/100 and BDE99/100 in sea ice samples reflect commercial pentaBDE products, suggesting that photodegradation of BDE99 is minimal during LRAT in the austral winter.
Publisher: American Chemical Society
Keywords: Antarktis; Sørishavet; atmosfæren; forurensning; miljøgifter; polarområdene

Low genetic diversity in Antarctic populations of the lichenforming ascomycete Cetraria aculeata and its photobiont - Domaschke, Stephanie; Fernández-Mendoza, Fernando; Garcia, Miquel A; Martín, Maria P; Printzen, Christian (Polar Research, 2012)
Lichens, symbiotic associations of fungi (mycobionts) and green algae or cyanobacteria (photobionts), are poikilohydric organisms that are particularly well adapted to withstand adverse environmental conditions. Terrestrial ecosystems of the Antarctic are therefore largely dominated by lichens. The effects of global climate change are especially pronounced in the maritime Antarctic and it may be assumed that the lichen vegetation will profoundly change in the future. The genetic diversity of populations is closely correlated to their ability to adapt to changing environmental conditions and to their future evolutionary potential. In this study, we present evidence for low genetic diversity in Antarctic mycobiont and photobiont populations of the widespread lichen Cetraria aculeata. We compared between 110 and 219 DNA sequences from each of three gene loci for each symbiont. A total of 222 individuals from three Antarctic and nine antiboreal, temperate and Arctic populations were investigated. The mycobiont diversity is highest in Arctic populations, while the photobionts are most diverse in temperate regions. Photobiont diversity decreases significantly towards the Antarctic but less markedly towards the Arctic, indicating that ecological factors play a minor role in determining the diversity of Antarctic photobiont populations. Richness estimators calculated for the four geographical regions suggest that the low genetic diversity of Antarctic populations is not a sampling artefact. Cetraria aculeata appears to have diversified in the Arctic and subsequently expanded its range into the Southern Hemisphere. The reduced genetic diversity in the Antarctic is most likely due to founder effects during long-distance colonization. The environmental conditions of the Antarctic are among the most adverse on Earth and are generally characterized by low mean annual temperatures, high wind velocities, extreme drought and extended periods of darkness. The effects of global climate change are especially pronounced in parts of the Antarctic (Turner et al. 2005). Air temperature in the maritime Antarctic has steadily increased within the last years (Smith & Stammerjohn 1996; Turner et al. 2005). On the western Antarctic Peninsula a temperature increase of more than 2.5 K has been observed over the last 50 years. The overall effect of such a temperature increase on terrestrial Antarctic organisms could be beneficial. For example, glacial melting will increase the availability of terrestrial (page number not for citation purpose). Keywords Genetic diversity; lichens; Cetraria aculeata; Trebouxia jamesii; polar lichens; global change.
Keywords: Antarktis; alger; fotobiont; genetisk mangfold; klimaendringer; lav; sopper; økosystemer

Leadership in politics and science within the Antarctic Treaty - Dudeney, John R; Walton, David W H (Polar Research, 2012)
For over 50 years the Antarctic has been governed through the Antarctic Treaty, an international agreement now between 49 nations of whom 28 Consultative Parties (CPs) undertake the management role. Ostensibly, these Parties have qualified for their position on scientific grounds, though diplomacy also plays a major role. This paper uses counts of policy papers and science publications to assess the political and scientific outputs of all CPs over the last 18 years. We show that a subset of the original 12 Treaty signatories, consisting of the seven claimant nations, the USA and Russia, not only set the political agenda for the continent but also provide most of the science, with those CPs producing the most science generally having the greatest political influence. None of the later signatories to the Treaty appear to play a major role in managing Antarctica compared with this group, with half of all CPs collectively producing only 7% of the policy papers. Although acceptance as a CP requires demonstration of a substantial scientific programme, the Treaty has no formal mechanism to review whether a CP continues to meet this criterion. As a first step to addressing this deficiency, we encourage the CPs collectively to resolve to hold regular international peer reviews of their individual science programmes and to make the results available to the other CPs. Keywords: Governance; claimant states; Antarctic policy; scientific publications.
Keywords: Antarktis; Antarktistraktaten; forvaltning; politikk; vitenskap

Norges forskningsinnsats i Antarktis 2013-2022 - Forskningsrådet; Divisjon for energi, ressurser og miljø (Norges forskningsråd, 2012)
Publication Title: Rapport / NFR. Divisjon for energi, ressurser og miljø
Keywords: Antarktis; Dronning Maud Land; forskning

Southern Weddell Sea shelf edge geomorphology: Implications for gully formation by the overflow of high-salinity water - Gales, Jennifer A; Larter, Robert David; Mitchell, Neil; Hillenbrand, Claus-Dieter; Østerhus, Svein; Shoosmith, Deb R (Journal of Geophysical Research: Earth Surface, 2012)
Keywords: Sørishavet; Weddellhavet; forskning; geomorfologi; isshelf; oseanografi

Correlative and dynamic species distribution modelling for ecological predictions in the Antarctic: a cross-disciplinary concept - Gutt, Julian; Zurell, Damaris; Bracegridle, Thomas J; Cheung, William; Clark, Melody S; Convey, Peter; Danis, Bruno; David, Bruno; De Broyer, Claude; di Prisco, Guido; Griffiths, Huw; Laffont, Rémi; et al. (Polar Research, 2012)
Keywords: Antarktis; biodiversitet; biosfære; miljø; oseanografi; økologi; økosystemer

Ice Shelf - Ocean Interaction in the Eastern Weddell Sea, Antarctica - Hattermann, Tore (Universitetet i Tromsø, 2012)
This thesis investigates the interaction of the Antarctic ice shelves along the coast of Dronning Maud Land with the ocean circulation in the Eastern Weddell Sea. A set of direct oceanic observations below the Fimbul Ice Shelf, which were acquired during three Antarctic field seasons in the austral summers 2009/10, 2010/11 and 2011/12, is a central element of the presented work. This new oceanographic dataset is complemented by a high-resolution state-of-the-art ice shelf - ocean circulation model. The results provide an estimate of the amount of basal melting at the Fimbul Ice Shelf, and revise the physical processes that determine the ocean heat fluxes over the East Antarctic continental slope. A major finding is that deep-ocean heat fluxes towards the ice are much more constrained than predicted by previous ocean models, causing substantially lower rates of basal melting than earlier suggested. The predicted basal melting is consistent with mass balance estimates from satellite data and implicates that the Fimbul Ice Shelf is currently not subject to rapid basal mass loss. Furthermore, the complex interplay of the processes within the coastal, frontal system, and their respective role in transporting heat for melting towards the ice is examined. The results emphasize the importance of oceanic eddies within the coastal circulation for controlling the inflow of Warm Deep Water into the ice shelf cavities. A realistic representation of the effect of the mesoscale eddy overturning is thus a crucial requirement in order to simulate basal melting along the Weddell Sea coast in the present and future climate. The results also imply that fresh, and solar-heated Antarctic Surface Water plays a central role for the ice shelf cavity exchange. Being produced by sea ice melting at the ocean surface, this water mass directly enters the cavity and increases the melting of shallow ice. Due to its buoyancy, the presence of Antarctic Surface Water also alters the coastal dynamics and regulates the inflow of warm water at depth, thus showing that a more detailed understanding of the role of this water mass for basal melting around Antarctica will need further attention. Finally, the results suggest a direct relationship between the simulated basal melting and only a few deterministic parameters of the coastal circulation, which is used to derive a simple parameterization of for basal melting at the Fimbul Ice Shelf.
Publication Title: Faculty of science and technology. Department of physics and technology Volume: Philosophiae Doctor Issue: DOKTOR-004 ISBN: 8282360783,9788282360784,8282360791,9788282360791
Keywords: Sørishavet; Weddellhavet; fysikk; fysisk oseanografi; isbrem; isshelf; klimaendringer

Two years of oceanic observations below the Fimbul Ice Shelf, Antarctica - Hattermann, Tore; Nøst, Ole Anders; Lilly, Jonathan M; Smedsrud, Lars H (Geophysical Research Letters, 2012)
The mechanisms by which heat is delivered to Antarctic ice shelves are a major source of uncertainty when assessing the response of the Antarctic ice sheet to climate change. Direct observations of the ice shelf-ocean interaction are extremely scarce and in many regions melt rates from ice shelf-ocean models are not constrained by measurements. Our two years of data (2010 and 2011) from three oceanic moorings below the Fimbul Ice Shelf in the Eastern Weddell Sea show cold cavity waters, with average temperatures of less than 0.1°C above the surface freezing point. This suggests low basal melt rates, consistent with remote sensing-based, steady-state mass balance estimates for this sector of the Antarctic coast. Oceanic heat for basal melting is found to be supplied by two sources of warm water entering below the ice: (i) eddy-like bursts of Modified Warm Deep Water that access the cavity at depth for eight months of the record; and (ii) fresh surface water that flushes parts of the ice base with temperatures above freezing during late summer and fall. This interplay of processes implies that basal melting at the Fimbul Ice Shelf cannot simply be parameterized by coastal deep ocean temperatures, but instead appears directly linked to both solar forcing at the surface as well as to the dynamics of the coastal current system.
Keywords: Sørishavet; Weddellhavet; fysisk oseanografi; innlandsis; isbrem; isshelf; klimaendringer; smelting

Norges ti viktigste polarekspedisjoner - Jaklin, Asbjørn; Jølle, Harald Dag (Norsk Polarinstitutt, 2012)
Publication Title: Norsk polarinstitutt. Rapportserie
Keywords: Antarktis; Carl Anton Larsen; Maudheim; NSBX 1949-52; Norge; Norsk-britisk-svenske antarktisekspedisjon; Roald Amundsen; Sydpolsekspedisjonen; polarekspedisjoner; polarforskning; polarområdene

Review of Race for the South Pole: the expedition diaries of Scott and Amundsen, by Roland Huntford - Jølle, Harald Dag (Polar Research, 2012)
Roland Huntford is the grand old man among polar historians. After his classic Scott and Amundsen in 1979 (later editions were retitled, The last place on Earth), he wrote a series of books on Norwegian and British polar heroes as well as a thorough study of the history of skiing (2006). Huntford challenged the British admiration of Robert Falcon Scott’s scientific programme and great courage*and insisted that Roald Amundsen’s expedition was far better prepared and carried out. Huntford’s scathing criticism of Scott’s fatal choices and lack of competence dared to assault this cherished British polar icon in a manner that would be unthinkable for Norwegian authors.
Keywords: Antarktis; Roald Amundsen; Robert Falcon Scott; Sydpolen; Sydpolsekspedisjonen; Sørpolen; bokanmeldelser; dagbøker; kappløpet; polarhistorie; polarområdene

Perspective: Strategic challenges of tourism development and governance in Antarctica: taking stock and moving forward - Lamers, Machiel; Liggett, Daniela; Amelung, Bas (Polar Research, 2012)
Keywords: Antarktis; forvaltning; turisme

Deciphering the role of southern gateways and carbon dioxide on the onset of the Antarctic Circumpolar Current - Lefebvre, Vincent; Donnadieu, Yannick; Sepulchre, Pierre; Swingedouw, Didier; Zhang, Zhong-Shi (Paleoceanography, 2012)
Growth of Antarctic ice sheet during the Cenozoic 34 million years ago appears as a potential tipping point in the long term cooling trend that began 50 Ma ago. For decades, the onset of the Antarctic Circumpolar Current (ACC) following the opening of the Drake Passage and of the Tasman Seaway has been suggested as the main driver of the continental-scale Antarctic glaciation. However, recent modeling works emphasized that the Eocene/Oligocene atmospheric carbon dioxide (CO2) lowering could be the primary forcing of the Antarctic glaciation, questioning the ACC theory. Here, we investigate the response of the ACC to changes in CO2concentrations occurring from the late Eocene to the late Oligocene. We used a fully coupled atmosphere-ocean model (FOAM) with a mid-Oligocene geography. We find that the opening of southern oceanic gateways does not trigger the onset of the ACC for CO2typical of the late Eocene (>840 ppm). A cooler background climatic state such as the one prevalent at the end of the Oligocene is required to simulate a well-developed ACC. In this cold configuration, the intensified sea-ice development around Antarctica and the resulting brine formation lead to a strong latitudinal density gradient in the Southern Ocean favoring the compensation of the Ekman transport, and consequently the ACC. Our results imply that the ACC has acted as a feedback rather than as a driver of the global cooling.
Keywords: Sørishavet; Sørishavsstrømmen; havstrømmer; karbondioksid; klimatologi; paleogeografi

Spatial variation of englacial radar attenuation: Modeling approach and application to the Vostok flowline - MacGregor, Joseph A.; Matsuoka, Kenichi; Waddington, Edwin D.; Winebrenner, Dale P.; Pattyn, Frank (Journal of Geophysical Research: Earth Surface, 2012)
Constraining the spatial variation of englacial radar attenuation is critical for accurate inference of the spatial variation of the englacial and basal properties of ice sheets from radar returned power. Here we evaluate attenuation models that account for spatial variations in ice temperature and chemistry and test them along the flowline that passes through the Vostok ice core site, Antarctica. The simplest model, often used but rarely valid, assumes a uniform attenuation rate everywhere along the flowline, so that total attenuation is proportional to ice thickness. The next simplest model uses spatially varying temperatures predicted by an ice-flow model and assumes uniform chemistry. Additional models account for spatially varying chemistry using englacial stratigraphy. We find that the roundtrip attenuation to the bed can easily differ by 10 dB or more between the uniform attenuation-rate model and models that account for variable ice temperature. Such differences are sufficient to confound the delineation of dry and wet beds. Also including spatial variations in chemistry produces smaller differences (<10 dB), but the magnitude of these differences depends on the relative importance of dry and wet deposition of impurities in the past. Accounting for dry-deposited impurities requires ice-flow modeling and results in larger differences from all other models, which assume uniform chemistry or wet deposition only. These results indicate that modeling the spatial variation of attenuation requires a spatially varying temperature model in order to infer bed conditions from bed returned power accurately, and that both ice core data and radar stratigraphy are also strongly desirable.
Keywords: Antarktis; geofysikk; glasiologi; innlandsis

Rapid development of anisotropic ice-crystal-alignment fabrics inferred from englacial radar polarimetry, central West Antarctica - Matsuoka, Kenichi; Power, Donovan; Fujita, Shuji; Raymond, Charles F (Journal of Geophysical Research: Earth Surface, 2012)
Anisotropy in englacial radar power was measured using 60-MHz and 179-MHz copolarized pulse-modulated radar at 19 sites in central West Antarctica. The study region is a 100 × 300 km2area near the West Antarctic Ice Sheet Divide that separates ice flow toward the Ross and Amundsen Embayments. The frequency dependence of the returned power indicates that most of the radar data are affected by vertical variations in the crystal-orientation fabric (COF), though the 60-MHz data are more affected by acidity contrasts in the top 1000 m. Significant polarimetric variations occur at most sites, likely due to effects of the anisotropic COF patterns. More anisotropic variations occur at sites with significant horizontal strain, whereas more isotropic variations occur at sites where vertical compression dominates. Azimuthal shifts with depth of the principal axes of COF were found in shallow ice near the current flow divide and at greater depths over locations of rough bed. The former indicates that the divide has differentially migrated, resulting in a rotation of the principal COF axes. Nevertheless, the regionally consistent radar signatures suggest that the first-order ice properties in this area have remained constant and that no major changes in the strain configuration or ice topography have occurred for the past five to eight thousand years. We conclude that shallow polarimetric features can be related to the current strain configurations, and that englacial polarimetric features can help constrain current ice rheology and evolution of the ice topography.
Keywords: Antarktis; glasiologi; innlandsis; iskrystaller; polarimetrisk radar; topografi

Review of A complete guide to Antarctic wildlife: birds and mammals of the Antarctic Continent and the Southern Ocean, by Hadoram Shirihai - Mehlum, Fridtjof (Polar Research, 2012)
This impressive book is an invaluable, fully illustrated, wildlife guide for tourists and scientists visiting the Southern Ocean and Antarctica.
Keywords: Antarktis; Sørishavet; bokanmeldelser; dyreliv; fugler; marin biologi; ornitologi; pattedyr; zoologi

Polar operations in Antarctica – operating the Troll Research Station, Dronning Maud Land - Mikelborg, Øystein; Pedersen, Ken (Fram forum, 2012)
Keywords: Dronning Maud Land; Troll forskningsstasjon; ekspedisjoner; logistikk; polarområdene

The oldest elasmosaurs (Sauropterygia, Plesiosauria) from Antarctica, Santa Marta Formation (upper Coniacian? Santonian-upper Campanian) and Snow Hill Island Formation (upper Campanian-lower Maastrichtian), James Ross Island - O'Gorman, José P (Polar Research, 2012)
Elasmosaurs are recorded for the first time in the Lachman Crags Member (Beta Member) of the Santa Marta Formation (lower Campanian) and in the Herbert Sound Member of the Snow Hill Island Formation (upper Campanian). These are the first elasmosaurids from James Ross Island, Antarctic Peninsula. These records greatly improve our knowledge of the taxonomic diversity of plesiosaurs of the Santa Marta Formation and Herbert Sound Member of the Snow Hill Island Formation, and extend the lower limit of the record of Elasmosauridae in Antarctica to the lower Campanian, making this the oldest record of an Antarctic elasmosaur. Keywords: Elasmosauridae; Antarctica; Late Cretaceous.
Keywords: Antarktis; geologi; paleontologi

Atmospheric mercury observations from Antarctica: seasonal variation and source and sink region calculations - Pfaffhuber, Katrine Aspmo; Berg, Torunn; Hirdman, D; Stohl, Andreas (Atmospheric Chemistry and Physics (Print), 2012)
Long term atmospheric mercury measurements in the Southern Hemisphere are scarce and in Antarctica completely absent. Recent studies have shown that the Antarctic continent plays an important role in the global mercury cycle. Therefore, long term measurements of gaseous elemental mercury (GEM) were initiated at the Norwegian Antarctic Research Station, Troll (TRS) in order to improve our understanding of atmospheric transport, transformation and removal processes of GEM. GEM measurements started in February 2007 and are still ongoing, and this paper presents results from the first four years. The mean annual GEM concentration of 0.93 ± 0.19 ng m−3 is in good agreement with other recent southern-hemispheric measurements. Measurements of GEM were combined with the output of the Lagrangian particle dispersion model FLEXPART, for a statistical analysis of GEM source and sink regions. It was found that the ocean is a source of GEM to TRS year round, especially in summer and fall. On time scales of up to 20 days, there is little direct transport of GEM to TRS from Southern Hemisphere continents, but sources there are important for determining the overall GEM load in the Southern Hemisphere and for the mean GEM concentration at TRS. Further, the sea ice and marginal ice zones are GEM sinks in spring as also seen in the Arctic, but the Antarctic oceanic sink seems weaker. Contrary to the Arctic, a strong summer time GEM sink was found, when air originates from the Antarctic plateau, which shows that the summertime removal mechanism of GEM is completely different and is caused by other chemical processes than the springtime atmospheric mercury depletion events. The results were corroborated by an analysis of ozone source and sink regions.
Publisher: Copernicus Publications
Keywords: Dronning Maud Land; Troll forskningsstasjon; atmosfæren; forurensning; miljøgifter; ozonlaget

Being there: examining the behaviour of Antarctic tourists through their blogs - Roura, Ricardo M (Polar Research, 2012)
Most visitors to Antarctica today are commercial tourists. Over 150 000 tourists visited Antarctica between 2007 and 2010, making up more than 700 000 person/landings. Despite the scale of tourism in Antarctica, knowledge about its environmental impacts is generally inconclusive, and monitoring is limited. This article examines tourist behaviour regarding the environment using information available on travel weblogs (blogs) posted by tourists on the Internet. Fifty blogs describing Antarctic travel were analysed, mostly as part of organized tourism cruises, during the four Antarctic summer seasons between 2007 and 2010, both qualitatively and quantitatively. The blogs described the activities of 90 people who had visited Deception Island as part of their itinerary and who, overall, had undertaken at least 190 person/landings in Antarctica. Blog analysis highlighted the importance of wildlife as a tourist attraction. In the blogs it was apparent that touristwildlife interactions result in a range of behaviours from both individual tourists and animals. Tourism results in cultural traces and other environmental consequences, although some of these would not be judged as ‘‘impacts’’ under the current practice of implementing the Protocol on Environmental Protection to the Antarctic Treaty. Blogs showed many more instances of compliance than of noncompliance with environmental regulations. Tourist blogs illustrate the behavioural processes by which environmental impacts from tourism could occur, which are repeated through thousands of person-landings and other activities in Antarctica every season. Precautionary action may be a practical alternative to manage tourism at some sites until it is clearer how this activity affects the environment.
Keywords: Antarktis; miljøvern; polarområdene; turisme

Surface mass balance and stable oxygen isotope ratios from shallow firn cores on Fimbulisen, East Antarctica - Schlosser, Elisabeth; Anschütz, Helgard; Isaksson, Elisabeth; Martma, T; Divine, Dmitry; Nøst, Ole Anders (Annals of Glaciology, 2012)
The mass balance of Antarctica is one of the crucial factors for determining sea-level change in a warming climate. The marginal zones of the continent, namely the ice shelves, are most sensitive to climate change. During the 2009/10 austral summer an extensive glaciological field campaign was carried out on Fimbulisen, an ice shelf in East Antarctica, to investigate its recent surface mass balance. Shallow (10–18 m) firn cores were drilled and accumulation rates and stable-isotope ratios determined. For firn-core dating, two different methods were compared: (1) seasonal variations of stable oxygen isotope ratios (δ18O), and (2) dielectric profiling, including using the volcanic eruptions of Pinatubo, Philippines (1991), and El Chichόn, Mexico (1982), as time markers. The mean annual accumulation for the period 1992–2009 ranges from 298 to 349 mmw.e. a–1. The interannual variability at the drilling sites is >30%. Accumulation rates show a weak decreasing trend during the past 20–30 years, which is statistically significant only for one of the cores. Stable-isotope ratios were compared to the snowfall temperature of Neumayer station. Neither the temperatures nor the δ18O values show any trend for the investigated time period.
Publisher: Cambridge University Press
Keywords: Dronning Maud Land; glasiologi

The impact of human activities on wilderness and aesthetic values in Antarctica - Summerson, Rupert; Bishop, Ian D. (Polar Research, 2012)
There has been little progress in implementing protection of wilderness and aesthetic values in Antarctica since the coming into force of the Protocol on Environmental Protection to the Antarctic Treaty in 1998. This can in part be attributed to a lack of research defining these values and showing how they may be assessed. In 2009, a survey comprising 90 images of Antarctic landscapes was established on the Internet to canvass as wide a cross-section of people with an interest in Antarctica as possible on their perceptions of wilderness and their aesthetic preference. At the time of writing, over 337 respondents from 23 nationalities have taken part in the survey. Responses were analysed to determine the effect of human presence, both transient and as infrastructure, on perceptions of wilderness and aesthetic values. The analysis was in three parts: (1) all images combined; (2) images grouped by landscape type, derived from the Environmental Domains of Antarctica regionalization; and (3) 16 pairs of digitally manipulated images of which respondents were shown either an original image or one in which human presence had been either digitally removed or added. Responses to images grouped by landscape type show that coastal and ice-free areas are less valued both aesthetically and as wilderness than mountainous and ice-covered terrains. Signs of human presence were found to make images significantly less likely to be considered as wilderness and also reduced their aesthetic rating. This demonstrates that human impacts on these values are measureable. Keywords: Antarctica; Madrid Protocol; wilderness; aesthetic; values; photographs.
Keywords: Antarktis; Antarktistraktaten; estetikk; menneskelig påvirkning; miljøpåvirkning; miljøvern

Chronostratigraphic framework for the IODP Expedition 318 cores from the Wilkes Land Margin: Constraints for paleoceanographic reconstruction - Tauxe, Lisa; Stickley, Catherine; Sugisaki, Saiko; Bijl, Peter K; Bohaty, S M; Brinkhuis, Henk; Escutia, Carlota; Flores, J A; Houben, A J P; Iwai, Masao; Jiménez-Espejo, Francisco J; McKay, Robert; et al. (Paleoceanography, 2012)
The Integrated Ocean Drilling Program Expedition 318 to the Wilkes Land margin of Antarctica recovered a sedimentary succession ranging in age from lower Eocene to the Holocene. Excellent stratigraphic control is key to understanding the timing of paleoceanographic events through critical climate intervals. Drill sites recovered the lower and middle Eocene, nearly the entire Oligocene, the Miocene from about 17 Ma, the entire Pliocene and much of the Pleistocene. The paleomagnetic properties are generally suitable for magnetostratigraphic interpretation, with well-behaved demagnetization diagrams, uniform distribution of declinations, and a clear separation into two inclination modes. Although the sequences were discontinuously recovered with many gaps due to coring, and there are hiatuses from sedimentary and tectonic processes, the magnetostratigraphic patterns are in general readily interpretable. Our interpretations are integrated with the diatom, radiolarian, calcareous nannofossils and dinoflagellate cyst (dinocyst) biostratigraphy. The magnetostratigraphy significantly improves the resolution of the chronostratigraphy, particularly in intervals with poor biostratigraphic control. However, Southern Ocean records with reliable magnetostratigraphies are notably scarce, and the data reported here provide an opportunity for improved calibration of the biostratigraphic records. In particular, we provide a rare magnetostratigraphic calibration for dinocyst biostratigraphy in the Paleogene and a substantially improved diatom calibration for the Pliocene. This paper presents the stratigraphic framework for future paleoceanographic proxy records which are being developed for the Wilkes Land margin cores. It further provides tight constraints on the duration of regional hiatuses inferred from seismic surveys of the region.
Keywords: Sørishavet; biostratigrafi; chronostratigrafi; magnetostratigrafi; paleoklimatologi; paleoseanografi; seismologi

Trampling on maritime Antarctica: can soil ecosystems be effectively protected through existing codes of conduct? - Tejedo, Pablo; Pertierra, Luis R; Benayas, Javier; Convey, Peter; Justel, Ana; Quesada, Antonio (Polar Research, 2012)
Soil trampling is one of the most obvious direct negative human impacts in Antarctica. Through a range of experiments and field studies based on quantitative physical (soil penetration resistance) and biological (collembolan abundance) indicators, we evaluate the current codes of conduct relating to the protection of Antarctic soils from the consequences of pedestrian impacts. These guidelines include using, where available, established paths that cross vegetation-free soils. However, the effectiveness of this strategy is highly dependent on context. Limited intensity use - below 100 foot passes per year - produces small changes at the soil surface that can recover relatively rapidly, suggesting that the dispersal of activity across wider corridors may be the most appropriate option. However, for paths with a higher use level and those located in steep-sloped sites, it is desirable to define a single track, following stony or bouldery surfaces wherever possible, to keep the disturbed area to a minimum. It is clear that both environmental conditions and expected use levels must be taken into account in determining when and where it is more appropriate to concentrate or disperse human activities. Even though they may have performed satisfactorily to date, the increasing pressure in terms of numbers of visits for certain sites may make it necessary to revise existing codes of conduct. Keywords: Trampling impacts; environmental monitoring; low impact practices; soil resilience; soil penetration resistance; collembolan abundance.
Keywords: Antarktis; jord; menneskelig påvirkning; miljøvern; økosystemer

Foreword: The complex business of managing human activities and protecting the environment of the polar regions - Tin, Tina; Liggett, Daniela; Maher, Patrick T (Polar Research, 2012)
The thematic cluster ‘‘Human impacts in the Arctic and Antarctic’’ in Polar Research has its origins in the International Polar Year (2007-09) Oslo Science Conference held in Oslo, Norway, from 8 to 12 June 2010. We were the co-convenors of the session ‘‘Human impacts in the Arctic and Antarctic: regulatory and management implications,’’ in which 27 talks and 21 posters were presented over the course of two days. We invited contributors to the conference session to explore all types of impacts of human activities and regional environmental change in the polar regions, with a special focus on highlighting the management priorities for the protection of the landscape (environment and people) of the polar regions in the face of increasing human activity. Exploring a wide range of topics ranging from human wildlife interactions to chemical contamination and from whaling to polar tourism, contributors provided examples of existing environmental management regimes that are working as well as those that are not.
Keywords: Antarktis; forurensning; menneskelig påvirkning; miljøvern; polarområdene; turisme; økosystemer

Culturable heterotrophic bacteria from Potter Cove, Antarctica, and their hydrolytic enzymes production - Tropeano, Mauro; Coria, Silvia; Turjanski, Adrían; Cicero, Daniel; Bercovich, Andrés; Mac Cormack, Walter; Vázquez, Susana (Polar Research, 2012)
Affiliations of the dominant culturable bacteria isolated from Potter Cove, South Shetland Islands, Antarctica, were investigated together with their production of cold-active hydrolytic enzymes. A total of 189 aerobic heterotrophic bacterial isolates were obtained at 4°C and sorted into 63 phylotypes based on their amplified ribosomal DNA restriction analysis profiles. The sequencing of the 16S rRNA genes of representatives from each phylotype showed that the isolates belong to the phyla Proteobacteria (classes Alpha- and Gamma-proteobacteria), Bacteroidetes (class Flavobacteria), Actinobacteria (class Actinobacteria) and Firmicutes (class Bacilli). The predominant culturable group in the site studied belongs to the class Gammaproteobacteria, with 65 isolates affiliated to the genus Pseudoalteromonas and 58 to Psychrobacter. Among the 189 isolates screened, producers of amylases (9.5%), pectinases (22.8%), cellulases (14.8%), CM-cellulases (25.4%), xylanases (20.1%) and proteases (44.4%) were detected. More than 25% of the isolates produced at least one extracellular enzyme, with some of them producing up to six of the tested extracellular enzymatic activities. These results suggest that a high culturable bacterial diversity is present in Potter Cove and that this place represents a promising source of biomolecules. Keywords: Microbial enzymes; Antarctic bacteria; marine bacteria; cold enzymes; psychrophiles.
Keywords: Sørishavet; alger; bakterier; biodiversitet; marin biologi; sjøvann; økologi; økosystemer

Chemical composition of tropospheric air masses encountered during high altitude flights (>11.5 km) during the 2009 fall Operation Ice Bridge field campaign - Yang, Mei Ying Melissa; Vay, Stephanie A; Stohl, Andreas; Choi, Yonghoon; Diskin, Glenn S; Sachse, Glen W; Blake, Donald R (Journal of Geophysical Research: Atmospheres, 2012)
As part of the 2009 Operation Ice Bridge campaign, the NASA DC-8 aircraft was used to fill the data-time gap in laser observation of the changes in ice sheets, glaciers and sea ice between ICESat-I (Ice, Cloud, and land Elevation Satellite) and ICESat-II. Complementing the cryospheric instrument payload were four in situ atmospheric sampling instruments integrated onboard to measure trace gas concentrations of CO2, CO, N2O, CH4, water vapor and various VOCs (Volatile Organic Compounds). This paper examines two plumes encountered at high altitude (12 km) during the campaign; one during a southbound transit flight (13°S) and the other at 86°S over Antarctica. The data presented are especially significant as the Southern Hemisphere is heavily under-sampled during the austral spring, with few if any high-resolution airborne observations of atmospheric gases made over Antarctica. Strong enhancements of CO, CH4, N2O, CHCl3, OCS, C2H6, C2H2 and C3H8 were observed in the two intercepted air masses that exhibited variations in VOC composition suggesting different sources. The transport model FLEXPART showed that the 13°S plume contained predominately biomass burning emissions originating from Southeast Asia and South Africa, while both anthropogenic and biomass burning emissions were observed at 86°S with South America and South Africa as indicated source regions. The data presented here show evidence that boundary layer pollution is transported from lower latitudes toward the upper troposphere above the South Pole, which may not have been observed in the past.
Keywords: Antarktis; atmosfæren; atmosfæriske gasser; forurensning; havis; innlandsis; isbreer; isbrem; kjemi; kjemiske analyser; menneskelig påvirkning; meteorologi; sjøis; sporgass

Variation of accumulation rates over the last eight centuries on the East Antarctic Plateau derived from volcanic signals in ice cores - Anschütz, Helgard; Sinisalo, Anna; Isaksson, Elisabeth; McConnell, Joseph R; Hamran, Svein Erik; Bisiaux, M M; Pasteris, Daniel R; Neumann, Thomas; Winther, Jan-Gunnar (Journal of Geophysical Research: Atmospheres, 2011)
Volcanic signatures in ice-core records provide an excellent means to date the cores and obtain information about accumulation rates. From several ice cores it is thus possible to extract a spatio-temporal accumulation pattern. We show records of electrical conductivity and sulfur from 13 firn cores from the Norwegian-USA scientific traverse during the International Polar Year 2007–2009 (IPY) through East Antarctica. Major volcanic eruptions are identified and used to assess century-scale accumulation changes. The largest changes seem to occur in the most recent decades with accumulation over the period 1963–2007/08 being up to 25% different from the long-term record. There is no clear overall trend, some sites show an increase in accumulation over the period 1963 to present while others show a decrease. Almost all of the sites above 3200 m above sea level (asl) suggest a decrease. These sites also show a significantly lower accumulation value than large-scale assessments both for the period 1963 to present and for the long-term mean at the respective drill sites. The spatial accumulation distribution is influenced mainly by elevation and distance to the ocean (continentality), as expected. Ground-penetrating radar data around the drill sites show a spatial variability within 10–20% over several tens of kilometers, indicating that our drill sites are well representative for the area around them. Our results are important for large-scale assessments of Antarctic mass balance and model validation.
Keywords: Antarktis; akkumulasjon; geovitenskap; glasiologi; innlandsis; iskjerner; klimatologi

Implications of meltwater pulse events for soil biology and biogeochemical cycling in a polar desert - Ball, Becky A; Barrett, J E; Gooseff, Mike N; Virginia, Ross A; Wall, Diana H (Polar Research, 2011)
The McMurdo Dry Valleys are one of the most arid environments on Earth. Over the soil landscape for the majority of the year, biological and ecosystem processes in the dry valleys are constrained by the low temperatures and limited availability of water. The prevalence of these physical limitations in controlling biological and ecosystem processes makes the dry valleys a climatesensitive system, poised to experience substantial changes following projected future warming. Short-duration increases in summer temperatures are associated with pulses of water from melting ice reserves, including glaciers, snow and permafrost. Such pulses alter soil geochemistry by mobilizing and redistributing soil salts (via enhanced weathering, solubility and mobility), which can alter habitat suitability for soil organisms. Resulting changes in soil community composition or distribution may alter the biogeochemical processes in which they take part. Here, we review the potential impacts of meltwater pulses and present new field data documenting instances of meltwater pulse events that result from different water sources and hydrological patterns, and discuss their potential influence on soil biology and biogeochemistry. We use these examples to discuss the potential impacts of future climate change on the McMurdo Dry Valley soil ecosystem.Keywords: Water pulse; climate change; polar desert; International Polar Year; discrete warming events; soil biogeochemistry.
Keywords: Antarktis; Det internasjonale geofysiske år (IGY); IPY; biogeokjemi; biologi; jord; klimaendringer; polarørken

Some like it cold: microbial transformations of mercury in polar regions - Barkay, Tamar; Kroer, Niels; Poulain, Alexandre J (Polar Research, 2011)
The contamination of polar regions with mercury that is transported from lower latitudes as inorganic mercury has resulted in the accumulation of methylmercury (MeHg) in food chains, risking the health of humans and wildlife. While production of MeHg has been documented in polar marine and terrestrial environments, little is known about the responsible transformations and transport pathways and the processes that control them. We posit that as in temperate environments, microbial transformations play a key role in mercury geochemical cycling in polar regions by: (1) methylating mercury by one of four proposed pathways, some not previously described; (2) degrading MeHg by activities of mercury resistant and other bacteria; and (3) carrying out redox transformations that control the supply of the mercuric ion, the substrate of methylation reactions. Recent analyses have identified a high potential for mercury-resistant microbes that express the enzyme mercuric reductase to affect the production of gaseous elemental mercury when and where daylight is limited. The integration of microbially mediated processes in the paradigms that describe mercury geochemical cycling is therefore of high priority especially in light of concerns regarding the effect of global warming and permafrost thawing on input of MeHg to polar regions. Keywords: Microbiology; mercury biogeochemistry; redox transformations; polar regions; methylation
Keywords: Antarktis; biogeokjemi; forurensning; mikrobiologi; miljøvern; polarområdene; økosystemer

Contaminant profiles of air and soil around Casey station, Antarctica; Discerning local and distant contaminant sources - Bengtson Nash, Susan; Xiao, H; Schlabach, Martin; Stark, J; King, C; Hung, H (Society for Environmental Toxicology and Chemistry (SETAC), Europe 21st Annual Meeting. Ecosystem Protection in a Sustainable World: A Challenge for Science and Regulation, 2011)
The primary input of Persistent Organic Pollutant (POP) contamination to the Antarctic is expected to be via Long Range Atmospheric Transport (LRAT) from emissions in neighboring Southern hemisphere nations In addition to LRAT, system input of POPs must increasingly consider alternate pathways Human activity in the Antarctic represents a potential direct source of both legacy and current-use chemicals It has been two decades since the organic chemical composition of air masses arriving in the Australian Antarctic Territory (AAT), which spans the majority of the eastern Antarctic sector, was last investigated Here we present the first atmospheric measurements made as part of a new continuous monitoring effort at Casey station (66°17’ S 110°31’ E), one of Australia’s all-year research stations The results are evaluated alongside POP contamination data of soil samples collected around the Casey station perimeter and the respective sample profiles are assessed for clues as to local and distant contamination sources Results suggest a potential local source of the currently produced, involatile, deca-brominated PBDE congener 209 which contributed substantially to PBDE profiles of all samples Profiles of polychlorinated biphenyls (PCBs) and rganochlorine pesticides on the other hand primarilly support LRAT as the primary input pathway of these contaminants, whilst a dominance of endosulfan in air samples evidences its ongoing application in the southern hemisphere.
Keywords: Antarktis; atmosfæren; forskningsstasjoner; forurensning; miljøgifter

Environmental forcings of Paleogene Southern Ocean dinoflagellate biogeography - Bijl, Peter K; Pross, Jörg; Warnaar, Jeroen; Stickley, Catherine E; Huber, Matthew; Guerstein, Raquel; Houben, Alexander J P; Sluijs, Appy; Visscher, Henk; Brinkhuis, Henk (Paleoceanography, 2011)
Despite warm polar climates and low meridional temperature gradients, a number of different high-latitude plankton assemblages were, to varying extents, dominated by endemic species during most of the Paleogene. To better understand the evolution of Paleogene plankton endemism in the high southern latitudes, we investigate the spatiotemporal distribution of the fossil remains of dinoflagellates, i.e., organic-walled cysts (dinocysts), and their response to changes in regional sea surface temperature (SST). We show that Paleocene and early Eocene (∼65–50 Ma) Southern Ocean dinocyst assemblages were largely cosmopolitan in nature but that a distinct switch from cosmopolitan-dominated to endemic-dominated assemblages (the so-called “transantarctic flora”) occurred around the early-middle Eocene boundary (∼50 Ma). The spatial distribution and relative abundance patterns of this transantarctic flora correspond well with surface water circulation patterns as reconstructed through general circulation model experiments throughout the Eocene. We quantitatively compare dinocyst assemblages with previously published TEX86–based SST reconstructions through the early and middle Eocene from a key locality in the southwest Pacific Ocean, ODP Leg 189 Site 1172 on the East Tasman Plateau. We conclude that the middle Eocene onset of the proliferation of the transantarctic flora is not linearly correlated with regional SST records and that only after the transantarctic flora became fully established later in the middle Eocene, possibly triggered by large-scale changes in surface-ocean nutrient availability, were abundances of endemic dinocysts modulated by regional SST variations.
Keywords: Sørishavet; biogeografi; fossiler; paleobotanikk; paleoseanografi; plankton

Variability of nutrient and thermal structure in surface waters between New Zealand and Antarctica, October 2004-January 2005 - Campanelli, Alessandra; Massolo, Serena; Grilli, Federica; Marini, Mauro; Paschini, Elio; Rivaro, Paola; Artegiani, Antonio; Jacobs, Stanley S (Polar Research, 2011)
We describe the upper ocean thermal structure and surface nutrient concentrations between New Zealand and Antarctica along five transects that cross the Subantarctic Front, the Polar Front and the southern Antarctic Circumpolar Current front. The surface water thermal structure is coupled with variations in surface nutrient concentrations, making water masses identifiable by both temperature and nutrient ranges. In particular, a strong latitudinal gradient in orthosilicate concentration is centred at the Polar Front. On the earlier sections, which extend south-west from the Campbell Plateau, orthosilicate increases sharply southward from 10-15 to 50-55µmol l-1, between 58°S and 60°S, while surface temperature drops from 7°C to 2°C. Nitrate increases more regularly toward the south, with concentrations ranging from 10-12µmol l-1 at 54°S to 25-30µmol l-1 at 66°S. The same features are observed during the later transects between New Zealand and the Ross Sea, but the sharp silica and surface temperature gradients are shifted between 60°S and 64°S. Both temporal and spatial factors may influence the observed variability. The January transect suggests an uptake of silica, orthophosphate and nitrate between 63°S and 70°S over the intervening month, with an average depletion near 37%, 44% and 29%, respectively. An N/P apparent drawdown ratio of 8.8±4.1 and an Si/N apparent drawdown ratio >1 suggests this depletion results from a seasonal diatom bloom. A southward movement of the oceanic fronts between New Zealand and the Ross Sea relative to prior measurements is consistent with reports of recent warming and changes in the Antarctic Circumpolar Current. Keywords: Southern Ocean, nutrients, silica belt, Antarctic Circumpolar Current, expendable bathythermograph.
Keywords: Rosshavet; Sørishavet; fytoplankton; havstrømmer; næringsstoff; vannmasser; økosystemer

Review of Tourism and change in polar regions: climate, environment and experience and Cruise tourism in polar regions: promoting environmental and social sustainability? - Capelotti, P J (Polar Research, 2011)
These two edited volumes, which cover much of the same ground, both begin from a common premise: polar tourism, as its been experienced by wealthy travellers for over a century, has a very definite shelf life. With the acceleration of global climate change, the Arctic and Antarctic are being changed, changed rapidly, perhaps permanently and, if one pays attention to the news, seemingly by the day. When combined with popular documentaries and feature films like An inconvenient truth, March of the penguins and Happy feet potential polar tourists have been sensitized to see the polar regions not as implacably hostile wastes once challenged only by the likes of Nansen, Amundsen, Scott and Shackleton but as irreplaceably fragile zones that, once lost, will take some essential part of the planet with them.
Keywords: Antarktis; bokanmeldelser; cruiseturisme; global oppvarming; klimaendringer; miljøvern; polarområdene; turisme; økologi

Princess Elisabeth Antarctica: an International Polar Year outreach and media success story - Cheek, Joseph; Huyge, Ben; Pomereu, Jean de (Polar Research, 2011)
One of the priorities of the fourth International Polar Year (IPY) was to increase awareness of the polar regions and polar science among the general public through education, communication and other forms of outreach. This paper reports on the media coverage of Princess Elisabeth Antarctica (PEA), Belgium’s ‘‘zero-emission’’ Antarctic research station designed by the nonprofit International Polar Foundation (IPF) to run on wind and solar energy and to employ state-of-the-art forms of energy management and other ‘‘green’’ technology. This paper provides background information on PEA, a review of IPF’s media strategy for the project, a description of media coverage of the station and a discussion of the way in which the IPF’s main messages were reported in the media. IPF staff surveyed approximately 300 media reports released between February 2004, when the PEA project was announced to the general public, and June 2010, when the IPF presented their findings at the IPY conference in Oslo. PEA was featured 580 times in print and web media in Belgium, and 303 times outside Belgium. Major international agencies such as the Associated Press, Agence France Presse, the BBC, Al-Jazeera and Reuters covered the project. On television and radio, PEA was featured in news broadcasts from all four major television networks in Belgium, most major radio stations and 34 different television and radio news outlets outside Belgium. The paper concludes that the media coverage for PEA was significant and suggests reasons why the project was so widely reported. Keywords: Media and outreach; media strategy; Antarctic research stations; energy management system; renewable energy; reducing environmental footprint
Keywords: Antarktis; Det internasjonale polaråret; fornybar energi; forskningsstasjoner; fotavtrykk; mediadekning; miljø; polarområdene

Global southern limit of flowering plants and moss peat accumulation - Convey, Peter; Hopkins, David W; Roberts, Stephen J; Tyler, Andrew N (Polar Research, 2011)
The ecosystems of the western Antarctic Peninsula, experiencing amongst the most rapid trends of regional climate warming worldwide, are important “early warning” indicators for responses expected in more complex systems elsewhere. Central among responses attributed to this regional warming are widely reported population and range expansions of the two native Antarctic flowering plants, Deschampsia antarctica and Colobanthus quitensis. However, confirmation of the predictions of range expansion requires baseline knowledge of species distributions. We report a significant southwards and westwards extension of the known natural distributions of both plant species in this region, along with several range extensions in an unusual moss community, based on new survey work in a previously unexamined and un-named low altitude peninsula at 69º22.0’S 71º50.7’W in Lazarev Bay, north-west Alexander Island, southern Antarctic Peninsula. These plant species therefore have a significantly larger natural range in the Antarctic than previously thought. This site provides a potentially important monitoring location near the southern boundary of the region currently demonstrated to be under the influence of rapidly changing climate trends. Combined radiocarbon and lead isotope radiometric dating suggests that this location was most likely deglaciated sufficiently to allow peat to start accumulating towards the end of the 19th century, which we tentatively link to a phase of post-1870 climate amelioration. We conclude that the establishment of vegetation in this location is unlikely to be linked to the rapid regional warming trends recorded along the Antarctic Peninsula since the mid-20th century. Antarctic plants, distribution limits, peat accumulation, dating.
Keywords: Antarktis; hårgress; klimaendringer; perleurt; planter; økosystemer

Polythermal glacier hydrology: a review - Irvine-Fynn, Tristram D L; Hodson, Andrew J; Moorman, Brian J; Vatne, Geir; Hubbard, Alun L (Reviews of Geophysics, 2011)
The manner by which meltwater drains through a glacier is critical to ice dynamics, runoff characteristics, and water quality. However, much of the contemporary knowledge relating to glacier hydrology has been based upon, and conditioned by, understanding gleaned from temperate valley glaciers. Globally, a significant proportion of glaciers and ice sheets exhibit nontemperate thermal regimes. The recent, growing concern over the future response of polar glaciers and ice sheets to forecasts of a warming climate and lengthening summer melt season necessitates recognition of the hydrological processes in these nontemperate ice masses. It is therefore timely to present an accessible review of the scientific progress in glacial hydrology where nontemperate conditions are dominant. This review provides an appraisal of the glaciological literature from nontemperate glaciers, examining supraglacial, englacial, and subglacial environments in sequence and their role in hydrological processes within glacierized catchments. In particular, the variability and complexity in glacier thermal regimes are discussed, illustrating how a unified model of drainage architecture is likely to remain elusive due to structural controls on the presence of water. Cold ice near glacier surfaces may reduce meltwater flux into the glacier interior, but observations suggest that the transient thermal layer of near surface ice holds a hydrological role as a depth-limited aquifer. Englacial flowpaths may arise from the deep incision of supraglacial streams or the propagation of hydrofractures, forms which are readily able to handle varied meltwater discharge or act as locations for water storage, and result in spatially discrete delivery of water to the subglacial environment. The influence of such drainage routes on seasonal meltwater release is explored, with reference to summer season upwellings and winter icing formation. Moreover, clear analogies emerge between nontemperate valley glacier and ice sheet hydrology, the discussion of which indicates how persistent reassessment of our conceptualization of glacier drainage systems is required. There is a clear emphasis that continued, integrated endeavors focused on process glaciology at nontemperate glaciers are a scientific imperative to augmenting the existing body of research centered on ice mass hydrology.
Keywords: Antarktis; geografi; glasiologi; global oppvarming; hydrologi; innlandsis; isbreer; isbrem; polarområdene

Krill og økosystemtokt med G.O.Sars i Sørishavet - Iversen, Svein A (Polaråret 2007-2008 : det norske bidraget, 2011)
Keywords: Bouvetøya; Det Internasjonale polaråret 2007; krill; marine økosystemer; plankton; polarforskning

Low-ozone events in the southern polar summer as indicated by Met Office ozone analyses - Jackson, David; Orsolini, Yvan Joseph; Engelsen, Ola (Journal of Geophysical Research: Atmospheres, 2011)
Southern summer low-ozone events (LOEs) are examined using Met Office ozone analyses for 2005–2007. At 31 hPa, tongues of low-ozone air are pulled out of the polar region and extend to lower latitudes. Low tongues are also seen at 100 hPa, but there the low ozone is transported from low to high latitudes. These low tongues are frequently superimposed on one another, meaning that there are often also reductions in total ozone. What is striking is that at high latitudes, summer total ozone is typically lower over the Weddell Sea than at other longitudes. The low-ozone tongues at 31 and 100 hPa are consistent with transport associated with planetary waves. Daily geopotential height fields show a poleward and westward wave tilt with height, indicating the presence of baroclinic waves. The tilt enables the superimposition of the low-ozone tongues at 100 and 31 hPa. Filtered geopotential height anomalies reveal the presence of waves reported in other studies and indicate the connection between tropospheric and stratospheric wave dynamics in driving the LOEs. There is also a high connection between the LOEs and ultraviolet (UV) Index. The Weddell Sea region gets up to 20–30% more UV than the zonal mean, and the tip of South America gets about 10–25% more. There have been numerous studies of the impacts of increased UV on the Antarctic marine ecosystem during the springtime ozone hole, and our results indicate there is a case for these studies being extended to the summer LOEs.
Keywords: Antarktis; UV-stråling; Weddellhavet; ozonlaget; polarområdene; stratosfæren; ultrafiolett stråling

The oldest plesiosaur (Reptilia, Sauropterygia) from Antarctica - Kellner, Alexander Wilhelm Armin; Simões, Tiago Rodrigues; Riff, Douglas; Grillo, Orlando; Romano, Pedro; Paula, Helder de; Ramos, Renato; Carvalho, Marcelo; Sayão, Juliana; Oliveira, Gustavo; Rodrigues, Taissa (Polar Research, 2011)
Antarctic plesiosaurs are known from the Upper Cretaceous López de Bertodano and Snow Hill Island formations (Campanian to upper Maastrichtian), which crop out within the James Ross Basin region of the Antarctic Peninsula. Here we describe the first plesiosaur fossils from the Lachman Crags Member of the Santa Marta Formation, north-western James Ross Island. This material constitutes the stratigraphically oldest plesiosaur occurrence presently known from Antarctica, extending the occurrence of plesiosaurians in this continent back to Santonian times (86.3-83.5 Mya). Furthermore, MN 7163-V represents the first plesiosaur from this region not referable to the Elasmosauridae nor Aristonectes, indicating a greater diversity of this group of aquatic reptiles in Antarctica than previously suspected. Keywords: James Ross Island; Antarctica; plesiosauria; Late Cretaceous; Museu Nacional.
Keywords: Antarktis; geologi; paleontologi; svaneøgler

Meteoritten som vitnet om liv på Mars - Knutsen, Henning; Matland, Aleksander (Naturen, 2011)
Har livet på Jorda blitt ført hit fra tidligere liv på planeten Mars? I 1996 hevdet en gruppe forskere at en meteoritt fra Mars faktisk inneholdt spor etter organisk liv. Hvis dette virkelig var tilfelle, ville det medføre en revolusjon for vårt syn på verden og det univers vi befinner oss i. Men vitenskapsfolk besitter sunn skepsis, og hos dem kommer ikke tvilen tiltalte til gode. Nå mener de fleste ekspertene at funnet var for godt til å være sant.
Keywords: Antarktis; astrofysikk; mikrobiologi

Seler brukt som "forskningsassistenter" for å utforske polhavene - Kovacs, Kit M (Polaråret 2007-2008 : det norske bidraget, 2011)
Keywords: Det Internasjonale polaråret 2007; Sørishavet; polarforskning; polarområdene; seler; sjøpattedyr

Recovery Lakes, East Antarctica: Radar assessment of sub-glacial water extent - Langley, Kirsty; Kohler, Jack; Matsuoka, Kenichi; Sinisalo, Anna; Scambos, Ted; Neumann, Thomas; Muto, Atsuhiro; Winther, Jan-Gunnar; Albert, Mary (Geophysical Research Letters, 2011)
A fast-flowing tributary of Recovery ice stream penetrates more than 500 km into the interior of East Antarctica. Recent satellite-based studies found surface features in the onset area of this tributary that indicate a significant subglacial hydraulic system, including four large smooth basins, the typical surface expression of large subglacial lakes, as well as eleven smaller areas over which ice-sheet surface elevations rapidly changed by discharge/filling of subglacial water. Here we present the first ice-penetrating radar evidence of subglacial conditions in this area. We identified a distinct ice-water interface only over a limited area within the boundaries of the investigated large smooth basins, previously hypothesized to be water-filled lakes. The radar characteristics in some areas are similar to those of a drained lake, indicating that parts of the bed are wet, but not a typical lake. We also find evidence for discrete water bodies outside of the lake boundaries. The lines of evidence indicate that the northern most two Recovery Lakes have recently drained.
Keywords: Antarktis; geofysikk; glasiologi; isbre; isstrøm; radar observasjoner; subglasial innsjø

Antarctic bacterial isolates that produce cold-active extracellular proteases at low temperature but are active and stable at high temperature - Martínez-Rosales, Cecilia; Castro-Sowinski, Susana (Polar Research, 2011)
We report the isolation and identification of bacteria that produce extracellular cold-active proteases, obtained from water samples collected near the Uruguayan Antarctic Base on King George Island, South Shetlands. The bacteria belonged to the genera Pseudomonas (growth between 4 and 30°C) and Flavobacterium (growth between 4 and 18°C). In all cases, extracellular protease production was evident when reaching the stationary phase at 18 and 4ºC, but was not detected at 30ºC. The zymogram revealed the secretion of one extracellular protease per isolate, each with different relative electrophoretic mobility. The extracellular proteases produced at 4ºC showed thermal activity and stability at 30ºC. Both activity and stability at temperature higher that 10ºC have no physiological meaning because the isolates do not experience such temperatures in the Antarctic environment; however, the possible ecological value of cold-active and -stable extracellular proteases is discussed. Keywords: Antarctic, cold-active enzymes, protease.
Keywords: Sørishavet; bakterier; biokjemi; marin biologi; oseanografi

A comparison of the present and last interglacial periods in six Antarctic ice cores - Masson-Delmotte, Valerie; Buiron, Daphné; Ekaykin, Alexey Anatolievich; Frezzotti, M; Gallée, Hubert; Jouzel, Jean; Krinner, Gerhard; Landais, Amaelle; Motoyama, Hideaki; Oerter, Hans; Pol, K; Pollard, D; et al. (Clim. Past, 2011)
We compare the present and last interglacial periods as recorded in Antarctic water stable isotope records now available at various temporal resolutions from six East Antarctic ice cores: Vostok, Taylor Dome, EPICA Dome C (EDC), EPICA Dronning Maud Land (EDML), Dome Fuji and the recent TALDICE ice core from Talos Dome. We first review the different modern site characteristics in terms of ice flow, meteorological conditions, precipitation intermittency and moisture origin, as depicted by meteorological data, atmospheric reanalyses and Lagrangian moisture source diagnostics. These different factors can indeed alter the relationships between temperature and water stable isotopes. Using five records with sufficient resolution on the EDC3 age scale, common features are quantified through principal component analyses. Consistent with instrumental records and atmospheric model results, the ice core data depict rather coherent and homogenous patterns in East Antarctica during the last two interglacials. Across the East Antarctic plateau, regional differences, with respect to the common East Antarctic signal, appear to have similar patterns during the current and last interglacials. We identify two abrupt shifts in isotopic records during the glacial inception at TALDICE and EDML, likely caused by regional sea ice expansion. These regional differences are discussed in terms of moisture origin and in terms of past changes in local elevation histories, which are compared to ice sheet model results. Our results suggest that elevation changes may contribute significantly to inter-site differences. These elevation changes may be underestimated by current ice sheet models.
Publisher: Copernicus Publications
Keywords: Antarktis; Dronning Maud Land; Sørishavet; atmosfæren; glasiologi; iskjerner; klimatologi; meteorologi; stabile isotoper

Pitfalls in radar diagnosis of ice-sheet bed conditions: Lessons from englacial attenuation models - Matsuoka, Kenichi (Geophysical Research Letters, 2011)
Radar power returned from ice-sheet beds has been widely accepted as an indicator of bed conditions. However, the bed returned power also depends on englacial attenuation, which is primarily a function of ice temperature. Here, using a one-dimensional attenuation model, it is demonstrated that, in most cases, variations in bed returned power are dominated by variations in englacial attenuation, rather than bed reflectivity. Both accumulation rate and geothermal flux anomalies can interfere with the interpretation. With the consequence, analytical radar algorithms that have been widely accepted likely yield false delineations of wet/dry beds. More careful consideration is needed when diagnosing bed conditions. Spatial patterns of shallow englacial radar reflectors can be used as a proxy for accumulation rates, which affect ice temperature and thus returned power. I argue that it is necessary to simultaneously interpret the returned power and englacial-reflector patterns to improve the bed diagnosis.
Keywords: Antarktis; geotermisk strømning; glasiologi; innlandsis; istykkelse; overflateakkumulering; polarområdene

Direct observations of nitric oxide produced by energetic electron precipitation into the Antarctic middle atmosphere - Newnham, David A; Espy, Patrick J; Clilverd, Mark A; Rodger, Craig J; Seppälä, Annika; Maxfield, David J; Hartogh, Paul; Holmén, Kim; Horne, Richard B (Geophysical Research Letters, 2011)
We report the first ground-based passive microwave observations made from Troll station, Antarctica, which show enhanced mesospheric nitric oxide (NO) volume mixing ratio reaching levels of 1.2 ppmv, or 2–3 orders of magnitude above background, at 70–80 km during small, relatively isolated geomagnetic storms in 2008. The mesospheric NO peaked 2 days after enhanced NO at higher altitudes (110–150 km) measured by the SABER satellite, and 2 days after peaks in the >30 keV and >300 keV electron flux measured by POES, although the 300 keV electron flux remained high. High time resolution data shows that mesospheric NO was enhanced at night and decayed during the day and built up to high levels over a period of 3–4 days. The altitude profile of mesospheric NO suggests direct production by ∼300 keV electron precipitation. Simulations using the Sodankylä Ion and Neutral Chemistry model show that the delay between thermospheric and mesospheric NO enhancements was primarily a result of the weaker production rate at lower altitudes by ∼300 keV electrons competing against strong day-time losses.
Keywords: Dronning Maud Land; Troll forskningsstasjon; geofysikk; geomagnetiske stormer; meteorologi; observasjoner; radiometer

Eddy overturning of the Antarctic Slope Front controls glacial melting in the Eastern Weddell Sea - Nøst, Ole Anders; Biuw, Martin; Tverberg, Vigdis; Lydersen, Christian; Hattermann, Tore; Zhou, Qianhe; Smedsrud, Lars Henrik; Kovacs, Kit M (Journal of Geophysical Research: Oceans, 2011)
Keywords: Sørishavet; Weddellhavet; isshelf; kontinentalsokkel; oseanografi

Resources for fish feed in future mariculture - Olsen, Yngvar (Aquaculture Environment Interactions, 2011)
There is a growing concern about the ability to produce enough nutritious food to feed the global human population in this century. Environmental conflicts and a limited freshwater supply constrain further developments in agriculture; global fisheries have levelled off, and aquaculture may have to play a more prominent role in supplying human food. Freshwater is important, but it is also a major challenge to cultivate the oceans in an environmentally, economically and energy-friendly way. To support this, a long-term vision must be to derive new sources of feed, primarily taken from outside the human food chain, and to move carnivore production to a lower trophic level. The main aim of this paper is to speculate on how feed supplies can be produced for an expanding aquaculture industry by and beyond 2050 and to establish a roadmap of the actions needed to achieve this. Resources from agriculture, fish meal and fish oil are the major components of pellet fish feeds. All cultured animals take advantage of a certain fraction of fish meal in the feed, and marine carnivores depend on a supply of marine lipids containing highly unsaturated fatty acids (HUFA, with ≥3 double bonds and ≥20 carbon chain length) in the feed. The availability of HUFA is likely the main constraint for developing carnivore aquaculture in the next decades. The availability of fish meal and oil will decrease, and the competition for plant products will increase. New harvested resources are herbivore zooplankton, such as Antarctic krill and red feed, and new produced resources are macroalgae, transgenic higher HUFA-producing plants and bacterial biomass. These products are to a limited extent components of the human food chain, and all these resources will help to move cultured carnivores to lower trophic levels and can thereby increase the production capacity and the sustainability of the production. Mariculture can only become as successful as agriculture in the coming century if carnivores can be produced at around Trophic Level 2, based mainly on plant resources. There is little potential for increasing the traditional fish meal food chain in aquaculture. KEYWORDS: Global aquaculture · Mariculture · Feed resources · Marine lipids · HUFA · Trophic level
Keywords: Sørishavet; alger; bakterier; biomasse; bioressurser; fiskeri; havbruksnæring; jordbruk; krill; marin biologi; marine planter; matproduksjon; oseanografi; zooplankton

Spring phytoplankton onset after the ice break-up and sea-ice signature (Adélie Land, East Antarctica) - Riaux-Gobin, Catherine; Poulin, Michel; Dieckmann, Gerhard; Labrune, Céline; Vétion, Gilles (Polar Research, 2011)
The phytoplankton onset following the spring ice break-up in Adélie Land, East Antarctica, was studied along a short transect, from 400 m off the continent to 5 km offshore, during the austral summer of 2002. Eight days after the ice break-up, some large colonial and solitary diatom cells, known to be associated with land-fast ice and present in downward fluxes, were unable to adapt in ice-free waters, while some other solitary and short-colony forming taxa (e.g., Fragilariopsis curta, F. cylindrus) did develop. Pelagic species were becoming more abundant offshore, replacing the typical sympagic (ice-associated) taxa. Archaeomonad cysts, usually associated with sea ice, were recorded in the surface waters nearshore. Rough weather restricted the data set, but we were able to confirm that some microalgae may be reliable sea-ice indicators and that seeding by sea ice only concerns a few taxa in this coastal area of East Antarctica. Keywords: Ice break-up; phytoplankton; sea-ice signature; East Antarctica
Keywords: Sørishavet; biogeokjemi; biomasse; fytoplankton; havis; oseanografi; sjøis

Hval, veid, fangst og norske kyster : linjer i norsk hvalfangsthistorie - Ringstad, Jan Erik (Norsk kulturråd, 2011)
Fram mot grunnlovsjubileet i 2014 vil det bli utarbeidet nasjonale rammefortellinger om utvalgte epoker og tema i kystens historie. Fortellingene lanseres under overskriften Fortellinger om kyst-Norge. Siden oppstarten i 2009 har det blitt produsert seks hefter. Det første heftet, Kyst- og havlandet viser bredden i norsk kysthistorie, og finnes også i engelsk utgave. Siden har heftet Riksvei nr. 1 tatt for seg maritim infrastruktur, Ressursar til låns og Den norsk arktiske torsken og verden har lagt vekt på sild og torsk sin betydning for norsk fiskeri- og kysthistorie. Videre formidler heftene Verdens Fraktemenn og Åkeren kan òg være blå sentrale sider ved norsk sjøfartshistorie og fremveksten av havbruksnæringen, to næringer som også i dag utgjør sentrale deler av det kystvendte næringslivet i Norge. Det siste heftet så langt, det syvende i rekken, handler om norsk hvalfangsthistorie, og har fått tittelen Hval, veid, fangst og norske kyster. Her blir hvalfangstens historie fulgt fra de eldste tiders fangst med enkle midler og nyttiggjørelse av strandede hvaler, til den ekspansive utviklingen av industrialisert hvalfangst både ved norskekysten og ved fjerne kyster i Sydishavet, og de konsekvenser dette fikk. Teksten er Jan Erik Ringstads verk, mens Sølvi Vik har vært billedredaktør. Museum Vest har koordinert den tekniske produksjonen og kontakten mellom forfatter og Redaksjonsrådet. Medlemmer i redaksjonsrådet har vært Pål Christensen fra Museum Nord, Jo van der Eyden fra Etatsmuseet for Kystverket, Per G. Norseng fra Norsk Maritimt Museum og Bjørg Christophersen, Anders Haaland og Årstein Svihus fra Museum Vest. Direktoratene og nettverksmuseene håper at de nasjonale rammefortellingene vil være til glede, ettertanke og nytte for alle kystkulturinteresserte, og at de kan bidra til et historisk perspektiv på nåtidens og framtidens utfordringer. Direktoratene og museene tar gjerne imot spørsmål eller synspunkter på prosjektet. Les mer om Fortellinger om kyst-Norge på www.kyst-norge.no. 10. oktober 2011 På østsiden av Larviksfjorden skjærer den lille bukta Rekkevik inn i det kuperte landskapet. På sletta innerst i bukta lå Colin Archers båtbyggeri hvor polarskipet Fram ble bygget. Like bak båtbyggeriet åpner det seg en åtte meter bred kløft som smalner av innover. Da man i 1914 skulle grave en brønn ytterst i denne kløfta, støtte man på noen meget store knokler som man hogg seg gjennom for å få brønnen tilstrekkelig dyp. De avhogde fragmentene ble innsendt til universitetet, hvor man fastslo at det var knokler av grønlandshval. Grønlandshvalen er en av tre hvalarter som lever hele sitt liv i Arktis – de andre to er hvithvalen og narhvalen. Funnstedet lå noe over 40 meter fra strandlinjen, fire, fem kilometer utenfor raet. En analyse av funnet indikerer at hvalen kan ha kjørt seg fast i kløfta da denne lå på ca. 30 meters dyp, og druknet. Klimaet må da ha vært høyarktisk, og dateringen ble satt til ca. 10 000 f. Kr. Hvalen følger mennesket i tid og rom. Det finnes knapt en kyst der mennesker har bodd uten at hval og andre sjøpattedyr har vært del av deres ressursgrunnlag. Fra kysten har man sett hvalens mektige ”blåst” og kraftige bevegelser. Iblant strandet store eksemplarer og ga opphav til mytiske forestillinger og inspirasjon til avbildninger. Hvalen kan altså følges 10-12 000 år tilbake langs våre kyster. Vi skal møte den i noen tekster fra norrøn tid av, diskutere ulike fangstprinsipper og omtale Svend Foyns granatharpun. Fra vår egen kyst skal vi følge fangsten til en rekke felt kloden rundt, især til Antarktis med annekteringer av store landområder i hvalfangstens kjølvann. En rekke aktører fortjener omtale, både investorer, arbeidere, motstandere, forskere, politikere og de som ble igjen hjemme da flåten dro av sted. Målet er at heftet skal bidra til kunnskap om viktige linjer i norsk hvalfangsthistorie.
Publication Title: Fortellinger om kyst-Norge
Keywords: Antarktis; Sørishavet; historie; hvalfangst; pelagisk hvalfangst

Hva er en helt? Kjønn i antarktislitteraturen - Ryall, Anka (Fortid : historiestudentenes tidsskrift, UiO, 2011)
Menneskenes historie i Antarktis er ikke mer enn noen hundre år gammel. De viktigste kildene til denne historien er ekspedisjonsberetningene – en omfangsrik litteratur som kan leses på mange måter, også fra et kjønnsperspektiv.
Keywords: Antarktis; ekspedisjoner; litteratur; polarhistorie

Deglacial history of the West Antarctic Ice Sheet in the western Amundsen Sea Embayment - Smith, James A.; Hillenbrand, Claus-Dieter; Kuhn, Gerhard; Larter, Robert D.; Graham, Alastair G.C.; Ehrmann, Werner; Moreton, Steven G.; Forwick, Matthias (Quaternary Science Reviews, 2011)
The Amundsen Sea Embayment (ASE) drains approximately 35% of the West Antarctic Ice Sheet (WAIS) and is one of the most rapidly changing parts of the cryosphere. In order to predict future ice sheet behaviour, modellers require long-term records of ice-sheet melting to constrain and build confidence in their simulations. Here, we present detailed marine geological and radiocarbon data along three palaeo-ice stream tributary troughs in the western ASE to establish vital information on the timing of deglaciation of the WAIS since the Last Glacial Maximum (LGM). We have undertaken multi-proxy analyses of the cores (core description, shear strength, x-radiographs, magnetic susceptibility, wet bulk density, total organic carbon/nitrogen, carbonate content and clay mineral analyses) in order to: (1) characterise the sedimentological facies and depositional environments; and (2) identify the horizon(s) in each core that would yield the most reliable age for deglaciation. In accordance with previous studies we identify three key facies, which offer the most reliable stratigraphies for dating deglaciation by recording the transition from a grounded ice sheet to open marine environments. These facies are: i) subglacial, ii) proximal grounding line, and iii) seasonal open marine. In addition, we incorporate ages from other facies (e.g., glaciomarine diamictons deposited at some distance from the grounding line, such as glaciogenic debris flows and iceberg-rafted diamictons and turbates) into our deglacial model. In total, we have dated 78 samples (mainly the acid insoluble organic (AIO) fraction, but also calcareous foraminifers), which include 63 downcore and 15 surface samples. Through careful sample selection prior to dating, we have established a robust deglacial chronology for this sector of the WAIS. Our data show that deglaciation of the western ASE was probably underway as early as 22,351 calibrated years before present (cal yr BP), reaching the mid-shelf by 13,837 cal yr BP and the inner shelf to within c.10–12 km of the present ice shelf front between 12,618 and 10,072 cal yr BP. The deglacial steps in the western ASE broadly coincide with the rapid rises in sea-level associated with global meltwater pulses 1a and 1b, although given the potential dating uncertainty, additional, more precise ages are required before these findings can be fully substantiated. Finally, we show that the rate of ice-sheet retreat increased across the deep (up to1600 m) basins of the inner shelf, highlighting the importance of reverse slope and pinning points in accelerated phases of deglaciation.
Keywords: Amundsenhavet; Sørishavet; deglasiasjon; glasiologi; innlandsis; isshelf; marin geologi

Using fluorescence to characterize dissolved organic matter in Antarctic sea ice brines - Stedmon, Colin A; Thomas, David N; Papadimitriou, Stathys; Granskog, Mats A; Dieckmann, Gerhard S (Journal of Geophysical Research: Biogeosciences, 2011)
Sea ice plays a dynamic role in the air-sea exchange of CO2. In addition to abiotic inorganic carbon fluxes, an active microbial community produces and remineralizes organic carbon, which can accumulate in sea ice brines as dissolved organic matter (DOM). In this study, the characteristics of DOM fluorescence in Antarctic sea ice brines from the western Weddell Sea were investigated. Two humic-like components were identified, which were identical to those previously found to accumulate in the deep ocean and represent refractory material. Three amino-acid-like signals were found, one of which was unique to the brines and another that was spectrally very similar to tryptophan and found both in seawater and in brine samples. The tryptophan-like fluorescence in the brines exhibited intensities higher than could be explained by conservative behavior during the freezing of seawater. Its fluorescence was correlated with the accumulation of nitrogen-rich DOM to concentrations up to 900 μmol L−1 as dissolved organic carbon (DOC) and, thus, potentially represented proteins released by ice organisms. A second, nitrogen-poor DOM fraction also accumulated in the brines to concentrations up to 200 μmol L−1 but was not correlated with any of the fluorescence signals identified. Because of the high C:N ratio and lack of fluorescence, this material is thought to represent extracellular polymeric substances, which consist primarily of polysaccharides. The clear grouping of the DOM pool into either proteinaceous or carbohydrate-dominated material indicates that the production and accumulation of these two subpools of DOM in sea ice brines is, to some extent, decoupled.
Keywords: Sørishavet; Weddellhavet; fluorescens; gassutveksling; havis; karbondioksid; marin økologi; mikrobielle organismer; mikrobiologi; sjøis

Spatial modelling of wetness for the Antarctic Dry Valleys - Stichbury, Glen; Brabyn, Lars; Green, T G Allan; Cary, Craig (Polar Research, 2011)
This paper describes a method used to model relative wetness for part of the Antarctic Dry Valleys using Geographic Information Systems (GIS) and remote sensing. The model produces a relative index of liquid water availability using variables that influence the volume and distribution of water. Remote sensing using Moderate Resolution Imaging Spectroradiometer (MODIS) images collected over four years is used to calculate an average index of snow cover and this is combined with other water sources such as glaciers and lakes. This water source model is then used to weight a hydrological flow accumulation model that uses slope derived from Light Detection and Ranging (LIDAR) elevation data. The resulting wetness index is validated using three-dimensional visualization and a comparison with a high-resolution Advanced Land Observing Satellite image that shows drainage channels. This research demonstrates that it is possible to produce a wetness model of Antarctica using data that are becoming widely available. Keywords: GIS; water; Antarctica; remote sensing.
Keywords: Antarktis; geografi; hydrologi; innsjø; isbreer; satellitt bilder; snø; vann; økosystemer

Using transport diagnostics to understand chemistry climate model ozone simulations - Strahan, Susan; Douglass, A R; Stolarski, R S; Akiyoshi, Hideharu; Bekki, Slimane; Braesicke, P; Butchart, N; Chipperfield, Martyn; Cugnet, David; Dhomse, Sandip; Frith, Stacey; Gettelman, Andrew; et al. (Journal of Geophysical Research: Atmospheres, 2011)
We use observations of N2O and mean age to identify realistic transport in models in order to explain their ozone predictions. The results are applied to 15 chemistry climate models (CCMs) participating in the 2010 World Meteorological Organization ozone assessment. Comparison of the observed and simulated N2O, mean age and their compact correlation identifies models with fast or slow circulations and reveals details of model ascent and tropical isolation. This process-oriented diagnostic is more useful than mean age alone because it identifies models with compensating transport deficiencies that produce fortuitous agreement with mean age. The diagnosed model transport behavior is related to a model's ability to produce realistic lower stratosphere (LS) O3 profiles. Models with the greatest tropical transport problems compare poorly with O3 observations. Models with the most realistic LS transport agree more closely with LS observations and each other. We incorporate the results of the chemistry evaluations in the Stratospheric Processes and their Role in Climate (SPARC) CCMVal Report to explain the range of CCM predictions for the return-to-1980 dates for global (60°S–60°N) and Antarctic column ozone. Antarctic O3 return dates are generally correlated with vortex Cly levels, and vortex Cly is generally correlated with the model's circulation, although model Cl chemistry and conservation problems also have a significant effect on return date. In both regions, models with good LS transport and chemistry produce a smaller range of predictions for the return-to-1980 ozone values. This study suggests that the current range of predicted return dates is unnecessarily broad due to identifiable model deficiencies.
Keywords: Antarktis; drivhusgasser; fysikk; geovitenskap; klimamodeller; meteorologi; ozonlaget; stratosfæren

Near-surface eddy dynamics in the Southern Ocean - Trani, Marilisa; Falco, Pierpaolo; Zambianchi, Enrico (Polar Research, 2011)
The Antarctic Circumpolar Current (ACC) is a crucial component of the global ocean conveyor belt, acting as a zonal link among the major ocean basins but, to some extent, limiting meridional exchange and tending to isolate the ocean south of it from momentum and heat income. In this work we investigate one of the most important mechanisms contributing to the poleward transfer of properties in the Southern Ocean, that is the eddy component of the dynamics. For this particular purpose, observations obtained from near-surface drifters have been used: they represent a very useful data set to analyse the eddy field because of their ability to catch a large number of scales of motion while providing a quasi-synoptic coverage of the investigated area. Estimates of the eddy heat and momentum fluxes are carried out using data taken from the Global Drifter Program databank; they refer to Surface Velocity Program drifter trajectories collected in the area south of 358S between 1995 and 2006. Eddy kinetic energies, variance ellipses, momentum and heat fluxes have been calculated using the pseudo-Eulerian method, showing patterns in good agreement with those present in the literature based on observational and model data, although there are some quantitative differences. The eddy fluxes have been separated into their rotational and divergent portions, the latter being responsible for the meridional transports. The associated zonal and depth-exponentially integrated meridional heat transport exhibits values spanning over a range between -0.4 PW and -1.1 PW in the ACC region, consistent with previous estimates. Keywords: Antarctic Circumpolar Current; eddy fluxes; Global Drifter Program data; Lagrangian oceanography; Helmholtz decomposition.
Keywords: Sørishavet; havstrømmer; hydrografi; oseanografi; virvelstrømmer

ICE Fimbulisen - top to bottom: season 2 expedition field report - Tronstad ed., Stein; Polarinstitutt, Norsk (Norsk Polarinstitutt, 2011)
Keywords: Dronning Maud Land; Sørishavet; glasiologi; isshelf; logistikk; oseanografi

Colonization and demographic structure of Deschampsia antarctica and Colobanthus quitensis along an altitudinal gradient on Livingston Island, South Shetland Islands, Antarctica - Vera, María Luisa (Polar Research, 2011)
The colonization capacity and demographic structure of populations of Deschampsia antarctica and Colobanthus quitensis were studied in different microhabitats between 10 and 147 m a.s.l. on Livingston Island, South Shetland Islands, near the Spanish Antarctic base Juan Carlos I, in February 2002. At the highest site (147 m a.s.l.), mean temperatures were about 1 ºC lower than at sea level. Both species are less common in inland areas and at the highest altitudes only occur at restricted sites that are frequently snow-free in the early austral summer. The diameters of the largest plants (C. quitensis cushions 7-8 cm ; D. antarctica tufts 10-11 cm) in the populations growing at the highest altitudes (110 and 147 m a.s.l.) suggest that these populations were established about 24-28 years ago. The largest diameter plants (Deschampsia 20 cm; Colobanthus 18 cm) were found at the lowest altitudes on deep soil. The presence of numerous seedlings and young individuals on the periphery of populations established several years ago or at recently colonized sites suggests an active process of expansion. There were more emerged seedlings of C. quitensis than of D. antarctica, but the density of established individuals was higher for D. antarctica, suggesting these species have different demographic strategies. Keywords: Antarctic vascular plants; altitude and habitat effect; colonization; population structure.
Keywords: Antarktis; biologi; flora; planter

Atmospheric histories and global emissions of the anthropogenic hydrofluorocarbons HFC-365mfc, HFC-245fa, HFC-227ea, and HFC-236fa - Vollmer, Martin K; Miller, Benjamin R; Rigby, Matthew; Reimann, Stefan; Mühle, Jens; Krummel, Paul B; O'Doherty, Simon; Kim, Jooil; Rhee, Tae Siek; Weiss, Ray F; Fraser, Paul J; Simmonds, Peter G; et al. (Journal of Geophysical Research: Atmospheres, 2011)
We report on ground-based atmospheric measurements and emission estimates of the four anthropogenic hydrofluorocarbons (HFCs) HFC-365mfc (CH3CF2CH2CF3, 1,1,1,3,3-pentafluorobutane), HFC-245fa (CHF2CH2CF3, 1,1,1,3,3-pentafluoropropane), HFC-227ea (CF3CHFCF3, 1,1,1,2,3,3,3-heptafluoropropane), and HFC-236fa (CF3CH2CF3, 1,1,1,3,3,3-hexafluoropropane). In situ measurements are from the global monitoring sites of the Advanced Global Atmospheric Gases Experiment (AGAGE), the System for Observations of Halogenated Greenhouse Gases in Europe (SOGE), and Gosan (South Korea). We include the first halocarbon flask sample measurements from the Antarctic research stations King Sejong and Troll. We also present measurements of archived air samples from both hemispheres back to the 1970s. We use a two-dimensional atmospheric transport model to simulate global atmospheric abundances and to estimate global emissions. HFC-365mfc and HFC-245fa first appeared in the atmosphere only ∼1 decade ago; they have grown rapidly to globally averaged dry air mole fractions of 0.53 ppt (in parts per trillion, 10−12) and 1.1 ppt, respectively, by the end of 2010. In contrast, HFC-227ea first appeared in the global atmosphere in the 1980s and has since grown to ∼0.58 ppt. We report the first measurements of HFC-236fa in the atmosphere. This long-lived compound was present in the atmosphere at only 0.074 ppt in 2010. All four substances exhibit yearly growth rates of >8% yr−1 at the end of 2010. We find rapidly increasing emissions for the foam-blowing compounds HFC-365mfc and HFC-245fa starting in ∼2002. After peaking in 2006 (HFC-365mfc: 3.2 kt yr−1, HFC-245fa: 6.5 kt yr−1), emissions began to decline. Our results for these two compounds suggest that recent estimates from long-term projections (to the late 21st century) have strongly overestimated emissions for the early years of the projections (∼2005–2010). Global HFC-227ea and HFC-236fa emissions have grown to average values of 2.4 kt yr−1 and 0.18 kt yr−1 over the 2008–2010 period, respectively.
Keywords: Dronning Maud Land; atmosfæren; drivhusgasser; global oppvarming; klimaendringer; klimatologi; målinger

Svarene på fortidens klimavariasjoner og framtidens havnivå ligger begravd i isen i Antarktis - Winther, Jan-Gunnar; Isaksson, Elisabeth (Polaråret 2007-2008 : det norske bidraget, 2011)
Keywords: Det Internasjonale polaråret 2007; Dronning Maud Land; glasiologi; havnivåstigning; klimaendringer; polarforskning

Mesospheric wind semidiurnal tides within the Canadian Middle Atmosphere Model Data Assimilation System - Xu, Xiaoyong; Manson, Alan H; Meek, Christopher; Jacobi, Christoph; Hall, Chris; Drummond, James (Journal of Geophysical Research: Atmospheres, 2011)
The horizontal wind data from the standard version of Canadian Middle Atmosphere Model Data Assimilation System (CMAM-DAS) for the years 2006–2008 are analyzed to obtain the global structure and seasonal variability of the semidiurnal tide (SDT) in the mesosphere. The modeled amplitudes and phases of the SDTs at single stations from middle/high northern latitudes are quite similar to those observed by radars. The primary nonmigrating tides identified in both the meridional wind and zonal wind semidiurnal spectra at 88 km include the westward propagating wave numbers s = 1 (SW1), 3 (SW3), 4 (SW4), 6 (SW6), the standing s = 0 (S0), and the eastward propagating s = 2 (SE2). The migrating SDT (SW2) amplitude maxima usually occur at 40°N–60°N during December–February and August–September, and also at 40°S–60°S in April–May, with the dominance of (2, 4) during October–April and (2, 3) and (2, 5) dominance for other months. The CMAM-DAS is quite successful in reproducing the dominance of SW1 in the Antarctic summer mesosphere. The modeled SW1 shows very good overall agreement in both amplitude and phase with wind measurements from UARS High Resolution Doppler Imager and Wind Imaging Interferometer (UARS-HRDI/WINDII) and from TIMED Doppler Interferometer (TIDI). The CMAM-DAS analyses for SW3, SW4, SW6, and S0 are also in reasonable agreement with those determined from the HRDI/WINDII or TIDI wind measurements. This work provides further evidence for the tidal forcing from below.
Keywords: Antarktis; atmosfæren; atmosfærisk tidevann; geofysikk; meteorologi

An inter-comparison of six latent and sensible heat flux products over the Southern Ocean - Yu, Lejiang; Zhang, Zhanhai; Zhong, Shiyuan; Zhou, Mingyu; Gao, Zhiqiu; Wu, Huiding; Sun, Bo (Polar Research, 2011)
The latent heat fluxes (LHF) and sensible heat fluxes (SHF) over the Southern Ocean from six different data sets are inter-compared for the period 1988- 2000. The six data sets include three satellite-based products, namely, the second version of the Goddard Satellite-Based Surface Turbulent Fluxes data set (GSSTF-2), the third version of the Hamburg Ocean Atmosphere Parameters and Fluxes from Satellite Data (HOAPS-3) and the Japanese Ocean Fluxes Data Sets with Use of Remote Sensing Observations (J-OFURO); two global reanalysis products, namely, the National Centers for Environmental Prediction-Department of Energy Reanalysis 2 data set (NCEP-2) and the European Centre for Medium-Range Weather Forecasts 40 Year Re-analysis data set (ERA-40); and the Objectively Analyzed Air-Sea Fluxes for the Global Oceans data set (OAFlux). All these products reveal a similar pattern in the averaged flux fields. The zonal mean LHF fields all exhibit a continuous increase equatorward. With an exception of HOAPS-3, the zonal mean SHF fields display a minimum value near 50°S, increasing both pole- and equatorward. The differences in the standard deviation for LHF are larger among the six data products than the differences for SHF. Over the regions where the surface fluxes are significantly influenced by the Antarctic Oscillation and the Pacific-South American teleconnection, the values and distributions of both LHF and SHF are consistent among the six products. It was found that the spatial patterns of the standard deviations and trends of LHF and SHF can be explained primarily by sea-air specific humidity and temperature differences; wind speed plays a minor role. Keywords: Latent heat flux; sensible heat flux; Southern Ocean.
Keywords: Sørishavet; klimatologi; meteorologi; observasjoner

The intraseasonal variability of winter semester surface air temperature in Antarctica - Yu, Lejiang; Zhang, Zhanhai; Zhou, Mingyu; Zhong, Shiyuan; Sun, Bo; Hsu, Hsiaoming; Gao, Zhiqiu; Wu, Huiding; Ban, Junmei (Polar Research, 2011)
This study investigates systematically the intraseasonal variability of surface air temperature over Antarctica by applying empirical orthogonal function (EOF) analysis to the National Centers for Environmental Prediction, US Department of Energy, Reanalysis 2 data set for the period of 1979 through 2007. The results reveal the existence of two major intraseasonal oscillations of surface temperature with periods of 26 - 30 days and 14 days during the Antarctic winter season in the region south of 60°S. The first EOF mode shows a nearly uniform spatial pattern in Antarctica and the Southern Ocean associated with the Antarctic Oscillation. The mode-1 intraseasonal variability of the surface temperature leads that of upper atmosphere by one day with the largest correlation at 300-hPa level geopotential heights. The intraseasonal variability of the mode-1 EOF is closely related to the variations of surface net longwave radiation the total cloud cover over Antarctica. The other major EOF modes reveal the existence of eastward propagating phases over the Southern Ocean and marginal region in Antarctica. The leading two propagating modes respond to Pacific-South American modes. Meridional winds induced by the wave train from the tropics have a direct influence on the surface air temperature over the Southern Ocean and the marginal region of the Antarctic continent. Keywords: Antarctic climate, surface air temperature, intraseasonal variability, Antarctic Oscillation.
Keywords: Antarktis; forskning; klima; lufttemperatur

Natural iron enrichment around the Antarctic Peninsula in the Southern Ocean - Ardelan, M. V.; Holm-Hansen, O.; Hewes, C. D.; Reiss, C. S.; Silva, N. S.; Dulaiova, H.; Steinnes, E.; Sakshaug, E. (Biogeosciences, 2010)
As part of the US-AMLR program in January-February of 2006, 99 stations in the South Shetland Islands-Antarctic Peninsula region were sampled to understand the variability in hydrographic and biological properties related to the abundance and distribution of krill in this area. Concentrations of dissolved iron (DFe) and total acid-leachable iron (TaLFe) were measured in the upper 150 m at 16 of these stations (both coastal and pelagic waters) to better resolve the factors limiting primary production in this area and in downstream waters of the Scotia Sea. The concentrations of DFe and TaLFe in the upper mixed layer (UML) were relatively high in Weddell Sea Shelf Waters (~0.6 nM and 15 nM, respectively) and low in Drake Passage waters (~0.2 nM and 0.9 nM, respectively). In the Bransfield Strait, representing a mixture of waters from the Weddell Sea and the Antarctic Circumpolar Current (ACC), concentrations of DFe were ~0.4 nM and of TaLFe ~1.7 nM. The highest concentrations of DFe and TaLFe in the UML were found at shallow coastal stations close to Livingston Island (~1.6 nM and 100 nM, respectively). The ratio of TaLFe:DFe varied with the distance to land: ~45 at the shallow coastal stations, ~15 in the high-salinity waters of Bransfield Strait, and ~4 in ACC waters. Concentrations of DFe increased slightly with depth in the water column, while that of TaLFe did not show any consistent trend with depth. Our Fe data are discussed in regard to the hydrography and water circulation patterns in the study area, and with the hypothesis that the relatively high rates of primary production in the central regions of the Scotia Sea are partially sustained by natural iron enrichment resulting from a northeasterly flow of iron-rich coastal waters originating in the South Shetland Islands-Antarctic Peninsula region.
Keywords: Sør-Shetlandsøyene; Sørishavet; biogeokjemi; fytoplankton; hydrografi; marin biologi; marin kjemi; oseanografi

An isopycnic ocean carbon cycle model - Assmann, K. M.; Bentsen, M.; Segschneider, J.; Heinze, C. (Geoscientific Model Development, 2010)
The carbon cycle is a major forcing component in the global climate system. Modelling studies, aiming to explain recent and past climatic changes and to project future ones, increasingly include the interaction between the physical and biogeochemical systems. Their ocean components are generally z-coordinate models that are conceptually easy to use but that employ a vertical coordinate that is alien to the real ocean structure. Here, we present first results from a newly-developed isopycnic carbon cycle model and demonstrate the viability of using an isopycnic physical component for this purpose. As expected, the model represents well the interior ocean transport of biogeochemical tracers and produces realistic tracer distributions. Difficulties in employing a purely isopycnic coordinate lie mainly in the treatment of the surface boundary layer which is often represented by a bulk mixed layer. The most significant adjustments of the ocean biogeochemistry model HAMOCC, for use with an isopycnic coordinate, were in the representation of upper ocean biological production. We present a series of sensitivity studies exploring the effect of changes in biogeochemical and physical processes on export production and nutrient distribution. Apart from giving us pointers for further model development, they highlight the importance of preformed nutrient distributions in the Southern Ocean for global nutrient distributions. The sensitivity studies show that iron limitation for biological particle production, the treatment of light penetration for biological production, and the role of diapycnal mixing result in significant changes of nutrient distributions and liniting factors of biological production.
Keywords: Sørishavet; biogeokjemi; karbon syklus; klimamodeller

Millennial scale evolution of the Southern Ocean chemical divide - Charles, Christopher D.; Pahnke, Katharina; Zahn, Rainer; Mortyn, P.G.; Ninnemann, Ulysses; Hodell, D.A. (Quaternary Science Reviews, 2010)
The chemical properties of the mid-depth and deep Southern Ocean are diagnostic of the mechanisms of abrupt changes in the global ocean throughout the late Pleistocene, because the regional water mass conversion and mixing help determine global ocean gradients. Here we define continuous time series of Southern Ocean vertical gradients by differencing the records from two high deposition rate deep sea sedimentary sequences that span the last several ice age cycles. The inferred changes in vertical carbon and oxygen isotopic gradients were dominated by variability on the millennial scale, and they followed closely the abrupt climate events of the high latitude Northern Hemisphere. In particular, the stadial events of at least the last 200kyr were characterized by enhanced mid-deep gradients in both δ13C (dissolved inorganic carbon) and δ18O (temperature). Interstadial events, conversely, featured reduced vertical gradients in both properties. The glacial terminations represented exceptions to this pattern of variability, as the vertical carbon isotopic gradient flattened dramatically at times of peak warmth in the Southern Ocean surface waters and with little or no corresponding change δ18O gradient. The available evidence suggests that properties of the upper layer of the Southern Ocean (Antarctic Intermediate Water) were influenced by an atmospherically mediated teleconnection to high latitude Northern Hemisphere.
Keywords: Sørishavet; geologi; oseanografi; paleoklimatologi

Observations of the Antarctic Slope Undercurrent in the southeastern Weddell Sea - Chavanne, Cédric P; Heywood, Karen J; Nicholls, Keith W; Fer, Ilker (Geophysical Research Letters, 2010)
The Antarctic Slope Front presents a dynamical barrier between the cold Antarctic shelf waters in contact with ice shelves and the warmer subsurface waters offshore. Two hydrographic sections with full-depth current measurements were undertaken in January and February 2009 across the slope and shelf in the southeastern Weddell Sea. Southwestward surface-intensified currents of ∼30 cm s−1, and northeastward undercurrents of 6–9 cm s−1, were in thermal-wind balance with the sloping isopycnals across the front, which migrated offshore by 30 km in the time interval between the two sections. A mid-depth undercurrent on February 23 was associated with a 130-m uplift of the main pycnocline, bringing Warm Deep Water closer to the shelf break. This vertical displacement, comparable to that caused by seasonal variations in wind speed, implies that undercurrents may affect the exchanges between coastal and deep waters near the Antarctic continental margins.
Keywords: Sørishavet; Weddellhavet; hydrografi; isbrem; isshelf; kontinentalmargin; kontinentalsokkel; oseanografi; understrømmer

Patterns of variation of serum oxidative stress markers in two seabird species - Costantini, David; Bonadonna, Francesco (Polar Research, 2010)
Variation in oxidative stress markers in natural populations may provide a useful background for understanding variation in life history strategies. In this study, we seek to evaluate patterns of variation in levels of reactive oxygen metabolites (markers of oxidative damage), serum antioxidant capacity, and serum concentration of thiols (antioxidants endogenously synthesized) in nestling and breeding blue petrels (Halobaena caerulea) and in breeding Antarctic prions (Pachyptila desolata). Male and female prions and nestling petrels did not differ in any of the oxidative stress markers. The serum antioxidant capacity positively correlated with the sample time in nestling blue petrels. Breeding petrels with higher body condition index had higher serum antioxidant capacity and circulating thiols. Finally, both seabird species showed lower levels of reactive oxygen metabolites and higher levels of serum antioxidant capacity than previously studied bird species.
Keywords: Antarktis; marin biologi; ornitologi; petreller; reproduksjon; sjøfugler; zoologi; økologi

Guest editorial—the 1959 Antarctic Treaty: reflecting on the 50th anniversary of a landmark agreement - Dodds, Klaus (Polar Research, 2010)
Commemorating a particular anniversary is always an arbitrary affair, an act of whimsy. After all, why acknowledge the 50th anniversary of someone or some event as opposed to the 48th? In terms of birthdays, we tend to celebrate each year as another rite of human passage. However, when it comes to events such as wars and diplomatic encounters, the media and political commentators like more substantial blocks of time: 10th, 25th, 50th, 75th and 100th anniversaries are particularly noteworthy. The year 2009 has proven no different in terms of representing a temporal marker for the 50th anniversary of the signing of the 1959 Antarctic Treaty. In December 2009 a so-called Antarctic Treaty Summit was held in Washington, D.C. to take advantage of not only such a milestone, but also “to highlight lessons learned about international governance ‘with the interests of science and the progress of all mankind’ ” (Antarctic Treaty Summit 2009, emphasis added).
Keywords: Antarktis; Antarktistraktaten; historie; internasjonal samarbeid; politikk

Review of Legacies and change in polar sciences: historical, legal and political reflections on the International Polar Year, edited by JM Shadian & M Tennberg - Dodds, Klaus (Polar Research, 2010)
The International Polar Year (IPY) of 2007–09 was an international scientific enterprise that encompassed all polar regions, and built on the legacies bequeathed by earlier endeavours stretching back to the late 19th century. The first such venture was initiated in 1882–83, the second was in 1932–33 and the last, the International Geophysical Year (IGY), occurred in 1957–58, and involved thousands of scientists working inter alia in the polar continent. Activity in the Arctic, for geopolitical reasons, was rather more limited, and was certainly not epitomized by free and unfettered scientific investigation. Sponsored by the International Council for Science, the most recent IPY was noteworthy for its explicit bi-polar focus, and its integration of the humanities and social sciences with the physical and environmental sciences. The role of indigenous communities was also notable in Arctic-based projects, a development that would have been inconceivable during the IGY. As with the IGY, however, a spectacular event in one of the theatres of scientific interest grabbed world headlines: in 1957 it was Sputnik orbiting the Earth, and in 2007 it was a Russian submersible planting a flag on the bottom of the central Arctic Ocean basin.
Keywords: Antarktis; Det internasjonale geofysiske år (IGY); bokanmeldelser; forskning; geopolitikk; internasjonal; polarområdene; samarbeid; vitenskap

Glaciomarine sediments and suspended particulate matter, Weddell Sea Shelf, Antarctica - Elverhøi, Anders; Roaldset, Elen (Polar Research, 2010)
Keywords: NARE 1978/79; Sørishavet; Weddellhavet; ekspedisjoner; forskning; geologi; sedimentologi; stratigrafi

Nature environment map: H.U. Sverdrupfjella, Dronning Maud Land, East Antarctica - Elvevold ed., Synnøve; Ohta ed., Yoshihide; Polarinstitutt, Norsk (Norwegian Polar Institute, 2010)
Publication Title: Temakart ISBN: 28
Keywords: Dronning Maud Land; geologi; glasiologi; kartlegging

Neogene biochronology of Antarctic diatoms: A comparison between two quantitative approaches, CONOP and UAgraph - Galster, Federico; Guex, Jean; Hammer, Oyvind (Palaeogeography, Palaeoclimatology, Palaeoecology, 2010)
A quantitative biochronological study by Cody et al. (2008) integrates comprehensive diatom biostratigraphy, magnetostratigraphy, and tephrostratigraphy from 32 Neogene sections around the Southern Ocean and Antarctic continental margin. A recent method, known as Constrained Optimization (CONOP), which can be viewed as a multidimensional version of graphic correlation, is applied to that very interesting database. The goal of the present paper is to discuss some theoretical aspects of quantitative biochronology and to compare the constrained optimization with the deterministic method called Unitary Associations (UAM), a graph theoretical model. We illustrate the fact that the UAM is an extremely powerful and unique theory allowing an in-depth analysis of the internal conflicting inter-taxon stratigraphic relationships, inherent to any complex biostratigraphical database.
Keywords: Antarktis; Sørishavet; biokronologi; diatomeer; paleogeografi; paleoklimatologi; paleontologi; paleoøkologi

"Det må gå!" : en kulturhistorisk studie av hvalfangerhustruer i Vestfold 1930-1968 - Garmel, Hanne; Gustavsson, Anders (Universitetet i Oslo, 2010)
I denne masteroppgaven har jeg med utgangspunkt i kvinner bosatt i og rundt Sandefjord kommune i Vestfold, sett nærmere på kvinnenes side av hvalfangsthistorien, og undersøkt hvordan hvalfangernes hustruer opplevde hverdagen med og uten ektemennene ved sin side under den pelagiske hvalfangsten i tidsrommet 1930-1968. Oppgavens hovedproblemstilling, ”hvalfangerhustruer, en gruppe sterke kvinner?” er inspirert av moderne kjønnsteori og kjønnsforskning, og stiller spørsmålstegn ved flere sentrale påstander i den eneste andre boken om hvalfangerhustruene i Vestfold, nemlig høyskolelæreren og forfatteren Jorunn Vesterlids bok Hvalfangerkoner og barn forteller fra 1992. Oppgaven er videre en kvalitativ studie, og bygger i hovedsak på muntlige kilder. Hovedkildene er egne intervjuer med tidligere hvalfangerhustruer og en hvalfanger, i tillegg til minnematerialet etter Jorunn Vesterlid, som også består av intervjuer med forhenværende hvalfangerhustruer. I tillegg består oppgavens kildegrunnlag av et supplerende kildemateriale som blant annet består av en privat brevsamling, foto og avisutklipp. Oppgaven består av totalt fire analysekapitler, som på ulike måter belyser og besvarer problemstillingen. I det første kapittelet ser jeg nærmere på hvalfangerhustruenes arbeid, og studerer både arbeidet til hvalfangerhustruene som bodde på gård, og arbeidet til hvalfangerhustruer som bodde i byen eller tettbygde strøk. Sentrale spørsmål er hvorvidt hvalfangerhustruenes arbeid skilte seg fra øvrige, samtidige kvinners arbeid, samt om mennenes fravær førte til at kvinnene fikk større ansvar. Denne diskusjonen fortsettes i kapittel tre, hvor jeg diskuterer kvinnenes arbeid og hverdagsliv under andre verdenskrig. I kapittel fire tar jeg for meg hvalfangerhustruenes fritid, og undersøker om de tilbrakte mye tid sammen under mennenes fravær, en diskusjon som igjen belyser hvorvidt kvinnene opplevde at de var del av en spesiell gruppe, eller et kollektiv som hvalfangerhustruer. Det siste analysekapittelet omhandler kvinnenes følelser, og jeg spør hvordan det var å leve med en ektemann som var fraværende store deler av året, og som i tillegg hadde et tidvis farlig yrke. På bakgrunn av analysen har jeg kommet frem til en hovedkonklusjon, hvor jeg hevder at hvalfangerhustruene nødvendigvis ikke var sterkere enn andre kvinner, men at de som følge av mennenes fravær likevel måtte takle så vel et utvidet ansvar som ekstra utfordringer. Jeg finner heller ikke at det medfører riktighet å omtale hvalfangerhustruene som en egen gruppe kvinner til enhver tid, til tross for at det forekom anledninger hvor kvinnene opplevde så vel liknende erfaringer som samhold.
Publication Title: Institutt for kulturstudier og orientalske språk Volume: M.Sc.
Keywords: Antarktis; Vestfold; hvalfangst; kulturhistorie; kvinner

Regime Management at the Bottom of the Food Web - Gjelsvik Tiller, Rachel (The Journal of Environment & Development, 2010)
Fishing down the food chain is a controversial issue that demands further exploration. Redfeed is a marine species located on the second to last level on the food web. It is also one of the potential saviors of the aquaculture industry. The role of effective management of this species is of utmost importance to avoid the potential catastrophe associated with its overharvesting. Using a calculation of behavioral effectiveness, a blueprint redfeed regime is compared with the Convention for the Conservation of the Antarctic Marine Living Resources (CCAMLR), an ecosystem-based management regime with the now famous krill as its key species. Though the regimes are similar in nature, their geopolitical differences suggest that a future redfeed regime will be effective even though CCAMLR has not been. Ensuring that the redfeed is not merely incorporated into existing regimes, but is treated separately in an ecosystem-based regime, will alleviate the interplay this future redfeed regime otherwise would encounter.
Publisher: SAGE Publications Inc
Keywords: Antarktistraktaten; Sørishavet; fiskerier; internasjonal rett; krill; marin økologi; marine økosystemer; plankton; polarområdene

Isopycnal diffusivities in the Antarctic Circumpolar Current inferred from Lagrangian floats in an eddying model - Griesel, Alexa; Gille, Sarah T; Sprintall, Janet; McClean, Julie L; Lacasce, Joseph H; Maltrud, Mathew E (Journal of Geophysical Research: Oceans, 2010)
Lagrangian subsurface isopycnal eddy diffusivities are calculated from numerical floats released in several regions of the Antarctic Circumpolar Current (ACC) of the 0.1° Parallel Ocean Program. Lagrangian diffusivities are horizontally highly variable with no consistent latitudinal dependence. Elevated values are found in some areas in the core of the ACC, near topographic features, and close to the Brazil-Malvinas Confluence Zone and Agulhas Retroflection. Cross-stream eddy diffusivities are depth invariant in the model ACC. An increase of Lagrangian eddy length scales with depth is masked by the strong decrease with depth of eddy velocities. The cross-stream diffusivities average 750 ± 250 m2 s−1 around the Polar Frontal Zone. The results imply that parameterizations that (only) use eddy kinetic energy to parameterize the diffusivities are incomplete. We suggest that dominant correlations of Lagrangian eddy diffusivities with eddy kinetic energy found in previous studies may have been due to the use of too short time lags in the integration of the velocity autocovariance used to infer the diffusivities. We find evidence that strong mean flow inhibits cross-stream mixing within the ACC, but there are also areas where cross-stream diffusivities are large in spite of strong mean flows, for example, in regions close to topographic obstacles such as the Kerguelen Plateau.
Keywords: Sørishavet; Sørishavsstrømmen; havstrømmer; oseanografi; vannmasser; vannvirvler

Data-based estimation of anthropogenic carbon and acidification in the Weddell Sea on a decadal timescale - Hauck, J.; Hoppema, M.; Bellerby, R. G. J.; Völker, C.; Wolf-Gladrow, D. (Journal of Geophysical Research: Oceans, 2010)
The amount of anthropogenic CO2 (Cant) that entered the Weddell Sea between 1992 and 2008 (Cant1992?2008) was assessed using the extended multiple linear regression (eMLR) method. In the Warm Deep Water (WDW) and the Weddell Sea Bottom Water (WSBW), Cant1992?2008 values were insignificant, whereas values as high as 8 ?mol kg?1 were observed over the shelf. Cant1992?2008 concentrations in the surface layer varied with latitude between 2 and 11 ?mol kg?1. Weak intrusion of anthropogenic CO2 into Weddell Sea Deep Water (WSDW) was demonstrated (Cant1992?2008 yields 1.5?2 ?mol kg?1). That more Cant1992?2008 was found in the WSDW than in the WSBW is surprising, but can be explained by intense ventilation of the WSDW originating from east of the Weddell Gyre. The invasion of Cant1992?2008 provokes a shift in the equilibria of the carbonate system, resulting in acidification and reduction of CO32? concentration. The mean decrease of pH in the upper 200 m layer was 0.016. The largest decrease of calcite and aragonite saturation states was observed at the surface. This implies that surface waters might become undersaturated with respect to aragonite in the future while the underlying WDW is still saturated. Results of this analysis suggest that complete undersaturation of surface waters in the Weddell Sea will be reached after the 21st century.
Publisher: John Wiley & Sons, Ltd
Keywords: Sørishavet; Weddellhavet; antropogenisk CO2; havforsuring; karbondioksid; oseanografi

Evaluating CERES angular distribution models for snow using surface reflectance observations from the East Antarctic Plateau - Hudson, Stephen R; Kato, Seiji; Warren, Stephen G (Journal of Geophysical Research: Atmospheres, 2010)
Clouds and the Earth's radiant energy system (CERES) is a satellite-based remote sensing system designed to monitor the Earth's radiation budget. In this paper we examine uncertainties in the angular distribution models (ADMs) used by CERES over permanently snow covered surfaces with clear skies. These ADMs are a key part of the CERES data processing algorithms, used to convert the observed upwelling radiance to an estimate of the upwelling hemispheric flux. We model top-of-atmosphere anisotropic reflectance factors using an atmospheric radiative transfer model with a lower boundary condition based on extensive reflectance observations made at Dome C, Antarctica. The model results and subsequent analysis show that the CERES operational clear-sky permanent-snow ADMs are appropriate for use over Dome C, with differences of less than 5% between the model results and the ADMs at most geometries used by CERES operationally. We show that the uncertainty introduced into the flux estimates through the use of the modeled radiances used in the ADM development is small when the fluxes are averaged over time and space. Finally, we show that variations in the angular distribution of radiance at the top of the atmosphere due to atmospheric variability over permanently snow covered regions are in most cases unlikely to mask the real variations in flux caused by these atmospheric variations.
Keywords: Antarktis; atmosfæren; fjernmåling; klima; meteorologi; observasjoner; snø; solstråling

A comparison of shortwave reflectance over the East Antarctic Plateau observed by CERES to that estimated from surface reflectance observations - Hudson, Stephen R; Warren, Stephen G; Kato, Seiji (Journal of Geophysical Research: Atmospheres, 2010)
Spectral albedo and bidirectional reflectance of snow were measured at Dome C on the East Antarctic Plateau for wavelengths of 350–2400 nm and solar zenith angles of 52°–87°. A parameterization of bidirectional reflectance, based on those measurements, is used as the lower boundary condition in the atmospheric radiation model SBDART to calculate radiance and flux at the top of the atmosphere (TOA). The model's atmospheric profile is based on radiosoundings at Dome C and ozonesoundings at the South Pole. Computed TOA radiances are integrated over wavelength for comparison with the Clouds and the Earth's Radiant Energy System (CERES) shortwave channel. CERES radiance observations and flux estimates from four clear days in January 2004 and January 2005 from within 200 km of Dome C are compared with the TOA radiances and fluxes computed for the same solar zenith angle and viewing geometry, providing 11,000 comparisons. The measured radiance and flux are lower than the computed values. The median difference is about 7% for CERES on Terra, and 9% on Aqua. Sources of uncertainty in the model and observations are examined in detail and suggest that the measured values should be less than the computed values, but only by 1.7% ± 4%. The source of the discrepancy of about 6% cannot be identified here; however, the modeled values do agree with observations from another satellite instrument (Multiangle Imaging Spectroradiometer), suggesting that the CERES calibration must be considered a possible source of the discrepancy.
Keywords: Antarktis; atmosfæren; fjernmåling; meteorologi; observasjoner; solstråling

Heat conservation during cold exposure in birds (vasomotor and respiratory implications) - Johansen, Kjell; Bech, Claus (Polar Research, 2010)
The mechanisms by :vhich peripheral circulation and respiration serve in maintaining thermal homeostasis in birds living in cold climates are reviewed. Three types of arteriovenous heat exchanger (an elaborate rete, asimple rete, and a venue comirantes system) are found in the legs of birds. The anatomical differences between the different types of A-V associations are described, and the regulation of peripheral blood flow, in respect to maximal heat conservation and prevention of tissue damage, is discussed. A nasal temporal counter current heat exchanger, lowering the temperature of the expired air to values considerably below the body temperature, is the most important mechanism for minimizing the respiratory heat and water loss. In addition, a decreased ventilatory requirement, caused by a changed respiratory pattern and an increased parabronchial oxygen extraction, lowers the amount of air ventilated relative to the amount of oxygen uptake. Thus, the relative loss of heat and water is reduced.
Keywords: Antarktis; fugler; kuldeeksponering; kuldetoleranse; ornitologi; zoofysiologi; zoologi

Swarm characteristics of Antarctic krill Euphausia superba relative to the proximity of land during summer in the Scotia Sea - Klevjer, Thor Aleksander; Tarling, Geraint A.; Fielding, S. (Marine Ecology Progress Series, 2010)
We studied the relationship between the proximity of land and the distribution and swarming characteristics of Antarctic krill across the Scotia Sea in January and February 2003. Krill swarms identified with a Simrad EK60 (38 kHz, 120 kHz) echosounder were grouped into 4 categories according to distance from shoreline: 0 to 50 km, 50 to 100 km, 100 to 200 km and >200 km. Cross-sectional areas of swarms were significantly larger inshore, with a mean value of 120 m^2 in the 0 to 50 km zone compared to <80 m^2 further offshore. The packing concentration of krill within inshore swarms was also significantly greater, with an average density of 95 ind. m^–3 compared to between 24 and 31 ind. m^–3 elsewhere. A large proportion of the biomass was concentrated into a small number of large, dense swarms throughout the survey area, and this trend increased with decreasing distance from shore. The highest median number of swarms per km and krill acoustic biomass per km was found in the 50 to 100 km zone. However, a significantly greater number of large, biomass-rich swarms occurred in the 0 to 50 km zone compared to all other zones. Swarms in the 0 to 50 km zone were also significantly further apart. The majority of swarms were located in the upper 50 m during the daytime although they were marginally deeper in the night in offshore regions. Krill are likely to move between inshore and offshore environments continuously over their lifetimes. The change in krill behaviour between environments could be a response to local predatory threats over short spatial and temporal scales.
Keywords: Scotiahavet; Sørishavet; ekkolodd; krill; marin biologi; oseanografi; plankton

Distribution and demography of Antarctic krill in the Southeast Atlantic sector of the Southern Ocean during the austral summer 2008 - Krafft, Bjørn A.; Melle, W.; Knutsen, T.; Bagøien, E.; Broms, C.; Ellertsen, B.; Siegel, V. (Polar Biology, 2010)
This study documents horizontal distribution and demography of Antarctic krill (Euphausia superba) from the Southern Ocean during January–March 2008. The cruise predominantly occurred in CCAMLR Subarea 48.6, where knowledge about the ecosystem is limited. E. superba were not found north of 52°S. The biomass, estimated from trawl catches, was highest (63.09 g/m2) at a station 680 km southeast of Bouvetøya and at two stations 1,400 and 600 km southeast and southwest of Bouvetøya, 54.67 and 61.38 g/m2, respectively. Body length ranged from 19 to 61 mm (N = 8,538), with a mean of 42.0 ± 6.4 mm (SD). The overall sex ratio was 1:1, 46.2% males (13.2% adults and 33.0% subadults), 46.1% females (33.6% adults and 12.5% subadults), while 7.5% were juveniles. Trawl stations dominated by adults were found west and north of Bouvetøya. Stations with high proportions of subadults and juveniles were mainly found southeast of the island. Four cluster groups were differentiated: analyzing data on krill sex proportions, maturity stages, hydrography, nutrients and chlorophyll concentrations. Two groups represented stations located in the northern part of the study area, where E. superba were absent; water temperatures were higher and the nutrient concentrations lower compared to the groups where E. superba were present. This study shows that bathymetric features like the North Weddell Ridge including Bouvetøya are important for concentrating krill probably due to water mass characteristics and advective processes which influence regional krill demography. The southern regions of CCAMLR sector 48.6 are essential for understanding regional krill recruitment and production.
Keywords: Bouvetøya; Sørishavet; krill; marin biologi; marine økosystemer; zooplankton

Antarctic clouds - Lachlan-Cope, Tom (Polar Research, 2010)
Sensitivity studies with global climate models show that, by their influence on the radiation balance, Antarctic clouds play a major role in the climate system, both directly at high southern latitudes and indirectly globally, as the local circulation changes lead to global teleconnections. Unfortunately, observations of cloud distribution in the Antarctic are limited and often of low quality because of the practical difficulty in observing clouds in the harsh Antarctic environment. The best surface observations suggest that the fractional cloud cover at the South Pole is around 50–60% in all seasons, whereas the cloud cover rises to around 80–90% close to the coast of the continent. Microphysical observations of cloud parameters are also very sparse in the Antarctic. However, the few measurements that do exist show predominantly ice-crystal clouds across the interior, with mixed-phase clouds close to the coasts. Crystal sizes vary from 5 to 30 mm (effective radius) in the interior to somewhat larger ice crystals and water drops near the coast. A wide range of crystal shapes is observed at all sites. This review considers the available cloud observations and highlights the importance of Antarctic clouds and the need for better observations in the future.
Keywords: Antarktis; klimatologi; meteorologi; observasjoner; satellitt bilder; skyer

Importance of the contribution of Limacina helicina faecal pellets to the carbon pump in Terra Nova Bay (Antarctica) - Manno, C.; Tirelli, V.; Accornero, A.; Fonda Umani, S. (Journal of Plankton Research, 2010)
The understanding of the role of the pteropods Limacina helicina in the ecosystem has become of greater interest as the debate on ocean acidification and its consequences for calcifying organisms has increased. Four incubation experiments were carried out in January and February 2006 in Terra Nova Bay Polynya (Ross Sea) to identify the faecal pellets (FPs) produced by L. helicina. Mean FP production rates were 6.1 ± 1.3 and 10.9 ± 2.1 pellets day−1 individual−1 in January and February, respectively. FPs produced by L. helicina had an oval shape with a more lengthened side. The identification of L. helicina faeces allowed us to quantify the amounts of L. helicina FPs in the material collected by sediment traps deployed in the same area from 1998 to 2001. We found that L. helicina FPs flux ranged from 71 × 103 FP m−2 year−1 to 362 × 103 FP m−2 year−1 and reach maximum values in March–April every year. The FPs flux of this organism contributed 19% of the particle organic carbon flux. The carbon pump may be modified if the L. helicina population declines as a consequence of the predicted acidification in polar and subpolar waters.
Keywords: Rosshavet; Sørishavet; havforsuring; krill; marin biologi; oseanografi; plankton

Review of Health of Antarctic wildlife: a challenge for science and policy, edited by Kerry R. Knowles & Martin J. Riddle - McMahon, Clive R (Polar Research, 2010)
Climate change and disease, among other factors, play an important role in the regulation and evolution of animal populations through the differential survival of individuals (Holmes 1996; Harvell et al. 2002). The study and monitoring of disease is important because diseases are likely to be spread more rapidly now than in the recent past because of increased globalization and rapid humaninduced climate change (Daszak et al. 2000; Ward & Lafferty 2004). Antarctic wildlife offers a unique opportunity to study disease spread in terms of globalization and climate change because: (1) Antarctic animals are increasingly exposed to humans and other disease vectors, such as introduced species; and (2) there is strong evidence of climatic changes in and around Antarctica (Mayewski et al. 2009), which together may affect the composition and virulence of pathogens or increase the overlap between Antarctic and other seabirds and their parasites (e.g., Kovats et al. 2001).

An observation of the banded structure of the Antarctic Coastal Current at the prime meridian - Núñez-Riboni, Ismael; Fahrbach, Eberhard (Polar Research, 2010)
Observations of three bands of westward flow and two countercurrents, spanning roughly 50 km from the ice-shelf edge in front of the Fimbul Ice Shelf (prime meridian) in Antarctica, are presented. A comparison with a numerical model and the proximity of two of these current cores to the ice shelf suggest that they split from the Antarctic Coastal Current because of the influence of sea ice on the surface drag. A comparison with previous studies suggests that the other core is the current associated with the Antarctic Slope Front. Because the Fimbul ice shelf overhangs the continental shelf, the Antarctic Coastal Current displaces offshore, getting close to the Antarctic Slope Front. The obtained structure is derived from conductivity–temperature–depth geostrophic velocities from February 2005, referenced with detided acoustic Doppler current profiler velocities.
Keywords: Sørishavet; geostrofisk; havis; havstrømmer; hydrografi; kyststrøm; meteorologi; sjøis

Glacier advance in southern middle-latitudes during the Antarctic Cold Reversal - Putnam, Aaron E.; Denton, George H.; Schaefer, Joerg M.; Barrell, David J. A.; Andersen, Bjørn G.; Finkel, Robert C.; Schwartz, Roseanne; Doughty, Alice M.; Kaplan, Michael R.; Schlüchter, Christian (Nature Geoscience, 2010)
The geographic extent of cooling associated with the Antarctic Cold Reversal is unclear. Dating of glacial moraines in New Zealand suggests that the cooling extended into the southern mid-latitudes, possibly as a result of the northward migration of the southern subtropical front.
Keywords: Antarktis; deglasiasjon; holocene; kryosfæren; paleoglasiologi; paleoklimatologi

An extreme precipitation event in Dronning Maud Land, Antarctica: a case study with the Antarctic Mesoscale Prediction System - Schlosser, Elisabeth; Powers, Jordan G.; Duda, Michael G.; Manning, Kevin W.; Reijmer, Carleen H.; van den Broeke, Michiel R. (Polar Research, 2010)
An extreme precipitation event that influenced almost the whole polar plateau of Dronning Maud Land, Antarctica, is investigated using Antarctic Mesoscale Prediction System archive data. For the first time a high-resolution atmospheric model especially adapted for polar regions was used for such a study in Dronning Maud Land. The outstanding event of 21–25 February 2003 was connected to a strong north-westerly flow, caused by a blocking high above eastern Dronning Maud Land, that persisted for several days and brought unusually large levels of moisture to the Antarctic Plateau. This weather situation is most effective in bringing precipitation to high-altitude interior Antarctic ice-core drilling sites, where precipitation in the form of diamond dust usually dominates. However, a few such precipitation events per year can account for a large percentage of the annual accumulation, which can cause a strong bias in ice-core data. Additionally, increased temperatures and wind speeds during these events need to be taken into account for the correct climatic interpretation of ice cores. A better understanding of the frequency of occurrence of intermittent precipitation in the interior of Antarctica in past and future climates is necessary for both palaeoclimatological studies and estimates of future sea-level change.
Keywords: Dronning Maud Land; havnivåstigning; klimaendringer; klimatologi; meteorologi; nedbør; polarområdene

Wintertime mixed layer measurements at Maud Rise, Weddell Sea - Sirevaag, Anders; McPhee, Miles G; Morison, James H; Shaw, William J; Stanton, Timothy P (Journal of Geophysical Research: Oceans, 2010)
Sea ice plays a crucial role in the exchange of heat between the ocean and the atmosphere, and areas of intense air-sea-ice interaction are important sites for water mass modification. The Weddell Sea is one of these sites where a relatively thin first-year ice cover is constantly being changed by mixing of heat from below and stress exerted from the rapidly changing and intense winds. This study presents mixed layer turbulence measurements obtained during two wintertime drift stations in August 2005 in the eastern Weddell Sea, close to the Maud Rise seamount. Turbulence in the boundary layer is found to be controlled by the drifting ice. Directly measured heat fluxes compare well with previous studies and are well estimated from the mixed layer temperatures and mixing. Heat fluxes are also found to roughly balance the conductive heat flux in the ice; hence, little freezing/melting was observed. The under-ice topography is estimated to be hydraulically very smooth; comparison with a steady 1-D model shows that these estimates are made too close to the ice-ocean interface to be representative for the entire ice floe. The main source and sink of turbulent kinetic energy are shear production and dissipation. Observations indicate that the dynamics of the under-ice boundary layer are influenced by a horizontal variability in mixed layer density and an increasing amount of open leads in the area.
Keywords: Sørishavet; Weddellhavet; atmosfæren; geofysikk; havis; hydrografi; oseanografi; pyknoklin; sjøis

Characteristics of atmospheric transport into the Antarctic troposphere - Stohl, Andreas; Sodemann, Harald (Journal of Geophysical Research: Atmospheres, 2010)
We have developed a 5.5 year climatology of atmospheric transport into the Antarctic troposphere, which uses the same data set and methods as described in a recent study for the Arctic. This allows direct comparisons of transport properties for the two polar regions. The climatology is based on a simulation with the Lagrangian particle dispersion model FLEXPART, where the model atmosphere was globally filled with particles. Transport characteristics as well as emission sensitivities were derived from 6 hourly particle positions. We found that the probability for near-surface air to originate from the stratosphere on a time scale of 10 days is an order of magnitude higher near the South Pole than near the North Pole, a result of higher topography and descent that partly compensates for the flow of air down the Antarctic Plateau with the katabatic winds. The stratospheric influence is largest in fall, which is opposite to the seasonality in the Arctic. Stratospheric influence is much smaller over the shelf ice regions and in a band around Antarctica. The average time for which air near the surface has been exposed to continuous darkness in July (continuous light in January) is longest over the Ronne Ice Shelf and Ross Ice Shelf at ∼11 days (20 days). We calculated how sensitive Antarctic air masses are to emission input up to 30 days before arriving in Antarctica if removal processes are ignored. The emission sensitivity shows strong meridional gradients and, as a result, is generally low over South America, Africa, and Australia. For a 10 day time scale, the largest emission sensitivities over these continents are 1–2 orders of magnitude smaller than over Eurasia for transport to the Arctic, showing that foreign continents have a much smaller potential to pollute the Antarctic than the Arctic troposphere. Emission sensitivities and derived black carbon (BC) source contributions over South America, Africa, and Australia are substantially (a factor 10 for Africa) larger in winter than in summer. In winter, biomass burning contributes more BC than anthropogenic sources. For typical aerosol lifetimes of 5–10 days, ship emissions south of 60°S account for half of the total BC concentrations in the lowest 1000 m of the atmosphere south of 70°S in December. The increasing number of tourists visiting Antarctica and fishing vessels operating close to Antarctica are, therefore, a matter of concern.
Keywords: Antarktis; cruiseturisme; forurensning; klimatologi; polarområdene; stratosfæren; utslipp

Roald Amundsen: Conqueror of the South Pole - Thyvold, Hans Olav; Cowlishaw, J Basil (Font forl., 2010)
ROALD AMUNDSEN (1872-1928), a Norwegian polar explorer and national hero. The first man to find and sail through the North-West Passage, and the first to set foot on the South Pole. NORWEGIAN HERITAGE is a series of illustrated books about our most important and best-known national icons. The respective titles introduce major personalities from the worlds of art and literature, science and sports, but also the many natural wonders of the country, as well as significant historical periods and cultural expressions. Each book offers an updated introduction to readers who wish to familiarize themselves with a given subject.
Publication Title: Norwegian Heritage
Keywords: Antarktis; Sydpolsekspedisjonen; oppdagelsesreiser; polarhistorie

A consistent data set of Antarctic ice sheet topography, cavity geometry, and global bathymetry - Timmermann, Ralph; Le Brocq, Anne M; Deen, Tara J; Domack, Eugene W; Dutrieux, Pierre; Galton-Fenzi, Benjamin K; Hellmer, Hartmut H; Humbert, Angelika; Jansen, Daniela; Jenkins, Adrian; Lambrecht, Astrid; Makinson, Keith; et al. (Earth Syst. Sci. Data, 2010)
Sub-ice shelf circulation and freezing/melting rates in ocean general circulation models depend critically on an accurate and consistent representation of cavity geometry. Existing global or pan-Antarctic data sets have turned out to contain various inconsistencies and inaccuracies. The goal of this work is to compile in- dependent regional fields into a global data set. We use the S-2004 global 1-minute bathymetry as the backbone and add an improved version of the BEDMAP topography (ALBMAP bedrock topography) for an area that roughly coincides with the Antarctic continental shelf. The position of the merging line is individually chosen in different sectors in order to get the best out of each data set. High resolution gridded data for upper and lower ice surface topographies and cavity geometry of the Amery, Fimbul, Filchner-Ronne, Larsen C and George VI Ice Shelves, and for Pine Island Glacier are carefully merged into the ambient ice and ocean topographies. Multibeam survey data for bathymetry in the former Larsen B cavity and the southeastern Bellingshausen Sea have been obtained from the data centers of Alfred Wegener Institute (AWI), British Antarctic Survey (BAS) and Lamont-Doherty Earth Observatory (LDEO), gridded, and blended into the existing bathymetry map. The resulting global 1-minute topography data set (RTopo-1) contains maps for upper and lower ice surface heights, bedrock bathymetry, and consistent masks for open ocean, grounded ice, floating ice, and bare land surface.
Publisher: Copernicus Publications
Keywords: Antarktis; Sørishavet; batymetri; glasiologi; havbunnen; topografi

Venom on ice: First insights into Antarctic octopus venoms - Undheim, E.A.B.; Georgieva, D.N.; Thoen, H.H.; Norman, J.A.; Mork, J.; Betzel, C.; Fry, B.G. (Toxicon, 2010)
The venom of Antarctic octopus remains completely unstudied. Here, a preliminary investigation was conducted into the properties of posterior salivary gland (PSG) extracts from four Antarctica eledonine (Incirrata; Octopodidae) species (Adelieledone polymorpha, Megaleledone setebos, Pareledone aequipapillae, and Pareledone turqueti) collected from the coast off George V’s Land, Antarctica. Specimens were assayed for alkaline phosphatase (ALP), acetylcholinesterase (AChE), proteolytic, phospholipase A2 (PLA2), and haemolytic activities. For comparison, stomach tissue from Cirroctopus sp. (Cirrata; Cirroctopodidae) was also assayed for ALP, AChE, proteolytic and haemolytic activities. Dietary and morphological data were collected from the literature to explore the ecological importance of venom, taking an adaptive evolutionary approach. Of the incirrate species, three showed activities in all assays, while P. turqueti did not exhibit any haemolytic activity. There was evidence for cold-adaptation of ALP in all incirrates, while proteolytic activity in all except P. turqueti. Cirroctopus sp. stomach tissue extract showed ALP, AChE and some proteolytic activity. It was concluded that the AChE activity seen in the PSG extracts was possibly due to a release of household proteins, and not one of the secreted salivary toxins. Although venom undoubtedly plays an important part in prey capture and processing by Antarctica eledonines, no obvious adaptations to differences in diet or morphology were apparent from the enzymatic and haemolytic assays. However, several morphological features including enlarged PSG, small buccal mass, and small beak suggest such adaptations are present. Future studies should be conducted on several levels: Venomic, providing more detailed information on the venom compositions as well as the venom components themselves; ecological, for example application of serological or genetic methods in identifying stomach contents; and behavioural, including observations on capture of different types of prey.
Keywords: Sørishavet; biokjemi; bløtdyr; marin biologi; toksikologi

Biogeochemical weathering under ice: Size matters - Wadham, Jemma L; Tranter, Martyn; Skidmore, Mark; Hodson, Andy; Priscu, John C; Lyons, W Berry; Sharp, Martin; Wynn, Peter; Jackson, Miriam (Global Biogeochemical Cycles, 2010)
The basal regions of continental ice sheets are gaps in our current understanding of the Earth's biosphere and biogeochemical cycles. We draw on existing and new chemical data sets for subglacial meltwaters to provide the first comprehensive assessment of sub-ice sheet biogeochemical weathering. We show that size of the ice mass is a critical control on the balance of chemical weathering processes and that microbial activity is ubiquitous in driving dissolution. Carbonate dissolution fueled by sulfide oxidation and microbial CO2 dominate beneath small valley glaciers. Prolonged meltwater residence times and greater isolation characteristic of ice sheets lead to the development of anoxia and enhanced silicate dissolution due to calcite saturation. We show that sub-ice sheet environments are highly geochemically reactive and should be considered in regional and global solute budgets. For example, calculated solute fluxes from Antarctica (72–130 t yr−1) are the same order of magnitude as those from some of the world's largest rivers and rates of chemical weathering (10–17 t km−2 yr−1) are high for the annual specific discharge (2.3–4.1 × 10−3 m). Our model of chemical weathering dynamics provides important information on subglacial biodiversity and global biogeochemical cycles and may be used to design strategies for the first sampling of Antarctic Subglacial Lakes and other sub-ice sheet environments for the next decade.
Keywords: Antarktis; biogeokjemi; biosfære; brehylle; glasiologi; innlandsis; isbrem; isshelf; subglasial biodiversitet; subglasial innsjø

The acoustic properties of Salpa thompsoni - Wiebe, Peter H.; Chu, Dezhang; Kaartvedt, Stein; Hundt, Anna; Melle, Webjorn; Ona, Egil; Batta-Lona, Paola (ICES Journal of Marine Science, 2010)
Wiebe, P. H., Chu, D., Kaartvedt, S., Hundt, A., Melle, W., Ona, E., and Batta-Lona, P. 2010. The acoustic properties of Salpa thompsoni. – ICES Journal of Marine Science, 67: 583–593.Aggregations of the salp Salpa thompsoni were encountered during the Antarctic krill and ecosystem-studies cruise on the RV “G.O. Sars” from 19 February to 27 March 2008. The salp's in situ target strength (TS), size, number of individuals in aggregate chains, and chain angle of orientation were determined. Shipboard measurements were made of Salpa thompsoni's material properties. Individual aggregates were mostly 45.5–60.6 mm in mean length; relatively rare solitaries were ∼100 mm. Chains ranged from 3 to at least 121 individuals, and in surface waters (<20 m), they showed no preferred angle of orientation. Sound-speed contrast (h) ranged from 1.0060 to 1.0201 and density contrast (g) estimates between 1.0000 and 1.0039. The in situ TS distributions peaked between −75 and −76 dB at 38 kHz, with a secondary peak at approximately −65 dB. TS ranged between −85 and −65 dB at 120 and 200 kHz and peaked around −74 dB. The measured in situ TS of salps reasonably matched the theoretical scattering-model predictions based on multi-individual chains. The backscattering from aggregate salps gives rise to TS values that can be similar to krill and other zooplankton with higher density and sound-speed contrasts.
Keywords: Bouvetøya; Sørishavet; copepoder; ekkolodd; krill; marin biologi; marine økosystemer; oseanografi; plankton

Cloning and heterologous expression of two cold-active lipases from the Antarctic bacterium Psychrobacter sp. G - Xuezheng, Lin; Shuoshuo, Cui; Guoying, Xu; Shuai, Wang; Ning, Du; Jihong, Shen (Polar Research, 2010)
Antarctic bacteria producing extracellular lipolytic enzymes with activity at low temperature were isolated, and the most promising strain, named G, was identified as a Psychrobacter species based on 16S rDNA sequence alignment. The genomic DNA of this bacterium was used to construct its plasmid genomic library into pUC118 plasmid vectors, and to screen the cold-active lipolytic enzyme genes. Two genes encoding for cold-active lipolytic enzymes, Lip-1452 (with an open reading frame of 1452 bp in length) and Lip-948 (with an open reading frame of 948 bp in length), were screened. The primary structure of the two lipases deduced from the nucleotide sequence showed a consensus pentapeptide containing the active serine (Lip-1452, GDSAG, and Lip-948, GNSMG) and a conserved His-Gly dipeptide in the N-terminal part of the enzyme. Protein sequence alignment and conserved regions analysis indicated that the two lipases probably belonged to family IV and family V of the bacterial lipolytic enzymes, respectively. The upstream and downstream sequences of the two lipolytic lipases were also obtained. The two lipase genes were cloned into the expression vector pCold III and integrated into Escherichia coli BL21 (DE3). The functional expression of both lipase genes by E. coli BL21 (DE3) cells was observed as the formation of clear haloes around colonies on a 1% (vol/vol) tributyrin plate upon induction with isopropyl-b-Dthiogalactopyranoside at 5°C. A lipase activity assay showed that the specific activity of the pCold III+Lip-948 expression system was up to 3.7 U ml-1, whereas that of pCold III+Lip-1452 was very low.
Keywords: Sørishavet; bakterier; bioteknologi; genkloning; genuttrykk; marin biologi; mikroorganismer

Seismic and radar investigations of Fourcade Glacier on King George Island, Antarctica - Young Kim, Ki; Lee, Joohan; Ho Hong, Myung; Kuk Hong, Jong; Keun Jin, Young; Shon, Howong (Polar Research, 2010)
To determine P- and S-wave velocities, elastic properties and subglacial topography of the polythermal Fourcade Glacier, surface seismic and radar surveys were conducted along a 470-m profile in November 2006. P- and S-wave velocity structures were determined by travel-time tomography and inversion of Rayleigh wave dispersion curves, respectively. The average P- and S-wave velocities of ice are 3466 and 1839 m s-1, respectively. Radar velocities were obtained by migration velocity analysis of 112 diffraction events. An estimate of 920 kg m-3 for the bulk density of wet ice corresponds to water contents of 5.1 and 3.2%, which were derived from the average P-wave and radar velocities, respectively. Using this density and the average P- and S-wave velocities, we estimate that the corresponding incompressibility and rigidity of the ice are 6.925 and 3.119 GPa, respectively. Synergistic interpretation of the radar profile and P- and S-wave velocities indicates the presence of a fracture zone above a subglacial high. Here, the P- and S-wave velocities are approximately 5 and 3% less than in the ice above a subglacial valley, respectively. The S-wave velocities indicate that warmer and less rigid ice underlies 10–15 m of colder ice near the surface of the glacier. Such layering is characteristic of polythermal glaciers. As a relatively simple non-invasive approach, integration of P-wave tomography, Rayleigh wave inversion and ground-towed radar is effective for various glaciological studies, including the elastic properties of englacial and subglacial materials, cold/warm ice interfaces, topography of a glacier bed and location of fracture zones.
Keywords: Antarktis; geofysikk; glasiologi; isbre; radarundersøkelse; seismisk undersøkelse; subglasial; tomografi; topografi

The first Antarctic whaling season of Admiralen (1905–1906): the diary of Alexander Lange - Adie, Susan; Basberg, Bjørn L; Lange, Alexander (Polar Record, 2009)
The first factory ship of the so-called modern era of Antarctic whaling was Admiralen, arriving together with two smaller catcher boats in the South Shetland Islands in January 1906, after a period of whaling in the Falkland Islands. The expedition leader was Alexander Lange, a Norwegian whaler with a long experience from whaling in northern Norway and Spitsbergen. He kept a diary for a considerable period and this covered several whaling voyages. The one dealing with the pioneer Antarctic season of 1905–1906 has been translated from Norwegian into English and is presented here with an introduction that places the expedition into its wider context.
Publisher: Cambridge University Press
Keywords: Nordmenn; Norge; Sørishavet; dagbøker; hvalfangere; hvalfangst; pelagisk

Isostatic stability of the East Antarctic station Dumont d’Urville from long-term geodetic observations and geophysical models - Amalvict, Martine; Willis, Pascal; Wöppelmann, Guy; Ivins, Erik R.; Bouin, Marie-Noëlle; Testut, Laurent; Hinderer, Jacques (Polar Research, 2009)
Geodetic measurements of the vertical crustal displacement collocated with absolute gravity changes provide a discriminatory measurement of present-day glacial changes, versus more deeply seated rock motions caused by glacial isostatic adjustment (GIA). At the East Antarctic station of Dumont d’Urville, we compare the displacements derived from continuous DORIS (1993.0– 2006.0) and Global Positioning System (GPS) (1999.0–2005.7) data, and observed changes in absolute gravity (2000–2006), with the predicted vertical displacement and change in gravity from GIA modelling. The geodetic results have mutual self-consistency, suggest station stability and provide upper bounds on both GIA and secular ice mass changes. The GIA models tend to predict amplitudes of rock motion larger than those observed, and we conclude that this part of Antarctica is probably experiencing a slight gain in ice mass, in contrast to West Antarctica.
Keywords: Antarktis; breendringer; geodesi; geofysikk; innlandsis; tidevannsmålinger

Revisiting sites of the South Pole Queen Maud Land Traverses in East Antarctica: Accumulation data from shallow firn cores - Anschütz, Helgard; Müller, Karsten; Isaksson, Elisabeth; McConnell, Joseph R.; Fischer, Helmut; Miller, Heinz; Albert, Mary; Winther, Jan-Gunnar (Journal of Geophysical Research: Atmospheres, 2009)
[1] Ground-based accumulation measurements are scarce on the high East Antarctic plateau, but highly necessary for model validation and the interpretation of satellite data for the determination of Antarctic mass balance. Here, we present accumulation results obtained from four shallow firn cores drilled in the Antarctic summer season 2007/2008. The cores were drilled along the first leg of the Norwegian-US IPY traverse through East Antarctica, visiting sites like Plateau Station and Pole of Relative Inaccessibility that have been covered by the South Pole Queen Maud Land Traverses (SPQMLT) in the 1960s. Accumulation has been determined from volcanic chronology established from the conductivity records measured by dielectric profiling (DEP). The Tambora 1815/unknown 1809 double peak is clearly visible in the conductivity data and serves as a reliable time marker. Accumulation rates averaged over the period 1815–2007 are in the range of 16 to 32 kg m−2 a−1, somewhat lower than expected from the SPQMLT data. The spatial pattern is mainly influenced by elevation and continentality. Three of the firn cores show a decrease of more than 20% in accumulation for the time period 1815–2007 in relation to accumulation rates during the period 1641–1815. The spatial representativity of the firn cores is assessed by ground-penetrating radar, showing a rather smoothly layered pattern around the drill sites. Validation of the DEP results is utilized by comparison with chemistry data, proving the validity of the DEP method for dating firn cores. The results help understanding the status of the East Antarctic ice sheet and will be important for e.g. future model-derived estimates of the mass balance of Antarctica.
Keywords: Dronning Maud Land; geofysikk; glasiologi; innlandsis; isbreer; vulkaner

What can GPR tell us about cryoconite holes? 3D FDTD modeling, excavation and field GPR data - Brandt, Ola; Taurisano, Andrea; Giannopoulos, Antonios; Kohler, Jack (Cold Regions Science and Technology, 2009)
Cryoconite holes form on ice due to enhanced ablation around particles deposited on the surface, and are present in the ablation area of glaciers worldwide. Here we investigate the use of Ground Penetrating Radar (GPR) as a non-destructive method to monitor and map cryoconite holes. We compare GPR data obtained from the Jutulsessen blue ice area in Dronning Maud Land, Antarctica, with modeled GPR data. The modeled GPR response to cryoconite holes is numerically calculated by solving Maxwell's equations with a 3D Finite-Difference Time-Domain (FDTD) scheme. The model includes a realistic shielded bowtie antenna and dimensions and constituent parameters of cryoconite holes excavated in the field. We have performed what-if scenarios with controlled variation of single parameters. We show that GPR can be used to determine the horizontal extent, depth and whether a cryoconite hole is frozen or contains liquid water, information unavailable from visual surface inspection. The cryoconite thickness can, for completely frozen holes, be determined to within a 1/4 of the GPR center frequency wavelength. The exact water content is not readily extractable because the GPR response is influenced by many other factors such as: cryoconite thickness, shape and roughness, as well as antenna ground coupling.
Keywords: Dronning Maud Land; georadar; glasiologi

Mixing on the continental slope of the southern Weddell Sea - Daae, Kjersti L.; Fer, Ilker; Abrahamsen, E. Povl (Journal of Geophysical Research: Oceans, 2009)
Shipboard hydrography and current profiles collected in 2003 and time series from moored current meters deployed in late 1990s are analyzed to study the variability of mixing in the southeastern Weddell Sea. Profiles of eddy diffusivity Kρ are inferred from fine-scale shear (vertical derivative of horizontal velocity) and strain (vertical derivative of isopycnal displacement) variance using parameterizations which relate the internal wave energy to the dissipation rate at small scales. The highest mixing rates are seen near the bottom where the eddy diffusivities are elevated by 1 order of magnitude from those in the interior and exceed 10−4 m2 s−1. The observations show latitudinal variability in Kρ, particularly near the bottom, where Kρ significantly increases near 74° 28′S, the critical latitude for lunar semidiurnal (M2) tides. In this region, the critical latitude coincides with near-critical topography on the upper continental slope, a situation which favors generation of M2 internal waves. Consistent with the results from fine-scale shear and strain parameterizations, which indicate highest bottom diffusivities near the critical latitude, independent analysis of current time series from moored instruments shows a thickening of the frictional bottom boundary layer near the critical latitude. Semidiurnal tidal dynamics at the upper continental slope together with the critical latitude effects lead to mixing that might significantly affect the regional heat budget and the circulation in the study area.
Keywords: Sørishavet; Weddellhavet; bunnvann; geofysikk; hydrografi; kontinentalmargin; oseanografi; vannvirvler

Report from the Workshop on the Development of the Weddell Sea - Dronning Maud Land Regional Working Group SOOS - de Steur, Laura; Gutt, Julian; Moreau, Sebastien ([Zenodo], 2009)
This report summaries the first workshop of the Southern Ocean Observing System (SOOS) Weddell Sea and Dronning Maud Land (WS-DML) Regional Working Group held Tromsø, Norway, in January 2019.
Publication Title: SOOS Report Series Volume: 9
Keywords: Dronning Maud Land; Sørishavet; geofysikk; geologi; konferanse; symposium

Tropical Pacific - high latitude south Atlantic teleconnections as seen in δ18O variability in Antarctic coastal ice cores - Divine, Dmitry; Isaksson, Elisabeth; Kaczmarska, Marzena; Godtliebsen, Fred; Oerter, Hans; Schlosser, Elisabeth; Johnsen, Sigfus J; van den Broeke, M; van de Wal, R S W (Journal of Geophysical Research: Atmospheres, 2009)
We use a network of eight ice cores from coastal Dronning Maud Land (DML), Antarctica, to examine the role of the tropical ENSO (El Niño-Southern Oscillation) in the temporal variability of δ18O in annual accumulation. The longest record from the S100 ice core covering the period 1737–1999 is used to analyze the teleconnections between the tropical Pacific and coastal DML on decadal scales and longer. A shorter stacked coastal DML δ18O series spanning 1955–1999 is constructed to assess the variability of ENSO teleconnection on interannual scales. Results suggest that, on typical ENSO timescales of 2–6 years, the strength of the teleconnection varies in time, being stronger for years with generally negative phase of the Southern Annular Mode (SAM). On the timescales of approximately two decades (bidecadal), positive isotope anomalies are associated with oceanic warming and a westward sea surface temperature (SST) gradient in the equatorial Pacific. Bidecadal variability in SAM, forced by the tropical Pacific, is proposed as a critical element in the teleconnection. Our analysis suggests that a multidecadal positive trend in the annual mean δ18O values from the analyzed cores can be indicative of the atmospheric warming that begun in this part of the DML already in the 1910s. The trend in δ18O, quantified in terms of long-term surface air temperature (SAT) changes, is consistent with the instrumental data. Yet, we speculate that the accurate estimation of SAT trends requires an assessment of the potential role of secular SAM and sea ice extent changes in shaping the isotopic signal.
Keywords: Dronning Maud Land; Sørishavet; geofysikk; klima

Shelf-derived iron inputs drive biological productivity in the southern Drake Passage - Dulaiova, H.; Ardelan, M. V.; Henderson, P. B.; Charette, M. A. (Global Biogeochemical Cycles, 2009)
In the Southern Ocean near the Antarctic Peninsula, Antarctic Circumpolar Current (ACC) fronts interact with shelf waters facilitating lateral transport of shelf-derived components such as iron into high-nutrient offshore regions. To trace these shelf-derived components and estimate lateral mixing rates of shelf water, we used naturally occurring radium isotopes. Short-lived radium isotopes were used to quantify the rates of shelf water entrainment while Fe/228Ra ratios were used to calculate the Fe flux. In the summer of 2006 we found rapid mixing and significant lateral iron export, namely, a dissolved iron flux of 1.1 × 105 mol d−1 and total acid leachable iron flux of 1.1 × 106 mol d−1 all of which is transported in the mixed layer from the shelf region offshore. This dissolved iron flux is significant, especially considering that the bloom observed in the offshore region (0.5–2 mg chl a m−3) had an iron demand of 1.1 to 4 × 105 mol Fe. Net vertical export fluxes of particulate Fe derived from 234Th/238U disequilibrium and Fe/234Th ratios accounted for only about 25% of the dissolved iron flux. On the other hand, vertical upward mixing of iron rich deeper waters provided only 7% of the lateral dissolved iron flux. We found that similarly to other studies in iron-fertilized regions of the Southern Ocean, lateral fluxes overwhelm vertical inputs and vertical export from the water column and support significant phytoplankton blooms in the offshore regions of the Drake Passage.
Keywords: Sørishavet; Sørishavsstrømmen; biogeokjemi; fytoplankton; marin kjemi; oseanografi; radiumisotoper

Fluid infiltration, heat transport, and healing of microcracks in the damage zone of magmatic veins: Numerical modeling - Engvik, Lars; Stöckhert, Bernhard; Engvik, Ane K (Journal of Geophysical Research: Solid Earth, 2009)
Alteration halos with sharp boundaries are flanking pegmatitic veins in high-grade metamorphic and magmatic rocks of Dronning Maud Land, Antarctica. These halos are interpreted to represent the damage zone, formed as the wake of the process zone at the tip of the propagating magma-filled fracture and infiltrated by the fluid phase liberated from the crystallizing hydrous melt. On the basis of a set of assumptions, our numerical model explores the time scales of the infiltration processes, taking into account the combined effects of fluid flow, heat transfer, and temperature-dependent decay of interconnected porosity due to microcrack healing. Assuming an initial magma temperature of 700°C, a far field temperature in the host rock of 300°C, an initial porosity range of 0.5–2% in the damage zone, a permeability of 10−16 m2, and a pressure difference of 300 MPa, we find that the fluid infiltration into the damage zone proceeds within seconds to minutes and that the fluid flow contributes significantly to the heat transfer into the host rock. Assuming an initial microcrack aperture of 1 μm, the model predicts that the crack healing time scale is significantly longer than that of fluid infiltration in the case of thin veins with narrow damage zones; in this case, crack healing does not hinder fluid infiltration. Only for thick veins with high heat content and prolonged crystallization history does permeability become reduced by crack healing during progressive fluid infiltration. The results indicate that the formation of the alteration halos flanking pegmatitic veins may be a quasi-instantaneous process on geological time scales.
Keywords: Dronning Maud Land; geofysikk; geologi; mineralogi

Tracing biomass burning aerosol from South America to Troll Research Station, Antarctica - Fiebig, Markus; Lunder, Chris René; Stohl, Andreas (Geophysical Research Letters, 2009)
The atmospheric observatory at the Norwegian Research Station Troll in Queen Maud Land, Antarctica, holds, since February 2007, the first all-year Antarctic atmospheric aerosol particle number size distribution measurements. These are colocated with measurements of the aerosol absorption and spectral scattering coefficients. In June 2007, this instrument set observed an aerosol whose properties were indicative of a biomass burning aerosol. These properties included two log-normal size distribution modes with median particle diameters of 0.105 μm and 0.36 μm, sharply falling off to smaller and larger sizes, and peaks in scattering and absorption coefficient. With backward plume calculations of the Lagrangian transport model FLEXPART and the MODIS fire activity product, a source-receptor relationship was established between biomass burning events in Central Brazil and the aerosol seen at Troll. This is the first direct evidence that the Antarctic continent is susceptible to emissions from as far north as Southern tropical latitudes.
Keywords: Dronning Maud Land; Troll forskningsstasjon; biomasse; klimatologi; meteorologi; utslipp

Evidence for northward expansion of Antarctic Bottom Water mass in the Southern Ocean during the last glacial inception - Govin, Aline; Michel, Elisabeth; Labeyrie, Laurent; Waelbroeck, Claire; Dewilde, Fabien; Jansen, Eystein (Paleoceanography, 2009)
We investigated deep water changes in the Southern Ocean during the last glacial inception, in relationship to surface hydrology and global climatology, to better understand the mechanisms of the establishment of a glacial ocean circulation. Changes in benthic foraminiferal δ13C from three high-resolution cores are compared and indicate decoupled intermediate and deep water changes in the Southern Ocean. From the comparison with records from the North Atlantic, South Atlantic, and the Southern Ocean, we show that the early southern deep water δ13C drop observed at the MIS 5.5–5.4 transition occurred before any significant reduction of North Atlantic Deep Water ventilation. We propose that this drop is linked to the northward expansion of poorly ventilated Antarctic Bottom Water (AABW) mass in the Southern Ocean. Associated with an early cooling in the high southern latitudes, the westerly winds and surface oceanic fronts would migrate equatorward, thus weakening the upwelling of Circumpolar Deep Waters. Reduced heat brought to Antarctic surface waters would enhance sea ice formation during winters and the deep convection of cold and poorly ventilated AABW.
Keywords: AABW; Sørishavet; bunnvann; havstrømmer; hydrologi; paleoklimatologi; paleoseanografi; vannmasser

Survey of waste water disposal practices at Antarctic research stations - Gröndahl, Fredrik; Sidenmark, Johan; Thomsen, Ann (Polar Research, 2009)
To inform the future practices to be employed for handling waste water and grey water at the Swedish Antarctic station,Wasa, in Dronning Maud Land, the Swedish Polar Research Secretariat took the initiative to survey the practices of the 28 nations with stations in Antarctica. A questionnaire was sent out to all members of the Antarctic Environment Officers Network during the autumn of 2005. Questions were asked about the handling of waste water and grey water, the type of sewage treatment, and installation and operational costs. The response to the questionnaire was very good (79%), and the results showed that 37% of the permanent stations and 69% of the summer stations lack any form of treatment facility. When waste water and grey water containing microorganisms are released, these microorganisms can remain viable in lowtemperature Antarctic conditions for prolonged periods. Microorganisms may also have the potential to infect and cause disease, or become part of the gut flora of local bird and mammal populations, and fish and marine invertebrates. The results from 71 stations show that much can still be done by the 28 nations operating the 82 research stations in Antarctica. The technology exists for effective waste water treatment in the challenging Antarctic conditions. The use of efficient technology at all permanent Antarctic research stations would greatly reduce the human impact on the pristine Antarctic environment. In order to protect the Antarctic environment from infectious agents introduced by humans, consideration should also be given to preventing the release of untreated waste water and grey water from the smaller summer stations.
Keywords: Dronning Maud Land; avfallshåndtering; forskningsstasjoner; menneskelig påvirkning; miljøvern; økologi

Atmospheric monitoring at the Norwegian Antarctic station Troll: measurement programme and first results - Hansen, Georg; Aspmo, Katrine; Berg, Torunn; Edvardsen, Kåre; Fiebig, Markus; Kallenborn, Roland; Krognes, Terje; Lunder, Chris; Stebel, Kersten; Schmidbauer, Norbert; Solberg, Sverre; Yttri, Karl Espen (Polar Research, 2009)
The Troll Atmospheric Station in Antarctica (72°01'S, 2°32'E, 1309 m a.s.l.) was established and put into operation in early 2007. The main foci of the measurement programme are pollution and aerosols in the transition zone between the coastal zone and the inland ice plateau, complementing existing observation programmes along the Antarctic coast and on the Antarctic Plateau. After one year of operation, the monitoring programme is fully operative, and a comprehensive set of data is being analysed. As far as comparable data are available, there is satisfactory agreement between previous and new data. Both aerosol data and measurements of pollution indicate the episodic influence of coastal air masses throughout the year. Background values of medium long-lived pollutants such as CO, O3 and Hg are up to 50% lower than at corresponding Arctic sites (depending on the season), but are still significant. Total ozone and UV doses manifest the recurring Antarctic stratospheric ozone hole, which was moderately severe, but very persistent in 2007. Specific episodes of elevated aerosol concentration and mercury activation are currently under detailed investigation, and will be published separately.
Keywords: Dronning Maud Land; Troll forskningsstasjon; atmosfæren; forurensning; meteorologi; målinger; ozonlaget

The water column as an attenuating factor of the UVR effects on bacteria from a coastal Antarctic marine environment - Hernández, Edgardo A; Ferreyra, Gustavo A; Ruberto, Lucas A M; Mac Cormack, Walter P (Polar Research, 2009)
The effect of UVR on the viability of the culturable bacterial community fraction (CBC), and two of their isolated components (Arthrobacter-UVvi and Bizionia-UVps), was studied in the top few metres of the water column at Potter Cove, King George Island, Antarctica. Quartz flasks containing CBC from surface waters were exposed to solar radiation at depths of 0, 1 and 3 m. Similar experiments using UVps and UVvi isolates were performed. In some experiments interferential filters were used to discriminate photosynthetic active radiation (PAR), UV-A and UV-B. CBC from depths of 0, 10 and 30 m were also exposed to surface solar radiation. The deleterious effect of UVR was observed at the surface and at a depth of 1 m, but not at a depth of 3 m. Studies with interferential filters showed low bacterial viability values at depths of 0 and 1 m under both UVR treatments. However, under low radiation doses the effect attributed to UV-B was higher than that caused by UV-A. The surface CBC was more resistant to UVR compared with CBC from a depth of 30 m. The results showed that CBC inhabiting waters above the pycnocline (located at a depth of 5–10 m) are more efficiently adapted to UVR than are those from below the pycnocline. The impact of UVR on the marine bacterioplankton studied was only detected in the first metre of the stratified water column of Potter Cove, which has high levels of suspended particulate matter. These results support the evidence for a significant UVR-attenuating effect in the water column of this coastal Antarctic water.
Keywords: Sørishavet; UV-stråling; bakterier; marin biologi; plankton; statistisk analyse; ultrafiolett stråling; vannsøyle

Vill etter krill : på ekspedisjon med G.O. SARS til Sørishavet - Iversen, Svein A (Red.); Myklevoll, Sigmund (Red.); Mæstad, Kjartan (Red.); Nøttestad, Leif (Red.) (Havforskningsinstituttet, 2009)
Keywords: Sørishavet; ekspedisjoner; euphausiacea; forskning; krill; marin biologi; marine økosystemer; plankton; raudåte

Vill etter krill : på ekspedisjon med G.O. SARS til Sørishavet - Iversen, Svein A; Myklevoll, Sigmund; Mæstad, Kjartan; Nøttestad, Leif; Alvarez, Jaime (Havforskningsinstituttet, 2009)
Keywords: Sørishavet; ekspedisjoner; krill; marin biologi; raudåte; økosystemer

A review of two decades (1986 2008) of geochronological work in Heimefrontfjella, and geotectonic interpretation of western Dronning Maud Land, East Antarctica - Jacobs, Joachim (Polarforschung, 2009)
During two decades (1986 - 2008) of geochronological work in Heimefrontfjella, nearly 130 geochronological ages were produced using a wide range of geochronological techniques. The ages fall into four broad age groups from Archaean to Cenozoic times, revealing a long and complex geological history. In general, Heimefrontfjella consists of Mesoproterozoic high grade basement related to the ∼1100 Ma Maud Belt. This basement is overlain by Permo-Carboniferous sedimentary rocks and Jurassic lavas. Archaean and Palaeoproterozoic detrital zircon ages are recorded from meta-sedimentary rocks probably characterizing the foreland of the Maud Belt. The protolith and metamorphic ages of the Mesoproterozoic Maud Belt fall into two groups. An older age group from ∼1200-1100 Ma is related to back-arc and island arc volcanism. High-grade metamorphism in the Maud Belt is dated between 1090-1060 Ma and is thought to reflect continent-continent collision, possibly related to the formation of Rodinia. Regional cooling to below 500-300 °C at ∼1010-960 Ma in part of the mountain range might indicate rifting of Rodinia. The eastern part of the mountain range is overprinted by the ∼600-500 Ma East African-Antarctic Orogen. The orogenic front of this major mobile belt is exposed in the study area as the Heimefront Shear Zone. East of this major lineament all Ar-Ar, K-Ar and Rb-Sr mineral ages are reset to ∼500 Ma. Initial Gondwana rifting affected the area at c. 180 Ma, when the Bouvet/Karroo mantle plume caused dynamic uplift of the area, followed by burial underneath up to 2 km of Jurassic lava. This led to tempering of the basement up to about 100 °C, as indicated by apatite fission track data. The lava pile underwent erosion in Cretaceous time, when renewed rifting affected the region. Latest tectonic movements might be related to Cenozoic ice loading related to the built up of the Antarctic ice sheet.
Publisher: Alfred-Wegener-Institut für Polar- und Meeresforschung und Deutsche Gesellschaft für Polarforschung Place: Bremerhaven, Germany ISBN: 2190-1090
Keywords: Dronning Maud Land; ekspedisjoner; geokronologi; geologi; tektonikk

Geological map of Heimefrontfjella, Dronning Maud Land, Antarctica (Scale 1:250,000) - Jacobs, Joachim; Bauer, Wilfried; Kreutzer, Stefan; Patzelt, Gernot; Schmidt, Rainer; Schulze, Peter; Siegesmund, Siegfried; Spaeth, Gerhard; Thomas, Robert J; Weber, Klaus; Zarske, Gerd (PANGAEA, 2009)
The geological overview map was compiled from 15 geological maps (1 : 25,000) and is based on Jacobs et al. 1996. The topographic basemaps were adapted from unpublished 1:250,000 provisional topographic maps, Institut f. Angewandte Geodäsie, Frankfurt, 1983. Part of the contour lines are from Radarsat (Liu et al. 2001).
Keywords: Dronning Maud Land; geologi; kart; topografi

Cold Recall : Reflections of a Polar Explorer - Kløver, Geir O (Red.) (The Fram Museum, 2009)
Publication Title: A Fram museum exhibition
Keywords: Antarktis; Roald Amundsen; Sydpolekspedisjon; oppdagelsesreiser

Kvalfangst i Sørishavet - Knarvik, Olaf (Kjelda, 2009)
Keywords: Sørishavet; fotografi; hvalfangst

Ice-ocean processes over the continental shelf of the southern Weddell Sea, Antarctica: A review - Nicholls, Keith W.; Østerhus, Svein; Makinson, Keith; Gammelsrød, Tor; Fahrbach, Eberhard (Reviews of Geophysics, 2009)
Interactions between the Southern Ocean and the Weddell Sea ice shelves are important both to the Antarctic Ice Sheet and to the production of globally significant water masses. Here we review the interaction between the Filchner-Ronne Ice Shelf and the shelf sea in which it floats. The continental shelf processes leading to the production of Weddell Sea deep and bottom waters from the original off-shelf source waters are discussed, and a new view is offered of the initial production of High-Salinity Shelf Water. Data from ship-based measurements at the ice front, from glaciological methods, and from measurements made within the sub–ice shelf cavity itself are used to describe the pattern of flows beneath the ice shelf. We also consider the variability observed within the cavity from tidal to interannual time scales and finish with a discussion of future research priorities in the region.
Keywords: AABW; Antarktis; Sørishavet; Weddellhavet; glasiologi; innlandsis; isfront; isshelf; oseanografi; vannmasser

Evolution of first-year and second-year snow properties on sea ice in the Weddell Sea during spring-summer transition - Nicolaus, Marcel; Haas, Christian; Willmes, Sascha (Journal of Geophysical Research: Atmospheres, 2009)
Observations of snow properties, superimposed ice, and atmospheric heat fluxes have been performed on first-year and second-year sea ice in the western Weddell Sea, Antarctica. Snow in this region is particular as it does usually survive summer ablation. Measurements were performed during Ice Station Polarstern (ISPOL), a 5-week drift station of the German icebreaker RV Polarstern. Net heat flux to the snowpack was 8 W m−2, causing only 0.1 to 0.2 m of thinning of both snow cover types, thinner first-year and thicker second-year snow. Snow thinning was dominated by compaction and evaporation, whereas melt was of minor importance and occurred only internally at or close to the surface. Characteristic differences between snow on first-year and second-year ice were found in snow thickness, temperature, and stratigraphy. Snow on second-year ice was thicker, colder, denser, and more layered than on first-year ice. Metamorphism and ablation, and thus mass balance, were similar between both regimes, because they depend more on surface heat fluxes and less on underground properties. Ice freeboard was mostly negative, but flooding occurred mainly on first-year ice. Snow and ice interface temperature did not reach the melting point during the observation period. Nevertheless, formation of discontinuous superimposed ice was observed. Color tracer experiments suggest considerable meltwater percolation within the snow, despite below-melting temperatures of lower layers. Strong meridional gradients of snow and sea-ice properties were found in this region. They suggest similar gradients in atmospheric and oceanographic conditions and implicate their importance for melt processes and the location of the summer ice edge.
Keywords: Sørishavet; Weddellhavet; atmosfæren; havis; klimatologi; meteorologi; målinger; oseanografi; sjøis; snø; økosystemer

Movements and dive behaviour of two leopard seals (Hydrurga leptonyx) off Queen Maud Land, Antarctica - Nordøy, Erling S; Blix, Arnoldus Schytte (Polar Biology, 2009)
Keywords: Sørishavet; marin biologi; observasjoner; pattedyr; seler; sjøpattedyr

Observations on the relationship between the Antarctic coastal diatoms Thalassiosira antarctica Comber and Porosira glacialis (Grunow) Jørgensen and sea ice concentrations during the late Quaternary - Pike, Jennifer; Crosta, Xavier; Maddison, Eleanor J.; Stickley, Catherine E.; Denis, Delphine; Barbara, Loïc; Renssen, Hans (Marine Micropaleontology, 2009)
The available ecological and palaeoecological information for two sea ice-related marine diatoms (Bacillariophyceae), Thalassiosira antarctica Comber and Porosira glacialis (Grunow) Jørgensen, suggests that these two species have similar sea surface temperature (SST), sea surface salinity (SSS) and sea ice proximity preferences. From phytoplankton observations, both are described as summer or autumn bloom species, commonly found in low SST waters associated with sea ice, although rarely within the ice. Both species form resting spores (RS) as irradiance decreases, SST falls and SSS increases in response to freezing ice in autumn. Recent work analysing late Quaternary seasonally laminated diatom ooze from coastal Antarctic sites has revealed that sub-laminae dominated either by T. antarctica RS, or by P. glacialis RS, are nearly always deposited as the last sediment increment of the year, interpreted as representing autumn flux. In this study, we focus on sites from the East Antarctic margin and show that there is a spatial and temporal separation in whether T. antarctica RS or P. glacialis RS form the autumnal sub-laminae. For instance, in deglacial sediments from the Mertz Ninnis Trough (George V Coast) P. glacialis RS form the sub-laminae whereas in similar age sediments from Iceberg Alley (Mac.Robertson Shelf) T. antarctica RS dominate the autumn sub-lamina. In the Dumont d'Urville Trough (Adélie Land), mid-Holocene (Hypsithermal warm period) autumnal sub-laminae are dominated by T. antarctica RS whereas late Holocene (Neoglacial cool period) sub-laminae are dominated by P. glacialis RS. These observations from late Quaternary seasonally laminated sediments would appear to indicate that P. glacialis prefers slightly cooler ocean–climate conditions than T. antarctica. We test this relationship against two down-core Holocene quantitative diatom abundance records from Dumont d'Urville Trough and Svenner Channel (Princess Elizabeth Land) and compare the results with SST and sea ice concentration results of an Antarctic and Southern Ocean Holocene climate simulation that used a coupled atmosphere–sea ice–vegation model forced with orbital parameters and greenhouse gas concentrations. We find that abundance of P. glacialis RS is favoured by higher winter and spring sea ice concentrations and that a climatically-sensitive threshold exists between the abundance of P. glacialis RS and T. antarctica RS in the sediments. An increase to >0.1 for the ratio of P. glacialis RS:T. antarctica RS indicates a change to increased winter sea ice concentration (to >80% concentration), cooler spring seasons with increased sea ice, slightly warmer autumn seasons with less sea ice and a change from ~7.5months annual sea ice cover at a site to much greater than 7.5months. In the East Antarctic sediment record, an increase in the ratio from <0.1 to above 0.1 occurs at the transition from the warmer Hypsithermal climate into the cooler Neoglacial climate (~4cal kyr) indicating that the ratio between these two diatoms has the potential to be used as a semi-quantitative climate proxy.
Keywords: Sørishavet; Weddellhavet; diatomeer; havis; marin biologi; mikropaleontologi; paleontologi; paleoøkologi; sjøis

Antarctic ascidians: an isolated and homogeneous fauna - Primo, Carmen; Vázquez, Elsa (Polar Research, 2009)
Several biogeographical studies have already been performed on the ascidians of the Antarctic region. However, new data obtained in the last few years have led us to a revision of the biogeography of this fauna. To examine the biogeographical structure of the Antarctic region, we divided it into 10 sectors, depending on the principal geographical features, and then applied cluster analysis and a multi-dimensional scaling ordination to a presence/absence matrix of species for each biogeographical area. Our study shows that Antarctic ascidians are a very homogeneous fauna, with a high level of endemism in the whole region (25–51% of Antarctic endemic species per sector), but with a low percentage of sector endemism (only up to 10%). This probably results from isolation arising from the Antarctic Convergence, and the vast geographical distances from adjacent regions, as well as from the relative constancy of the hydrographical conditions and the dispersal of organisms through circumpolar currents. In fact, cosmopolitan species represented only 0–7% of the total ascidian fauna in all sectors. Only the Bellingshausen Sea (low sample size), Bouvetøya (young and isolated, with an impoverished ascidian fauna) and the South Sandwich Islands (also young and isolated) are relatively separated. The insular sectors were more closely related to the South America and sub- Antarctic regions than the continental ones, showing a latitudinal gradient.
Keywords: Sørishavet; biogeografi; fauna; sekkdyr; zoogeografi

Impacts of the Oceans on Climate Change - Reid, Philip C; Fischer, Astrid C; Lewis-Brown, Emily; Meredith, Michael P; Sparrow, Mike; Andersson, Andreas J; Antia, Avan; Bates, Nicholas R; Bathmann, Ulrich; Beaugrand, Gregory; Brix, Holger; Dye, Stephen; et al. (Advances in Marine Biology, 2009)
The oceans play a key role in climate regulation especially in part buffering (neutralising) the effects of increasing levels of greenhouse gases in the atmosphere and rising global temperatures. This chapter examines how the regulatory processes performed by the oceans alter as a response to climate change and assesses the extent to which positive feedbacks from the ocean may exacerbate climate change. There is clear evidence for rapid change in the oceans. As the main heat store for the world there has been an accelerating change in sea temperatures over the last few decades, which has contributed to rising sea‐level. The oceans are also the main store of carbon dioxide (CO2), and are estimated to have taken up ∼40% of anthropogenic-sourced CO2 from the atmosphere since the beginning of the industrial revolution. A proportion of the carbon uptake is exported via the four ocean ‘carbon pumps’ (Solubility, Biological, Continental Shelf and Carbonate Counter) to the deep ocean reservoir. Increases in sea temperature and changing planktonic systems and ocean currents may lead to a reduction in the uptake of CO2 by the ocean; some evidence suggests a suppression of parts of the marine carbon sink is already underway. While the oceans have buffered climate change through the uptake of CO2 produced by fossil fuel burning this has already had an impact on ocean chemistry through ocean acidification and will continue to do so. Feedbacks to climate change from acidification may result from expected impacts on marine organisms (especially corals and calcareous plankton), ecosystems and biogeochemical cycles. The polar regions of the world are showing the most rapid responses to climate change. As a result of a strong ice–ocean influence, small changes in temperature, salinity and ice cover may trigger large and sudden changes in regional climate with potential downstream feedbacks to the climate of the rest of the world. A warming Arctic Ocean may lead to further releases of the potent greenhouse gas methane from hydrates and permafrost. The Southern Ocean plays a critical role in driving, modifying and regulating global climate change via the carbon cycle and through its impact on adjacent Antarctica. The Antarctic Peninsula has shown some of the most rapid rises in atmospheric and oceanic temperature in the world, with an associated retreat of the majority of glaciers. Parts of the West Antarctic ice sheet are deflating rapidly, very likely due to a change in the flux of oceanic heat to the undersides of the floating ice shelves. The final section on modelling feedbacks from the ocean to climate change identifies limitations and priorities for model development and associated observations. Considering the importance of the oceans to climate change and our limited understanding of climate-related ocean processes, our ability to measure the changes that are taking place are conspicuously inadequate. The chapter highlights the need for a comprehensive, adequately funded and globally extensive ocean observing system to be implemented and sustained as a high priority. Unless feedbacks from the oceans to climate change are adequately included in climate change models, it is possible that the mitigation actions needed to stabilise CO2 and limit temperature rise over the next century will be underestimated.
Keywords: Sørishavet; global oppvarming; havnivåstigning; klimaendringer; klimatologi

Large-scale force budget: identification of interest areas and assessment of a data set for the large drainage basin of Jutulstraumen, East Antarctica - Rolstad, Cecilie (Norsk Geografisk Tidsskrift - Norwegian Journal of Geography, 2009)
A large-scale force budget is a relatively simple but useful tool for initial investigation of ice dynamics; however, it requires an extensive data set. Identification of key measurement areas and assessment of the spatial variability of the required measurement accuracies is advantageous prior to measuring such large drainage basins. Identification of areas and assessment of data requires several steps and in the paper velocities and surface topography are modelled numerically for Jutulstraumen drainage basin, representing ~1% of the Antarctic ice sheet (124,000 km2). A preliminary large-scale force budget is calculated from the modelled results, and key areas are identified. Finally, the required measurement accuracies yielding 10% uncertainty of the estimated stresses are calculated through error propagation of the force budget equations. Based on the results it is recommended to prioritize more accurate measurements for determining the driving stresses for the entire basin, and the longitudinal stresses in the funnel area of Jutulstraumen. The required measurement accuracy varies strongly over the basin, limiting the effective use of remote sensed data for deriving stresses. Radar altimetry surface elevation data can be used on the lower half of the plateau, and InSAR velocity data on the lower parts of the plateau and down-glacier.
Keywords: Dronning Maud Land; glasiologi; modellering

Asymmetries in the moisture origin of Antarctic precipitation - Sodemann, Harald; Stohl, Andreas (Geophysical Research Letters, 2009)
The seasonality of moisture sources for precipitation in Antarctica is studied with a Lagrangian moisture source diagnostic. Moisture origin for precipitation in Antarctica has strongly asymmetric properties, which are related to the Antarctic topography, seasonal sea ice coverage, and the land/ocean contrasts in the mid-latitudes of the southern hemisphere. The highest altitudes of the East Antarctic ice shield, where major ice cores have been drilled, have mean source latitudes of 45–40°S year-round. This finding contrasts to results from previous Lagrangian studies which detected a more southerly moisture origin due to too short trajectories. Now, results from Lagrangian moisture source diagnostics are consistent with findings from general circulation models with tagged tracers. Thus, both approaches can serve as a common benchmark for the interpretation of moisture source indicators based on stable isotopes, such as deuterium excess, in Antarctic ice cores.
Keywords: Antarktis; klimatologi; meteorologi; nedbør

Variability and predictability of Antarctic krill swarm structure - Tarling, Geraint A.; Klevjer, Thor; Fielding, Sophie; Watkins, Jon; Atkinson, Angus; Murphy, Eugene; Korb, Rebecca; Whitehouse, Mick; Leaper, Russell (Deep Sea Research Part I: Oceanographic Research Papers, 2009)
Swarming is a fundamental part of the life of Euphausia superba, yet we still know very little about what drives the considerable variability in swarm shape, size and biomass. We examined swarms across the Scotia Sea in January and February 2003 using a Simrad EK60 (38 and 120kHz) echosounder, concurrent with net sampling. The acoustic data were analysed through applying a swarm-identification algorithm and then filtering out all non-krill targets. The area, length, height, depth, packing-concentration and inter-swarm distance of 4525 swarms was derived by this method. Hierarchical clustering revealed 2 principal swarm types, which differed in both their dimensions and packing-concentrations. Type 1 swarms were generally small (<50m long) and were not very tightly packed (<10ind.m−3), whereas type 2 swarms were an order of magnitude larger and had packing concentrations up to 10 times greater. Further sub-divisions of these types identified small and standard swarms within the type 1 group and large and superswarms within the type 2 group. A minor group (swarm type 3) was also found, containing swarms that were isolated (>100km away from the next swarm). The distribution of swarm types over the survey grid was examined with respect to a number of potential explanatory variables describing both the environment and the internal-state of krill (namely maturity, body length, body condition). Most variables were spatially averaged over scales of ∼100km and so mainly had a mesoscale perspective. The exception was the level of light (photosynthetically active radiation (PAR)) for which measurements were specific to each swarm. A binary logistic model was constructed from four variables found to have significant explanatory power (P<0.05): surface fluorescence, PAR, krill maturity and krill body length. Larger (type 2) swarms were more commonly found during nighttime or when it was overcast during the day, when surface fluorescence was low, and when the krill were small and immature. A strong pattern of diel vertical migration was not observed although the larger and denser swarms tended to occur more often at night than during the day. The vast majority of krill were contained within a minor fraction of the total number of swarms. These krill-rich swarms were more common in areas dominated by small and immature krill. We propose that, at the mesoscale level, the structure of swarms switches from being predominantly large and tightly packed to smaller and more diffuse as krill grow and mature. This pattern is further modulated according to feeding conditions and then level of light.
Keywords: Scotiahavet; Sørishavet; ekkolodd; krill; marin biologi; marine økosystemer; plankton

Contrasting climate change in the two polar regions - Turner, John; Overland, Jim (Polar Research, 2009)
The two polar regions have experienced remarkably different climatic changes in recent decades. The Arctic has seen a marked reduction in sea-ice extent throughout the year, with a peak during the autumn. A new record minimum extent occurred in 2007, which was 40% below the long-term climatological mean. In contrast, the extent of Antarctic sea ice has increased, with the greatest growth being in the autumn. There has been a large-scale warming across much of the Arctic, with a resultant loss of permafrost and a reduction in snow cover. The bulk of the Antarctic has experienced little change in surface temperature over the last 50 years, although a slight cooling has been evident around the coast of East Antarctica since about 1980, and recent research has pointed to a warming across West Antarctica. The exception is the Antarctic Peninsula, where there has been a winter (summer) season warming on the western (eastern) side. Many of the different changes observed between the two polar regions can be attributed to topographic factors and land/sea distribution. The location of the Arctic Ocean at high latitude, with the consequently high level of solar radiation received in summer, allows the icealbedo feedback mechanism to operate effectively. The Antarctic ozone hole has had a profound effect on the circulations of the high latitude ocean and atmosphere, isolating the continent and increasing the westerly winds over the Southern Ocean, especially during the summer and winter.
Keywords: Antarktis; Sørishavet; havis; klimaendringer; klimatologi; ozonhull; ozonlaget; polarområdene; sjøis

Pleomorphism in the Antarctic flagellate Pyramimonas gelidicola (Prasinophyceae, Chlorophyta) - van den Hoff, John; Ferris, John M (Polar Research, 2009)
Species of the genus Pyramimonas (Prasinophyceae) are a common, widespread, but minor component of the Antarctic marine phytoplankton. They are often associated with the seasonal sea-ice environment. Pyramimonas gelidicola (McFadden, Moestrup & Wetherbee, 1982) was isolated from the water column of a saline Antarctic lake, and observations on the organism’s life history as it grew in unialgal cultures were made. The alga proved to be pleomorphic: capable of producing several morphologically distinct life stages. We recorded motile single-celled quadriflagellates that formed two statistically distinct size classes, a rare uniflagellate cell-type, and aggregations of quadriflagellate cells, multilobed forms and an encystment stage. Multilobed forms and cell aggregations, never before observed in an Antarctic Pyramimonas species, are presumed to be growth medium-induced morphotypes. Multilobed forms contained an equal number of nuclei and lobes, suggesting that they are the product of asexual reproduction. Some of the morphotypes we report here may never be observed under natural field conditions, but the potential for this alga to alternate between morphotypes is clearly demonstrated.
Keywords: Sørishavet; alger; fytoplankton; marin biologi

Two decades of geological mapping and research in Heimefrontfjella, Dronning Maud Land, Antarctica - Weber, Klaus; Jacobs, Joachim (Polarforschung, 2009)
Heimefrontfjella is a strongly segmented NE–SW trending mountain range some 130 km long with a maximum width of about 30 km. The range takes the form of a prominent escarpment, which rises more than 1000 m above the ice plains to the northwest. The maximum elevation reaches 2700 m above sea level. Since its discovery during the German Antarctic Expedition 1938/39, very few scientists had visited Heimefrontfjella by 1985. During the mid 1960s two British geologists had visited the Heimefrontfjella and provided a geological overview of the area. Thereafter, detailed geological investigations became possible with the establishment of the Georg von Neumayer Station on the Ekström ice shelf in 1981, situated some 450 km north of Heimefrontfjella. Since then, the Georg von Neumayer Station has provided a logistical base for multidisciplinary research programs within the Atlantic sector of East Antarctica.
Publisher: Alfred-Wegener-Institut für Polar- und Meeresforschung und Deutsche Gesellschaft für Polarforschung Place: Bremerhaven, Germany ISBN: 2190-1090
Keywords: Dronning Maud Land; ekspedisjoner; geologi; kartlegging

Satellite microwave observations of the interannual variability of snowmelt on sea ice in the Southern Ocean - Willmes, Sascha; Haas, Christian; Nicolaus, Marcel; Bareiss, Jörg (Journal of Geophysical Research: Oceans, 2009)
Snowmelt processes on Antarctic sea ice are examined. We present a simple snowmelt indicator based on diurnal brightness temperature variations from microwave satellite data. The method is validated through extensive field data from the western Weddell Sea and lends itself to the investigation of interannual and spatial variations of the typical snowmelt on Antarctic sea ice. We use in-situ measurements of physical snow properties to show that despite the absence of strong melting, the summer period is distinct from all other seasons with enhanced diurnal variations of snow wetness. A microwave emission model reveals that repeated thawing and refreezing cause the typical microwave emissivity signatures that are found on perennial Antarctic sea ice during summer. The proposed melt indicator accounts for the characteristic phenomenological stages of snowmelt in the Southern Ocean and detects the onset of diurnal snow wetting. An algorithm is presented to map large-scale snowmelt onset based on satellite data from the period between 1988 and 2006. The results indicate strong meridional gradients of snowmelt onset with the Weddell, Amundsen, and Ross Seas showing earliest (beginning of October) and most frequent snowmelt. Moreover, a distinct interannual variability of melt onset dates and large areas of first-year ice where no diurnal freeze thawing occurs at the surface are determined.
Article Number: C03006
Keywords: Amundsenhavet; Rosshavet; Sørishavet; Weddellhavet; fjernmåling; havis; miljøsatellitter; oseanografi; sjøis; snøsmelting

Metabolism and biomass vertical distribution of zooplankton in the Bransfield Strait during the austral summer of 2000 - Yebra, Lidia; Hernández-León, Santiago; Almeida, Carlos; Bécognée, Pierrick (Polar Research, 2009)
The vertical distribution (0–550 m) of zooplankton biomass, and indices of respiration (electron transfer system [ETS]) and structural growth (aminoacyltRNA synthetases activity [AARS]), were studied in waters off the Antarctic Peninsula during the austral summer of 2000. The dominant species were the copepod Metridia gerlachei and the euphausiid Euphausia superba. We observed a vertical krill/copepod substitution in the water column. The zooplankton biomass in the layer at a depth of 200–500 m was of the same magnitude as the biomass in the layer at a depth of 0–200 m, indicating that biomass in the mesopelagic zone is an important fraction of the total zooplankton in Antarctic waters. The metabolic rates of the zooplankton community were sustained by less than 0.5% of the primary production in the area, suggesting that microplankton or small copepods are the main food source. Neither food availability nor predation seemed to control mesozooplankton biomass. The wide time lag between the abundance peak of the dominant copepod (M. gerlachei) and the phytoplankton bloom is suggested to be the main explanation for the low summer zooplankton biomass observed in these waters.
Keywords: Sørishavet; biomasse; fytoplankton; hydrologi; krill; metabolisme; oseanografi; zooplankton

Sedimentological, geochemical and palaeontological evidence for a neoglacial cold event during the late Holocene in the continental shelf of the northern South Shetland Islands, West Antarctica - Yoo, Kyu-Cheul; Yoon, Ho Il; Kim, Jin-Kyung; Khim, Boo-Keun (Polar Research, 2009)
Two sediment cores obtained from the continental shelf of the northern South Shetland Islands, West Antarctica, consist of: an upper unit of silty mud, bioturbated by a sluggish current, and a lower unit of well-sorted, laminated silty mud, attributed to an intensified Polar Slope Current. Geochemical and accelerator mass spectrometry 14C analyses yielded evidence for a late Holocene increase in sea-ice extent and a decrease in phytoplankton productivity, inferred from a reduction in the total organic carbon content and higher C : N ratios, at approximately 330 years B.P., corresponding to the Little Ice Age. Prior to this, the shelf experienced warmer marine conditions, with greater phytoplankton productivity, inferred from a higher organic carbon content and C : N ratios in the lower unit. The reduced abundance of Weddell Sea ice-edge bloom species (Chaetoceros resting spores, Fragilariopsis curta and Fragilariopsis cylindrus) and stratified cold-water species (Rhizosolenia antennata) in the upper unit was largely caused by the colder climate. During the cold period, the glacial restriction between the Weddell Sea and the shelf of the northern South Shetland Islands apparently hindered the influx of ice-edge bloom species from the Weddell Sea into the core site. The relative increases in the abundance of Actinocyclus actinochilus and Navicula glaciei, indigenous to the coastal zone of the South Shetland Islands, probably reflects a reduction in the dilution of native species, resulting from the diminished influx of the ice-edge species from the Weddell Sea. We also document the recent reduction of sea-ice cover in the study area in response to recent warming along the Antarctic Peninsula.
Keywords: Antarktis; Den lille istid; Vestantarktis; Weddellhavet; diatomeer; fytoplankton; geokjemi; havis; klimaendringer; klimatologi; kontinentalsokkel; marin biologi; mikropaleontologi; oseanografi; sedimenter; sedimentologi; sjøis

Self-scattering of a powerful HF radio wave on stimulated ionospheric turbulence - Zalizovski, Andriy; Kashcheyev, S B; Yampolski, Y M; Galushko, V G; Belyey, Vasyl; Isham, B; Rietveld, M T; La Hoz, C; Brekke, A; Blagoveshchenskaya, N F; Kornienko, V A (Radio Science, 2009)
An analysis is presented of high-frequency (HF) signals from the European Incoherent Scatter HF ionospheric modification transmitter received during 26–30 October 2002 at three sites, two in Europe and one in Antarctica. Two components with different characteristics (“mirror-reflected” and “scattered”) were observed in the signal spectra. The mirror-reflected component can be associated with radiation through the side lobes of the transmitting antenna thus bypassing the modified volume on its way to the receiving sites. In contrast, the scattered component was radiated through the main antenna beam and then scattered by pump-induced ionospheric irregularities above the heater. As a result, variations in the scattered component signal intensity and Doppler frequency shifts (DFS) recorded at the greatly separated sites showed a high level of correlation. It is shown that the Doppler frequency variations can be associated with variations in the plasma density and/or physical motion velocities of stimulated inhomogeneities within the volume common to all propagation paths. Analysis of Doppler frequency shifts at greatly separated sites would allow identifying the mechanism responsible for the self-scattering effect. In the case of DFSs due to motion of the pump-induced scatterers it would be also possible to reconstruct the full velocity vector of the inhomogeneities.
Keywords: Antarktis; astronomi; fysikk; ionosfæren; polarområdene

Review of Footsteps on the ice: the Antarctic diaries of Stuart D. Paine, Second Byrd Expedition, by M.L. Paine - Baughman, Timothy H (Polar Research, 2008)
If the reader is looking for another rehashing of one of the adventures of the “Heroic Era” of Antarctic exploration, or another reshaping of the same old material about the three or four explorers from that period who get all the attention, M.L. Paine’s Footsteps on the ice: the Antarctic diaries of Stuart D. Paine, Second Byrd Expedition is not the book for you. But if you are a serious Antarctic buff who wants to learn something new, and really get inside one of the early expeditions of the 20th century, Paine’s volume will be a compelling read.
Keywords: Antarktis; Richard Evelyn Byrd; Sydpolflyvningen; bokanmeldelser; dagbøker; ekspedisjoner; fly; luftfart; oppdagelsesreiser; polarflyving; turisme

Persistent organohalogen contaminant burdens in Antarctic krill (Euphausia superba) from the eastern Antarctic sector: A baseline study - Bengtson Nash, Susan M; Poulsen, Anita H.; Kawaguchi, So; Vetter, Walter; Schlabach, Martin (Science of the Total Environment, 2008)
A baseline for persistent organohalogen compound (POC) accumulation in the Antarctic keystone species, Antarctic krill (Euphausia superba) has been established for a 50° longitudinal range of the eastern Antarctic sector. Samples of adult krill, caught from 12 sites distributed between 30° and 80°E (60–70°S), were analysed for >100 organohalogen compounds including chlorinated pesticides, polychlorinated biphenyls (PCBs), polybrominated organic compounds and polychlorinated dibenzo-p-dioxins/furans (PCDD/Fs). Organochlorine pesticides dominated measured krill contaminant burdens with hexachlorobenzene (HCB) as the single most abundant compound quantified. Krill HCB concentrations were comparable to those detected at this trophic level in both the Arctic and temperate northwest Atlantic, lending support for the hypothesis that HCB will approach global equilibrium at a faster rate than other POCs. Para, para′-dichlorodiphenylethene (p,p′-DDE) was detected at notable concentrations. Measurements of DDT and its degradation products provide an important baseline for monitoring the temporal and geographical influence of renewed, DDT usage for malaria-control in affected southern hemisphere countries. In contrast to the Arctic, PCBs did not feature prominently in contaminant burdens of Antarctic krill. The major commercial polybrominated diphenyl ether (PBDE) congeners -99 and -47 were quantified at low background levels with clear concentration spikes observed at around 70°E , in the vicinity of modern, active research stations. The likelihood that local anthropogenic activities are supplementing low PBDE levels, delivered otherwise primarily via long range environmental transport, is discussed. The suspected naturally occurring brominated organic compound, 2,4,6-tribromoanisole (TBA), was a ubiquitous contaminant in all samples whereas the only PCDD/Fs quantifiable were trace levels of octachlorodibenzo-p-dioxin (OCDD) and 1,2,3,4,7,8/1,2,3,4,7,9-hexachlorodibenzofuran (HxCDF). With the aims of; i) Generating a robust and broadly applicable POC auditing platform for the scarcely studied eastern Antarctic sector; ii) Determining the compounds accumulating in Antarctic krill for further toxicity evaluation studies and iii) Establishing a baseline for Antarctic predator exposure to POCs, this study represents one of the most comprehensive reports of POC contamination of the Antarctic food web to date.
Keywords: Sørishavet; forurensning; krill; marine økosystemer; menneskelig påvirkning; miljøgifter; plankton; toksikologi

"En livbåt halvfull av vann er funnet". Forlis og ulykker i hvalfangsten på 1920-tallet - Børresen, Dag Ingemar (Norsk sjøfartsmuseum. Årbok, 2008)
Publisher: Norsk sjøfartsmuseum
Keywords: Sørishavet; hvalbåter; hvalfangere; hvalfangstindustri; hvalkokerier; isfangsten; pelagisk; sjøfolk

Southern Ocean frontal structure and sea-ice formation rates revealed by elephant seals - Charrassin, J.-B.; Hindell, M.; Rintoul, S. R.; Roquet, F.; Sokolov, S.; Biuw, M.; Costa, D.; Boehme, L.; Lovell, P.; Coleman, R.; Timmermann, R.; Meijers, A.; et al. (Proceedings of the National Academy of Sciences, 2008)
Polar regions are particularly sensitive to climate change, with the potential for significant feedbacks between ocean circulation, sea ice, and the ocean carbon cycle. However, the difficulty in obtaining in situ data means that our ability to detect and interpret change is very limited, especially in the Southern Ocean, where the ocean beneath the sea ice remains almost entirely unobserved and the rate of sea-ice formation is poorly known. Here, we show that southern elephant seals (Mirounga leonina) equipped with oceanographic sensors can measure ocean structure and water mass changes in regions and seasons rarely observed with traditional oceanographic platforms. In particular, seals provided a 30-fold increase in hydrographic profiles from the sea-ice zone, allowing the major fronts to be mapped south of 60°S and sea-ice formation rates to be inferred from changes in upper ocean salinity. Sea-ice production rates peaked in early winter (April?May) during the rapid northward expansion of the pack ice and declined by a factor of 2 to 3 between May and August, in agreement with a three-dimensional coupled ocean?sea-ice model. By measuring the high-latitude ocean during winter, elephant seals fill a ?blind spot? in our sampling coverage, enabling the establishment of a truly global ocean-observing system.
Publisher: Proceedings of the National Academy of Sciences
Keywords: Sørishavet; havis; hydrografi; klimaendringer; marin biologi; oseanografi; polarområdene; sjøelefanter; sjøis; sjøpattedyr

Cenozoic Climate History from Seismic Reflection and Drilling Studies on the Antarctic Continental Margin - Cooper, Alan K; Brancolini, Giuliano; Escutia, Carlota; Kristoffersen, Yngve; Larter, Rob; Leitchenkov, German; O'Brien, Phillip; Jokat, Wilfried (Developments in Earth and Environmental Sciences, 2008)
Keywords: Antarktis; geomorfologi; innlandsis; isbreer; kontinentalmargin; paleoseanografi; stratigrafi

Regeneration of Fe(II) during EIFeX and SOFeX - Croot, Peter L.; Bluhm, Kathrin; Schlosser, Christian; Streu, Peter; Breitbarth, Eike; Frew, Russell D.; Ardelan, Murat van (Geophysical Research Letters, 2008)
Investigations into Fe(II) cycling during two Southern Ocean mesoscale iron enrichment experiments, SOFeX and EIFeX, clearly show the importance of Fe(II) to iron speciation during these experiments. In both cases the added Fe(II) persisted significantly longer than its expected oxidation time indicating a significant Fe reduction process at work. During EIFeX diel studies showed a strong photochemically induced cycle in Fe(II) production in sunlit surface waters. Our results suggest that the photochemical cycling of iron may also be important in unfertilized waters of the Southern Ocean.
Keywords: Sørishavet; biogeokjemi; fytoplankton; marin biologi; polarområdene

Ground-based measurements of spatial and temporal variability of snow accumulation in East Antarctica - Eisen, Olaf; Frezzotti, Massimo; Genthon, Christophe; Isaksson, Elisabeth; Magand, Olivier; van den Broeke, Michiel R; Dixon, Daniel A; Ekaykin, Alexey; Holmlund, Per; Kameda, Takao; Karlöf, Lars; Kaspari, Susan; et al. (Reviews of Geophysics, 2008)
The East Antarctic Ice Sheet is the largest, highest, coldest, driest, and windiest ice sheet on Earth. Understanding of the surface mass balance (SMB) of Antarctica is necessary to determine the present state of the ice sheet, to make predictions of its potential contribution to sea level rise, and to determine its past history for paleoclimatic reconstructions. However, SMB values are poorly known because of logistic constraints in extreme polar environments, and they represent one of the biggest challenges of Antarctic science. Snow accumulation is the most important parameter for the SMB of ice sheets. SMB varies on a number of scales, from small-scale features (sastrugi) to ice-sheet-scale SMB patterns determined mainly by temperature, elevation, distance from the coast, and wind-driven processes. In situ measurements of SMB are performed at single points by stakes, ultrasonic sounders, snow pits, and firn and ice cores and laterally by continuous measurements using ground-penetrating radar. SMB for large regions can only be achieved practically by using remote sensing and/or numerical climate modeling. However, these techniques rely on ground truthing to improve the resolution and accuracy. The separation of spatial and temporal variations of SMB in transient regimes is necessary for accurate interpretation of ice core records. In this review we provide an overview of the various measurement techniques, related difficulties, and limitations of data interpretation; describe spatial characteristics of East Antarctic SMB and issues related to the spatial and temporal representativity of measurements; and provide recommendations on how to perform in situ measurements.
Keywords: Antarktis; akkumulasjon; fjernmåling; glasiologi; havnivåstigning; innlandsis; paleoklimatologi; snø

Apatite single-grain (U-Th)/He data from Heimefrontfjella, East Antarctica: Indications for differential exhumation related to glacial loading? - Emmel, Benjamin; Jacobs, Joachim; Crowhurst, P; Austegard, Atle; Schwarz-Schampera, Ulrich (Tectonics, 2008)
Single-grain (U-Th)/He ages from two profiles were used to reconstruct the post-Permian tectonic-thermal history of basement rocks in Heimefrontfjella, East Antarctica. The (U-Th)/He ages from one sample collected below the late Carboniferous/Early Permian sedimentary cover rocks indicate Jurassic–Early Cretaceous basement paleotemperatures of ∼40°–60°C due to post-Permian burial. Combined apatite fission track and (U-Th)/He analyses from samples of a profile in Sivorgfjella suggest a period of flexural-related tilting after ∼87 Ma. The timing was further constrained using forward and inverse models of the (U-Th)/He data. Model results indicate a Cenozoic phase of relatively rapid cooling from ∼40°C to surface temperatures. As the driving mechanism, we propose flexural isostatic rebound due to glacial load during the development of the intracontinental ice sheet in the hinterland of the Heimefrontfjella region.
Keywords: Antarktis; geologi; tektonikk; termokronologi

Fornybare energiløsninger i Antarktis - Gammelsæter, Marte; Finden, Per (Norges teknisk-naturvitenskapelige universitet, 2008)
Volume: M.Sc.
Keywords: Dronning Maud Land; bygninger; energi; teknologi

Fast-ice distribution in East Antarctica during 1997 and 1999 determined using RADARSAT data - Giles, A Barry; Massom, Robert A; Lytle, Victoria I (Journal of Geophysical Research: Oceans, 2008)
We present the first detailed maps of fast ice around East Antarctica (75°E–170°E), using an image correlation technique applied to RADARSAT ScanSAR images from November in 1997 and 1999. This method is based upon searching for, and distinguishing, correlated regions of the ice-covered ocean which remain stationary, in contrast to adjacent moving pack ice. Within the overlapping longitudinal range of ∼86°E–150.6°E, the total fast-ice area is 141,450 km2 in 1997 and 152,216 km2 in 1999. Calibrated radar backscatter data are also used to determine the distribution of two fast-ice classes based on their surface roughness characteristics. These are “smooth” fast ice (−25.4 dB to −13.5 dB) and “rough” fast ice (−13.5 dB to −2.5 dB). The former comprises ∼67% of the total area, with rough fast ice making up the remaining ∼33%. An estimate is made of fast-ice volume, on the basis of fast-ice type as a proxy measure of ice thickness and area. Results suggest that although fast ice forms 2–16% of the total November sea ice area for this sector of East Antarctica in 1997 and 1999 (average 8.3% across maps), it may comprise 6–57% of the total ice volume (average ∼28% across maps). Grounded icebergs play a key role in fast-ice distribution in all regions apart from 150°E–170°E. These are “snapshot” estimates only, and more work is required to determine longer-term spatiotemporal variability.
Keywords: Sørishavet; batymetri; biologi; havis; kartlegging; landfast is; satellite bilder; sjøis; økologi

From the editor: halfway through the IPY—halfway for an Antarctic traverse - Goldman, Helle V (Polar Research, 2008)
April is here and we have just passed the midpoint of the International Polar Year (IPY), which began on 1 March 2007 and will conclude on 1 March 2009. The “year” stretches over 24 months to accommodate two summer field seasons in both polar regions. The northern summer is fast approaching, and scientists who will undertake a second IPY summer season in the Arctic are making their final preparations. At the opposite end of the planet, summer is over and scientists have wrapped up the first IPY field season. Those whose projects will carry on for a second summer season will have to wait until late this year to resume work in Antarctica.
Keywords: Antarktis; Det internasjonale geofysiske år (IGY); Norsk Polarinstitutt; ekspedisjoner; forskning; polarområdene; vitenskap

Decline in energy storage in the Antarctic minke whale (Balaenoptera bonaerensis) in the Southern Ocean - Konishi, Kenji; Tamura, Tsutomu; Zenitani, Ryoko; Bando, Takeharu; Kato, Hidehiro; Walløe, Lars (Polar Biology, 2008)
The annual trend in energy storage in the Antarctic minke whale was examined using catch data from all 18 survey years in the Japanese Whale Research Program (JARPA). Regression analyses clearly showed that blubber thickness, girth and fat weight have been decreasing for nearly 2 decades. The decrease per year is estimated at approximately 0.02 cm for mid-lateral blubber thickness and 17 kg for fat weight, corresponding to 9% for both measurements over the 18-year period. Furthermore, "date", "extent of diatom adhesion", "sex", "body length", "fetus length", "latitude", "age" and "longitude" were all identified as partially independent predictors of blubber thickness. The direct interpretation of this substantial decline in energy storage in terms of food availability is difficult, since no long-term krill abundance series is available. However, an increase in the abundance of krill feeders other than minke whales and a resulting decrease in the krill population must be considered as a likely explanation.
Keywords: Sørishavet; hvaler; krill; marin biologi; plankton; vågehvaler

Crustal structure and tectonic provinces of the Riiser-Larsen Sea area (East Antarctica): results of geophysical studies - Leitchenkov, German; Guseva, J; Gandyukhin, V; Grikurov, G; Kristoffersen, Yngve; Sand, M; Golynsky, A; Aleshkova, N (Marine Geophysical Researches, 2008)
Keywords: Sørishavet; kontinentalmargin; marin geofysikk; seismologi; stratigrafi

Halo of ice deformation observed over the Maud Rise seamount - Lindsay, Ronald; Kwok, Ronald; de Steur, Laura; Meier, Walt (Geophysical Research Letters, 2008)
A distinctive halo of sea ice deformation was observed above the Maud Rise seamount in the eastern Weddell Sea in the winter of 2005. The deformation halo is coincident with a halo of low mean ice concentration that is often observed in the region. Monthly mean ice vorticity estimates for the months July through November reveal the deformation zone most clearly in an arc about 100 km northwest of the seamount where there is a strong gradient in the bathymetry at depths of 3000–5000 m. The deformation was computed from satellite-based ice motion vectors derived from Envisat Synthetic Aperture Radar backscatter images. The deformation halo is evidence of a Taylor cap circulation over the seamount, which has been described and analyzed with modeling studies and concurrent oceanographic observations obtained during an extensive field campaign.
Keywords: Sørishavet; Weddellhavet; havis; havstrømmer; hydrografi; oseanografi; sjøis; vannvirvler

The use and abuse of dogs on Scott's and Amundsen's South Pole expeditions - Murray, Carl (Polar Record, 2008)
In the century since Roald Amundsen and Robert F. Scott led the first and second expeditions to reach the South Pole, commentators have frequently passed judgement on the different means of transport that the two explorers employed. In hindsight, and since he ‘won,’ they have consistently praised Amundsen for using dogs exclusively and criticised Scott for not doing the same. Surprisingly, however, almost no attention has been given to the experience of Amundsen's dogs, whose extreme suffering seems to have vanished into a collective blind spot. Here, with the aim of restoring balance to one part of the vexed historiography of the two explorers, that record is set straight. Amundsen's troubled and contradictory attitude towards his animals is also explored and common misconceptions about Scott's views on the use of dogs for transport are confuted.
Publisher: Cambridge University Press
Keywords: Antarktis; Sydpolsekspedisjonen; oppdagelsesreiser; polarhistorie; sledehunder

Wintertime ocean conditions over the southern Weddell Sea continental shelf, Antarctica - Nicholls, Keith W; Boehme, Lars; Biuw, Martin; Fedak, Michael A (Geophysical Research Letters, 2008)
During the austral winter of 2007 a Weddell Seal tagged with a miniaturized conductivity-temperature-depth (CTD) instrument travelled over the central southern Weddell Sea continental shelf. The instrument yielded 750 CTD profiles, 250 of them to the sea floor. The data show a full depth flow of water onto the shelf via a sill at the shelf break (74°S 44°W). The warmth from the core of the flow was able to maintain the surface mixed layer above the freezing point, resulting in a band of reduced ice-production. An estimate of the on-shelf flux suggests that this flow accounts for most of the estimated 3 Sv of water draining from the southern Weddell Sea continental shelf.
Keywords: Sørishavet; Weddellhavet; kontinentalsokkel; marin zoologi; oseanografi; saltinnhold; seler; temperatur

Hilsen fra Sørishavet - Pedersen, Ronald (Berlevågingen, 2008)
Keywords: Sørishavet; forskning; krill; marinbiologi; teknologi

Comparison of contemporary and fossil diatom assemblages from the western Antarctic Peninsula shelf - Pike, Jennifer; Allen, Claire S.; Leventer, Amy; Stickley, Catherine E.; Pudsey, Carol J. (Marine Micropaleontology, 2008)
During the past ten years, the Antarctic Peninsula has been identified as the most rapidly warming region of the Southern Hemisphere and it is important to place this warming in the context of the natural climate and oceanographic variability of the recent geological past. Many biological proxies, such as marine diatom assemblages, have been used to determine Southern Ocean palaeoceanographic conditions during the Late Quaternary, however, few investigations have attempted to link observations of modern floras with the fossil record. In this study we examine a suite of modern austral spring (December 2003) and summer (February 2002) surface water samples from along the western Antarctic Peninsula (WAP) continental shelf and compare these to core-top, surface sediment samples. Using detrended correspondence analysis (DCA) and principal component analysis (PCA) of diatom abundance data we investigate the relationship of contemporary diatom floras with the fossil record. This multivariate analysis reveals that our modern assemblages can be divided into three groups: summer southern WAP sites, summer northern WAP sites, and spring WAP sites. Sea surface temperature (SST) is an important environmental variable for explaining seasonal differences in diatom assemblages between spring and summer, but sea surface salinity (SSS) is more important for understanding temporally-equivalent regional variations in assemblage. Our summer diatom samples are more reminiscent of early season assemblages, reflecting the unusually late sea ice retreat from the region that year. When the modern assemblages are compared to the fossil record, it is clear that most of the important diatoms from the summer assemblage are not preserved into the sediments, and that the fossil record more closely reflects spring assemblages. This observation is important for any future attempts to quantitatively reconstruct palaeoceanographic conditions along the WAP during the Late Quaternary and highlights the need for many more such studies in order to address longer timescales, such as interannual variability, in the context of the fossil record.
Keywords: Sørishavet; Vestantarktis; diatomeer; marin biologi; marin geologi; mikropaleontologi; paleoseanografi

Temperature effects on biodegradation of petroleum contaminants in cold soils - Rike, Anne Gunn; Schiewer, Silke; Filler, Dennis M (Bioremediation of Petroleum Hydrocarbons in Cold Regions, 2008)
Bioremediation in cold climates is frequently regarded with skepticism. Owners of polluted sites and regulatory agencies may doubt the effectiveness of biological degradation at near freezing temperatures. While it is true that biodegradation rates decrease with decreasing temperatures, this does not mean that bioremediation is inappropriate for cold regions. Microbial degradation of hydrocarbons occurs even around 0 °C (Chapter 4). In remote alpine, Arctic, and Antarctic locations, excavation and shipping of contaminated soil may be prohibitively expensive. Bioremediation may be the most cost-effective alternative. This chapter discusses microbial adaptation to cold temperatures as well as results of laboratory and field studies of bioremediation at low temperatures.Microorganisms can grow at temperatures ranging from subzero to more than 100 °C. Microbes are divided into four groups based on the range of temperature at which they can grow. The psychrophiles grows at temperatures below 20 °C, the mesophiles between 20 °C and 44 °C, the thermophiles between 45 °C and 70 °C, and the hyperthermophiles require growth temperatures above 70 °C to over 110 °C. The term “cold-adapted microorganisms” (CAMs) is frequently used for describing bacteria growing at or close to zero degrees Celsius. Depending on the cardinal temperatures (the minimal, the optimal, and the maximum growth temperature), CAMs can be classified as psychrophiles or psychrotrophs. Morita's (1975) definition, which holds that psychrophiles have a maximum growth temperature of less than 20 °C and an optimal growth temperature of less than 15 °C, while psychrotrophs have a maximum temperature of 40 °C and an optimal growth temperature higher than 15 °C, is widely accepted.
Keywords: Antarktis; biodiversitet; forurensning; polarområdene; økologi; økosystemer

Contamination, regulation, and remediation: an introduction to bioremediation of petroleum hydrocarbons in cold regions - Snape, Ian; Acomb, Larry; Barnes, David L; Bainbridge, Steve; Eno, Robert; Filler, Dennis M; Plato, Natalie; Poland, John S; Raymond, Tania C; Rayner, John L; Riddle, Martin J; Rike, Anne G; et al. (Bioremediation of Petroleum Hydrocarbons in Cold Regions, 2008)
Oil and fuel spills are among the most extensive and environmentally damaging pollution problems in cold regions and are recognized as potential threats to human and ecosystem health. It is generally thought that spills are more damaging in cold regions, and that ecosystem recovery is slower than in warmer climates (AMAP 1998; Det Norske Veritas 2003). Slow natural attenuation rates mean that petroleum concentrations remain high for many years, and site managers are therefore often forced to select among a range of more active remediation options, each of which involves a trade-off between cost and treatment time (Figure 11). The acceptable treatment timeline is usually dictated by financial circumstance, perceived risks, regulatory pressure, or transfer of land ownership.In situations where remediation and site closure are not urgent, natural attenuation is often considered an option. However, for many cold region sites, contaminants rapidly migrate off-site (Gore et al. 1999; Snape et al. 2006a). In seasonally frozen ground, especially in wetlands, a pulse of contamination is often released with each summer thaw (AMAP 1998; Snape et al. 2002). In these circumstances natural attenuation is likely not a satisfactory option. Simply excavating contaminants and removing them for off-site treatment may not be viable either, because the costs are often prohibitive and the environmental consequences of bulk extraction can equal or exceed the damage caused by the initial spill (Filler et al. 2006; Riser-Roberts 1998).
Keywords: Antarktis; biodiversitet; forurensning; polarområdene; økologi; økosystemer

The Cosmonaut Sea Wedge - Solli, Kenneth; Kuvaas, Berit; Kristoffersen, Yngve; Leitchenkov, German; Guseva, J; Gandyukhin, V (Marine Geophysical Researches, 2008)
Keywords: Sørishavet; kontinentalmargin; marin geofysikk; sedimenter

Blocking primers to enhance PCR amplification of rare sequences in mixed samples – a case study on prey DNA in Antarctic krill stomachs - Vestheim, Hege; Jarman, Simon N. (Frontiers in Zoology, 2008)
Identification of DNA sequence diversity is a powerful means for assessing the species present in environmental samples. The most common molecular strategies for estimating taxonomic composition depend upon PCR with universal primers that amplify an orthologous DNA region from a range of species. The diversity of sequences within a sample that can be detected by universal primers is often compromised by high concentrations of some DNA templates. If the DNA within the sample contains a small number of sequences in relatively high concentrations, then less concentrated sequences are often not amplified because the PCR favours the dominant DNA types. This is a particular problem in molecular diet studies, where predator DNA is often present in great excess of food-derived DNA.
Keywords: Scotiahavet; Sørishavet; genetikk; genetisk analyse; krill; marin biologi; plankton; taksonomi

Evaluation of AMSR-E snow depth product over East Antarctic sea ice using in situ measurements and aerial photography - Worby, Anthony P; Markus, Thorsten; Steer, Adam D; Lytle, Victoria I; Massom, Robert A (Journal of Geophysical Research: Oceans, 2008)
The Antarctic Remote Ice Sensing Experiment (ARISE) was conducted in the East Antarctic sea ice zone during September–October 2003. A key objective of this program was the acquisition of in situ measurements suitable for evaluating the EOS Aqua Advanced Microwave Scanning Radiometer (AMSR-E) snow depth product. A strategy is presented for comparing snow thickness measurements over spatial scales ranging from point measurements to satellite pixels. In situ measurements of snow thickness were taken across eight Lagrangian grid cells defined and tracked using an array of drifting buoys. These data are coupled with ice-type analyses from digital aerial photographs to calculate area-averaged snow thicknesses that are compared with the AMSR-E derived snow thickness product. The results show considerable underestimates of the AMSR-E snow depths for rough sea ice by a factor of 2.3. We investigate the impact of underlying sea ice roughness on snow depth retrievals and conclude that in situ measurements of snow thickness underrepresent snow depth over rough ice, which is then not adequately accounted for in the development of the algorithm coefficients.

Liksomoppdagerne i Antarktis - Aasheim, Stein P (Snø & ski: årbok, 2007)
Keywords: Sørishavet; ekspedisjoner

Growth rate and its variability in erect Antarctic bryozoans - Barnes, David K. A.; Webb, Karen E.; Linse, Katrin (Polar Biology, 2007)
Climate is altering rapidly in parts of the Arctic and Antarctic but we know little about how marine organisms are responding to, or might respond to such changes. Knowledge of within-taxon variability is the vital context (currently missing) to interpretation of environmental signals. We investigated growth in six species and three genera of erect Antarctic bryozoans, an ideal model taxon to investigate such response. Cellarinella margueritae, C. nodulata, C. rogickae, C. watersi, Melicerita obliqua and Stomhypselosaria watersi, extended 3.4, 5.2, 4.6, 4.1, 4.9 and 4.5 mm year(-1) and synthesised 24, 55, 45, 176, 34 and 46 mg CaCO3 year(-1), respectively. The maximum ages of these species ranged from 11 to 15 years except M. obliqua, which reached 32 years. This is the first investigation of growth rates of closely related Antarctic invertebrate species and reports the slowest growth rates of bryozoans known from anywhere to date. Our data coupled with that from literature shows that Antarctic bryozoan growth varies << 10(1) between species, 10(1) between genera, 10(2) between morphologies and is similar to 10(1) slower than in tropical or temperate regions. However, within encrusting types the slowest growing species grow at similar rates from poles to tropics. Age was a strong confounding factor across our Antarctic study species but age-standardised data showed a possible decline in annual growth from 1992 to 2003. We identify several factors increasing this environmental signal strength, including (1) the importance of generic (though not necessarily species) identification and (2) use of dry-mass or ash-free dry-mass as the measures of growth.
Keywords: Sørishavet; bryozoa; klimaendringer; marin biologi; mosdyr

De første skiturene i Antarktis - Barr, Susan (Snø & ski: årbok, 2007)
Keywords: Antarktis; ekspedisjoner; historie; logistikk

Variations in behavior and condition of a Southern Ocean top predator in relation to in situ oceanographic conditions - Biuw, Martin; Boehme, L.; Guinet, C.; Hindell, M.; Costa, D.; Charrassin, J.-B.; Roquet, F.; Bailleul, F.; Meredith, M.; Thorpe, S.; Tremblay, Y.; McDonald, B.; et al. (Proceedings of the National Academy of Sciences, 2007)
Responses by marine top predators to environmental variability have previously been almost impossible to observe directly. By using animal-mounted instruments simultaneously recording movements, diving behavior, and in situ oceanographic properties, we studied the behavioral and physiological responses of southern elephant seals to spatial environmental variability throughout their circumpolar range. Improved body condition of seals in the Atlantic sector was associated with Circumpolar Deep Water upwelling regions within the Antarctic Circumpolar Current, whereas High-Salinity Shelf Waters or temperature/salinity gradients under winter pack ice were important in the Indian and Pacific sectors. Energetic consequences of these variations could help explain recently observed population trends, showing the usefulness of this approach in examining the sensitivity of top predators to global and regional-scale climate variability.
Publisher: Proceedings of the National Academy of Sciences
Keywords: Sørishavet; marin biologi; oseanografi; sjøelefanter

Ross seal (Ommatophoca rossii) annual distribution, diving behaviour, breeding and moulting, off Queen Maud Land, Antarctica - Blix, Arnoldus Schytte; Nordøy, Erling S. (Polar Biology, 2007)
Six out of ten adult Ross seals that were tagged with Argos satellite-linked dive recorders off Queen Maud Land, just after the moult in February, provided data on location and diving activity throughout a year. Shortly after tagging, the animals headed 2,000 km north and stayed pelagic in the area south of the Antarctic Polar Front, until October when they went south into the pack-ice. Throughout the year they made about 100 dives a day, most to a depth of 100–300 m, the deepest dive on record being 792 m, while some dives were very shallow during their stay in the pack-ice. Most dives, outside the breeding and moulting period, lasted for 5–15 min throughout the year. This diving behaviour is consistent with feeding on mid-water fish, like Pleurogramma antarcticum, squid, and to some extent krill (Euphausia superba), when in the pack-ice, and myctophid fish and several species of squid, when in the open ocean. The nursing period was 13 days in mid-November, and moulting occurs in late January–early February, which is the period when sightings surveys for this species should be done.
Keywords: Sørishavet; marin biologi; pinnipedier; satellittsendere; seler; telemetri; zoologi

Norway and past International Polar Years—a historical account - Bones, Stian (Polar Research, 2007)
Surveying Norway’s role in past International Polar Years (IPYs), this essay by historian Stian Bones contributes to a broader understanding of Norway as a “polar nation”. He describes the strengths of Norway’s scientific traditions in the polar regions, and examines the varying motivations driving Norwegian involvement in the first three IPYs: 1882–83, 1932–33 and 1957–58 (also known as the International Geophysical Year).
Keywords: Antarktis; Det internasjonale geofysiske år (IGY); Norge; historie; polarområdene; vitenskap

Reproductive performance and organochlorine pollutants in an Antarctic marine top predator: The south polar skua - Bustnes, Jan O; Tveraa, Torkild; Varpe, Øystein; Henden, John A; Skaare, Janneche U (Environment International, 2007)
Keywords: Dronning Maud Land; forurensning; miljø; ornitologi; polarområdene; reproduksjon; økologi

Fra selfangstskuter til vitenskapelige ekspedisjonsskip. Svend Foyn og ishavsekspansjonen fra Sør-Norge - Christensen, Olav (Norsk sjøfartsmuseum. Årbok, 2007)
Publisher: Norsk sjøfartsmuseum Place: Oslo
Keywords: Carl Anton Larsen; Nordmenn; Sørishavet; Vestfold; ekspedisjoner; fangst; hvalfangere; hvalfangst; oppdagelsesreiser; polarområdene; vitenskap

National and institutional productivity and collaboration in Antarctic science: an analysis of 25 years of journal publications (1980–2004) - Dastidar, Prabir G. (Polar Research, 2007)
Journal publications on Antarctic science were analysed for a period of 25 years (1980–2004) through a set of scientometrics and network analysis techniques. The study is based on 10 942 records (research articles, review articles, letters, etc.) with the word fragment “antarc*” in the title published in 961 international, peer-reviewed journals and retrieved from Thomson Scientific’s Science Citation Index database. During the period under investigation, productivity increased threefold and there was a 13-fold increase in journal publications co-written by authors from different countries. The five nations with the highest output were the USA (with 26.7% of the total output), the UK (13.8%), Australia (9.7%), Germany (8.8%) and Italy (6.0%). The top five institutions in terms of journal publications were the British Antarctic Survey (972 publications), the Alfred Wegener Institute of Polar and Marine Research, Germany (475), the Australian Antarctic Division (312), the University of Tasmania, Australia (305), and the National Aeronautics and Space Administration, USA (293).
Keywords: Antarktis; dataanalyse; forskning; scientometri; tidsskriftspublikasjoner

Diversity and species distribution of polychaetes, isopods and bivalves in the Atlantic sector of the deep Southern Ocean - Ellingsen, Kari E.; Brandt, Angelika; Ebbe, Brigitte; Linse, Katrin (Polar Biology, 2007)
We examined deep-sea benthic data on polychaetes, isopods and bivalves from the Atlantic sector of the Southern Ocean. Samples were taken during the expeditions EASIZ II (1998), ANDEEP I and II (2002) (depth: 742-6,348 m). The range between sites varies from 3 to 1,900 km. Polychaetes (175 species in total) and isopods (383 species) had a high proportion of species restricted to one or two sites (72 and 70%, respectively). Bivalves (46 species) had a higher proportion of species represented at more sites. Beta diversity (Whittaker and Jaccard) was higher for polychaetes and isopods than for bivalves. The impact of depth on species richness was not consistent among groups; polychaetes showed a negative relationship to depth, isopods displayed highest richness in the middle depth range (2,000-4,000 m), whereas bivalves showed no clear relationship to depth. Species richness was not related to latitude (58-74 degrees S) or longitude (22-60 degrees W) for any group.
Keywords: Sørishavet; biodiversitet; flerbørstemarker; isopoder; marin biologi; muslinger; skjell; tanglus

Polar Research evolves, and Norway and the IPY - Goldman, Helle V (Polar Research, 2007)
Keywords: Antarktis; Det internasjonale geofysiske år (IGY); Norge; Norsk Polarinstitutt; ekspedisjoner; forskning; polarområdene; vitenskap

Observasjoner av atmosfæriske parametere ved Troll-stasjonen i Antarktis - forskning og overvåkning basert på lange tidsserier. Fase 1 (2005/06) - NFR/NARE prosjekt 168908/S30 - Hansen, Georg Heinrich; Aspmo, Katrine; Berg, Torunn; Edvardsen, Kåre; Fiebig, Markus; Kallenborn, Roland; Lunder, Chris Rene; Nilsen, Tore; Schmidbauer, Norbert; Solberg, Sverre; Stebel, Kerstin; Wasseng, Jan; et al. (NILU, 2007)
Fra årsskifte 2006/2007 har den norske Antarktisstasjonen Troll (72º S, 2º E, 1270 m.o.h.) i Dronning-Maud-Land vært en helårsbemannet forsknings-, overvåkings- og servicestasjon. Dette åpnet for muligheten til å gjennomføre kontinuerlige målinger av en rekke viktige atmosfæriske parametre. I februar 2007 ble den nye NILU-atmosfære målestasjonen på Troll satt i gang. Måleprogrammet omfatter optiske, fysiske og kjemiske egenskaper av aerosoler, totalozon og UV-stråling, uorganisk og organisk forurensning inkludert tungmetaller som kvikksølv, samt meteorologiske parametre. Programmet omfatter også oppbyggingen av et luftflaskearkiv. Etter de første 6 månedene med den første Antarktisvinteren ser alle instrumenter ut til å være i meget god tilstand og levererkontinuerlig nye data. Disse analyseres for tiden, og de første resultatene vil bli publisert tidlig i 2008. Måleprogrammet finansieres i all hovedsak gjennom forskningsprogrammet NARE (Norwegian Antarctic Research Expeditions) ved Norsk polarinstitutt.
Publication Title: NILU Technical reports Volume: TR, 07/2007 Issue: NILU:105055
Keywords: Dronning Maud Land; Troll forskningsstasjon; miljøovervåking; målinger

Changes at Peter I Øy - Headland, Robert K (Polar Research, 2007)
Peter I Øy, a remote Norwegian territory, is one of the most rarely visited of the peri-Antarctic islands. Since the last Norwegian research visit, in 1987, approximately 10 tourist ships have been to the island, and about half of these have made landings. Where practical, reports have been sent to the Norwegian Polar Institute and other interested parties. I have made five visits, landing during four of them, while employed by Quark Expeditions to lecture on Antarctic history and geography aboard Kapitan Khlebnikov . My most recent visit, on 21 November 2006, demonstrated the continual geological erosion of the coast. In 2004 at Pingvinholet there was a splendid triple natural arch: the outer arch was formed by black basaltic deposits, and the inner one was capped by a stratum of red oxidized larva. The third arch was the result of a basalt flake slipping and propping itself against the middle column. The sea penetrated through all three arches so that it would have been possible, although reckless, to take a small boat through the largest of them. In late 2006, while sailing from South America to New Zealand near the Antarctic coast, I noted the entire inner section had collapsed. Only one large arch now remains and this no longer admits the sea. The collapse of both the cap of red larva and supporting pillar has formed a pile of rubble several metres above the sea.
Keywords: Peter I. Øy; geologi; turisme

Marine-sedimentary geology - Kuhn, Gerhard; Hillenbrand, Claus-Dieter; Hass, Christian; Lensch, Norbert; Forwick, Matthias; Daniel, Kristin; Kober, Martin; Krüger, Stefan; Petitat, Manuel; Veit, Andreas (The Expedition ANT-XXIII/4 of the Research Vessel Polarstern in 2006, 2007)
Dynamic behaviour of the West Antarctic ice sheet in the Amundsen Sea Embayment during the later quaternary climatic cycles, pliocene to quaternary palaeoceanography in the Southwest Pacific, and holocene climate history of Maxwell Bay, King George Island.
Keywords: Sørishavet; havnivåstigning; innlandsis; klimaendringer; marin geologi; oseanografi

De fire store : og hvordan de ledet sine menn - Kvam, Ragnar (Gyldendal, 2007)
De satte seg nesten uvirkelige mål. De skulle erobre de siste uoppdagede steder på kloden. Kan deres egenskaper og lederstil fortelle oss hvorfor noen lyktes bedre enn andre? Nansen var først ute. Skituren over Grønland hadde gitt ham ukuelig vågemot: Nå var målet Nordpolen. Siden ville Amundsen samme vei. Britene festet blikket på Antarktis. Først Schackleton, så Scott. Fire menn med store drømmer, sterk vilje, kraftig ego. Som vi vet, skulle ekspedisjonene føre til triumf . og tragedie. I sin nye bok skildrer Ragnar Kvam jr. noen av polarhistoriens mest dramatiske kapitler. Han setter søkelyset på hvem de er, disse fire lederskikkelsene. Hva var det som drev dem? Hvordan ledet de sine menn? Kan deres egenskaper og lederstil fortelle oss hvorfor noen lyktes bedre enn andre? Gjennom fire fortellinger får leseren et fascinerende portrett av "de fire store", av deres evne til å skape motivasjon og lagånd, av deres psykiske utrustning og evne til å takle ekstreme situasjoner. Kvams mål er å kaste nytt lys over det som i siste instans virkelig bestemmer deres måte å lede på deres personlighet.
Keywords: Antarktis; Roald Amundsen; Sydpolsekspedisjonen; biografier; polarekspedisjoner; polarhistorie

Modulation of the bipolar seesaw in the Southeast Pacific during Termination 1 - Lamy, Frank; Kaiser, Jérôme; Arz, Helge W; Hebbeln, Dierk; Ninnemann, Ulysses; Timm, Oliver; Timmermann, Axel; Toggweiler, J R (Earth and Planetary Science Letters, 2007)
The termination of the last ice age (Termination 1; T1) is crucial for our understanding of global climate change and for the validation of climate models. There are still a number of open questions regarding for example the exact timing and the mechanisms involved in the initiation of deglaciation and the subsequent interhemispheric pattern of the warming. Our study is based on a well-dated and high-resolution alkenone-based sea surface temperature (SST) record from the SE-Pacific off southern Chile (Ocean Drilling Project Site 1233) showing that deglacial warming at the northern margin of the Antarctic Circumpolar Current system (ACC) began shortly after 19,000 years BP (19 kyr BP). The timing is largely consistent with Antarctic ice-core records but the initial warming in the SE-Pacific is more abrupt suggesting a direct and immediate response to the slowdown of the Atlantic thermohaline circulation through the bipolar seesaw mechanism. This response requires a rapid transfer of the Atlantic signal to the SE-Pacific without involving the thermal inertia of the Southern Ocean that may contribute to the substantially more gradual deglacial temperature rise seen in Antarctic ice-cores. A very plausible mechanism for this rapid transfer is a seesaw-induced change of the coupled ocean–atmosphere system of the ACC and the southern westerly wind belt. In addition, modelling results suggest that insolation changes and the deglacial CO2 rise induced a substantial SST increase at our site location but with a gradual warming structure. The similarity of the two-step rise in our proxy SSTs and CO2 over T1 strongly demands for a forcing mechanism influencing both, temperature and CO2. As SSTs at our coring site are particularly sensitive to latitudinal shifts of the ACC/southern westerly wind belt system, we conclude that such latitudinal shifts may substantially affect the upwelling of deepwater masses in the Southern Ocean and thus the release of CO2 to the atmosphere as suggested by the conceptual model of [Toggweiler, J.R., Rusell, J.L., Carson, S.R., 2006. Midlatitude westerlies, atmospheric CO2, and climate change during ice ages. Paleoceanography 21. doi:10.1029/2005PA001154].
Keywords: Sørishavet; Sørishavsstrømmen; havstrømmer; oseanografi; paleoklimatologi

The Norwegian-British-Swedish Expedition (NBSX) to Antarctica 1949-52 - science and security - Lewander, Lisbeth (Berichte zur Polar- und Meeresforschung = Reports on Polar and Marine Research, 2007)
The most frequent way of summarizing the story of the NBSX may be illustrated by the following few paragraphs. Shortly after the Second World War had ended Norway took a leading role in organising the first international expedition to Antarctica. Norway was in charge of meteorology and surveying, Great Britain was responsible for geology and Sweden was entrusted with glaciology. The British RAF assisted in air operations 1949/50 with five officers (in finding a landing place for the expedition as well as for meteorological investigations, one officer remained as radio operator), the Norwegian Wideröe Company assisted in 1950/51 (air surveying) and the Swedish Air Force in 1951/52, with 6 officers (originally for reconnaissance of ice conditions as well as being prepared for emptying the base). The Norwegian sealer Norsel landed the party and the whaler Thorshövdi assisted as well for transport of dogs aircraft and weasels. For general overviews and details of the scientific achievements, logistics and perspectives of international cooperation there are several works available.
Publisher: Alfred-Wegener-Institut für Polar- und Meeresforschung Place: Bremerhaven
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon

Kap. 4. Is og snø smelter. Kap. 5. Øyer og lavland kan drukne - Mathismoen, Ole; Ulvestad, Knut Ola (bildered.); Lie, Maya (bildered.) (Klima : hva skjer?, 2007)
Keywords: Antarktis; Sørishavet; drivhuseffekten; global oppvarming; havnivåstigning; klimaendringer

Polaroppdraget - Paulsen, Øystein S (Forsvarets forum, 2007)
Keywords: Dronning Maud Land; ekspedisjoner; fly; logistikk

A new surface accumulation map for western Dronning Maud Land, Antarctica, from interpolation of point measurements - Rotschky, Gerit; Holmlund, Per; Isaksson, Elisabeth; Mulvaney, Robert; Oerter, Hans; Van Den Broeke, Michiel R; Winther, Jan-Gunnar (Journal of Glaciology, 2007)
As a result of intensive field activities carried out by several nations over the past 15 years, a set of accumulation measurements for western Dronning Maud Land, Antarctica, was collected, based on firn-core drilling and snow-pit sampling. This new information was supplemented by earlier data taken from the literature, resulting in 111 accumulation values. Using Geographical Information Systems software, a first region-wide mean annual snow-accumulation field was derived. In order to define suitable interpolation criteria, the accumulation records were analyzed with respect to their spatial autocorrelation and statistical properties. The resulting accumulation pattern resembles well- known characteristics such as a relatively wet coastal area with a sharp transition to the dry interior, but also reveals complex topographic effects. Furthermore, this work identifies new high-return shallowdrilling sites by uncovering areas of insufficient sampling density.
Publisher: Cambridge University Press
Keywords: Dronning Maud Land; glasiologi

Til Antarktis for å simulere fremtiden - Sirevaag, Anders (AKA : tverrfaglig studentlektyre, 2007)
Publisher: Studentene ved Universitetet i Bergen Place: Bergen
Keywords: Antarktis; klimaendringer; populærvitenskap

A seismo-stratigraphic analysis of glaciomarine deposits in the eastern Riiser-Larsen Sea (Antarctica) - Solli, Kenneth; Kuvaas, Berit; Kristoffersen, Yngve; Leitchenkov, German; Guseva, J; Gandjukhin, V (Marine Geophysical Researches, 2007)
Keywords: Sørishavet; innlandsis; kontinentalsokkel; seismologi; stratigrafi

Seismic morphology and distribution of inferred glaciomarine deposits along the East Antarctic continental margin, 20°E–60°E - Solli, Kenneth; Kuvaas, Berit; Kristoffersen, Yngve; Leitchenkov, German; Guseva, J; Gandjukhin, V (Marine Geology, 2007)
Keywords: Antarktis; innlandsis; isstrøm; kontinentalstiging; marin geologi; morfologi; sedimentologi; seismologi

Quantitative analysis of soft-bottom molluscs in the Bellingshausen Sea and around Peter I Island - Troncoso, Jesús S; Aldea, Cristian; Arnaud, Patrick; Ramos, Ana; García, Francisco (Polar Research, 2007)
Macrobenthic soft-bottom molluscs were sampled in 30 stations located in the Bellingshausen Sea at depths ranging from 90 to 3304 m. The samples were collected using a quantitative grab box-corer during the cruises BENTART 03, from 24 January to 3 March 2003, and BENTART 06, from 2 January to 16 February 2006. Molluscs represent 1074 specimens belonging to 62 species of Polyplacophora, Gastropoda, Bivalvia and Scaphopoda. The bivalve Cyamiocardium denticulatum was the most abundant species (448 specimens). The abundance per station varied between 1 and 446 specimens. The Shannon–Wiener diversity index ranged between one specimen and 2.36, the Pielou evenness index ranged between 0.00 and 1 and species richness ranged from 1 to 14 species. Diversity showed great variations at different stations. After multivariate analysis (cluster analysis and nonmetrical multidimensional scaling) based on Bray–Curtis similarities, we were able to separate two principal clusters. The first cluster groups together species from shallower bottoms near Peter I Island and the Antarctic Peninsula, and the second cluster groups together species from deeper bottoms in the Bellingshausen Sea. The combination of environmental variables with the highest correlations with faunistic data was that of depth and coarse sand at the surface.
Keywords: Peter I. Øy; Sørishavet; bløtdyr; marin biologi; marine økosystemer; mollusker; oseanografi

Crustacea in Arctic and Antarctic Sea Ice: Distribution, Diet and Life History Strategies - Arndt, Carolin E.; Swadling, Kerrie M. (Advances in Marine Biology, 2006)
This review concerns crustaceans that associate with sea ice. Particular emphasis is placed on comparing and contrasting the Arctic and Antarctic sea ice habitats, and the subsequent influence of these environments on the life history strategies of the crustacean fauna. Sea ice is the dominant feature of both polar marine ecosystems, playing a central role in physical processes and providing an essential habitat for organisms ranging in size from viruses to whales. Similarities between the Arctic and Antarctic marine ecosystems include variable cover of sea ice over an annual cycle, a light regimen that can extend from months of total darkness to months of continuous light and a pronounced seasonality in primary production. Although there are many similarities, there are also major differences between the two regions: The Antarctic experiences greater seasonal change in its sea ice extent, much of the ice is over very deep water and more than 80% breaks out each year. In contrast, Arctic sea ice often covers comparatively shallow water, doubles in its extent on an annual cycle and the ice may persist for several decades. Crustaceans, particularly copepods and amphipods, are abundant in the sea ice zone at both poles, either living within the brine channel system of the ice‐crystal matrix or inhabiting the ice–water interface. Many species associate with ice for only a part of their life cycle, while others appear entirely dependent upon it for reproduction and development. Although similarities exist between the two faunas, many differences are emerging. Most notable are the much higher abundance and biomass of Antarctic copepods, the dominance of the Antarctic sea ice copepod fauna by calanoids, the high euphausiid biomass in Southern Ocean waters and the lack of any species that appear fully dependent on the ice. In the Arctic, the ice‐associated fauna is dominated by amphipods. Calanoid copepods are not tightly associated with the ice, while harpacticoids and cyclopoids are abundant. Euphausiids are nearly absent from the high Arctic. Life history strategies are variable, although reproductive cycles and life spans are generally longer than those for temperate congeners. Species at both poles tend to be opportunistic feeders and periods of diapause or other reductions in metabolic expenditure are not uncommon.
Keywords: Sørishavet; copepoder; crustacea; havis; krill; marin biologi; plankton; polarområdene; sjøis

Perspectives on the Economic History of the Antarctic Region - Basberg, Bjørn L (Discussion paper Norges handelshøyskole, Institutt for samfunnsøkonomi, 2006)
Keywords: Antarktis; ekspedisjoner; fiskeindustri; forskning; hvalfangst; ressurser; turisme; økonomi; økonomisk historie

The biodiversity of the deep Southern Ocean benthos - Brandt, A; De Broyer, C; De Mesel, I; Ellingsen, K.E; Gooday, A.J; Hilbig, B; Linse, K; Thomson, M.R.A; Tyler, P.A (Philosophical Transactions of the Royal Society B: Biological Sciences, 2006)
Our knowledge of the biodiversity of the Southern Ocean (SO) deep benthos is scarce. In this review, we describe the general biodiversity patterns of meio-, macro- and megafaunal taxa, based on historical and recent expeditions, and against the background of the geological events and phylogenetic relationships that have influenced the biodiversity and evolution of the investigated taxa. The relationship of the fauna to environmental parameters, such as water depth, sediment type, food availability and carbonate solubility, as well as species interrelationships, probably have shaped present-day biodiversity patterns as much as evolution. However, different taxa exhibit different large-scale biodiversity and biogeographic patterns. Moreover, there is rarely any clear relationship of biodiversity pattern with depth, latitude or environmental parameters, such as sediment composition or grain size. Similarities and differences between the SO biodiversity and biodiversity of global oceans are outlined. The high percentage (often more than 90%) of new species in almost all taxa, as well as the high degree of endemism of many groups, may reflect undersampling of the area, and it is likely to decrease as more information is gathered about SO deep-sea biodiversity by future expeditions. Indeed, among certain taxa such as the Foraminifera, close links at the species level are already apparent between deep Weddell Sea faunas and those from similar depths in the North Atlantic and Arctic. With regard to the vertical zonation from the shelf edge into deep water, biodiversity patterns among some taxa in the SO might differ from those in other deep-sea areas, due to the deep Antarctic shelf and the evolution of eurybathy in many species, as well as to deep-water production that can fuel the SO deep sea with freshly produced organic matter derived not only from phytoplankton, but also from ice algae.
Publisher: Royal Society
Keywords: Sørishavet; bentos; biodiversitet; biogeografi; marin biologi

Organochlorines in Antarctic and Arctic Avian Top Predators: A Comparison between the South Polar Skua and Two Species of Northern Hemisphere Gulls - Bustnes, Jan O; Tveraa, Torkild; Henden, John A; Varpe, Øystein; Janssen, Kirstin; Skaare, Janneche U (Environmental Science & Technology, 2006)
Different organochlorine compounds (OCs) were measured in the blood of breeding south polar skuas (Catharacta maccormicki) at Svarthamaren, Dronning Maud Land (Antarctica) and compared to those in two species of northern hemisphere gulls: the Arctic glaucous gull (Larus hyperboreus) and the subarctic great black-backed gull (Larus marinus). The skuas had 8% and 29% of the ∑OC levels (45 ng/g, wet weight) of glaucous gulls (591 ng/g) and great black-backed gulls (158 ng/g), respectively. Polychlorinated biphenyls (PCBs) and p,p‘-dichlorodiphenyldichloroethylene (p,p‘-DDE) were very low in skuas compared to northern gulls, but the mean hexachlorobenzene (HCB) level was 1.7 times higher than in great black-backed gulls and one-third of the glaucous gull level. Mirex levels in skuas were among the highest reported in birds, the mean level being 3 and 26 times higher than those in glaucous gull and great black-backed gulls, respectively. In skuas, the mean levels of HCB, oxychlordane, p,p‘-DDE, and PCBs increased by about 30% during a 2-week period, and mirex increased by nearly 60%. In glacuous gulls, HCB, p,p‘-DDE, and PCBs increased by 10−20%. For HCB, mirex, and oxychlordane, only a relatively small proportion of the increase in skuas could be explained by changes in lipid pools and the levels at first sampling, compared to glaucous gulls. Thus, skuas were probably accumulating these compounds when present in Antarctica. p,p‘-DDE and PCB levels, in contrast, seemed much more stable in the skuas. Relatively high levels of mirex and HCB in south polar skuas are concerning with regard to potential adverse effects.
Publisher: American Chemical Society
Keywords: Dronning Maud Land; kjemiske analyser; ornitologi; polarområdene; sjøfugler

Haul-out pattern of itinerant male Antarctic fur seals (Arctocephalus gazella) at Laurie Island, South Orkney Islands - Carlini, Alejandro R; Daneri, Gustavo A; Casaux, Ricardo; Márquez, María E I (Polar Research, 2006)
The seasonal haul-out pattern of itinerant male Antarctic fur seals (Arctocephalus gazella) was determined by regular counts at Mossman Peninsula, Laurie Island, South Orkney Islands, from 1996 to 2005. Small numbers of animals began to arrive at the beach in late December / early January (mean date 28 December ± 15 days, n = 10). Peak numbers of animals ashore changed considerably between seasons. In 1996, 1998 and 2001, peak numbers were registered in March (6/3, 18/3 and 6/3, respectively). Numbers peaked in 1997, 1999 and 2005 at the end of January / beginning of February (26/1, 2/2 and 28/1, respectively). In 2000, 2002, 2003 and 2004 peaks were registered in the third week of February (15/2, 22/2, 14/2 and 20/2, respectively). Peaks in numbers of seals ashore also varied between years, being minimum during 2001 (2531 individuals) and maximum during 2006 (16 610 individuals). In March 1998 the coasts of Laurie Island were surveyed by navigating inflatable boats near the shoreline; 18 haul-out places were identified. The big differences in peak numbers, as well as in the dates of peak events among years, suggest that local conditions could have an effect on the numbers of animals hauled out in a given year. It may therefore be difficult to predict trends from summer censuses in non-breeding places.
Keywords: Antarktis; pelsseler; zoologi

Late Pan-African Fluid Infiltration in the Mühlig-Hofmann- and Filchnerfjella of Central Dronning Maud Land, East Antarctica - Engvik, Ane K; Elvevold, Synnøve (Antarctica: Contributions to Global Earth Sciences. Proceedings of the IX International Symposium of Antarctic Earth Sciences Potsdam, 2003, 2006)
Keywords: Dronning Maud Land; geologi; nunataker; petrografi

Hierarchical Patch Dynamics and Animal Movement Pattern - Fauchald, Per; Tveraa, Torkild (Oecologia, 2006)
In hierarchical patch systems, small-scale patches of high density are nested within large-scale patches of low density. The organization of multiple-scale hierarchical systems makes non-random strategies for dispersal and movement particularly important. Here, we apply a new method based on first-passage time on the pathway of a foraging seabird, the Antarctic petrel (Thalassoica antarctica), to quantify its foraging pattern and the spatial dynamics of its foraging areas. Our results suggest that Antarctic petrels used a nested search strategy to track a highly dynamic hierarchical patch system where small-scale patches were congregated within patches at larger scales. The birds searched for large-scale patches by traveling fast and over long distances. Once within a large-scale patch, the birds concentrated their search to find smaller scale patches. By comparing the pathway of different birds we were able to quantify the spatial scale and turnover of their foraging areas. On the largest scale we found foraging areas with a characteristic scale of about 400 km. Nested within these areas we found foraging areas with a characteristic scale of about 100 km. The large-scale areas disappeared or moved within a time frame of weeks while the nested small-scale areas disappeared or moved within days. Antarctic krill (Euphausia superba) is the dominant food item of Antarctic petrels and we suggest that our findings reflect the spatial dynamics of krill in the area.
Publisher: Springer
Keywords: Dronning Maud Land; NARE ekspedisjoner; fugler; ornitologi; petreller; satellittelemetri; zoologi

Entanglement of Antarctic fur seals at Bouvetøya, Southern Ocean - Greg Hofmeyr, G J; Bester, Marthán N; Kirkman, Steve P; Lydersen, Christian; Kovacs, Kit M (Marine Pollution Bulletin, 2006)
Keywords: Bouvetøya; forurensning; marin biologi; pelsseler; pinnipedier

Entanglement of Antarctic fur seals at Bouvetøya, Southern Ocean - Greg Hofmeyr, G.J.; Bester, Marthán N.; Kirkman, Steve P.; Lydersen, Christian; Kovacs, Kit M. (Marine Pollution Bulletin, 2006)
Entanglements of Antarctic fur seals Arctocephalus gazella were recorded during four summers from 1996 to 2002 at the subantarctic island, Bouvetøya. Rates of entanglement varied between 0.024% and 0.059%. These rates are low for a pinniped population and might be because of the geographic isolation of the haulout site. An apparent decrease in the levels of entanglement over the course of the study was likely due, at least in part, to the removal of entanglements by observers. At least two-thirds of entangling materials were generated by fishery sources. Since there is no known local source of anthropogenic marine pollution, seals become entangled either in waters distant from the island, or when materials drift into local waters. Significantly more subadults were found entangled than expected from the postulated population age class distribution.
Keywords: Bouvetøya; Sørishavet; marin biologi; marin forurensning; pelsseler; pinnipedier

Fra Stangsgate til Sørishavet - Henningsen, Rune (Broen: aasgaardstrandiana, 2006)
Keywords: Sørishavet; historie; hvalfangst

Ice core melt features in relation to Antarctic coastal climate - Kaczmarska, Marzena; Isaksson, Elisabeth; Karlöf, Lars; Brandt, Ola; Winther, Jan-Gunnar; van de Wal, Roderik S W; van den Broeke, Michiel; Johnsen, Sigfus J (Antarctic Science, 2006)
Measurement of light intensity transmission was carried out on an ice core S100 from coastal Dronning Maud Land (DML). Ice lenses were observed in digital pictures of the core and recorded as peaks in the light transmittance record. The frequency of ice layer occurrence was compared with climate proxy data (e.g. oxygen isotopes), annual accumulation rate derived from the same ice core, and available meteorological data from coastal stations in DML. The mean annual frequency of melting events remains constant for the last ∼150 years. However, fewer melting features are visible at depths corresponding to approximately 1890–1930 AD and the number of ice lenses increases again after 1930 AD. Most years during this period have negative summer temperature anomalies and positive annual accumulation anomalies. The increase in melting frequency around ∼1930 AD corresponds to the beginning of a decreasing trend in accumulation and an increasing trend in oxygen isotope record. On annual time scales, a relatively good match exists between ice layer frequencies and mean summer temperatures recorded at nearby meteorological stations (Novolazarevskaya, Sanae, Syowa and Halley) only for some years. There is a poor agreement between melt feature frequencies and oxygen isotope records on longer time scales. Melt layer frequency proved difficult to explain with standard climate data and ice core derived proxies. These results suggest a local character for the melt events and a strong influence of surface topography.
Publisher: Cambridge University Press
Keywords: Dronning Maud Land; glasiologi; klima; stratigrafi

How representative is a time series derived from a firn core? A study at a low-accumulation site on the Antarctic plateau - Karlöf, Lars; Winebrenner, Dale P; Percival, Donald B (Journal of Geophysical Research: Earth Surface, 2006)
The acquisition and interpretation of increasingly high-resolution climate data from polar ice and firn cores motivates the question: What is the finest depth or timescale on which measurements on cores arrayed over a given area correlate? We analyze dated depth series of electrical and oxygen isotope measurements from a spatial array of firn cores with 3.5–7 km spacing in Dronning Maud Land, Antarctica, each with a temporal span of approximately 200 years. We use wavelet analysis to decompose the series into components associated with changes of averages on different scales, and thus deduce which scales are dominated by environmental noise, and which may contain a common signal. We find that common signals in electrical records have timescales of approximately 1–3 years. We identify only one electrical signal which rises significantly above the background in our 200-year records, evidently corresponding to the Tambora eruption. Several smaller signals correlate in a few of pairs of cores, one of which may correspond to a known volcanic event, but the others appear to be spurious. We present a simulation-based method for testing the significance of apparent electrical signal correlations, and highlight the importance of accurate relative dating between cores. In the case of oxygen-isotope records, we find, surprisingly, no significant correlation on any scale in the records, for any of the pairs of cores. There is, however, a weak trend toward positive correlation at longer timescales (up to 16 years). Statistical theory for the relevant confidence intervals and the observed statistics of the records permit estimation of the length of a data series necessary to reliably detect a hypothetical correlation equal to that observed. For the highest correlation observed on 16-year scales, core records of about 380 years (approximately 30 m at the Dronning Maud Land site) would be necessary to establish significance.
Keywords: Dronning Maud Land; geofysikk; glasiologi; iskjerner; klimatologi; meteorologi; tidsserieanalyse

“Deckchair Explorers”: The Origin and Development of Organised Tourist Voyages to Northern and Southern Polar Regions - Kolltveit, Bård (International Journal of Maritime History, 2006)
Keywords: Antarktis; ekspedisjoner; historie; miljø; næringslivet; polarområdene; turisme

Norwegian-Japanese whaling relations in the early 20th century : a case of successful technology transfer - Mageli, Eldrid (Scandinavian Journal of History, 2006)
Publisher: Routledge
Keywords: Japan; Norge; Sørishavet; hvalindustri; pelagisk hvalfangst

Effect of critical latitude and seasonal stratification on tidal current profiles along Ronne Ice Front, Antarctica - Makinson, Keith; Schröder, Michael; Østerhus, Svein (Journal of Geophysical Research: Oceans, 2006)
Keywords: Antarktis; Weddellhavet; havstrømmer; isfront; isshelf; oseanografi; tidevannsstrømmer

Evaluation of Global Ozone Monitoring Experiment (GOME) ozone profiles from nine different algorithms - Meijer, Yasjka; Swart, Daan P; Baier, F; Bhartia, Pawan K; Bodeker, G E; Casadio, Stefano; Chance, Kelly V; Del Frate, F; Erbertseder, T; Felder, Martin D; Flynn, Lawrence E; Godin-Beekmann, Sophie; et al. (Journal of Geophysical Research: Atmospheres, 2006)
An evaluation is made of ozone profiles retrieved from measurements of the nadir-viewing Global Ozone Monitoring Experiment (GOME) instrument. Currently, four different approaches are used to retrieve ozone profile information from GOME measurements, which differ in the use of external information and a priori constraints. In total nine different algorithms will be evaluated exploiting the optimal estimation (Royal Netherlands Meteorological Institute, Rutherford Appleton Laboratory, University of Bremen, National Oceanic and Atmospheric Administration, Smithsonian Astrophysical Observatory), Phillips-Tikhonov regularization (Space Research Organization Netherlands), neural network (Center for Solar Energy and Hydrogen Research, Tor Vergata University), and data assimilation (German Aerospace Center) approaches. Analysis tools are used to interpret data sets that provide averaging kernels. In the interpretation of these data, the focus is on the vertical resolution, the indicative altitude of the retrieved value, and the fraction of a priori information. The evaluation is completed with a comparison of the results to lidar data from the Network for Detection of Stratospheric Change stations in Andoya (Norway), Observatoire Haute Provence (France), Mauna Loa (Hawaii), Lauder (New Zealand), and Dumont d'Urville (Antarctic) for the years 1997–1999. In total, the comparison involves nearly 1000 ozone profiles and allows the analysis of GOME data measured in different global regions and hence observational circumstances. The main conclusion of this paper is that unambiguous information on the ozone profile can at best be retrieved in the altitude range 15–48 km with a vertical resolution of 10 to 15 km, precision of 5–10%, and a bias up to 5% or 20% depending on the success of recalibration of the input spectra. The sensitivity of retrievals to ozone at lower altitudes varies from scheme to scheme and includes significant influence from a priori assumptions.
Keywords: Antarktis; fjernmåling; meteorologi; ozonlaget; stratosfæren

Remembering Tore Gjelsvik (1916–2006) - Orheim, Olav (Polar Research, 2006)
Tore Gjelsvik, former director of the Norwegian Polar Institute, died at the beginning of this year. He is fondly remembered by a great many people. In this piece, Olav Orheim recalls the man and his key role in Norwegian polar activities. Orheim was head of Antarctic Research at the Norwegian Polar Institute in 1972–1993 and was the institute’s director from 1993 to 2005.
Keywords: Antarktis; Norsk Polarinstitutt; biografi; geologi; polarområdene

Spatial and temporal variations in the thermodynamics since the Last Glacial Maximum at Jutulstraumen drainage basin, East Antarctica - Rolstad, Cecilie (Norsk Geografisk Tidsskrift - Norwegian Journal of Geography, 2006)
Publisher: Routledge
Keywords: Antarktis; akkumulasjon; glasiologi; isstrøm; nunataker

Comparison of the microalgal community within fast ice at two sites along the Ross Sea coast, Antarctica - Ryan, K.G.; Hegseth, E.N.; Martin, A.; Davy, S.K.; O'Toole, R.; Ralph, P.J.; McMinn, A.; Thorn, C.J. (Antarctic Science, 2006)
Diverse microbial communities survive within the sea ice matrix and are integral to the energy base of the Southern Ocean. Here we describe initial findings of a four season survey (between 1999–2004) of community structure and biomass of microalgae within the sea ice and in the underlying water column at Cape Evans and Cape Hallett, in the Ross Sea, Antarctica as part of the Latitudinal Gradient Project. At Cape Evans, bottom-ice chlorophyll a levels ranged from 4.4 to 173 mg Chl a m−2. Dominant species were Nitzschia stellata, N. lecointei, and Entomoneis kjellmanii, while the proportion of Berkeleya adeliensis increased steadily during spring. Despite being obtained later in the season, the Cape Hallett data show considerably lower standing stocks of chlorophyll ranging from 0.11 to 36.8 mg Chl a m−2. This difference was attributed to a strong current, which may have ablated much of the bottom ice biomass and provided biomass to the water below. This loss of algae from the bottom of the ice may explain why the ice community contributed only 2% of the standing stock in the total water column. Dominant species at Cape Hallett were Nitzschia stellata, Fragilariopsis curta and Cylindrotheca closterium. The low biomass at Cape Hallett and the prevalence of smaller-celled diatoms in the bottom ice community indicate that the ice here is more typical of pack ice than fast ice. Further data will allow us to quantify and model the extent to which ice-driven dynamics control the structure and function of the sea ice ecosystem and to assess its resilience to changing sea ice conditions.
Edition: 2006/11/14 Publisher: Cambridge University Press
Keywords: Rosshavet; Sørishavet; alger; biomasse; fytoplankton; marin biologi

Modeling ocean processes below Fimbulisen, Antarctica - Smedsrud, Lars H.; Jenkins, Adrian; Holland, David M.; Nøst, Ole Anders (Journal of Geophysical Research: Oceans, 2006)
Model simulations of circulation and melting beneath Fimbulisen, Antarctica, obtained using an isopycnic coordinate ocean model, are presented. Model results compare well with available observations of currents and hydrography in the open ocean to the north of Fimbulisen and suggest that Warm Deep Water exists above the level of a sub-ice-shelf bedrock sill, the principal pathway for warm waters to enter the sub-ice-shelf cavity. The model shows a southward inflow of Warm Deep Water over this sill and into the cavity, producing a mean cavity temperature close to −1.0°C. This leads to high levels of basal melting (>10 m/a) at the grounding line of Jutulstraumen and an average melting over the ice shelf base close to 1.9 m/a. The southward inflow is a compensating flow caused by the northward outflow of fresh, cold water produced by the basal melting. Results on inflow and melting are difficult to validate since no in situ measurements yet exist in the cavity. If such high melt rates are realistic, the mass balance of Fimbulisen must be significantly negative, and the ice shelves along Dronning Maud Land must contribute about 4.4 mSv of melt water to the Weddell Sea, about 15% of the total Antarctic meltwater input to the Southern Ocean.
Keywords: Dronning Maud Land; Sørishavet; Weddellhavet; geofysikk; hydrografi; isshelf; oseanografi

Ozone profiles in the high-latitude stratosphere and lower mesosphere measured by the Improved Limb Atmospheric Spectrometer (ILAS)-II: Comparison with other satellite sensors and ozonesondes - Sugita, Takafumi; Nakajima, Hideaki; Yokota, T; Kanzawa, Hiroshi; Gernandt, Hartwig; Herber, A; von der Gathen, P; König-Langlo, Gert; Sato, Kaoru; Dorokhov, Valery; Yushkov, V A; Murayama, Yasuhiro; et al. (Journal of Geophysical Research: Atmospheres, 2006)
A solar occultation sensor, the Improved Limb Atmospheric Spectrometer (ILAS)-II, measured 5890 vertical profiles of ozone concentrations in the stratosphere and lower mesosphere and of other species from January to October 2003. The measurement latitude coverage was 54–71°N and 64–88°S, which is similar to the coverage of ILAS (November 1996 to June 1997). One purpose of the ILAS-II measurements was to continue such high-latitude measurements of ozone and its related chemical species in order to help accurately determine their trends. The present paper assesses the quality of ozone data in the version 1.4 retrieval algorithm, through comparisons with results obtained from comprehensive ozonesonde measurements and four satellite-borne solar occultation sensors. In the Northern Hemisphere (NH), the ILAS-II ozone data agree with the other data within ±10% (in terms of the absolute difference divided by its mean value) at altitudes between 11 and 40 km, with the median coincident ILAS-II profiles being systematically up to 10% higher below 20 km and up to 10% lower between 21 and 40 km after screening possible suspicious retrievals. Above 41 km, the negative bias between the NH ILAS-II ozone data and the other data increases with increasing altitude and reaches 30% at 61–65 km. In the Southern Hemisphere, the ILAS-II ozone data agree with the other data within ±10% in the altitude range of 11–60 km, with the median coincident profiles being on average up to 10% higher below 20 km and up to 10% lower above 20 km. Considering the accuracy of the other data used for this comparative study, the version 1.4 ozone data are suitably used for quantitative analyses in the high-latitude stratosphere in both the Northern and Southern Hemisphere and in the lower mesosphere in the Southern Hemisphere.
Keywords: Antarktis; klimatologi; meteorologi; ozonlaget; polarområdene; stratosfæren

Kvalfangst - Urdal, Sverre (Segn og soge: sogeblad for Ølen og Bjoa, 2006)
Keywords: Sørishavet; hvalfangst

Is, fly og skip : oppdagelse og kartlegning med fly i Øst-Antarktis 1929-1939 - Widerøe, Turi; Drivenes, Einar-Arne (Universitetet i Tromsø, 2006)
Publication Title: Institutt for historie. Det samfunnsvitenskapelige fakultet
Keywords: Antarktis; ekspedisjoner; fly; fotogrammetri; geografi; historie; hvalfangst; kartlegging; kartografi; oppdagelsesreiser

Amundsen Sea ice production and transport - Assmann, Karen M.; Hellmer, Hartmut H.; Jacobs, Stanley S. (Journal of Geophysical Research: Oceans, 2005)
Drift and variability of sea ice in the Amundsen Sea are investigated with ice buoys deployed in March 2000 and a coupled ice-ocean model. The Bremerhaven Regional Ice Ocean Simulations (BRIOS) model results are compared with in situ ocean, atmosphere, and sea ice measurements; satellite observations; and 8?19 months of buoy drift data. We identify a zone of coastal westward drift and a band of faster eastward drift, separated by a broad transition region characterized by variable ice motions. The model represents drift events at scales approaching its resolution but is limited at smaller scales and by deficiencies in the National Centers for Environmental Prediction forcing. Two thirds of the modeled ice production in the southern Amundsen moves westward near the coast, its transport modulated by meridional wind strength, damping sea ice formation in the eastern Ross Sea. Half of the ice exported from the Ross moves eastward into the northern Amundsen Sea, a net sea ice sink that also receives more than one third of the ice generated to its south. A low rate of exchange occurs with the Bellingshausen Sea, which must have a more independent ice regime. Snow ice formation resulting from high precipitation accounts for one quarter of the ice volume in the Amundsen Sea, aiding the formation of thick ice in a region with generally divergent ice drift. Freshwater extraction by sea ice formation is roughly balanced by precipitation and ice shelf melting, but a positive trend in the surface flux is consistent with an Amundsen source for reported freshening in the Ross Sea.
Publisher: John Wiley & Sons, Ltd
Keywords: Amundsenhavet; Rosshavet; Sørishavet; geofysikk; havis; oseanografi

Iron and mixing affect biological carbon uptake in SOIREE and EisenEx, two Southern Ocean iron fertilisation experiments - Bakker, Dorothee C.E.; Bozec, Yann; Nightingale, Philip D.; Goldson, Laura; Messias, Marie-José; de Baar, Hein J.W.; Liddicoat, Malcolm; Skjelvan, Ingunn; Strass, Volker; Watson, Andrew J. (Deep Sea Research Part I: Oceanographic Research Papers, 2005)
This study explores the changes in the surface water fugacity of carbon dioxide (fCO2) and biological carbon uptake in two Southern Ocean iron fertilisation experiments with different hydrographic regimes. The Southern Ocean Iron Release Experiment (SOIREE) experiment was carried out south of the Antarctic Polar Front (APF) at 61°S, 141°E in February 1999 in a stable hydrographic setting. The EisenEx experiment was conducted in a cyclonic eddy north of the APF at 48°S, 21°E in November 2000 and was characterised by a rapid succession of low to storm-force wind speeds and dynamic hydrographic conditions. The iron additions promoted algal blooms in both studies. They alleviated algal iron limitation during the 13-day SOIREE experiment and probably during the first 12 days of EisenEx. The fCO2 in surface water decreased at a constant rate of 3.8μatmday−1 from 4 to 5 days onwards in SOIREE. The fCO2 reduction was 35μatm after 13 days. The evolution of surface water fCO2 in the iron-enriched waters (or ‘patch’) displayed a saw tooth pattern in EisenEx, in response to algal carbon uptake in calm conditions and deep mixing and horizontal dispersion during storms. The maximum fCO2 reduction was 18–20μatm after 12 and 21 days with lower values in between. The iron-enriched waters in EisenEx absorbed four times more atmospheric CO2 than in SOIREE between 5 and 12 days, as a result of stronger winds. The total biological uptake of inorganic carbon across the patch was 1389ton C (±10%) in SOIREE and 1433ton C (±27%) in EisenEx after 12 days (1ton=106g). This similarity probably reflects the comparable size of the iron additions, as well as algal growth at a similar near-maximum growth rate in these regions. The findings imply that the different mixing regimes had less effect on the overall biological carbon uptake across the iron-enriched waters than suggested by the evolution of fCO2 in surface water.
Keywords: Sørishavet; alger; biogeokjemi; hydrografi; karbondioksid; marin kjemi; oseanografi

Roald Amundsen : tidenes polfarer - Barr, Susan; Amundsen, Roald; Ekeberg, Jan Ove (Stenersen forl., 2005)
Keywords: Antarktis; Belgica ekspedisjon; Roald Amundsen; Sydpolsekspedisjonen; biografier; dagbøker; oppdagelsesreiser

Pioneer whalers in the Ross Sea, 1923–33 - Barr, William; Watt, James P C (Polar Record, 2005)
On Christmas Eve 1923, the whaling factory ship Sir James Clark Ross, commanded by Captain Carl Anton Larsen and accompanied by five catchers, reached the front of the Ross Ice Shelf; these were the first whaling vessels to operate in the Ross Sea. They had been dispatched by the Norwegian whaling company Hvalfangeraktienselskapet Rosshavet, which had obtained a licence from the British government. For most of the 1923–24 season, Sir James Clark Ross occupied an uneasy anchorage in the deep waters of Discovery Inlet, a narrow embayment in the front of the Ross Ice Shelf, while her catchers pursued whales widely in the Ross Sea. During that first season they killed and processed 221 whales (211 blue whales and 10 fin whales), which yielded 17,300 barrels of oil. During the next decade, with the exception of the 1931–32 season, Sir James Clark Ross and two other factory ships operated by Rosshavet, C.A. Larsen and Sir James Clark Ross II, operated in the Ross Sea. From the 1926–27 season onwards these ships were joined by up to three other factory ships and their catchers, operated by other companies. During the decade 1923–33 the Rosshavet ships killed and processed 9122 whales in the Ross Sea sector, mainly in the open waters of the Ross Sea south of the pack-ice belt. Total harvest for all factory ships from the Ross Sea sector for the period was 18,238 whales (mainly blue whales) producing 1,490,948 barrels of oil. From 1924 onwards the Rosshavet catchers wintered in Paterson Inlet on Stewart Island, New Zealand, and from 1925 onwards a well-equipped shipyard, Kaipipi Shipyard, operated on Price Peninsula in Paterson Inlet to service the Rosshavet ships.
Publisher: Cambridge University Press
Keywords: Carl Anton Larsen; Rosshavet; Sørishavet; hvalfangere; hvalfangstselskaper; pelagisk

On the taxonomic status of the Antarctic amphipod crustacean genera Eclysis (Astyridae) and Bathypanoploea (Stilipedidae), with partial redescription of their type species and description of Bathypanoploea polarsterni n. sp. - Berge, Jørgen; Vader, Wim (Organisms Diversity & Evolution, 2005)
The monotypic genus Eclysis K.H. Barnard, 1932 and its type species, E. similis Barnard, are redescribed based upon a newly discovered second specimen. The genus Bathypanoploea Schellenberg, 1939 is reviewed; B. schellenbergi Holman and Watling, 1983 is fixed as the type species. B. polarsterni n. sp. is described; Alexandrella pulchra Ren in Ren and Huang, 1991 is a new junior synonym of B. schellenbergi. The morphology of Eclysis and Bathypanoploea is examined, as well as their relationships to the Astyridae and Stilipedidae. See also Electronic Supplement at: http://www.senckenberg.de/odes/05-03.htm
Keywords: Sørishavet; amfipoder; taksonomi; zoologi

Snow chemistry across Antarctica - Bertler, N.; Mayewski, Paul Andrew; Aristarain, A.; Barrett, P.; Becagli, S.; Bernardo, R.; Bo, S.; C, Xiao; Curran, M.; D, Qin; Dixon, D.; Ferrona, F.; et al. (Annals of Glaciology, 2005)
An updated compilation of published and new data of major-ion (Ca, Cl, K, Mg, Na, NO3, SO4) and methylsulfonate (MS) concentrations in snow from 520 Antarctic sites is provided by the national ITASE (International Trans-Antarctic Scientific Expedition) programmes of Australia, Brazil, China, Germany, Italy, Japan, Korea, New Zealand, Norway, the United Kingdom, the United States and the national Antarctic programme of Finland. The comparison shows that snow chemistry concentrations vary by up to four orders of magnitude across Antarctica and exhibit distinct geographical patterns. The Antarctic-wide comparison of glaciochemical records provides a unique opportunity to improve our understanding of the fundamental factors that ultimately control the chemistry of snow or ice samples. This paper aims to initiate data compilation and administration in order to provide a framework for facilitation of Antarctic-wide snow chemistry discussions across all ITASE nations and other contributing groups. The data are made available through the ITASE web page (http://www2.umaine.edu/itase/content/syngroups/snowchem.html) and will be updated with new data as they are provided. In addition, recommendations for future research efforts are summarized.
Publisher: Cambridge University Press
Keywords: Antarktis; geovitenskap; glasiokjemi; glasiologi; iskjerner; transantarktiske ekspedisjoner

Hvalfangerselskapet Kosmos - Boye, Tore (Anders Jahres pengebinge, 2005)
Keywords: Sørishavet; hvalfangstindustri; hvalfangstselskaper; hvalindustri; pelagisk

Southern Ocean deep-sea isopod species richness (Crustacea, Malacostraca): influences of depth, latitude and longitude - Brandt, Angelika; Ellingsen, Kari E.; Brix, Saskia; Brökeland, Wiebke; Malyutina, Marina (Polar Biology, 2005)
We examined deep-sea epibenthic sledge isopod data from the Atlantic sector of the Southern Ocean (SO) (depth range=742–5,191 m). Samples were taken during the expeditions EASIZ II (ANT XV-3) in 1998 and ANDEEP I and II (ANT XIX3/4) in 2002. A total of 471 isopod species were recorded from 28 sites. The species richness of the epibenthic sledge samples was highly variable (6–82 species). Species richness was highest at site 131-3 in 3,053 m depth in the north-eastern Weddell Sea. The highest numbers of species were sampled in the middle depth range and lower species richness was found in the shallower and deeper parts of the study area. Depth is suggested to explain isopod species richness better than both latitude and longitude. Between 58°S and 65°S, the number of species ranged from 9 to 82 (mean=35.9). Further south in the Weddell Sea, between 73°S and 74°S, species richness was lower and the number of species ranged from 6 to 35 (mean=19.2). With regard to longitude, the highest species richness (up to 82 species) was found between 50°W and 60°W in the area of the South Shetland Islands and around the Antarctic Peninsula, while numbers did not exceed 50 species in the eastern Weddell Sea. The haul length, ranging from 807 to 6,464 m, was positively correlated with depth; however, there was no linear relationship between haul length and species richness. We therefore suggest that depth was the most important factor explaining isopod species richness. However, only 28 sites were visited and the statistical power is thus limited. Sampling in the deep sea is expensive and time consuming and as yet this is the best isopod data set available from the Atlantic sector of the SO. Future expeditions are therefore important to better explain the current patterns of benthic diversity in Antarctica.
Keywords: Sør-Shetlandsøyene; Sørishavet; Weddellhavet; biodiversitet; isopoder; marin biologi

Polar bivalves are characterized by high antioxidant defences - Camus, Lionel; Gulliksen, Bjørn; Depledge, Michael H; Jones, Malcolm B (Polar Research, 2005)
Inevitably, aerobic life leads to the formation of deleterious reactive oxygen species (ROS) which participate in biomolecule oxidation, hence augmenting biomolecule turnover. Organisms have adapted to counteract the noxious effects of ROS by developing a battery of antioxidant defences (AOX) which comprise enzymes and low-molecular weight scavengers. Past studies have reported elevated AOX levels in polar pectinid bivalves compared with temperate congeners. This fi nding is controversial as mitochondrial ROS generation is low in polar versus temperate species, and, to date, there is no generally accepted explanation of the causes of increased basal AOX levels in polar waters. We suggest that the low food availability in those ecosystems may result in polar marine ectotherms diverting some energy into the maintenance of high AOX. We tested this hypothesis by comparing the total oxyradical scavenging capacity (peroxyl, hydroxyl and peroxynitrite) of three clam species: Laternula elliptica (Antarctic), Mya truncata (Arctic) and Mya arenaria (temperate). The data confi rmed that polar bivalves are characterized by higher AOX. Herein, we propose that high AOX is required in environments characterized by low food availability as AOX effi ciently protects biomolecules, notably the RNA expressed at high levels by cold-water ectotherms. Also, high AOX may explain the relatively long lifespan of most polar ectotherms.
Keywords: Sørishavet; marin biologi; muslinger; polarområdene

Taxonomic turnover and abundance in Cretaceous to Tertiary wood floras of Antarctica: implications for changes in forest ecology - Cantrill, David J.; Poole, Imogen (Palaeogeography, Palaeoclimatology, Palaeoecology, 2005)
Based on the temporal distribution, abundance, and taxonomic composition of wood floras, four phases of vegetation development are recognized through the Cretaceous to Early Tertiary of the Antarctic Peninsula: (1) Aptian to Albian communities dominated by podocarpaceous, araucarian, and minor taxodiaceous/cupressaceous conifers with rare extinct gymnosperms (Sahnioxylon). (2) Progressive replacement of these communities in ?Cenomanian to Santonian times by angiosperms, most without modern analogues. (3) Increasing dominance of angiosperms becoming important both in terms of diversity and abundance towards the mid-Late Cretaceous. (4) Modernization of the flora during the Campanian to Maastrichtian with the extinction of earlier forms, appearance of the Nothofagaceae and diversification of associated elements. These patterns broadly follow trends seen in the leaf and palynological record but with some important differences. During the Cretaceous, conifer composition undergoes a change whereby Phyllocladoxylon-type woods increase relative to the older Podocarpoxylon forms. During the Paleocene to Eocene period, a marked extinction in wood types occurs associated with an increase in the abundance of nothofagaceous wood. Detailed examination of wood abundance and distributions from sections within Maastrichtian and Paleocene formations points to strong environmental control on taxonomic compositions. Similar differences are encountered when comparing coeval floras from different geographic regions and palaeoenvironments.
Keywords: Antarktis; flora; geologi; paleobotanikk; paleogeografi; paleontologi

Magma-driven hydraulic fracturing and infiltration of fluids into the damaged host rock, an example from Dronning Maud Land, Antarctica - Engvik, Ane K.; Bertram, Andreas; Kalthoff, Jörg F.; Stöckhert, Bernhard; Austrheim, Håkon; Elvevold, Synnøve (Journal of Structural Geology, 2005)
Excellent outcrops in Dronning Maud Land, Antarctica, provide unique insight into the mode and extent of fluid infiltration into metamorphic and plutonic rocks in the middle crust. The fluids are liberated from pegmatitic veins and give rise to alteration halos. In the alteration halos, the conspicuous change in colour is correlated with (1) hydration mineral reactions, and (2) high density of microcracks in quartz and feldspar exceeding that observed in the unaltered host rock by an order of magnitude. The field relations indicate that the veins originated as melt-driven hydraulic fractures, sealed by pegmatite and aplite crystallising from volatile-rich melts, with the alteration halo being the wake of the process zone formed at the tip of the propagating fractures. It is proposed that (1) the size of the alteration zone and the width of the vein are correlated, resulting in higher values of both these quantities for cracks propagating at higher velocities and consequently higher crack propagation toughnesses; (2) the damage zone is characterised by a transient state of high permeability which was short-lived due to rapid healing and sealing of microcracks; (3) the infiltration and retrogression of the high-grade rocks can be considered as a quasi-instantaneous process on geologic time scales with a duration of hours to weeks.
Keywords: Dronning Maud Land; geologi; petrologi

Population changes of Antarctic fur seals at Nyrøysa, Bouvetøya - Hofmeyr, Greg; Krafft, Bjørn; Kirkman, Stephen; Bester, Marthán; Lydersen, Christian; Kovacs, Kit (Polar Biology, 2005)
Antarctic fur seal Arctocephalus gazella pup production at Nyrøysa, Bouvetøya was estimated to be approximately 15,000 per annum during each of four summers from 1996 to 2002, indicating a total population of about 66,000. While the Bouvetøya population is the second largest for this species, pup production at this site still accounts for only 2.4% of the global total. This population experienced a mean annual rate of increase of 30.6% for the period 1989–1996, perhaps due, in part, to significant immigration, but has been stable since 1996. Historical accounts of significant numbers of animals being present towards the end of the period of sealing (C.1800–1930), indicate that the geographic isolation and inaccessibility of this site may have resulted in the Bouvetøya population being one of three populations that survived a series of periods of extreme exploitation of this species.
Keywords: Bouvetøya; marin biologi; pelsseler; pinnipedier; seler; zoologi

Modeling the middle Pliocene climate with a global atmospheric general circulation model - Jiang, Dabang; Wang, Huijun; Ding, Zhongli; Lang, Xianmei; Drange, Helge (Journal of Geophysical Research: Atmospheres, 2005)
A new climate simulation for the middle Pliocene (ca. 3 Ma BP) is performed by a global grid-point atmospheric general circulation model developed at the Institute of Atmospheric Physics (IAP AGCM) with boundary conditions provided by the U. S. Geological Survey's Pliocene Research, Interpretations, and Synoptic Mapping (PRISM) group. It follows that warmer and slightly wetter conditions dominated at the middle Pliocene with a globally annual mean surface temperature increase of 2.60°C, and an increase in precipitation of 4.0% relative to today. At the middle Pliocene, globally annual terrestrial warming was 1.86°C, with stronger warming toward high latitudes. Annual precipitation enhanced notably at high latitudes, with the augment reaching 33.5% (32.5%) of the present value at 60–90°N (60–90°S). On the contrary, drier conditions were registered over most parts at 0–30°N, especially in much of East Asia and the northern tropical Pacific. In addition, both boreal summer and winter monsoon significantly decreased in East Asia at the middle Pliocene. It is indicated that the IAP AGCM simulation is generally consistent with the results from other atmospheric models and agrees well with available paleoclimatic reconstructions in East Asia. Additionally, it is further revealed that the PRISM warmer sea surface temperature and reduced sea ice extent are main factors determining the middle Pliocene climate. The simulated climatic responses arising from the PRISM reconstructed vegetation and continental ice sheet cannot be neglected on a regional scale at mid to high latitudes (like over Greenland and the Qinghai-Tibetan Plateau, and around the circum-Antarctic) but have little influence on global climate.
Keywords: Antarktis; global klimamodell; global oppvarming; innlandsis; paleoklimatologi; polarområdene

Notes on two subantarctic pannariaceous lichens - Jørgensen, Per Magnus (Cryptogamie Mycologie, 2005)
It is shown by use of a newly discovered, old photo of the missing type that Siphulina orphnina (Hue) C. W. Dodge is identical with Pannaria caespitosa P. M. Jorg. The new combination Pannaria orphnina (Hue) R M. Jorg. is made, and the name neotypitied. Parmeliella austroshetlandica Sochting & Ovstedal is shown to be a species in the small subantarctic genus Peltularia R. Sant. (Coccocarpiaceae), and is transferred to that genus.
Keywords: Antarktis; biologi; botanikk; lav; planter

Physical properties and stratigraphy of surface snow in western Dronning Maud Land, Antarctica - Kärkäs, Eija; Martma, Tõnu; Sonninen, Eloni (Polar Research, 2005)
Information about the spatial variations of snow properties and of annual accumulation on ice sheets is important if we are to understand the results obtained from ice cores, satellite remote sensing data and changes in climate patterns. The layer structure and spatial variations of physical properties of surface snow in western Dronning Maud Land were analysed during the austral summers 1999/2000, 2000/01 and 2003/04 in fi ve different snow zones. The measurements were performed in shallow (1 - 2 m) snow pits along a transect extending 350 km from the seaward edge of the ice shelf to the polar plateau. These pits covered at least the last annual accumulation and ranged in elevation from near sea level to 2500 m a.s.l. The ?18O values and accumulation rates had a good linear correlation with the distance from the coast. The mean accumulation on the ice shelf was 312 ± 28 mm water equivalent (w.e.); in the coastal region it was 215 ± 43 mm w.e. and on the polar plateau it was 92 ± 25 mm w.e. The mean annual conductivity and grain size values decreased exponentially with increasing distance from the ice edge, by 48 %/100 km and 18 %/100 km respectively. The mean grain size varied between 1.5 and 1.8 mm. Depth hoar layers were a common phenomenon, especially under thin ice crusts, and were associated with low dielectric constant values.
Keywords: Dronning Maud Land; geofysikk; geologi; havnivå; innlandsis; klimatologi; miljøendringer; overflatesnø; snø akkumulasjon; stratigrafi

Accumulation variability over a small area in east Dronning Maud Land, Antarctica, as determined from shallow firn cores and snow pits: some implications for ice-core records - Karlöf, Lars; Isaksson, Elisabeth; Winther, Jan-Gunnar; Gundestrup, Niels; Meijer, Harro A J; Mulvaney, Robert; Pourchet, Michel; Hofstede, Coen; Lappegard, Gaute; Pettersson, Rickard; Van Den Broeke, Michiel; Van De Wal, Roderik S W (Journal of Glaciology, 2005)
We investigate and quantify the variability of snow accumulation rate around a medium-depth firn core (160 m) drilled in east Dronning Maud Land, Antarctica (75°00′ S, 15°00’ E; 3470 m h.a.e. (ellipsoidal height)). We present accumulation data from five snow pits and five shallow (20 m) firn cores distributed within a 3.5–7 km distance, retrieved during the 2000/01 Nordic EPICA (European Project for Ice Coring in Antarctica) traverse. Snow accumulation rates estimated for shorter periods show higher spatial variance than for longer periods. Accumulation variability as recorded from the firn cores and snow pits cannot explain all the variation in the ion and isotope time series; other depositional and post-depositional processes need to be accounted for. Through simple statistical analysis we show that there are differences in sensitivity to these processes between the analyzed species. Oxygen isotopes and sulphate are more conservative in their post-depositional behaviour than the more volatile acids, such as nitrate and to some degree chloride and methanesulphonic acid. We discuss the possible causes for the accumulation variability and the implications for the interpretation of ice-core records.
Publisher: Cambridge University Press
Keywords: Dronning Maud Land; glasiologi; klimamodeller; klimatologi

Økonomi og økologi i ishavene - Kjeldstadli, Knut (Et splittet samfunn : 1905-1935, 2005)
Keywords: Norge; Sørishavet; hvalfangst; pelagisk; økologi; økonomi

Belgica in the Arctic - Kjær, Kjell-G. (Polar Record, 2005)
Belgica, which Adrien de Gerlache used on the first expedition to winter in the Antarctic, was originally a bottlenose whaler named Patria, built in Norway in 1884. She was designed and constructed by Johan Chr. Jakobsen, renowned for his design of polar ships. Patria was sold to Adrien de Gerlache and renamed Belgica in 1896. In 1896–97 she was refitted and equipped in Sandefjord, Norway, for an Antarctic expedition. Nansen and Amundsen met for the first time on Belgica's deck. Late in 1899 Belgica returned to Antwerp after more than two years on an Antarctic expedition. From 1901 to 1904 Belgica returned to bottlenose whaling and, in addition, made a voyage to northeast Greenland to establish depots and build houses for the Baldwin-Ziegler Polar Expedition. In 1905 the Duc d'Orléans chartered her to survey the coast of northeast Greenland, and on her return he bought her. In 1907 and 1909 she sailed on Arctic expeditions led by the Duc d'Orléans and captained by de Gerlache. In 1916 she was sold to Det Norske Kulsyndikat and renamed Isfjord. She became a freighter carrying coal from Longyearbyen to ports in northern Norway. In 1918 she was sold and her new owner converted her into a floating cod-liver oil refinery and fish-processing plant. In 1940 she was impounded by British forces and used as a floating ammunition depot. On 19 May 1940 she was sunk during a German air raid. Her wreck was re-discovered in 1990.
Edition: 2005/08/01 Publisher: Cambridge University Press
Keywords: Antarktis; Belgica (skip); Belgica ekspedisjon; Roald Amundsen; overvintring; polarekspedisjoner; polarområdene

Telonema antarcticum sp. nov., a common marine phagotrophic flagellate - Klaveness, Dag; Shalchian-Tabrizi, Kamran; Thomsen, Helge Abildhauge; Eikrem, Wenche; Jakobsen, Kjetill S. (International Journal of Systematic and Evolutionary Microbiology, 2005)
Telonema is a widely distributed group of phagotrophic flagellates with two known members. In this study, the structural identity and molecular phylogeny of Telonema antarcticum was investigated and a valid description is proposed. Molecular phylogeny was studied using small-subunit rRNA (SSU rRNA) gene sequences. The pear-shaped cell had two subequal flagella that emerged laterally on the truncated antapical tail. One flagellum had tripartite hairs. The cell was naked, but had subsurface vesicles containing angular paracrystalline bodies of an unknown nature. A unique complex cytoskeletal structure, the subcortical lamina, was found to be an important functional and taxonomic feature of the genus. Telonema has an antero-ventral depression where food particles are ingested and then transferred to a conspicuous anterior food vacuole. The molecular phylogeny inferred from the SSU rRNA gene sequence suggested that Telonema represents an isolated and deep branch among the tubulocristate protists.
Publisher: Microbiology Society Type: Journal Article
Keywords: Sørishavet; Weddellhavet; fylogenetikk; marin biologi; mikrobiologi

Sediment characterization by echosounding and sampling - Kuhn, Gerhard; Brückner, Sylvia; Didik, Claudia; Forwick, Matthias; Hass, Christian; Lensch, Norbert; Schmitt, Wolfgang; Waldthausen, Constanze V; Wittling, Thomas (The Expedition ANTARKTIS-XX of RV Polarstern in 2002/2003 Reports of Legs 1 and 2, 2005)
The reconstruction of the paleoclimatic and paleoceanographic development of the late Quaternary Southern Ocean and adjacent continental areas in high temporal and spatial resolution is a main goal of our longterm study. During ANT-XX/2 the sedimentary budget of biogenic and terrigenous components and their variability was investigated in cooperation with geochemical projects. Main objectives were the relationships between production of biogenic components and input of terrigenous components and involved nutrients.
Keywords: Sørishavet; geokjemi; marin geologi; oseanografi; paleoklimatologi

Interplay of turbidite and contourite deposition along the Cosmonaut Sea/Enderby Land margin, East Antarctica - Kuvaas, Berit; Kristoffersen, Yngve; Guseva, J.; Leitchenkov, German; Gandjukhin, V.; Løvås, O.; Sand, Morten; Brekke, Harald (Marine Geology, 2005)
Multichannel seismic reflection data from the Cosmonaut Sea margin of East Antarctica have been interpreted in terms of depositional processes on the continental rise. A major sediment lens is present below the upper continental rise along the entire Cosmonaut Sea margin. The lens probably consists of sediments supplied from the shelf and slope, being constantly reworked by westward flowing bottom currents redepositing the sediments into a large-scale plastered drift deposit prior to the main glacigenic input along the margin. High-relief elongated and sometimes semicircular depositional structures are found on the upper continental rise, stratigraphically above the regional sediment lens, and were mainly deposited by the action of closely spaced turbidity currents. On the lower continental rise, large-scale sediment bodies extend perpendicular to the continental margin and were deposited as a result of down-slope turbidity transport and westward flowing bottom currents. The elongated sediment mounds on the upper and lower continental rise were deposited after initiation of glacigenic input to the slope and rise.
Keywords: Antarktis; Sørishavet; marin geofysikk; marin geologi

Quality assurance of the solar UV network in the Antarctic - Lakkala, Kaisa; Redondas, Alberto; Meinander, Outi; Torres, Carlos; Koskela, Tapani; Cuevas, Emilio; Taalas, Petteri; Dahlback, Arne; Deferrari, Guillermo Alejandro; Edvardsen, Kåre; Ochoa, Héctor (Journal of Geophysical Research: Atmospheres, 2005)
Measuring ultraviolet radiation in the Antarctic region, where weather conditions are extremely challenging, is a demanding task. Proper quality control of the measurements and quality assurance of the data, which are the basis of all scientific use of data, has to be especially well planned and executed. In this paper we show the importance of proper quality assurance and describe the methods used to successfully operate the NILU-UV multichannel radiometers of the Antarctic network stations at Ushuaia, 54°S, and Marambio, 64°S. According to our experience, even though multichannel instruments are supposed to be rather stable as a function of time, severe drifts can occur in the sensitivity of the channels under these harsh conditions. During 2000–2003 the biggest drifts were 35%, both at Ushuaia and Marambio, with the sensitivity of the channels dropping at different rates. Without proper corrections in the data, this would have seriously affected the calculated UV dose rates. As part of the quality assurance of the network a traveling reference NILU-UV, which was found to be stable, was used to transfer the desired irradiance scale to the site NILU-UV data. Relative lamp tests were used to monitor the stability of the instruments. Each site NILU-UV was scaled channel by channel to the traveling reference by performing solar comparisons. The method of scaling each channel separately was found to be successful, even though the differences between the raw data of the site NILU-UV and the reference instruments were, before the data correction, as much as 40%. After the correction, the mean ratios of erythemally weighted UV dose rates measured during the solar comparisons in 2000–2003 between the reference NILU-UV and the site NILU-UV were 1.007 ± 0.011 and 1.012 ± 0.012 for Ushuaia and Marambio, respectively, when the solar zenith angle varied up to 80°. These results make possible the scientific use of NILU-UV data measured simultaneously at quite different locations, e.g., the Antarctic and Arctic, and the method presented is also practicable for other multichannel radiometer networks.
Keywords: Antarktis; UV-stråling; meteorologi; målinger; ultrafiolett stråling

The International Trans-Antarctic Scientific Expedition (ITASE): an overview - Mayewski, Paul Andrew; Frezzotti, Massimo; Bertler, Nancy; Ommen, Tas V. A. N.; Hamilton, Gordon; Jacka, Tim H.; Welch, Brian; Frey, Markus; Dahe, Qin; Jiawen, Ren; Simões, Jefferson; Fily, Michel; et al. (Annals of Glaciology, 2005)
From its original formulation in 1990 the International Trans-Antarctic Scientific Expedition (ITASE) has had as its primary aim the collection and interpretation of a continent-wide array of environmental parameters assembled through the coordinated efforts of scientists from several nations. ITASE offers the ground-based opportunities of traditional-style traverse travel coupled with the modern technology of GPS, crevasse detecting radar, satellite communications and multidisciplinary research. By operating predominantly in the mode of an oversnow traverse, ITASE offers scientists the opportunity to experience the dynamic range of the Antarctic environment. ITASE also offers an important interactive venue for research similar to that afforded by oceanographic research vessels and large polar field camps, without the cost of the former or the lack of mobility of the latter. More importantly, the combination of disciplines represented by ITASE provides a unique, multidimensional (space and time) view of the ice sheet and its history. ITASE has now collected >20 000km of snow radar, recovered more than 240 firn/ice cores (total length 7000 m), remotely penetrated to ~4000m into the ice sheet, and sampled the atmosphere to heights of >20 km.
Publisher: Cambridge University Press
Keywords: Antarktis; Dronning Maud Land; ekspedisjoner; geovitenskap; glasiologi; klimatologi; transantarktiske ekspedisjoner

Forskrift om ferdselsbegrensning i Nyrøysaområdet på Bouvetøya - miljødepartementet, Klima- og (Lovdata, 2005)
Volume: 2005-06-24-687 Place: Oslo
Keywords: Bouvetøya; naturvern

A comparison of the NW European glaciated margin with other glaciated margins - Nielsen, Tove; De Santis, L.; Dahlgren, K.I. Torbjørn; Kuijpers, A.; Laberg, J.S.; Nygård, Atlé; Praeg, D.; Stoker, M.S. (The STRATAGEM Project, 2005)
The present paper provides an overview of glacial related seabed features and sedimentary sequences found along the formerly glaciated NW European margin and compare it with those found on contemporary glaciated margins from both the Southern and Northern Hemispheres. A brief review of the seabed physiography and strata architecture of the margins under consideration is followed by comparison of the most relevant similarities and differences. Comparison of the present-day bathymetric setting of both former and contemporary glaciated margins reveals no clear link to the effect of neither ice sheet or sediment load. Three different types of glacially eroded shelf transverse troughs have been identified, while marginal troughs seem connected to similar geological settings everywhere. Beyond the shelf edge interaction between downslope and alongslope processes has occurred resulting, amongst others, in the formation of large sedimentary mounds on the rise. More frequent large-scale mass wasting occurs on the former glaciated NW European margin than the Greenland and Antarctic margins in the latest Neogene to recent times. A two-stage evolution of the shelf prograding wedges is observed on all margins under consideration, which may reflect a general development of an ice cover from an initial phase of non- to restricted glaciation, evolving to a mature stage of expansive glaciation.
Keywords: Antarktis; geofysikk; marin geologi

Seleksjon av personell til overvintring i Antarktis - Orre, Ingrid Jangård; Eriksen, Hege Randi; Ursin, Holger; Grant, Iain; Palinkas, Lawrence A; Suedfeld, Peter (Tidsskrift for Norsk psykologforening, 2005)
Keywords: Antarktis; ekspedisjoner; psykologi; stasjoner

An Observational Study of the Final Breakdown of the Southern Hemisphere Stratospheric Vortex in 2002 - Orsolini, Yvan J.; Randall, Cora E.; Manney, Gloria L.; Allen, Douglas R. (Journal of the Atmospheric Sciences, 2005)
The 2002 Southern Hemisphere final warming occurred early, following an unusually active winter and the first recorded major warming in the Antarctic. The breakdown of the stratospheric polar vortex in October and November 2002 is examined using new satellite observations from the Michelson Interferometer for Passive Atmospheric Sounding (MIPAS) instrument aboard the European Space Agency (ESA) Environment Satellite (ENVISA7-) and meteorological analyses, both high-resolution fields from the European Centre for Medium-Rangc Weather Forecasts and the coarser Met Office analyses. The results derived from MIPAS observations are compared to measurements and inferences from well-validated solar occultation satellite instruments [Halogen Occultation Experiment (HALOE), Polar Ozone and Aerosol Measurement lit (POAM III), and Stratospheric Aerosol and Gas Experiments II and III (SAGE II and III)] and to finescale tracer fields reconstructed by transporting trace gases based oil MIPAS or climatological data using a reverse-trajectory method. These comparisons confirm the features in the MIPAS data and the interpretation of the evolution of the flow during the vortex decay revealed by those features. Mapped ozone and water vapor from MIPAS and the analyzed isentropic potential vorticity vividly display the vortex breakdown, which occurred earlier than usual. A large tongue of vortex air was pulled out westward and coiled up in an anticyclone, while the vortex core remnant shrank and drifted eastward and equatorward over the South Atlantic. By roughly mid-November, the vortex remnant at 10 mb had shrunk below scales resolved by the satellite observations, while a vortex core remained in the lower stratosphere.
Place: Boston MA, USA Publisher: American Meteorological Society
Keywords: Antarktis; klimatologi; meteorologi; polarvirvelen; stratosfæren

A multi-proxy approach to determine Antarctic terrestrial palaeoclimate during the Late Cretaceous and Early Tertiary - Poole, Imogen; Cantrill, David; Utescher, Torsten (Palaeogeography, Palaeoclimatology, Palaeoecology, 2005)
Fossil wood is abundant throughout the Cretaceous and Tertiary sequences of the northern Antarctic Peninsula region. The fossil wood represents the remains of the vegetation that once grew at the southern high palaeolatitudes at 59–62°S through the general decline in climate, from the Late Cretaceous global warmth through to the mid-Eocene cool period prior to the onset of glaciation. This study draws on the largest dataset ever compiled of Antarctic conifer and angiosperm woods in order to derive clearer insights into the palaeoclimate. Parameters including mean annual temperature, mean annual range in temperature, cold month mean, warm month mean, mean annual precipitation are recorded. The fossil wood assemblages have been analysed using anatomical (physiognomic) characteristics to determine the palaeoclimate variables from the Coniacian–Campanian to the middle Eocene. These results are compared with data derived from Coexistence Analysis of the fossil floras (composed of leaves, wood and palynomorphs) and published data based on leaf physiognomic characters. These studies indicate a relatively warm and wet Late Cretaceous that becomes drier and cooler in the Early Paleocene and subsequently returns to warmer, wetter conditions by the latest Early Paleocene. During the Eocene the climate becomes relatively cool and dry once again. The discrepancies obtained from these two methods coupled with other published data are discussed in the context of the fluctuations in the temperatures of the surrounding oceans and global patterns of climate change.
Keywords: Antarktis; paleobotanikk; paleogeografi; paleoklimatologi; paleontologi

Holocene climate evolution in the high-latitude Southern Hemisphere simulated by a coupled atmosphere-sea ice-ocean-vegetation model - Renssen, Hans; Goosse, Hugues; Fichefet, Thierry; Masson-Delmotte, Valérie; Koç, Nalân (Holocene, 2005)
The Holocene climate is simulated in a 9000-yr-long transient experiment performed with the ECBilt-CLIO-VECODE coupled atmosphere-sea ice-ocean-vegetation model. This experiment is forced with annually varying orbital parameters and atmospheric concentrations of CO2 and CH4. The objective is to study the impact of these long-term forcings on the surface temperature evolution during different seasons in the high-latitude Southern Hemisphere. We find in summer a thermal optimum in the midHolocene (6-3 ka BP), with temperatures locally 3°C above the preindustrial mean. In autumn the temperatures experienced a long-term increase, particularly during the first few thousand years. The opposite trend was simulated for winter and spring, with a relatively warm Southern Ocean at 9 ka BP in winter (up to 3.5°C above the preindustrial mean) and a warm continent in spring (+3°C), followed by a gradual cooling towards the present. These long-term temperature trends can be explained by a combination of (1) a delayed response to orbital forcing, with temperatures lagging insolation by 1 to 2 months owing to the thermal inertia of the system, and (2) the long memory of the Southern Ocean. This long memory is related to the storage of the warm late winter-spring anomaly below the shallower summer mixed layer until next winter. Sea ice plays an important role as an amplifying factor through the ice-albedo and ice-insulation feedbacks. Our experiments can help to improve our understanding of the Holocene signal in proxies. For instance, the results suggest that, in contrast to recent propositions, teleconnections to the Northern Hemisphere appear not necessarily to explain the history of Southern Hemisphere temperature changes during the Holocene.
Keywords: Sørishavet; holocene; klimaendringer; klimamodeller; paleoklimatologi

”Admiralen” til Sydishavet – et 100 års minne - Ringstad, Jan Erik (Kulturminner, 2005)
Den 21. oktober 1905 forlot flytende kokeri Admiralen og hvalbåtene Ornen og Hauken Sandefjord med kurs for Falklandsayene og Syd Shetland. Dermed innledes et nytt kapittel i den moderne hvalfangsts histone. lnitiativtaker var Christen Christensen, hovedaksjoner og disponent for Aktieselskabet "Ørnen" som eide skipene det første norske hvalfangstselskap som uttrykkelig ble startet for eventuelt innkjøp av et dampskip for innredning til koker.
Keywords: Sørishavet; historie; hvalfangstselskaper; oppdagelsesreiser; pelagisk

Warming of the deep water in the Weddell Sea along the Greenwich meridian: 1977–2001 - Smedsrud, Lars H. (Deep Sea Research Part I: Oceanographic Research Papers, 2005)
The Weddell Deep Water (WDW) warmed substantially along the Greenwich meridian following the Weddell Polynya of the 1970s. Areas affected by the polynya contained ∼14GJ/m2 more heat in 2001 than in 1977. This warming would require a flux of ∼390W/m2 if it were to take place over a year. Large variations in heat content of the WDW are found between the Antarctic coast and Maud Rise (64°S). The small variation found north of Maud Rise is opposite in phase to that to the south, and the warming was close to monotonic south of 68°S. The mean warming of WDW along the section is ∼0.032°C per decade, comparable to the warming of the Antarctic Circumpolar Current. The mean warming compares with a surface heat flux of 4W/m2 over the 25 year period, an order of magnitude higher than the warming of the global ocean. As variation in mean salinity of the WDW follows the warming/cooling events, variation in inflow probably explains a cooling event between 1984 and 1989, and a warming event between 1989 and 1992. Cooling during the late 1990s is probably related to the reappearance of a polynya like feature in some winter months as an area 100km in diameter close to Maud Rise with 10–20% lower sea ice concentrations than the surrounding ocean.
Keywords: Sørishavet; Weddellhavet; havstrømmer; oseanografi; polynja

Dagbok fra en Sydhavstur 1906 - Sørlle, Petter; Kolltveit, Bård (Norsk sjøfartsmuseum. Årbok, 2005)
Publisher: Norsk sjøfartsmuseum Place: Oslo
Keywords: Sørishavet; dagbøker; hvalfangere; hvalfangstindustri; hvalindustri; hvalkokeri; polareksspedisjoner

Isolation and partial characterization of a parapoxvirus isolated from a skin lesion of a Weddell seal - Tryland, M.; Klein, J.; Nordøy, E.S.; Blix, A.S. (Virus Research, 2005)
A solitary skin lesion was found on the neck of a Weddell seal (Leptonychotes weddellii), chemically immobilized in Queen Maud Land (70°09′S, 05°22′E) Antarctica 2001. The lesion was elevated and 3cm in diameter, consisting of partly fresh and partly necrotic tissue, and proliferative papilloma-like structures were seen. Electron microscopy on a biopsy from the lesion revealed typical parapoxvirus particles. Polymerase chain reaction (PCR; B2L gene) generated amplicons of approximately 594 base pairs, comparable to Orf-virus, the prototype parapoxvirus. A comparison of these B2L PCR amplicon DNA sequences with corresponding sequences from other parapoxviruses, showed that the Weddell seal virus resembled isolates from grey seal (Halichoerus grypus) and harbour seal (Phoca vitulina) more than parapoxvirus from red deer (Cervus elaphus), sheep, cattle and Japanese serows (Capricornis crispus). It is thus concluded that the Weddell seal parapoxvirus belong to the tentative seal parapoxvirus species. Since parapox and orthopoxviruses may cause similar clinical diseases, we suggest that the term sealpox should be restricted to the clinical disease, whereas seal parapoxvirus should be used when caused by a parapoxvirus, rather than the general term “sealpox virus”. This is the first verified case of parapoxvirus infection in a Weddell seal, and also the first report of any such infections in the Antarctic.
Keywords: Dronning Maud Land; Weddellhavet; fylogenetikk; marin biologi; mikrobiologi; pinnipedier; seler; virologi

Forskrift om grunnlinjen for sjøterritoriet ved Bouvetøya - Utenriksdepartementet (Lovdata, 2005)
Volume: 2005-02-25-174 Place: Oslo
Keywords: Bouvetøya; forvaltning; jus

Chick survival in relation to nest site: is the Antarctic petrel hiding from its predator? - Varpe, Øystein; Tveraa, Torkild (Polar Biology, 2005)
In birds, the characteristics of the nest site may affect reproductive success. We found that shelter is an important characteristic of the Antarctic petrel (Thalassoica antarctica) nests because shelter prevents chick predation. However, the benefit of shelter was countervailed by melt water which mainly entered well-sheltered nests. Chick survival was monitored until the chick was left unattended for the first time. Late-hatched chicks had a higher survival probability than early-hatched chicks, possibly because late hatchers swamp the predator, the south polar skua (Catharacta maccormicki). Poorly sheltered nests tended to be occupied by parents with low body mass and late-hatched eggs. The results suggest that both shelter per se and parental characteristics may explain the relationship between predation risk and shelter. We need experiments to study the influence of nest site on reproductive success, and we need to map the frequency of melt water as a cause of reproductive failure.
Keywords: Antarktis; fugler; ornitologi; petreller; reproduksjon; zoologi

Decision Processes and Interactions During a Two-Woman Traverse of Antarctica - Atlis, Mera M.; Leon, Gloria R.; Sandal, Gro M.; Infante, Michael G. (Environment and Behavior, 2004)
This investigation assessed an international two-woman team engaged in a 97-day traverse of Antarctica. Measures consisted of preexpedition personality assessments; expedition weekly ratings of individual and team status and work performance; postexpedition semistructured interview. Both participants scored relatively highest on the Multidimensional Personality Questionnaire (MPQ) Absorption scale, the Personality Characteristics Inventory (PCI) Work and Positive Expressivity scales and lowest on the PCI Verbal Aggressiveness scale. One member reported sensed presence experiences, which served as an important motivating factor when fatigued or disappointed about daily progress. Enjoyment and awe of the environment were significant aspects of the daily trek and sources of psychological strength. Advantages of the co-equal dyad were evident in the cooperative nature of decision making and substantial similarities in approach to solving problems. Differences from the usual military command structure in decision-making processes and implications for planetary expeditions are discussed.
Publisher: SAGE Publications Inc
Keywords: Antarktis; kvinner; polarekspedisjoner; psykologi

Eight glacial cycles from an Antarctic ice core - Augustin, Laurent; Barbante, Carlo; Barnes, Piers R. F.; Marc Barnola, Jean; Bigler, Matthias; Castellano, Emiliano; Cattani, Olivier; Chappellaz, Jerome; Dahl-Jensen, Dorthe; Delmonte, Barbara; Dreyfus, Gabrielle; Durand, Gael; et al. (Nature, 2004)
The Antarctic Vostok ice core provided compelling evidence of the nature of climate, and of climate feedbacks, over the past 420,000 years. Marine records suggest that the amplitude of climate variability was smaller before that time, but such records are often poorly resolved. Moreover, it is not possible to infer the abundance of greenhouse gases in the atmosphere from marine records. Here we report the recovery of a deep ice core from Dome C, Antarctica, that provides a climate record for the past 740,000 years. For the four most recent glacial cycles, the data agree well with the record from Vostok. The earlier period, between 740,000 and 430,000 years ago, was characterized by less pronounced warmth in interglacial periods in Antarctica, but a higher proportion of each cycle was spent in the warm mode. The transition from glacial to interglacial conditions about 430,000 years ago (Termination V) resembles the transition into the present interglacial period in terms of the magnitude of change in temperatures and greenhouse gases, but there are significant differences in the patterns of change. The interglacial stage following Termination V was exceptionally long—28,000 years compared to, for example, the 12,000 years recorded so far in the present interglacial period. Given the similarities between this earlier warm period and today, our results may imply that without human intervention, a climate similar to the present one would extend well into the future.
Keywords: Antarktis; klimagasser; paleoklimatologi

Whaler's cross on Deception Island - Barr, Susan; Downie, Rod; Sánchez, Rodolfo (Polar Record, 2004)
The cemetery at Whalers Bay, Deception Island, was the largest in the Antarctic prior to being partially buried and partially washed away during a volcanic eruption in 1969. In 2002 a wooden cross at Argentina's Decepción Station was identified as being that of the Norwegian whaler Peder Knapstad. It was removed, secured in a base, and re-erected at Whalers Bay.
Edition: 2004/01/19 Publisher: Cambridge University Press
Keywords: Antarktis; Deceptionøya; Sørishavet; kulturminneforvaltning; kulturminner

Interannual controls on Weddell Sea surface water fCO2 during the autumn–winter transition phase - Bellerby, Richard G.J.; Hoppema, Mario; Fahrbach, Eberhard; de Baar, Hein J.W.; Stoll, Michel H.C. (Deep Sea Research Part I: Oceanographic Research Papers, 2004)
The fugacity of carbon dioxide (fCO2) of the surface waters of the Weddell Sea along the prime meridian has been described for the austral autumn in 1996 and 1998. For individual years, fCO2 has a strong linear relationship with sea surface temperature, although the relationships cannot be reconciled to provide an interannually consistent algorithm for remotely sensed assessment of fCO2. However, from the assumption that Weddell Sea surface water has a single end member (upwelled Warm Deep Water) we have determined the relative contributions of heating, ice-melt, and biological activity on fCO2. A breakdown of the controls shows that the measured annual fCO2 distributions can be recreated for both transects by adjusting solely for thermodynamic forcing, and model adjustments for salinity are small except in regions of significant upwelling during 1998. The incorporation of nitrate utilisation into the model results in a general and significant underestimation of fCO2. This runs contrary to the earlier findings of Sabine and Key (Mar. Chem. 60 (1998) 95) in the Southern Ocean although it is consistent with models in the area (Louanchi et al., Deep-Sea Res. I 48 (2001) 1581). A major caveat to these findings is the significant departure of the thermodynamic model and a tightening of the nitrate-adjusted model in 1998 in areas with deeper mixing in the southern Weddell Sea. We propose that there are two reasons for the discrepancies in our model: the source waters are not as homogenous as the model assumes; and there are geographical and seasonal variations of CO2 exchange with the atmosphere and the input of inorganic carbon and nitrate from below the mixed layer resulting in imbalances in the mixed layer concentration ratios.
Keywords: Sørishavet; Weddellhavet; karbon syklus; karbondioksid; marin biologi; marin kjemi; oseanografi

Two new Antarctic stegocephalid (Amphipoda: Stegocephalidae: Stegocephalinae) species, with implications for the phylogeny and classification of the two genera Pseudo and Schellenbergia - Berge, Jørgen; Vader, Wim (ANDEEP (Antarctic benthic DEEP-sea) biodiversity: colonization history and recent community patterns: a tribute to Howard L. Sanders, 2004)
Descriptions and figures of two new species of the genus Pseudo Berge & Vader, 2001 (Stegocephalidae: Stegocephalinae) are presented, but the two species are not given formal scientific names due to lack of material (both are only known by a single specimen each). However, the two new species have a significant impact on the classification and proposed phylogeny of the subfamily, as the two genera Pseudo Berge & Vader, 2001 and Schellenbergia Berge & Vader, 2001 now have to be considered synonymous. Pseudo is selected as the senior synonym. A discussion of the relationships among the genera of the subfamily Stegocephalinae is provided.
Keywords: Sørishavet; amfipoder; fylogenetikk; taksonomi; zoologi

A survey of amphipod associates of sea urchins, with description of new species in the genera Lepidepecreella (Lysianassoidea: lepidepecreellid group) and Notopoma (Photoidea: Ischyroceridae) from Antarctic cidarids - Berge, Jørgen; Vader, Wim; Lockhart, Susanne (ANDEEP (Antarctic benthic DEEP-sea) biodiversity: colonization history and recent community patterns: a tribute to Howard L. Sanders, 2004)
The known associations between amphipods and echinoids are listed, separated into five different categories depending upon the nature of the associations. The new species Lepidepecreella andeep, found attached around the mouth of the cidarid sea urchin Aporocidaris antarctica, is described, as well as the new species Notopoma cidaridis. The tubes of the latter were found attached to the spines of the cidarid sea urchin Rhynchocidaris triplopora. These cases represent the first associations reported between amphipods and echinoids in the Antarctic. A key to both genera is provided.
Keywords: Sørishavet; Weddellhavet; amfipoder; krepsdyr; pigghuder; sjøpiggsvin; taksonomi; zoologi

Flytende fabrikker – de norske hvalkokeriene - Bernhardt, Pernille Brastad (Fabrikken, 2004)
Keywords: Nordmenn; Sørishavet; arbeidsforhold; historie; hvalfangstindustri; hvalindustri; hvalkokerier; kulturhistorie; pelagisk; sjøfolk

Numerical simulation of three-dimensional, transient snow drifting around a cube - Beyers, Meiring; Sundsbø, Per Arne; Harms, Thomas M. (Journal of Wind Engineering and Industrial Aerodynamics, 2004)
This paper presents the results of the numerical simulation of drifting snow surrounding a simple 2m cubicle structure. These results are compared and verified against data from snow drifting experimental tests carried out at SANAE IV research station, Antarctica, during the summer research period of January 2002. In addition to the snow drifting field observations, wind profile data were also obtained from cup-type anemometers mounted on a 6m wind mast. These data were employed to derive the characteristic surface roughness, shear velocity and approaching wind profile functions. The present work numerically simulates a transient three-dimensional turbulent viscous flow in an Eulerian coordinate frame including snow advection. A modified turbulent wall law is employed that accounts for the effects of snow saltation on the effective aerodynamic surface roughness. The numerical simulation employed the commercial CFD code, FLOW-3D, with additional user Fortran coding added to model the snow entrainment, subsequent accumulation or erosion of snow as well as temporal snow surface changes. The snow accumulation and erosion model is presented and discussed. The snow accumulation predicted by this numerical simulation compares favourably with the experimental results obtained from the Antarctica field testing.
Keywords: Antarktis; forskningsstasjoner; geofysikk; ingeniørvitenskap; mekanikk; numerisk modellering

På hvalfangst under sovjetstjernen - Børresen, Dag Ingemar (Arbeiderhistorie, 2004)
Keywords: Nordmenn; Norge; Sørishavet; arbeiderbevegelse; arbeidsforhold; historie; hvalfangst; pelagisk; sjøfolk

Slope failure dynamics and impacts from seafloor and shallow sub-seafloor geophysical data: case studies from the COSTA project - Canals, M.; Lastras, G.; Urgeles, R.; Casamor, J.L.; Mienert, Jürgen; Cattaneo, A.; De Batist, M.; Haflidason, Haflidi; Imbo, Y.; Laberg, J.S.; Locat, J.; Long, D.; et al. (COSTA - Continental Slope Stability, 2004)
Holocene and slightly pre-Holocene submarine landslide are found both in high-latitude glacial-dominated margins and in lower latitude, river-dominated margins. This paper constitutes a major assessment on some of the best-studied submarine instabilities in the world. We review and update from original data and literature reports the current state of knowledge of Storegga, Traenadjupet and Finneidfjord slides from the mid-Norwegian margin, Afen Slide from the Faeroe-Shetland Channel, BIG'95 Slide and Central Adriatic Deformation Belt (CADEB) from continental slope and inner continental shelf settings off the Ebro and Po rivers in the Mediterranean Sea, Canary Slide west of the westernmost, youngest Canary Islands and Gebra Slide off the northern tip of the Antarctic Peninsula in the southern hemisphere, i.e. those studied in the Continental Slope Stability (COSTA) project. The investigated slides range in size from the gigantic 90,000 km2 and almost 3000 km3 Storegga Slide to the tiny 1 km2 and 0.001 km3 Finneidfjord Slide. Not only do individual submarine landslides rarely involve processes precisely fitting with pre-established categories, mostly based on subaerial research, but also they display complex mechanical behaviors within the elastic and plastic fields. Individual events can involve simultaneous or successive vertical to translational movements including block detachment, block gliding, debris flow, mud flow and turbidity currents. The need for an in-depth revision of the classification criteria, and eventually for a new classification system, based on the new imaging capabilities provided by modern techniques, is more than obvious. We suggest a new system, which, for the moment, is restricted to debris flows and debris avalanches. Volume calculation methods are critically reviewed and the relations between some key geomorphic parameters are established for the selected slides. The assumed volume missing from scar areas does not necessarily match the actual volume of sediment remobilised by an individual event since in situ sediment can be remoulded and eventually incorporated during the slide downslope journey. CADEB, a shore-parallel prodelta detached from its source, is the exception to the good correlation found between across slope width and alongslope length with slide area. Height drop measured from the headwall upper rim to its foot correlates with the debris deposit maximum thickness unless the slide moves into restricted areas, which prevent farther forward expansion of the deposit, such as Gebra and BIG'95. In such cases, “over-thickened” deposits are found. A particularly loose and fluid behavior can be deduced for slides showing an “over-thinned” character, such as the Canary Slide that traveled 600 km. Scar areas and slip planes have been investigated with particular emphasis. Although slide headwalls might present locally steep gradients (up to 23° for Storegga Slide), the slope gradients of both the failed segment margins and the main slip planes are very low (max. 2° and usually around 1° and less). An exception is the Finneidfjord Slide (20°–<5°) that occurred in 1996 because of a combination of climatic and anthropogenic factors leading to excess pore pressure and failure. Mechanically distinct, low permeable clayey “weak layers” often correspond to slip planes beyond the slide headwall. Since not only formation of these “weak layers” but also sedimentation rates are climatically controlled, we can state that slide pre-conditioning is climatically driven too. Run-out distances reflect the degree of disintegration of the failed mass of sediment, the total volume of initially failed material and transport mechanisms, including hydroplanning. Commonly, specific run-outs could be attributed to distinct elements, such as cohesive blocks and looser matrix, as nicely illustrated by the BIG'95 Slide. Total run-outs usually correspond to matrix run-outs since the coarser elements tend to rest at shorter distances. Outrunner blocks are, finally, a very common feature proving the ability of those elements to glide over long distances with independence of the rest of the failed mass. In addition to pre-conditioning factors related to geological setting and sedimentation conditions, a final trigger is required for submarine landslides to take place, which is most often assumed to be an earthquake. In high latitude margins, earthquake magnitude intensification because of post-glacial isostatic rebound has likely played a major role in triggering landslides. Although it cannot be totally ruled out, there is little proof, at least amongst the COSTA slides, that gas hydrate destabilisation or other processes linked to the presence of shallow gas have acted as final triggers.
Keywords: Antarktis; batymetri; geofysikk; marin geologi

The distribution and speciation of iron along 6°E in the Southern Ocean - Croot, Peter L.; Andersson, Karen; Öztürk, Murat; Turner, David R. (The SWEDARP 1997/98 Expedition, 2004)
The distribution and speciation of iron was determined along a transect in the eastern Atlantic sector (6°E) of the Southern Ocean during a collaborative Scandinavian/South African Antarctic cruise conducted in late austral summer (December 1997/January 1998). Elevated concentrations of dissolved iron (>0.4nM) were found at 60°S in the vicinity of the Spring Ice Edge (SIE) in tandem with a phytoplankton bloom, chiefly dominated by Phaeocystis sp. This bloom had developed rapidly after the loss of the seasonal sea ice cover. The iron that fuelled this bloom was mostly likely derived from sea ice melt. In the Winter Ice Edge (WIE), around 55°S, dissolved iron concentrations were low (<0.2nM) and corresponded to lower biological productivity, biomass. In the Antarctic Polar Front, at approximately 50°S, a vertical profile of dissolved iron showed low concentrations (<0.2nM); however, a surface survey showed higher concentrations (1–3nM), and considerable patchiness in this dynamic frontal region. The chemical speciation of iron was dominated by organic complexation throughout the study region. Organic iron-complexing ligands ([L]) ranged from 0.9 to 3.0nM Fe equivalents, with complex stability logKFeL′=21.4–23.5. Estimated concentrations of inorganic iron (Fe′) ranged from 0.03 to 0.79pM, with the highest values found in the Phaeocystis bloom in the SIE. A vertical profile of iron-complexing ligands in the WIE showed a maximum consistent with a biological source for ligand production and near surface minimum possibly consistent with loss via photodecomposition. This work further confirms the role iron that has in the Southern Ocean in limiting primary productivity.
Keywords: Bouvetøya; Sørishavet; biogeokjemi; marin kjemi; oseanografi

Diesel oil and PCB-degrading psychrotrophic bacteria isolated from Antarctic seawaters (Terra Nova Bay, Ross Sea) - De Domenico, Maria; Lo Giudice, Angelina; Michaud, Luigi; Saitta, Marcello; Bruni, Vivia (Polar Research, 2004)
Fifty-seven Antarctic marine bacteria were examined for their ability to degrade commercial diesel oil as the sole organic substrate at both 4 °C and 20 °C. Based on the preliminary screening, two isolates (B11 and B15) with high capacity to degrade diesel oil were selected and their biodegradation effi ciency was quantifi ed by gas chromatographic analysis. As expected for psychrotrophs, diesel oil biodegradation was slower at 4 °C than at 20 °C. The two strains also mineralized the C28 n-paraffi n octacosane at 20 °C and polychlorinated biphenyls (PCBs) at 4 °C and 20 °C.
Keywords: Rosshavet; Sørishavet; bakterier; biologisk nedbrytning; kjemi; marin biologi; marin økologi

Fiskerier i Antarktis (6.4) - Dommasnes, Are; Iversen, Svein A; Løbach, Terje (Havets ressurser 2004 (Fisken og havet : Særnummer), 2004)
Keywords: Antarktis; fangst; fiskeindustri; fiskeriforskning; krill; ressurser

Evaluating global ocean carbon models: The importance of realistic physics - Doney, Scott C; Lindsay, Keith; Caldeira, Ken; Campin, J.-M.; Drange, Helge; Dutay, Jean-Claude; Follows, Michael; Gao, Yongqi; Gnanadesikan, Anand; Gruber, N; Ishida, Akio; Joos, Fortunat; et al. (Global Biogeochemical Cycles, 2004)
A suite of standard ocean hydrographic and circulation metrics are applied to the equilibrium physical solutions from 13 global carbon models participating in phase 2 of the Ocean Carbon-cycle Model Intercomparison Project (OCMIP-2). Model-data comparisons are presented for sea surface temperature and salinity, seasonal mixed layer depth, meridional heat and freshwater transport, 3-D hydrographic fields, and meridional overturning. Considerable variation exists among the OCMIP-2 simulations, with some of the solutions falling noticeably outside available observational constraints. For some cases, model-model and model-data differences can be related to variations in surface forcing, subgrid-scale parameterizations, and model architecture. These errors in the physical metrics point to significant problems in the underlying model representations of ocean transport and dynamics, problems that directly affect the OCMIP predicted ocean tracer and carbon cycle variables (e.g., air-sea CO2 flux, chlorofluorocarbon and anthropogenic CO2 uptake, and export production). A substantial fraction of the large model-model ranges in OCMIP-2 biogeochemical fields (±25–40%) represents the propagation of known errors in model physics. Therefore the model-model spread likely overstates the uncertainty in our current understanding of the ocean carbon system, particularly for transport-dominated fields such as the historical uptake of anthropogenic CO2. A full error assessment, however, would need to account for additional sources of uncertainty such as more complex biological-chemical-physical interactions, biases arising from poorly resolved or neglected physical processes, and climate change.
Keywords: Sørishavet; biogeokjemi; hydrografi; karbon syklus; karbondioksid; klimaendringer; oseanografi

"Havfruer" og sjøkvinner - Elstad, Åsa (Kystkvinner i Norge, 2004)
Keywords: Norge; Sørishavet; Vestfold; hvalfangst; kulturhistorie; pelagisk

Antarktis: gamle gneiser og spektakulære granitter - Engvik, Ane K; Elvevold, Synnøve (Geo: energi & ressurser, 2004)
Keywords: Antarktis; Dronning Maud Land; geologi

Ice shelf water overflow and bottom water formation in the southern Weddell Sea - Foldvik, Arne; Gammelsrød, Tor; Østerhus, Svein; Fahrbach, Eberhard; Rohardt, Gerd; Schröder, Michael; Nicholls, Keith William; Padman, Laurie; Woodgate, Rebecca A. (Journal of Geophysical Research: Oceans, 2004)
Cold shelf waters flowing out of the Filchner Depression in the southern Weddell Sea make a significant contribution to the production of Weddell Sea Bottom Water (WSBW), a precursor to Antarctic Bottom Water (AABW). We use all available current meter records from the region to calculate the flux of cold water (<−1.9°C) over the sill at the northern end of the Filchner Depression (1.6 ± 0.5 Sv), and to determine its fate. The estimated fluxes and mixing rates imply a rate of WSBW formation (referenced to −0.8°C) of 4.3 ± 1.4 Sv. We identify three pathways for the cold shelf waters to enter the deep Weddell Sea circulation. One path involves flow constrained to follow the shelf break. The other two paths are down the continental slope, resulting from the cold dense water being steered northward by prominent ridges that cross the continental slope near 36°W and 37°W. Mooring data indicate that the deep plumes can retain their core characteristics to depths greater than 2000 m. Probably aided by thermobaricity, the plume water at this depth can flow at a speed approaching 1 m s−1, implying that the flow is occasionally supercritical. We postulate that such supercriticality acts to limit mixing between the plume and its environment. The transition from supercritical to slower, more uniform flow is associated with very efficient mixing, probably as a result of hydraulic jumps.
Keywords: Sørishavet; Weddellhavet; havstrømmer; isshelf; oseanografi

The effect of diapycnal mixing on the ventilation and CFC-11 uptake in the Southern Ocean - Gao, Yongqi; Drange, Helge (Advances in Atmospheric Sciences, 2004)
The Miami Isopycnic Coordinate Ocean Model (MICOM) is used to investigate the effect of diapycnal mixing on the oceanic uptake of CFC-11 and the ventilation of the surface waters in the Southern Ocean (south of 45°S). Three model experiments are performed: one with a diapycnal mixing coefficientKd (m2 s−1) of 2 × 10−7/N (Expt. 1), one withKd = 0 (Expt. 2), and one withKd = 5 × 10−8/N (Expt. 3),N (s−1) is the Brunt-Väisälä frequency. The model simulations indicate that the observed vertical distribution of CFC-11 along 88°W (prime meridian at 0°E) in the Southern Ocean is caused by local ventilation of the surface waters and westward-directed (eastward-directed) isopycnic transport and mixing from deeply ventilated waters in the Weddell Sea region. It is found that at the end of 1997, the simulated net ocean uptake of CFC-11 in Expt. 2 is 25% below that of Expt. 1. The decreased uptake of CFC-11 in the Southern Ocean accounts for 80% of this difference. Furthermore, Expts. 2 and 3 yield far more realistic vertical distributions of the ventilated CFC-waters than Expt. 1. The experiments clearly highlight the sensitivity of the Southern Ocean surface water ventilation to the distribution and thickness of the simulated mixed layer. It is argued that inclusion of CFCs in coupled climate models could be used as a test-bed for evaluating the decadal-scale ocean uptake of heat and CO2.
Keywords: Sørishavet; geofysikk; klimamodeller; klimatologi; oseanografi; strømmodeller

Effect of solar radiation and the subsequent dark periods on two newly isolated and characterized Antarctic marine bacteria - Hernández, Edgardo A; Ferreyra, Gustavo A; Mac Cormack, Walter P (Polar Research, 2004)
Two strains of psychrotolerant Antarctic marine bacteria were isolated and characterized using biochemical and molecular techniques. Sequencing of 16S rRNA gene showed that UVvi strain belongs to the genus Arthrobacter whereas UVps strain is related to the Flexibacter-Cytophaga-Bacteroides (FCB) group. Response of the strains to solar radiation was studied during the summer of 1999 in Potter Cove, near Jubany station (South Shetland Island, Antarctica). The effect of photosynthetically available radiation (PAR, 400-700 nm), ultraviolet-A (UV-A, 320-400 nm) and ultraviolet-B radiation (UV-B, 280-320 nm) on cell viability was studied using mixed cultures in quartz bottles covered with interferential filters and exposed to solar radiation. In all experiments, four treatments were used: dark (with light screened out), PAR (with UV radiation screened out), PAR+UV-A (UV-B screened out) and PAR+UV-A+UV-B. Under the assayed conditions, PAR+UV-A and PAR+UV-A+UV-B radiation showed similar negative effects on the viability of the studied strains. However, at the end of the exposure time, mortality values in PAR+UV-A+UV-B treatments were higher than those observed under PAR+UV-A treatments. In both PAR+UV-A and PAR+UV-A+UV-B treatments we observed high levels of hydrogen peroxide compared with the dark control. The Arthrobacter UVvi strain showed significant recovery in dark conditions after exposure to the PAR+UV-A but not after the PAR+UV-A+UV-B treatment. This strain proved to be more resistant to UV radiation than the FCB group-related UVps strain. The results showed that UV radiation has a deleterious effect on these Antarctic marine bacteria and also revealed that the analysed components of the Antarctic bacterioplankton may have different responses when they are exposed to the same irradiance conditions.
Keywords: Sørishavet; UV-stråling; bakterier; biokjemi; marin biologi; ozonlaget; plankton; ultrafiolett stråling

Seasonal ventilation of the cavity beneath Filchner-Ronne Ice Shelf simulated with an isopycnic coordinate ocean model - Jenkins, Adrian; Holland, David M.; Nicholls, Keith W.; Schröder, Michael; Østerhus, Svein (Journal of Geophysical Research: Oceans, 2004)
The ocean cavity beneath Filchner-Ronne Ice Shelf is observed to respond to the seasonal cycle of water mass production on the continental shelf of the southern Weddell Sea. Here we use a numerical model to investigate the propagation of newly formed shelf waters into the cavity. We find that the model reproduces the most distinctive features of the observed seasonality and offers a plausible explanation for those features. The most saline shelf waters are produced in the far west, where the inflow to the cavity peaks twice each year. The major peak occurs during the short period around midwinter when convection reaches full depth and the densest waters are generated. Once the surface density starts to decline, dynamic adjustment of the restratified water column leads to a gradual fall in the salinity at depth and a secondary peak in the inflow that occurs in summer at the western coast. Beneath the ice shelf the arrival of the wintertime inflow at the instrumented sites is accompanied by a rapid warming, while the slower decline in the inflow leads to a more gradual cooling. Water brought in by the secondary, summer peak flows mainly to the eastern parts of the cavity. Here the seasonality is suppressed because the new inflows mix with older waters that recirculate within a topographic depression. This pooling of waters in the east, where the primary outflow of Ice Shelf Water is generated, dampens the impact of seasonality on the local production of Weddell Sea Bottom Water.
Keywords: Antarktis; Weddellhavet; geofysikk; oseanografi

Accumulation variability derived from an ice core from coastal Dronning Maud Land, Antarctica - Kaczmarska, Marzena; Isaksson, Elisabeth; Karlöf, Lars; Winther, Jan-Gunnar; Kohler, Jack; Godtliebsen, Fred; Olsen, Lena Ringstad; Hofstede, Coen M.; Van Den Broeke, Michiel R.; Van De Wal, Roderik S. W.; Gundestrup, Niels (Annals of Glaciology, 2004)
A 100 m long ice core was retrieved from the coastal area of Dronning Maud Land (DML), Antarctica, in the 2000/01 austral summer. The core was dated to AD 1737 by identification of volcanic horizons in dielectrical profiling and electrical conductivity measurement records in combination with seasonal layer counting from high-resolution oxygen isotope (δ18O) data. A mean long-term accumulation rate of 0.29 ma–1w.e. was derived from the high-resolution δ18O record as well as accumulation rates during periods in between the identified volcanic horizons. A statistically significant decrease in accumulation was found from about 1920 to the present. A comparison with other coastal ice cores from DML suggests that this is a regional pattern.
Publisher: Cambridge University Press
Keywords: Dronning Maud Land; geofysikk; glasiologi; iskjerner; klimatologi

Analyses of firn gas samples from Dronning Maud Land, Antarctica: Study of nonmethane hydrocarbons and methyl chloride - Kaspers, Karsten Adrian; van de Wal, Roderick S. W.; de Gouw, Joost; Hofstede, Coen; van den Broeke, Michiel Roland; van der Veen, Carina; Neubert, Rolf; Meijer, Harro A. J.; Brenninkmeijer, Carl; Karlöf, Lars; Winther, Jan-Gunnar (Journal of Geophysical Research: Atmospheres, 2004)
Firn air was sampled on the Antarctic plateau in Dronning Maud Land (DML), during the Norwegian Antarctic Research Expedition (NARE) 2000/2001. In this paper, we describe the analyses for methyl chloride and nonmethane hydrocarbons (NMHCs) in these firn air samples. For the first time, the NMHCs ethane, propane, and acetylene have been measured in Antarctic firn air, and concentration profiles for these gases have been derived. A one-dimensional numerical firn air diffusion model was used to interpret the measured profiles and to derive atmospheric concentrations as a function of time. The atmospheric trends we derived for the NMHC and methyl chloride at DML cover the period from 1975 to 2000. Methyl chloride shows a decreasing trend of 1.2 ± 0.6 ppt per year (annual mean concentration 548 ± 32 ppt). For ethane we found an increasing trend of 1.6 ± 0.6 ppt per year (annual mean concentration 241 ± 12 ppt). The concentrations of propane and acetylene appear to be constant over the period 1975–2000, with annual mean concentrations of 30 ± 4 ppt for propane and 24 ± 2 ppt for acetylene.
Keywords: Dronning Maud Land; NARE 2000/01; atmosfæren; gasskonsentrasjoner; geofysikk

Seasonal cycles of nonmethane hydrocarbons and methyl chloride, as derived from firn air from Dronning Maud Land, Antarctica - Kaspers, Karsten Adrian; van de Wal, Roderick S W; de Gouw, Joost; Hofstede, Coen; van den Broeke, Michiel; Reijmer, Carleen; van der Veen, Carina; Neubert, Rolf; Meijer, Harro A J; Brenninkmeijer, Carl; Karlöf, Lars; Winther, Jan-Gunnar (Journal of Geophysical Research: Atmospheres, 2004)
This paper presents atmospheric concentrations of ethane, propane, acetylene, and methyl chloride, inferred from firn air by using a numerical one-dimensional firn diffusion model. The firn air was collected on the Antarctic plateau in Dronning Maud Land during the Norwegian Antarctic Research Expedition (NARE) 2000/2001. The influences of seasonal variations in temperature and pressure and the variation in accumulation rate were studied and are not negligible, but appear to cancel each other out if all variability is taken into account. This paper also demonstrates that firn air from the uppermost firn layer (30 m) can be used to derive seasonal cycles of these trace gases, without needing a year-round facility. These cycles display higher atmospheric mixing ratios during the Antarctic winter and lower atmospheric mixing ratios in summer. The cycles for the year 2000 show amplitudes of 140 ± 25 ppt for ethane, 30 ± 10 ppt for propane, 24 ± 6 ppt for acetylene, and 40 ± 20 ppt for methyl chloride. For ethane and propane the amplitudes and months of maximum atmospheric concentration (phase) are in reasonable agreement with year-round measurements at the South Pole and Baring Head (New Zealand). The amplitudes for methyl chloride and acetylene are significantly greater than seen in year-round measurements at the South Pole and at Neumayer (Antarctica), although the phase is in line. While biomass burning and removal by OH radicals can partially explain these large amplitudes, the exact cause still remains unclear for methyl chloride and acetylene.
Keywords: Dronning Maud Land; NARE 2000/01; atmosfæren; gasskonsentrasjoner; geofysikk; meteorologi

Input of Glaciomarine Sediments along the East Antarctic Continental Margin; Depositional Processes on the Cosmonaut Sea Continental Slope and Rise and a Regional Acoustic Stratigraphic Correlation from 40° W to 80° E - Kuvaas, Berit; Kristoffersen, Yngve; Guseva, J.; Leitchenkov, German; Gandjukhin, , V; Kudryavtsev, Genadii (Marine Geophysical Researches, 2004)
Multichannel seismic reflection data from the Cosmonaut Sea margin of East Antarctica have been interpreted in terms of depositional processes in the continental slope and rise area. A major sediment lens is present below the upper continental rise along the entire Cosmonaut Sea margin. The lens probably consists of sediments supplied from the shelf and slope, being constantly reworked by westward flowing bottom currents, which redeposited the sediments into a large scale drift deposit prior to the main glaciogenic input along the margin. High-relief semicircular or elongated depositional structures are also found on the upper continental rise stratigraphically above the regional sediment lens, and were deposited by the combined influence of downslope and alongslope sediment transport. On the lower continental rise, large-scale sediment bodies extend perpendicular to the continental margin and were deposited as a result of downslope turbidity transport and westward flowing bottom currents after initiation of glacigenic input to the slope and rise. We compare the seismostratigraphic signatures along the continental margin segments of the adjacent Riiser Larsen Sea, the Weddell Sea and the Prydz Bay/Cooperation Sea, focussing on indications that may be interpreted as a preglacial-glaciomarine transition in the depositional environment. We suggest that earliest glaciogenic input to the continental slope and rise occurred in the Prydz Bay and possibly in the Weddell Sea. At a later stage, an intensification of the oceanic circulation pattern occurred, resulting in the deposition of the regional plastered drift deposit along the Cosmonaut Sea margin, as well as the initiation of large drift deposits in the Cooperation Sea. At an even later stage, possibly in the middle Miocene, glacial advances across the continental shelf were initiated along the Cosmonaut Sea and the Riiser Larsen Sea continental margins.
Keywords: Sørishavet; Weddellhavet; marin geofysikk; marin geologi; oseanografi

Seismic expression of glaciomarine deposits in the eastern Riiser Larsen Sea, Antarctica - Kuvaas, Berit; Kristoffersen, Yngve; Leitchenkov, German; Guseva, J.; Gandjukhin, V. (Marine Geology, 2004)
By studying multichannel seismic data across the continental slope and rise of the eastern Riiser Larsen Sea and through a comparison with other East Antarctic continental margins, the base of the glaciomarine deposits has been traced in this area. The seismic data reveal the presence of large channel-levee complexes as well as multiple types of contourite accumulations. Downslope and alonglope processes thus interacted in forming the glaciomarine deposits. The deposits are attributed to the advances of ice sheet, delivering huge amounts of sediment to the shelf edge and upper slope during glacial maxima. Oversteepening and instability generated down-slope turbidity currents forming channel–levee complexes whereas the contourite accumulations were probably mostly formed during interglacials. The spatial distribution of the current controlled deposits indicates that bottom currents flow along the western slope of the Gunnerus Ridge.
Keywords: Dronning Maud Land; Sørishavet; marin geologi; oseanografi; seismologi

Evaluation of ocean carbon cycle models with data-based metrics - Matsumoto, K; Sarmiento, J L; Key, R M; Aumont, O; Bullister, J L; Caldeira, K; Campin, J.-M.; Doney, S C; Drange, H; Dutay, J.-C.; Follows, M; Gao, Y; et al. (Geophysical Research Letters, 2004)
New radiocarbon and chlorofluorocarbon-11 data from the World Ocean Circulation Experiment are used to assess a suite of 19 ocean carbon cycle models. We use the distributions and inventories of these tracers as quantitative metrics of model skill and find that only about a quarter of the suite is consistent with the new data-based metrics. This should serve as a warning bell to the larger community that not all is well with current generation of ocean carbon cycle models. At the same time, this highlights the danger in simply using the available models to represent the state-of-the-art modeling without considering the credibility of each model.

Pole-to-pole validation of Envisat GOMOS ozone profiles using data from ground-based and balloon sonde measurements - Meijer, Yasjka; Swart, Daan P J; Allaart, M; Andersen, S B; Bodeker, G; Boyd, I; Braathen, Geir; Calisesi, Yasmine; Claude, H; Dorokhov, Valery; von der Gathen, P; Gil, M; et al. (Journal of Geophysical Research: Atmospheres, 2004)
In March 2002 the European Space Agency (ESA) launched the polar-orbiting environmental satellite Envisat. One of its nine instruments is the Global Ozone Monitoring by Occultation of Stars (GOMOS) instrument, which is a medium-resolution stellar occultation spectrometer measuring vertical profiles of ozone. In the first year after launch a large group of scientists performed additional measurements and validation activities to assess the quality of Envisat observations. In this paper, we present validation results of GOMOS ozone profiles from comparisons to microwave radiometer, balloon ozonesonde, and lidar measurements worldwide. Thirty-one instruments/launch sites at twenty-five stations ranging from the Arctic to the Antarctic joined in this activity. We identified 6747 collocated observations that were performed within an 800-km radius and a maximum 20-hour time difference of a satellite observation, for the period between 1 July 2002 and 1 April 2003. The GOMOS data analyzed here have been generated with a prototype processor that corresponds to version 4.02 of the operational GOMOS processor. The GOMOS data initially contained many obviously unrealistic values, most of which were successfully removed by imposing data quality criteria. Analyzing the effect of these criteria indicated, among other things, that for some specific stars, only less than 10% of their occultations yield an acceptable profile. The total number of useful collocated observations was reduced to 2502 because of GOMOS data unavailability, the imposed data quality criteria, and lack of altitude overlap. These collocated profiles were compared, and the results were analyzed for possible dependencies on several geophysical (e.g., latitude) and GOMOS observational (e.g., star characteristics) parameters. We find that GOMOS data quality is strongly dependent on the illumination of the limb through which the star is observed. Data measured under bright limb conditions, and to a certain extent also in twilight limb, should be used with caution, as their usability is doubtful. In dark limb the GOMOS data agree very well with the correlative data, and between 14- and 64-km altitude their differences only show a small (2.5–7.5%) insignificant negative bias with a standard deviation of 11–16% (19–63 km). This conclusion was demonstrated to be independent of the star temperature and magnitude and the latitudinal region of the GOMOS observation, with the exception of a slightly larger bias in the polar regions at altitudes between 35 and 45 km.
Keywords: Antarktis; fjernmåling; meteorologi; målinger; ozonlaget; polarområdene; stratosfæren

Circulation and water masses beneath the northern Ronne Ice Shelf, Antarctica - Nicholls, Keith W.; Makinson, Keith; Østerhus, Svein (Journal of Geophysical Research: Oceans, 2004)
We present oceanographic data from beneath the northern Ronne Ice Shelf. The data were collected during the austral summer of 2002–2003 from four sites located near the ice front in the Ronne Depression. They consist of conductivity-temperature-depth (CTD) profiles and time series from moored instruments that vary in length from 9 to 20 weeks. A strong, tidally modulated inflow of relatively fresh water was found at the eastern margin of the Ronne Depression. This low-density inflow powers high basal melt rates that are responsible for a substantially thinned area of ice shelf. A northward flow of Ice Shelf Water along the western margin of the depression (the Antarctic Peninsula coast) was inferred from the CTD data. From the new CTD and current meter data, and from published results from cruises along the ice front, we suggest that the flows at the margins of the Ronne Depression establish east-west density gradients that drive an anticyclonic circulation within the depression. The barotropic component of the circulation forms a gyre of strength 5 × 105 m3 s−1 and occupies a bowl in the field of water column thickness in the northern portion of the depression. All water masses sampled had temperatures below the surface freezing point and are therefore classified as Ice Shelf Water. The relatively complex nature of the oceanographic regime in the Ronne Depression is overlain by a seasonal variability that is hinted at by the available time series, probably explaining the apparent absence of inflowing HSSW at the time of the measurements.
Keywords: Antarktis; geofysikk; isfront; isshelf; oseanografi; vannmasser

Interannual variability and ventilation timescales in the ocean cavity beneath Filchner-Ronne Ice Shelf, Antarctica - Nicholls, Keith William; Østerhus, Svein (Journal of Geophysical Research: Oceans, 2004)
Multiyear time series of ocean current and temperatures from beneath Filchner-Ronne Ice Shelf, Antarctica, demonstrate both seasonal and interannual variability. The seasonal signal is visible at all measurement sites, although it was swamped for a 2-year period (1999–2001) when extraordinarily light sea-ice cover in the southern Weddell Sea during the 1997–1998 Austral summer caused an anomalously large pulse of High Salinity Shelf Water to flush beneath the ice shelf. The pulse was observed twice at an instrumented site near the Berkner Island coast, once on its way to the Filchner Depression and once after the signal had propagated around the depression and returned to the site as an anomalously large pulse of Ice Shelf Water. The timings of the signal allow an estimate of 24–30 months for the flushing timescales of the sub-ice shelf ocean cavity, indicating that the cavity is highly responsive to external forcing. A timescale for the full ventilation of the cavity of 4–5 years is obtained from the length of time the sub-ice shelf conditions take to return to their original state, a timescale significantly shorter than previous estimates.
Keywords: Antarktis; Weddellhavet; geofysikk; havstrømmer; oseanografi

Holocene climate in the Atlantic sector of the Southern Ocean: Controlled by insolation or oceanic circulation? - Nielsen, Simon Harder Holm; Koç, Nalân; Crosta, Xavier (Geology, 2004)
The Holocene climate of the Southern Ocean is not well understood, mainly because of the lack of high-resolution reconstructions of ocean surface properties. Here we present a 12,500-yr-long, decadal-scale record of Holocene sea-surface temperatures and sea- ice presence from the Polar Front of the East Atlantic Southern Ocean. The record shows gradual climate change, with no abrupt Neoglacial cooling, and an unprecedented late Holocene warming. The dominant forcing factor appears to be precessional insolation; Northern Hemisphere summer insolation correlates to at least the early to middle Holocene climate trend. Spectral analysis reveals centennial-scale cyclic climate changes with periods of 1220, 1070, 400, and 150 yr. The record shows good correlation to East Antarctic ice cores and to climate records from South Georgia and Bunger Oasis. However, the record shows out-of-phase behavior with regard to climate records from the western Antarctic Peninsula and the Peru-Chile Current; such behavior hints at a climatic divide through Patagonia, the Drake Passage, and between West and East Antarctica.
Keywords: Antarktis; Sørishavet; geologi; havis; klimaendringer; paleoklimatologi

Measurements of ice thickness and seabed topography under the Fimbul Ice Shelf, Dronning Maud Land, Antarctica - Nøst, Ole Anders (Journal of Geophysical Research: Oceans, 2004)
This paper presents results from seismic measurements of the ice and water column thickness of the Fimbul Ice Shelf in the northeastern Weddell Sea. Seismic reflection measurements were conducted at 183 stations covering most of the ice shelf. Seismic velocities in the ice were derived from refraction measurements at 12 stations, distributed evenly across the area, as well as from temperature and density data from the Fimbul Ice Shelf. Velocities in the water were derived from temperature and salinity data from beneath the Fimbul Ice Shelf. Ice thicknesses were found to vary between 160 m and 550 m with uncertainties up to ±10 m. Water column thicknesses up to 900 m were found within the central ice shelf cavity, and values exceed 2000 m where the ice shelf overhangs the continental slope. Uncertainties in water column thickness are estimated to be ±60 m, and are dominated by the uncertainties in the shape of the seabed. Ice draft and seabed elevation was derived from ice and water column thickness assuming hydrostatic pressure. The resulting map of seabed elevation and water column thickness suggests that the strong westward flowing coastal current will be steered under the ice shelf and thus drive a sub-ice-shelf flow. Warm Deep Water does not have direct access to the ice shelf cavity, while relatively cold coastal waters shallower than 500 m will interact closely with the Fimbul Ice Shelf.
Keywords: Sørishavet; Weddellhavet; geofysikk; havbunnen; isshelf; oseanografi

Additions and corrections to the Lichens of Antarctica and South Georgia - Øvstedal, Dag; Smith, Ronald I. Lewis (Cryptogamie, Mycologie, 2004)
The taxonomic listing given in Lichens of Antarctica and South Georgia (Øvstedal & Lewis Smith 2001) has been updated. 17 additional taxa of lichenised fungi are described, including several nomenclatural changes. 14 of these are considered as new records for the Antarctic and one is new to South Georgia. One is described as new to science.
https://sciencepress.mnhn.fr/sites/default/files/articles/pdf/cryptogamie-mycologie2004v25f4a2.pdf
Keywords: Antarktis; biogeografi; botanikk; lav; planter; taksonomi

Iron enrichment and photoreduction of iron under UV and PAR in the presence of hydroxycarboxylic acid: implications for phytoplankton growth in the Southern Ocean - Öztürk, Murat; Croot, Peter L.; Bertilsson, Stefan; Abrahamsson, Katarina; Karlson, Bengt; David, Roland; Fransson, Agneta; Sakshaug, Egil (The SWEDARP 1997/98 Expedition, 2004)
Iron(III) photoreduction and the responses of phytoplankton under ultraviolet (UV) and photosynthetically available radiation (PAR) were investigated with the presence of hydroxycarboxylic acid (glucaric acid (GA), a model compound for organic acids excreted by phytoplankton). The incubation experiments were carried out on board using seawater samples collected in the location of the winter ice edge (WIE) and the spring ice edge (SIE) of the Southern Ocean. In this paper, we focus on the results of experiment in WIE. Throughout the experiments, dissolved Fe(II), major nutrients and in vivo fluorescence were monitored regularly. In addition, Chl-a, POC/PON, cell densities of phytoplankton and bacteria, bacterial production, organic peroxide, hydrogen peroxide and total CO2 were measured. The results from the WIE show that iron enrichment had a substantial effect on phytoplankton growth rate. Fe(III) addition in the presence of GA (FeGA) gave higher Fe(II) concentration and higher growth rate of phytoplankton than those in controls. Our results suggest that hydroxycarboxylic acid had a significant chemical and biological impact. The presence of GA influenced iron photochemistry and iron availability to phytoplankton. Phytoplankton growth responses to iron enrichments in incubations under UV and PAR were completely dissimilar. It seems that FeGA addition prominently changes the harmful effect of UV on the phytoplankton population. This study provides preliminary information on how the photoreduction of iron(III) and the phytoplankton growth are affected by iron enrichment in the presence of hydroxycarboxylic acid.
Keywords: Sørishavet; biokjemi; fotosyntese; marin biologi; oseanografi; phytoplankton

FINAL Comprehensive Environmental Evaluation (CEE) for the upgrading of the Norwegian summer station Troll in Dronning Maud Land, Antarctica, to permanent station - Polarinstitutt, Norsk; Instituttet (Norwegian Polar Institute, 2004)
Keywords: Dronning Maud Land; forskningsstasjoner; miljøvern

The diatom Fragilariopsis cylindrus and its potential as an indicator species for cold water rather than for sea ice - Quillfeldt von, Cecilie Hellum (Vie et Milieu / Life & Environment, 2004)
The importance of the diatom Fragilariopsis cylindrus (Grunow) Krieger in Helmcke & Krieger in the Arctic and Antarctic is well known. It is used as an indicator of sea ice when the paleoenvironment is being described. It is often among the dominant taxa in different sea ice communities, sometimes making an important contribution to a subsequent phytoplankton growth when released by ice melt. However, it may also dominate phytoplankton blooms in areas never experiencing sea ice. The use of F. cylindrus as an indicator for reconstruction of palaeoceanographic conditions is assessed from literature records. Its potential as an indicator species for sea ice appears to vary from region to region, but it is a good indicator of cold water.
Keywords: Sørishavet; diatomeer; marin biologi; paleoseanografi; phytoplankton; polarområdene

Improved Seismic Stratigraphy of the Mesozoic Weddell Sea - Rogenhagen, Johannes; Jokat, Wilfried; Hinz, Karl; Kristoffersen, Yngve (Marine Geophysical Researches, 2004)
We present a compilation of more than 45,000 km of multichannel seismic data acquired in the last three decades in the Weddell Sea. In accordance with recent tectonic models and available drillhole information, a consistent stratigraphic model for depositional units W1–W5 is set up. In conjunction with existing aeromagnetic data, a chronostratigraphic timetable is compiled and units W1.5, W2 and W3 are tentatively dated to have ages of between 136 Ma and 114 Ma. The age of W3 is not well constrained, but might be younger than 114 Ma. The data indicate that the thickest sediments are present in the western and southern Weddell Sea. These areas formed the earliest basins in the Weddell Sea and so the distribution of Mesozoic sediments is in accordance with the tectonic development of the ocean basin. In terms of Cenozoic glacial sediments, the largest depocenters are situated in front of the Filchner–Ronne Shelf, i.e. at the Crary Fan, with a thickness of up to 3 km.
Keywords: Antarktis; Weddellhavet; geofysikk; oseanografi; seismologi; stratigrafi; tektonikk

Frazil ice formation in an ice shelf water plume - Smedsrud, Lars H.; Jenkins, Adrian (Journal of Geophysical Research: Oceans, 2004)
We present a model for the growth of frazil ice crystals and their accumulation as marine ice at the base of Antarctic ice shelves. The model describes the flow of buoyant water upward along the ice shelf base and includes the differential growth of a range of crystal sizes. Frazil ice formation starts when the rising plume becomes supercooled. Initially, the majority of crystals have a radius of ?0.3 mm and concentrations are below 0.1 g/L. Depending on the ice shelf slope, which controls the plume speed, frazil crystals increase in size and number. Typically, crystals up to 1.0 mm in radius are kept in suspension, and concentrations reach a maximum of 0.4 g/L. The frazil ice in suspension decreases the plume density and thus increases the plume speed. Larger crystals precipitate upward onto the ice shelf base first, with smaller crystals following as the plume slows down. In this way, marine ice is formed at rates of up to 4 m/yr in some places, consistent with areas of observed basal accumulation on Filchner-Ronne Ice Shelf. The plume continues below the ice shelf as long as it is buoyant. If the plume reaches the ice front, its rapid rise produces high supercooling and the ice crystals attain a radius of several millimeters before reaching the surface. Similar ice crystals have been trawled at depth north of Antarctic ice shelves, but otherwise no observations exist to verify these first predictions of ice crystal sizes and volumes.
Publisher: John Wiley & Sons, Ltd
Keywords: Antarktis; geofysikk; glasiologi; numerisk modellering; oseanografi

Ozone loss rates over the Arctic 2002/03 and Antarctic 2003 measured with the Match approach - Streibel, Martin; von der Gathen, P; Rex, M; Deckelmann, H; Harris, N; Braathen, G; Chipperfield, M; Millard, G; Reimer, E; Alfier, R; Allaart, M; Andersen, S; et al. (20th Quadrennial Ozone Symposium, 2004)
To improve our understanding of wintertime polar ozone losses, two ozonesonde Match campaigns were performed. The first one was carried out in the Arctic winter 2002/03. About 450 coordinated ozonesondes were launched from late November 2002 to March 2003. Temperatures low enough for the formation of polar stratospheric clouds (PSC) occurred already in the second half of November. At 475 K the Match analysis shows increasing ozone loss rates from early December until the second half of January with peaking loss rates of 35 ppbv/day. Afterwards the rate of ozone loss decreased and stopped after a month. Throughout the whole winter we find accumulated ozone loss of about 1.5 ppmv at the 500 K isentrope and approximately 60 DU in the total ozone column, which is about half of the maximum loss found in past winters. From June to October 2003 an Antarctic Match campaign was carried out for the first time. About 400 sondes were launched by 9 stations. Ozone loss rates of up to 75 ppbv/day were found inside the polar vortex at the 475 K potential temperature level during the first half of September. The timing of the fastest ozone loss coincides with the return of sunlight to the vortex after the Antarctic winter. During the whole time period temperatures were low enough for PSCs, including ice clouds, to form. Results for the potential temperature range between 400 K and 550 K will be presented.
Keywords: Antarktis; ozonlaget; polarområdene; stratosfæren

Light rather than iron controls photosynthate production and allocation in Southern Ocean phytoplankton populations during austral autumn - van Oijen, Tim; van Leeuwe, Maria A.; Granum, E.; Weissing, Franz J.; Bellerby, Richard G. J.; Gieskes, W. W. C.; de Baar, Hein J. W. (Journal of Plankton Research, 2004)
The role of iron and light in controlling photosynthate production and allocation in phytoplankton populations of the Atlantic sector of the Southern Ocean was investigated in April–May 1999. The 14C incorporation into five biochemical pools (glucan, amino acids, proteins, lipids and polysaccharides) was measured during iron/light perturbation experiments. The diurnal Chl a-specific rates of carbon incorporation into these pools did not change in response to iron addition, yet were decreased at 20 μmol photons m−2 s−1, an irradiance comparable with the one at 20–45 m in situ depth. This suggests that the low phytoplankton biomass encountered (0.1–0.6 μg Chl a L−1) was mainly caused by light limitation in the deep wind mixed layer (>40 m). Regional differences in Chl a-specific carbon incorporation rates were not found in spite of differences in phytoplankton species composition: at the Antarctic Polar Front, biomass was dominated by a diatom population of Fragilariopsis kerguelensis, whereas smaller cells, including chrysophytes, were relatively more abundant in the Antarctic Circumpolar Current beyond the influence of frontal systems. Because mixing was often in excess of 100 m in the latter region, diatom cells may have been unable to fulfil their characteristically high Fe demand at low average light conditions, and thus became co-limited by both resources. Using a model that describes the 14C incorporation, the consistency was shown between the dynamics in the glucan pool in the field experiments and in laboratory experiments with an Antarctic diatom, Chaetoceros brevis. The glucan respiration rate was almost twice as high during the dark phase as during the light phase, which is consistent with the role of glucan as a reserve supplying energy and carbon skeletons for continued protein synthesis during the night.
Keywords: Sørishavet; biokjemi; fotosyntese; fytoplankton; marin biologi; oseanografi; planteplankton

State-dependent parental care in the Antarctic petrel: responses to manipulated chick age during early chick rearing - Varpe, Øystein; Tveraa, Torkild; Folstad, Ivar (Oikos, 2004)
Life histories are state-dependent, and an individual's reproductive decisions are determined by its available resources and the needs of its offspring. Here we test how a chick's needs for food and protection influence parental decisions in the Antarctic petrel, Thalassoica antarctica, where the parents, due to their long breeding lifespan, are expected to give priority to their own needs before those of the young. We exchanged one-day-old chicks with four-day-old chicks and studied how the parents subsequently provided care to the chick. The duration of the guarding period was adjusted, and parents left older chicks earlier and younger chicks later compared to controls. Three mechanisms were responsible for the adjustments. 1) Parents with an older chick co-ordinated fewer guarding spells whereas parents with a younger chick co-ordinated more guarding spells. 2) At the last guarding spell, i.e. where a parent left the chick alone before the partner returned, less time was spent with older chicks, and more time with younger chicks. 3) Foraging trip duration was shortened by parents given older chicks and prolonged by parents given younger chicks, probably in response to the chick's food demand. Hence, the parents responded quickly to the altered needs of the chick. Parents with high body mass guarded longer and were better able to co-ordinate the guarding spells compared to lighter parents. In conclusion, Antarctic petrels adjust reproductive decisions to their own, their mate's, and their chick's state, and they seem to respond to the chick's needs for both food and protection.
Keywords: Dronning Maud Land; NARE 2000/01; fugler; ornitologi; petreller; zoologi; økologi

Adaptations and lifestyle in polar marine environments: a biological challenge for the study of fish evolution - Verde, Cinzia; Cocca, Ennio; de Pascale, Donatella; Parisi, Elio; di Frisco, Guido (Polar Research, 2004)
The climatic features of Antarctic waters are more extreme and constant than in the Arctic. The Antarctic has been isolated and cold longer than the Arctic. The polar ichthyofaunas differ in age, endemism, taxonomy, zoogeographic distinctiveness and physiological tolerance to environmental parameters. The Arctic is the connection between the Antarctic and the temperate-tropical systems. Paradigmatic comparisons of the pathways of adaptive evolution of fish from both poles address the oxygen-transport system and the antifreezes of northern and southern species, (i) Haemoglobin evolution has included adaptations at the biochemical, physiological and molecular levels. Within the study of the molecular bases offish cold adaptation, and taking advantage of the information on haemoglobin amino acid sequence, we analysed the evolutionary history of the ? and ? globins of Antarctic, Arctic and temperate haemoglobins as a basis for reconstructing phylogenetic relationships. In the trees, the constant physico-chemical conditions of the Antarctic waters are matched by clear grouping of globin sequences, whereas the variability typical of the Arctic ecosystem corresponds to high sequence variation, reflected by scattered intermediate positions between the Antarctic and non-Antarctic clades. (ii) Antifreeze (glyco)proteins and peptides allow polar fish to survive at sub-zero temperatures. In Antarctic Notothenioidei the antifreeze gene evolved from a trypsinogen-like serine protease gene. In the Arctic polar cod the genome contains genes which encode nearly identical proteins, but have evolved from a different genomic locus–a case of convergent evolution.
Keywords: Sørishavet; biokjemi; biologi; evolusjon; fauna; fisker; fysiologi; klima; miljø; zoogeografi; økosystemer

Evidence for orbitally controlled size variations of the East Antarctic Ice Sheet during the late Miocene - Grützner, J.; Rebesco, M.A.; Cooper, A.K.; Forsberg, C.F.; Kryc, K.A.; Wefer, G. (Geology, 2003)
Ocean Drilling Program Site 1165 penetrated drift sediments on the East Antarctic continental rise and recovered sediments from a low-energy depositional environment. The sediments are characterized by prominent alternations between a green to greenish-gray diatom-bearing hemipelagic facies and gray to dark gray hemiturbiditic facies. Our investigation of an upper Miocene section, using high-resolution color spectra, multisensor core logs, and X-ray fluorescence scans, reveals that sedimentation changes occur at Milankovitch orbital frequencies of obliquity and precession. We use this finding to derive an astronomical calibrated time scale and to calculate iron mass-accumulation rates, as a proxy for sediment-accumulation rates. Terrigenous iron fluxes change by as much as 100% during each obliquity cycle. This change and an episodic pattern of enhanced ice-rafted debris deposition during times of deglaciation provide evidence for a dynamic and likely wet-based late Miocene East Antarctic Ice Sheet (EAIS) that underwent large size variations at orbital time scales. The dynamic behavior of the EAIS implies that a significant proportion of the variability seen in oxygen isotope records of the late Miocene reflects Antarctic ice-volume changes.
Keywords: Antarktis; Sørishavet; geologi; glasiologi; maringeologi; paleoklimatologi

Decadal decrease of Antarctic sea ice extent inferred from whaling records revisited on the basis of historical and modern sea ice records - Ackley, Stephen; Wadhams, Peter; Comiso, Josefino C; Worby, Anthony P (Polar Research, 2003)
In previous work, whaling catch positions were used as a proxy record for the position of the Antarctic sea ice edge and mean sea ice extent greater than the present one spanning 2.8° latitude was postulated to have occurred in the pre-1950s period, compared to extents observed since 1973 from microwave satellite imagery. The previous conclusion of an extended northern latitude for ice extent in the earlier epoch applied only to the January (mid-summer) period. For this summer period, however, there are also possible differences between ship and satellite-derived measurements. Our work showed a consistent summer offset (November– December), with the ship-observed ice edge 1 - 1.5° north of the satellitederived ice edge. We further reexamine the use of whale catch as an ice edge proxy where agreement was claimed between the satellite ice edge (1973–1987) and the ship whale catch positions. This examination shows that, while there may be a linear correlation between ice edge position and whale catch data, the slope of the line deviates from unity and the ice edge is also further north in the whale catch data than in the satellite data for most latitudes. We compare the historical (direct) record and modern satellite maps of ice edge position accounting for these differences in ship and satellite observations. This comparison shows that only regional perturbations took place earlier, without significant deviations in the mean ice extents, from the pre-1950s to the post-1970s. This conclusion contradicts that previously stated from the analysis of whale catch data that indicated Antarctic sea ice extent changes were circumpolar rather than regional in nature between the two periods.
Keywords: Sørishavet; Weddellhavet; endringer; havis; historisk; hvalfangere; hvalfangst; iskant; observasjoner; satellite bilder; sjøis

Utfordringene for legene ved polarekspedisjoner omkring år 1900 - Albretsen, Carl Severin (Tidsskrift for den Norske Laegeforening, 2003)
Publisher: Den norske lægeforening ISBN: 0807-7096
Keywords: Antarktis; medisin; polarkespedisjoner

In the wake of Tønnessen and Johnsen : trends in whaling history research after 1970 - Basberg, Bjørn L (Discussion paper Norges handelshøyskole, Institutt for samfunnsøkonomi, 2003)
Publisher: Norwegian School of Economics and Business Administration. Department of Economics Place: Bergen
Keywords: Antarktis; Norge; husholdning; hvalfangere; hvalfangst; pelagisk; økonomisk historie

Proterozoic–Cambrian history of Dronning Maud Land in the context of Gondwana assembly - Bauer, Wilfried; Thomas, Robert J; Jacobs, Joachim (Proterozoic East Gondwana: Supercontinent Assembly and Breakup, 2003)
Dronning Maud Land contains a fragment of an Archaean craton covered by sedimentary and magmatic rocks of Mesoproterozoic age, surrounded by a Late Mesoproterozoic metamorphic belt. Tectonothermal events at the end of the Mesoproterozoic and in Late Neoproterozoic–Cambrian times (Pan-African) have been proved within the metamorphic belt. In western Dronning Maud Land a juvenile Mesoproterozoic basement was accreted to the craton at c. 1.1 Ga. Mesoproterozoic rocks were also detected by zircon SHRIMP dating of gneisses in central Dronning Maud Land, followed by a long hiatus for which geochronological data are lacking, an amphibolite to granulite facies metamorphism and syntectonic granitoid emplacement of Pan-African age have been dated. During this orogeny older structures were completely overprinted in a sinistral tranpressive deformation regime, leading to the mainly coast-parallel tectonic structures of the East Antarctic Orogen. Putting Antarctica back in its Gondwana position, the East Antarctic Orogen continues northward in East Africa as the East African Orogen, whereas a connection to the marginal Ross Orogen at the Pacific margin of East Antarctica is suggested along the Shackleton Range. The East Antarctic-East African Orogen resulted from closure of the Mozambique Ocean and collision of West and East Gondwana, i.e. western Dronning Maud Land was part of West Gondwana. During this collision the lithospheric mantle probably delaminated, allowing the asthenosphere to underplate the continental crust and producing heat for the voluminous, typically anhydrous, Pan-African granitoids of central Dronning Maud Land.
Keywords: Dronning Maud Land; geologi

Metandania tordi, a new stegocephalid (Crustacea: Peracarida: Amphipoda) species from the Southern Ocean - Berge, Jørgen; Vader, Wim (Proceedings of the Biological Society of Washington, 2003)
A new stegocephalid (Amphipoda) species, Metandania tordi n.sp, is described, belonging to the subfamily Andaniexinae Berge & Vader 2001. The new species is the first record of the genus in the southern hemisphere. In addition, a morphological trait, previously not figured nor described within this family, is presented: a process proximally on the inner anterior surface of the fourth coxa. This locking-process is interpreted, and named accordingly, to enhance a relative stabilization of the third and fourth coxae. A brief comparison of the morphology of the fourth coxa between all five stegocephalid subfamilies is presented.
Keywords: Sørishavet; amfipoder; marin biologi; taksonomi

Some features of electron density behaviour in the high latitude D-region derived from in situ measurements - Danilov, A.D.; Smirnova, N.V.; Blix, Tom Arild; Thrane, E.V.; Vanina, L.B. (Journal of Atmospheric and Solar-Terrestrial Physics, 2003)
A large database of rocket measurements of the D-region electron concentration has been studied. The data were obtained at four sites in the Antarctic (Molodezhnaya and Syowa) and Arctic (Heiss Island, and Andøya/Kiruna). The electron densities were analysed in terms of their variations with solar zenith angle, geomagnetic activity and atmospheric temperature. We found that there is a particle ionisation source in the auroral oval even in quiet conditions. The energy of the particles is such, that they penetrate down to 85km, are partially absorbed between 85 and 80km but do not penetrate (are completely absorbed) below 75km. Analysis of the dependence of the electron concentration [e] on the daily sum of Kp indices, ∑Kp, shows that at all heights considered there is an increase of [e] with ∑Kp up to some saturation value of ∑Kp and beyond this level [e] is either constant (with large scatter of the data) or even decreases. This indicates that when the auroral oval expands with increasing geomagnetic activity, a particular station may move from a position outside or at the boundary of the oval, to a position inside the polar cap. An attempt is made to find the temperature dependence of the electron concentration. It is found that [e] at 75 and 80km increases with temperature T. Analysis of the flights conducted during noctilucent cloud (NLC) events at Andøya/Kiruna reveals a strong dependence of [e] on ∑Kp at 80 and 85km. This dependence is stronger and better defined than that for the entire data set. This may be explained by the low mesopause temperatures observed in summer when NLC occur. A comparison of the electron density data sets with empirical and theoretical models is presented and during quiet magnetic conditions a good agreement with mid-latitude models is found.
Keywords: Antarktis; geofysikk; geomagnetiske stormer; ionosfæren; meteorologi; polarområdene

Sea ice extent and the global climate system - Dick, Chad (Polar Research, 2003)
Sea ice is a remarkable component of the global climate system. It can form over up to about 10 % of the global ocean area, and creates an insulating barrier between the relatively warm seawater and the cold atmosphere, allowing a temperature difference that may be tens of degrees over only a couple of meters. It reduces evaporation from the ocean, leading to a drier atmosphere than would otherwise exist. Sea ice modifies the radiation balance at the Earth’s surface because it supports snow (the most reflective of the Earth’s natural surfaces, with an albedo of up to approximately 0.8), where otherwise there would be seawater (the least reflective, with an albedo of about 0.07). As sea ice forms it excludes brine, deepening the ocean surface mixed layer and influencing the formation of deep and bottom water. As it melts, it releases relatively fresh water, stratifying the upper layers of the ocean. Through these processes sea ice exerts an enormous influence on the atmospheric and oceanic circulation in cold regions and indeed the climate of the rest of the globe.
Keywords: Sørishavet; globale klimasystemet; havis; klimaendringer; polarområdene; sjøis

Using First-Passage Time in the Analysis of Area-Restricted Search and Habitat Selection - Fauchald, Per; Tveraa, Torkild (Ecology, 2003)
How animals change their movement patterns in relation to the environment is a central topic in a wide area of ecology, including foraging ecology, habitat selection, and spatial population ecology. To understand the underlying behavioral mechanisms involved, there is a need for methods to measure changes in movement patterns along a pathway through the landscape. We used simulated pathways and satellite tracking of a long-ranging seabird to explore the properties of first-passage time as a measure of search effort along a path. The first-passage time is defined as the time required for an animal to cross a circle with a given radius. It is a measure of how much time an animal uses within a given area. First-passage time is scale dependent, and a plot of variance in first-passage time vs. spatial scale reveals the spatial scale at which the animal concentrates its search effort. By averaging the first-passage time on a geographical grid, it is possible to relate first-passage time to environmental variables and the search pattern of other individuals.
Publisher: Ecological Society of America
Keywords: Dronning Maud Land; NARE 2000/01; fugler; ornitologi; petreller; satellittelemetri; økologi

A hindcast simulation of Arctic and Antarctic sea ice variability, 1955-2001 - Fichefet, Thierry; Goosse, Hugues; Morales Maqueda, Miguel Angel (Polar Research, 2003)
A hindcast simulation of the Arctic and Antarctic sea ice variability during 1955–2001 has been performed with a global, coarse resolution ice–ocean model driven by the National Centers for Environmental Prediction / National Center for Atmospheric Research reanalysis daily surface air temperatures and winds. Both the mean state and variability of the ice packs over the satellite observing period are reasonably well reproduced by the model. Over the 47-year period, the simulated ice area (defined as the total ice-covered oceanic area) in each hemisphere experiences large decadal variability together with a decreasing trend of ~1 % per decade. In the Southern Hemisphere, this trend is mostly caused by an abrupt retreat of the ice cover during the second half of the 1970s and the beginning of the 1980s. The modelled ice volume also exhibits pronounced decadal variability, especially in the Northern Hemisphere. Besides these fluctuations, we detected a downward trend in Arctic ice volume of 1.8 % per decade and an upward trend in Antarctic ice volume of 1.5 % per decade. However, caution must be exercised when interpreting these trends because of the shortness of the simulation and the strong decadal variations. Furthermore, sensitivity experiments have revealed that the trend in Antarctic ice volume is model-dependent.
Keywords: Sørishavet; forskning; geofysikk; havis; observasjoner; polarområdene; satellitt; sjøis

A 1.3-Myr palaeoceanographic record from the continental margin off Dronning Maud Land, Antarctica - Forsberg, Carl Fredrik; Løvlie, Reidar; Jansen, Eystein; Solheim, Anders; Sejrup, Hans Petter; Lie, Hans Erik (Palaeogeography, Palaeoclimatology, Palaeoecology, 2003)
A 12.5 m long core was retrieved from the continental margin off Dronning Maud Land, Antarctica. Magnetostratigraphy, stable isotopes, 14C accelerator mass spectrometer and amino acid analyses indicate a continuous sediment record going back 1.3 Myr. Comparison of CaCO3 results with those from ODP Site 1089 and an index of North Atlantic Deep Water (NADW) influence in surface waters indicate that NADW upwelled along the Antarctic continental margin during the whole of this period. The mid-Pleistocene transition (1.0–0.6 Ma) was accompanied by an apparent decline in the NADW influence, and was followed by extended carbonate dissolution during the interglacials of marine isotope stages (MIS) 13 and 11. Less extensive periods of dissolution occur at the end of the interglacials younger than MIS 11. While interglacial dissolution is characteristic of the Pacific and Indian oceans, the carbon isotopes return to pre-transition values indicative of renewed NADW upwelling. The concentration of ice-rafted debris may reflect changes in the relative rate of interglacial sedimentation. It is speculated that the high ice rafted debris (IRD) concentrations during interglacials younger than 400 kyr may be due to a reduced relative sedimentation rate of other interglacial components whereas the low concentrations during interglacials before the mid-Pleistocene transition may be due to a higher relative sedimentation rate of these.
Keywords: Dronning Maud Land; Weddellhavet; geologi; magnetostratigrafi; oseanografi; paleoklimatologi; paleoseanografi; stabile isotoper

Description and evaluation of the bergen climate model: ARPEGE coupled with MICOM - Furevik, Tore; Bentsen, Mats; Drange, Helge; Kindem, I. K. T.; Kvamstø, Nils Gunnar; Sorteberg, Asgeir (Climate Dynamics, 2003)
A new coupled atmosphere–ocean–sea ice model has been developed, named the Bergen Climate Model (BCM). It consists of the atmospheric model ARPEGE/IFS, together with a global version of the ocean model MICOM including a dynamic–thermodynamic sea ice model. The coupling between the two models uses the OASIS software package. The new model concept is described, and results from a 300-year control integration is evaluated against observational data. In BCM, both the atmosphere and the ocean components use grids which can be irregular and have non-matching coastlines. Much effort has been put into the development of optimal interpolation schemes between the models, in particular the non-trivial problem of flux conservation in the coastal areas. A flux adjustment technique has been applied to the heat and fresh-water fluxes. There is, however, a weak drift in global mean sea-surface temperature (SST) and sea-surface salinity (SSS) of respectively 0.1 °C and 0.02 psu per century. The model gives a realistic simulation of the radiation balance at the top-of-the-atmosphere, and the net surface fluxes of longwave, shortwave, and turbulent heat fluxes are within observed values. Both global and total zonal means of cloud cover and precipitation are fairly close to observations, and errors are mainly related to the strength and positioning of the Hadley cell. The mean sea-level pressure (SLP) is well simulated, and both the mean state and the interannual standard deviation show realistic features. The SST field is several degrees too cold in the equatorial upwelling area in the Pacific, and about 1 °C too warm along the eastern margins of the oceans, and in the polar regions. The deviation from Levitus salinity is typically 0.1 psu – 0.4 psu, with a tendency for positive anomalies in the Northern Hemisphere, and negative in the Southern Hemisphere. The sea-ice distribution is realistic, but with too thin ice in the Arctic Ocean and too small ice coverage in the Southern Ocean. These model deficiencies have a strong influence on the surface air temperatures in these regions. Horizontal oceanic mass transports are in the lower range of those observed. The strength of the meridional overturning in the Atlantic is 18 Sv. An analysis of the large-scale variability in the model climate reveals realistic El Niño – Southern Oscillation (ENSO) and North Atlantic–Arctic Oscillation (NAO/AO) characteristics in the SLP and surface temperatures, including spatial patterns, frequencies, and strength. While the NAO/AO spectrum is white in SLP and red in temperature, the ENSO spectrum shows an energy maximum near 3 years.
Keywords: Sørishavet; geofysikk; klimamodeller; klimatologi; polarområdene

Magnitude scales for very local earthquakes. Application for Deception Island Volcano (Antarctica) - Havskov, Jens; Peña, José A; Ibáñez, Jesús M; Ottemöller, Lars; Martı́nez-Arévalo, Carmen (Putting Volcano Seismology in a Physical Context. In memory of Bruno Martinelli, 2003)
Different magnitude scales are calculated for a set of volcano-tectonic earthquakes recorded in Deception Island Volcano (Antarctica). The data set includes earthquakes recorded during an intense seismic series that occurred in January–February 1999, with hypocentral distances that range between 0.5 and 15 km. This data set is enlarged to include some regional earthquakes with hypocentral distances up to 200 km. The local magnitude scale, ML, fixed at a hypocentral distance of 17 km, is used as the reference for the other magnitude scales studied in the present work. ML is determined on a standard Wood–Anderson simulated trace assuming a gain of 2080. Maximum peak-to-peak amplitudes are measured on the vertical components of a short-period sensor. The Mw scale is calculated, in the vertical component, both for P and S waves. The attenuation correction of the ground motion displacement spectra is introduced using data from coda waves studied in the area. The comparison between ML values and Mw estimations indicates severe discrepancies between both values. A magnitude–duration scale is calibrated from the comparison between coda durations of the recorded events and their assigned local magnitude scales. In order to investigate the causes of the discrepancy between the ML and Mw values we analyze two possible error sources: a wrong coda Q value, or the effects of the near-surface attenuation that initially are not taken into account in the correction of the ground displacement spectra. The analysis reveals that the main cause of this discrepancy is the effect of the near-surface attenuation. The near-surface attenuation is also the cause of the determination of an anomalous spectral decay slope, after the corner frequency, and the determination of this corner frequency value. This near-surface attenuation, represented by κ, is estimated over the data set, obtaining an average value of 0.025. With this κ value, the Mw scale is recalculated using an automatic algorithm. The new Mw values are more consistent with the ML values, obtaining a relationship of Mw=0.78ML−0.02.
Keywords: Antarktis; Deceptionøya; geologi; vulkaner

Calcareous dinoflagellate associations and Maastrichtian–Tertiary climatic change in a high-latitude core (ODP Hole 689B, Maud Rise, Weddell Sea) - Hildebrand-Habel, Tania; Streng, Michael (Palaeogeography, Palaeoclimatology, Palaeoecology, 2003)
The distribution of calcareous dinoflagellates has been analysed for the Maastrichtian–Miocene interval of Ocean Drilling Project Hole 689B (Maud Rise, Weddell Sea). The investigation thus represents a primary evaluation of the long-term evolution in high-latitude calcareous dinoflagellate assemblages during the transition from a relatively warm Late Cretaceous to a cold Neogene climate. Major assemblage changes during this interval occurred in characteristic steps: (1) an increase in relative abundance of tangentially structured species – particularly Operculodinella operculata – at the Cretaceous/Tertiary boundary; (2) a diversity decrease and several first and last appearances across the Middle–Late Eocene boundary, possibly attributed to increased climate cooling; (3) a diversity decrease associated with the dominance of Calciodinellum levantinum in the late Early Oligocene; (4) the reappearance and dominance of Pirumella edgarii in the Early Miocene, probably reflecting a warming trend; (5) monogeneric assemblages dominated by Caracomia spp. denoting strong Middle Miocene cooling. The results not only extend the biogeographic ranges of many taxa into the Antarctic region, but also indicate that the evolution of high-latitude calcareous dinoflagellate assemblages parallels the changing environmental conditions in the course of the Cenozoic climate transition. Therefore, calcareous dinoflagellates contribute to our understanding of the biotic effects associated with palaeoenvironmental changes and might possess the potential for reconstructing past conditions. The flora in the core includes one new taxon: Caracomia arctica forma spinosa Hildebrand-Habel and Streng, forma nov. Additionally, two new combinations are proposed: Fuettererella deflandrei (Kamptner, 1956) Hildebrand-Habel and Streng, comb. nov. and Fuettererella flora (Fütterer, 1990) Hildebrand-Habel and Streng, comb. nov.
Keywords: Sørishavet; Weddellhavet; geologi; klimaendringer; paleogeografi; paleoklimatologi; polarområdene

The Late Pleistocene and Holocene Glacial and Climate History of the Antarctic Peninsula Region as Documented by the Land and Lake Sediment Records- A Review - Hjort, Christian; Ingólfsson, Ólafur; Bentley, Michael J; Björck, Svante (Antarctic Peninsula Climate Variability: Historical and Paleoenvironmental Perspectives, 2003)
This chapter contains sections titled: Introduction Methods Glaciation History and the Raised Marine Shorelines Mid-Holocene Glacial Readvances The Holocene Climatic Optimum Neoglaciation and the Little Ice Age Discussion and Conclusions
Keywords: Antarktis; glasiologi; paleoglasiologi; sedimentologi

Glacial and Climate History of the Antarctic Peninsula since the Last Glacial Maximum - Ingólfsson, Ólafur; Hjort, Christian; Humlum, Ole (Arctic, Antarctic, and Alpine Research, 2003)
During the Last Glacial Maximum (LGM), ice thickened considerably and expanded toward the outer continental shelf around the Antarctic Peninsula. Deglaciation occurred between >14 ka BP and ca. 6 ka BP, when interglacial climate was established in the region. Deglaciation of some local sites was as recent as 4?3 ka BP. After a climate optimum, peaking ca. 4?3 ka BP, a distinct climate cooling occurred. It is characterized at a number of sites by expanding glaciers and ice shelves. Rapid warming during the past 50 yr may be causing instability of some Antarctic Peninsula ice shelves. Detailed reconstructions of the glacial and climatic history of the Antarctic Peninsula since LGM are hampered by scarcity of available archives, low resolution of many datasets, and problems in dating samples. Consequently, the configuration of LGM ice sheets, pattern of subsequent deglaciation, and environmental changes are poorly constrained both temporally and spatially.
Publisher: Taylor & Francis
Keywords: Antarktis; glasiologi; klimaendringer; marin geologi; paleoklimatologi

Hvalfangsteventyret - Jacobsen, Erik (Cicero grafisk, 2003)
Keywords: Nordmenn; Sørishavet; Vestfold; biografier; erindringer; historie; hvalfangst; pelagisk; sjøfolk

Postglacial marine environmental changes in Maxwell Bay, King George Island, West Antarctica - Khim, Boo-Keun; Yoon, Ho Il (Polar Research, 2003)
Sediment textural properties and total organic carbon (TOC) contents of three sediment cores from Maxwell Bay, King George Island, West Antarctica, record changes in Holocene glaciomarine sedimentary environments. The lower sedimentary unit is mostly composed of TOC-poor diamictons, indicating advanced coastal glacier margins and rapid iceberg discharge in proximal glaciomarine settings with limited productivity and meltwater supply. Fine-grained, TOC-rich sediments in the upper lithologic unit suggest more open water and warm conditions, leading to enhanced biological productivity due to increased nutrient-rich meltwater supply into the bay. The relationship between TOC and total sulfur (TS) indicates that the additional sulfur within the sediment has not originated from in situ pyrite formation under the reducing condition, but rather may be attributed to the detrital supply of sand-sized pyrite from the hydrothermal-origin, quartz-pyrite rocks widely distributed in King George Island. The evolution of bottom-water hydrography after deglaciation was recorded in the benthic foraminiferal stable-isotopic composition, corroborated by the TOC and lithologic changes. The Ø18O values indicate that bottom-water in Maxwell Bay was probably mixed gradually with intruding 18O-rich seawater from Bransfield Strait. In addition, the Ø13C values reflect a spatial variability in the carbon isotope distribution in Maxwell Bay, depending on marine productivity as well as terrestrial carbon fluxes by meltwater discharge. The distinct lithologic transition, dated to approximately 8000 yr BP (uncorrected) and characterized by textural and geochemical contrasts, highlights the postglacial environmental change by a major coastal glacier retreat in Maxwell Bay.
Keywords: Sørishavet; geofysikk; geokjemi; marin geologi; miljøendringer; sedimenter

Blant pelssel og pingvinar. Ei julereise til Sør-Georgia og Antarktis - Kolltveit, Bård (Norsk sjøfartsmuseum. Årbok, 2003)
Publisher: Norsk sjøfartsmuseum Place: Oslo
Keywords: Antarktis; cruiseturisme; dagbøker; polareksspedisjoner; reisebeskrivelser; reiseskildringer

Bønder i Antarktis : hvalfangst og landbruk 1925-1940 - Lalla, Robert (Institutt for økonomi og ressursforvaltning, Norges landbrukshøgskole, 2003)
ISBN: 8257505722 08023220
Keywords: Norge; Sørishavet; husholdning; hvalfangere; hvalfangst; pelagisk; økonomisk historie

The making and unmaking of a supercontinent: Rodinia revisited - Meert, Joseph G.; Torsvik, Trond H. (Orogenic Belts, Regional and Global Tectonics: A Memorial Volume to Chris McAulay Powell, 2003)
During the Neoproterozoic, a supercontinent commonly referred to as Rodinia, supposedly formed at ca. 1100 Ma and broke apart at around 800–700 Ma. However, continental fits (e.g., Laurentia vs. Australia–Antarctica, Greater India vs. Australia–Antarctica, Amazonian craton [AC] vs. Laurentia, etc.) and the timing of break-up as postulated in a number of influential papers in the early–mid-1990s are at odds with palaeomagnetic data. The new data necessitate an entirely different fit of East Gondwana elements and western Gondwana and call into question the validity of SWEAT, AUSWUS models and other variants. At the same time, the geologic record indicates that Neoproterozoic and early Paleozoic rift margins surrounded Laurentia, while similar-aged collisional belts dissected Gondwana. Collectively, these geologic observations indicate the breakup of one supercontinent followed rapidly by the assembly of another smaller supercontinent (Gondwana). At issue, and what we outline in this paper, is the difficulty in determining the exact geometry of the earlier supercontinent. We discuss the various models that have been proposed and highlight key areas of contention. These include the relationships between the various ‘external’ Rodinian cratons to Laurentia (e.g., Baltica, Siberia and Amazonia), the notion of true polar wander (TPW), the lack of reliable paleomagnetic data and the enigmatic interpretations of the geologic data. Thus, we acknowledge the existence of a Rodinia supercontinent, but we can place only loose constraints on its exact disposition at any point in time.
Keywords: Antarktis; Dronning Maud Land; geologi; paleogeografi

Water mass modification over the continental shelf north of Ronne Ice Shelf, Antarctica - Nicholls, Keith William; Padman, Laurie; Schröder, Michael; Woodgate, Rebecca A.; Jenkins, Adrian; Østerhus, Svein (Journal of Geophysical Research: Oceans, 2003)
We use new data from the southern Weddell Sea continental shelf to describe water mass conversion processes in a formation region for cold and dense precursors of Antarctic Bottom Water. The cruises took place in early 1995, 1998, and 1999, and the time series obtained from moored instruments were up to 30 months in length, starting in 1995. We obtained new bathymetric data that greatly improve our definition of the Ronne Depression, which is now shown to be limited to the southwestern continental shelf and so cannot act as a conduit to northward flow from Ronne Ice Front. Large-scale intrusions of Modified Warm Deep Water (MWDW) onto the continental shelf occur along much of the shelf break, although there is only one location where the MWDW extends as far south as Ronne Ice Front. High-Salinity Shelf Water (HSSW) produced during the winter months dominates the continental shelf in the west. During summer, Ice Shelf Water (ISW) exits the subice cavity on the eastern side of the Ronne Depression, flows northwest along the ice front, and reenters the cavity at the ice front's western limit. During winter the ISW is not observed in the Ronne Depression north of the ice front. The flow of HSSW into the subice cavity via the Ronne Depression is estimated to be 0.9 ± 0.3 Sv. When combined with inflows along the remainder of Ronne Ice Front (reported elsewhere), sufficient heat is transported beneath the ice shelf to power an average basal melt rate of 0.34 ± 0.1 m yr−1.
Art. no. 3260
Keywords: AABW; Sørishavet; Weddellhavet; geofysikk; havstrømmer; isshelf; kontinentalsokkel; oseanografi

Moment Magnitude Determination for Local and Regional Earthquakes Based on Source Spectra - Ottemöller, Lars; Havskov, Jens (Bulletin of the Seismological Society of America, 2003)
We investigated the use of an automated routine to determine moment magnitudes from the displacement spectra of local and regional earthquakes. Two algorithms, a genetic algorithm and a converging grid search, were developed and tested with earthquake data from Mexico, Norway, and Deception Island (Antarctica). It was found that compared with manual analysis, the algorithms give reliable automatic moment magnitude (Mw) estimates in the range -1 < M < 8. The converging grid search appeared to be more cost-effective than the genetic algorithm. Mw at local and regional distances seems superior to amplitude-based magnitudes that saturate for large earthquakes. The application of the automated algorithm in near real time may help to obtain a nonsaturated magnitude estimate in the case of a large earthquake immediately after the earthquake has occurred. Also, the method can be useful for processing large amounts of data.
Keywords: Antarktis; Deceptionøya; Sør-Shetlandsøyene; seismologi

A geochronological and geochemical study of rocks from Gjelsvikfjella, Dronning Maud Land, Antarctica—implications for Mesoproterozoic correlations and assembly of Gondwana - Paulsson, Oskar; Austrheim, Håkon (Precambrian Research, 2003)
The Jutulsessen nunataks (72°00′S; 2°30′E), Gjelsvikfjella, Dronning Maud Land (DML), consist mainly of migmatites of two types. A heterogeneous banded amphibolite facies gneisses and a more homogeneous part. In the more homogeneous part, partial melts form along axial planes to tight folds. Numerous pegmatitic dykes occur in both migmatites. The homogeneous part of the migmatite has a granodiorite composition. It displays the depletion of Nb–Ta typical for rocks from destructive plate margins and a strongly fractionated REE pattern, specially in LREE (La/Lu ratios varying between 500 and 800). SIMS dating of zircon from the homogeneous migmatite and two pegmatite dykes resulted in two age groups. A concordant age of 1163±6 Ma is calculated from zircon crystals with no rim/core structure and from cores from structurally complex crystals. This age represents the age of the protolith of the migmatite. A Cambrian age of 504±6 Ma is obtained from zircon rims and from sector-zoned zircons. This age represent the time of migmatisation. Sm–Nd depleted mantle model ages range from 1390 to 1770 Ma and suggest that the protolith to the migmatites contained components of older crust (pre-1163 Ma). An igneous complex consisting of a syenite plug (Stabben syenite), gabbroic rocks and aplitic dykes intrudes the metamorphic complex. The syenite and the aplitic dykes are neither deformed nor migmatised or penetrated by pegmatitic dykes. These rocks have elevated LREE and LILE concentrations with an La/Lu ratio of 450 and an Nb–Ta trough. The gabbroic rocks range in composition from melagabbro to monzogabbro and host numerous pegmatitic dykes. SIMS zircon U–Pb data from the Stabben syenite give an age of 500±8 Ma. This age is regarded as the intrusive age of the Stabben syenite. By the single zircon–Pb evaporation method an age of 495±14 Ma is obtained from the aplitic dykes. Sm–Nd depleted mantle model ages between 1800 and 2220 Ma indicate that the dykes formed from a Paleoproterozoic source. A Mesoproterozoic volcanic arc setting of DML and a correlation with the Natal Province, as suggested by several authors, is supported by data in this study. The studied area has consequently been a part of the Kaapvaal/Kalahari craton since Mesoproterozoic time. The Cambrian migmatisation and the intrusions are interpreted as a result of post-collision activity related to the collision between the Kalahari craton and the combined block of Antarctica and Australia during the final assembly of Gondwana. This collision is suggested to be included in the Kuunga Orogeny introduced by Meerat and Van der Voo [J. Geodynam. 23 (1997) 223].
Keywords: Dronning Maud Land; NARE 1989/90; geokjemi; geokronologi; geologi; nunataker; petrologi

Radionuclides deposition over Antarctica - Pourchet, Michel; Magand, Olivier; Frezzotti, Massimo; Ekaykin, Alexey A.; Winther, Jan Gunnar (Journal of Environmental Radioactivity, 2003)
A detailed and comprehensive map of the distribution patterns for both natural and artificial radionuclides over Antarctica has been established. This work integrates the results of several decades of international programs focusing on the analysis of natural and artificial radionuclides in snow and ice cores from this polar region. The mean value (37±20 Bq m−2) of 241Pu total deposition over 28 stations is determined from the gamma emissions of its daughter 241Am, presenting a long half-life (432.7 yrs). Detailed profiles and distributions of 241Pu in ice cores make it possible to clearly distinguish between the atmospheric thermonuclear tests of the fifties and sixties. Strong relationships are also found between radionuclide data (137Cs with respect to 241Pu and 210Pb with respect to 137Cs), make it possible to estimate the total deposition or natural fluxes of these radionuclides. Total deposition of 137Cs over Antarctica is estimated at 760 TBq, based on results from the 90–180° East sector. Given the irregular distribution of sampling sites, more ice cores and snow samples must be analyzed in other sectors of Antarctica to check the validity of this figure.
Keywords: Antarktis; geofysikk; geologi; glasiologi; radioaktivitet

How fast do demersal longlines sink? - Robertson, Graham; Moe, Egil; Haugen, Roy; Wienecke, Barbara (Fisheries Research, 2003)
Longlines that sink fast reduce the time available to seabirds to attack baited hooks and are important in efforts to minimise seabird by-catch in longline fisheries. We measured sink rates in still seawater of longlines commonly used in the world’s demersal fisheries. Lines with integrated weight (lead cores) sank two to three times faster (45–52cm/s) than conventional (unweighted) lines. Conventional 9mm diameter lines made from polyester sank at 23cm/s compared to 18cm/s for 9mm Silver lines (blend of polyester, polyethylene and polypropylene). Samples of lines set by hand in still water sank significantly faster than longlines set from a fishing vessel, presumably because of the effect of the sea swell and upwellings from the propeller on the line set from the vessel.
Keywords: Sørishavet; fiskefartøy; fiskerier

Sea ice formation on a very cold surface - Smedsrud, Lars Henrik; Saloranta, Tuomo; Haugan, Peter M; Kangas, Tor-Villy (Geophysical Research Letters, 2003)
In this study laboratory experiments of sea ice formed on a vertical surface with initial temperature of −30 to −50°C are presented. The ice formation is rapid, and in 300 s >5 mm of sea ice is formed. Ice formation cooled and salinified the water, and induced a vertical down wards flow of ∼5 mm/s with a boundary layer about 5 mm thick. This ice has a structure with columnar crystals that have small circular cross sections (0.2–1.0 mm) and sea ice salinities are between 24 and 32. A simple model approach indicate that the thermal conductivity of such ice is lower than for other types of sea ice.
Keywords: Antarktis; geofysikk; glasiologi; havis; innlandsis; isshelf; laboratorieeksperimenter; polarområdene; sjøis

The mid-Pliocene (4.3–2.6 Ma) benthic stable isotope record of the Southern Ocean: ODP Sites 1092 and 704, Meteor Rise - Andersson, Carin; Warnke, Detlef A.; Channell, James E.T.; Stoner, Joseph S.; Jansen, Eystein (Palaeogeography, Palaeoclimatology, Palaeoecology, 2002)
We present mid-Pliocene (4.3–2.6 Ma) benthic stable oxygen and carbon isotope data from Ocean Drilling Program Site 1092 (ODP Leg 177) drilled in the sub-Antarctic sector of the Southern Ocean. The results are compared with the stable isotope results from nearby Site 704 (ODP Leg 114). Oxygen isotope data show that minimum values are about 0.5‰ less than those of the Holocene, which is consistent with the results from Site 704, indicating only minor deglaciation of Antarctica during the studied interval. Oxygen isotope data from both Site 1092 and Site 704 are slightly higher relative to Pacific values during several intervals which could be related to the contribution of warm, saline North Atlantic Deep Water (NADW). Comparisons of benthic carbon isotope gradients between sites located in the North Atlantic, sub-Antarctic sector of the Southern Ocean, and Pacific indicate that at times, the gradient between the Southern Ocean and the Pacific evolved differently than the Atlantic–Pacific gradient. This suggests that variations in NADW strength alone might not be responsible for the observed carbon isotope values in the Southern Ocean.
Keywords: Sørishavet; geologi; oseanografi; paleomagnetisme; paleontologi; stabile isotoper

Skipsdagboken fra hvalkokeriet "Pythia" : beriberi utbruddet i 1928 - Børresen, Dag Ingemar (Sandar historielag, 2002)
Keywords: Norge; Sørishavet; dagbøker; hvalfangst; hvalkokerier

Selv under ekstreme betingelser har man liv, finnes det også liv utenfor jorda? - Brunfelt, Arild O (Naturen, 2002)
Livets opprinnelse er et mysterium. Ikke desto mindre er mange forskere beskjeftiget med å forsøke og rekonstruere dette. Moderne forskning på livet under ekstreme betingelser på Jorda som f.eks. i dyphavet, i en innsjø under isen i Antarktis eller i en gruppe sjeldne meteoritter, har ført til en viss optimisme når det gjelder å finne liv på planeten Mars og på Jupiters månesatelliter Europa, Callisto og Ganymede.
Keywords: Antarktis; kjemiske analyser; mikrober; mikrobiologi; subglasial innsjø

Contracted spleen in seals, estimates of dilated organs, and diving capacity - Cabanac, A. J. (Polar Biology, 2002)
The spleens of several seals from both the Arctic and the Antarctic were isolated and weighed when contracted. Spleens of the crabeater, leopard, and Weddell seals formed 0.23%, 0.39%, and 0.86% of the seals' body weights; those of the hooded and harp seals formed 0.56% and 0.35% of the seals' body weights. In these 5 phocids, a contracted spleen relates to the seal's body weight according to the equation (in which weights are in kilograms; n=26; r2=0.65): contracted spleen=0.006 (body weight)-0.11. Further, using the criterion reported in the literature that contracted spleens of hooded seal and harp seals weigh 80% less than when dilated, the sizes of dilated spleens were estimated for the 5 phocids of the study, plus that of the southern elephant seal. Dilated spleens ranged from 1 to 4% of the seal's body weight, which is in agreement with determinations of dilated spleens reported in the literature (harbor, 0.8–3.0%; harp, 1.5%; hooded, 2.2–4.0%). The general correlation among dilated spleens and the 6 phocids' body weights is: dilated spleen=0.026 (body weight)-0.39(where weights are in kilograms; n=31; r2=0.70). The size of the spleen (either contracted or dilated) from the different species of seals in this study appeared to be correlated with the diving capacity of the phocids, as given in the literature. The phocids with greater diving capacities are the ones with the larger spleens.
Keywords: NARE 1996/97; Sørishavet; Weddellhavet; marin biologi; pinnipedier; seler

Joint marine project during NARE 200/01: dissolved oxygen and nutrient tracers in the marine Norwegian sector of the Antarctic - Fransson, Agneta; Nøst, Ole Anders; Olsson, Kristina; O'Dwyer, Jane; Drange, Helge; Børsheim, Knut Yngve; Gammelsrød, Tor; Søreide, Janne; Karlsen, Tor Ivan; Jensen, Glen (Norwegian Antarctic Research Expedition (NARE) 2000/2001, 2002)
Keywords: NARE 2000/01; Sørishavet; biogeokjemi; ekspedisjoner; marin biologi; oseanografi

Cryogenic grooves on a granite nunatak, Northern Victoria Land, Antarctica - French, Hugh; Guglielmin, Mauro (Norsk Geografisk Tidsskrift - Norwegian Journal of Geography, 2002)
Publisher: Routledge
Keywords: Antarktis; glasiologi; nunataker

Low phytoplankton biomass and ice algal blooms in the Weddell Sea during the ice-filled summer of 1997 - Hegseth, Else Nøst; Quillfeldt von, Cecilie Hellum (Antarctic Science, 2002)
The summer of 1997 was characterized by unusually large amounts of pack ice in the southeastern Weddell Sea, and less than 10% of the area that is commonly ice-free in summer was open. A modest phytoplankton bloom developed in the upper mixed layer in the northernmost area (72°S). The bloom peaked in mid-February with max chlorophyll concentrations of 1.5 μg l−1, and integrated stocks of 55–60 mg m−2. Autotrophic flagellates dominated the biomass (80–90% of the chlorophyll) at first, while diatoms increased relative to flagellates during the bloom. Nutrient deficits, however, indicated that a much larger biomass was produced than was observed. Freezing starting after mid-February probably terminated the bloom, resulting in a pelagic growth season limited in time (less than two months) and space. The sea ice had a distinct brown layer of algae, usually at 1–2 m depth, with average chlorophyll biomass of 10.3 mg m−2. The ice cover exhibited a substantial amount of ridges, with ice algae growing in cavities and other structures, but with lower biomass than in the bands. Ice algae were also found growing on the lower 2 m of the ice shelf (visible at low tide). The overall growth season in the ice lasted several months, and ice algal production may have exceeded pelagic production in the Weddell Sea during the growth season of 1997. Pennate diatoms, like Fragilariopsis curta and F. cylindrus, dominated both in ice and in open water above the pycnocline, while Phaeocystis antarctica dominated in deeper layers and in crack pools. Euphausiids, particularly young stages, were frequently observed grazing on ice algae in ridges and on all sides of the floes, (confirmed by the gut content). Ice algae would thus have served as an ample food supply for the krill in the summer of 1997.
Edition: 2004/04/22 Publisher: Cambridge University Press
Keywords: Sørishavet; Weddellhavet; fytoplankton; havis alger; hydrografi; krill; oseanografi

Renewal time and transport of unventilated Central Intermediate Water of the Weddell Sea derived from biogeochemical properties - Hoppema, Mario; de Baar, Hein J. W.; Fahrbach, Eberhard; Bellerby, Richard G. J. (Journal of Marine Research, 2002)
We have investigated the intermediate water mass of the central Weddell Gyre using TCO2 and oxygen data of FS Polarstern cruises in 1992, 1996 and 1998. This water mass, designated as Central Intermediate Water (CIW), is enriched in CO2 and depleted in O-2 relative to its source water due to biological degradation. CO2 enrichment and O-2 depletion were quantified by calculating the difference between the concentrations in the CIW and those in the, more southern source water, the Circumpolar Deep Water, which derives from the Antarctic Circumpolar Current. Inventories of enrichment and depletion were determined over the whole depth range of CIW, i.e. about 200800 m. The O-2 depletion inventory was greater than that of TCO2 enrichment which is in line with a biological origin of the signal. Spatial and interannual variation appeared to be small. Because subsurface remineralization in the central Weddell Gyre is largely restricted to the CIW, the export production estimate from previous work has been applied to compute the renewal time of CIW from these inventories. A renewal time of only three years was found. TCO2- and O-2-based computations were consistent, the former showing larger variation, though. From renewal time and volume of the CIW, a transport velocity (renewal rate) of 6-7 Sv was obtained. Of this, about I Sv is upwelled into the surface layer. The remaining 5-6 Sv CIW must be exported to the north, which is opposite to previous views. Results of water mass age and transport rate have thus been obtained using a method based on biogeochemical parameters. As the CIW cannot be identified by temperature and salinity, nor with transient tracers because it is hardly ventilated, this is the only way to obtain such results. As part of the CIW export, a large amount of remineralized CO2 enters the abyssal oceans where it is sequestered for long periods of time. The CIW is a principal and highly efficient player in the biological pump mechanism of the Southern Ocean.
Keywords: AABW; Sørishavet; Weddellhavet; biogeokjemi; geofysikk; havstrømmer; oseanografi; vannmasser

Annual export production in the interior Weddell Gyre estimated from a chemical mass balance of nutrients - Hoppema, Mario; de Baar, Hein J.W.; Bellerby, Richard G.J.; Fahrbach, Eberhard; Bakker, Karel (The Southern Ocean I: Climatic Changes in the Cycle of Carbon in the Southern Ocean, 2002)
Nitrate, phosphate and silicate data are presented from 1992 austral winter and 1998 austral autumn cruises with “FS Polarstern” in the Weddell Gyre. Because in the Weddell Gyre, away from the boundary current, the surface layer is eventually formed from upwelled deep water, the difference in nutrient concentrations between these layers can be used to compute net nutrient consumptions (identical with the export production). This method renders a value for the export production that is based on observed annual changes. The results are consistent for two years and two regions within the central gyre. The calculated net nitrate and phosphate consumptions were scaled to net carbon consumptions using canonical Redfield ratios, yielding 16–17μmolCkg−1yr−1. This equals 21±4gCm−2yr−1 as a robust estimate for the marginal ice zone. The net annual silicate consumption in the surface layer, which equals the export of biogenic silica, amounts to 15–18μmolkg−1yr−1. There is a tendency for higher values in the eastern Weddell Gyre. The estimated silicate consumption of about 1.8molSim−2yr−1 is relatively high compared to earlier estimations of biogenic silica export. The silicate to carbon consumption ratio of about 1 is very high, and documents the dominance of diatoms in the export of organic material. Résumé Sont présentées les distributions verticales de nitrate, de phosphate et de silicate en Mer de Weddell, pour les périodes de l’hiver austral 1992 et de l’automne austral 1998. Les eaux de surface du tourbillon à grande échelle de la Mer de Weddell (temps de résidence égal à 2.9 ans) sont formées par l’upwelling des eaux profondes. La différence de concentrations des sels nutritifs entre les couches profondes et de surface permettent de calculer la consommation annuelle, équivalente à la production exportée de l’élément nutritif considéré vers les couches profondes. Les résultats sont comparables pour les deux scénarios annuels étudiés. La production exportée de carbone pour les eaux de surface de la zone marginale de la glace, calculée à partir des consommations annuelles en nitrates et phosphates après transformation grâce aux rapports de Redfield, est estimée à 16–17μmolCkg−1yr−1 soit en moyenne 21±4gCm−2yr−1. La consommation annuelle de silicate est estimée à 1.8mol Si m−2yr−1, relativement élevée en comparaison des estimations antérieures. Le rapport molaire Si/C, voisin de 1 dans le matériel exporté, traduit la dominance des diatomées dans l’export de matières organiques.
Keywords: Sørishavet; Weddellhavet; fytoplankton; geofysikk; karbondioksid; marin biologi; oseanografi

Glacial history of the Antarctic Peninsula since the Last Glacial Maximum–a synthesis - Ingólfsson, Ólafur; Hjort, Christian (Polar Research, 2002)
The extent of ice, thickness and dynamics of the Last Glacial Maximum (LGM) ice sheets in the Antarctic Peninsula region, as well as the pattern of subsequent deglaciation and climate development, are not well constrained in time and space. During the LGM, ice thickened considerably and expanded towards the middle–outer submarine shelves around the Antarctic Peninsula. Deglaciation was slow, occurring mainly between >14 Ky BP (14C kilo years before present) and ca. 6 Ky BP, when interglacial climate was established in the region. After a climate optimum, peaking ca. 4 - 3 Ky BP, a cooling trend started, with expanding glaciers and ice shelves. Rapid warming during the past 50 years may be causing instability to some Antarctic Peninsula ice shelves.
Keywords: Antarktis; glasiologi; klimaendringer; marin geologi; paleoklimatologi

Trends and patterns in the recent accumulation and oxygen isotopes in coastal Dronning Maud Land, Antarctica: interpretations from shallow ice cores - Isaksson, Elisabeth; Melvold, Kjetil (Annals of Glaciology, 2002)
To investigate recent variability in accumulation and δ18O, we synthesize data from five snow cores, covering the period 1932–96, from the sector 16˚38’ W–4˚48’ E in coastal Dronning Maud Land (DML), Antarctica. the δ18O records from the different sites are remarkably similar and suggest a common stable moisture source for this coastal section of DML. While the accumulation pattern is local, and specific features restricted to the individual sites, the overall accumulation pattern is related to the temperature variability as indicated by coastal instrumental records. Accumulation and δ18O correlate between 1955 and 1985 but deviate thereafter, with the proxy-temperature record showing a positive trend while accumulation decreased. This occurs at the same time as an increase in sea-ice extent in the area, which may have resulted in circulation changes and more northerly storm paths. Both stacked accumulation and δ18O records show that large-scale atmospheric signals, as well as some pronounced individual events, are recorded in DML coastal ice cores.
Keywords: Dronning Maud Land; glasiologi; iskjerner

Species richness of marine soft sediments - John, S Gray (Marine Ecology Progress Series, 2002)
Marine soft sediments comprise one of the largest and oldest habitats in the world, yet remarkably little is known about patterns of species richness. Here I present a short review of patterns of species richness and possible factors that influence such patterns. Species richness in general is remarkably high in both shallow coastal areas and the deep sea. However, there are clear differences the deep-sea has higher number of species for a given number of individuals than the coast. This can be explained by the larger amounts of primary production that reach coastal compared with deep-sea sediments, leading to higher numbers of individuals per unit area. Species density (the number of species per unit area) is also higher in the deep-sea than in coastal areas, but it is not obvious why this is so. Most studies of the broad patterns of species richness have used samples taken at small scales only. The problem with such analyses is that unless a large number of samples are taken, the true underlying pattern (or lack of it) may be wrongly interpreted. Recent studies have analysed species richness at larger scales. In general there seems to be a cline of increasing species richness from the Arctic to the tropics, but this is not the case in the southern hemisphere, where Antarctic species richness is high. However, it is not known whether high species richness in the Antarctic occurs at all spatial scales. To what extent these patterns are determined by evolutionary factors remains to be determined by the application of molecular methods. The available evidence suggests that environmental factors such as productivity, temperature, and sediment grain-size diversity play dominant roles in determining patterns of regional-scale species richness and patterns in species turnover, and it is probably the regional scale that primarily determines local species richness. KEYWORDS: Diversity · Deep sea · Coasts · Patterns · Scales
Keywords: Sørishavet; biodiversitet; marin biologi; polarområdene

Production and mortality of phytoplankton and sea-ice microalgae in the Southern ocean - Johnsen, Geir; Børsheim, Knut Yngve; Johansen, Torunn (Norwegian Antarctic Research Expedition (NARE) 2000/2001, 2002)
Keywords: Bouvetøya; NARE 2000/01; Sørishavet; alger; fytoplankton; havis; marin biologi; oseanografi; sjøis; zooplankton

Studies of seals and seabirds on Bouvetøya 2000/01 - fieldwork and preliminary results - Krafft, Bjørn; Hofmeyr, Greg J G; Keith, Dave; Harck, Bianca I B; Kovacs, Kit M (Norwegian Antarctic Research Expedition (NARE) 2000/2001, 2002)
Keywords: Bouvetøya; NARE 2000/01; biologi; fugler; ornitologi; seler; zoologi

Typisk pingvin!: en bok fra Antarktis - Lillevik, Linda (Eide, 2002)
Keywords: Antarktis; Sørishavet; barnebøker; fugler

Environmental aspects of the 2000/2001 Norwegian Antarctic research expedition - Njåstad, Birgit (Norwegian Antarctic Research Expedition (NARE) 2000/2001, 2002)
Keywords: Antarktistraktaten; Dronning Maud Land; NARE 2000/01; avfallshåndtering; fauna; flora; forurensning; kartlegging; miljøvern

Distribution and food consumption of Ross seals (Ommatophoca rossii) and Leopard seals (Hydrurga leptonyx) - Nordøy, Erling S; Blix, Arnoldus Schytte (Norwegian Antarctic Research Expedition (NARE) 2000/2001, 2002)
Keywords: NARE 2000/01; Sørishavet; havis; marin biologi; seler; sjøis; zoologi

Klarius Mikkelsen's landing site: some further notes on the 1935 Norwegian visit to the Vestfold Hills, East Antarctica - Norman, Frederick Ian; Gibson, John A E; Jones, R T; Burgess, J S (Polar Record, 2002)
Further details regarding the landing made by Klarius Mikkelsen in the Tryne Islands, Vestfold Hills, East Antarctica, are given, being derived mainly from newspaper accounts made by Leif Sørsdal. All involved in the landing on 20 February 1935 have been identified, details of material left in the depot under the raised flag are given, and more extended information relating to the voyage to and from the site and the area generally are presented. Some comparison is made between Sørsdal's accounts and others. While the national importance of the landing was commented on, only Sørsdal apparently realised (but did not state) the insular nature of the site. Recent observations at the site suggest that its location is 68°22′38.22″S, 78°24′50.10″E, rather than that previously stated; bracing of the flagpole itself has been modified at some stage since its erection. Finally, some discussion is made regarding on-going questions relating to the accepted time on board ship, and possible consequences of errors.
Publisher: Cambridge University Press
Keywords: Antarktis; Nordmenn; Thorshavn ekspedisjon; første landgang; kvinner; oppdagelsesreiser

Construction and operation of Troll Runway: initial environmental evaluation - Norsk Polarinstitutt; Polarinstitutt, Norsk (Norwegian Polar Institute, 2002)
Keywords: Dronning Maud Land; logistikk; luftfart

Measuring ice shelf draft and seabed topography below Fimbulisen - Nøst, Ole Anders; Goodwin, Harvey; Rønstad, Tore; Thorsen, Stein Hugo (Norwegian Antarctic Research Expedition (NARE) 2000/2001, 2002)
Keywords: Dronning Maud Land; NARE 2000/01; glasiologi; havbunnen; isbreer; isshelf; kontinentalsokkel; topografi

Oceanographic measurements near Fimbulisen ice shelf - O'Dwyer, Jane; Nøst, Ole Anders; Karlsen, Tor Ivan; Søreide, Janne; Jensen, Glen; Fransson, Agneta; Savinov, Vladimir (Norwegian Antarctic Research Expedition (NARE) 2000/2001, 2002)
Keywords: NARE 2000/01; Sørishavet; Weddellhavet; glasiologi; hydrografi; oseanografi

Hvalfangere i Sydishavet og Sør-Afrika, 1910-1970 - Ødegaard, Torbjørn (Kystforl., 2002)
Keywords: Nordmenn; Sørishavet; biografier; erindringer; historie; hvalfangst; pelagisk; sjømenn

The gastrointestinal tract of Adélie penguins – morphology and function - Olsen, Monica; Myklebust, Reidar; Kaino, Turid; Elbrønd, Vibeke; Mathiesen, Svein (Polar Biology, 2002)
Keywords: Antarktis; pingviner; zoologi

Transport and transfer of organochlorines in the marine Norwegian Antarctic sector: field sampling programme during NARE 200/01 - Olsson, Kristina; Poltermann, Michael; Savinov, Vladimir; Vögele, Barbara; Kassobokova, Ksenia; Fransson, Agneta (Norwegian Antarctic Research Expedition (NARE) 2000/2001, 2002)
Keywords: NARE 2000/01; Sørishavet; marin biologi; oseanografi; plankton

Contribution of algal sinking and zooplankton grazing to downward flux in the Lazarev Sea (Southern Ocean) during the onset of phytoplankton bloom: a lagrangian study - Pakhomov, Evgeny A.; Froneman, Pierre W.; Wassmann, Paul; Ratkova, Tatjana; Arashkevich, Elena (Marine Ecology Progress Series, 2002)
ABSTRACT: Hydrography, chlorophyll a, phytoplankton and zooplankton dynamics and the vertical flux of particulate organic carbon (POC) and pigments in the upper 200 m were investigated for 12 consecutive days during a drogue study conducted in the open waters of the ice-edge zone of the Lazarev Sea during the austral summer (December/January) 1994/95. Results of the study indicate that during the experiment, primary production, although variable, increased from ~300 to ~800 mgC m^-2d^-1. This increase could likely be related to development of a shallow pycnocline. Analysis of sediment trap data showed that the vertical carbon flux resulting from sedimentation and grazing activity was greatest in the upper water column (<80 m). The importance of grazers to total POC flux was highest at the beginning and the end of the investigation and accounted for up to 15% of total carbon flux. The contribution of grazers to vertical flux was negligible (<2%) during the intermediate part of the Southern Ocean Drogue study. Lower contribution of grazers to sedimentation of POC at depth can likely be related to community composition of zooplankton. Sedimentation of phytoplankton cells from the upper water column increased during the study. Here, downward POC flux resulting from sedimentation of microphytoplankton was equivalent to 15-75% of the total. Increase in sedimentation of phytoplankton during the study can be related to an increase in the average size of phytoplankton cells. Transport of POC from surface waters to deeper depths resulting from sedimentation or grazing activity was equivalent to <48% of total daily primary production, measured at 50 m, while the same value for phytoplankton flux did not exceed 27% of the total. Zooplankton density was insufficient to exert either a positive (via faecal pellets) or negative (via reducing suspended phytoplankton concentration) effect on particulate carbon sedimentation. This resulted in algal sink being the most important mechanism in downward POC flux during the onset of the phytoplankton bloom period in the Marginal Ice Zone, even in the presence of pelagic tunicates.
Keywords: Sørishavet; alger; biokjemi; marin biologi; oseanografi; phytoplankton; zooplankton

Sea ice concentration off Dronning Maud Land, Antarctica - Pavlova, Olga; Winther, Jan-Gunnar (Norsk Polarinstitutt, 2002)
This project was undertaken by the Norwegian Polar Institute for the Norwegian Petroleum Directorate (Oljedirektoratet) as support for planning of marine geophysical surveys offshore from Dronning Maud Land (DML), Antarctica. The project was carried out by scientists Olga Pavlova and Jan-Gunnar Winther at the Norwegian Polar Institute under the direction of Morten Sand at the Norwegian Petroleum Directorate. The main objectives of the project were to: a) calculate 10-day average historical (i.e., 1978-1996) sea ice concentrations off DML for the months of December through April b) identify the minimum and maximum sea ice extent occurring in the period 1978-1996 c) present the above information graphically. Daily microwave satellite data covering the period 1978-1996 with 25 x 25 km spatial resolution were used as basis for this study (see text below for description of data set).
Publication Title: Norsk polarinstitutt. Rapportserie
Keywords: Dronning Maud Land; havis; kartlegging; marin geofysikk; meteorologi; sjøis

Seaweeds in Cold Seas: Evolution and Carbon Acquisition - Raven, John A.; Johnston, Andrew M.; Kübler, Janet E.; Korb, Rebecca; Mcinroy, Shona G.; Handley, Linda L.; Scrimgeour, Charlie M.; Walker, Diana I.; Beardall, John; Clayton, Margaret M.; Vanderklift, Mathew; Fredriksen, Stein; et al. (Annals of Botany, 2002)
Much evidence suggests that life originated in hydrothermal habitats, and for much of the time since the origin of cyanobacteria (at least 2·5 Ga ago) and of eukaryotic algae (at least 2·1 Ga ago) the average sea surface and land surface temperatures were higher than they are today. However, there have been at least four significant glacial episodes prior to the Pleistocene glaciations. Two of these (approx. 2·1 and 0·7 Ga ago) may have involved a ‘Snowball Earth’ with a very great impact on the algae (sensu lato) of the time (cyanobacteria, Chlorophyta and Rhodophyta) and especially those that were adapted to warm habitats. By contrast, it is possible that heterokont, dinophyte and haptophyte phototrophs only evolved after the Carboniferous–Permian ice age (approx. 250 Ma ago) and so did not encounter low (≤5 °C) sea surface temperatures until the Antarctic cooled some 15 Ma ago. Despite this, many of the dominant macroalgae in cooler seas today are (heterokont) brown algae, and many laminarians cannot reproduce at temperatures above 18–25 °C. By contrast to plants in the aerial environment, photosynthetic structures in water are at essentially the same temperature as the fluid medium. The impact of low temperatures on photosynthesis by marine macrophytes is predicted to favour diffusive CO2 entry rather than a CO2‐concentrating mechanism. Some evidence favours this suggestion, but more data are needed.
Keywords: Sørishavet; alger; biogeografi; botanikk; makroalger; marin biologi

Comparison of measurements and model calculations of stratospheric bromine monoxide - Sinnhuber, Björn‐Martin; Arlander, D William; Bovensmann, H; Burrows, J P; Chipperfield, M P; Enell, Carl-Fredrick; Frieß, U; Hendrick, F; Johnston, P V; Jones, R L; Kreher, K; Mohamed-Tahrin, N; et al. (Journal of Geophysical Research: Atmospheres, 2002)
Ground-based zenith sky UV–visible measurements of stratospheric bromine monoxide (BrO) slant column densities are compared with simulations from the SLIMCAT three-dimensional chemical transport model. The observations have been obtained from a network of 11 sites, covering high and midlatitudes of both hemispheres. This data set gives for the first time a near-global picture of the distribution of stratospheric BrO from ground-based observations and is used to test our current understanding of stratospheric bromine chemistry. In order to allow a direct comparison between observations and model calculations, a radiative transfer model has been coupled to the chemical model to calculate simulated slant column densities. The model reproduces the observations in general very well. The absolute amount of the BrO slant columns is consistent with a total stratospheric bromine loading of 20 ± 4 ppt for the period 1998–2000, in agreement with previous estimates. The seasonal and latitudinal variations of BrO are well reproduced by the model. In particular, the good agreement between the observed and modeled diurnal variation provides strong evidence that the BrO-related bromine chemistry is correctly modeled. A discrepancy between observed and modeled BrO at high latitudes during events of chlorine activation can be resolved by increasing the rate constant for the reaction BrO + ClO → BrCl + O2 to the upper limit of current recommendations. However, other possible causes of the discrepancy at high latitudes cannot be ruled out.
Keywords: Antarktis; atmosfæren; fysikk; kjemiske analyser; meteorologi; miljø; målinger; polarområdene; stratosfæren

Helse på hvalfangst - Thoresen, Per (Vestfoldminne, 2002)
Publisher: Vestfoldmuseene
Keywords: Antarktis; arbeidsforhold; erindringer; helse; hvalfangere; hvalfangst; lege; medisin; pelagisk; sjøfolk; sjømenn

Studies of population dynamics and life history strategies of Antarctic petrels at Svarthamarehn - Tveraa, Torkild; Birkeland, Ingve; Henden, John-André; Varpe, Øystein (Norwegian Antarctic Research Expedition (NARE) 2000/2001, 2002)
Keywords: Dronning Maud Land; NARE 2000/01; fugler; ornitologi; petreller; zoologi; økologi

Body Condition and Parental Decisions in the Snow Petrel (Pagodroma nivea) - Tveraa, Torkild; Guttorm, N. Christensen (The Auk, 2002)
In Procellariiformes, parents guard the chick for some time after it has attained homeothermy. Such a strategy may have evolved to protect the chick from predation or inclement weather, but it is costly because only one parent can forage at a time. Therefore, the decision to leave the chick seems to be a trade-off between the chick's ability to care for itself, body condition of the parent present at the nest, and ability of the bird out foraging to return to the nest before its mate's body condition has degraded. We studied chick growth and survival together with number of days Snow Petrel (Pagodroma nivea) chicks were guarded before being left alone for the first time in relation to the parents body condition and ability to return to the nest in time. Parents in good body condition were more likely to produce a chick that survived the guard stage. They also guarded their chick for a longer period (range 2–8 days, x̄ = 4.5) and finally left it alone with a higher body mass than those in poor body condition. However, whether the foraging bird was able to return to the nest in time to relieve its mate was also strongly related to number of days the chick was guarded and its body mass. The chicks' survival from when they were left alone and until day 10 posthatch was positively related both to number of days they were guarded and their body condition (body mass corrected for age).
Publisher: American Ornithological Society Second DOI: https://doi.org/10.1093/auk/119.1.266
Keywords: Antarktis; fugler; ornitologi; petreller; zoologi

Effect of isolation temperature on the characteristics of extracellular proteases produced by Antarctic bacteria - Vazquez, Susana C; Mac Cormack, Walter P (Polar Research, 2002)
Protease-producing psychrotolerant bacteria were isolated from Antarctic biotopes on casein agar plates using different incubation temperatures. Most of the isolates were non-spore-forming Gram-negative motile rods with catalase activity, 30% were pigmented and none of them were glucose fermenters. All the strains were grown in liquid cultures at 20°C and protease secretion was tested using the azocasein method. Despite their capacity for production of a clear zone of hydrolysis in agar plates, some strains did not produce detectable levels of proteolytic activity in liquid cultures. The lowest apparent optimum temperature for protease activity found in culture supernatants was 40°C. Almost all the strains showed activation energy values about 10-20 kJ-mol?1 lower than that observed for a mesophilic Subtilisin. Most of the proteases showed optimal activity at neutral or alkaline pH values and developed a multiple-band profile on gelatine-SDS-PAGE. It was observed that the lower the strain isolation temperature was, the more stongly cold-adapted–in terms of optimal temperature and activation energy–were the proteases produced by them. This dependence of the characteristics of the proteases on the isolation temperature is an important factor to take into account in the design of screening programmes directed towards the isolation of psychrotolerant bacteria able to produce proteases strongly or weakly adapted to work in the cold. The Antarctic area explored proved to be a promising source of proteolytic bacteria with potential use in industrial processes to be carried out at low or moderate temperatures.
Keywords: Antarktis; analyser; bakterier; ekspedisjoner; mikrobiologi

Norwegian Antarctic Research Expedition (NARE) 2000/2001 - Winther, Jan-Gunnar (ed.) (Norsk Polarinstitutt, 2002)
Publication Title: Norsk Polarinstitutt. Rapportserie
Keywords: Dronning Maud Land; biologi; ekspedisjoner; forskning; geodesi; glasiologi; logistikk; marin biologi; miljøvern; naturressurser

European project for ice coring in Antarctica (EPICA) - Nordic traverse in 2000/01 - Winther, Jan-Gunnar; Karlöf, Lars; Hofstede, Coen; Johansen, Einar; Johansen, Jan-Tore; De Jong, Eric-Jan; Kaspers, Karsten; Lappegard, Gaute; Pettersson, Rikard; Tronstad, Stein; Van De Wal, Roderik (Norwegian Antarctic Research Expedition (NARE) 2000/2001, 2002)
Keywords: Dronning Maud Land; NARE 2000/01; akkumulasjon; atmosfæren; ekspedisjoner; geofysikk; geografi; glasiologi; innlandsis; is radar; iskjerner; klimatologi; meteorologi; snø radar; topografi

Norwegian use of the polar oceans as occupational arenas and exploration routes - Barr, Susan (Polar Record, 2001)
Publisher: Cambridge University Press
Keywords: Antarktis; Nordmenn; Norge; ekspedisjoner; forskning; geografi; historie; oppdagelsesreiser; polarområdene

Holocene and pre-Holocene temporary disappearance of the George VI Ice Shelf, Antarctic Peninsula - Bentley, Michael J.; Hjort, Christian; Ingólfsson, Ólafur (Antarctic Science, 2001)
We present evidence for the absence of the George VI Ice Shelf during a brief period in the mid-Holocene and during one or more earlier interstadials or interglacials. Barnacle Bathylasma corolliforme shells sampled from ice shelf moraines at Two Step Cliffs on Alexander Island have been dated to c, 5750–6000 14C yr BP(c. 6550–6850 cal yr BP) and imply seasonally open water in the George VI Sound during this period. Other shells are beyond the range of radiocarbon dating and imply open water during one or more previous interglacial or interstadial period, prior to 40 000 14C yr BP. Our results show that the ongoing collapse of some Antarctic Peninsula ice shelves is not unprecedented.
Edition: 2004/04/27 Publisher: Cambridge University Press
Keywords: Antarktis; geomorfologi; glasiologi; holocene; isshelf

Den 3. Fram-ferd - Berg, Kåre (Polarskipet Fram : unik skipskonstruksjon for tre polarferder : Nansen minneforelesning 11. oktober 1999, 2001)
Keywords: Antarktis; Fram (skip); Sydpolsekspedisjonen; oppdagelsesreiser; polarekspedisjoner

Revision of Stegosoladidus Barnard and Karaman, 1987 (Crustacea: Amphipoda: Stegocephalidae), redescription of two species and description of three new species - Berge, Jørgen (Journal of Natural History, 2001)
Stegosoladidus simplex (K. H. Barnard, 1930) and S. ingens (Chevreux, 1906) are both figured and redescribed. Three new species (Stegosoladidus antarcticus, S. complex and S. debroyeri) are described. The terminology used for classification of both setae and different setae arrangements is discussed, and the main types of setae are figured.
Publisher: Taylor & Francis
Keywords: Sørishavet; amfipoder; taksonomi; zoologi

Current measurements near Ronne Ice Shelf: implications for circulation and melting - Foldvik, Arne; Gammelsrød, Tor; Nygaard, E.; Østerhus, Svein (Journal of Geophysical Research: Oceans, 2001)
We present the first year-long current meter records ever obtained near the floating Filchner-Ronne Ice Shelf in the Weddell Sea. The currents are steered along the ice front, but in the lower layer where the bottom topography is descending toward the west the current has a component toward the ice front of about 3 cm s−1. During winter the temperature stayed near the surface freezing point, while the salinity increased, indicating that ice was formed and brine released. The seasonal variation in salinity was 0.15±0.05 psu, corresponding to the formation of 1–2 m of ice on a shelf depth of 400 m. The transport of High-Salinity Shelf Water (HSSW) into the ice shelf cavity was found to be of the order 0.5×106 m3 s−1. The production of this water due to oscillating tides and off shelf winds was found to be of the same order of magnitude. In contact with glacial ice at great depths, and because of the depression of the freezing point, the HSSW is transformed to Ice Shelf Water (ISW) by cooling and melting processes. The melting rate was estimated to 1×1011 ton yr−1. This corresponds to the melting of 0.2 m ice per year if the melting is evenly distributed over the Filchner-Ronne Ice Shelf. If the melting is concentrated along a path from the Berkner Shelf around the Berkner Island to the Filchner Depression, then melting rates up to 7 m yr−1 must be expected. A comparison of HSSW characteristics in the Ronne Depression, our winter observations on the Berkner Shelf, and the ISW flowing out of the Filchner Depression indicates that very little water passes through the cavity from the Ronne to the Filchner Depression. It appears that most of the ISW originating from processes on the Berkner Shelf escapes the cavity in the Filchner Depression. This leaves the Berkner Shelf as the important source of ISW and subsequently of the Weddell Sea Bottom Water formed from ISW.
Keywords: Antarktis; Weddellhavet; havstrømmer; isshelf; oseanografi

Antarctic marine benthic biodiversity in a world-wide latitudinal context - Gray, John S. (Polar Biology, 2001)
In the 1950s and 1960s, the first data sets were assembled to examine whether or not there was a latitudinal gradient of species richness in the sea. These data comprised very few species and were from very small areas. However, recent data from large species lists covering broad geographical ranges suggest strongly that there is a gradient of increasing species richness from the Arctic to the tropics. However, the Southern Ocean has high species richness and in the southern hemisphere there is no clear evidence of a cline of increasing richness from pole to tropic. The great richness of the Southern Ocean compared with the Arctic is probably due to its great age, the fact that it covers a much larger area and that it has higher structural heterogeneity formed by living organisms. The importance of area as a determinant of species richness needs to be studied in more detail since most studies have been confined to small areas. A number of hypotheses have been proposed to explain the species:area relationship and these are discussed. An alternative explanation for the latitudinal cline in the northern hemisphere is the energy-input hypothesis, but again this has not been adequately tested. Two studies on the relationship between local and regional species richness show a significant positive correlation. These findings suggest that local assemblages are not tightly organised and saturated with species but are open to recruitment from the regional species pool. Whether or not such a relationship holds in Antarctica is unknown. It is concluded that further studies of the Southern Ocean are likely to provide new findings fundamental to the "new" discipline of macroecology, which examines patterns and processes at the geographic scale.
Keywords: Sørishavet; bentiske organismer; bentos; biodiversitet; marin biologi; økologi

Direct measurements reveal insignificant storage of anthropogenic CO2 in the Abyssal Weddell Sea - Hoppema, Mario; Roether, Wolfgang; Bellerby, Richard G. J.; de Baar, Hein J. W. (Geophysical Research Letters, 2001)
In the northern Weddell Gyre at the prime meridian, Total TCO2 changes in the Weddell Sea Bottom Water (WSBW) have been investigated. Following a suggestion by [Poisson and Chen, 1987], the TCO2 difference at potential temperatures of 0.2°C and −0.8°C was determined using data from 1996 and 1998. No significant difference was found to similar differences for the years 1973 and 1981 reported by Poisson and Chen. Thus, over a period of 25 years an at most minor amount of anthropogenic CO2 has penetrated into the WSBW at this location. This suggests that this abyssal subpolar region is relatively unimportant for the storage of anthropogenic CO2. The same core of WSBW exhibited a marked increase of chlorofluorocarbon (CFC). For the Southern Ocean, therefore, CFCs are apparently of limited value as analogues of anthropogenic CO2, in contrast to some other ocean provinces.
Keywords: Sørishavet; Weddellhavet; antropogenisk CO2; drivhusgasser; geofysikk; klimagasser

Tropospheric response to stratospheric ozone loss - Kindem, Ina T; Christiansen, Bo (Geophysical Research Letters, 2001)
The response to realistic total column ozone trends on the troposphere and the stratosphere as simulated by the ARPEGE General Circulation Model (GCM) has been investigated. In both hemispheres, the lower stratosphere cooled and the polar vortex strengthened significantly during spring/early summer. The cooling trend was weaker than the observed trend in the Northern Hemisphere (NH), but stronger than the observed trend in the Southern Hemisphere (SH). In the troposphere, the changes in geopotential height resembled the positive phase of the Arctic Oscillation (AO) in the NH in March and the positive phase of the Antarctic Oscillation (AAO) in the SH during summer (December–February).
Keywords: Antarktis; geofysikk; meteorologi; ozonhull; ozonlaget

Counts of southern elephant seals, Mirounga leonina, at Bouvet Island - Kirkman, S. P.; Hofmeyr, G. J. G.; Bester, M. N.; Isaksen, K. (Polar Biology, 2001)
Southern elephant seals were counted and classified into subjective sex-age classes on a weekly basis during expeditions to Bouvet Island in the austral summers of 1996/1997 and 1998/1999. The expeditions coincided with the moulting period of elephant seals aged one year and older. The presence of weaned pups at the principal haulout site, Nyrøysa/Westwindstranda, during the latter expedition, indicates that breeding took place here during 1998. Elephant seal counts from previous expeditions are summarised.
Keywords: Bouvetøya; NARE 1996/97; NARE 1998/99; marin biologi; pinnipedier; seler

Measuring snow and glacier ice properties from satellite - König, Max; Winther, Jan-Gunnar; Isaksson, Elisabeth (Reviews of Geophysics, 2001)
Satellite remote sensing is a convenient tool for studying snow and glacier ice, allowing us to conduct research over large and otherwise inaccessible areas. This paper reviews various methods for measuring snow and glacier ice properties with satellite remote sensing. These methods have been improving with the use of new satellite sensors, like the synthetic aperture radar (SAR) during the last decade, leading to the development of new and powerful methods, such as SAR interferometry for glacier velocity, digital elevation model generation of ice sheets, or snow cover mapping. Some methods still try to overcome the limitations of present sensors, but future satellites will have much increased capability, for example, the ability to measure the whole optical spectrum or SAR sensors with multiple polarization or frequencies. Among the methods presented are the satellite-derived determination of surface albedo, snow extent, snow volume, snow grain size, surface temperature, glacier facies, glacier velocities, glacier extent, and ice sheet topography. In this review, emphasis is put on the principles and theory of each satellite remote sensing method. An extensive list of references, with an emphasis on studies from the 1990s, allows the reader to delve into specific topics.
Keywords: Antarktis; glasiologi; satellite bilder

Kval i sikte - frå fjellbygda : nokre blad or soga om kvalfangarane i Rauland og Vinje - Landsverk, Helga; Kjelingtveit, Tone Liv; Bylander, Olof; Henriksveen, Herman (Rauland historielag, 2001)
Keywords: Nordmenn; Sørishavet; historie; hvalfangere; pelagisk hvalfangst

Don Pedro : Norges mest vellykkede emigrant - Larsen, Joar Hoel (Kagge, 2001)
Keywords: Carl Anton Larsen; Nordmenn; Sørishavet; fiskeindustri; hvalfangere; hvalfangstindustri; hvalindustri; pelagisk; økonomi

Rapid climate shifts in the southern African interior throughout the Mid to Late Holocene - Lee-Thorp, Julia; Holmgren, Karin; Lauritzen, Stein Erik; Linge, Henriette; Moberg, Anders; Partridge, Timothy C; Stevenson, Chris; Tyson Peter D. (Geophysical Research Letters, 2001)
A detailed climate proxy record based on δ18O, δ13O, and grey index of a well-dated stalagmite from Cold Air Cave in the Makapansgat Valley of north-eastern South Africa suggests that regional precipitation, temperatures and vegetation oscillated markedly and rapidly over the last ∼6500 years on centennial and multi-decadal scales. The mid-Holocene prior to 5200 years ago was humid and warm. A fundamental transition occurred 3200 years ago, leading to drier and cooler conditions that culminated at 1750 AD. Comparisons with ice core records suggest synchronous changes implicating rapid global teleconnections.
Keywords: Antarktis; arkeologi; geografi; geologi; klimaendringer; klimatologi; paleontologi

Growing Gondwana and Rethinking Rodinia: A Paleomagnetic Perspective - Meert, Joseph G. (Gondwana Research, 2001)
The formation of Gondwana during the late Neoproterozoic to early Cambrian times (550-530 Ma) was traditionally viewed as the welding of two, more or less contiguous, Proterozoic continental masses called East and West Gondwana. The notion of a united West Gondwana is no longer tenable as a wealth of geochronologic and structural data indicate major orogenesis amongst its constituent cratons during the final stages of greater Gondwana assembly. The idea that East Gondwana may also have formed through the amalgamation of a collage of cratonic nuclei during the Cambrian is controversial. Recent paleomagnetic, geochronologic and structural data from elements of East Gondwana indicate that its formation may have extended well into Cambrian time. Thus, the terms ‘East’ and ‘West’ Gondwana may be relegated to convenient geographical terms rather than any connotation of tectonic coherence during the Proterozoic. In addition, the paleomagnetic data also challenge the conventional views of the Neoproterozoic supercontinent Rodinia and the SWEAT fit. Alternative variants including Protopangea and AUSWUS are not supported by paleomagnetic data during the interval 800–700 Ma.
Keywords: Antarktis; geokronologi; geologi; paleomagnetisme

Oceanographic conditions south of Berkner Island, beneath Filchner-Ronne Ice Shelf, Antarctica - Nicholls, Keith William; Østerhus, Svein; Makinson, Keith; Johnson, Michaela R. (Journal of Geophysical Research: Oceans, 2001)
We have made oceanographic measurements at two sites beneath the southern Filchner-Ronne Ice Shelf. Hot-water drilled access holes were made during January 1999, allowing conductivity-temperature-depth (CTD) profiling and the deployment of instrument moorings. The CTD profiles show that the entire water column is below the surface freezing point. We estimate the (summer) flux of water between the two sites to be 2×106 m3 s−1. The summer potential temperature-salinity properties of the water column suggest that this flow is part of a recirculation in the deepest part of the subice shelf cavity and the Filchner Depression. The recirculation is driven by a combination of the melting of deep basal ice and the freezing that results from the depressurization of the cold buoyant water as it ascends the ice shelf base. The source of the water was high-salinity shelf water (HSSW) produced in the Ronne Depression. This is the water that provides the external heat necessary for the strong melting at the deep grounding lines in the vicinity of Foundation Ice Stream. Instruments moored at the drill sites show that during the winter HSSW formed on the Berkner Shelf flows beneath the ice shelf and largely displaces the recirculating water from the two sites. This provides an externally driven through flow that is warmer (nearer the surface freezing point) and slower than the internal recirculation and which is low enough in density to escape the Filchner Depression.
Keywords: Antarktis; geofysikk; havstrømmer; oseanografi

Quantitative models for reconstructing catchment ice-extent using physical-chemical characteristics of lake sediments - Noon, P.E.; Birks, H.J.B.; Jones, V.J.; Ellis-Evans, J.C. (Journal of Paleolimnology, 2001)
The physical characteristics of surface sediments from a suite of pristine lakes on Signy Island, maritime Antarctic, were used to develop a quantitative link between catchment ice-extent and lake-sediment response. Percentage dry weight, median particle size, percentage loss-on-ignition and wet density of the lakes' surface sediments were the most significant variables explaining contemporary catchment ice-extent. Two independent reconstruction models – Partial Least Squares (PLS) and a Modern Analog Technique (MAT) – were applied to dated sediment cores at two sites on Signy Island. The validity of the reconstructions was tested against historical information on catchment ice-extent. With sufficiently high sedimentation rates and sampling resolution, the models can predict sub-decadal changes in ice-extent. The model results are best regarded as indicators of erosion resulting from meltwater activity in the catchment. Comparison of results with Twentieth Century climate records affirms the hypothesis that climatic warming is the most likely cause for the ice retreat observed on Signy Island during the last 40 yrs. Similar reconstruction models using these simple sedimentary measures could be developed for analogous locations in the Antarctic and in Arctic and Alpine regions.
Keywords: Antarktis; innsjø; klimaendringer; paleolimnologi; sedimenter; økologi

Historien om skuta Vesleper - Olsen, Else Mehren (Follominne: årbok, 2001)
Keywords: Antarktis; Bouvetøya; Peter I. Øy; Sørishavet; ekspedisjoner; historie; hvalfangst

Phytoplankton dynamics at the ice-edge zone of the Lazarev Sea (Southern Ocean) during the austral summer 1994/1995 drogue study - Pakhomov, Evgeny; Ratkova, Tatjana; Froneman, Pierre W.; Wassmann, Paul (Polar Biology, 2001)
Phytoplankton dynamics in the open waters of the ice-edge zone of the Lazarev Sea were investigated over 12 consecutive days during a drogue study conducted in austral summer (December/January) 1994/1995. Throughout the study, the upper water column (<30 m) was stratified with a well-defined pycnocline evident. Although a subsurface intrusion of colder, more saline water into the region was recorded on days 5–9 of the experiment, its effect on the water column structure was negligible. Total surface chlorophyll a biomass doubled between days 1 and 5 (from 0.82 to 1.62 mg m–3), and then showed a tendency to stabilise, while the depth-integrated chlorophyll a standing stock displayed an increasing trend during the entire experiment. All changes in biomass were associated with an increase in microphytoplankton. Flagellates and picoplankton dominated cell counts, while diatoms composed most of the phytoplankton biovolume. Results of the study indicate that, during the period of investigation, average cell abundance decreased. Coupled with this decrease was an increase in the biovolume and average size of the phytoplankton. Phytoplankton succession was observed in the ice edge during the drogue study. Typical ice-associated species of genera Haslea, Fragilariopsis and Chaetoceros, which dominated at the beginning of study, were replaced by open-water species of genera Corethron, Dactyliosolen and Rhizosolenia. The shift in phytoplankton species composition and size can likely be related to high light intensities and grazing by microzooplankton. The intrusion of colder, more saline water on day 5 appeared to modify the diatom succession, indicating extreme variability in phytoplankton dynamics in the near ice-edge zone of the Lazarev Sea.
Keywords: Sørishavet; fytoplankton; marin biologi; oseanografi

Protecting whales by distorting uncertainty: non-precautionary mismanagement? - Schweder, Tore (Fisheries Research, 2001)
Precautionary management is based on science, and is incompatible with large fluctuations in the management regime. Whaling is managed by the International Whaling Commission, and has seen large fluctuations. It is argued that both the period of intense Antarctic whaling and the current period of protectionism have been unduly prolonged by scientists expanding out of proportion the uncertainty surrounding management issues. In the 1950s, uncertainty concerning fin whale stock status and trend was consistently distorted from one quarter, and in the 1990s a minority in the Scientific Committee blocked consensus over the revised management procedure that had been successfully developed by the Committee. In both cases, the political consequence of expanded uncertainty in the science was lack of action resulting in a continuation of business as usual. Extending a period of heavy exploitation longer than the resource can sustain is mismanagement. Extending a period of extreme protectionism when the resource is known to scientists to sustain valuable exploitation is also mismanagement even from a conservationist point of view. This might, in fact, erode the role of science in management and thus prepare the ground for subsequent overexploitation. Distorting uncertainty by injecting controversy or otherwise expanding uncertainty has contributed to excessive fluctuations in management regimes and consequently in stock abundance. Detrimental fluctuations might continue, since science is side tracked and management now is based on sentiments that might fade.
Keywords: Den internasjonale hvalfangstkommisjonen; Sørishavet; fiskeri; hvalfangst; marine økosystemer

Kvalfangsteventyret i Antarktis - Tokheim, Henrik (Vindetreet: sogeskrift for Vindafjord, 2001)
Keywords: Sørishavet; historie; hvalfangst

Man in extreme environments - Brubakk, Alf O. (Aviation, space, and environmental medicine, 2000)
Humans have demonstrated the ability to live and work in many adverse environments. Many examples demonstrate that our understanding of humans ability to adapt to extreme environments is limited, but it is reasonable to assume that the main problems in space exploration will be psychological and social. It is argued that polar expeditions of an earlier age are a better model for space exploration than confinement studies or Antarctic overwintering. Some aspects of the reason for the success of these expeditions are discussed and the lessons that can be used are pointed out.
Supplement: S
Keywords: Antarktis; fysiologi; overvintring; polarekspedisjoner; polarområdene

Et liv i isen : polarkokken Adolf H. Lindstrøm - Ekeberg, Jan Ove (Kagge forl., 2000)
Keywords: Antarktis; Roald Amundsen; Sydpolsekspedisjonen; oppdagelsesreiser; polarekspedisjoner

Fra Haugesund til isødet i Antarktis: en hvalfanger forteller - Evensen, Karin H (Akademisk fagforlag, 2000)
Keywords: Antarktis; historie; hvalfangst

Lipids, trophic relationships, and biodiversity in Arctic and Antarctic krill - Falk-Petersen, Stig; Hagen, Wilhelm; Kattner, Gerhard; Clarke, Andrew; Sargent, John (Canadian Journal of Fisheries and Aquatic Sciences, 2000)
Environmental seasonality is a critical factor in structuring polar marine ecosystems. The extensive data now available on the lipids of Arctic and Antarctic euphausiids show that all species are characterised by a seasonally high lipid content, and neutral lipids, whether wax esters or triacylglycerols, are primarily accumulated for reproduction. The Arctic Thysanoessa inermis and the Antarctic Euphausia crystallorophias contain high levels of wax esters and higher concentrations of 18:4(n-3) and 20:5(n-3) and a lower ratio of 18:1(n-9)/(n-7) fatty acids in their neutral lipids than the Arctic Thysanoessa raschii and the Antarctic Thysanoessa macrura and Euphausia superba. Large amounts of phytol in the lipids of T. raschii and E. crystallorophias during winter suggest the ingestion of decaying algae originating in sedimenting material or in sea ice. Thysanoessa raschii, T. macrura, and E. superba have a high ratio of 18:1(n-9)/ (n-7) fatty acids, indicating animal carnivory. We conclude that T. inermis and E. crystallorophias are true high polar herbivores, while T. raschii, T. macrura, and E. superba are omnivores with a more boreal distribution. The Arctic species Thysanoessa longicaudata and Meganyctiphanes norvegica are carnivores feeding on Calanus, as indicated by high amounts of 20:1(n-9) and 22:1(n-11) fatty acids.
Keywords: Antarktis; biodiversitet; copepoder; krill; marin biologi; marine økosystemer; plankton

Spatial gradients in snow layering and 10 m temperatures at two EPICA-Dronning Maud Land (Antarctica) pre-site-survey drill sites - Holmlund, P.; Gjerde, K.; Gundestrup, N.; Hansson, M.; Isaksson, E.; Karlöf, L.; Nman, M.; Pettersson, R.; Pinglot, F.; Reijmer, C. H.; Stenberg, M.; Thomassen, M.; et al. (Annals of Glaciology, 2000)
During the 1997/98 field season, Sweden, Norway and The Netherlands performed a pre-site survey for EPICA in Dronning Maud Land, Antarctica. This paper summarizes the results and pays special attention to the high spatial gradients found in snow layering and temperatures. The sites were "Camp Victoria" (CV) on Amundsenisen (76° S, 8° W; 2400 m a.s.l.), approximately 550 km from the coast, and "Camp Maudheimvidda" (CM) on Maudheimvidda (74° S 13° W; 362 m a.s.L), some 140 km from the coast.The drilling programme included both medium-long firn/ice cores and shallow firn cores. These were analysed by means of δ18O, DEP, ECM,β activity, density, and ion content. The combined results suggests a mean annual accumulation rate of 60 mm. we. for CV and 220 mm. we. for CM.Variability measurements of spatial snow layering were performed at two scales; over tens of kilometres by radar and over a few metres by pits and high-resolution radar soundings. Results, as measured by relative standard deviation, were typically 10% on the polar plateau and as high as 50% near the coast.The 10 m temperature measurements were –38.5°C (std dev. = 0.5°) for CV and –17.6°C (std dev.=0.15°) for CM.Snow chemistry was sampled at each medium-long-core drill site. Comparison of δ18O profiles from snow pits and the uppermost part of the CV medium-long core showed large variations. Mean δ18O valuesover 2 m profiles varied between 41.6%, and 39.7%o within a horizontal distance of 50 m.
Edition: 2017/09/14 Publisher: Cambridge University Press
Keywords: Dronning Maud Land; glasiologi; iskjerner; klimatologi

Studies of seabirds and seals on Bouvetøya 1998/99 - Isaksen, Kjell; Huyser, Onno; Kirkman, Steve; Wanles, Ross; Wilson, Wendy (2000)
Keywords: Bouvetøya; forskning; fugler; pinnipedier; seler; zoologi

A 1500 year record of accumulation at Amundsenisen western Dronning Maud Land, Antarctica, derived from electrical and radioactive measurements on a 120 m ice core - Karlöf, Lars; Winther, Jan-Gunnar; Isaksson, Elisabeth; Kohler, Jack; Pinglot, Jean Francis; Wilhelms, Frank; Hansson, Margareta; Holmlund, Per; Nyman, M; Pettersson, Rikard; Stenberg, Malin; Thomassen, M P A; et al. (Journal of Geophysical Research: Atmospheres, 2000)
During the Nordic EPICA pre-site survey in Dronning Maud Land in 1997/1998 a 120 m long ice core was retrieved (76°00′S 08°03′W, 2400 m above sea level). The whole core has been measured using the electric conductivity measurement (ECM) and dielectric profiling (DEP) techniques, and the core chronology has been established by detecting major volcanic eruptions. In a nearby shallow core radioactive traces from nuclear tests conducted during the 1950s and 1960s have been identified. Altogether, 13 ECM and DEP peaks in the long core are identified as originating from specific volcanic eruptions. In addition two peaks of increased total β activity are identified in the short core. Accumulation is calculated as averages over the time periods between these dated events. Accumulation rate is 62 millimetres (w. eq./yr) for the last 181 years (1816 A.D. to present) and 61 mm w. eq./yr for the last 1457 years (540 A.D. to present). Our record shows an 8% decrease in accumulation between 1452 and 1641 A.D. (i.e. part of the Little Ice Age), compared to the long-term mean.
Keywords: Dronning Maud Land; geofysikk; glasiologi; innlandsis; iskjerner; paleoklimatologi

Geochronologic evidence for Early Cretaceous volcanic activity on Barton Peninsula, King George Island, Antarctica - Kim, Hyeoncheol; Ik Lee, Jong; Young Chose, Moon; Cho, Moonsup; Zheng, Xiangshen; Sang, Haiquing; Qiu, Ji (Polar Research, 2000)
Ages of six volcanic and plutonic rocks on Barton Peninsula, King George Island, were determined using 40Ar/39Ar and K-Ar isotopic systems. The 40Ar/39Ar and K-Ar ages of basaltic andesite and diorite range from 48 My to 74 My and systematically decrease toward the upper stratigraphic section. Two specimens of basaltic andesite which occur in the lowermost sequence of the peninsula, however, apparently define two distinct plateau ages of 52-53 My and 119-120 My. The latter is interpreted to represent the primary cooling age of basaltic andesite, whereas the former is interpreted as the thermally-reset age caused by the intrusion of Tertiary granitic pluton. The isochron ages calculated from the isotope correlation diagram corroborate our interpretation based on the apparent plateau ages. It is therefore likely that volcanism was active during the Early Cretaceous on Barton Peninsula. When the K-Ar ages of previous studies are taken into account with our result, the ages of basaltic andesite in the northern part of the Barton Peninsula are significantly older than those in the southern part. Across the north-west-south-east trending Barton fault bounding the two parts, there are significant differences in geochronologic and geologic aspects.
Keywords: Antarktis; geokronologi; geologi; vulkaner

Diet and estimated food consumption of Antarctic fur seals at Bouvetøya during summer - Kirkman, Stephen; Wilson, W.; Klages, Norbert; Bester, Marthán; Isaksen, Kjell (Polar Biology, 2000)
Collection and analysis of natural regurgitations and fresh scats, deposited by Antarctic fur seals at the Nyrøysa colony, Bouvetøya, during December 1998 to February 1999, afforded a comprehensive description of the dietary composition of this expanding population during the summer months. Mature, adult Euphausia superba was the staple diet of fur seals at Nyrøysa, while squid and myctophid fish appeared to be taken opportunistically. In metric tons, the total Bouvetøya fur seal population is estimated to have consumed a minimum of 14,365 t krill (representing 1.2713 × 1010 individuals of 1.13 g mass), 186 t fish, 184 t squid and 14,735 t over 3 months, but there are many possible sources of error in these estimates. It is presumed that over-indulgence in krill may cause animals to regurgitate ashore.
Keywords: Bouvetøya; marin biologi; pelsseler; pinnipedier; seler; zoologi

Effort explores 130 Million years of Antarctic paleoenvironment - Kristoffersen, Yngve; Goodwin, Ian D; Cooper, Alan K (Eos, Transactions American Geophysical Union, 2000)
Antarctic climate history has been dominated by events and turning points with causes that are poorly understood. To fill the gaps in our knowledges new effort is underway in the international geologic community to acquire and coordinate the circum-Antarctic geologic data needed to derive and model paleoenvironments of the past 130 m.y. The effort, which focuses principally on using shallow (<100 m) stratigraphic drilling and coring to acquire the geologic data, is being led by the Antarctic Offshore Stratigraphy Project (ANTOSTRAT), a group that works under the aegis of the Scientific Committee on Antarctic Research (SCAR). About 40 scientists from 12 countries met this past summer in Wellington, New Zealand, at an ANTOSTRAT meeting to discuss strategies for implementing the desired paleoenvironmental field and modeling studies. The meeting was held in conjunction with the 8th International Symposium on Antarctic Earth Sciences.
Keywords: Antarktis; geologi; geovitenskap; klimatologi; paleontologi; stratigrafi

Pilot shallow drilling on the continental shelf, Dronning Maud Land, Antarctica - Kristoffersen, Yngve; Strand, Kari; Vorren, Tore; Harwood, Dave; Webb, Peter (Antarctic Science, 2000)
A light, mining drill rig deployed from the stern of a research vessel has been used to carry out shallow drilling in 212 m water depth on the continental shelf in the eastern Weddell Sea. Penetration was 15 m below the seabed with 18% recovery in the 31 hours available for the experiment. The recovered glacigenic sediments are predominantly volcanic material of basaltic and andesitic composition with petrological characteristics and age similar to the continental flood basalts exposed in Vestfjella, about 130 km upstream from the drill site. The sediments include a reworked marine Miocene diatom flora. The material documents oscillations of the East Antarctic Ice Sheet over the past 30 ka. The lowermost diamicton probably represents a deformation till, and the grounding line retreated past the drill site 30 km from the shelf edge about 30 kyr BP. A readvance occurred during the Late Wisconsin Glacial Maximum. Assuming a reservoir correction of 1300 yr, marine conditions existed at the site between 10.1-7 kyr BP, and later at least between 2.8 and 2.5 kyr BP. The stratigraphy at the site has been disturbed by iceberg ploughing and/or contact between the ice shelf and the sea floor during local advances after 2.5 kyr BP.
Publisher: Cambridge University Press
Keywords: Dronning Maud Land; Weddellhavet; geokjemi; geologi; glasiologi; havbunnen; innlandsis; isshelf; kontinentalsokkel; stratigrafi

Shelf progradation on a glaciated continental margin, Queen Maud Land, Antarctica - Kristoffersen, Yngve; Winterhalter, Boris; Solheim, Anders (Marine Geology, 2000)
A detailed survey of the continental margin in the eastern Weddell Sea demonstrates shelf progradation by material input from discrete glacial wedges that amalgamate to form the present near rectilinear shelf edge. Kvitkuven Ice Rise is located between two trough mouth fans and rests on a thick sediment substratum that predates the shelf sequences north of it. Shelf progradation, west of the ice rise, preceded the progradation east of it. In this way the seaward progression of a shelf edge may reflect the broad scale expansion of the East Antarctic Ice Sheet, but the timing of shelf progradation can be different in adjacent areas. The progradational glacial wedges on the continental shelf mapped by this survey are correlated stratigraphically to be within the post Late Miocene glacial sequence, drilled at ODP Site 693 on the middle continental slope 200 km to the northeast. Two submarine moraine ridge complexes on the shelf parallel the shelf edge. A radiocarbon age of 18:950 280 years BP from the front of the inner complex (water depth 319 m) suggests that grounded ice at most reached the present mid-shelf area in front of the ice rise during the Late Wisconsin Glacial Maximum, or had retreated to this position at that time.
Keywords: Dronning Maud Land; Weddellhavet; marin geofysikk; marin geologi; oseanografi; seismisk stratigrafi

Combined characterisation of GOME and TOMS total ozone measurements from space using ground-based observations from the NDSC - Lambert, J.-C.; Van Roozendael, M.; Simon, P.C.; Pommereau, J.-P.; Goutail, F.; Gleason, J.F.; Andersen, S.B.; Arlander, D.W.; Bui Van, N.A.; Claude, H.; de La Noë, J.; De Mazière, M.; et al. (Advances in Space Research, 2000)
Several years of total ozone measured from space by the ERS-2 GOME, the Earth Probe TOMS, and the ADEOS TOMS, are compared with high-quality ground-based observations associated with the Network for the Detection of Stratospheric Change (NDSC), over an extended latitude range and a variety of geophysical conditions. The comparisons with each spaceborne sensor are combined altogether for investigating their respective solar zenith angle (SZA) dependence, dispersion, and difference of sensitivity. The space- and ground-based data are found to agree within a few percent on average. However, the analysis highlights for both GOME and TOMS several sources of discrepancies: (i) a SZA dependence with TOMS beyond 80° SZA; (ii) a seasonal SZA dependence with GOME beyond 70° SZA; (iii) a difference of sensitivity with GOME at high latitudes; (iv) a difference of sensitivity to low ozone values between satellite and SAOZ sensors around the southern tropics; (v) a north/south difference of TOMS with the ground-based observations; and (vi) internal inconsistencies in GOME total ozone.
Keywords: Antarktis; fjernmåling; geofysikk; meteorologi; ozonlaget; polarområdene; satellitt observasjoner

Snow and blue-ice distribution patterns on the coastal Antarctic Ice Sheet - Liston, Glen E.; Winther, Jan-Gunnar; Bruland, Oddbjørn; Elvehøy, Hallgeir; Sand, Knut; Karlöf, Lars (Antarctic Science, 2000)
Surface patterns of alternating snow and blue-ice bands are found in the Jutulgryta area of Dronning Maud Land, Antarctica. The snow-accumulation regions exist in the lee of blue-ice topographic ridges aligned perpendicular to winter winds. The snow bands are c. 500–2000 m wide and up to several kilometres long. In Jutulgryta, these features cover c. 5000 km2. These alternating snow and blue-ice bands are simulated using a snow transport and redistribution model, SnowTran-3D, that is driven with a winter cycle of observed daily screen-height air temperature, humidity, and wind speed and direction. The snow-transport model is coupled to a wind model that simulates wind flow over the relatively complex topography. Model results indicate that winter winds interact with the ice topographic features to produce alternating surface patterns of snow accumulation and erosion. In addition, model sensitivity simulations suggest that subtle topographic variations, on the order of 5m elevation change over a horizontal distance of 1 to 1.5 km, can lead to snow-accumulation variations that differ by a factor of six. This result is expected to have important consequences regarding the choice of sites for ice-coring efforts in Antarctica and elsewhere.
Edition: 2004/05/06 Publisher: Cambridge University Press
Keywords: Dronning Maud Land; blåis; geofysikk; glasiologi; iskjerner

Molecular Evidence for Extrapair Paternity and Female-Female Pairs in Antarctic Petrels - Lorentsen, Svein-Håkon; Amundsen, Trond; Anthonisen, Kristin; Lifjeld, Jan T. (The Auk, 2000)
Considerable interspecific variation exists in the frequency of extrapair fertilizations (EPFs) in birds. In general, EPFs are more common and occur at higher frequencies in passerines than in nonpasserines (Westneat and Sherman 1997). Lower rates of EPFs are typical for territorial nonpasserines as well as those that breed colonially (Westneat and Sherman 1997). This seems to contradict Birkhead and Møller's (Birkhead and Møller 1992, Møller and Birkhead 1993) hypothesis of intense sperm competition in colonial birds. Their arguments were based on the assumption that the need for nest defense in dense aggregations restricts the ability of males to guard their mates, and that the high number of potential extrapair mates available in colonies selects for a high rate of extrapair copulations (EPCs). In contrast, Westneat and Sherman (1997) found no correlation across species between the frequency of EPFs and nesting dispersion, local breeding density, or breeding synchrony, although EPFs were related to nesting density within species. This suggests that EPC rates are not informative regarding EPF rates in colonial birds (Westneat and Sherman 1997), or that the pattern reported by Møller and Birkhead (1993) does not hold true when more species are included. The conflicting evidence regarding the relationship between extrapair activities and breeding density calls for more empirical studies, especially among colonial nonpasserines. Social monogamy is the predominant mating system in the Procellariiformes (Warham 1990). Several aspects of their breeding biology may, however, provide favorable opportunities for extrapair sexual activity. First, colonial breeding provides ample opportunities for EPCs because many potential partners are available at close range (Birkhead and Møller 1992, Møller and Birkhead 1993). Second, when the sexes are spatially and/or temporally separated, as may be the case in procellariiforms where adults seek food far from the colony, males have few cues to assess whether their mates have been unfaithful. Hence, few reasons exist to expect a facultative decrease in male parental investment if cuckolded, in contrast to the case for many territorial species where a male may have more reliable cues to his mate's unfaithfulness (e.g. female disappearance, high intrusion rate, etc.). Accordingly, colonial breeding may facilitate EPCs for both sexes, and colonial species may be expected to display high rates of EPC. Paternity studies require error-free sex determination of adults. This is straightforward for clearly dimorphic species, or if sex determination can be done from genitalia during the fertile period. But if fieldwork can be performed only during the nestling period, sex determination may be problematic for largely monomorphic species, and indirect methods must be used. In the Antarctic Petrel (Thalassoica antarctica), the two sexes differ slightly in mean body size. Lorentsen and Røv (1994) used this difference to determine the sex of Antarctic Petrels by discriminant function analysis (DFA). The procedure correctly determined the sex of 92% of the birds in a sample from the same year. This does not necessarily imply a similar resolution if the discriminant function is adopted for samples from other years, or if data are collected by other observers. Moreover, although useful for many purposes, 92% resolution in sex determination is insufficient for paternity studies. Therefore, we performed molecular sexing of all breeding adults according to the PCR-based method of Griffiths et al. (1998). The main aim of our study was to analyze whether extrapair paternity occurs in a colonial procellariiform, the Antarctic Petrel. We also tested the robustness of morphological sex determination (from DFA) across seasons relative to that obtained from molecular techniques.
Keywords: Dronning Maud Land; NARE 1993/94; fugler; ornitologi; petreller; zoologi

Flood Basalts of Vestfjella: Jurassic Magmatism Across an Archaean–Proterozoic Lithospheric Boundary in Dronning Maud Land, Antarctica - Luttinen, Arto V.; Furnes, Harald (Journal of Petrology, 2000)
Continental flood basalts (CFBs) of Jurassic age make up the Vestfjella mountains of western Dronning Maud Land and demonstrate an Antarctic extension of the Karoo large igneous province. A detailed geochemical study of the 120-km-long Vestfjella range shows the CFB suite to consist mainly of three intercalated basaltic rock types designated CT1, CT2 and CT3 (chemical types 1, 2 and 3) that exhibit different incompatible trace element ratios. CT1 and CT2 of north Vestfjella record wide ranges of Nd and Sr isotopic compositions with initial εNd and εSr ranging from +7·6 to −16·0 and −16 to +65, respectively. The southern Vestfjella is dominated by CT3 with near-chondritic εNd (+2·0 to −4·1) and εSr (−11 to +19). A volumetrically minor suite of ocean island basalt (OIB-)like CT4 dykes (εNd +3·6, εSr +1) cuts the lava sequence in north Vestfjella. The pronounced isotopic differences suggest different magmatic plumbing systems for the heterogeneous CT1 and CT2 suites and the relatively homogeneous CT3 lavas. This is further supported by the palaeoflow directions, which point to major source regions to the north (CT1 and CT2) and east (CT3) of Vestfjella. These source regions can be associated with two contemporaneous major lithospheric thinning zones that permitted magma emplacement and controlled the melting of upper-mantle sources in the Jurassic Dronning Maud Land. The CT1 and CT2 magmas utilized the northern zone of thinning and were emplaced into the 3 Ga Grunehogna craton, whereas the CT3 magmas were emplaced through thinned Proterozoic Maud Belt lithosphere. Trace element and isotopic studies of the identified magma types reveal a complex history of fractionation and contamination at different lithospheric levels. All extrusive rock types show evidence of crustal contamination but this had rather small impact on their diagnostic trace element ratios. Much stronger overprint, in the CT1 and CT2 suites, resulted from contamination with veined Archaean lithospheric mantle, which produced wide ranges of isotopic and highly incompatible element ratios. CT3, in turn, does not show evidence of interaction with the Proterozoic lithospheric mantle. The high-εNd endmembers of CT1, CT2 and CT3 probably closely resemble uncontaminated mantle-derived magmas and indicate three different mantle sources. The CT2 primary magmas were derived from light rare earth element (LREE)-depleted, slightly large ion lithophile element (LILE)-enriched sources, whereas data on the volumetrically preponderant CT1 and CT3 point to variably LREE-enriched, strongly LILE-enriched sources. The sources of CT1, CT2 and CT3 may record large-scale lateral heterogeneity generated by subduction-contamination of the Gondwanan upper mantle. The OIB-like CT4 dykes probably reflect asthenospheric heterogeneities that were unrelated to the proposed subduction-contamination.
Keywords: Dronning Maud Land; geokjemi; geologi; petrografi; petrologi

Subglacial topography of Jutulstraumen outlet glacier, East Antarctica, mapped from ground-penetrating radar, optical and interferometric synthetic aperture radar satellite data - Melvold, Kjetil; Rolstad, Cecilie Eie (Norsk Geografisk Tidsskrift - Norwegian Journal of Geography, 2000)
Publisher: Routledge
Keywords: Antarktis; geologi; glasiologi; isstrøm; topografi

Etableringen av Norsk polarinstitutt i 1948 : gammel vin i nye skinnsekker? - Nilsen, Frode (Universitetet i Tromsø, 2000)
Publication Title: Institutt for historie. Det samfunnsvitenskapelige fakultet
Keywords: Antarktis; Norsk Polarinstitutt; historie; internasjonal; polarområdene; politikk

Hvite horisonter - Oterhals, Leo (Lagunen, 2000)
Keywords: Antarktis; Sørishavet; ekspedisjoner; historie

Arctic and Antarctic ozone layer observations: chemical and dynamical aspects of variability and long-term changes in the polar stratosphere - Rex, Markus; Dethloff, Klaus; Handorf, Dörthe; Herber, Andreas; Lehmann, Ralph; Neuber, Roland; Notholt, Justus; Rinke, Annette; von der Gathen, Peter; Weisheimer, Antje; Gernandt, Hartwig (Polar Research, 2000)
The altitude dependent variability of ozone in the polar stratosphere is regularly observed by balloon-borne ozonesonde observations at Neumayer Station (70°S) in the Antarctic and at Koldewey Station (79°N) in the Arctic. The reasons for observed seasonal and interannual variability and long-term changes are discussed. Differences between the hemispheres are identified and discussed in light of differing dynamical and chemical conditions. Since the mid- 1980s, rapid chemical ozone loss has been recorded in the lower Antarctic stratosphere during the spring season. Using coordinated ozone soundings in some Arctic winters, similar chemical ozone loss rates have been detected related to periods of low temperatures. The currently observed cooling trend of the stratosphere, potentially caused by the increase of anthropogenic greenhouse gases, may further strengthen chemical ozone removal in the Arctic. However, the role of internal climate oscillations in observed temperature trends is still uncertain. First results of a 10000 year integration of a low order climate model indicate significant internal climate variability. on decadal time scales, that may alter the effect of increasing levels of greenhouse gases in the polar stratosphere.
Keywords: Antarktis; drivhusgasser; klimaendringer; klimagasser; meteorologi; observasjoner; ozonlaget; polarområdene; stratosfæren

Havforskning i tung sjø - Schwach, Vera (Havet, fisken og vitenskapen: fra fiskeriundersøkelser til havforskningsinstitutt 1860-2000, 2000)
Keywords: Sørishavet; forskning; historie; hvalfangst; pelagisk

Pingviner - Skår, Astrid (Landbruksforlaget, 2000)
Keywords: Antarktis; Sørishavet; fugler; zoologi

The impact of greenhouse gases and halogenated species on future solar UV radiation doses - Taalas, Petteri; Kaurola, Jussi; Kylling, Arve; Shindell, Drew; Sausen, Robert; Dameris, Martin; Grewe, Volker; Herman, Jay; Damski, Juhani; Steil, Benedikt (Geophysical Research Letters, 2000)
The future development of stratospheric ozone layer depends on the concentration of chlorine and bromine containing species. The stratosphere is also expected to be affected by future enhanced concentrations of greenhouse gases. These result in a cooling of the winter polar stratosphere and to more stable polar vortices which leads to enhanced chemical depletion and reduced transport of ozone into high latitudes. One of the driving forces behind the interest in stratospheric ozone is the impact of ozone on solar UV-B radiation. In this study UV scenarios have been constructed based on ozone predictions from the chemistry-climate model runs carried out by GISS, UKMO and DLR. Since cloudiness, albedo and terrain height are also important factors, climatological values of these quantities are taken into account in the UV calculations. Relative to 1979–92 conditions, for the 2010–2020 time period the GISS model results indicate a springtime enhancement of erythemal UV doses of up to 90% in the 60–90 °N region and an enhancement of 100% in the 60–90 °S region. The corresponding maximum increases in the annual Northern Hemispheric UV doses are estimated to be 14% in 2010–20, and 2% in 2040–50. In the Southern Hemisphere 40% enhancement is expected during 2010–20 and 27% during 2040–50.
Keywords: Antarktis; UV-stråling; drivhusgasser; klimaendringer; klimatologi; ozonlaget; polarområdene; ultrafiolett stråling

Very little in situ produced radiocarbon retained in accumulating Antarctic ice - van der Kemp, Wybe J.M.; Alderliesten, Cees; van der Borg, Klaas; Holmlund, Per; de Jong, Arie F.M.; Karlöf, Lars; Lamers, R.A.N.; Oerlemans, Johannes; Thomassen, Martijn P.A.; van de Wal, Roderik S.W. (8th International Conference on Accelerator Mass Spectrometry, 2000)
Ice samples from Dronning Maud Land, Antarctica, were analyzed for 14CO2 and 14CO by accelerator mass spectrometry. Only a small amount (∼2%) of in situ produced radiocarbon was detected. The calibrated radiocarbon ages, corrected for in situ produced 14C, are in fair agreement with age estimates obtained from stratigraphical methods added to a gas inclusion model. The ages of the entrapped air range from recent to ca. 1200 AD.
Keywords: Dronning Maud Land; fysikk; karbondatering; karbondioksid; kjemi; massespektrometri

Emerging Law of the Sea Issues in the Antarctic Maritime Area: A Heritage for the New Century? - Vidas, Davor (Ocean Development & International Law, 2000)
This article focuses on three emerging law of the sea issues for states cooperating in management of the Antarctic and its maritime area. The first of these is no newcomer: How to regulate the dramatic increase in illegal, unregulated and unreported fishing of Patagonian toothfish (Dissostichus eleginoides) in the Southern Ocean? The second question, according to the letter of the UN Convention on the Law of the Sea, awaits the countries claiming sovereignty over portions of territory in the Antarctic 10 years from the entry into force of the Convention for each of them. The question here is what to do with the requirement contained in that Convention relating to the submission of information on the outer limit of the continental shelf beyond 200 nautical miles to the Commission on the Continental Shelf? Finally, there is a third tricky question: Who is competent to regulate, and accordingly to ban, mineral activities in the Southern Ocean seabed? Is it the International Seabed Authority as the global body, or the Antarctic Treaty Consultative Parties through their regional cooperation? This question may well never be put on the policy agenda for any global forum; but it may well be posed at any time and by any third party, whether in the UN General Assembly or, more likely, in the Assembly of the International Seabed Authority.
Publisher: Taylor & Francis
Keywords: Antarktis; Antarktistraktaten; Sørishavet; fiskeri; havrett; internasjonal rett; kontinentalsokkel

Johan Koren : feltzoolog og polar-pioner - Wikan, Steinar (Schibsted, 2000)
EN NORSK FELTZOOLOG OG POLAR-PIONER 17 år gammel drar snekkerlærlingen JOHAN KOREN ut fra hjembyen i Fredrikstad i 1897 som deltager i historiens første overvintringekspedisjon i Antarktis, Belgica-ekspedisjonen. Styrmann om bord er en landsmann, den unge Roald Amundsen. I likhet med ham, blir Koren snart kjent og omtalt som en av tidenes dristigste oppdagelsesreisende, med Antarktis og Arktis som virkefelt. Men for Koren blir berømmelsen ikke varig. Bare 39 år gammel dør han i spanskesyken, alene på et hospital i Vladivostok. Og med tiden går det slik at han blir "Gutten Norge glemte" - slik tittelen lød på en senere guttebok, inspirert av hans begivenhetsrike og dramatiske liv. Blant feltzoologer regnes han imidlertid den dag i dag som en pionerskikkelse, og rundt om i verdens zoologiske museer finnes tusenvis av vitnesbyrd om hans innsats for vitenskapen som samler av fugle- og dyrearter. Forfatteren, historikeren og biologen STEINAR WIKAN bygger denne beretningen på Johan Korens delvis bevarte dagbøker, samtlige brev, dokumenter og presseomtaler, erindringsbøker og - ikke minst - samtaler med en gammel mann i det fjerneste Sibir som kjente Koren.
Keywords: Antarktis; Belgica ekspedisjon; biografier; forskning; oppdagelser; overvintring; polarekspedisjoner; zoologi

Postsealing genetic variation and population structure of two species of fur seal (Arctocephalus gazella and A. tropicalis) - Wynen, Louise P.; Goldsworthy, Simon D.; Guinet, Christophe; Bester, Marthán N.; Boyd, Ian L.; Gjertz, Ian; Hofmeyr, Greg J. G.; White, Robert W. G.; Slade, Rob (Molecular Ecology, 2000)
Abstract Commercial sealing in the 18th and 19th centuries had a major impact on the Antarctic and subantarctic fur seal populations (Arctocephalus gazella and A. tropicalis) in the Southern Ocean. The intensive and unrestricted nature of the industry ensured substantial reductions in population sizes and resulted in both species becoming locally extinct at some sites. However, both species are continuing to recover, through the recolonization of islands across their former range and increasing population size. This study investigated the extent and pattern of genetic variation in each species to examine the hypothesis that higher levels of historic sealing in A. gazella have resulted in a greater loss of genetic variability and population structure compared with A. tropicalis. A 316-bp section of the mitochondrial control region was sequenced and revealed nucleotide diversities of 3.2% and 4.8% for A. gazella and A. tropicalis, respectively. There was no geographical distribution of lineages observed within either species, although the respective ΦST values of 0.074 and 0.19 were significantly greater than zero. These data indicate low levels of population structure in A. gazella and relatively high levels in A. tropicalis. Additional samples screened with restriction endonucleases were incorporated, and the distribution of restriction fragment length polymorphism (RFLP) and sequence haplotypes were examined to identify the main source populations of newly recolonized islands. For A. tropicalis, the data suggest that Macquarie Island and Iles Crozet were probably recolonized by females from Marion Island, and to a lesser extent Ile Amsterdam. Although there was less population structure within A. gazella, there were two geographical regions identified: a western region containing the populations of South Georgia and Bouvet?ya, which were the probable sources for populations at Marion, the South Shetland and Heard Islands; and an eastern region containing the panmictic populations of Iles Kerguelen and Macquarie Island. The latter region may be a result of a pronounced founder effect, or represent a remnant population that survived sealing at Iles Kerguelen.
Publisher: John Wiley & Sons, Ltd
Keywords: Bouvetøya; Sørishavet; genetikk; marin biologi; pinnipedier; seler